2,5-dioxido-1,4-benzoquinonediimine (H2L2-), a hydrogen-bonding noninnocent bridging ligand related to aminated topaquinone: different oxidation state distributions in complexes [(bpy)(2)Ru(2)(mu-H2L)](n) (n=0,+,2+,3+,4+) and [(acac)(2)Ru(2)(mu-H2L)] - Kar, S.; Sarkar, B.; Ghumaan, Sandeep; Janardanan, D.; van Slageren, J.; Fiedler, Jan; Puranik, Vedavati G.; Sunoj, R. B.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry - a European Journal, 2005)
{The symmetrically dinuclear title compounds were isolated as diamagnetic [(bpy)(2)Ru(mu-H2L)Ru(bpy)(2)]- (ClO4)(2) (1-(ClO4)(2)) and as paramagnetic [(acac)(2)Ru(mu-H2L)Ru(acac)(2)] (2) complexes (bpy = 2,2'-bipyridine; acac(-) -
Keywords: bridging ligands; Density functional calculations; EPR spectroscopy; N; O ligands; ruthenium

Analysis of the use of genomic DNA as a universal reference in two channel DNA microarrays - Gadgil, Mugdha; Lian, W.; Gadgil, Chetan J.; Kapur, V.; Wu, WS (BMC Genomics, 2005)
Background: DNA microarray is an invaluable tool for gene expression explorations. In the two-dye microarray, fluorescence intensities of two samples, each labeled with a different dye, are compared after hybridization. To compare a large number of samples, the 'reference design' is widely used, in which all RNA samples are hybridized to a common reference. Genomic DNA is an attractive candidate for use as a universal reference, especially for bacterial systems with a low percentage of non-coding sequences. However, genomic DNA, comprising of both the sense and anti-sense strands, is unlike the single stranded cDNA usually used in microarray hybridizations. The presence of the antisense strand in the 'reference' leads to reactions between complementary labeled strands in solution and may cause the assay result to deviate from true values. Results: We have developed a mathematical model to predict the validity of using genomic DNA as a reference in the microarray assay. The model predicts that the assay can accurately estimate relative concentrations for a wide range of initial cDNA concentrations. Experimental results of DNA microarray assay using genomic DNA as a reference correlated well to those obtained by a direct hybridization between two cDNA samples. The model predicts that the initial concentrations of labeled genomic DNA strands and immobilized strands, and the hybridization time do not significantly affect the assay performance. At low values of the rate constant for hybridization between immobilized and mobile strands, the assay performance varies with the hybridization time and initial cDNA concentrations. For the case where a microarray with immobilized single strands is used, results from hybridizations using genomic DNA as a reference will correspond to true ratios under all conditions. Conclusion: Simulation using the mathematical model, and the experimental study presented here show the potential utility of microarray assays using genomic DNA as a reference. We conclude that the use of genomic DNA as reference DNA should greatly facilitate comparative transcriptome analysis.

Copper- and ligand-free sonogashira reaction catalyzed by Pd(0) nanoparticles at ambient conditions under ultrasound irradiation - Gholap, Atul R.; Venkatesan, K.; Pasricha, R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Organic Chemistry, 2005)
The Sonogashira reaction proceeds at ambient temperature (30 degrees C) in acetone or room-temperature ionic liquid, 1,3-di-n-butylimidazolium tetrafluoroborate ([bbim]BF4), as solvent under ultrasound irradiation to give enhanced reaction rates, excellent chemoselectivity, and high yields in the absence of a copper cocatalyst and a phosphine ligand. TEM analysis showed the formation of stable, crystalline, and polydispersed Pd(0) nanoparticles as catalyst for the reaction.

Effect of 2-(2-pyridyl)azole-based ancillary ligands (L1-4) on the electrophilicity of the nitrosyl function in [Ru-II(trpy)(L1-4)(NO)](3+) [trpy=2,2 `: 6 `,2 `'-terpyridine]. synthesis, structures, and spectroscopic, electrochemical, and kinetic aspects - Chanda, N.; Paul, D.; Kar, S.; Mobin, Shaikh M.; Datta, Anindya; Puranik, Vedavati G.; Rao, K. K.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2005)
Ruthenium nitrosyl complexes [Ru(trpy)(L1-4)(NO)](3+) (13-16) [trpy = 2,2':6',2"-terpyridine, L-1 = 2-(2-pyridyl)-benzoxazole, L-2 = 2-(2-pyridyl)benzthiazole, L-3 = 2-(2-pyridyl)benzimidazole, L-4 = 1-methyl-2-(2-pyridyl)-1H-benzimidazole] were obtained in a stepwise manner starting from [Ru-II(trpy)(L1-4) (Cl)]ClO4 (1-4) &RARR; [Ru-II(trpy)(L1-4) (H2O)](ClO4)(2) (5-8) &RARR; [Ru-II(trpy)(L1-4) (NO2)ClO4 (9-12) &RARR; [Ru-II(trpy)(L-1,L-2,L-4) (NO)](ClO4)(3) (13, 14, 16)/[Ru-II(trpy)(L-3) (NO)](Cl)(4))(2)(NO3) (15). Crystal structures of 1, 2, 4, 9, 12, 13, 15, and 16 established the stereoretentive nature of the transformation processes. Though the complexes of L1, L3, and L 4 were isolated in the isomeric form A (π-acceptor trpy and azole ring in the equatorial plane and the pyridine and chloride donors in the axial positions), complexes of L 2 preferentially stabilized in form B (trpy and pyridine in the equatorial plane and the azole ring and chloride donors in the axial positions). The v(NO) stretching frequency varied in the range of 1957-1932 cm(-1), 13 &MGT; 14 &MGT; 15 > 16, primarily depending on the electronic aspects of L as well as the isomeric structural forms. The coordinated nitrosyl function underwent successive reductions of [Ru-II-NO+](3+) &RARR; [Ru-II-NO&BULL;](2+) and [Ru-II-NO&BULL;](2+) - [Ru-II-NO-](+), and the first reduction potential follows the order 14 > 13 &MGT; 15 &AP; 16. The nearly axial EPR spectra having nitrogen hyperfine splittings (A &AP; 26 G) at 77 K of 13(-)-16(-) with (g) &AP; 2.0 established that the reduction process is largely centered around the nitrosyl function. Despite an appreciably high v(NO), the complexes were found to be unusually stable even in the aqueous medium. They transformed slowly and only partially into the corresponding nitro derivatives in H2O (k &AP; 10(-4) s(-1) and K = 0.4-3.8). The chloro (1-4), aqua (5-8), and nitro (9-12) derivatives displayed reasonably strong emissions near 700 nm at 77 K (φ = 10(-1)-10(-2)). The aqua derivative 7 was found to interact with the calf thymus and the circular form of p-Bluescript SK DNA.

Formation of nanosized zirconia-supported 12-tungstophosphoric acid in mesoporous silica SBA-15: a stable and versatile solid acid catalyst for benzylation of phenol - Sawant, D. P.; Vinu, A.; Jacob, Nalini E.; Lefebvre, F.; Halligudi, Shivappa B. (Journal of Catalysis, 2005)
A nanosized zirconia-supported 12-tungstophosphoric acid (TPA) in SBA-15 composite was prepared by wet impregnation of TPA/ZrO2 nanoparticles inside the mesoporous channels of SBA-15. The resulting composite material was calcined at 1123 K and characterized by elemental analysis, powder X-ray diffraction, nitrogen adsorption isotherms, transmission electron microscopy (TEM), scanning electron microscopy (SEM), solid-state P-31 CP-MAS NMR, Si-29 MAS NMR, UV-vis diffuse reflectance spectra, FTIR, TPD of ammonia, FTIR pyridine adsorption, and thermogravimetric analysis (TG-DTG). The synthesized TPA/ZrO2/SBA-15 showed a well-ordered hexagonal inesoporous structure and mesoporous support SBA-15 stabilized ZrO2-t (tetragonal) phase with crystal size in the range of 3-4 nm. SBA-15 was a better support than MCM-41 and MCM-48 because it retained its mesostructure even after high TPA loading and high calcination temperatures. Mesoporous silica support plays an important role in stabilizing the catalytically active tetragonal phase of zirconia, which gave the most active catalysts. The catalysts were examined for their catalytic activities in the liquid phase benzylation of phenol with benzyl alcohol and the catalyst 15 wt% TPA/ 22.4 wt% ZrO2/SBA-15 calcined at 1123 K was found to have high acidity and to be 10 times more active than neat TPA/ZrO2 Under the reaction conditions studied in benzylation of phenol. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: nanosized; phenol benzylation reaction; terragonal phase; TPA/ZrO2

Growth of PbS nanopyramidal particulate films for potential applications in quantum-dot photovoltaics and nanoantennas - Hawaldar, Ranjit R.; Mulik, Uttam P.; Patil, K.; Pasricha, R.; Sathaye, S.; Lewis, A.; Amalnerkar, Dinesh P. (Materials Research Bulletin, 2005)
We report a simple interfacial process called the liquid-liquid interface reaction technique (LLIRT) that leads to the formation of nanosized PbS particulate films with hitherto unreported pyramidal morphology. The resultant PbS films were characterized by transmission electron microscopy (TEM) with selected area electron diffraction (SAED), X-ray diffractometery (XRD), atomic force microscopy (AFM), near field scanning optical microscopy (NSOM) and UV-vis spectroscopy. The pyramidal morphology is speculated to originate from the preferred orientation of the 2 2 0 plane of cubic PbS. Our nanopyramidal PbS particulate films display remarkably sharp excitonic peak centered around 656 nm that accounts for a band gap of 1.8 eV suggesting, in turn, their potential application in QD photovoltaics. Interestingly, the feasibility of such nanopyramids to potentially act as nanoantennas (as revealed by the NSOM) is also suggested. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Atomic force microscopy; Chemical synthesis; Electron microscopy; Nanostructures; Optical properties

Highly active new alpha-diimine nickel catalyst for the polymerization of alpha-olefins - Liu, Hua-Rong; Gomes, P. T.; Costa, S. I.; Duarte, M. T.; Branquinho, R.; Fernandes, A. C.; Chien, J. C. W.; Singh, R. P.; Marques, Maria M. (Journal of Organometallic Chemistry, 2005)
A new silylated alpha-diimine ligand, bis[N,N `-(4-tert-butyl-diphenylsilyl-2,6-diisopropylphenyl)imino]acenaphthene 3, and its corresponding Ni(II) complex, {bis[N,N `-(4-tert-butyl-diphenylsilyl-2,6-diisopropylphenyl)imino]acenaphthene} dibromonickel 4, have been synthesized and characterized. The crystal structures of 3 and 4 were determined by X-ray crystallography. In the solid state, complex 4 is a dimer with two bridging Br ligands linking the two nickel centers, which have square pyramidal geometries. Complex 4, activated either by diethylaluminum chloride (DEAC) or methylaluminoxane (MAO) produces very active catalyst systems for the polymerization of ethylene and moderately active for the polymerization of propylene. The activity values are in the order of magnitude of 10(7) g PE (mol Ni [E] h)(-1) for the polymerization of ethylene and of 10(5) g PP (mol Ni [P] h)(-1) for the polymerization of propylene. NMR analysis shows that branched polyethylenes (PE) are obtained at room or higher temperatures and almost linear PE is obtained at 0 degrees C with 4/DEAC. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: alpha-diimine nickel complex; Ethylene polymerization; late transition-metal; propylene polymerization

Hydrophobically modified poly(acrylic acid) using 3-pentadecylcyclohexylamine: synthesis and rheology - Shedge, A. S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique; Pcrrin, P.; Chassenieux, Christophe; Badiger, Manohar V. (Macromolecular Chemistry and Physics, 2005)
Hydrophobically modified poly(acrylic acid) was synthesized using 3-pentadecylcyclohexylamine (3-PDCA), which was in turn synthesized from 3-pentadecylphenol, one of the components of cashew-nut shell liquid (CNSL), a renewable resource material. H-1 NMR spectra confirmed the incorporation of 3-PDCA onto PAA and a series of HMPs with three different molar concentrations, viz. congruent to 3, 5 and 7 mol-% of 3-PDCA, were synthesized. An increase in viscosity with increasing hydrophobic content was observed by rheological measurements. The critical association concentrations were determined using an Ubbelohde viscometer and a controlled stress rheometer. The stability of HMPs towards temperature and shear was studied. Rheological measurements showed that there was a steady increase in viscosity with increase in hydrophobe content due to the formation of reversible networks. These polymers exhibited gel-like behavior at low concentrations (greater than or equal to2 wt.-%) with an apparent yield stress (ca. 10 Pa) and showed shear thinning properties (non-Newtonian). However, below a critical concentration, c [eta], they showed Newtonian behavior.
Keywords: 3-pentadecylcyclohexylamine (3-PDCA); hydrophobically modified polymers (HMPs); poly(acrylic acid); reversible associations; Rheology

In situ polymerization of ethylene with bis(imino)pyridine iron(II) catalysts supported on clay: the synthesis and characterization of polyethylene-clay nanocomposites - Ray, S; Galgali, G; Lele, Arundhati C.; Sivaram, S (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
Polyethylene-clay nanocomposites were synthesized by in situ polymerization with 2,6-bis[1-(2,6-diisopropylphenylimino)ethyl] pyridine iron(II) dichloride supported on a modified montmorillonite clay pretreated with methylaluminoxane (MAO). The catalysts and the obtained nanocomposites were examined with wide-angle X-ray scattering. The exfoliation of the clay was further established by transmission electron microscopy. Upon the treatment of the clay with MAO, there was an increase in the d-spacing of the clay galleries. No further increase in the d-spacing of the galleries was observed with the iron catalyst supported on the MAO-treated clay. The catalyst activity for ethylene polymerization was independent of the Al/Fe ratio. The exfoliation of the clay inside the polymer matrix depended on various parameters, such as the clay content, catalyst content, and Al/Fe ratio. The crystallinity percentage and crystallite size of the nanocomposites were affected by the degree of exfoliation of the clay. Moreover, when ethylene was polymerized with a mixture of the homogeneous iron(II) catalyst and clay, the degree of exfoliation was significantly lower than when the polymerization was performed with a preformed clay-supported catalyst. This observation suggested that in the supported catalyst, at least some of the active centers resided within the galleries of the clay. (C) 2004 Wiley Periodicals, Inc.
Keywords: clay; In situ polymerization; Nanocomposites; polyethylene (PE); TEM; WAXS

Isothermal kinetic study of nitric oxide adsorption and decomposition on Pd(111) surfaces: molecular beam experiments - Thirunavukkarasu, K; Thirumoorthy, K; Libuda, X; Gopinath, Chinnakonda S. (Journal of Physical Chemistry B, 2005)
The kinetics of NO adsorption and dissociation on Pd(111) surfaces and the NO sticking coefficient (S-NO) were probed by isothermal kinetic measurements between 300 and 525 K using a molecular beam instrument. NO dissociation and N-2 productions were observed in the transient state from 425 K and above on Pd(l 11) surfaces with selective nitrogen production. Maximum nitrogen production was observed between 475 and 500 K. It was found that, at low temperatures, between 300 and 350 K, molecular adsorption occurs with a constant initial SNO of 0.5 until the Pd(I 11) surface is covered to about 70-80% by NO. Then SNO rapidly decreases with further increasing NO coverage, indicating typical precursor kinetics. The dynamic adsorption-desorption equilibrium on Pd(I 11) was probed in modulated beam experiments below 500 K. CO titration experiments after NO dosing indicate the diffusion of oxygen into the subsurface regions and beginning surface oxidation at >= 475 K. Finally, we discuss the results with respect to the rate-limiting character of the different elementary steps of the reaction system.

Matched asymptotic solution for flow in a semi-hyperbolic die - Subramanian, G; Ranade, V; Nagarkar, S; Lele, Arundhati C. (Chemical Engineering Science, 2005)
A semi-hyperbolic converging geometry finds application as an inexpensive elongation rheometer under certain flow conditions. We provide a matched asymptotic solution for the flow of a Newtonian fluid under no-slip boundary conditions. The predicted velocity and pressure profiles agree nearly quantitatively with CFD simulated values. Our theoretical approach has certain advantages over the known similarity solution proposed by James (1991. A.I.Ch.E. Journal 37, 59-64). (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: elongation viscosity; matched asymptotic solution; semi-hyperbolic

MCM-41-supported platinum carbonyl cluster-derived asymmetric hydrogenation catalyst - Basu, Susmit; Paul, Himadri; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2005)
Anionic platinum carbonyl cluster has been ion paired with cinchonidium groups that are chemically bound to the surface of MCM-41 and fumed silica. In the hydrogenation of methyl pyruvate or acetophenone the fumed silica-based catalyst gives zero enantioselectivity, but under optimum conditions enantiomeric excesses of >90 and similar to40%, respectively, are obtained with the MCM-41-based catalyst. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: asymmetric catalysis; functionalized inorganic oxides; hydrogenation catalysts; platinum carbonyl cluster

Mitochondrial sequence reveals high levels of gene flow between breeds of domestic sheep from Asia and Europe - Meadows, J. R. S.; Li, K.; Kantanen, J.; Tapio, M.; Sipos, W.; Pardeshi, V.; Gupta, V.; Calvo, J. H.; Whan, V.; Norris, B.; Kijas, J. W. (Journal of Heredity, 2005)
Sequence variation present within the mitochondrial genome was used to investigate genetic diversity within sheep breeds from Asia and Europe. Comparison of 2027 bp of sequence from 121 animals revealed 44 phylogenetically informative nucleotide positions and a single insertion/deletion. A total of 57 haplotypes were observed which formed two distinct clades. Type A haplotypes were found in breeds from Asia (India, Indonesia, Mongolia, and Tibet), while type B haplotypes were observed at the highest frequency in breeds sourced from Europe (nine breeds from Austria, angstrom land, Finland, Spain, and northwestern Russia). The distribution of haplotypes indicates sheep appear to have the weakest population structure and the highest rate of intercontinental dispersal of any domestic animal reported to date. Only 2.7% of the sequence variation observed was partitioned between continents, which is lower than both goat (approximately 10%) and cattle (approximately 50%). Diagnostic restriction fragment length polymorphism polymerase chain reaction (RFLP-PCR) tests which distinguish type A and B haplotypes were used to test an additional 223 animals from 17 breeds of European and Asian origin. A mixture of the two lineages was found in every breed except Suffolk and the Indian Garole, indicating introgression has played a major part during breed development and subsequent selection.

Modular synthesis of cyclic peptidomimetics inspired by gamma-turns - Ramanathan, S. K.; Keeler, J.; Lee, H. L.; Reddy, D. Srinavasa; Lushington, G.; Aube, J. (Organic Letters, 2005)
A series of peptidomimetics based on a gamma-turn motif were synthesized using a modular approach, in which N-protected piperidones were reacted with a selection of 2-hydroxyalkyl azides derived from common L-amino acids. Hydrolysis of the initially formed iminium ethers afforded the targeted series of substituted 1,4-diazepin-5-ones.

Molecular beam study of the NO plus CO reaction on Pd(111) surfaces - Thirunavukkarasu, K; Thirumoorthy, K; Libuda, J; Gopinath, Chinnakonda S. (Journal of Physical Chemistry B, 2005)
Nitric oxide (NO) reduction with carbon monoxide (CO) on the Pd(111) surface was studied under isothermal conditions by molecular beam techniques as a function of temperature, NO:CO beam composition, and beam flux. Systematic experiments were performed under transient and steady state conditions. Displacement of adsorbed CO by NO in the transient state of the reaction was observed at temperatures between 375 and 475 K for all the NO: CO compositions studied. NO accumulation occurs on Pd(l 11) surface under steady state conditions, below 475 K, due to stronger chemisorption of NO. The steady state reaction rates attain a maximum at about 475 K, nearly independent of beam composition. N-2 was found to be the major product of the reduction, along with a minor production of N2O. The production of N2 and N2O indicates molecular and dissociative adsorption of NO on Pd(l 11) at temperatures up to 525 K. Postreaction TPD measurements were performed in order to determine the nitrogen coverage under steady-state conditions. Finally, the results are discussed with respect to the rate-controlling character of the different elementary steps of the reaction system.

Molecular mapping of stem and leaf rust resistance in wheat - Khan, R. R.; Bariana, Harbans S.; Dholakia, Bhushan B.; Naik, S. V.; Lagu, Meena D.; Rathjen, A. J.; Bhavani, Sridhar; Gupta, V. S. (Theoretical and Applied Genetics, 2005)
Stem rust caused by Puccinia graminis f. sp. tritici Eriks and Henn and leaf rust caused by Puccinia triticina Rob. ex Desm. are major constraints to wheat production worldwide. In the present study, F-4-derived SSD population, developed from a cross between Australian cultivars `Schomburgk' and `Yarralinka', was used to identify molecular markers linked to rust resistance genes Lr3a and Sr22. A total of 1,330 RAPD and 100 ISSR primers and 33 SSR primer pairs selected on the basis of chromosomal locations of these genes were used. The ISSR marker UBC 840(540) was found to be linked with Lr3a in repulsion at a distance of 6.0 cM. Markers cfa2019 and cfa2123 flanked Sr22 at a distance of 5.9 cM (distal) and 6.0 cM (proximal), respectively. The use of these markers in combination would predict the presence or absence of Sr22 in breeding populations. A previously identified PCR-based diagnostic marker STS638 linked to Lr20 was validated in this population. This marker showed a recombination value of 7.1 cM with Lr20.

Novel one-pot synthesis of 2-Aryl-4(3H)-quinazolinones using room temperature ionic liquid as reaction medium as well as promoter - Potewar, T. M.; Nadaf, R. N.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Synthetic Communications, 2005)
An efficient one-pot synthesis of 2-aryl-4(3H)-quinazolinones from 2-amino benzamides and substituted benzoyl chlorides in a room temperature ionic liquid is described. Compared with the classical reaction conditions, this new synthetic method has the advantages of recyclability of ionic liquid, very good to excellent yields (78-92%), the absence of hazardous and expensive catalysts, and easy workup procedures giving rise to a process with minimum waste.
Keywords: 2-amino benzamide; 2-aryl-4(3H)-quinazolinones; benzoyl chlorides; Ionic liquid

Optimization and scale up of production of alkaline protease from Conidiobolus coronatus - Laxman, Ryali Seeta; Sonawane, A. P.; More, Shivaji V.; Rao, B. S.; Rele, M. V.; Jogdand, Vitthal V.; Deshpande, V. V.; Rao, M. B. (Process Biochemistry, 2005)
Alkaline protease secreted by Conidiobolus coronatus has been evaluated extensively in tanneries and finds application in pre-tanning operations in leather manufacture. It is important to produce the enzyme in inexpensive and optimized media on large scale for the process to be commercially viable. The present paper describes optimization of fermentation conditions in shake flasks and scale up of production to 100 L in fermentors. The production is complete in 2-3 days comparable to bacterial fermentations. The organism utilized several carbon sources such as starch, sucrose, lactose, glucose and fructose for production. Soyabean meal at an optimum concentration of 2-3% was found to be best inducer. Diammonium hydrogen phosphate, casamino acids and Hi-media peptone gave activities comparable to yeast extract. Preservation and stabilization studies showed that glycerol conferred considerable stabilization at room temperature while ammonium sulphate precipitated enzyme at 0.9 saturation was best with stability up to 2 years even at room temperature. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Conidiobolus; Fermentation; Optimization; scale up

Photodegradation of ethylene/propylene/polar monomers co- and terpolymers. I - Prepared by group 4 catalyst systems - Fernandes, Susete N.; Correia, Sandra; Prasad, A. V.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Marques, Maria M.; Singh, R. P. (Journal of Macromolecular Science-Pure and Applied Chemistry, 2005)
The photooxidative degradation behavior of polyethylene, its copolymers (propylene/polar monomers) and terpolymers, synthesized by a group 4 catalyst system, has been studied by Fourier transform infrared spectroscopy and confirmed with scanning elecrton microscopy for morphological changes. The kinetics of photodegradation has also been studied. Surface damage caused by polychromatic (>= 290 nm) at 55 degrees C in air is presented in different micrographs. The rate of photodegradation is very fast in terpolymers containing polar monomers as compared with copolymers and polyethylene. Morphological study of these photodegraded samples showed a very good relation with photodegradation results.
Keywords: functional polyolefins; Photodegradation; UV irradiation

Quantitative method for normalization of transfection efficiency using enhanced green fluorescent protein - Dandekar, D. H.; Kumar, M.; Ladha, J. S.; Ganesh, Krishna N.; Mitra, Debashis (Analytical Biochemistry, 2005)

Room temperature ionic liquid promoted improved and rapid synthesis of 2,4,5-triaryl imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone - Siddiqui, S. A.; Narkhede, U. C.; Palimkar, S. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Tetrahedron, 2005)
An improved and rapid one-pot synthesis of 2,4,5-triaryl imidazoles in a room temperature ionic liquid is described, which does not need any added catalyst. Different ionic liquids based on 1-n-butyl and 1,3-di-n-butyl imidazolium salts were screened and their efficacy in terms of acidity and polarity have been correlated with yields and reaction period. The one-pot methodology resulting in excellent isolated yields in short reaction times is characterized by simple work up procedures and efficient recovery and recycling of the ionic liquid, which acts as a promoter. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 2-Diketones; 4; 5-triaryl imidazoles; alpha-hydroxyketone; ammonium acetate; benzaldehydes; ionic liquid (IL)

Simple procedure for the synthesis of gamma-hydroxy-alpha,beta-(E)-alkenoic esters: formal synthesis of (+)-macrosphelides A and B - Rao, K. Srinivasa; Mukkanti, K.; Reddy, D. Srinivasa; Pal, Manojit; Lqbal, Javed (Tetrahedron Letters, 2005)
A highly trans-selective conjugate reduction of 7-hydroxy-alpha,beta-alkynoic esters to produce gamma-hydroxy-alpha,beta-(E)-alkenoic esters using LiAlH4 is reported. The application of this methodology is demonstrated by a formal synthesis of the potent cell-cell adhesion inhibitors (+)-macrosphelides A and B. (c) 2005 Elsevier Ltd. All rights reserved.

Stereoselective synthesis of (2S,7S)-7-(4-phenoxymethyl)2-(1-N-hydroxyureidyl-3-butyn-4-yl)oxepane: a potential anti-asthmatic drug candidate - Gurjar, M. K.; Rao, B. V.; Krishna, L. M.; Chorghade, Mukund S.; Ley, S. V. (Tetrahedron-Asymmetry, 2005)
We have achieved a short, efficient stereoselective synthesis of 7-membered oxepane derivatives with potential against asthma. Highlights of our synthetic strategy are regioselective oxidation of a hydroxyl group and efficient ring closure of an open chain aldehyde to a 2-benzenesulfonyl oxepane derivative with PhSO2H. Surprisingly the cis-isomer showed better activity than the traps-isomer. (C) 2005 Elsevier Ltd. All rights reserved.

Stochastic model for first order reaction networks - Gadgil, Chetan J.; Lee, Chang Hyeong; Othmer, Hans G. (Bulletin of Mathematical Biology, 2005)
A stochastic model for a general system of first-order reactions in which each reaction may be either a conversion reaction or a catalytic reaction is derived. The governing master equation is formulated in a manner that explicitly separates the effects of network topology from other aspects, and the evolution equations for the first two moments are derived. We find the surprising, and apparently unknown, result that the time evolution of the second moments can be represented explicitly in terms of the eigenvalues and projections of the matrix that governs the evolution of the means. The model is used to analyze the effects of network topology and the reaction type on the moments of the probability distribution. In particular, it is shown that for an open system of first-order conversion reactions, the distribution of all the system components is a Poisson distribution at steady state. Two different measures of the noise have been used previously, and it is shown that different qualitative and quantitative conclusions can result, depending on which measure is used. The effect of catalytic reactions on the variance of the system components is also analyzed, and the master equation for a coupled system of first-order reactions and diffusion is derived.

Synthesis, characterization, and performance evaluation of novel stabilized TDI-based polyurethane coatings under accelerated weathering - Kumar, A. P.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Raut, K. G.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2005)
Some toluene dilsocyanate (TDI)-based polyurethane resins (PURs) for coating applications were synthesized with castor oil and their performance was estimated under accelerated UV weathering with and without a novel UV absorber. Changes in physical properties, chemical structure, and color of the samples were monitored by mechanical property testing, FTIR spectroscopy, and colorimetry, respectively. A stable polyurethane coating was achieved at 0.5% concentration of additive in the host matrix. Mechanical properties were also retained as in the pristine PUR after mixing. Commercial Tinuvin P and benzotriazole-based novel UV absorbers were found to improve the photoresistance of the PUR coating, and the highest efficiency of the novel UV absorber against weathering was estimated at 0.5 wt% concentration.(c) 2005 Society of Plastics Engineers.

Synthesis, characterization, and performance evaluation of polymeric HALS in ethylene-propylene-diene terpolymer (EPDM) - Lonkar, Sunil P.; Rana, S.; Singh, R. P.; Lacoste, Jacques; Gardette, Jean Luc; Jestin, F.; Brocord, E. (Journal of Macromolecular Science, Part A: Pure and Applied Chemistry, 2005)
A polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the maleic anhydride graft ethylene-propylene-diene terpolymer (EPDM) was synthesized. This involves photoinduced grafting of maleic anhydride groups on unsaturated sites of EPDM, followed by incorporation of amino terminated HALS. The grafting and functionalization reactions were characterized by FTIR and C-13 NMR spectroscopy. The surface changes upon degradation are studied by SEM. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The HALS grafted EPDM showed significantly improved photostabilizing efficiency.
Keywords: EPDM; light induced grafting; Photostabilization; polymeric HALS

Synthesis of chromium substituted nano particles of cobalt zinc ferrites by coprecipitation - Sharma, R. K.; Suwalka, O.; Lakshmi, N.; Venugopalan, K.; Banerjee, Abhik; Joy, Pattayil Alias (Materials Letters, 2005)
Nano particles of chromium substituted cobalt zinc ferrite have been synthesized by a chemical co-precipitation method. X-ray diffraction studies of the nano particles of CrxCo0.5-xZn0.5Fe2O4 (x = 0.1 to 0.5) heat-treated at 300 degrees C show that the particle sizes are in the range of 2 to 7 nm. Room temperature Fe-57 Mossbauer spectra of all the samples show only two doublets, confirming the presence of superparamagnetic relaxation in the nano particles. An exponential decrease in the superparamagnetic blocking temperature, with increasing chromium concentration, is observed for these samples. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Co0.5Zn0.5Fe2O4; Mossbauer spectroscopy; nano materials

Synthesis of linear alkyl benzenes over zirconia-supported 12-molybdophosphoric acid catalysts - Devassy, Biju M.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction, and P-31 MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. 3 1 P MAS NMR spectra show that the nature of phosphorous species depend on MPA loading and calcination temperature, and it show the existence of three types of phosphorous species, one is the Keggin unit and the other is the decomposition product of MPA and third one an unidentified species. FTIR pyridine adsorption on 15% MPA catalyst calcined at 700 degrees C showed the presence both Bronsted and Lewis acidity. Under the reaction conditions of 83 C, benzene/1-olefin molar ratio of 10 (time, 1 h), the most active catalyst, 15% MPA calcined at 700 C gave more than 90% olefin conversion with selectivity to 2-phenyl octane, 55% and 2-phenyl dodecane, 45%. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; benzene alkylation; linear alkyl benzene; Zirconia

Synthesis, structure, electrochemistry and ROMP-activity of new ferrocenyl analog of Grubbs' metathesis catalyst - Maishal, T. K.; Mondal, Biplab; Puranik, Vedavati G.; Wadgaonkar, P. P.; Lahiri, Goutam Kumar; Sarkar, A. (Journal of Organometallic Chemistry, 2005)
Treatment of [(PCy3)(2)Cl2Ru=CH-Ph] (1) with vinylferrocene 1 and 1-ferrocenyl-1,3-butadiene 2 yielded solid products. These new complexes were characterized by H-1 NMR, P-31 NMR and C-13 NMR spectroscopy. X-ray crystal structures of both the complexes have been solved. The crystal structure of II confirmed the assigned structure and revealed existence of two sets of intermolecular C-H-Cl(M) type interactions, viz. (Ru)Cl-H-C(ferrocene) and (Ru)Cl-H-CHCl2. The air-stable, dark solid II is all efficient catalyst for ring-opening metathesis polymerization (ROMP) of cyclopentene, norbornene and cycloocta-1,5-diene. Electrochemical behavior of the complexes clearly reflects electronic communication between two metal centers. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; ferrocene; Metathesis; non-covalent interactions; ring-opening metathesis polymerization; ruthenium carbene

Tetrazine derived mononuclear Ru-II(acac)(2)(L)(1), [Ru-II(bpy)(2)(L)](ClO4)(2)(2) and [Ru-II(bpy)(L)(2)](ClO4)(2)(3) (L=3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate, bpy=2,2 '-bipyridine): syntheses, structures, spectra - Nayak, A.; Patra, S.; Sarkar, B.; Ghumaan, Sandeep; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Polyhedron, 2005)
Mononuclear ruthenium complexes of tetrazine derived L, Ru-II(acac)(2)(L) (1), [Ru-II(bpy)(2)(L)](ClO4)(2) (2) and [Ru-II(bpy)(L)(2)](ClO4)2 (3) (L = 3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate and bpy = 2,2'-bipyridine) were prepared. The free L exists as a dimeric entity in the solid state via hydrogen bonding interactions involving L and water molecules present in the crystal lattice. 1 exhibits unusually strong bonds from Ru-II to coordinating pyrazolyl-N (2.040(2) Angstrom) and especially to tetrazine-N (1.913(2) Angstrom). The Ru-III/Ru-II couples of 1-3 appeared at 0.28, 1.34 and 1.50 V versus SCE, respectively. The tetrazine and bpy-based reductions were observed at -1.33 (1); -0.55 and -1.55/-1.75/-1.98 (2); -0.47/-0.78 and -1.80/-2.02 V (3), respectively. 1, 2 and 3 displayed two MLCT bands each, corresponding to dpi(Ru-II) --> pi* (L, tetrazine) and dpi(Ru-II) --> pi* (acac or bpy or L) transitions. 1(+) and 2(+) showed rhombic EPR spectra at 110 and 4 K, respectively and 1(-), 2(-) and 3(-) exhibited multiple line EPR spectra at 300 K. 1-3 exhibited moderately strong emission spectra in EtOH-MeOH glass at 77 K. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; redox; ruthenium-tetrazine; spectra; structure; synthesis

Thermal, magnetic and spectral studies of metal-quinone complexes Part III. radical coordination and hydrogen bonding mediated exchange interaction in copper-hydroxyquinone complex - Salunke-Gawali, S.; Rane, S. Y.; Boukheddaden, K.; Codjovi, E.; Linares, J.; Varret, F.; Bakare, P. P. (Journal of Thermal Analysis and Calorimetry, 2005)
The reaction of CuCl with 2HNQ, ( viz. 2- hydroxy- 1,4- naphthoquinone), in methanol results in [Cu-2( II, II)(4HNSQ)(2)(ONQ)(2)(H2O)(4)], Cu- 3 complex; [ where ONQ is the deprotonated oxidized form of ligand ( viz. 2- oxido- 1,4- naphthoquinone) and 4HNSQ one electron reduced tautomeric form of the ligand (i.e. 4- hydroxy - 1,2- naphthosemiquinone)]. The mixed valent redox ligation is confirmed in [ 9] by us. In present report complex Cu- 3 investigated by variable temperature magnetic susceptibility measurements ( SQUID), X and Q- band EPR, DSC and CV techniques. A break is observed in the chi(m)(-1) vs. T plot similar to 200 K in Cu- 3 which is attributed to a phase transition. In Cu- 3 a quintet state ( S= 2) is populated above 200 K by the molecular association of two exo Cu( II)( 4HNSQ) units via hydrogen bonding between Cu(ONQ) unit of endo ligands in dimer. Magnetic susceptibility data is treated with tetramer model with S= 1/2,1/2,1/2,1/2. The interdimer triplet- triplet interaction ( J) in two [ Cu( 4HNSQ)] units and intradimer ( zJ(1)) interaction between [ Cu( II)( 4HNSQ)] are best fitted with J= -50 cm(-1) and zJ(1)= 28 cm(-1), respectively, using g= 2.2. `Quintet- triplet' phase transition occurs with an enthalpy change of 31.83 kJ mol(-1) estimated from DSC. Cu( II)double left right arrow Cu( I) and NSQ double left right arrow CAT redox couples at E-1/2= 0.68 V and E-1/2 = -1.12 V, respectively are result of exo ligands and Cu( II) ions interaction, while shifts of ligand based peaks viz. NQ -> NSQ and NSQ double left right arrow CAT at - 0.44 and - 0.67 V towards positive potential on complexation are due to electron transfer interactions between endo ligand and Cu( II) ion.
Keywords: antiferromagnetic coupling; copper complexes; Lawsone; model complexes; quinones; triplet state

Trans-5-Aminopipecolyl-aegPNA chimera: design, synthesis, and study of binding preferences with DNA/RNA in duplex/triplex mode - Lonkar, P. S.; Kumar, V. A. (Journal of Organic Chemistry, 2005)
[GRAPHICS] The design and synthesis of novel chiral PNA monomer based on traps-5-aminopipecolic acid is reported. The trans diequatorial disposition of the 1,4 ring substituents in six-membered 5-aminopipecolic acid derivative could be favorable over trans 1,3 axial-equatorial disposition in 4-amino-pipecolic acid of PNA. Studies on the synthesis of traps-4/ 5-aminopipecolyl PNA-eagPNA chimeras and their binding preferences to DNA/RNA in duplex/triplex modes are described.

Transparent chiral polymers for optical applications - Pujari, N. S.; Kulkarni, M. R.; Large, M. C. J.; Bassett, I. M.; Ponrathnam, S. (Journal of Applied Polymer Science, 2005)
Optically active chiral polymers and copolymers of cholesteryl methacrylate have been studied for use in optical applications including plastic optical fibers. Homopolymers of chiral cholesteryl methacrylate with differing molecular weights and copolymers with methyl methacrylate were synthesized by free-radical copolymerization in tetrahydrofuran using azobisisobutyronitrile at 67 degrees C for 26 h. All polymers were characterized for molecular weight, glass-transition temperature, optical rotation, transparency, and refractive index and solution blended to test for compatibility with poly(methyl methacrylate). Such chiral materials are of particular interest because they offer useful polarization properties without requiring bulk orientation of the molecules. This makes it possible to produce low cost optical elements such as circularly birefringent or circularly polarizing optical elements with potential applications in polarization manipulations and sensing. (c) 2005 Wiley Periodicals, Inc.
Keywords: chiral; cholesteryl methacrylate; optically active; plastic optical fiber; poly(cholesteryl methacrylate); poly(cholesteryl methacrylate-co-methyl methacrylate)

Unusual monodentate binding mode of 2,2 `-dipyridylamine (L) in isomeric trans(acac)(2)Ru-II(L)2, trans-[(acac)(2)Ru-III(L)(2)]ClO4, and cis-(acac)(2)Ru-II(L)(2) (acac = acetylacetonate). Synthesis, structures, and spectroscopic, electrochemical, and magn - Kar, S.; Chanda, N.; Mobin, Shaikh M.; Urbanos, F. A.; Niemeyer, M.; Puranik, Vedavati G.; Jimenez-Aparicio, Reyes; Lahiri, Goutam Kumar (Inorganic Chemistry, 2005)
{The reaction of cis-Ru(acac)(2)(CH3CN)(2) (acac = acetylacetonate) with 2,2'-dipyridylamine (L) in ethanolic medium resulted in facile one-pot synthesis of stable [(acac)(2)Ru-III(L)]ClO4 ([1]ClO4), trans-[(acac)(2)Ru-II(L)2] (2), trans[(acac)(2)Ru-III(L)(2)[ClO4 ([2]ClO4), and cis-[(acac)(2)Ru-II(L)(2)] (3). The bivalent congener 1 was generated via electrochemical reduction Of [1]ClO4. Although in [1](+) the dipyridylamine ligand (L) is bonded to the metal ion in usual bidentate fashion, in 2/[2](+) and 3, the unusual monodentate binding mode of L has been preferentially stabilized. Moreover, in 2/[2](+) and 3, two such monodentate L's have been oriented in the trans- and cis-configurations, respectively. The binding mode of L and the isomeric geometries of the complexes were established by their single-crystal X-ray structures. The redox stability of the Ru(II) state follows the order 1 < 2 much less than 3. In contrast to the magnetic moment obtained for [1]ClO4

Zirconia-supported 12-tungstophosphoric acid as a solid catalyst for the synthesis of linear alkyl benzenes - Devassy, Biju M.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated with zirconia-supported 12-tungstophosphoric acid (TPA) as catalysts. We prepared the catalysts, with different TPA loading (5-20 wt% calcined at 750 degrees C) and calcination temperatures (15 wt% calcined from 650 to 850 degrees C), by suspending hydrous zirconia in a methanol solution of TPA, followed by drying and calcination. These catalysts were characterized by X-ray diffraction, DTG-DTA, FTIR pyridine adsorption, NH3-TPD, and P-31, MAS NMR spectroscopy measurements. The catalyst with optimum TPA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents and characterized by P-31 MAS NMR spectroscopy. The XRD results indicate that TPA stabilizes the tetragonal phase of zirconia. The catalysts show both Bronsted and Lewis acidity, and 15% TPA on zirconia calcined at 750 degrees C shows the highest acidity. P-31 MAS NMR spectra show two types of phosphorous species: one is the Keggin unit and the other is the decomposition product of TPA. The relative amount of each depends on TPA loading, calcination temperature, and the solvent used for the catalyst preparation. Under reaction conditions of 84 degrees C and a benzene/1-olefin molar ratio of 10 (time 1 h), the most active catalyst, 15% TPA, calcined at 750 degrees C, gave more than 98% olefin conversion with selectivity for 2-phenyl octane (53.5%) and 2-phenyl dodecane (47%). (c) 2004 Elsevier Inc. All rights reserved.
Keywords: 12-tungstophosphoric acid; linear alkyl benzene; solvent effect; Zirconia

Zirconia-supported phosphotungstic acid as catalyst for alkylation of phenol with benzyl alcohol - Devassy, Biju M.; Shanbhag, G. V.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of phenol with benzyl alcohol was carried out using zirconia-supported phosphotungstic acid (PTA) as catalyst. The catalysts with different PTA loadings (5-20 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 650 to 850 degrees C) were prepared and characterized by (31)p MAS NMR and FT-IR pyridine adsorption spectroscopy. The catalyst with optimum PTA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents. 31p MAS NMR spectra of the catalysts showed two types of phosphorous species, one is the Keggin unit and the other is the decomposition product of PTA and the relative amount of each depends on PTA loading, calcination temperature and the solvent used for the catalyst preparation. The catalysts with 15% PTA on zirconia calcined at 750 degrees C showed the highest Bronsted acidity. At 130 degrees C and phenol/benzyl alcohol molar ratio of 2 (time, I h), the most active catalyst, 15% PTA calcined at 750 degrees C gave 98% benzyl alcohol conversion with 83% benzyl phenol selectivity. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Benzylation; phenol; Phosphotungstic acid; Zirconia

2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz)-derived [Ru-II(tptz)(acac)(CH3CN)](+) and mixed-valent [(acac)(2)Ru-III(mu-tptz-H+)(-)Ru-II(acac)(CH3CN)](+) - Ghumaan, Sandeep; Kar, S.; Mobin, Shaikh M.; Harish, B.; Puranik, Vedavati G.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
Mononuclear [Ru-II(tptz)(acac:)(CH3CN)]ClO4 ((ClO4)-Cl-[1]) and mixed-valent dinuclear [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(CH3CN)]ClO4 ([5]ClO4; acac = acetylacetonate) complexes have been synthesized via the reactions of Ru-II(acac)2(CH3CN)(2) and 2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz), in 1:1 and 2:1 molar ratios, respectively. In [1]ClO4, tptz binds with the Ru-II ion in a tridentate N,N,N mode (motif A), whereas in [5]ClO4, tptz: bridges the metal ions unsymmetrically via the tridentate neutral N,N,N mode with the Ru-II center and cyclometalated N,C- state with the Ru-III site (motif F). The activation of the coordinated nitrile function in [1]ClO4 and [5]ClO4 in the presence of ethanol and alkylamine leads to the formation of iminoester ([2]ClO4 and [7]ClO4) and amidine ([4]ClO4) derivatives, respectively. Crystal structure analysis of [2]ClO4 reveals the formation of a beautiful eight-membered water cluster having a chair conformation. The cluster is H-bonded to the pendant pyridyl ring N of tptz and also with the O atom of the perchlorate ion, which, in turn, makes short (C-H––-O) contacts with the neighboring molecule, leading to a H-bonding network. The redox potentials corresponding to the (RuI)-I-I state in both the mononuclear {[(acac)(tptz)Ru-II-N=-C-CH3]ClO4 ([1]ClO4) >> [(acac)(tptz)Ru-II-NH=C(CH3)-OC2H5]ClO4 ([2]ClO4) > [(acac)(tptz)(RuNH2)-N-II-C6H4(CH3)]ClO4 ([3]ClO4) > [(acac)(tptz)Ru-II-NH=C(CH3)-NHC2H5]ClO4 ([4]ClO4)} and dinuclear {[(acac)(2)Ru-III-{mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 {(mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 ([5]ClO4), [(acac)(2)Ru-III[(mu-tptz-H+(N-O ([6]ClO4), [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NH=C(CH3)-OC2H5)]ClO4( [7]ClO4), and [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NC4H4N)]ClO4 ([8]ClO4), complexes vary systematically depending on the electronic nature of the coordinated sixth ligands. However, potentials involving the Ru-III center in the dinuclear complexes remain more or less invariant. The mixed-valent (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) exhibits high comproportionation constant (K-c) values of 1.1 X 10(12)-2 x 109, with substantial contribution from the donor center asymmetry at the two metal sites. Complexes display Ru-II- and Ru-III-based metal-to-ligand and ligand-to-metal charge-transfer transitions, respectively, in the visible region and ligand-based transitions in the UV region. In spite of reasonably high K, values for [5]ClO4[8]ClO4, the expected intervalence charge-transfer transitions did not resolve in the tpical near-IR region up to 2000 nm. The paramagnetic (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) displays rhombic electron paramagnetic resonance (EPR) spectra at 77 K (< g > similar to 2.15 and Delta g similar to 0.5), typical of a low-spin Ru-III ion in a distorted octahedral environment. The one-electron-reduced tptz complexes [RuII(tptz center dot-)(acac)(CH3CN)] (1) and [(acac)(2)Ru-III{mu-tptz-H+)(center dot 2-)}-Ru-II(acac)(CH3CN)] (5), however, show a free-radical-type EPR signal near g = 2.0 with partial metal contribution.

CFD simulation of shortstopping runaway reactions in vessels agitated with impellers and jets - Dakshinamoorthy, D.; Khopkar, A. R.; Louvar, J. F.; Ranade, V. V. (Journal of Loss Prevention in the Process Industries, 2006)
Runaway reactions are continuing to be a problem in the chemical industry. A recent study showed that 26% of our major chemical plant accidents are due to runaways. The consequences of runaway reactions are usually mitigated with (a) reliefs and containment systems or (b) shortstopping (reaction inhibition). This study covers the concept of shortstopping. One of the major reasons for runaways is power failure. In the advent of a power failure, mixing an inhibiting agent with the reactor contents is challenging. However, jets or impellers driven by a small generator can be used for mixing. This study compares shortstopping results in vessels agitated with jets and impellers using computational fluid dynamics (CFD). A commercial CFD code, Fluent is used. For shortstopping systems relying on jet mixing, angle and diameter of jet nozzle and jet velocity are the key design/operating parameters. For the systems with impellers, type, size and RPM of impeller are the key parameters. In this work, mixing with a jet mixer is first investigated for three nozzle diameters and two angles of injection. The best jet mixer configuration on the basis of mixing time is used for shortstopping studies. The simulated shortstopping results with the jet mixer are then compared with those obtained with impeller (Rushton and pitched blade turbine) stirred vessels. Our results identify the conditions for effective shortstopping; i.e., agitation requirements, locations for adding the inhibitor, and the quantity of inhibitor. The distribution of excess inhibitor is shown to be an important and essential design criterion for effective shortstopping when using impeller stirred vessels. The comparative study with a single jet shows that jet mixer is ineffective when used for shortstopping. Efforts such as adding excess inhibitor and inhibition with higher reaction rates at the same power, proved to be ineffective when using jet mixer compared to the results with impellers. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; impeller stirred vessels; jet mixer; runaway reaction; shortstopping

Characterization of polydimethylsiloxane rubber upon photochemical, thermal, salt-fog ageings and exposure to acid vapours - Delor-Jestin, Florence; Tomer, N. S.; Singh, R. P.; Lacoste, Jacques (E-Polymers, 2006)
The changes in the chemical structure and the physical properties of a filled crosslinked polydimethylsiloxane rubber were monitored as a function of various ageing factors. The variables included photochemical, thermal, salt-fog ageings and exposure to acid vapours. Unaged and aged samples were studied by IR spectroscopy, hardness measurements, Differential Scanning Calorimetry (DSC) and thermogravimetric analysis (TGA) coupled with IR spectroscopy. No significant oxidation was detected after all ageings, except for nitric acid treatment. The presence of aluminium trihydrate was clearly identified as responsible for the observed chemical changes. Then an important vulnerability of this filled silicone rubber towards the cross-linking reactions provoked by usual ageings was also detected. The DSC-thermoporosimetry measurements of the mesh size distribution gave a comparison of cross-linking densities for each ageing. The complementary analysis with TGA-IR allowed us to differenciate the thermal stability of the formulation after various ageings and to acquire new knowledge about thermal decomposition.

Comparative study of conductive polypyrrole and polyaniline coatings on electro-active papers - Kim, Jachwan; Deshpande, S. D.; Yun, Sungryul; Li, Qubo (Polymer Journal, 2006)
{A comparative study is performed on the conductive polymer-coated electro-active paper (EAPap) actuators by aiming at improving the overall performance of the actuators. Conductive Polymer coated Electro-active Paper [
IUPAC Symposium on Ionic Polymerization, Goa, INDIA, OCT 23-28, 2005
Keywords: conifer; glufosinate; particle bombardment; Pinus roxburghii; stable transformation

Copper-, ligand- and solvent-free synthesis of ynones by coupling acid chlorides with terminal alkynes - Palimkar, Sanjay S.; Kumar, P. Harish; Jogdand, Nivrutti R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron Letters, 2006)
A general and efficient copper-, ligand- and solvent-free synthesis of ynones by coupling of a wide range of acid chlorides with terminal alkynes catalyzed by palladium(II) acetate at room temperature is reported. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ligandless; neat; ynones

Densities and heat capacities of the ammonia plus water plus NaOH and ammonia plus water plus KOH solutions - Salavera, D.; Libotean, S.; Patil, K. R.; Esteve, X.; Coronas, Alberto (Journal of Chemical and Engineering Data, 2006)
Ammonia + water + sodium hydroxide and ammonia + water + potassium hydroxide mixtures were chosen as potential candidates for absorption chillers driven by low-temperature heat sources. Heat capacity and density were studied between (293.15 and 353.15) K at a constant pressure of 1.8 MPa for these solutions using a heat flux Calvet-type calorimeter and a vibrating-tube densimeter, respectively. Measured data were well-correlated with temperature and composition using simple polynomial equations. The relative deviations between the experimental and calculated values in the density and heat capacity measurements were 0.20 % and 0.49 % for NH3 + H2O + NaOH solutions and 0.10 % and 0.36 % for NH3 + H2O + KOH solutions, respectively. Also, two density prediction methods were checked using the experimental data. Previously, it was necessary to measure the density of ammonia and hydroxide aqueous solutions in similar conditions. The results showed that both methods are suitable for predicting the density of these solutions.

Effect of spacer groups on the performance of MCM-41-supported platinum cluster-derived hydrogenation catalysts - Maity, Niladri; Basu, Susmit; Mapa, Maitri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
MCM-41 was functionalized with (EtO)(3)SiCH2Cl, (MeO)(3)SiCH2CH2CH2Cl, and (CH3)Cl2SiCH2Cl. The functionalized materials were characterized by solid-state NMR (CPMAS, Si-29 and C-13) and XPS. The NMR data indicate that three new silicon environments were created by(EtO)(3)SiCH2Cl and (MeO)(3)SiCH2CH2CH2Cl, whereas with (CH3)Cl2SiCH2Cl, two new silicon environments were obtained. XPS results from Si 2p core level and the valence band from the material functionalized by (MeO)(3)Si(CH2)(3)Cl was found to be the same as that of the corresponding fresh catalyst (1a), in contrast to that of the materials functionalized by the other two silane reagents. After further functionalization with triethylamine, these materials were used as inorganic anion exchangers to support the cluster anion [Pt-12(CO)(24)](2-). Solid-state NMR (29Si, C-13, N-15) was used to establish the presence of the quaternary ammonium group in the cluster-supported species. Analogous materials were also created using fumed silica as the support, and all of the cluster-supported materials were tested as catalysts for the hydrogenation of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, ethylacetoacetate, 4-nitrotoluene, cyclohexanone, allyl alcohol, and styrene. The best activity was obtained for the catalyst that had MCM-41 as the support and chloropropyl as the spacer group. TEM showed that the supports and the spacer groups had observable effects on the platinum crystallite size of the catalysts. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: functionalized inorganic oxides; hydrogenation catalysts; MCM-41; platinum carbonyl cluster; Solid-state NMR; spacer groups; XPS

Enantioselective synthesis of (+)-(S,S)-reboxetine - Siddiqui, Shafi A.; Narkhede, Umesh C.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synlett, 2006)
An efficient enantioselective synthesis leading directly to (+)-(S,S)-reboxetine has been described from commercially available trans-cinnammyl bromide using Sharpless asymmetric dihydroxylation as the key step.
Keywords: coupling; Dihydroxylation; Hydrogenation; reboxetine; trans-cinnamyl bromide

Field emission studies of novel ZnO nanostructures in high and low field regions - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S.; Pillai, Vijayamohanan K. (Nanotechnology, 2006)
A study of the field emission characteristics of novel structures of ZnO, namely marigolds, multipods and microbelts, has been carried out in both the close proximity configuration and the conventional field emission microscope. The use of a conventional field emission microscope overcomes the drawback of arc formation at high field values. The nonlinearity in the Fowler - Nordheim ( F - N) plot, a characteristic feature of semiconductors has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability exhibited by these structures is also promising for future device applications.

Flexible ring polymers in an obstacle environment: Molecular theory of linear viscoelasticity - Iyer, Balaji V. S.; Lele, Ashish K.; Juvekar, Vinay A. (Physical Review E, 2006)
We formulate a coarse-grained mean-field approach to study the dynamics of the flexible ring polymer in any given obstacle (gel or melt) environment. The similarity of the static structure of the ring polymer with that of the ideal randomly branched polymer is exploited in formulating the dynamical model using aspects of the pom-pom model for branched polymers. The topological constraints are handled via the tube model framework. Based on our formulation we obtain expressions for diffusion coefficient D, relaxation times tau, and dynamic structure factor g(k,t). Further, based on the framework we develop a molecular theory of linear viscoelasticity for ring polymers in a given obstacle environment and derive the expression for the relaxation modulus G(t). The predictions of the theoretical model are in agreement with previously proposed scaling arguments and in qualitative agreement with the available experimental results for the melt of rings.

Genetic diversity analysis in Gaultheria fragrantissima wall. (Ericaceae) from the two biodiversity hotspots in India using ISSR markers - Apte, G. S.; Bahulikar, R. A.; Kulkarni, R. S.; Lagu, Meena D.; Kulkarni, B. G.; Suresh, H. S.; Rao, P. S. N.; Gupta, V. S. (Current Science, 2006)
Our study involves Inter Simple Sequence Repeat markers to analyse genetic diversity of an undershrub, Gaultheria fragrantissima Wall. (Ericaceae) from two plant diversity hotspots in India, namely Western Ghats and Northeastern Himalayas. The plants from these two regions show no morphological differences but the total heterozygosity (H-T = 0.505) is high. Furthermore, the average heterozygosity of G. fragrantissima at WG (H-s = 0.433) is higher than that at NE region (H-s, = 0.231). Within population variance is higher (15.56 %) than among population variance (8.31 %) as seen in outcrossing plant species. Mantel's test shows a strong positive correlation between the genetic and geographic distances. The plants within WG show high gene flow, which may be enough to prevent genetic drift, however, the gene flow in NE population is very low.
Keywords: Gaultheria fragrantissima; Genetic diversity; heterozygosity; ISSR markers

Heteropoly acid supported on titania as solid acid catalyst in alkylation of p-cresol with tert-butanol - Kumbar, Suresh M.; Shanbhag, G. V.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Butylation of p-cresol with tert-butanol was investigated on titania modified with 12-tungstophosphoric acid (TPA/TiO2) catalyst under vapor phase conditions. Catalysts with different TPA loadings (10-25 wt.%) and calcination temperatures (650-750 degrees C) were prepared by suspending titanium hydroxide in methanol solution of TPA followed by drying and calcination. These catalysts were characterized by surface area, XRD, P-31 MAS NMR, XPS, NH3-TPD, and FTIR pyridine adsorption. XRD results indicated that the presence of TPA retarded the crystallization of titania and stabilized TiO2 in anatase phase. P-31 MAS NMR indicated the presence of TPA in various forms (dispersed, highly fragmented and Keggin intact). These catalysts showed both Bronsted and Lewis acidity, and 20% TPA on TiO2 calcined at 700 degrees C (from here after words 20% TT 700) had the highest Bronsted as well as total acidity. Further, the catalytic activities were examined in tert-butylation of p-cresol with tent-butanol. The catalytic activity depended on TPA coverage, and the highest activity corresponded to the monolayer of TPA on titania. The most active catalyst 20% TT-700 gave 82% conversion of p-cresol and 89.5% selectivity towards 2-tert-butyl cresol (TBC), 2,6-di-tert-butyl cresol (DTBC) 7.5% and cresol-tert-butyl ether (CTBE) 3% under optimized conditions. The activity was always higher than that of WO3/ZrO2, sulfated zirconia (SZ), USY, H-beta zeolites and montmorillonite K-10 (K-10mont) under similar conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2; 2-tert-butyl-p-cresol; 6-di-tert-butyl-p-cresol; Alkylation; heteropoly acid; p-Cresol; tert-butanol; titania

High-throughput screening of RNA polymerase inhibitors using a fluorescent UTP analog - Bhat, Jyothi; Rane, Rajendra; Solapure, Suresh M.; Sarkar, Dhiman; Sharma, Umender; Harish, M. N.; Lamb, Sarah; Plant, Darren; Alcock, Peter; Peters, Steve; Barde, Shubhada; Roy, Raman K. (Journal of Biomolecular Screening, 2006)
RNA polymerase (RNAP) is a well-validated target for the development of antibacterial and antituberculosis agents. Because the purification of large quantities of native RNA polymerase from pathogenic mycobacteria is hazardous and cumbersome, the primary screening was carried out using Escherichia coli RNAP. The authors have developed a high-throughput screening (HTS) assay to screen for novel inhibitors of RNAP. In this assay, a fluorescent analog of UTP, gamma-amino naphthalene sulfonic acid (gamma-AmNS) UTP, was used as one of the nucleotide substrates. Incorporation of UMP in RNA results in the release of gamma-AmNS-PPi, which has higher intrinsic fluorescence than (gamma-AmNS) UTP. The assay was optimized in a 384-well format and used to screen 670,000 compounds at a concentration of 10 mu M. About 0.1% of the compounds showed more than 60% inhibition in the primary HTS. All the primary actives tested for dose response using the same assay had an EC50 below 100 mu M. Eighty percent of the primary HTS actives obtained using E. coli RNAP showed comparable activity against Mycobacterium smegmatis RNAP in the conventional radioactive assay. Activity of hits selected for the hit-to-lead optimization was also confirmed against Mycobacterium bovis RNAP which has > 99% sequence identity with Mycobacterium tuberculosis RNAP subunits.

Ionic liquid promoted facile one-pot synthesis of 1-pyridylimidazo[1,5-a]pyridines from dipyridylketone and aryl aldehydes - Siddiqui, Shafi A.; Potewar, Taterao M.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synthesis-Stuttgart, 2006)
A highly efficient one-pot methodology has been developed to synthesize a class of substituted 1-pyridylimidazo[ 1,5-a]pyridines, using Bronsted acidic ionic liquid 1-butylimidazolium tetrafluoroborate, [Hbim]BF4 in excellent isolated yields in the absence of any catalyst. The methodology is characterized by simple work-up procedures along with efficient recovery and recycling of the ionic liquid, which acts as a reaction medium as well as a promoter.
Keywords: 5-a]pyridines; Aldehyde; ammonium acetate; heterocycles; imidazo[1; ionic liquids

Ligand-, copper-, and amine-free one-pot synthesis of 2-substituted indoles via Sonogashira coupling 5-endo-dig cyclization - Palimkar, Sanjay S.; Kumar, P. Harish; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron, 2006)
Results of the optimized conditions for the one-pot synthesis of 2-substituted indoles via palladium acetate catalyzed tandem Sonogashira coupling 5-endo-dig cyclization at room temperature under ultrasonic irradiation and standard stirred conditions are described. Electron-donating and electron-withdrawing groups present in both Coupling partners were well tolerated under these mild conditions. A copper-, ligand- and amine-free condition is an important feature of this protocol. Significant enhancement of reaction rates was observed for the reactions employing ultrasonic irradiation. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 5-endo-dig cyclization; Indole; synthesis; Ultrasound

MCM-41-supported platinum carbonyl cluster-derived catalysts for asymmetric and nonasymmetric hydrogenation reactions - Basu, Susmit; Mapa, Maitri; Gopinath, Chinnakonda S.; Doble, Mukesh; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
Anionic platinum carbonyl Cluster ([Pt-12(CO)(24)](2-)) was ion-paired with the 3-chloropropyltrimethoxysilyl-ammonium group chemically bound to the surface of MCM-41. The materials undergo quick decarbonylation and have been characterized before decarbonylation by IR and UV-vis spectroscopy and after decarbonylation by XPS and TEM. They have been used as catalysts for the hydrogenations of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, and ethylacetoacetate. The support and the quaternary ammonium groups have significant effects on surface platinum concentration, crystallite size, and observed activity. In the hydrogenation of the prochiral substrates methyl pyruvate or acetophenone, the cinchonidine-based catalyst gives significant enantioselectivity under optimum conditions. A kinetic model that includes an enantioselective product-formation step and a hydrogen pressure-dependent step for the deactivation of the enantioselective sites gives reasonable agreement between predicted and observed enantioselectivity. The model is also in accordance with the XPS and TEM data. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: asymmetric/non-asymmetric catalysis; Enantioselectivity; functionalized MCM-41; hydrogenation catalysts; platinum carbonyl cluster

Metal-induced reductive ring opening of 1,2,4,5-tetrazines: Three resulting coordination alternatives, including the new non-innocent 1,2-diiminohydrazido(2-) bridging ligand system - Maji, Somnath; Sarkar, B.; Patra, S.; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
{Reaction of 3,6-diaryl-1,2,4,5-tetrazines (aryl = R = phenyl, 2-furyl or 2-thienyl) with 2 equiv of Ru(acac)(2)(CH3-CN)(2) results in reductive tetrazine ring opening to yield diruthenium complexes [
Keywords: crystal engineering; hydrogen bonds; molecular; recocynition; Self-assembly; supramolecular chemistry

Modifications in magnetic anisotropy of M-type strontium hexaferrite crystals by swift heavy ion irradiation - Kaur, Balwinder; Bhat, Monita; Licci, F.; Kumar, Ravi; Kulkarni, S. D.; Joy, Pattayil Alias; Bamzai, K. K.; Kotru, P. N. (Journal of Magnetism and Magnetic Materials, 2006)
Using vibrating sample magnetometery (VSM) 50 MeV Li(3+) ion irradiation effects on magnetic properties of single crystals of SrGa(x)In(y)Fe(12-(x+y))O(19) (where x = 0, 5, 7, 9; y = 0, 0.8, 1.3, 1.0), are reported. The substitution of Ga and In in strontium hexaferrite crystals decreases the value of magnetization sharply, which is attributed to shifting of collinear magnetic order to a non-collinear one. Reduction of magnetization is also explained to be as a result of the occupation of the crystallographic sites of Fe(3+) by Ga(3+) and In(3+). The Li(3+) ion irradiation decreases the value of magnetization, irrespective of whether the crystals are Ga-In substituted or unsubstituted crystals of SrFe(12)O(19). The result is interpreted in terms of the occurrence of a paramagnetic doublet in crystals replacing magnetic sextuplet as a result of irradiation. Substitution of Ga-In in Strontium hexaferrite decreases the value of anisotropy constant. Irradiation with Li(3+) ions increases the values of anisotropy field for both substituted as well as unsubstituted crystals. Substitution with Ga-In also decreases the Curie temperature (T(c)) but the irradiation with Li(3+) ions does not affect the curie temperature of either Ga-In substituted or pure SrFe(12)O(19) crystals. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: anisotropy field; Curie temperature; irradiation; Magnetic anisotropy; Magnetization

Morphological mutants of gibberella fujikuroi for enhanced production of gibberellic acid - Lale, Geetanjali; Jogdand, Vitthal V.; Gadre, Ramchandra V. (Journal of Applied Microbiology, 2006)
Aims: To examine the production of gibberellic acid by selected morphological mutants of Gibberella fujikuroi in liquid cultures. Methods and Results: Mutants of G. fujikuroi having different morphological characteristics were selected after UV irradiation. The production of gibberellic acid by mutants that had different hyphal lengths was examined in shake flasks in media with different concentrations of nutrients as well as different volumes of the medium. Fed-batch fermenter study was performed to evaluate the mutant Mor-25 for growth and production of gibberellic acid. The broth was analysed by high performance liquid chromatography for fusaric acid, the common mycotoxin produced by strains of Fusarium. A variety of morphological mutants having different mycelial and soluble pigmentation as well as colony morphologies were generated from G. fujikuroi upon exposure to UV radiation. A nonpigmented mutant (Car-1) was selected as intermediate parent and later, mutants Mor-1 and Mor-25 were selected based on their distinct morphology. The colonies on regeneration agar plates were small, compact and dry. In liquid medium, mutant Mor-25 grew in a micro-pelleted form and the mycelium had short, highly branched hyphae, curly at tips with thick, swollen cells. Mutant Mor-25 grew rapidly in a low-cost medium containing defatted groundnut flour, sucrose and salts. In media with higher nutrient concentrations as well as larger volumes, it produced twofold more gibberellic acid than the parent. Fusaric acid, the common mycotoxin, was absent in the fermentation broth of mutant Mor-25. The mutants have been deposited in National Collection of Industrial Microorganisms (NCIM), National Chemical Laboratory, Pune, India under following culture collection numbers (Car-1, NCIM 1323; Mor-1, NCIM 1322; and Mor-25, NCIM 1321). Conclusion: Growth of unpigmented, morphological mutants of G. fujikuroi that led to lower viscosity in fermentation broth resulted in increased production of gibberellic acid. Significance and Impact of Study: The use of morphological mutants that have lower viscosity in liquid cultures for gibberellic acid production is not reported earlier. Similar mutants can be useful for other types of fungal fermentations also.

Nanocomposites of polypropylene impact copolymer and organoclays: role of compatibilizers - Deenadayalan, E.; Vidhate, Shailesh; Lele, Ashish K. (Polymer International, 2006)
Nanocomposites of polypropylene impact copolymer and organoclays were prepared using different compatibilizers (polypropylene-graft-(maleic anhydride) (PPMA), polyethylene-graft-(maleic anhydride) (PEMA) and their mixture) and varying percentages of clay (3 and 6%) in an attempt to obtain balanced mechanical properties. The nanocomposites were prepared by melt compounding and test specimens were prepared by injection molding. Mechanical properties such as tensile, flexural and Izod impact strength are reported. The clay dispersion was investigated using wide-angle X-ray diffraction while the phase morphology was characterized using scanning electron microscopy. It is shown that the mechanical properties of the system with mixed PPMA and PEMA compatibilizers showed the best balance of mechanical properties among the nanocomposites explored. (C) 2006 Society of Chemical Industry.
Keywords: clay; compatibilizers; Nanocomposites; polypropylene

Optimization of fermentation media for exopolysaccharide production from lactobacillus plantarum using artificial intelligence-based techniques - Desai, Kiran M.; Akolkar, S. K.; Badhe, Yogesh P.; Tambe, S. S.; Lele, S. S. (Process Biochemistry, 2006)
A Lactobacillus strain was isolated from the fermented Eleusine coracana. This strain was characterized as Lactobacillus plantarum and was found to produce an exopolysaccharide (EPS) in quantitative amounts. The objective of the present paper is to determine optimum media composition and inoculum volume for the stated fermentative production of the EPS. A hybrid methodology comprising the Plackett-Burman (PB) design method, artificial neural networks (ANN) and genetic algorithms (GA) was utilized. Specifically, the PB, ANN and GA forrnalisms were used for identifying influential media components, modeling non-linear process and optimizing the process, respectively. More specifically, the PB method was used to determine those media components, which significantly influence the EPS yield. By ignoring the less influential media components, the dimensionality of the input space of the process model could be reduced significantly. Out of the five media components only three were found influential namely, lactose, casein hydrolysate and triammonium citrate. Next, an ANN-based process model was developed for approximating the non-linear relationship between the fermentation operating variables and the EPS yield. The average % error and correlation coefficient for the developed ANN model were 4.8 and 0.999, respectively. The input parameters of ANN model were subsequently optimized using the GA formalism for obtaining maximum EPS yield in batch fermentation. The optimized media composition has predicted the yield of 7.01 g/l. The GA-optimized solution comprising media composition and inoculum volume was verified experimentally and it comes out be 7.14 g/l. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Artificial neural network; exopolysaccharide; Fermentation; Genetic algorithm; Lactobacillus plantarum; Media optimization; Plackett-Burman

Remarkably rapid regioselective synthesis of beta-enaminones using silica chloride in a heterogeneous as well as an ionic liquid in a homogeneous medium at room temperature - Gholap, Atul R.; Chakor, N. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Molecular Catalysis A-Chemical, 2006)
{Silica chloride as a heterogeneous catalyst has been used for the regioselective synthesis of P-amino-a,P unsaturated esters and ketones. Similar regioselective synthesis was also performed using an ionic liquid 1-n-butyl imidazolium tetrafluoroborate [
6th International Conference on Solvothermal Reactions, Mysore, INDIA, AUG 24-27, 2004
Keywords: direct oxidation of H-2 to H2O2; H2O2 decomposition; H2O2 hydrogenation; Promoting action of chloride or bromide anions; supported Pd catalysts

Studies on shrikhand rheology - Kulkarni, C.; Belsare, N.; Lele, Ashish K. (Journal of Food Engineering, 2006)
Shrikhand, a popular Indian dessert made from yogurt, is manufactured on an industrial scale using several chemical engineering unit operations such as mixing, filtration and heat transfer. Understanding the rheology of shrikhand is not only relevant for designing large scale mixers but can also provide quantitative means for linking the microstructure of shrikhand to its perception of texture, consistency and taste. We show here that shrikhand exhibits a combination of several rheological properties such as weak gel-like viscoelasticity, an apparent yield stress, thixotropy and long structural recovery time scales. For instance, the elastic modulus is always higher than the loss modulus over the measurable frequency range and that both moduli show only weak frequency dependence that is a characteristic of gel-like consistency. Forward and reverse rate sweep tests show a distinct hysteresis loop, which is a signature of thixotropic character. In an attempt to trace the origins of these rheological properties in shrikhand we characterized its microstructure and showed that there exist two different microstructures: one composed of crystallites of milk fats having a length scale of similar to 50-100 mu m, and the other composed of aggregates of colloidal cascin micelles of similar to 0.5-10 mu m size. Our studies show that while the temperature sensitivity of the viscoelastic parameters is dominated by the semicrystalline milk fat microstructure, the shear sensitivity is largely dictated by the protein network. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Microstructure; Rheology; shrikhand

Surface characterization of diblock copolymers containing poly(ethylene oxide) and various hydrophobic moieties - Logan, Jennifer; Marcano, Kyle; Palaskar, Dnyaneshwar; Wadgaonkar, Prakash; Jost, Robert W.; Wudl, Fred; Baker, Shenda M. (231st National Meeting of the American-Chemical-Society, 2006)
231st National Meeting of the American-Chemical-Society, Atlanta, GA, MAR 26-30, 2006

Surface modification of polyacrylonitrile based ultrafiltration membrane - Lohokare, Harshada R.; Kumbharkar, S. C.; Bhole, Yogesh S.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2006)
Ultrafiltration membrane based on polyacrylonitrile prepared by phase inversion method using zinc chloride as an additive showed more than 90% rejection for BSA and 90-110 Im(-2) h(-1) water flux. The surface modification of this membrane was studied using ethanolamine, triethylamine, sodium hydroxide, and potassium hydroxide solutions. The effect of base treatment time and temperature on water flux and rejection was investigated. The membranes exhibited swelling by NaOH treatment followed by deswelling by HCl post-treatment, similar to pH responsive membranes. The treatment by organic as well as inorganic bases improved water flux with a slight lowering in BSA rejection by dead-end mode type treatment. A 230% increase in water flux was achieved by sodium hydroxide treatment in crossflow mode without a noticeable pore swelling by SEM. The contact angle of the modified membranes was decreased as compared to the unmodified one indicating appreciable surface modification. As the treatment time or temperature increased, the ESCA analysis showed increased population of Na-carboxylate groups. (c) 2006 Wiley Periodicals, Inc.
Keywords: BSA rejection; chemical treatment; polyacrylonitrile membrane; surface modification; Ultrafiltration

Synthesis and characterization of novel hydrophobically end-capped poly(ethylene oxide)s [PEOs] - Badiger, Manohar V.; Kadam, Vijay S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique (Macromolecular Symposia, 2006)
We report on the synthesis and characterization of a novel hydrophobically modified end-capped poly(ethylene oxide)s. The end-capping agent of this polymer was designed and synthesised from a renewable resource material namely, gallic acid (i.e. 3,4,5-trihydroxybenzoic acid), the byproduct of tannin industry. The hydroxyl groups at 3, 4 and 5 positions of gallic acid provide an opportunity for varying the hydrophobicity of the compound. The hydrophobic end-capping compound, 3,4,5tridodecyloxy bezoylazide was prepared from gallic acid and PEGS with different chain lengths (of number average molecular weights, 10000 and 35000 g/mol) were endcapped. using 3,4,5-tridodecyloxybenzoyl azide. The quantitative analysis of end-capping in the polymers was demonstrated by H-1-NMR spectroscopy and the rheological studies were carried out in the surfactant solutions.
Indo-French Symposium on Fibrillar Networks as Advanced Materials, Inst Charles Sadron, Strasbourg, FRANCE, SEP 21-23, 2005
Keywords: end-capped PEOs; hydrophobically modified polymers; water-soluble polymers

Thermotropic behavior of lithocholic acid derivative linked hydroxyethyl cellulose - Shaikh, V. A. E.; Maldar, Noormahamad N.; Lonikar, Shrikant Vitthal; Rajan, C. R.; Ponrathnam, S. (Journal of Applied Polymer Science, 2006)
Various mesogenic lithocholic acid (LA) derivatives [3-acetyl LA (LAAC); 3-propionyl LA (LAP), 3-cinnamoyl LA (LACin); 3-benzoyl LA (LAB), 3-(4-nitrobenzoyl) LA (LANB); and methyl-3-(3-carboxypropionyl) LA, i.e., LA methyl ester monosuccinate (LAMeMS)] were reacted with hydroxyethyl cellulose (HEC) to obtain a series of LA derivatives of HEC. These polymers were characterized by the mesogen content, 1.1, differential scanning calorimetry, and hot-stage coupled polarizing optical microscopy. The degree Of Substitution (DS) ranged from 0.27 to 1.11. Polymers HEC-LAB (DS = 1.11), HEC-LANB (DS = 0.80), HEC-LACin (DS = 0.76), and HEC-LAP (DS = 0.27) exhibited a mesophase on heating whereas HEC-LAB also showed a mesophase on cooling. The other polymers HEC-LAAC (DS = 0.89) and HEC-LAMeMS (DS = 0.36) did not reveal mesophase formation with either heating or cooling. It is observed that the formation of a mesophase is affected by the type of mesogen that is used rather than the mesogen content of the polymer. (c) 2006 Wiley Periodicals, Inc.
Keywords: hydroxyethyl cellulose; lithocholic acid; thermotropic

ZnO multipods, submicron wires, and spherical structures and their unique field emission behavior - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; More, Mahendra A.; Mulla, Imtiaz S.; Joag, Dilip S.; Vijayamohanan, K. (Journal of Physical Chemistry B, 2006)
A simple method of vapor deposition for the shape selective synthesis of ZnO structures, namely, multipods, submicron wires, and spheres, has been successfully demonstrated. A plausible growth mechanism based on the studies of scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) is proposed. Our studies suggest that the growth of a multipod structure is governed by the screw dislocation propagation while the vapor-liquid-solid (VLS) mechanism is responsible for the formation of submicron wires and spheres. Moreover, the flow rate of the carrier gas plays a crucial role in governing the morphology. Further, these structures exhibit an enhanced field emission behavior. The nonlinearity in the Fowler-Nordheim (F-N) plot, a characteristic feature of electron emission from semiconductors, is explained by considering the contributions from both the conduction and the valence bands of ZnO.

Au nanoparticle templated synthesis of pNIPAm nanogels - Singh, Neetu; Lyon, L. Andrew (Chemistry of Materials, 2007)

Bioconjugation of soft nanomaterials - Singh, Neetu; Blackburn, William H.; Lyon, L. Andrew (Biomedical Nanostructures, 2007)

Blocking effects in irreversible adsorption of linear macromolecules - Shelke, Pradip B.; Banpurkar, Arun G.; Ogale, S. B.; Limaye, A. V. (Surface Science, 2007)
{A new variant of random sequential adsorption (RSA), namely random sequential ballistic adsorption (RSBA), is proposed to explore the possible role of blocking effects in the adsorption dynamics of ballistically arriving objects. These objects upon adsorption can protrude outside the substrate and in turn can obstruct and hence reject the adsorption of newly arriving objects. Adsorption of linear macromolecules (modeled as infinitesimally thin needles), on a two-dimensional continuum substrate is studied using RSBA model. It is shown analytically that in late time regime, the number n(t) of adsorbed objects at time t follows a power law n(t) similar to t(alpha), as in RSA, but with a different exponent
Keywords: Adsorption; adsorption kinetics; Monte Carlo simulations; random sequential adsorption (RSA)

Cholesterol-linked beta-cyclodextrin - a thermotropic liquid-crystalline derivative - Shaikh, Vasi Ahmed Ebrahim; Lonikar, Shrikant Vitthal; Dhoble, Deepa Arun; Pawar, G. M. (Bulletin of the Chemical Society of Japan, 2007)
Liquid-crystalline derivative of ss-cyclodextrin (BCD) was prepared by covalent linking of monocholesteryl succinate (ChMS) with ss-cyclodextrin. To the best of our knowledge, this was first ever attempt so far of its kind, in which BCD has been converted into its liquid-crystalline derivative through covalent linkage of a mesogen. The degree of substitution (DS) obtained was approximate to 2.00. The product was characterized by various techniques, such as FT-IR, NMR, DSC, hot-stage-coupled optical polarizing microscopy (OPM), microanalysis and chemical methods. Cholesterol-linked ss-cyclodextrin (CDCh) derivative was found to exhibit thermotropic liquid-crystalline behavior. The product exhibited birefringence during first heating above 130 degrees C, and it became isotropic at about 180 degrees C, whereas the parent compound BCD decomposed without melting above 250 degrees C. A comparison of CDCh derivative to similar liquid-crystalline polysaccharide derivatives is presented.

Cross-linking assessment after accelerated ageing of ethylene propylene diene monomer rubber - Tomer, N. S.; Delor-Jestin, Florence; Singh, R. P.; Lacoste, Jacques (Polymer Degradation and Stability, 2007)
The ageing of filled and cross-linked ethylene propylene diene elastomer (EPDM) has been studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C, thermal ageing at 100 degrees C and in nitric acid vapours for different time intervals. Hardness measurements were performed. DSC-thermoporosimetry was used to estimate the mesh size distribution and cross-linking densities for each ageing. The development of functional groups was monitored by ATR spectroscopy. An increase in oxidation with exposure time after the different types of ageing was observed. The thermal stability of EPDM was assessed by TGA and evolved volatile gases were identified using FTIR spectroscopy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ageing; EPDM; Oxidation; thermal analysis; thermoporosimetry

Direct hydrothermal synthesis of mesoporous Sn-SBA-15 materials under weak acidic conditions - Shah, P.; Ramaswamy, A. V.; Lazar, Karoly; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2007)
A direct synthetic route for the preparation of Sn-SBA-15 materials with n(Si)/n(Sn), ratios ranging from 100 to 10 under milder acidic conditions than normally employed for the preparation of Si-SBA-15 is reported. The changes in the pH conditions of the gel were made through an adjustment of the molar ratio of n(H2O) to n(HCl) (< 1 pH < 2) during preparation. The samples prepared under three different acidic conditions have been characterized by various techniques. An expansion of the lattice (powder XRD) and an increase in mesopore area (low temperature N-2 adsorption) indicate that the hexagonal structure of the SBA- 15 is maintained with no loss of long range ordering. The UV-vis reflectance spectra of Sn-SBA-15 samples show the presence of Sn4+ ions both in tetrahedral and octahedral environment. Si-29 MAS NMR spectra of samples prepared under an intermediate acid condition show the presence Of Q(3) and Q(4) species. Their ratio increases with a decrease in tin content. The presence of Si in (2Si, 2Sn) i.e., Q(2) environment may point to incorporation of considerable Sn4+ ions in tetrahedral positions. Sn-Mossbauer spectroscopic studies reveal that Sn2+ species form upon reductive treatments and can probably be stabilized in the pore wall upon reoxidation. This to some extent is an indication of the formation and stabilization of Si-O-Sn-O-Si linkages in Sn-SBA-15. A progressive increase in the pH of the medium (increasing the n(H2O) to n(HCl), ratio) results in the location of Sn4+ ions, (a) at the surface of the mesopores (surface of the corona region) as a thin film of SnO2 or small aggregates (loss in mesopore area) depending on the concentration of Sn; (b) at the walls of the mesopore structure, substituting Si4+ ions (some lattice expansion and tetrahedral Sn4+ ions); and/or (c) as a part of the corona region, neutralizing the resulting Si-OH groups (a loss of micropore area and octahedral Sn4+ ions). The studies reveal that the method of preparation, n(H2O)/n(HCl) ratio and the n(Si)/n(Sn) ratio (concentration of SnCl4) of the gel significantly influence the type of tin species in the resulting Sn-SBA-15 samples. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: direct synthesis of Sn-SBA-15; Si-29 and Sn-119 MAS-NMR; Sn-mossbauer spectroscopic studies; Sn-SBA-15; tin-mesoporous silica

Displacement-induced switching rates of bioresponsive hydrogel microlenses - Kim, Jongseong; Singh, Neetu; Lyon, L. Andrew (Chemistry of Materials, 2007)

Excellent exo/endo-selectivity in the 1,3-dipolar cycloaddition of cyclic azomethine ylide: exploring the facile investigation of cocaine antagonists - Laha, Joydev K. (Letters in Organic Chemistry, 2007)
High exo-selectivity was achieved in the 1,3-dipolar cycloaddition of a cyclic azomethine ylide and phenyl vinyl sulfone or Opplozer's camphorsultam chiral dipolarophile leading to the synthesis of two novel tropane compounds.
Keywords: 1; 3-dipolar cycloaddition; cocaine antagonists; cyclic azomethine ylide; exo/endo-selectivity.; tropane

Fabrication of MEMS composite-polymer gas sensor arrays for electronic nose - Pant, B. D.; Kutnar, Mahesh; Lakshmi, Subha; Arora, Anil; Prasad, Mahanth; Sharma, Akshdeep; Patel, Mohan; Radhakrishnan, S.; Dwivedi, V. K. (Indian Journal of Pure & Applied Physics, 2007)
Sensor arrays capable of sensing different gases combined with a sampling system and a means of pattern classification and recognition comprise a basic system for an `Electronic Nose' In the present work, a complete process for the fabrication of micro-cavities with sensing electrodes and volumes ranging from 2.5 to 12 nano-liters for the development of polymer gas sensors has been reported. An array of eight sensing cells in four sizes have been fabricated using SU-8 negative tone resist through UV-LIGA process developed at CEERI, Pilani. The length and width of the SU-8 cavities are: 250 x 250, 300 x 300, 500 x 500 and 500 x 600 micron and the depth of each of them was optimized to be 40 micron. These cavities filled with different polymer composites comprise the basic sensing cells for a variety of gases. The current paper presents the salient features of the fabrication process in detail and the results obtained in ethanol and methanol ambient using a polymer composite developed through dissolution of styrene and polyaniline in PMMA. A number of other composites such as Pc-Ppy, Pr-Ppy, Fc(+)-PPy have also been synthesized and tested for a high sensitivity in carbon monoxide.
Indo-Chinese Workshop on Micro Electron Mechanical Systems (MEMS) and Related Technologies, Natl Phys Lab, New Delhi, INDIA, APR 05-07, 2006
Keywords: composite polymer; conducting polymer; electronic nose; polymer gas sensor; selectivity; sensitivity; sensor array

Field emission investigations of RuO2-doped SnO2 wires - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Applied Surface Science, 2007)
Field emission studies of a bunch and a single isolated RuO2:SnO2 wire have been performed. A current density of 5.73 x 10(4) A/cm(2) is drawn from the single wire emitter at an applied field of 8.46 x 10(4) V/mu m. Nonlinearity in the Fowler-Nordheim (F-N) plot has been observed and explained on the basis of electron emission from both the conduction and the valence bands of the semiconductor. The current stability recorded at the preset value of 1.5 LA is observed to be good. Overall the high emission current density, good stability and mechanically robust nature of the RuO2:SnO2 wires offer advantages as field emitters for many potential applications. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emission; field enhancement factor; RuO2; SnO2

Gas permeation in amine functionalized silicon rubber membranes - Achalpurkar, Manoj P.; Kharul, Ulhas K.; Lohokare, Harshada R.; Karadkar, Prasad B. (Separation and Purification Technology, 2007)
Silicon rubber (SR) based thin film composite (TFC) membranes find increasing applicability in various industrial separations owing to its excellent thermal and chemical stability. The functionalization of SR would provide enhanced separation characteristics for certain separation applications. The present research focuses on gas permeation properties of dense and thin film composite membranes based on amine substituted silicon rubber (ASR) and unsubstituted silicon rubber (SR). The dense membrane sorption analysis indicated that presence of amine functionality in ASR increased pressure dependant CO2 sorption capacity. Owing to this, an elevation Of CO2 permeability by 15% and CO2 based selectivities by 22-34% in comparison to that of unsubstituted SR was observed. The TFC membranes with SR and ASR as the selective layer on the top of different ultrafiltration (UF) supports with varying properties based on polyacrylonitrile and polysulfone were prepared. The effects of crucial parameters that affected TFC membrane performance, viz., coating solution concentration, UF support membrane porosity and nature of materials were investigated. The preparation of ASR based TFC membranes was demonstrated with a simple crosslinking agent-glutaraldehyde while analyzing effects of crosslinking time on their permeation properties. Polyacrylonitrile (PAN) was found to be better support layer material for ASR based TFC formation than polysulfone (PSF). Thin defect free coating layer can be obtained by appropriate combination of coating solution concentration and support UF membrane porosity. The analysis of effective skin layer thickness of TFC membranes indicated that careful optimization of these parameters is necessary to achieve defect free TFC membranes possessing a good combination of permeance and selectivity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; Gas permeation; silicon rubber; thin film composite membrane

Geometrical solution to the sharkskin instability - Pol, Harshawardhan V.; Joshi, Yogesh M.; Tapadia, Prashant S.; Lele, Ashish K.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2007)
We study the effect of die exit divergence on the sharkskin behavior, both experimentally as well as through the use of computational fluid dynamics (CFD) simulations. Sharkskin or surface fracture is known to occur immediately after the die exit, because of the large elongational deformation that a polymer melt experiences as it exits the die. We show that the diverging taper at the die exit postpones or completely removes the occurrence of sharkskin. The corresponding CFD simulations of an equivalent K-BKZ fluid show that the taper at the die exit significantly reduces the severity of the elongational flow, thereby reducing the normal stresses as the polymer melt leaves the die. We believe that, in an extrusion operation, the provision of a diverging taper at the die exit is one of the potential measures by which sharkskin instability can be eliminated on an industrial scale.

Impact of orientational distribution of adsorbing objects on dynamics of Random Sequential Ballistic Adsorption (RSBA) dynamics - Shelke, Pradip B.; Banpurkar, Arun G.; Ogale, Satishchandra B.; Limaye, A. V. (Surface Science, 2007)
Recently, by proposing a new variant of Random Sequential Adsorption (RSA) namely Random Sequential Ballistic Adsorption (RSBA) model [Pradip B. Shelke, A.G. Banpurkar, S.B. Ogale, A.V. Limaye, Surf. Sci. 601 (2007) 274], we addressed the issue of adsorption dynamics of extended objects where the objects, upon adsorption, protrude outside the substrate. This study brought out the role of the arriving trajectory in the adsorption dynamics. In the present work the possible role of the orientational distribution of the arriving objects in the RSBA dynamics is investigated. The dynamics of RSBA of needles (line segments) is studied analytically and by computer simulation for different types of theta distributions of arriving needles, theta being the angle made by the arriving needle with normal to the substrate. Three types of theta distributions, namely a uniform distribution over the range (0, pi/2), a Gaussian distribution and a distribution uniform over the solid angle, are considered. Analytical treatment establishes that in all the three cases, the number n(t) of adsorbed objects at a late time t follows a power law n(t) similar to t(alpha), and the exponent a depends on the specifics of the theta distribution. In general, for distribution f(theta) proportional to theta(beta), for theta -> 0, alpha is found to be 2/(beta + 3). The simulation results are in excellent agreement with the analytical findings and together they reveal that the orientational distribution of arriving objects has significant consequences for the Random Sequential Ballistic Adsorption (RSBA) process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Adsorption; adsorption kinetics; Monte Carlo simulations; random sequential adsorption (RSA)

Improve polyethylene process control and product quality - using artificial intelligence-based sensors can improve costs - Badhe, Yogesh P.; Lonari, J.; Tambe, S. S.; Kulkarni, B. D.; Valecha, N. K.; Deshmukh, S. V.; Ravichandran, S. (Hydrocarbon Processing, 2007)

Influence of ancillary binding and nonspecific adsorption on bioresponsive hydrogel microlenses - Kim, Jongseong; Singh, Neetu; Lyon, L. Andrew (Biomacromolecules, 2007)

Low temperature synthesis of magnetite and maghemite nanoparticles - Bhagwat, Shrikant; Singh, Hema; Athawale, Anjali; Hannoyer, Beatrice; Jouen, Samuel; Lefez, Benoit; Kundaliya, Darshan; Pasricha, Renu; Kulkarni, Shailaja; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2007)
We report on the synthesis of iron oxide nanoparticles below 100 degrees C by a simple chemical protocol. The uniqueness of the method lies in the use of Ferrous ammoniurn sulphate (in conjugation with FeCl3) which helps maintain the stability of Fe-2+ state in the reaction sequence thereby controlling the phase formation. Hexamine was added as the stabilizer. The nanoparticles synthesized at three different temperatures viz, 5 degrees, 27 degrees, and 95 degrees C are characterized by several techniques. Generally, when a mixture of Fe3+ and Fe2+ is added to sodium hydroxide, alpha-Fe2O3 (the anti-ferromagnetic phase) is formed after the dehydration process of the hydroxide. In our case however, the phases formed at all the three temperatures were found to be ferro (ferri) magnetic, implying modification of the formation chemistry due to the specifics of our method. The nanoparticles synthesized at the lowest temperature exhibit magnetite phase, while increase in growth temperature to 95 degrees C leads to the maghemite phase.
Keywords: low temperature synthesis; maghemite; magnetite; Nanoparticles

Novel one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in water - Palimkar, Sanjay S.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Green Chemistry, 2007)
A novel green and efficient one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in excellent isolated yields has been reported. The methodology initially involves the formation of ynones via coupling of a wide range of acid chlorides with terminal alkynes catalysed by Pd(OAc)(2) under copper-, ligand- and solvent-free conditions in just 10 min at rt followed by the Michael addition and cyclocondensation of o-phenylenediamines added in situ using water as a solvent at reflux temprature. In addition, the structure of the benzodiazepine was confirmed to be the diimino molecule and not the enamine by X-ray crystallographic analysis of the benzodiazepine 4b. The methodology is suitable for the operation in combi-chem mode to generate libraries of a diverse array of benzodiazepines. The methodology has been successful in achieving the twin green chemistry objectives of a solvent and ligand free operation and the use of water as a non-hazardous, inexpensive and readily available solvent in the sequential reaction steps performed in situ, thus combining the features of both economic and environmental advantages.

Organotin-oxometalate coordination polymer catalyzed oxyfunctionalization of monoterpenes - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Keywords: Heck reaction; kinetics; Palladacycle

Photo-stabilization of EPDM-clay nanocomposites: effect of antioxidant on the preparation and durability - Lonkar, Sunil P.; Kumar, A. Pratheep; Singh, Raj Pal (Polymers for Advanced Technologies, 2007)
The present study is to examine the photo-stabilization effect of an antioxidant on the photo-oxidation of ethylene-propylene-diene monomer (EPDM)-clay nanocomposites. During the preparation of EPDM-clay nanocomposites via melt processing antioxidants are usually incorporated along with clay, which allows phenolic antioxidant molecules to get adsorbed onto acidic clay platelets and their interaction with metallic impurities reduces the stabilizing efficiency of the antioxidant. The nanocomposites were obtained by solution dispersion followed by melt compounding of EPDM and organophilic montmorillonite (OMMT). The samples were characterized by conventional tools such as X-ray diffraction (XRD), Fourier Transform Infra Red (FT-IR) spectroscopy, and thermo-gravimetric analysis (TGA). It was found, upon photo-irradiation (lambda > 290 nm) studies by following the changes in functional groups and surface morphology, that photo-degradation was lowered by the antioxidant and the efficiency of the antioxidant could be improved by initial incorporation of antioxidant in the EPDM matrix. In EPDM-clay nanocomposites, a stabilizing activity of the antioxidant was observed above some threshold concentration of the antioxidant. The relationship between the nanoclay reinforcement and stabilizing efficiency in terms of photo-oxidation and surface morphology for their applicability are discussed. The methodology adopted for this study is also justified through our observation. Copyright (C) 2007 John Wiley & Sons, Ltd.
International Conference on Frontier in Polymer Science and Technology, Calcutta, INDIA, FEB 10-12, 2006
Keywords: ethylene-propylene-diene monomer; nanocomposites photo-degradation antioxidant and stabilization

Selective oxidation of anthracene using inorganic-organic hybrid materials based on molybdovanadophosphoric acids - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
{Inorganic-organic hybrid materials were synthesized by immobilization of molybdovanadophosphoric acids onto mesoporous silicas, such as MCM-41, MCM-48, and SBA-15, through an organic linker. 12-Molybdovanadophosphoric acids of the general formula H3+xPMO12-xVxO40 (x = 0-3).nH(2)O, such as H-4[
Keywords: EPDM; Photostabilization; polymeric HALS

Simulation of viscoelastic flows of polymer solutions in abrupt contractions using an arbitrary lagrangian eulerian (ALE) based finite element method - Ganvir, Vivek; Lele, Ashish K.; Thaokar, Rochish; Gautham, Basavarsu P. (Journal of Non-Newtonian Fluid Mechanics, 2007)
We present a method for simulation of viscoelastic flows using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation. The ALE technique provides advantages of both Lagrangian and Eulerian frameworks by allowing the computational mesh to move in an arbitrary manner, independent of the material motion. In the present method, a fractional step ALE technique is employed in which the Lagrangian phase of material motion and convection arising out of mesh motion are decoupled. In the first step the relevant flow and constitutive equations are solved in Lagrangian framework. The simpler representation of polymer constitutive equations in a Lagrangian framework avoids the difficulties associated with convective terms thereby resulting in a robust numerical formulation. In the second step the mesh is moved in ALE mode and the associated convection of the stress is performed using a Godunov type scheme. This ALE technique is easy to implement and can accurately simulate the complex viscoelastic behaviour of transient polymer flow through complex geometries. In the present study, steady flows through abrupt contractions of planar and axisymmetric geometries are studied by performing transient flow simulations until steady state is achieved. The proposed method is validated with previously published numerical and experimental studies for polymer solutions obeying the Oldroyd B and Phan Thien Tanner (PTT) models. The simulated corner and lip vortex enhancement mechanism and flow behavior are in good agreement with experimentally obtained flow visualization photographs. The strength of the proposed method lies in its ability to simulate free surface flows such as swell. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: abrupt contraction; Arbitrary Lagrangian Eulerian; finite element; simulations

Synthesis of La0.7Sr0.3MnO3 at 800 degrees C using citrate gel method - Ravi, V.; Kulkarni, S. D.; Samuel, V.; Kale, Sangeeta N.; Mona, J.; Rajgopal, R.; Daundkar, A.; Lahoti, P. S.; Joshi, Rakesh S. (Ceramics International, 2007)
Manganite systems have been of considerable interest in the recent past due to their potential to operate in wide property range and also to serve as effective magnetic sensing and storing devices when synthesized using stringent conditions. We report a novel citrate gel method, in which La0.7Sr0.3MnO3 system has been synthesized at temperature 800 degrees C (LSMO800) with the synthesis duration is 6 h. The results have been compared with the sample synthesized at 1050 degrees C (LSMO1050). The synthesized bulk polycrystalline sample shows single-phase nature with the increase in particle size from similar to 50 nm to 300 nm with the increase in the sintering temperature. The magnetization data for LSMO800 shows well-defined hysteresis with saturation magnetization at around 1800 Oe and Curie temperature at 360 K, which is slightly lower than that of LSMO1050, which is 375 K. The results can be well attributed to the grain boundary effects. (C) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Citrate gel method; CMR; Oxides

Titania nanoparticles synthesis in mesoporous molecular sieve MCM-41 - Lihitkar, N. B.; Abyaneh, Majid Kazemian; Samuel, V.; Pasricha, R.; Gosavi, S. W.; Kulkarni, S. K. (Journal of Colloid and Interface Science, 2007)
Nanocrystalline titanium oxide (TiO2) is one of the most useful oxide material, because of its widespread applications in photocatalysis, solar energy conversion, sensors and optoelectronics. The control of particle size and monodispersity of TiO2 nanoparticles is a challenging task. The use of MCM-41, an inorganic template of uniform pore size (2-10 nm), can overcome this difficulty and produce stable nanoparticles of uniform size and shape. Here, we demonstrate the synthesis of titania nanoparticles inside the pores of silica based MCM-41 forming a TiO2/Si-MCM composite. Composites are formed in the alcoholic medium by incipient wetness impregnation method. Titania particles of average 3 nm size are obtained. Effect of silica and titania precursors on the quality of nanoparticles has been investigated. The characterization of titania-MCM-41 composites has been carried out using a variety of techniques like UV-vis absorption spectroscopy, X-ray diffraction, FT-IR spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy and photoluminescence spectroscopy. It has been found that the titania particles are co-ordinated with Si-MCM by Si-O-Ti covalent bond. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: incipient wetness impregnation; Mesoporous material; template; titania

Tungstophosphoric acid supported over zirconia in mesoporous channels of MCM-41 as catalyst in veratrole acetylation - Sawant, Dhanashri P.; Vinu, A.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Tungstophosphoric acid (TPA) over zirconia dispersed uniformly in mesoporous silica (MS) channels of MCM-41 and MCM-48 were synthesized and tested for their catalytic activity in veratrole acetylation. Catalysts with different TPA loadings (5-50 wt.%) on 22.4 wt.%ZrO2/MCM-41 and 15 wt.%TPA on different zirconia loadings (10-70 wt.%)/MCM-41 were prepared and calcined at 1123 K. The physico-chemical characterization of the supported catalysts was done by powder X-ray diffraction (XRD), surface area measurement (BET), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transformed-infrared (FT-IR) spectroscopy, UV-vis diffuse reflectance spectra, Temperature programmed desorption (TPD) of ammonia, FT-IR pyridine adsorption and (31) P cross polarization-magic angle spinning (CP-MAS) NMR spectroscopy. The mesoporous silica supports play an important role in stabilizing catalytically active TPA along with tetragonal phase of zirconia. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/MCM-41 calcined at 1123 K was found to have highest acidity and at least four times more active than neat 15 wt.%TPA/ZrO2 in veratrole acetylation to acetoveratrone by acetic anhydride. Reaction conditions were evaluated with 15 wt.%TPA/22.4 wt:%ZrO2/MCM-41 calcined at 1123 K to get higher conversion of acetic anhydride to acetoveratrone. The reaction was found to be heterogeneously catalyzed and no contribution from homogeneous (leached) TPA into the medium under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acetoveratrone; acetylation; MCM-41; TPA/ZrO2; veratrole

Unprecedented two-dimensional polymeric [Zn(OOC-C6H4-COO)(2)](2_)(n)[+H3N-(CH2)(3)-NH(3])(+)n system bearing one-dimensional chain of zinc(II) bis(phthalate) dianions held by propane-1,3-diammonium cations: crystal structure, thermal and fluorescent pr - Padmanabhan, A.; Joseph, K. C.; Puranik, Vedavati G.; Huang, Xiaoying; Li, Jing (Solid State Sciences, 2007)
A novel zinc(II) phthalate compound, [Zn{C6H4(COO)(2)}(2)](n)(2-)[NH3-(CH2)(3)-NH3](n)(2+), 1 Which contains four different phthalate moieties coordinated to the Zn(II) ion through one each of their carboxyl ate moieties in a eta(1)-form and each phthalate moiety acting as a bridging unit with an overall tetrahedral geometry around the metal ion has been prepared and structurally characterized. The structure is unique in the sense that the dianionic moieties [Zn{C6H4(COO)(2)}(2)](2-) form an infinite one-dimensional network composed of 14-membered cyclic units interconnected in a way that they are disposed alternatively in almost perpendicular planes. The dicationic [NH3-(CH2)(3)-NH3](2+) units are seen to hold these one-dimensional chains by strong coulombic and hydrogen bond interaction, resulting in an infinite two-dimensional layered structure of 1. The compound is thermally stable up to 250 degrees C. Above this temperature it loses one equivalent of phthalate moiety along with the diammonium unit to yield Zn(II) phthalate. The thermodynamic and kinetic parameters associated with this process could be evaluated using Coats-Redfern equation which shows the activation energy Ea for the process as 305.0 kJ mol(-1), the frequency factor A as 1.49 x 10(11) s(-1) and the entropy change Delta S as -35.90 JK(-1) mol(-1). Fluorescent emission properties of 1 was studied by exciting the compound at 380 nm and also at 322 nm which were found to be the two lambda(max) corresponding to absorptions of the molecule. Interestingly, the compound gave same type of emission spectra showing a maximum around 444 nm on exciting at these two different wavelengths, indicating that the molecule comes to the first excited state from the higher excited state by a fast non-radiative process before it exhibits singlet emission to come to the ground state. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1; 3-diammonium; cyclic chain; fluorescent emission; layered structure; propane; zinc(II) bis(phthalate) dianion; zinc-phthatate

Anomalous microwave heating effects in Ce-doped La(0.7)Sr(0.3)MnO(3): possible role of grain boundary capacitative effects across cerium solubility limit - Kale, Sangeeta N.; Mona, J.; Lofland, S. E.; Kulkarni, S. D.; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
Ce-doped manganite bulk nanocompacts [La(0.7-x)Ce(x)Sr(0.3)MnO(3) (0 < x < 0.1)] are studied for their microwave heating properties at 2.45 GHz. The heating effect is found to be nonmonotonic as a function of cerium concentration, and anomalously large heating (burning) is observed for a small concentration window near x=0.03. The x-ray diffraction studies show signatures of CeO(2) phase in x>0.03 samples. The various characterizations collectively point to the key role of the developing grain boundary CeO(2) layer which leads to highest capacitative intergrain-coupling and related charging-discharging effects when it is thinnest near the apparent Ce solubility limit of x similar to 0.03. (c) 2008 American Institute of Physics.

Blob-spring model for the dynamics of ring polymer in obstacle environment - Lele, Ashish K.; Iyer, Balaji V. S.; Juvekar, Vinay A. (XVTH International Congress on Rheology - the Society of Rheology 80th Annual Meeting, Pts 1 and 2, 2008)
The dynamical behavior of cyclic macromolecules in a fixed obstacle (FO) environment is very different than the behavior of linear chains in the same topological environment; while the latter relax by a snake-like reptational motion from their chain ends(1) the former can relax only by contour length fluctuations since they are endless.(2) Duke, Obukhov and Rubinstein proposed a scaling model (the DOR model) to interpret the dynamical scaling exponents shown by Monte Carlo simulations of rings in a FO environment.(2) We present a model (blob-spring model) to describe the dynamics of flexible and non-concatenated ring polymer in FO environment based on a theoretical formulation developed for the dynamics of an unentangled fractal polymer.(3) We argue that the perpetual evolution of ring perimeter by the motion of contour segments results in an extra frictional load. Our model predicts self-similar dynamics with scaling exponents for the molecular weight dependence of diffusion coefficient and relaxation times that are in agreement with the scaling model proposed by Obukhov et al.(2).
15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, Monterey, CA, AUG 03-08, 2008
Keywords: fractal polymer dynamics; linear viscoelasticity; ring polymer dynamics

Chemical inhomogeneity and mixed-state ferromagnetism in diluted magnetic semiconductor Co : TiO2 - Ogale, Satishchandra B.; Kundaliya, Darshan; Mehraeen, Shareghe; Fu, Lian-feng; Zhang, Shixiong; Lussier, Alexandre; Dvorak, Joe; Browning, Nigel D.; Idzerda, Yves; Venkatesan, Thirumalai (Chemistry of Materials, 2008)
Diluted magnetic semiconductors (DMS) are among the most intensely investigated materials in recent times in view of their great application potential. Yet, they are also the most controversial because of the possibility of extrinsic effects attributable to dopant solubility and clustering, point defects, incorporation of unintentional impurities, etc. This has highlighted the central role of materials chemistry in rendering a specific microstate and property response. In this work, we provide a combined window of high-resolution scanning transmission electron microscopy and electron energy-loss spectrometry, X-ray absorption (XAS)/X-ray magnetic circular dichroism (XMCD), and magnetization measurements on epitaxial rutile CoxTi1-xO2 (x = 0-0.06) system (the first discovered oxide-DMS, which continues to be controversial) grown at low temperature (400 degrees C) under different ambient atmospheres. The study brings out a mixed-state scenario of ferromagnetism involving intrinsic DMS (uniform dopant distribution at low dopant concentration) and coupled cluster magnetism, involving cobalt associations within the matrix at higher concentrations. We also show that by matrix valence control during growth, it is possible to realize a uniform embedded cluster state and the related coupled cluster magnetism.

Chiral Mn(III) salen complex immobilized onto ionic liquid modified mesoporous silica for oxidative kinetic resolution of secondary alcohols - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Tetrahedron Letters, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a chiral Mn(III) salen complex onto ionic liquid modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high enantioselectivity and activity in the oxidative kinetic resolution of secondary alcohols, and could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mesoporous silica SBA-15; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Convenient access to 1, 3,4-trisubstituted pyrazoles carrying 5-nitrothiophene moiety via 1,3-dipolar cycloaddition of sydnones with acetylenic ketones and their antimicrobial evaluation - Rai, N. Satheesha; Kalluraya, Balakrishna; Lingappa, B.; Shenoy, Shaliny; Puranik, Vedavati G. (European Journal of Medicinal Chemistry, 2008)
Novel 1-aryl-3-(5-nitro-2-thienyl)-4-aroyl-pyrazoles 7 have been synthesized by the 1,3-dipolar cycloaddition of 3-arylsydnones 3 with 1-aryl-3-(5-nitro-2-thienyl)-2-propyn- 1-ones 6. The newly synthesized compounds were well characterized by elemental analysis, IR, (1)H NMR and mass spectral studies. They were also screened for their antibacterial and antifungal activities against a variety of microorganisms and the results of such studies have been discussed in this article. (c) 2007 Elsevier Masson SAS. All fights reserved.
Keywords: 1; 3-dipolar cycloaddition; 5-nitrothiophene; acetylenic ketone; Antibacterial; antifungal; Pyrazole; sydnone

Durability of crosslinked polydimethylsyloxanes: the case of composite insulators - Delor-Jestin, Florence; Tomer, Namrata S.; Singh, Raj Pal; Lacoste, Jacques (Science and Technology of Advanced Materials, 2008)
Most applications of silicones are linked to their hydrophobic properties and (or) their high resistance to ageing (e. g. thermal ageing and photoageing). However, when placed in extreme environments, these materials can fail as in the case of epoxy/fiber glass composite powerlines insulators, where crosslinked polymethylsyloxanes (PDMSs) are used as the protective envelope (housing) of the insulator. We report on the behavior of both pure/noncrosslinked PDMSs and typical formulations used in industrial insulators, i.e. containing peroxide crosslinked PDMS, alumina trioxide hydrated (ATH) and silica. Special attention is paid on both (i) the sources of potential degradation and (ii) the best analytical methods that can be applied to the study of very complex formulations. (i) Aside from conventional types of ageing such as photo-ageing and thermal, hydrolytic, and service life ageings, treatments with acidic vapors, plasma and ozone possibly generating species from the reaction of a high electric field with air were also performed, which allowed to accelerate electrical and out-door ageings and to obtain differently aged materials. (ii) Aside from conventional analytical methods of polymer degradation such as FTIR/ATR spectroscopy and SEC, TG, hardness measurements, more specific methods like photo/DSC, TG/IR, thermoporosimetry, resistivity and density measurements were also performed to characterize the chemical and physical evolutions of polymer materials. In particular, it was found that treatment with nitric acid vapor has detrimental effects on the properties of both fire retardants (e. g. ATH) and PDMSs, affecting the hardness and resistivity of the formulated material.
International Conference on Magneto-Science, Hiroshima, JAPAN, NOV, 2007
Keywords: composite insulators; durability; PDMS; post-crosslinking; silicone

Effective arsenic removal using polyacrylonitrile-based ultrafiltration (UF) membrane - Lohokare, Harshada R.; Muthu, M. R.; Agarwal, Gopal P.; Kharul, Ulhas K. (Journal of Membrane Science, 2008)
Applicability of polyacrylonitrile (PAN)-based negatively charged ultrafiltration (UF) membrane for effective arsenic removal has been demonstrated, to our knowledge, for the first time. The hydrolysis of PAN-based UF membrane surface by NaOH leading to the formation of carboxylate (-COO-) groups and reduction in initial pore size rendered As-V rejection capability by Donnan exclusion principle. A lowering in pore size was indicated by the reduction in water flux and elevation in rejection of protein and polyethylene glycol (PEG). NaOH treatment leading to formation of carboxylate group on the membrane surface was indicated by FTIR-ATR, while contact angle measurement indicated increased hydrophilicity. This treatment rendered membrane surface smoothening as confirmed by SEM and AFM analyses. The molecular weight cut off after the NaOH treatment was found to be similar to 6 kDa. The rejection of pentavalent arsenic (As-V) by these surface modified membranes was studied with different feed concentration, cross-flow velocity, pressure, temperature and pH. Experiments with 50 ppb As-V in feed showed that arsenic rejection was close to 100% and remained constant up to 6 h. Feed sample concentration of 1000 ppb and 50 ppm of As-V showed >95% rejection at pH 7 and room temperature, but for 1000 ppm feed concentration, the rejection was 40-65%. For concentrations <= 50 ppm of arsenic in the feed, the rejection coefficient was not dependent on cross-flow velocity or transmembrame pressure. The rejection for 1000 ppm. concentration of As-V varied from 40 to 65% with variation in the cross-flow velocity and transmembrane pressure as the concentration polarization was important. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; concentration polarization; cross-flow velocity; Polyacrylonitrile; surface modification; Ultrafiltration

Efficient synthesis of 1,8-dioxo-octahydro-xanthene derivatives promoted by a room temperature ionic liquid at ambient conditions under ultrasound irradiation - Venkatesan, K.; Pujari, Suresh S.; Lahoti, Rajgopal J.; Srinivasan, K. V. (Ultrasonics Sonochemistry, 2008)
The condensation reaction involving an aldehyde and diketone was efficiently promoted by the Ionic liquid, [Hbim]BF(4) (IL) as a reaction medium with methanol as co-solvent at ambient temperature under ultrasonic irradiation to afford the corresponding 1,8-dioxo-octahydroxantliene (xanthene) derivatives in excellent yields. The advantages of this method include among others the use of a recyclable, non-volatile ionic liquid, which promotes this protocol under ambient temperature without the requirement of ally added catalyst. The reaction times and yields are compared with p-TSA catalyzed synthesis of xanthenes under thermal conditions, which is also reported for the first time under our reaction conditions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: aldehydes; ambient conditions; Bronsted acidity; dimedone; Ionic liquid; Ultrasound; Xanthenes

Enantioselective hydrogenation of olefins by chiral iridium phosphorothioite complex covalently anchored on mesoporous silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
Chiral monodentate phosphorous-based ligands have proven effective for the enantioselective hydrogenation of olefins. Binol-derived monodentate phosphorothioite (PS) ligand was synthesized from binol and thiopropyltriethoxysilane, and its iridium complex was covalently anchored to mesoporous silica supports like SBA-15, MCM-41, and MCM-48. These catalysts were characterized by different physicochemical techniques and assessed for their catalytic performances in the heterogeneous asymmetric hydrogenation of itaconic acid and its derivatives. It was found that the catalytic activities and enantioselectivities of the heterogenized iridium complex (IrPSSBA-15) in the hydrogenation reactions were comparable to its homogeneous analogue. Binol-derived monodentate phosphorothioite ligand in heterogeneously anchored form (iridium complex) is a more effective catalyst than the reported monodentate phosphorous ligand systems in the hydrogenation reactions, possibly due to the changes in electronic properties around the iridium metal center. The effects of substrate-to-catalyst molar ratio, solvents, and temperature on substrate conversions and enantioselectivities, of the products were investigated in hydrogenation reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: binol; Enantioselective hydrogenation; Immobilization; iridium complex; itaconic acid; Mesoporous silica SBA-15; monodentate ligand; phosphorothioite ligand

Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds

Enhanced field emission from hexagonal rhodium nanostructures - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Late, Dattatray J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2008)
Shape selective synthesis of nanostructured Rh hexagons has been demonstrated with the help of a modified chemical vapor deposition using rhodium acetate. An ultralow threshold field of 0.72 V/mu m is observed to generate a field emission current density of 4 x 10(-3) mu A/cm(2). The high enhancement factor (9325) indicates that the origin of electron emission is from nanostructured features. The smaller size of emitting area, excellent current density, and stability over a period of more than 3 h are promising characteristics for the development of electron sources. (C) 2008 American Institute of Physics.

Furfural: hemicellulose/xylosederived biochemical - Mamman, Ajit Singh; Lee, Jong-Min; Kim, Yeong-Cheol; Hwang, In Taek; Park, No-Joong; Hwang, Young Kyu; Chang, Jong-San; Hwang, Jin-Soo (Biofuels Bioproducts & Biorefining-Biofpr, 2008)
Hemicellulose, the second, most common polysaccharide in nature constitutes approximately 20-35% of lignocellulosic biomass. Effective utilization of biomass, hitherto underutilized, is gaining tremendous importance for the production of energy, fuels, and chemicals. Amongst the vast array of chemicals derived from lignocellulosics, furfural is the key chemical that finds wide applications in oil refining, plastics, pharmaceutical and agrochemical industries. There is no synthetic route for the production of furfural. A few conventional technologies currently in practice for its separation and subsequent isolation are appropriately reviewed. Major disadvantages associated with processes currently used for the production of furfural based on acid-catalyzed hydrolysis have been discussed. A need to develop a process which is devoid of all the shortcomings associated with conventional process is emphasized. Several important aspects of chemistry underlying the acid hydrolysis of xylose are discussed. The importance of myriad pre-treatment steps involved to surmount the physical and chemical barriers and to liberate xylose from the confines of acid-resistant layer of lignin has been emphasized. New developments in the production of furfural from cyclodehydration of xylose using solid acid catalysts in the recent past have been reviewed appropriately in present communication. Finally, the production of furfural and furfuryl alcohol, their domestic market and export in China deserve some coverage and therefore have appropriately been discussed as well. (c) 2008 Society of Chemical Industry and John Wiley & Sons, Ltd
Keywords: acid hydrolysis; cyclodehydration; furfural; Hemicellulose; pre-treatment of lignocellulosics; Xylose

Gelation of regenerated fibroin solution - Nagarkara, Shailesh; Lele, Ashish K.; Chassenieux, Christophe; Nicolai, Taco; Durand, Dominique (15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, 2008)
Silk fibroin is a high molecular weight multiblock ampiphillic protein known for its ability to form high strength fibers. It is also biocompatible; silk sutures have been traditionally used for many centuries. Recently, there has been much interest in making silk hydrogels for applications ranging from tissue engineering to controlled delivery. Fibroin gels can be formed from aqueous solutions by changing one or more state variables such as pH, temperature and ionic strength. In this work we present our investigations on the gelation of aqueous fibroin solutions derived from Bombyx Mori silk using light scattering, confocal microscopy and rheological techniques.
15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, Monterey, CA, AUG 03-08, 2008
Keywords: dynamic light scattering; Rheology; silk fibroin gel

Heteropoly acid-based supported ionic liquid-phase catalyst for the selective oxidation of alcohols - Bordoloi, Ankur; Sahoo, Suman; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a heteropolyacid, molybdovanadophosphoric acid, onto ionic liquid-modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high activity in the aerobic oxidation of primary and secondary alcohols to aldehydes and ketones, respectively. No overoxidation of the primary alcohols to carboxylic acids was observed. Secondary alcohols were chemoselectively oxidized to ketones in the presence of primary alcohol, hetero atom, and allyl groups. This catalyst could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Air as an oxidant; Mesoporous silica SBA-15; Molybdovanadophosphoric acid; Selective oxidation; Supported ionic liquid

Hexavalent chromate reduction by immobilized streptomyces griseus - Poopal, Ashwini C.; Laxman, Ryali Seeta (Biotechnology Letters, 2008)
Hexavalent chromium, which is a mutagen and carcinogen, was efficiently reduced by Streptomyces griseus. This activity was associated with the cell. Cr6+ reduction by free as well as immobilized cells was studied: cells in PVA- alginate had the highest ( 100%) Cr6+ removal efficiency in 24 h with reduction rates similar to free cells. Immobilized cells completely reduced 25 mg Cr6+ l(-1) in 24 h. PVA- alginate immobilized cells could be reused four times to completely reduce 25 mg Cr6+ l(-1) in 24 h each time. Chromate in a simulated effluent containing Cu2+, Mg2+, Mn2+ and Zn2+ was completely reduced by PVA- alginate immobilized cells within 9 h.
Keywords: Chromate reduction; Immobilized cells; polyvinyl alcohol; Streptomyces griseus

Improved procedure for the synthesis of (2R)-N-propenoylbornane-2,10-sultam - Laha, Joydev K. (Organic Preparations and Procedures International, 2008)

Inorganic-organic hybrid materials based on functionalized silica and carbon: a comprehensive understanding toward the structural property and catalytic activity difference over mesoporous silica and carbon supports - Bordoloi, Ankur; Mathew, Nevin T.; Lefebvre, F.; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2008)
Inorganic-organic hybrid materials based on functionalized silica and carbon were synthesized by anchoring molybdovanadophosphoric acid (H-5[PMo10V2O40]center dot 32.5H(2)O) onto amine-functionalized SBA-15, ethane-bridged SBA-15 and mesoporous carbon, respectively. Small angle X-ray diffraction, N-2 sorption analysis, HRTEM, SEM, IFT-IR, CP-MAS NMR were used to diagnose the mesoporous structure of inorganic-organic hybrid materials. The structural integrity of molybdovanadophosphoric acid has been found to be retained after immobilization over mesoporous materials. These inorganic-organic hybrid materials were tested in the environmentally friendly oxidation of 2-methylnaphthalene (2MN) with 30%, aqueous hydrogen peroxide. Molybdovanadophosphoric acid containing mesoporous organosilica hybrid material (ethane-bridged SBA-15) exhibited higher catalytic activities in the oxidation of 2MN to give a clean product 2-methy-1,4-naphthoquinone (menadione vitamin K3 precursor), because of the improved hydrophobicity of the material. The correlation between structural properties and catalytic activities of these hybrid materials has been well addressed in our present studies. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: 2-Methylnaphthalene; inorganic-organic hybrid materials; mesoporous carbon; mesoporous organosilica; Oxidation

Local electronic structure and magnetic properties of LaMn(0.5)Co(0.5)O(3) studied by x-ray absorption and magnetic circular dichroism spectroscopy - Burnus, T.; Hu, Z.; Hsieh, H. H.; Joly, V. L. Joseph; Joy, Pattayil Alias; Haverkort, M. W.; Wu, Hua; Tanaka, A.; Lin, H. -J.; Chen, C. T.; Tjeng, L. H. (Physical Review B, 2008)
We have studied the local electronic structure of LaMn(0.5)Co(0.5)O(3) using soft-x-ray absorption spectroscopy at the Co-L(3,2) and Mn-L(3,2) edges. We found a high-spin Co(2+)-Mn(4+) valence state for samples with the optimal Curie temperature. We discovered that samples with lower Curie temperatures contain low-spin nonmagnetic Co(3+) ions. Using soft-x-ray magnetic circular dichroism, we established that the Co(2+) and Mn(4+) ions are ferromagnetically aligned. We also revealed that the Co(2+) ions have a large orbital moment: morb/mspin approximate to 0.47. Together with model calculations, this suggests the presence of a large magnetocrystalline anisotropy in the material and predicts a nontrivial temperature dependence for the magnetic susceptibility.

MCM-41-supported organometallic-derived nanopalladium as a selective hydrogenation catalyst - Maity, Niladri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Physical Chemistry C, 2008)
Palladium nanocatalysts have been prepared by anchoring (eta(3)-C(3)H(5))(2)Pd(2)Cl(2) onto dian-tine-functionalized MCM-41 supports followed by reaction with hydrogen under catalytic conditions. The catalyst precursor and used catalyst have been studied by solid-state NMR ((13)C, (29)Si), XPS, and TEM. The organometallic-derived catalyst exhibits the best performance (activity and selectivity) to date toward the selective hydrogenation of industrially relevant o- and m-chloronitrobenzene to the corresponding chloroaniline derivatives and is distinctly superior to 5% Pd/C. Grazing angle XPS studies reveal that conversion of the tethered molecular species to the nanoparticles of palladium produces a core-shell nanostructure.

MCM-41-supported ruthenium carbonyl cluster-derived catalysts for asymmetric hydrogenation reactions - Indra, Arindam; Basu, Susmit; Kulkarni, Dhanashree G.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2008)
{The anionic ruthenium carbonyl cluster [Ru-4(mu-H)(3)(CO)(12)](-) has been ion-paired with (3-chloropropyl)-trimethoxysilyl-cinchonidium or sparteinium groups chemically bound to the surfaces of MCM-41 [(MCM-41-)(-O)(3)SiCH2CH2CH2NR3+Cl-
Keywords: asymmetric catalysis; functionalized MCM-41; hydrogenation catalysts; nanocatalyst; ruthenium carbonyl cluster

Microwave assisted low temperature rapid synthesis of manganite system using La0.67Ce0.03Sr0.3MnO3 mini-cavity furnace - Kale, Sangeeta N.; Rajagopal, Rajashree; Mona, J.; Londhe, D. P.; Joshi, Rakesh S.; Jagadale, Tushar C.; Satyanarayana, C.; Ravi, V. (Materials Letters, 2008)
Amorphous La0.7Sr0.3MnO3 (LSMO) and La0.7Ca0.3MnO3 (LCMO) precursor powders synthesized by the citrate gel method at 673 K, have been found to crystallize by microwave irradiation in just 60 s using La0.67Ce0.03Sr0.3MnO3 (Ce-LSMO) as couplant. This is the lowest temperature treatment and synthesis time so far reported in literature for the fort-nation of manganite systems. Using ceramic route, the same amorphous samples crystallize on heat treatment only at temperatures greater than 1000 K. The microwave heating through this method is novel and has tremendous potential for accelerating the evolution of the product phase in very shorter durations, with just low temperature processing of the precursors, which cannot be realized in normal process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; LSMO; Manganites; Microwave; Oxides

Molecular genetic mapping of quantitative trait loci associated with loaf volume in hexaploid wheat (Triticum aestivum) - Elangovan, M.; Rai, R.; Dholakia, Bhushan B.; Lagu, Meena D.; Tiwari, R.; Gupta, R. K.; Rao, V. S.; Roeder, M. S.; Gupta, V. S. (Journal of Cereal Science, 2008)
Major efforts in wheat research are being made to improve the yield and quality of wheat. Loaf volume (Lv) is the main quality parameter deciding the bread making potential of wheat. To genetically dissect quantitative trait loci (QTLs) for Lv, a Recombinant Inbred Line (RIL) population (F-8) was developed from a cross between two Indian wheat varieties ``H 1977'' and ``HD 2329''. A total of 914 SSR and 100 ISSR primers were used for molecular analysis and the genetic map comprising 19 chromosomes was constructed with 202 SSR markers and 2 HMW glutenin subunit loci: Glu-B1 and Glu-B1. The phenotypic data were collected from six environments including three different agro-climatic zones for 2 consecutive years. Dissection of Lv through AMMI model revealed significant G x E variance for the trait. QTL analysis was performed using composite interval mapping. A total of 30 QTLs for Lv were detected and significant QTLs were identified on 6B and 6D chromosomes; 1B, 1D, 2A, 3A, 513 and 5D also contributed genetically to Lv. Association between 6B and 6D QTLs and variable expression of gliadins on group 6 chromosomes were discussed. QTLs detected in this study were compared with other QTL analysis in wheat. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: breadmaking; loaf volume; QTL; SSR; wheat quality

Multiple weak supramolecular interactions stabilize a surprisingly twisted As2L3 assembly - Pitt, Melanie A.; Zakharov, Lev N.; Vanka, Kumar; Thompson, Ward H.; Laird, Brian B.; Johnson, Darren W. (Chemical Communications, 2008)
A combined crystallographic, DFT and NMR spectroscopic study of a flexible As(2)(3) assembly reveals temperature dependent conformational behavior in solution and a highly asymmetric structure stabilized by As-pi and edge-to-face aromatic interactions.

Non-phosgene route for the synthesis of methyl phenyl carbamate using ordered AISBA-15 catalyst - Lucas, Nishita; Amrute, Amol P.; Palraj, K.; Shanbhag, G. V.; Vinu, Ajayan; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
Methyl phenyl carbamate (MPC) has been synthesized Under liquid phase conditions from dimethyl carbonate and aniline by using mesoporous AISBA-15 catalyst. The catalyst with different Si/Al ratio was synthesized by isomorphous Substitution of aluminium into the framework of siliceous SBA-15. The structural integrity of the catalyst system was diagnosed with the help of various characterization techniques Such as X-ray diffraction, Surface analysis, and the acidity measurement has been done by TPD using ammonia as probe molecule. AISBA-15 (Si/Al = 10) exhibited highest catalytic activity in the synthesis of MPC under the reaction Conditions Studied. The effect of parameters Such as molar ratio of reactants, catalyst concentration. reaction temperature and time on the conversion of aniline was investigated. The results demonstrated that an aniline conversion of 99% and MPC selectivity of 71% were achieved when the reaction was carried out at 100 C, DMC to aniline mole ratio of 10 with 5% of catalyst (wt% of total reaction mixture) for 3 h. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: amines; Dimethyl carbonate; Mesoporous AISBA-15; Methoxycarbonylation; Methyl phenyl carbamate

Optimal xylanase production using Penicilium janthinellum NCIM 1169: a model based approach - Meshram, Mukesh; Kulkarni, Abhijit; Jayaraman, Valadi K.; Kulkarni, B. D.; Lele, S. S. (Biochemical Engineering Journal, 2008)
Xylanases are an industrially important class of hydrolytic enzymes that degrade xylans. Production of xylanase from a fungal culture by submerged fermentation and optimization of the operating conditions for maximum activity are the two aims of the present study. Penicillium janthinellum NCIM 1169 with Mandels-Weber medium, sugarcane bagassse (40#) as a carbon source and beef extract as a nitrogen source were used in the experiments. We did 41 experiments to see the effect of variations in carbon, nitrogen source, pH, and inoculum on xylanase activity. This data was then used to build an input/output model using multiple linear regression, back propagation neural network and lazy learning algorithm. It was found that lazy learning model correlated well in mapping input/output data. This model was then utilized as an objective function in genetic algorithm to find the optimal combination of the operating conditions to get the maximum xylanase activity. It was observed that with carbon source, 1.63%, nitrogen source, 0.16%, pH, 4.1, and inoculum, 5.5%, maximum xylanase activity of 28.98 +/- 1.73 U/ml was achieved. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Artificial intelligence; Enzyme activity; Fermentation; Modeling; Optimization; Xylanase

Peculiarities of the adsorption kinetics of mixed convex plus concave contour objects - Shelke, Pradip B.; Ogale, S. B.; Khandkar, M. D.; Limaye, A. V. (Physical Review E, 2008)
Random sequential adsorption of mixed convex plus concave contour (MC) objects exhibits some distinctly different peculiar characteristics than the cases of purely convex objects. Though the substrate coverage approaches the jamming limit with time t as t(-p), same as that for convex objects, the law p similar to 1/d(f), valid for convex objects with d(f) degrees of freedom, does not hold for MC objects. Interestingly, for a fixed number of degrees of freedom, the exponent p changes with the degree of nonconvexity and bears a near perfect correlation with the same.

Photocatalytic activity and characterization of sol-gel-derived Cr(III)-doped TiO(2)-coated active carbon composites - Gambhire, A. B.; Lande, Machhindra K.; Mandale, A. B.; Patil, K. R.; Arbad, B. R. (Philosophical Magazine, 2008)
Cr(III)-doped, TiO(2)-coated active carbon (Cr-TiO(2)/AC) were prepared by a sol-gel method. The effect of supports, including TiO(2) and active carbon (AC), on the molecular structure and photocatalytic activity of chromium oxide for complete decomposition of EDTA has been examined with respect to the content of Cr on the catalyst surface. The photocatalytic activity of the Cr-TiO(2)/AC composites was evaluated in the decomposition of EDTA solution under UV irradiation. The results indicate that Cr-TiO(2)/AC has a higher efficiency in decomposition of EDTA than TiO(2), TiO(2)/AC or active carbon. This was attributed to the different functions of active carbon and chromate species. (1) Nanosize TiO(2) particles on composites were not reunited, possible because active carbon retards transformation of anatase into rutile and decreases the crystallite size. (2) Production of high concentrations of organic compound near Cr-TiO(2). (3) Carbon in active carbon causes some of the TiO(2) to reduce to Ti(3+) ions, which prevents electron-hole pair recombination. (4) Formation of polychromate species, with a stronger redox capability, on the surface of TiO(2)/AC. It was found that the addition of Cr to TiO(2) sol could suppress the grain growth of TiO(2) crystals and increase the hydroxyl content on the surface of TiO(2)/AC. The photocatalytic efficiency and activity of the composites remained good, even after three cycles.
Keywords: EDTA; photoactive; sol-gel; Titanium dioxide; XPS

Potential plasmid-curing agent, 8-epidiosbulbin E acetate, from dioscorea bulbifera L. against multidrug-resistant bacteria - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Puranik, Vedavati G.; Rojatkar, Supada; Dhakephalkar, Prashant K.; Shitole, M. G. (International Journal of Antimicrobial Agents, 2008)
Bioassay-guided fractionation of an aqueous methanolic extract of Dioscorea bulbifera L. bulbs was performed using organic solvents. A novel plasmid-curing compound was identified as 8-epidiosbulbin E acetate (EEA) (norditerpene) on the basis of modern spectroscopic analysis and X-ray crystallography. EEA exhibited broad-spectrum plasmid-curing activity against multidrug-resistant (MDR) bacteria, including vancomycin-resistant enterococci. EEA cured antibiotic resistance plasmids (R-plasmids) from clinical isolates of Enterococcus faecalis, Escherichia coli, Shigella sonnei and Pseudomonas aeruginosa with 12-48% curing efficiency. The reference plasmids of Bacillus subtilis (pUB110), E. coli (RP4), P. aeruginosa (RIP64) and Salmonella typhi (R136) were cured with efficiency ranging from 16% to 64%. EEA-mediated R-plasmid curing decreased the minimal inhibitory concentration of antibiotics against MDR bacteria, thus making antibiotic treatment more effective. The antibiotic resistance pattern revealed that the compound was effective in the reversal of bacterial resistance to various antibiotics. In addition, the compound did not show any cytotoxicity against a broad range of human cancer cell lines, namely MCF-7 (breast cancer), SiHa (cervical cancer) and A431 (epidermal carcinoma), and hence has the potential to be used as a lead compound for drug discovery programmes. (C) 2008 Elsevier B. V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 8-Epidiosbulbin E acetate; Antibiotic resistance; Dioscorea bulbifera; Plasmid curing

RuO(2) doped SnO(2) nanobipyramids on Si (100) as a field emitter - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Thin Solid Films, 2008)
Thin films of RuO(2): SnO(2) nanobipyramids have been grown on silicon (100) flat substrates, and their field emission behavior has been investigated. The field emission experiments have been performed in parallel plate configuration. In this experiment, the onset field for 0. 1 gA/ cm 2 current density has been found to be 0.2 V/mu m. The Fowler-Nordheim plot shows non-linear nature typical that of a semiconductor. The field enhancement factor has been estimated to be 35,600 cm(-1), indicating that the field emission originates from the nanometric features of the emitter. The current stability recorded at a preset value of I tA is observed to be good. Our field emission results on RuO(2): SnO(2) nanobipyramids indicate that, RuO(2): SnO(2) nanobipyramids are a potential candidate for futuristic field emission based devices. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emitter; field enhancement factor; ruthenium oxide; tin oxide

Selective oxidation of ethane over Mo-V-Al-O oxide catalysts: insight to the factors affecting the selectivity of ethylene and acetic acid and structure-activity correlation studies - Sankaranarayanan, T. M.; Ingle, Rohit H.; Gaikwad, T. B.; Lokhande, S. K.; Raja, T.; Devi, R. N.; Ramaswamy, V.; Manikandan, Palanichamy (Catalysis Letters, 2008)
Catalysts of general formula, MoVAlOx were prepared with the initial elemental composition of 1:0.34:0.167 (Mo:V:Al) at a pH value in the range of 1-4. The elemental analysis showed that the final composition of the catalysts is pH dependant. The performance of the catalysts was tested for selective oxidation of ethane to give ethylene and acetic acid. While all of them were active for ethane oxidation with a moderate conversion, the catalyst prepared at pH 2 showed a highest activity with 23% ethane conversion and a combined selectivity of 80.6% to ethylene and acetic acid. The catalyst prepared at pH 4 was least selective to ethylene and acetic acid. Various techniques like powder XRD, SEM, Raman, UV-Vis and EPR were used to characterize the catalysts and to identify the active phases responsible for the selective oxidation of ethane. The powder XRD data showed that the catalysts prepared at pH 1 and 2 contain mainly of MoO3 and MoV2O8 along with traces of Mo4O11. The amount of MoO3 was slightly higher in the catalyst prepared at pH 1. However, the catalyst prepared at pH 3 contains mainly of MoV2O8 with no trace of MoO3. The catalyst prepared at pH 4 showed V2O5 as the major phase along with MoVAlO4 phase. The Raman data corroborated the XRD results. EPR and UV-Vis studies indicated the presence of traces of V-4 in pH 1 and 2 catalysts and significant amount of Mo5+ in all the catalysts. Thus, the high activity and selectivity to ethylene and acetic acid are attributed to the presence of MoV2O8 phase and other reduced species like Mo4O11 phase supported on MoO3. The presence of V and Mo ions in a partially reduced form seems to play a crucial role in the selective oxidation of ethane.
Keywords: Acetic acid; ethane; Ethylene; mixed metal oxide; Selective oxidation

Self-diffusion coefficient of ring polymers in semidilute solution - Iyer, Balaj V. S.; Shanbhag, Sachin; Juvekar, Vinay A.; Lele, Ashish K. (Journal of Polymer Science Part B-Polymer Physics, 2008)
In a topologically constraining environment the size of a flexible nonconcatenated ring polymer (macrocycles) and its dynamics are known to differ from that of linear polymers. Hence, the diffusion coefficient of ring polymers can be expected to be different from linear chains. We present here scaling arguments for the concentration and molecular weight dependence of self-diffusion coefficient of ring polymers in semidilute solutions, and show that contrary to expectations these scaling relations are identical to what is known for linear polymers. At higher concentrations excluded volume interactions arising from possibilities of segmental overlap can become effective for large ring polymers. In this regime the diffusion coefficient of large ring polymers shows a relatively weaker dependence on concentration and molecular weight. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2370-2379, 2008
Keywords: Diffusion; Macrocycles; Monte Carlo simulation

Sol-gel synthesis of MoO(3)/SiO(2) composite for catalytic application in condensation of anisole with paraformaldehyde - Amrute, Amol P.; Bordoloi, Ankur; Lucas, Nishita; Palraj, K.; Halligudi, Shivaraj B. (Catalysis Letters, 2008)
MoO(3)/SiO(2) composite with varying amounts of MoO(3) loading (1-20 wt.%) were prepared by sol-gel method and calcined at 500 C. These catalysts were employed for the liquid phase condensation of anisole with paraformaldehyde. All the catalysts were characterized by N(2) sorption, XRD, and NH(3)-TPD. The activities of synthesized MoO(3)/SiO(2) catalysts were compared with p-toluene sulfonic acid (p-TSA), the most frequently used catalyst for the condensation reactions, and with a supported metal oxide (WO (x) /ZrO(2)). Under the similar reaction conditions, synthesized 10 wt.% MoO(3)/SiO(2) catalyst calcined at 500 C was found to be the most active in the condensation of anisole with paraformaldehyde.
Keywords: 4; 4'-Dimethoxydiphenylmethane; Condensation of anisole; MoO(3)/SiO(2) composites; Paraformaldehyde; Sol-gel synthesis

Structural elucidation of propargylated products of 3-substituted-1,2,4-triazole-5-thiols by NMR techniques - Chaudhary, Preeti M.; Chavan, Sayalee R.; Kavitha, M.; Maybhate, Shailaja P.; Deshpande, Sunita R.; Likhite, Anjali P.; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2008)
Propargylation of 3-substituted-1,2,4-triazole-5-thiols, which predominantly exist as their thione tautomers, was carried out with the view to synthesize different heterocycles and study their biological activity. Three different products namely, a mono S-propargyl and two S,N-dipropargyl regioisomers, arising from N1/N2 substitution, were isolated and characterized. Unambiguous structural elucidation of the regioisomers of S,N-dipropargyl derivatives was achieved by means of (13)C-(1)H HMBC technique. The proportion of the regioisomers was found to vary with the substituent on the 1,2,4-triazole thiols. No product corresponding to N4 substitution was isolated from any of the reactions carried out. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: (1)H NMR; (13)C NMR; (15)N NMR; 1; 2; 4-triazoles; HMBC; NMR; Regioisomers

Structure sensitivity of nano-structured CdS/SBA-15 containing Au and PtCo-catalysts for the photocatalytic splitting of water - Lunawat, Puja S.; Kumar, Rajiv; Gupta, Narendra M. (Catalysis Letters, 2008)
Photocatalysts containing nanocrystallites of cadmium sulphide dispersed in the channels of mesoporous silicate SBA-15 exhibited enhanced activity for visible-light mediated splitting of water, as compared to bulk CdS. Whereas the incorporation of 1 wt.% Pt co-catalyst in CdS/SBA-15 led to a substantial increase in H-2 yield, Au at similar loading resulted in marginally decreased activity. The results indicate that the photocatalytic activity of CdS crystallites is structure sensitive. Similarly, the role of a noble metal may be associated with the particle size dependent micro-structural features, rather than its electronic properties such as the work function or the heat of adsorption of reactant or product molecules.
Keywords: nano-structured cadmium sulphide; Photocatalysis; role of noble metal co-catalyst; Splitting of water; structure sensitivity

Synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Materials Chemistry and Physics, 2008)
In the present investigation the synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial has been reported. The material was synthesized by coprecipitation process combined with surfactant incorporating method. The concentration level of Ce (III) additive was varied systematically from 1 to 11 wt.%. After calcinations at500 degrees C,a high BET surface area of 40 m(2)/g was obtained for 7 wt.% CeO2. The effect of variation of sintering temperature (600-800 degrees C/2h) on the particle size and surface area of a CeO2/SnO2 system was investigated. The material obtained was nanocrystalline, having particle size in the range of 10-16 nm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CeO2:SnO2; Nanomaterials; sensors

Synthesis and characterizations of NiTiO(3) nanoparticles prepared by the sol-gel process - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Mandale, A. B.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Philosophical Magazine Letters, 2008)
Nanocrystalline nickel titanate (NiTiO(3)) composite powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 750 degrees C for 2 h in air. The results revealed that a pure hexagonal phase of NiTiO(3) could be obtained at the low temperature of 750 degrees C. The phase evolution of NiTiO(3) was investigated by X-ray diffraction patterns, Fourier-transform infrared spectroscopy, and X-ray photoelectron spectroscopy. Particle size and morphology were studied by transmission electron microscopy.
Keywords: Nanoparticles; nickel titanate; sol-gel process

Synthesis, characterization and catalytic activity of Sn-SBA-15 mesoporous molecular sieves - Ramaswamy, Veda; Shah, Pallavi; Lazar, Karoly; Ramaswamy, A. V. (Catalysis Surveys from Asia, 2008)
Our recent reports on the synthesis of Sn-incorporated mesoporous SBA-15 materials have been reviewed. The preparation of the samples with different Si/Sn ratios followed two procedures, the first is the post-synthesis modification of SBA-15 by impregnation with Sn chloride or acetate, and the second is the direct method in which Sn chloride was introduced in to Si precursor along with amphiphilic triblock copolymer, while varying the ratio of the synthesis gel. Detailed characterization of the Sn-SBA-15 samples by a variety of techniques shows how the synthesis procedures influence the properties of the samples that reflect on the differences in (a) the structural features, (b) morphology and textural properties, such as the pore characteristics, (c) the possible location of Sn4+ ions in the meso silica structure and their reducibility, (d) the nature of the Sn species and their the coordination sphere and (e) the acid-base characteristics. We developed a possible model for the localization of Sn species in SBA-15 pore structure for different conditions of preparation. This report includes our investigations on the catalytic properties of these Sn-SBA-15 samples in 3 industrially important reactions, viz., trans-esterification of diethyl malonate, synthesis of nopol by Prins condensation of beta-pinene with para-formaldehyde and the epoxidation of norbornene. In each of this reaction, while demonstrating the catalytic role of Sn species, we show that the requirement of the type and the environment of Sn species are different for these reactions.
Keywords: mesoporous materials; Properties of Sn-SBA-15; Sn-containing SBA-15; Sn-SBA-15 catalysts; Synthesis of Sn-SBA-15

Synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an important intermediate for (3S,4R)-Cisapride - Shirode, Nilesh M.; Likhite, Anjali P.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2008)
An efficient synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an useful intermediate for the chiral synthesis of important drug molecule Cisapride and its analogs, from enantiopure 4-formylazetidin-2-one is described. Synthesis of trans as well as cis isomers of 4-amino-3-methoxypiperidine from 4-formylazetidin-2-one is also achieved in good yield. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: 4-aminopiperidine; azetidin-2-ones; Cisapride; Staudinger reaction; stereoselective synthesis

Synthesis of multifunctional nanogels using a protected macromonomer approach - Singh, Neetu; Lyon, L. Andrew (Colloid and Polymer Science, 2008)

Titania supported silicotungstic acid: an efficient solid acid catalyst for veratrole acylation - Waghmare, Nilesh G.; Kasinathan, Palraj; Amrute, Amol P.; Lucas, Nishita; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Titania supported silicotungstic acid (STA) with different STA loading (10-25 wt%) and calcination temperature (650-750 degrees C) were prepared by wet impregnation method. The catalysts have been represented by a general formula xSTiO(2)y (where x denotes wt%, S denotes STA and y denotes calcination temperature in degrees C). These catalysts were characterized by techniques such as X-ray diffraction, surface analysis, FTIR-pyridine and TPD-NH(3) and were used as heterogeneous solid acid catalysts in the liquid phase acylation of veratrole with acetic anhydride (Ac(2)O). It was found that 20STiO(2)700 gave the highest activity in acylation reaction due to its highest acidity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acetic anhydride; Acylation; Silicotungstic acid; titania; veratrole

Valence-state analysis through spectroelectrochemistry in a series of quinonoid-bridged diruthenium complexes [(acac)(2)Ru(mu-L)Ru(acac)(2)](n) (n =+2,+1, 0,-1,-2) - Ghumaan, Sandeep; Sarkar, Biprajit; Maji, Somnath; Puranik, Vedavati G.; Fiedler, Jan; Urbanos, Francisco A.; Jimenez-Aparicio, Reyes; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry-A European Journal, 2008)
The quinonoid ligand-bridged diruthenium compounds [(acac)(2)Ru(mu-L2-)Ru(acac)(2)] (acac(-) = acetylacetonato = 2,4-pentanedionato; L2- = 2,5-dioxido-1,4-benzoquinone, 1; 3,6-dichloro-2,5-dioxido-1,4-benzoquinone, 2; 5,8-dioxido-1,4-naphthoquinone, 3; 2-3-dichloro-5,8-dioxido-1,4-naphthoquinone, 4; 1,5-dioxido-9,10-anthraquinone, 5; and 1,5-diimido-9,10-anthraquinone, 6) were prepared and characterized analytically. The crystal structure analysis of 5 in the rac configuration reveals two tris(2,4-pentanedionato)ruthenium moieties with an extended anthracenedione-derived bis(ketoenolatee) pi-conjugated bridging ligand. The weakly antiferro-magnetically coupled {Ru-III(mu-L2-)Ru–(III)} configuration in 1-6 exhibits complicated overall magnetic and EPR responses,. ne simultaneous presence of highly redox-active quinonoid-bridging ligands and of two ruthenium centers capable of adopting the oxidation states +2, +3, and +4 creates a large variety of possible oxidation state combinations. Accordingly. the complexes 1-6 exhibit two reversible one-electron oxidation steps and at least two reversible reduction processes. Shifts to positive potentials were observed on introduction of Cl substituents (1 -> 2, 3 -> 4) or through replacement of NH by O (6 -> 5). The ligand-to-metal charge transfer (LMCT) absorptions in the visible region of the neutral molecules become more intense and shifted to lower energies on stepwise reduction with two electrons. On oxidation, the para-substituted systems 1-4 exhibit monocation intermediates with intervalence charge transfer (IVCT) transitions of (RuRuIV)-Ru-III mixed-valent species. In contrast, the differently substituted systems 5 and 6 show no such near infrared (NIR) absorption. While the first reduction steps are thus assigned to largely ligand-centered processes, the oxidation appears to involve metal-ligand delocalized molecular orbitals with variable degrees of mixing.
Keywords: magnetic properties; quinones; ruthenium; spectroelectrochemistry; structure elucidation; valence-state distributions

Zinc oxide nanoparticles as novel alpha-amylase inhibitors - Dhobale, Sandip; Thite, Trupti; Laware, S. L.; Rode, C. V.; Koppikar, Soumya J.; Ghanekar, Ruchika-Kaul; Kale, Sangeeta N. (Journal of Applied Physics, 2008)
Amylase inhibitors, also known as starch blockers, contain substances that prevent dietary starches from being absorbed by the body via inhibiting breakdown of complex sugars to simpler ones. In this sense, these materials are projected as having potential applications in diabetes control. In this context, we report on zinc oxide nanoparticles as possible alpha-amylase inhibitors. Zinc oxide nanoparticles have been synthesized using soft-chemistry approach and 1-thioglycerol was used as a surfactant to yield polycrystalline nanoparticles of size similar to 18 nm, stabilized in wurtzite structure. Conjugation study and structural characterization have been done using x-ray diffraction technique, Fourier transform infrared spectroscopy, UV-visible spectroscopy, and transmission electron microscopy. Cytotoxicity studies on human fibrosarcoma (HT-1080) and skin carcinoma (A-431) cell lines as well as mouse primary fibroblast cells demonstrate that up to a dose of 20 mu g/ml, ZnO nanoparticles are nontoxic to the cells. We report for the first time the alpha-amylase inhibitory activity of ZnO nanoparticles wherein an optimum dose of 20 mu g/ml was sufficient to exhibit 49% glucose inhibition at neutral pH and 35 degrees C temperature. This inhibitory activity was similar to that obtained with acarbose (a standard alpha-amylase inhibitor), thereby projecting ZnO nanoparticles as novel alpha-amylase inhibitors. (C) 2008 American Institute of Physics. [DOI: 10.1063/1.3009317]

Acetalization of glycerol using mesoporous MoO3/SiO2 solid acid catalyst - Shubhangi B. Umbarkar; Kotbagi, Trupti V.; Biradar, Ankush V.; Pasricha, Renu; Chanale, Jyoti; Dongare, Mohan K.; Mamede, Anne-Sophie; Lancelot, Christine; Payen, Edmond (Journal of Molecular Catalysis A-Chemical, 2009)
Acetalization of glycerol with various aldehydes has been carried out using mesoporous MoO3/SiO2 as a solid acid catalyst. A series of MoO3/SiO2 catalysts with varying MoO3 loadings(1-20 mol%) were prepared by sol-gel technique using ethyl silicate-40 and ammonium heptamolybdate as silica and molybdenum source respectively. The sol-gel derived samples were calcined at 500 degrees C and characterized using various physicochemical characterization techniques. The XRD of the calcined samples showed the formation of amorphous phase up to 10 mol% MoO3 loading and at higher loading of crystalline alpha-MoO3 on amorphous silica support. TEM analyses of the materials showed the uniform distribution of MoO3 nanoparticles on amorphous silica support. Raman spectroscopy showed the formation of silicomolybdic acid at low Mo loading and a mixture of alpha-MoO3 and polymolybdate species at high Mo loadings. Moreover the Raman spectra of intermediate loading samples also suggest the presence of beta-MoO3. Acetalization of glycerol with benzaldehyde was carried out using series of MoO3/SiO2 catalysts with varying MoO3 loadings (1-20 mol%). Among the series, MoO3/SiO2 With 20 mol% MoO3 loadings was found to be the most active catalyst in acetalization under mild conditions. Maximum conversion of benzaldehyde (72%) was obtained in 8 h at 100 degrees C with 60% selectivity for the six-membered acetal using 20% MoO3/SiO2. Interestingly with substituted benzaldehydes under same reaction conditions the conversion of aldehydes decreased with increase in selectivity for six-membered acetals. These results indicate the potential of this catalyst for the acetalization of glycerol for an environmentally benign process. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acetalization; Aldehyde; Glycerol; Silicomolybdic acid; solid acid

Antiplasmid activity of 1 `-acetoxychavicol acetate from alpinia galanga against multi-drug resistant bacteria - Latha, C.; Shriram, Varsha D.; Jahagirdar, Sheetal S.; Dhakephalkar, Prashant K.; Rojatkar, Supada R. (Journal of Ethnopharmacology, 2009)
Ethnopharmacological relevance: Alpinia galanga (L.) Swartz is traditionally used in the treatment of various ailments across India, China, and Southeast Asian countries. In India it is a reputed drug in indigenous system of medicine and largely used as antibacterial and antiseptic. In southern India the rhizomes has been used as a domestic remedy against bacterial infections. Aim of the study: To identify a potential antiplasmid compound from Alpinia galanga against multi-drug resistant bacteria. Materials and methods: The crude rhizome extract of Alpinia galanga was prepared in acetone. Antibacterial activity was checked by MIC and antiplasmid activity was checked by SIC. The principal compound responsible for the antiplasmid activity, in the crude extract, was identified by bioassay guided fractionation using hexane-acetone. Antibiotic resistance profile of plasmid harboring strains and plasmid cured strains was determined by disc diffusion method. Results: The crude acetone extract of the rhizomes of Alpinia galanga exhibited antiplasmid activity against Salmonella typhi, Escherichia coli and vancomycin resistant Enterococcus faecalis with an efficiency of 92%, 82% and 8% respectively at 400 mu g/ml SIC. The principal compound responsible for the activity was identified as 1'-acetoxychavicol acetate. 1'-Acetoxychavicol acetate demonstrated the ability to cure plasmid encoded antibiotic resistance in various multi-drug resistant bacterial strains of clinical isolates such as Enterococcus faecalis, Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli and Bacillus cereus with curing efficiency of 66%, 75%, 70%, 32% and 6% respectively at SIC of 400-800 mu g/ml. Conclusion: 1'-Acetoxychavicol acetate mediated R-plasmid curing significantly reduced the minimal inhibitory concentration of antibiotics required to inhibit growth of bacteria, thus making the antibiotic treatment more effective. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: 1 `-Acetoxychavicol acetate; Alpinia galanga; Antibiotic resistance; Antiplasmid

Applications of a high performance platinum nanocatalyst for the oxidation of alcohols in water - Maity, Prasenjit; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Green Chemistry, 2009)
Nanoparticles of platinum (NP-Pt), have been synthesized by supporting high nuclearity anionic carbonyl cluster (Chini cluster) on a water soluble anion exchanger, and the performance of this material, 1, as an oxidation catalyst for alcohols in water has been studied. The E-factor for the synthesis of NP-Pt by this method has been calculated and compared with that of other NP-Pt recently reported in the literature. With 1 as a catalyst, oxidations of a variety of primary and secondary alcohols by dioxygen are achieved and high turnover numbers and selectivities are obtained. The performances of 1 in the oxidation of benzyl alcohol and 1-phenylethanol are compared with those of three other platinum catalysts. These are platinum nanoparticles 2 prepared by the hydrogen reduction of [PtCl6](2-) supported on the same water soluble polymer, 5% Pt on carbon, and 5% Pt on alumina, designated as 3 and 4, respectively. 1 has been found to be considerably more active than 2- 4 and also other reported water soluble platinum nanocatalysts. After many turnovers (similar to 1000 and similar to 165 for benzyl alcohol and 1-phenyl ethanol, respectively) partial deactivation (similar to 40%) is observed, but the deactivated catalyst can be fully regenerated by treatment with dihydrogen. The TEM data of fresh, deactivated and regenerated 1 show a correlation between the particle size and activity. A mechanism consistent with this and other experimental observations including XPS data is proposed.

Azoic dye hosted in layered double hydroxide: physicochemical characterization of the intercalated materials - Mandal, Sujata; Tichit, Didier; Lerner, Dan A.; Marcotte, Nathalie (Langmuir, 2009)
Intercalation compounds were obtained by introduction of guest methyl orange (MO) into the interlayer space of host Mg/Al and Ni/Al layered double hydroxides (LDHs). Three synthesis methods of organic anion-LDH intercalation compounds, i.e., coprecipitation, reconstruction of the M(II)(Al)O mixed oxides, and anion exchange of LDH were compared. The former Method gives rise to a highly organized MO-intercalated Mg/Al LDH with an interlayer spacing of 2.43 rim and up to seven (001) reflection orders. Reconstruction or the mixed oxide by intercalation with MO in the restored LDH was only achieved with Mg(Al)O. In this case. a competitive adsorption of MO on the external Surface Of the crystals was also seen. On the other hand, intercalation compounds exhibiting interlayer spacing of 2.43 run were obtained with both Mg- and Ni-containing LDH using the anionic exchange method. The equilibrium and kinetic adsorption properties of the compounds were analyzed by UV-visible spectroscopy in anionic exchange experiments. According to the pseudo-second-order adsorption model, the amounts of adsorbed MO reach 3.82 and 2.83 mequiv/g for Mg- and Ni-containing LDHs, respectively, which are close to their respective anionic exchange capacity. The adsorption rates are on the same order of magnitude for the two LDHs (0.10-0.44 g mmol(-1) min(-1)), the equilibrium being reached in less than 60 min. The decomposition of MO by combustion of the organic moieties under an oxidizing atmosphere is delayed in Mg-containing MO-LDH hybrids when compared to the free MO molecule, showing that the thermal stability of MO species is enhanced after intercalation. In Ni-containing LDH, the main decomposition step of MO occurs 300 degrees C below that of Mg-containing LDH. This was rationalized in terms of a catalysis by the Ni-containing oxides formed during the thermal treatment. So these materials exhibit several advantage useful for the development of eco-friendly processes for the removal Of dyes from effluents of textile, plastic, and paper industries.

Chemical bath deposition of CdS quantum dots on vertically aligned ZnO nanorods for quantum dots-sensitized solar cells - Lee, Wonjoo; Min, Sun Ki; Dhas, Vivek V.; Ogale, Satishchandra B.; Han, Sung-Hwan (Electrochemistry Communications, 2009)
Formation of US quantum dots (Q dots) on the vertically aligned ZnO nanorods electrode was carried out by chemical bath deposition. The diameter and thickness of ZnO nanorods are similar to 100-150 nm and similar to 1.6 mu m, respectively, and CdS Q dots on ZnO nanorods have a diameter of smaller than 15 nm. In application of the Q dots-sensitized solar cells, composite film exhibited a power conversion efficiency of 0.54% under air mass 1.5 condition (80 mW/cm(2)), and incident-photon-to-current conversion efficiency showed 18.6%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical bath deposition; Photosensitization; quantum dots; solar cells; Wet-chemical process

Chlorophyll-based photocatalysts and their evaluations for methyl orange photoreduction - Joshi, Meenal M.; Kamble, Sanjay R.; Labhsetwar, Nitin K.; Parwate, D. V.; Rayalu, Sadhana S. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Immobilization of chlorophyll on different functionalized mesoporous materials has been attempted. The replacement of butanediol with monoethanol amine has resulted in increase in chlorophyll loading by a factor of two. The maximum immobilization of chlorophyll was on MCM-41 functionalized with monoethanolamine MCM-41/MEA/Chl) as compared to other mesoporous materials. This material has been characterized using XRD, UV-vis diffuse reflectance spectroscopy, scanning electron microscopy (SEM-EDX) and fluorescence spectroscopy. The photocatalytic reduction of methyl orange (MO)was studied using MCM-41/MEA/Chl as photocatalyst under the visible light. The photocatalytic reduction of MO was 0.396 mg/g of MCM-41/MEA/Chl photocatalyst as compared to 0.508 mg/g of TiO(2) for that of Degussa P-25 photocatalyst. The effect of various operating parameters like catalyst loading, initial concentration and intensity of light has also been studied. Photocatalytic property of chlorophyll-based photocatalytic material indicates that chlorophyll acts as a reaction center, which absorbs visible light and generates electron, which is transferred to different electron acceptors reducing MO into derivative of hydrazine. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Chlorophyll-based photocatalyst; Mesoporous material; Methyl orange; Photoreduction

Chromate reduction by PVA-alginate immobilized streptomyces griseus in a bioreactor - Poopal, Ashwini C.; Laxman, Ryali Seeta (Biotechnology Letters, 2009)
Microbial reduction of toxic Cr(6+) to the less toxic Cr(3+) is potentially a useful bioremediation process. Among the matrices tested for whole cell immobilization of an efficient chromate-reducing Streptomyces griseus strain, PVA-alginate was the most effective and was used for reduction of Cr(VI) in a bioreactor. Cr(6+) reduction efficiency decreased as Cr(6+) was increased from 2 to 12 mg l(-1) but increased with an increase in biomass concentration. However, increasing the flow rate from 2 to 8 ml h(-1) did not significantly affect Cr(6+) reduction. The reduction was faster in simulated effluent than in synthetic medium and complete removal of 8 mg Cr(6+) l(-1) from effluent and synthetic medium occurred in 2 and 12 h, respectively. Our results indicate that immobilized S. griseus cells could be applied for the large-scale bioremediation of chromate-containing effluents and wastewaters.
Keywords: Bioremediation; Chromate reduction; Immobilized cells; Polyvinyl alcohol-alginate; Streptomyces griseus

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia

Defluoridation of drinking water using chemically modified bentonite clay - Kamble, Sanjay P.; Dixit, Priyadarshini; Rayalu, Sadhana S.; Labhsetwar, Nitin K. (Desalination, 2009)
Adsorption potential of metal oxide (lanthanum, magnesium and manganese) incorporated bentonite clay was investigated for defluoridation of drinking water using batch equilibrium experiments to gain insight of adsorption behavior, kinetics and mechanisms of adsorption of fluoride ion. The effect of various physicochemical parameters such as pH, adsorbent dose, initial fluoride concentration and the presence of interfering co-ions on adsorption of fluoride has been investigated. The 10%La-bentonite shows higher fluoride uptake capacity for defluoridation of drinking water as compared to Mg-bentonite, Mn-bentonite and bare bentonite clay. The uptake of fluoride in acidic pH was higher as compared to alkaline pH. The equilibrium adsorption data fitted reasonably well in both Langmuir and Freundlich isotherm models. It was also observed that in the presence of certain co-existing ions can have positive effect on removal of fluoride, while carbonate and bicarbonate anions show deleterious effect. The rate of adsorption was reasonably rapid and maximum fluoride uptake was attained within 30 min. The modified adsorbent material shows better fluoride removal properties for actual field water, which could be due to the positive effect of other co-ions present in the field water. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 10%La-bentonite; Defluoridation; Kinetic modeling; Langmuir and Freundlich adsorption isotherms; Water treatment

Effect of relative humidity and sea level pressure on electrical conductivity of air over Indian ocean - Pawar, S. D.; Murugavel, P.; Lal, D. M. (Journal of Geophysical Research-Atmospheres, 2009)
The electrical conductivity measured over the Indian Ocean (15 degrees N, 77 degrees E to 20 degrees S, 58 degrees E) during the Indian Ocean Experiment (INDOEX-1999) from 20 January to 12 March 1999 has been analyzed. The conductivity values over two oceanic regions, one with very low aerosol concentration and another with very high aerosol concentration, are studied in relation with meteorological parameters such as relative humidity and sea level pressure. The average conductivity is as low as 0.295 x 10(-14) Sm-1 in the region of high aerosol concentration and it is 0.783 x 10(-14) Sm-1 in the region of very low aerosol concentration. In both the regions, conductivity shows an inverse relation with relative humidity and this effect is more in the presence of high aerosol concentration. The hydrate growth of aerosol particles in high-humidity condition may be responsible for the inverse relation between conductivity and relative humidity. Size distributions of aerosol particles measured in the same cruise during high-humid conditions are also analyzed to show that sizes, rather than numbers, of aerosol particles increase with an increase in humidity. The relationship between conductivity and sea level pressure in these two regions is also studied and it shows good correlation in the region where the background aerosol concentration is low and no correlation in the region where aerosol concentration is high. The inverse relation between sea level pressure and electrical conductivity is attributed to the possible transportation of ultrafine particles from free troposphere, with subsiding motions associated with high pressure. The positive correlation between ultrafine particles and sea level pressure supports this idea.

Electronic manifestation of cation-vacancy-induced magnetic moments in a transparent oxide semiconductor: anatase Nb:TiO2 - Zhang, Shixiong; Ogale, Satishchandra B.; Yu, Weiqiang; Gao, Xingyu; Liu, Tao; Ghosh, Saurabh; Das, Gour P.; Wee, Andrew T. S.; Greene, Richard L.; Venkatesan, Thirumalai (Advanced Materials, 2009)
Nb-doped anatase TiO2 thin films grown by pulsed-laser deposition show Kondo scattering in elctronic-transport measurements, providing evidence for the formation of magnetic moments. The origin of magnetism is attributed to cation (Ti) vacancies, confirmed by X-ray absorption spectroscopy and first-principle calculations. The Ti vacancies are controlled by oxygen partial pressure during growth.

Enhanced conversion efficiency in dye-sensitized solar cells based on hydrothermally synthesized TiO2-MWCNT nanocomposites - Muduli, Subas; Lee, Wonjoo; Dhas, Vivek V.; Mujawar, Sarfraj; Dubey, Megha; Vijayamohanan, K.; Han, Sung-Hwan; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2009)
A 50 % enhancement in the conversion efficiency (4.9-7.37 %) is realized in dye-sensitized solar cells Using hydrothermally synthesized TiO2-multiwalled carbon nanotube (MWCNT) nanocomposites as compared to hydrothermally synthesized TiO2 without MWCNT and Degussa P25. Several characterizations have been employed to reveal the nature of the modification imparted to the MWCNTs under hydrothermal processing conditions and the resulting TiO2-MWCNT conjugation through -COOH groups. Efficient charge transfer In the nanocomposite and efficient electron transport by MWCNT (significantly higher Incident-photon-to-current conversion efficiency) are suggested to be the possible reasons for the enhancement.
Keywords: Carbon nanotubes; charge transfer; Dye-sensitized solar cells; Hybrid composite; hydrothermal

Epitaxially grown zinc-blende structured Mn doped ZnO nanoshell on ZnS nanoparticles - Limaye, Mukta V.; Singh, Shashi B.; Date, Sadgopal K.; Gholap, Ramkrishna S.; Kulkarni, Sulabha K. (Materials Research Bulletin, 2009)
Zinc oxide in the bulk as well as in the nanocrystalline form is thermodynamically stable in the wurtzite structure. However, zinc oxide in the zinc-blende structure is more useful than that in the wurtzite structure due to its superior electronic properties as well as possibility of efficient doping. Therefore, zinc oxide shell is grown epitaxially on zinc sulphide core nanoparticles having zinc-blende structure. It is shown that doping of manganese could be achieved in zinc oxide nanoshell with zinc-blende structure. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Luminescence; Nanostructures; Semiconductors; X-ray diffraction

Exploration of click reaction for the synthesis of modified nucleosides as chitin synthase inhibitors - Chaudhary, Preeti M.; Chavan, Sayalee R.; Shirazi, Fazal; Razdan, Meenakshi; Nimkar, Prachi; Maybhate, Shailaja P.; Likhite, Anjali P.; Gonnade, Rajesh G.; Hazra, Braja G.; Deshpande, Mukund V.; Deshpande, Sunita R. (Bioorganic & Medicinal Chemistry, 2009)
Click reaction approach toward the synthesis of two sets of novel 1,2,3-triazolyl linked uridine derivatives 19a-19g and 21a-21g was achieved by Cu(I)-catalyzed 1,3-dipolar cycloaddition of 5'-azido-5'-deoxy-2',3'-O-(1-methylethylidene) uridine (17) with propargylated ether of phenols 18a-18g and propargylated esters 20a-20g. Structure of one of the representative compound 19d was unambiguously confirmed by X-ray crystallography. Chitin synthase inhibition study of all these compounds 19a-19g and 21a-21g was carried out to develop antifungal strategy. Compounds 19d, 19e, 19f, and 21f were identified as potent chitin synthase inhibitors by comparing with nikkomycin. Compounds 19a, 19b, 19c, 19d, 21a, and 21b showed good antifungal activity against human and plant pathogens. Compounds 19a, 19b, 19f, 21c, 21f, and 21g were identified as lead chitin synthase inhibitors for further modi. cations by comparing results of inhibition of growth, % germ tube formation and chitin synthase activity. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; 4-Disubstituted-1; 5 `-Azidouridine; Antifungal compounds; Chitin synthase activity; Click reaction; Uridine nucleosides

Field emission investigation of single Fe-doped SnO2 wire - Bhise, Ashok B.; Late, Dattatray J.; Sathe, Bhaskar R.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Solid State Sciences, 2009)
Tin oxide submicronwires doped with Fe element were prepared by the thermal evaporation method. Morphological and structural characterizations revealed wires with sub micron size and crystalline in nature. The field electron emission from the single Fe:SnO2 wire was carried out in conventional field emission microscope. The Fowler-Nordheim plot obtained from I-V characteristics of the wire showed a linear behavior typical that of metal. The field enhancement factor estimated from the slope of the F-N plot is 7455 cm(-1), indicating that the field emission is from nanometric features of the emitter. A current density of 10 A/cm(2) has been obtained at an applied field of 4.845 x 10(3) V/mu m. The field emission current-time record at a current level of 1 mu A for more than 3 h duration is promising for various field emissions based applications. (C) 2009 Published by Elsevier Masson SAS.
Keywords: Current stability; Fe doped; field emission; SnO2

Hydrolysis of cellulose derived from steam exploded bagasse by penicillium cellulases: comparison with commercial cellulase - Singh, Rajkumar; Varma, Anjanikumar; Laxman, Ryali Seeta; Rao, Mala (Bioresource Technology, 2009)
A complete cellulase from Penicillium pinophilum was evaluated for the hydrolysis of a-cellulose derived from steam exploded sugarcane bagasse and other cellulosic substrates. alpha-Cellulose at 1% substrate concentration was completely hydrolyzed by Penicillium cellulase within 3 h wherein at 10% the hydrolysis was 100% within 24 h with an enzyme loading of 10 FPU/g. The hydrolysate yielded glucose as major end product as analyzed by HPLC. Under similar conditions, hydrolysis of Sigmacell (microcrystalline cellulose), CP-123 (pulverized cellulose powder) and ball milled Solka Floc were 42%, 56% and 52%, respectively. Further the hydrolysis performance of Penicillium sp. cellulase is compared with Trichoderma reesei cellulase (Accellerase (TM) 1000) from Genencore. The kinetics of hydrolysis with respect to enzyme and substrate concentration will be presented. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Accellerase (TM) 1000; Enzymatic hydrolysis; High beta-glucosidase; Penicillium cellulase; Sugarcane bagasse

On the influence of spatial heterogeneity on an internal boundary layer at a short fetch - Murthy, B. S.; Latha, R.; Sukumaran, Cini; Shivaji, A.; Sivaramakrishnan, S. (Journal of Earth System Science, 2009)
Surface layer meteorological data collected at a coastal site, at Vasco-Da-Gama (15A degrees 21'N, 73A degrees 51'E, 58.5m MSL) (13-18 July, 2002) with prevailing southwesterly surface winds are analyzed to study the characteristics of internal boundary layer at a short fetch using an instrumented tower (9 m). The spectral and turbulence characteristics of wind are compared with earlier measurements made at a comparatively homogeneous terrain and the standards available in literature. The study show the smaller eddies in the vertical velocity spectrum attains equilibrium with the underlying surface at a short fetch itself and follows spectral similarity. However, this is not followed by longitudinal and transverse velocity spectra under unstable as well as stable conditions.
Keywords: heterogeneity; IBL; sea-land interface; wind spectra

Isothermal crystallization and melting behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Singh, R. P. (Thermochimica Acta, 2009)
The effect of layered double hydroxide (LDH) nanolayers on the crystallization behavior of polypropylene (PP) was studied based on the preparation of nanocomposites by a melt intercalation method. The isothermal crystallization kinetics and subsequent melting behavior of PP/LDH hybrids were studied with differential scanning calorimetry (DSC), polarized optical microscopy (POM), and wide-angle X-ray diffraction (WAXD). Studies revealed that the LDH promoted heterogeneous nucleation, accelerating the crystallization of PR The Avrami equation successfully describes the isothermal crystallization kinetics of PP/LDH hybrids and signifies heterogeneous nucleation in crystal growth of PR The varying values of Avrami exponent (n) and half crystallization time (t(1/2)) of PP and PP/LDH hybrids describes overall crystallization behavior. The crystallite size (D(hkl)) and distribution of different crystallites in PP varied in presence of LDH. A significant increase in melting temperature is observed for PP/LDH hybrids. The POM showed that smaller and less perfect crystals were formed in nanocomposites because of molecular interaction between PP chains and LDH. The value of fold surface free energy (sigma(e)) of PP chains decreased with increasing LDH content. Finally, the overall results signify that LDH at nanometer level acted as nucleating agent and accelerate the overall crystallization process of PR (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Isothermal crystallization; Layered double hydroxide; Melting behavior; Polypropylene nanocomposites

Non-templated hydrothermal growth of anisotropic magnetite nanostructures using hexamine as the directing agent - Bhagwat, S. V.; Jouen, Samuel; Kundaliya, D. C.; Singh, H.; Jagadale, Tushar C.; Athawale, A. A.; Lofland, S. E.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2009)
Anisotropic growth of magnetite (Fe(3)O(4)) nanoparticles is achieved in a hydrothermal growth process using hexamine to play a dual role of oxide forming and directing agent. The samples are characterized by X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, squid magnetometry, ferromagnetic resonance technique, diffuse reflectance spectroscopy and Mossbauer spectroscopy, which collectively establish the formation of Fe(3)O(4) phase. Anisotropic structures such as nanorods and nanotubules are revealed and these are shown to exhibit good humidity sensing properties.
Keywords: Anisotropic Nanostructures; Hexamine; hydrothermal; magnetite; Mossbauer

Novel/conceptual floating pulsatile system using high internal phase emulsion based porous material intended for chronotherapy - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Benson, James R.; Li, Nai-Hong; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The aim of the present study was to design a novel/conceptual delivery system using ibuprofen, anticipated for chronotherapy in arthritis with porous material to overcome the formulation limits (multiple steps, polymers, excipients) and to optimize drug loading for a desired release profile suitable for in vitro investigations. The objective of this delivery system lies in the availability of maximum drug amount for absorption in the wee hours as recommended. Drug loading using 3(2) factorial design on porous carrier, synthesized by high internal phase emulsion technique using styrene and divinylbenzene, was done via solvent evaporation using methanol and dichloromethane. The system was evaluated in vitro for drug loading, encapsulation efficiency, and surface characterization by scanning electron, atomic force microscopy, and customized drug release study. This study examined critical parameters such as solvent volume, drug amount, and solvent polarity on investigations related to drug adsorption and release mostly favoring low-polarity solvent dichloromethane. Overall release in all batches ranged 0.98-52% in acidic medium and 71-94% in basic medium. These results exhibit uniqueness in achieving the least drug release of 0.98%, an ideal one, without using any release modifiers, making it distinct from other approaches/technologies for time and controlled release and for chronotherapy.
Keywords: chronotherapy; floating pulsatile drug delivery system; high internal phase emulsion; ibuprofen; multiparticulate porous carriers

Optical investigations of interaction between zinc tetra phenyl porphyrin and CdSe nanoparticles - Lihitkar, N. B.; Singh, S. B.; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Chemical Physics Letters, 2009)
Interactions between nanoparticles of zinc tetra phenyl porphyrin (ZnTPP) with CdSe nanoparticles in dimethyl sulphoxide solvent have been investigated. A ZnTPP-CdSe complex was formed which showed substantial changes in the UV-Vis absorption spectra in the presence of CdSe. Fluorescence measurements showed an interesting behavior at low as well as high concentrations of CdSe. When low concentrations of CdSe nanoparticles were added to the ZnTPP nanoparticles solution, besides two fluorescence bands due to ZnTPP nanoparticles, an intense new band appeared. On the other hand at high concentrations of CdSe one of the fluorescence band of ZnTPP at similar to 604 nm increased. (C) 2009 Published by Elsevier B. V.

Optoelectronic photoinduced charge transfer system with mu 3PhN-Ru-3 cluster functionalized single-walled carbon nanotubes - Lee, Wonjoo; Koo, Gumae; Ogale, Satishchandra B.; Han, Sung-Hwan (Journal of Materials Chemistry C, 2009)
Optoelectronic photoinduced charges have been attracting great attention lately in view of their applicability to diverse optoelectronic device systems. Here, we report the design and implementation of a charge transfer system based on triruthenium (Ru) cluster compounds on viologen modified single-walled carbon nanotubes (V-SWNTs) by an in situ preparation method. We examine the photoinduced (intensity dependent and temporal) changes in the transport properties of the Ru-cluster functionalized V-SWNT coating and identify the possible charge transfer mechanism. Furthermore, we demonstrate the applicability of such Ru-cluster functionalized V-SWNT films to photoelectrochemical cells.

Oxidative kinetic resolution of alcohols using chiral Mn-salen complex immobilized onto ionic liquid modified silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
The supported ionic liquid strategy has been applied for the immobilization of chiral Mn(III) salen complex onto ionic liquid modified silica. Chiral Mn(III) salen complex was immobilized over silica through a thin film of covalently anchored imidazolium ionic liquid. These catalysts were characterized by N(2) sorption, XRD, MR, DRUV-vis, and elemental analysis. The results showed that the chiral Mn(III) salen complex could be successfully immobilized onto the modified mesoporous materials and that the long-range mesoporous ordering of parent supports was maintained after the immobilization. The immobilized catalyst provided good enantioselectivity and activity in the heterogeneous catalysis of the oxidative kinetic resolution of secondary alcohol and can be recovered and recycled for four times without obvious loss of enantioselectivity and activity. Oxidative kinetic resolutions of meso-diols, hydroxyl ester and primary alcohol were also studied using this catalyst system. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mesoporous silica; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Polymeric ladderphanes - Chou, Chih-Ming; Lee, Shern-Long; Chen, Chih-Hsien; Biju, Akkattu T.; Wang, Hsian-Wen; Wu, Yi-Lin; Zhang, Guo-Fu; Yang, Kuang-Wei; Lim, Tsong-Shin; Huang, Min-Jie; Tsai, Po-Yu; Lin, Kin-Chuan; et al. (Journal of the American Chemical Society, 2009)
A new class of polymers, which have a double-stranded polybinorbornene skeleton with multilayer planar oligoaryl linkers, defined as polymeric ladderphanes, are synthesized. The structures of these ladderphanes are determined by spectroscopic means. Photophysical studies and time-resolved fluorescence spectroscopic investigations reveal that there is a strong interaction between the chromophore linkers. Thus, Soret band splitting in the absorption spectrum of the polymer with porphyrin linker (12e), significant fluorescence quenching with oligoaryl linkers (12b−d), and excimer emission with a terphenylene-diethynylene linker (12a) are characteristic photophysical properties of these polymers. Scanning tunneling microscopy shows that polymers 12b and d exhibit a ladder-like morphology and form a supramolecular assembly leading to a two-dimensional ordered array on a highly oriented pyrolytic graphite surface.

Prediction of extrudate swell in polymer melt extrusion using an Arbitrary Lagrangian Eulerian (ALE) based finite element method - Ganvir, Vivek; Lele, Ashish K.; Thaokar, Rochish; Gautham, Basavarsu P. (Journal of Non-Newtonian Fluid Mechanics, 2009)
Accurate prediction of extrudate (die) swell in polymer melt extrusion is important as this helps in appropriate die design for profile extrusion applications. Extrudate swell prediction has shown significant difficulties due to two key reasons. The first is the appropriate representation of the constitutive behavior of the polymer melt. The second is regarding the simulation of the free surface, which requires special techniques in the traditionally used Eulerian framework. In this paper we propose a method for simulation of extrudate swell using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation. The ALE technique provides advantages of both Lagrangian and Eulerian frameworks by allowing the computational mesh to move in an arbitrary manner, independent of the material motion. In the present method, a fractional-step ALE technique is employed in which the Lagrangian phase of material motion and convection arising out of mesh motion are decoupled. In the first step, the relevant flow and constitutive equations are solved in Lagrangian framework. The simpler representation of polymer constitutive equations in a Lagrangian framework avoids the difficulties associated with convective terms thereby resulting in a robust numerical formulation besides allowing for natural evolution of the free surface with the flow. In the second step, mesh is moved in ALE mode and the associated convection of the variables due to relative motion of the mesh is performed using a Godunov type scheme. While the mesh is fixed in space in the die region, the nodal points of the mesh on the extrudate free surface are allowed to move normal to flow direction with special rules to facilitate the simulation of swell. A differential exponential Phan Thien Tanner (PTT) model is used to represent the constitutive behavior of the melt. Using this method we simulate extrudate swell in planar and axisymmetric extrusion with abrupt contraction ahead of the die exit. This geometry allows the extrudate to have significant memory for shorter die lengths and acts as a good test for swell predictions. We demonstrate that our predictions of extrudate swell match well with reported experimental and numerical simulations. (c) 2008 Elsevier BY. All rights reserved.
Keywords: Arbitrary Lagrangian Eulerian; Extrudate (die) swell; Free surface simulations

Preparation and nonisothermal crystallization behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Morlat-Therias, Sandrine; Caperaa, N.; Leroux, Fabrice; Gardette, Jean Luc; Singh, R. P. (Polymer, 2009)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared via melt intercalation using dodecyl sulfate anion modified LDH and maleated PP as compatibilizing agent. Evidently the interlayer anions in LDH galleries react with maleic anhydride groups of PP-g-MA and lead to a finer dispersion of individual LDH layers in the PP matrix. The nanostructure was characterized by XRD and TEM; the examinations confirmed the nanocomposite formation with exfoliated/intercalated layered double hydroxides well distributed in the PP matrix. The nonisothermal crystallization behavior of resulting nanocomposites was extensively studied using differential scanning calorimetry (DSC) technique at various cooling rates. In nonisothermal crystallization kinetics, the Ozawa approach failed to describe the crystallization behavior of nanocomposites, whereas the Avrami analysis and Jeziorny method well define the crystallization behavior of PP/LDH nanocomposite. Combined Avrami and Ozawa analysis (Liu model) also found useful. The results revealed that very small amounts of LDH (1%) could accelerate the crystallization process relative to the pure PP and increase in the crystallization rates was attributed to the nucleating effect of the nanoparticles. Polarized optical microscopy (POM) observations also support the DSC results. The effective crystallization activation energy was estimated as a function of the relative degree of crystallinity using the isoconversional analysis. Overall, results indicated that the LDH particles in nanometer size might act as nucleating agent and distinctly change the type of nucleation, growth and geometry of PP crystals. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Layered double hydroxide; Nonisothermal crystallization kinetics; Polypropylene nanocomposites

Process for the preparation of polymeric absorbents - Lele, Ashish Kishor; Varghese, Shyni; Badiger, Manohar V.; Mashelkar, Raghunath Anant (2009)
The invention discloses a process for the preparation of polymeric absorbents useful for gelling organic liquids. The process comprises mixing one or more monomers with a cross-linking agent, a free radical initiator, an optional solvent, optionally in the presence of a transition metal source and subjecting the mixture so obtained to a conventional polymerisation method. The polymer is removed, crushed to obtain polymer powder, washed with solvent and dried by conventional methods to remove unreacted monomers, followed by swelling in alcohols to obtain the desired product.

Reactive extrusion of poly(L-Lactic Acid) with glycidol - Deenadayalan, E.; Lele, Ashish K.; Balasubramanian, M. (Journal of Applied Polymer Science, 2009)
Glycidol modified polylactic acid (PLLA) polymers have been prepared by reactive extrusion. Influences of residence time and the concentration of glycidol on the extent of reaction with different weight average molecular weight (45,000, 65,000, and 100,000) PLLA's were studied. Structure-property relationship has been established by measuring molecular, mesoscopic, and macroscopic properties. Under reactive extrusion conditions glycidol reacted with the end groups of PLLA to initiate chain extension. Low-molecular weight PLLA reacted with glycidol faster than the medium molecular weight PLLA, whereas high-molecular weight PLLA did not show significant reactions. The glass transition temperature, melting temperature, crystallization temperature, and heat of fusion were measured for unmodified and modified PLLA's. Chain extended PLLA had higher T(g) and T(m) than the unmodified samples. Time sweep rheological experiments were performed to test the melt stability of PLLA. Chain extended PLLA's were found to retain viscoelastic properties for much longer time than the unreacted samples. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 1391-1398, 2009
Keywords: biodegradable; reactive extrusion; Rheology; structure-property relations; Thermal properties

Recyclable amberlyst-70 as a catalyst for biginelli reaction: an efficient one-pot green protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones - Chandak, Hemant S.; Lad, Nitin P.; Upare, Pravin P. (Catalysis Letters, 2009)
An environmentally benign aqueous protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones using Amberlyst-70 as a recyclable catalyst has been developed. The use of resinous, nontoxic, thermally stable and inexpensive Amberlyst-70, as a recyclable heterogeneous catalyst, makes the process simple with negligible chemical waste. Thus renders this method an environmentally acceptable synthetic tool for Biginelli reaction.
Keywords: Amberlyst-70; Biginelli reaction; green chemistry; heterogeneous catalysis

Responsive assemblies and microgel-based materials - Lyon, L. Andrew; Meng, Z.; Singh, Neetu; Sorrell, C. D.; John, A. (Chemical Society Reviews, 2009)

Scolecite as an efficient heterogeneous catalyst for the synthesis of 2,4,5-triarylimidazoles - Gadekar, Lakshman S.; Mane, Shivshankar R.; Katkar, Santosh S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2009)
Natural scolecite has been found as an effective catalyst for the one-pot synthesis of 2,4,5-triarylimidazole derivatives via a three component reaction using benzil or benzoin, aldehydes and ammonium acetate. This method provides several advantages such as being environmentally benign, reusable, possessing high yields with increased variations of the substituents in the product and preparative simplicity.
Keywords: 2; 4; 5-Triarylimidazoles; heterogeneous catalyst; Three-component reaction

Scolecite catalyzed facile and efficient synthesis of polyhydroquinoline derivatives through hantzsch multi-component condensation - Gadekar, Lakshman S.; Katkar, Santosh S.; Mane, Shivshankar R.; Arbad, Balasaheb R.; Lande, Machhindra K. (Bulletin of the Korean Chemical Society, 2009)
A facile and efficient synthetic route has been developed for the polyhydroquinoline via four component reactions of aldehydes, dimedone, ethyl acetoacetate and ammonium acetate in the presence of catalytic amount of scolecite in ethanol at 70 degrees C through Hantzsch reaction. This method gives remarkable advantages such as simple work-up procedure. environmentally friendly, inexpensive, non-toxic and recyclable catalyst, shorter reaction time along with excellent yields
Keywords: heterogeneous catalyst; Multicomponent reaction; Polyhydroquinoline; Reusable catalyst

Self-assembly of silica particles in a nonionic surfactant hexagonal mesophase - Sharma, Kamendra P.; Kumaraswamy, Guruswamy; Ly, Isabelle; Mondain-Monval, Olivier (Journal of Physical Chemistry B, 2009)
We investigate the process of self-assembly, and the resultant structures in composites of silica particles with a hexagonal mesophase of a nonionic surfactant and water. We report a systematic transition in behavior when the particle size is increased relative to the characteristic mesophase spacing. Water dispersible cage-like silsesquioxanes that are molecular analogues of silica particles and are smaller than the mesophase spacing swell the space between the surfactant cylinders. Silica particles comparable to the characteristic hexagonal spacing partition into the hexagonal phase and into strandlike particulate aggregates. Even larger particles phase separate from the hexagonal phase to form particulate strands that organize with a mesh size comparable to the wavelength of visible light. This self-assembly is reversible and the particles disperse by breaking up the aggregates on heating the composite into the isotropic phase. On cooling from the isotropic phase into the hexagonal, the particles are expelled from the growing hexagonal domains and finally impinge to form strandlike aggregates. Unusually, the isotropization temperature is increased in the composites as the particles nucleate the formation of the hexagonal phase.

Self-similar dynamics of a flexible ring polymer in a fixed obstacle environment: a coarse-grained molecular model - Iyer, Balaji V. S.; Lele, Ashish K.; Juvekar, Vinay A.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
In this contribution we concern ourselves with an interesting problem, namely, the dynamics of ideal flexible ring polymers constrained in tin array of fixed obstacles. The fundamental issue in this problem is to understand how a topologically constrained polymer chain is able to relax its conformation in the absence of chain ends. The key physics was provided in tin elegant scaling theory by Rubinstein and co-workers (Obukhov, S. P; Rubinstein, M.; Duke, T. Dynamics of a Ring Polymer in a Gel. Phys. Rev. Lett. 1994, 73, 1263-1267). In this work we develop a coarse-grained mean-field model based oil the physical arguments of the scaling theory and derive constitutive relations for rings in fixed obstacle and melt environments. The model is composed of three distinct steps. In the first step the dynamics of an arbitrary section of a ring chain is worked out based oil fractal Blob-Spring (BS) dynamics, and the center of mass diffusion and the relaxation spectrum of this section are determined. In the second step the center of mass diffusion obtained using the BS dynamics is used to model the one-dimensional diffusion of the section in a topologically constrained environment. In the final step we invoke the idea of dynamic self-similarity and argue that the dynamics described in the first and the second step, for any arbitrary section of the chain, applies to all sections of the chain. The constitutive relation is obtained consequently as the superposition of dynamic response of all sections of the ring chain.

Some mechanistic insights into the gelation of regenerated silk fibroin sol - Nagarkar, Shailesh; Patil, Avinash; Lele, Ashish K.; Bhat, Suresh K.; Bellare, Jayesh R.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
We provide some new insights into the kinetics and mechanism of sol-gel transition as it pertains to regenerated silk fibroin, which is the principle structural protein of silkworm silk fiber. Silk fibroin was dissolved in lithium bromide and dialyzed against deionized water to prepare a regenerated fibroin solution. This solution was found to be unstable at lower pH and transformed into a colloidal gel. The kinetics and mechanism of the sol-gel transition were investigated using rheology and light scattering. We show that gelation proceeds in two steps. In the first step, a weak gel is formed almost immediately upon lowering the pH, while in the second step further gelation proceeds rapidly after a long induction time to form a self-similar structure.

Stereo-controlled approach to pyrrolidine iminosugar C-glycosides and 1,4-dideoxy-1,4-imino-L-allitol using a D-mannose-derived cyclic nitrone - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D.; Lombardo, Marco (Tetrahedron Letters, 2009)
Intramolecular N-alkylation of 2,3-O-isopropylidene-5-O-methanesulfonyl-6-O-t-butyldimethylsilyl-D-mann ofuranose-oxime 7 afforded a five-membered cyclic nitrone 9, which on N-O bond reductive cleavage followed by deprotection of -OTBS and acetonide functionalities gave 1,4-dideoxy-1,4-imino-L-allitol (DIA) 3. Addition of allylmagnesium chloride to nitrone 9 afforded alpha-allylated product 10a in high diastereoselectivity providing an easy entry to N-hydroxy-C1-alpha-allyl-substituted pyrrolidine iminosugar 4a after removal of protecting group, while N-O bond reductive cleavage in 10a afforded C1-alpha-allyl-pyrrolidine iminosugar 4b. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclic nitrone; Enzyme inhibitors; Iminosugars; pyrrolidine

Structural characterization of azoic dye hosted layered double hydroxides - Mandal, Sujata; Lerner, Dan A.; Marcotte, Nathalie; Tichit, Didier (Zeitschrift fur Kristallographie, 2009)
The removal of methyl orange (MO) from an aqueous solution was performed using layered double hydroxides (LDHs) in a move to develop cleaning processes of effluents contaminated with dye molecules. The intercalation of the guest anionic MO species into host M(II)/Al(III) LDHs differing by the nature of the divalent cations (M(II) = Mg, Ni or Zn) was achieved by anionic exchange of the initially NO(3)(-) present in the interlayer space and led to MO/LDH intercalation compounds. The exchange process was followed by XRD and UV-visible absorption spectroscopy at different stages. Almost all MO in solution is uptaken by the Mg-containing LDH in the concentration range corresponding to its anionic exchange capacity (AEC). A lower exchange is reached with the Ni- and Zn-containing LDHs, for which the diffusion of MO is limited due to a larger crystallite size. MO-Zn/Al LDH intercalation compounds exhibit the highest crystallinity and display a remarkable stacking of the layers at maximal MO exchange. This behaviour can be assigned to the higher intrinsic charge density of the host layers in agreement with its lower M(II)/Al(III) molar ratio (Zn(II)/Al(III) approximate to 1.5 whereas Mg(II)/Al(III) and Ni(II)/Al(III) = 2). The maximum amount of MO retained by the different LDHs is higher for Mg-containing LDH, than for Ni- and Zn-containing LDH, reaching respectively 1.15, 0.84 and 0.77 g/g.
Keywords: Anionic exchange; Depollution; layered double hydroxides; Methyl orange; X-ray diffraction

Studies on biological reduction of chromate by Streptomyces griseus - Poopal, Ashwini C.; Laxman, Ryali Seeta (Journal of Hazardous Materials, 2009)
Chromium is a toxic heavy metal used in various industries and leads to environmental pollution due to improper handling. The most toxic form of chromium Cr(VI) can be converted to less toxic Cr(III) by reduction. Among the actinomycetes tested for chromate reduction, thirteen strains reduced Cr(VI) to Cr(III), of which one strain of Streptomyces griseus (NCIM 2020) was most efficient showing complete reduction within 24h. The organism was able to use a number of carbon sources as electron donors. Sulphate, nitrate, chloride and carbonate had no effect on chromate reduction during growth while cations such as Cd, Ni, Co and Cu were inhibitory to varying degrees. Chromate reduction was associated with the bacterial cells and sonication was the best method of cell breakage to release the enzyme. The enzyme was constitutive and did not require presence of chromate during growth for expression of activity. Chromate reduction with cell free extract (CFE) was observed without added NADH. However, addition of NAD(P)H resulted in 2-3-fold increase in activity. Chromate reductase showed optimum activity at 28 degrees C and pH 7 (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bioreduction; Chromate reductase; Hexavalent chromium; Streptomyces griseus

Synthesis and characterization of CoCrxFe2-xO4 nanoparticles - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Lokhande, P. D.; Gajbhiye, N. S. (Journal of Alloys and Compounds, 2009)
Spinel-phase nanocrystalline CoCrxFe2-xO4 powders (0.0 <= x <= 2.0) were synthesized by citrate-gel precursor method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM). transmission electron microscopy (TEM) and infra-red spectroscopy (FT-IR). The XRD and selected-area electron diffraction (SAED) patterns indicated that the synthesized nanoparticles have single-phase spinet structure without the presence of any other impurities. The changes in electrical and magnetic properties of different stiochiometric compositions have also been investigated. It is seen that with increase in chromium contents, the measured magnetic hysteresis loops become narrow with decreasing trend in saturation magnetization. Electrical resistivity indicated that all the compounds are semiconducting nature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Magnetic measurements; Sintering; transmission electron microscopy; X-ray diffraction

Synthesis and characterization of high-surface-area Ag2O-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Philosophical Magazine Letters, 2009)
Nanosized tin dioxide-based powders containing silver and palladium oxides have been prepared by coprecipitation reaction. XRD, TEM, and XPS analysis were carried out for investigation of crystalline structure and surface morphology. The best reactive conditions were determined, such as the concentration of the reactants, pH value, surfactants, reaction temperature, and time. The material obtained is nanocrystalline, having a particle size in the range of 5.21-7.42 nm. Effect of doped-Ag2O on the crystal size of the nanoparticles and the influence of the presence of a second dopant (Pd) on the Ag2O/SnO2 matrix was discussed.
Keywords: Ag2O:SnO2; Nanomaterials; XPS

Synthesis of chiral sulfoxides by enantioselective sulfide oxidation and subsequent oxidative kinetic resolution using immobilized Ti-binol complex - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2009)
Chiral Ti-binol complex was immobilized onto ionic liquid modified SBA-15 and characterized by different physicochemical techniques. The catalyst was found to be highly enantioselective in the heterogeneous asymmetric oxidation of prochiral sulfides to sulfoxides and subsequent oxidative kinetic resolution of the sulfoxides using aqueous tert-butylhydroperoxide as the oxidant. A positive non-linear effect was observed in the oxidation-kinetic resolution of thioanisole using this supported catalyst. The supported catalyst was reused in multiple catalytic runs without any loss of enantioselectivity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Kinetic resolution; Mesoporous silica; Non-linear effect; Sulfides; Sulfoxides; Supported ionic liquid; Ti-binol

Synthesis of Sb-doped SnO2 nanowires and hyperbranched structures - Sathe, Bhaskar R.; Patil, Mrudula; Walke, Pravin S.; Vivek, J. P.; Lele, Ashish K.; Pillai, Vijayamohanan K.; Mulla, Imtiaz S. (Science of Advanced Materials, 2009)
Branched nanostructures of semiconducting materials are of great interest for their potential applications in optoelectronic, photonic devices and sensors. We herein describe a facile single-step chemical vapor deposition route for the synthesis of Sb-SnO2 hyperbranched nanostructures comprised of elongated nanowires with 30-40 nm diameter and 10-20 Am length. The morphology and structure has been characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), selective area electron diffraction (SAED), and powder X-ray diffraction (XRD). Also, a possible mechanism is proposed for the growth of nanowires into the hyperbranched form on the basis of the substrate effect, the role of Au nanoparticles, and the effect of Sb doping on specific morphology evolution. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron-transport mechanisms with activation energies of 0.55 and 0.17 eV, which correspond to pure SnO2 and Sb-SnO2 nanowires, respectively. A precise control over the operating parameters not only envisages custom-designed, branched structures by a simple and economical route but also offers an alternative method to the expensive and tedious nanofabrication techniques for industrial applications.
Keywords: Au Nanoparticles; chemical vapor deposition; Sb-SnO2 Hyperbranched Nanostructures

Vapour sensing with conductive polymer nanocomposites (CPC): polycarbonate-carbon nanotubes transducers with hierarchical structure processed by spray layer by layer - Lu, Jianbo; Kumar, Bijandra; Castro, Mickael; Feller, Jean-Francois (Sensors and Actuators B-Chemical, 2009)
The development of conductive polymer nanocomposite (CPC) sensors for volatile organic compounds (VOC) detection has been carried out using a spray layer by layer (LbL) process. This technique was successfully used to hierarchically structure polycarbonate-multiwall carbon nanotubes (PC-CNT) solutions into a double percolated architecture as attested by atomic force microscopy (AFM) and optical microscopy (OM). PC-CNT vapour sensing behaviour was investigated as a function of CNT content, films thickness, vapour flow and vapours solubility parameter. The response ranking A(r)(toluene)>A(r)(methanol)>A(r)(water)of PC-CNT was found to be coherent with kappa(12) Flory-Huggins interaction parameters provided that signals are normalised by analyte molecules number. Signals shape was interpreted to the light of Langmuir-Henry-Clustering (LHC) model and found to be proportional to vapour content. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Atomic force microscopy; carbon nanotube; Chemo-electrical behaviour; Conductive polymer nanocomposite; Vapour Sensing; Volatile organic compounds

Visible light induced photoreduction of methyl orange by N-doped mesoporous titania - Joshi, Meenal M.; Labhsetwar, Nitin K.; Mangrulkar, Priti A.; Tijare, Saumitra N.; Kamble, Sanjay P.; Rayalu, Sadhana S. (Applied Catalysis A-General, 2009)
N-doped mesoporous titania was synthesized using templating method. Biopolymer chitosan was used as a template and also as a nitrogen source along with ammonium hydroxide. Three different types of N-doped mesoporous titania were synthesized by varying composition of chitosan and titania precursor. These photocatalysts were characterized using XRD, BET-SA, FTIR, UV-DRS, SEM-EDX and XPS analysis. The photocatalytic activity of mesoporous titania was studied by methyl orange (MO) photoreduction reaction. From the experimental results it was observed that the N-doped mesoporous titania (1:2) gives the highest photocatalytic reduction of MO as compared to N-doped mesoporous titania prepared with (1:1) and (1:3) stoichiometry. This could be due to the optimal level of `N' incorporation in the N-doped mesoporous titania (1:2). Photocatalysts reduce the MO dye into derivative of hydrazine. Photoactivity of N-doped mesoporous titania (1:2) is 1.0721 mg of MO reduced per g of TiO2 vis-a-vis 0.508 mg of MO reduced per g of TiO2 for Degussa P25 photocatalyst. The effect of various operating parameters like photocatalyst loading. initial concentration and intensity of light also has been studied. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: biopolymer; Chitosan; MO photoreduction; N-doped mesoporous titania; Visible active photocatalyst

Abrupt shear thickening of aqueous solutions of hydrophobically modified poly(N,N `-dimethylacrylamide-co-acrylic acid) - Lele, Ashish K.; Shedge, Aarti; Badiger, Manohar V.; Wadgaonkar, Prakash; Chassenieux, Christophe (Macromolecules, 2010)
We report some new and interesting observations on the abrupt and large shear-induced thickening of aqueous solutions of hydrophobically modified poly(N,N'-dimethylacrylamide-co-acrylic acid). High molecular weight copolymer was prepared by free radical copolymerization of N,N'-dimethylacrylamide [DMA] and acrylic acid [AA] and was subsequently modified to different extents using a hydrophobic compound, namely, 3-pentadecylcyclohexylamine [3-PDCA], which is derived from a renewable resource material, cashew nutshell liquid [CNSL]. The structural elucidation of the base copolymer and the hydrophobically modified copolymers was performed by (1)H and (13)C NMR spectroscopy. The zero shear viscosities [eta(0)] of the hydrophobically modified polymers were lower than that of the precursor poly(N,N'-dimethylacrylamide-co-acrylic acid) until some critical polymer concentration, which increased with increase in hydrophobic modification. Above the critical concentrations, the eta(0) of the hydrophobically modified copolymers surpassed that of the precursor at the same concentration. At moderate shear rates some of these hydrophobically modified copolymers exhibited an abrupt shear-induced thickening in which the viscosity of the samples increased severalfold. We show here from creep experiments that thickening occurs only when the shear rate reaches a critical value, (gamma) over dot(crit), and that the thickened samples can be trapped in different metastable states by controlling the applied stress. Interestingly, the shear thickened samples showed further thickening upon decreasing the applied stress. Eventually, the metastable samples revert to their equilibrium states at characteristic time that depends on (small) probe stress.

Adsorption induced enzyme denaturation: the role of polymer hydrophobicity in adsorption and denaturation of alpha-chymotrypsin on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Lahari, Challa; Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Sontakke, Kalpana; Ingavle, Ganesh C.; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Langmuir, 2010)
Effects of changes in hydrophobicity of polymeric support oil structure and activity of alpha-chymotrypsin (E.C.3.4.21.1) have been studied with copolymers of allyl glycidyl ether (AGE) and ethylene glycol dimethacrylate (EGDM) with increasing molar ratio of EGDM to AGE (cross-link density 0.05 to 1.5). The enzyme is readily adsorbed front aqueous buffer at room temperature following Langmuir adsorption isotherms in unexpectedly large amounts (25% w/w). Relative hydrophobicity of the copolymers has been assessed by studying adsorption of naphthalene and Fmoc-methionine by the series of copolymers from aqueous solutions. Polymer hydrophobicity appears to increase linearly oil increasing cross-link density from 0.05 to 0.25. Further increase in cross-link density Causes a decrease in naphthalene binding but has little effect on binding of Fmoc-Met. Binding of alpha-chymotrypsin to these copolymers follow the trend for Fmoc-methionine binding, rather than naphthalene binding, indicating involvement of polar interactions along with hydrophobic interactions during binding of protein to the polymer. The adsorbed enzyme undergoes extensive denaturation (ca. 80%) with loss of both tertiary and secondary structure on contact with the copolymers as revealed by fluorescence, CID and Raman spectra of the adsorbed protein. Comparison of enzyme adsorption behavior with Eupergit C, macroporous Amberlite XAD-2, and XAD-7 Suggests that polar interactions of the EGDM ester functional groups with the protein play a significant role in enzyme denaturation.

Adsorption of fluoride from aqueous solution by alumina of alkoxide nature: batch and continuous operation - Kamble, Sanjay P.; Deshpande, Gunavant; Barve, Prashant P.; Rayalu, Sadhana; Labhsetwar, Nitin K.; Malyshew, Alexander; Kulkarni, Bhaskar D. (Desalination, 2010)
In this investigation, we report the adsorption potential of alkoxide origin alumina for defluoridation of drinking water using batch and continuous mode of operations. The effects of different operating parameters such as adsorbent dose, initial fluoride concentration, pH of the solution and interfering ions (usually present in groundwater) were studied with a view to understand the adsorption behavior of the material under various conditions. A thermodynamic study shows that the adsorption of fluoride by alkoxide origin alumina is an exothermic and spontaneous process. The kinetic results showed that the fluoride sorption follows pseudo-second-order kinetics. The applicability of adsorbent in the field is also tested through column breakthrough studies. It has been observed that with an increase in the flow rate and initial fluoride concentration, the breakthrough curve becomes sharper and the breakthrough time and adsorbed fluoride ion concentration decrease. The breakthrough curve also becomes steeper as the bed height increases. The alkoxide origin alumina based adsorbent media can be used directly for field applications since it is also commercially available in granular form. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Alkoxide alumina; Breakthrough studies; Fluoride; Kinetic modeling

Antibacterial & antiplasmid activities of Helicteres isora L. - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Dhakephalkar, Prashant K.; Rojatkar, Supada; Shitole, Mahadeo G. (Indian Journal of Medical Research, 2010)
Background & objectives: The multiple drug resistance (MDR) is a serious health problem and major challenge to the global drug discovery programmes. Most of the genetic determinants that confer resistance to antibiotics are located on R-plasmids in bacteria. The present investigation was undertaken to investigate the ability of organic extract of the fruits of Helicteres isora to cure R-plasmids from certain clinical isolates. Methods: Active fractions demonstrating antibacterial and antiplasmid activities were isolated from the acetone extracts of shade dried fruits of H. isora by bioassay guided fractionation. Minimal inhibitory concentration (MIC) of antibiotics and organic extracts was determined by agar dilution method. Plasmid curing activity of organic fractions was determined by evaluating the ability of bacterial colonies (pre treated with organic fraction for 18 h) to grow in the presence of antibiotics. The physical loss of plasmid DNA in the cured derivatives was further confirmed by agarose gel electrophoresis. Results: The active fraction did not inhibit the growth of either the clinical isolates or the strains harbouring reference plasmids even at a concentration of 400 mu g/ml. However, the same fraction could cure plasmids from Enterococcus faecalis, Escherichia coli, Bacillus cereus and E. coli (RP4) at curing efficiencies of 14, 26, 22 and 2 per cent respectively. The active fraction mediated plasmid curing resulted in the subsequent loss of antibiotic resistance encoded in the plasmids as revealed by antibiotic resistance profile of cured strains. The physical loss of plasmid was also confirmed by agarose gel electrophoresis. Interpretation & conclusions: The active fraction of acetone extract of H. isora fruits cured R-plasmids from Gram-positive and Gram-negative clinical isolates as well as reference strains. Such plasmid loss reversed the multiple antibiotic resistance in cured derivatives making them sensitive to low concentrations of antibiotics. Acetone fractions of H. isora may be a source to develop antiplasmid agents of natural origin to contain the development and spread of plasmid borne multiple antibiotic resistance.
Keywords: antibacterial activity; Antibiotic resistance; antiplasmid activity; Helicteres isora; multiple drug resistance; plasmid-curing

Chronic inflammatory responses to microgel-based implant coatings - Bridges, Amanda W.; Whitmire, Rachel E.; Singh, Neetu; Templeman, Kellie L.; Babensee, Julia E.; Lyon, L. Andrew; Garcia, Andres J. (Journal of Biomedical Materials Research, 2010)

Colossal thermoelectric power in Gd-Sr manganites - Sagar, S.; Ganesan, V.; Joy, Pattayil Alias; Thomas, Senoy; Liebig, A.; Albrecht, M.; Anantharaman, Maliemadom R. (EPL, 2010)
Manganites belonging to the series Gd(1-x)Sr(x)MnO(3) (x=0.3, 0.4 and 0.5) were prepared by wet solid-state reaction and their thermoelectric power was evaluated. Thermoelectric power measurements revealed a peak value at similar to 40 K. All the samples exhibited a colossal thermopower at similar to 40K and in that Gd(0.5)Sr(0.5)MnO(3) exhibited a maximum value of similar to 35 V/K, which is the largest reported for these class of materials at this temperature. Temperature-dependent magnetisation measurements showed that the samples exhibit a phase transition from paramagnetic to spin-glass-like state at these temperatures. Plausible mechanisms responsible for the observed colossal thermoelectric power in Gd-Sr manganites are discussed. Copyright (C) EPLA, 2010

Effect of leakage current and dielectric constant on single and double layer oxides in MOS structure - Laha, Pinaki; Panda, A. B.; Dahiwale, S.; Date, Kalyani S.; Patil, K. R.; Barhai, P. K.; Das, A. K.; Banerjee, Indrani; Mahapatra, S. K. (Thin Solid Films, 2010)
MOS structure of Al/Al2O3/n-Si, Al/TiO2/n-Si and Al/Al2O3/TiO2/n-Si was obtained by deposition of Al2O3 and TiO2 on silicon substrate by RF Magnetron Sputtering system. The total thickness of the oxide layer similar to 40 +/- 5 nm in the MOS structure was kept constant. Samples were characterized by X-Ray diffraction (XRD). X-Ray photoelectron spectroscopy (XPS), Impedance analyzer and Current-voltage (J-V) characteristics. The variations in the dielectric constant and tan 8 of the MOS capacitor in the frequency range of 1000Hz-1MHz were measured by impedance analyzer. The variation in dielectric constant of the Al/Al2O3/TiO2/n-Si multilayer compared to single layer of Al/Al2O3/n-Si and Al/TiO2/n-Si is due to high probability of defects, lattice mismatch and interface interactions. The steep rise of Tan 6 values in the Al/Al2O3/TiO2/n-Si structure is due to the resonance effect of both Al2O3 and TiO2 layers. The leakage current mechanisms of MOS structures were extracted from Schottky coefficient and Poole-Frenkel coefficient. Theoretical values of Schottky coefficients (beta(SC)) and Poole-Frenkel coefficients (beta(PF)) for each sample were estimated using the real part of the dielectric constant. The experimental values were calculated from J-V characteristics and compared with theoretical values. The appropriate model has been proposed. It was found that Schottky and Poole-Frenkel mechanisms are applicable at low and high field respectively for all MOS structures. The combination of Al/Al2O3/TiO2/n-Si is found to be a promising structure with high dielectric constant and low leakage current suitable for MOS devices. (C) 2010 Elsevier B.V. All rights reserved.
37th International Conference on Metallurgical Coatings and Thin Films, San Diego, CA, APR 26-30, 2010
Keywords: Al2O3; dielectric constant; Leakage current; MOS device; Poole-Frenkel emission; Schottky emission; TiO2

Effect of nanoparticle conjugation on gene silencing by RNA interference - Singh, Neetu; Agrawal, Amit C.; Leung, Anthony K. L.; Sharp, Phillip A.; Bhatia, Sangeeta N. (Journal of American Chemical Society, 2010)

Elucidation of the role of hexamine and other precursors in the formation of magnetite nanorods and their stoichiometry - Singh, Hema; Bhagwat, Shrikant; Jouen, Samuel; Lefez, Benoit; Athawale, Anjali A.; Hannoyer, Beatrice; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2010)
Hexamine is known to assist anisotropic growth of metal oxides and the same is also found to be true for magnetite nanosynthesis. In this work we elucidate the role of hexamine and other precursors in the formation of magnetite nanorods by the hydrothermal route and their stoichiometry. Various others hydrolyzing agents such as sodium hydroxide (NaOH), sodium hydroxide + hexamine, ammonia (NH(3)), ammonia + formaldehyde are also studied. The synthesized nanoparticles are characterized with the help of various techniques such as X-ray diffraction (XRD), FT-IR spectroscopy, UV-VIS-NIR spectroscopy, transmission electron microscopy (TEM), Mossbauer spectroscopy and SQUID magnetization measurements. It is found that only when ferric chloride, ferrous ammonium sulfate (FAS) and hexamine are used, well defined nanorods are formed. When sodium hydroxide and hexamine are used as a hydrolyzing system nearly spherical nanoparticles with small size (similar to 13 nm) are formed, as compared to the case of sodium hydroxide alone which leads to bigger cube like nanoparticles. Interestingly the decomposition products of hexamine do not lead to nanorod formation. Thus, slow decomposition of hexamine at elevated temperature and the consequent slow rise in pH is the key to the anisotropic growth of the iron oxide system.

Enhanced production of gibberellin A(4) (GA(4)) by a mutant of Gibberella fujikuroi in wheat gluten medium - Lale, Geetanjali; Gadre, Ramchandra V. (Journal of Industrial Microbiology & Biotechnology, 2010)
Mutants of Gibberella fujikuroi with different colony characteristics, morphology and pigmentation were generated by exposure to UV radiation. A mutant, Mor-189, was selected based on its short filament length, relatively high gibberellin A(4) (GA(4)) and gibberellin A(3) (GA(3)) production, as well as its lack of pigmentation. Production of GA(4) by Mor-189 was studied using different inorganic and organic nitrogen sources, carbon sources and by maintaining the pH of the fermentation medium using calcium carbonate. Analysis of GA(4) and GA(3) was done by reversed-phase high-performance liquid chromatography and LC-MS. The mutants of G. fujikuroi produced more GA(4) when the pH of the medium was maintained above 5. During shake flask studies, the mutant Mor-189 produced 210 mg l(-1) GA(4) in media containing wheat gluten as the nitrogen source and glucose as the carbon source. Fed-batch fermentation in a 14 l agitated fermenter was performed to evaluate the applicability of the mutant Mor-189 for the production of GA(4). In 7-day fed-batch fermentation, 600 mg l(-1) GA(4) were obtained in the culture filtrate. The concentration of GA(4) and GA(3) combined was 713 mg l(-1), of which GA(4) accounted for 84% of the total gibberellin. These values are substantially higher than those published previously. The present study indicated that, along with maintenance of pH and controlled glucose feeding, the use of wheat gluten as the sole nitrogen source considerably enhances GA(4) production by the mutant Mor-189.
Keywords: Fermentation; GA(4); Gibberella fujikuroi; Mutant; Wheat gluten

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Facile synthesis of N-substituted maleimides - Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Chaudhary, Preeti M. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
A simple and efficient method for the synthesis of N-substituted malemides from the corresponding maleamie acids under the phase transfer catalysis has been described
Keywords: Maleamic acids; maleimides; phase transfer catalysis; synthesis

High current density, low threshold field emission from functionalized carbon nanotube bucky paper - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Late, Dattatray J.; Chavan, Padmakar G.; Sheini, Farid J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2010)
Field emission studies of bucky paper of multiwalled carbon nanotubes (MWNTs), prepared after microwave (MW) assisted acid functionalization are reported along with a comparison with that of ``as-grown'' sample. MW treated bucky papers reveal an interesting linear field emission behavior in Fowler-Nordheim plot. The field emission currents at preset value are found to be remarkably stable over a period of more than 3 h sustaining current densities of 4.9 mA/cm(2) and 8.5 mA/cm(2) for ``as-grown'' and functionalized sample, respectively. The enhancement in the field emission due to functionalization has been discussed in terms of tip opening and defect induced charge transport caused by intershell and intertubular interaction. (C) 2010 American Institute of Physics. [doi:10.1063/1.3479049]
Keywords: Carbon nanotubes; current density; field emission; fullerenes

Hydroformylation of 1-octene using [Bmim][PF6]-decane biphasic media and rhodium complex catalyst: thermodynamic properties and kinetic study - Sharma, Amit; Lebigue, Carine Julcour; Deshpande, Raj Madhukar; Kelkar, Ashutosh A.; Delmas, Henri (Industrial & Engineering Chemistry Research, 2010)
A chemical reaction engineering approach is reported to investigate the biphasic hydroformylation of I-octene using [bmim][PF6] ionic liquid. It is based both on a process parameter investigation (temperature, concentrations, and pressures) and a thermodynamic study of the reaction medium (gas liquid and liquid liquid equilibria). Initial rate data show complex behavior with respect to operating parameters and are best described by a rate equation based on a mechanistic model. Complete reaction scheme including isomerization is then modeled accounting from the time dependent concentration of the organic substrates measured in organic phase and recalculated in ionic liquid phase from liquid liquid equilibria.
21st International Symposium on Chemical Reaction Engineering (ISCRE 21), Philadelphia, PA, JUN 13-16, 2010

Hydrogen evolution by a low cost photocatalyst: bauxite residue - Mangrulkar, Priti A.; Joshi, Meenal V.; Kamble, Sanjay P.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
Bauxite residue or red mud which is an aluminium industry waste has been used as a novel low cost photocatalyst active in visible light for the generation of hydrogen from water. The driving force behind the use of bauxite residue as a photocatalyst is not only the fact that it is widely available but also bauxite residue is a fine grained mixture of oxides and hydroxides (Fe(2)O(3), TiO(2), SiO(2), and Al(2)O(3), Al(OH)3). The photocatalyst was characterized with respect to BET-SA, UV-DRS, XRD, SEM and EDX. Hydrogen yield of 4600 mu mol/h/g of TiO(2) was achieved as compared to hydrogen evolution rate of 164 mu mol/h/g of TiO(2) for commercially available titania Degussa P-25. However, the hydrogen evolution was 20.85 mu mol/h/g of photocatalyst. The results suggest that bauxite residue appears to be a novel low cost photocatalyst. The various operating conditions of photocatalytic hydrogen generation were studied which include amount of catalyst, illumination intensity, illumination time, effect of various sacrificial donors etc. (C) 2009 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: Aluminium industry waste; Bauxite residue; Hydrogen generation; Red mud; Sacrificial donors

Hydrophobically modified poly(vinyl alcohol) using alkoxy-substituted methyl gallate: synthesis and rheology - Shedge, Aarti S.; Wadgaonkar, Prakash P.; Lele, Ashish K.; Badiger, Manohar V. (Journal of Polymer Science Part B-Polymer Physics, 2010)
Hydrophobically modified poly(vinyl alcohol) (HMPVA) polymers were synthesized by potassium t-butoxide-catalyzed reaction of PVA with methyl 3,4,5-tris(n-octyloxy) benzoate (MGC(8))/3,4,5-tris(n-dodecyloxy) benzoate (MGC(12)) and 1,3-propane sultone. The concentration of 1,3-propane sultone was kept constant at 10 mol %. and that of MGC(8) (2, 3, and 4 mol %)/MGC(12) (2 and 3 mol %) was varied to obtain HMPVAs with different hydrophobic contents. The incorporation of MGC(8)/MGC(12) and 1,3-propane sultone onto HMPVA was confirmed by NMR spectroscopy. Rheological properties of aqueous solutions also confirmed the presence of hydrophobic and charged functional groups on HMPVAs. In the semidilute regime, the specific viscosity of HMPVAs followed concentration scaling that is typical of polyelectrolytes. At higher concentrations, the HMPVA solutions with 3 and 4 mol % of MGC(8) exhibited large increase in specific viscosity. Oscillatory experiments on these solutions exhibited gel-like behavior at polymer concentrations of 40-50 g/L. Confocal microscopy images of HMPVA with 4 mol % of MGC(8) clearly indicated the existence of microgels. The tendency of formation of microgels further increased with increasing chain length of the hydrophobe, that is, with MGC(12). These samples exhibited rheological behavior that is typical of soft solids and was therefore probed by the strain-rate frequency superposition technique reported recently in the literature. HMPVAs with improved rheological properties show potential applications as thickeners in cosmetic creams, lotions and as drug carriers in pharmaceutical formulations. (C) 2010 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 48: 1054-1063, 2010
Keywords: gallic acid; hydrophobically modified poly(vinyl alcohol); Rheology; water-soluble polymers

Influence of zeolitic structure on photoreduction property and hydrogen evolution reaction - Chatti, Ravikrishna V.; Dubey, Nidhi; Joshi, Meenal V.; Labhsetwar, Nitin K.; Joshi, P. N.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
A new photocatalytic material developed by supporting TiO(2) in combination with transition metal ion like cobalt and heteropolyacid (HPA) on the surface is facilitating enhanced photoreduction of water and methyl orange Zeolites being a solid acid play an important role in the electron transfer reaction, facilitated by the Lewis acid sites in the form of aluminium ions In the present work, four different zeolite matrices namely, NaY zeolite, ultrastable zeolite Y, beta zeolite and titanium silicate-1 have been used for the synthesis of new photocatalytic materials These materials have been evaluated for water splitting by an initial screening procedure using methyl orange photoreduction The photocatalyst containing Na Y has emerged as a potential photocatalyst with hydrogen evolution rate of 2730 mu mol/h/g of TiO(2) Hydrogen evolution was not observed for the composite photocatalysts synthesized using the other zeolite matrices It has been observed that physicochemical properties like Si/Al ratio, acidity and basicity of the zeolite support have a tremendous influence on the photoreduction property of these zeolite matrices (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: H(2) evolution; Lewis acidity; Si/Al ratio; water splitting; Zeolite structure

Phylogeographical studies in disjunct populations of symplocos laurina wall. using cytoplasmic PCR-RFLP approach - Banu, Sofia; Lagu, Meena D.; Gupta, Vidya S. (Tree Genetics & Genomes, 2010)
Genetic variation, haplotype relationships, and potential regions of diversity in Symplocos laurina Wall. (Symplocaceae), a montane tree species from India, have been tested using molecular and biogeographical data to infer phylogeographic patterns. The polymerase chain reaction-restriction fragment length polymorphism technique was used to determine the chloroplast (cp) and mitochondrial (mt) DNA haplotypes of 218 individuals from 12 populations, collected from Northeast India (NEI), which is a part of Indo-Burma biodiversity hotspot, and South India, which includes the Western Ghats (WG), another biodiversity hotspot from India and Eastern Ghats (EG). Nine cpDNA (chlorotypes) and 24 mtDNA haplotypes (mitotypes) were identified; the WG region was identified as the most diverse for chlorotypes and the NEI region for mitotypes. Although a strong population differentiation was observed, phylogeographic structure was found to be absent for both the genomes. The haplotype network revealed the presence of two main lineages: NEI-WG lineage and EG lineage, largely without overlapping distributions. The study tests two hypotheses, namely vicariance and dispersal, to understand the distribution of plants in India. The population structure of S. laurina strongly suggests the persistence of the species in putative refugial areas preglaciation and further establishment of other populations of S. laurina from these refugial populations.
Keywords: Cytoplasmic genome; Genetic diversity; Phylogeography

Polyarylate based thin film composite (TFC) membranes: effects of coating parameters, gutter layer, and intrinsic material properties - Chendake, Yogesh J.; Bhole, Yogesh S.; Lohokare, Harshada R.; Kharul, Ulhas K. (Separation Science and Technology, 2010)
Investigations in thin film composite (TFC) membrane formation with polyacrylonitrile ultrafiltration membrane as a support and three polyarylates with sequentially increased polarity are reported. Effects of TFC membrane preparation parameters viz., concentration of the coating solution, dip time, presence of solvent in pores of UF membrane support, and presence of the gutter layer were examined towards the formation of the selective skin layer, which was assessed by gas permeation analysis. TFC membranes prepared using dimethyl bisphenol-A based polyarylate exhibited similar to 3 orders of magnitude higher permeability and comparable selectivity as that of its dense membrane.
Keywords: Gas permeation; gutter layer; polarity; polyarylates; TFC membrane

QTL mapping of 1000-kernel weight, kernel length, and kernel width in bread wheat (Triticum aestivum L.) - Ramya, P.; Chaubal, A.; Kulkarni, K.; Gupta, L.; Kadoo, Narendra Y.; Dhaliwal, Harcharan Singh; Chhuneja, Parveen; Lagu, Meena D.; Gupta, V. (Journal of Applied Genetics, 2010)
Kernel size and morphology influence the market value and milling yield of bread wheat (Triticum aestivum L.). The objective of this study was to identify quantitative trait loci (QTLs) controlling kernel traits in hexaploid wheat. We recorded 1000-kernel weight, kernel length, and kernel width for 185 recombinant inbred lines from the cross Rye Selection 111 x Chinese Spring grown in 2 agro-climatic regions in India for many years. Composite interval mapping (CIM) was employed for QTL detection using a linkage map with 169 simple sequence repeat (SSR) markers. For 1000-kernel weight, 10 QTLs were identified on wheat chromosomes 1A, 1D, 2B, 2D, 4B, 5B, and 6B, whereas 6 QTLs for kernel length were detected on 1A, 2B, 2D, 5A, 5B and 5D. Chromosomes 1D, 2B, 2D, 4B, 53 and 5D had 9 QTLs for kernel width. Chromosomal regions with QTLs detected consistently for multiple year-location combinations were identified for each trait. Pleiotropic QTLs were found on chromosomes 2B, 2D, 4B, and 5B. The identified genomic regions controlling wheat kernel size and shape can be targeted during further studies for their genetic dissection.
Keywords: composite interval mapping; kernel shape; kernel size; quantitative trait loci; Stable QTLs; Triticum aestivum

Renewable H-2 from glycerol steam reforming: effect of La2O3 and CeO2 addition to Pt/Al2O3 catalysts. - Montini, Tiziano; Singh, Rakesh; Das, Piyali; Lorenzut, Barbara; Bertero, Nicolas; Riello, Pietro; Benedetti, Alvise; Giambastiani, Giuliano; Bianchini, Claudio; Zinoviev, Sergey; Miertus, Stanislav; Fornasiero, Paolo (Chemsuschem, 2010)
Glycerol is the main byproduct of biodiesel production and its increased production volume derives from the increasing demand for biofuels. The conversion of glycerol to hydrogen-rich mixtures presents an attractive route towards sustainable biodiesel production. Here we explored the use of Pt/Al2O3-based catalysts for the catalytic steam reforming of glycerol, evidencing the influence of La2O3 and CeO2 doping on the catalyst activity and selectivity. The addition of the latter metal oxides to a Pt/Al2O3 catalyst is found to significantly improve the glycerol steam reforming, with high H-2 and CO2 selectivities. A good catalytic stability is achieved for the Pt/La2O3/Al2O3 system working at 350 degrees C, while the Pt/CeO2/Al2O3 catalyst sharply deactivates after 20 h under similar conditions. Studies carried out on fresh and exhausted catalysts reveal that both systems maintain high surface areas and high Pt dispersions. Therefore, the observed catalyst deactivation can be attributed to coke deposition on the active sites throughout the catalytic process and only marginally to Pt nanoparticle sintering. This work suggests that an appropriate support composition is mandatory for preparing high-performance Pt-based catalysts for the sustainable conversion of glycerol into syngas.
Keywords: biofuels; Glycerol; heterogeneous catalysis; platinum; supported catalysts

Room temperature synthesis of rutile TiO2 hierarchical nanoneedle flower morphology for dye sensitized solar cell - Hyam, Rajeshkumar S.; Bhosale, Reshma K.; Lee, Wonjoo; Han, Sung-Hwan; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2010)
Rutile TiO2 nanoneedle flowers (representing concurrent nano-micro hierarchical morphology) with high shape anisotropy ratio are synthesized at room temperature by using a simple and efficient one step electrochemical process of anodic dissolution. This process employs highly acidic bath of perchloric acid (pH < 2) and a large current density on the surface of Titanium foil to form nanostructures. The diameter and length of rutile TiO2 nanoneedle is similar to 8 nm and 100 nm respectively (aspect ratio > 10). Dye sensitized solar cell (DSSC) configured using such rutile TiO2 flowers is shown to exhibit IPCE of 30% and power conversion efficiency of similar to 3.6%.
Keywords: Anodization; DSSC; Nanoneedles; Rutile TiO2

Small molecule inhibition of phosphatidylinositol-3,4,5-triphosphate (PIP3) binding to pleckstrin homology domains - Miao, Benchun; Skidan, Igor; Yang, Jinsheng; Lugovskoy, Alexey; Reibarkh, Mikhail; Long, Kai; Brazell, Tres; Durugkar, Kulbhushan A.; Maki, Jenny; Ramana, C. V.; Schaffhausen, Brian; Wagner, Gerhard; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The PI3-kinase (PI3K) pathway regulates many cellular processes, especially cell metabolism, cell survival, and apoptosis. Phosphatidylinositol-3,4,5-trisphosphate (PIP3), the product of PI3K activity and a key signaling molecule, acts by recruiting pleckstrin-homology (PH) domain-containing proteins to cell membranes. Here, we describe a new structural class of nonphosphoinositide small molecule antagonists (PITenins, PITs) of PIP3-PH domain interactions (IC50 ranges from 13.4 to 31 mu M in PIP3/Akt PH domain binding assay). PITs inhibit interactions of a number of PIP3-binding PH domains, including those of Akt and PDK1, without affecting several PIP2-selective PH domains. As a result, PITs suppress the PI3K-PDK1-Akt pathway and trigger metabolic stress and apoptosis. A PIT-1 analog displayed significant antitumor activity in vivo, including inhibition of tumor growth and induction of apoptosis. Overall, our studies demonstrate the feasibility of developing specific small molecule antagonists of PIP3 signaling.
Keywords: Anticancer; PIP3 antagonist

Strain-rate frequency superposition in large-amplitude oscillatory shear - Kalelkar, Chirag; Lele, Ashish K.; Kamble, Samruddhi (Physical Review E, 2010)
In a recent work, Wyss et al. [Phys. Rev. Lett. 98, 238303 (2007)] have noted a property of ``soft solids'' under oscillatory shear, the so-called strain-rate frequency superposition. We extend this study to the case of soft solids under large-amplitude oscillatory shear (LAOS). We show results from LAOS studies in a mono-disperse hydrogel suspension, an aqueous gel, and a biopolymer suspension and show that constant strain-rate frequency sweep measurements with soft solids can be superimposed onto master curves for higher harmonic moduli with the same shift factors as for the linear viscoelastic moduli. We show that the behavior of higher harmonic moduli at low frequencies in constant strain- rate frequency sweep measurements is similar to that at large strain amplitude in strain- amplitude sweep tests. We show surface plots of the harmonic moduli and the energy dissipation rate per unit volume in LAOS for soft solids and show experimentally that the energy dissipated per unit volume depends on the first harmonic loss modulus alone, in both the linear and the nonlinear viscoelastic regime.

Structural diversity in manganese, iron and cobalt complexes of the ditopic 1,2- bis(2,2’-bipyridyl-6-yl)ethyne ligand and observation of epoxidation and catalase activity of manganese compounds - Madhu, Vedichi; Ekambaram, Balaraman; Shimon, Linda J. W.; Diskin, Yael; Leitus, Gregory; Neumann, Ronny (Royal Society of Chemistry, 2010)
A ditopic 1,2-bis(2,2′-bipyridyl-6-yl)ethyne ligand, L, has been synthesized for the first time by consecutive Suzuki and Sonogashira coupling reactions either in a one- or two-step synthesis. Coordination of L with some first-row transition metals, Fe, Mn and Co showed a very rich structural diversity that can be obtained with this ligand. Reaction of L with MnII(OAc)2 yielded a dimanganese(II) complex, [Mn2L(μ-OAc)3]PF6, (1) where the two somewhat inequivalent trigonal-bipyramidal Mn atoms separated by 3.381 Å are bridged by L and three acetate moieties. A similar reaction of L with MnIII(OAc)3 yielded a very different dimanganese complex [Mn2L′(OH)(OAc)2(DMF)2]PF6·DMF (2) where L′ is a E-1,2-bis(2,2′-bipyridyl-6-yl)ethene fragment that was formed in situ. The L′ ligand bridges between the two Mn centers, despite its trans configuration, which leads to a very strained ethene bridging moiety. The Mn atoms are also bridged by two acetate ligands and a hydroxy group that bridges between the Mn atoms and the ethene fragment; DMF completes the octahedral coordination around each Mn atom which are separated by 3.351 Å. A comproportionation reaction of L with MnII(OAc)2 and n-Bu4NMnO4 yielded a tetramanganese compound, [Mn4(μ3-O)2(OAc)4(H2O)2L2](PF6)2·2CH3CN (3). Compound 3 has a dimer of dimers structure of the tetranuclear Mn core that consists of binuclear [Mn2O(OAc)2L]+ fragment and a PF6 anion. BVS calculations indicate that 3 is a mixed-valent 2MnII plus 2MnIII compound where two [MnII2O(OAc)2L]+ fragments are held together by MnIII–O inter-fragment linkers which have a distorted octahedral geometry. The Mn atoms in the [Mn2O(OAc)2L]+ fragments have a capped square-pyramid configuration where an aqua ligand is capped on one of the faces. Although the aqua ligand is well within a bonding distance to a carbon atom of the proximal ethyne bridge, there does not appear to be an oxygen–carbon bond formation, rather the ligand is constrained in this position, as deduced by the observation that the bond lengths and angles of the ligand are essentially the same as those for the free ligand, L. Reaction of L with perchlorate or triflate salts of Fe(II), Mn(II) and Co(II) in dry acetonitrile yielded binuclear triple helicate structures (2[thin space (1/6-em)]:[thin space (1/6-em)]3 metal to L ratios) [Fe2L3](CF3SO3)4·CH3CN (4), [Mn2L3](ClO4)4·1.7CH3CN·1.65EtOEt (5) and [Co2L3](ClO4)4·2CH3CN·2EtOEt (6) where each M(II) center with a slightly distorted octahedral geometry is bridged by three of the ditopic ligands. The M–M distances varied; 5.961 Å (Mn), 6.233 Å (Co) 6.331 Å (Fe). Reaction of L with Co(ClO4)2·6H2O in wet acetonitrile yielded a dicobalto(III) compound, [Co2L′3(O)2](ClO4)2·H2O (7), with two types of L′ fragments; one bridging between the two Co centers and two non-bridging ligands, each bonded to a Co atom via one bipyridyl group where the other is non-bonding. The octahedral coordination sphere around each Co atom is completed by the formation of a cobalt–carbon bond from the two carbon atoms of the ethene moiety of the bridging ligand and by a hydroxy moiety that is also bonded to the ethene group of the non-bridging ligand. Reaction of L with Co(ClO4)2·6H2O in dry acetonitrile in the presence of Et3N yielded the tetracobalto(II) complex {[Co2L4(OH)4](ClO4)4}2 (8) with a unique twisted square configuration of cobalt ions with Co–Co distances of 3.938 to 4.131 Å. In addition to the L bridging ligand the Co atoms are linked by hydroxy moieties. Some preliminary catalytic studies showed that the Mn compounds 1 and 2 were active (high yield within 3 min) for alkene epoxidation with peracetic acid and hydrogen peroxide dismutation (catalase activity).

Structure and gelation mechanism of silk hydrogels - Nagarkar, Shailesh; Nicolai, Taco; Chassenieux, Christophe; Lele, Ashish K. (Physical Chemistry Chemical Physics, 2010)
Silk fibroin was regenerated from cocoons produced by the silkworm Bombyx Mori. Light scattering showed that an aqueous solution of the regenerated silk fibroin (RSF) was made of individual proteins with a weight average molar mass of about 4 x 10(5) g mol(-1) and a hydrodynamic radius of about 10 nm. Gel formation of RSF in acidic solutions was investigated as a function of the pH (2-4), concentration (0.5-10 g L(-1)) and temperature (5-70 degrees C). The structure of the gels was studied using light scattering and confocal laser scanning microscopy. The structure was found to be self-similar from length scales of less than 15 nm up to length scales of about 1 mm, and characterized by a correlation length of a few microns. Gel formation was tracked using turbidity, rheology, light scattering and circular dichroism. Gelation involves the formation of self-similar aggregates with a growth rate that increases exponentially. The protein aggregation is correlated to, and perhaps caused by, the formation of beta-sheets, the fraction of which also increases exponentially with time.

Synthesis of acrolein by gas-phase dehydration of glycerol over silica supported bronsted acidic ionic liquid catalysts - Munshi, Mudassir K.; Lomate, Samadhan T.; Deshpande, Raj Madhukar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Chemical Technology and Biotechnology, 2010)
BACKGROUND: Glycerol has become readily available as a byproduct from the biodiesel industry. High functionality and relatively low price make it a potential building block to produce value-added derivatives such as acrolein. RESULTS: Dehydration of glycerol to acrolein was performed over several silica supported Bronsted acidic ionic liquids as catalysts. All the catalysts prepared were active for the synthesis of acrolein (conversion of glycerol was observed in the range 35-90% with selectivity to acrolein in the range 29-58%). CONCLUSIONS: Catalyst prepared from triphenyl (3-sulfopropyl) phosphonium 4-methylbenzenesulfonate gave good activity and selectivity at 4 h reaction time. The conversion of glycerol decreased with increase in glycerol concentration. Higher temperature (325 degrees C) resulted in significantly lower conversion as well as selectivity to acrolein. With the use of two additional traps cooled to -7 degrees C, the selectivity to acrolein increased significantly for good catalysts. (C) 2010 Society of Chemical Industry
Keywords: acidic ionic liquids; acrolein; glycerol dehydration; supported catalyst

Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans via a two-step sequential Michael-Evans aldol cyclization strategy: total synthesis of (+)-magnolone - Pandey, Ganesh; Luckorse, Srikanth; Budakoti, Asha; Puranik, Vedavati G. (Tetrahedron Letters, 2010)
Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans is described employing a two-step Michael-Evans aldol cyclization strategy. The approach is successfully applied for the total synthesis of furano lignan natural product (+)-magnolone. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: HWE reaction; Lignans; Magnolone; Michael-Evans aldol reaction; Tetrahydrofuran

Total synthesis of tropinone using 1,3-dipolar cycloaddition of cyclic azomethine ylide and phenyl vinyl sulfone as the key step - Laha, Joydev K. (Chemistry of Natural Compounds, 2010)
Total synthesis of tropinone from the readily available piperidone 2 is described. The rapid assembly of the tropane skeleton was achieved by 1,3-dipolar cycloaddition of cyclic azomethine ylide 3 to phenyl vinyl sulfone.
Keywords: 1; 3-dipolar cycloaddition; cyclic azomethine ylide; phenyl vinyl sulfone; tropane alkaloids; tropinone

Understanding the genetic structure of symplocos laurina wall. populations using nuclear gene markers - Banu, Sofia; Bhagwat, Rasika M.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, V. S. (Genetica, 2010)
To characterize the genetic diversity of present populations of Symplocos laurina, which grow in the montane forests in India, we analyzed the DNA sequences of a nuclear gene. Using the 881 bp sequence of cytosolic Glyceraldehyde-3-phosphate dehydrogenase gene, we detected 24 haplotypes among 195 individuals sampled from 14 populations. Two dominant haplotypes were distributed over the entire range of this species in India and several private haplotypes were found. Low genetic diversity within population, high differentiation, number of population specific haplotypes and deviation from neutral evolution characterized the present populations of S. laurina. An analysis of molecular variance indicated the presence of geographic structure within the haplotype distribution. The occurrence of S. laurina preglaciation in India is the most parsimonious explanation for the current geographic structure observed. The populations are presumably ancient and might have spread across its extant distribution range in India through a recent range expansion event.
Keywords: GapC; Genetic diversity; Glaciation; Refugium

ZnO-beta zeolite: as an effective and eco-friendly heterogeneous catalyst for the synthesis of benzothiazole derivatives - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Vidhate, Kaluram N.; Lande, Machhindra K. (Chinese Chemical Letters, 2010)
A cheap and recyclable ZnO-beta zeolite was used as catalyst for the synthesis of benzothiazole derivatives. This method provides several advantages such as environmental friendliness, short reaction times, high yields, simple work-up procedure and catalyst was successfully reused for four cycles without significant loss of activity. (C) 2009 Machhindra K. Lande. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Benzothiazole; cyclocondensation; heterogeneous catalyst; ZnO-beta zeolite

ZnO-beta zeolite: as an effective and reusable heterogeneous catalyst for the one-pot synthesis of polyhydroquinolines - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Green Chemistry Letters and Reviews, 2010)
ZnO-beta zeolite, an inexpensive and mild catalyst, has been used for the synthesis of polyhydroquinolines in excellent yields from the one-pot four-component condensation of aldehydes, dimedone, ethyl acetoacetate, and ammonium acetate in ethanol at room temperature. The remarkable advantages offered by this method are a green catalyst, mild reaction conditions, simple work-up procedures, much faster reactions, and excellent yield of products. Furthermore, the catalyst could be reused several times keeping its initial activity in recycled reactions.
Keywords: Hantzsch condensation; heterogeneous catalyst; multicomponent; ZnO-beta zeolite

ZnO-beta zeolite mediated simple and efficient method for the one-pot synthesis of quinoxaline derivatives at room temperature - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2010)
A rapid and an efficient one-pot method for the synthesis of quinoxalines catalysed by ZnO-beta zeolite at room temperature is described. This environmentally benign method provides several advantages over methods that are currently employed such as a simple work-up, mild reaction conditions, good to excellent yields, and a process to recover and reuse the catalyst for several cycles with consistent activity.
Keywords: cyclocondensation; Quinoxaline; Room temperature; ZnO-beta zeolite

Bioresponsive mesoporous silica nanoparticles for triggered drug release - Singh, Neetu; Karambelkar, Amrita; Gu, Luo; Lin, Kevin; Miller, Jordan S.; Chen, Christopher S.; Sailor, Michael J.; Bhatia, Sangeeta N. (Journal of the Americal Chemical Society, 2011)

Degradation of methylene blue via photocatalysis of transition metal-loaded sulfated TiO2 - Gambhire, A. B.; Lande, Machhindra K.; Arbad, B. R.; Rathod, S. B.; Gholap, Ramkrishna S.; Patil, K. R. (Materials Chemistry and Physics, 2011)
Transition metal-loaded nanocrystalline SO42-/TiO2 powders were prepared by sol-gel method. Anatase is found as the active phase in all the samples. Sulfation process clearly stabilizes TiO2 catalyst phase against sintering, maintaining anatase phase and relatively high surface area values with respect to pure TiO2. Wide structural and surface characterization of samples was carried out in order to establish a correlation between the effect of sulfation and metal incorporation on the TiO2 photocatalytic properties. The maximum photocatalytic decomposition of methylene blue solution was achieved with sulfation of TiO2. In addition, incorporation of metal into the structure of SO42-/TiO2 seems to enhance the photocatalytic activity of the samples, which is ascribed to the enlargement of specific surface area, photogenerated carriers separation, light absorption, as well as the higher surface acidity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: nanomaterial; Photocatalytic activity; sol-gel process

Electron-rich PNP- and PNN-type Ru(II) hydrido-borohydride complexes. synthesis, structure and catalytic activity towards dehydrogenation of alcohols and hydrogenation of esters - Zhang, Jing; Balaraman, Ekambaram; Leitus, Gregory; Milstein, David (Organometallics, 2011)
Electron-rich PNP- and PNN-type ruthenium(II) hydrido borohydride pincer complexes, [RuH(BH4)(tBu-PNP)] (tBu-PNP = (2,6-bis(di-tert-butylphosphinomethyl)pyridine) (5) and [RuH(BH4)(tBu-PNN)] (tBu-PNN = 2-di-tert-butylphosphinomethyl-6-diethylaminomethylpyridine) (6), were prepared from their corresponding N2-bridged dinuclear Ru(II) complexes [(tBu-PNP)RuCl2]2(μ-N2) (3) and [(tBu-PNN)RuCl2]2(μ-N2) (4), respectively. The X-ray structure of 5 reveals a BH4– anion η2 coordinated to ruthenium through two bridging hydrides. A variable-temperature 1H NMR study of 6 exhibits interesting fluxional behavior of the BH4– ligand. Similarly, the Ru(II) hydrido borohydride complex 9, in which the BH4– moiety is coordinated in a η1 bonding mode, was obtained by reaction of [RuCl2(PPh3)(iPr-PNP)] (iPr-PNP = 2,6-bis(diisopropylphosphinomethyl)pyridine) (8) with two equivalents of NaBH4 at room temperature. The hydrido borohydride pincer complexes 5, 6, and 9 catalyze the acceptorless dehydrogenative coupling of primary alcohols to esters and the dehydrogenation of secondary alcohols to the corresponding ketones, accompanied by evolution of hydrogen gas. The reactivity follows the order 6 > 9 > 5. With the hydrido borohydride complex 6 as catalyst, high yields (up to 98%) and high turnover numbers (TON ∼1000) were obtained in the dehydrogenation of primary alcohols under mild and neutral conditions. In addition, 6 effectively catalyzes the hydrogenation of nonactivated aromatic and aliphatic esters to the corresponding alcohols with TON ∼200 under a relatively mild pressure of dihydrogen and neutral and homogeneous conditions. Thus, an efficient homogeneous catalytic system for the dehydrogenation–hydrogenation reactions of alcohols is developed, which is relevant to the current interest in hydrogen storage.

Extrudate swell of linear and branched polyethylenes: ALE simulations and comparison with experiments - Ganvir, Vivek; Gautham, Basavarsu P.; Pol, Harshawardhan; Bhamla, M. Saad; Sclesi, Lino; Thaokar, Rochish; Lele, Ashish K.; Mackley, Malcolm (Journal of Non-Newtonian Fluid Mechanics, 2011)
Extrudate swell is a common phenomenon observed in the polymer extrusion industry. Accurate prediction of the dimensions of an extrudate is important for appropriate design of dies for profile extrusion applications. Prediction of extrudate swell has been challenging due to (i) difficulties associated with accurate representation of the constitutive behavior of polymer melts, and (ii) difficulties associated with the simulation of free surfaces, which requires special techniques in the traditionally used Eulerian framework. In a previous work we had argued that an Arbitrary Lagrangian Eulerian (ALE) based finite element formulation may have advantages in simulating free surface deformations such as in extrudate swell. In the present work we reinforce this argument by comparing our ALE simulations with experimental data on the extrudate swell of commercial grades of linear polyethylene (LLDPE) and branched polyethylene (LOPE). Rheological behavior of the polymers was characterized in shear and uniaxial extensional deformations, and the data was modeled using either the Phan-Thien Tanner (PTT) model or the eXtended Pom-Pom (XPP) model. Additionally, flow birefringence and pressure drop measurements were done using a 10:1 contraction-expansion (CE) slit geometry in a MultiPass Rheometer. Simulated pressure drop and contours of the principal stress difference were compared with experimental data and were found to match well. This provided an independent test for the accuracy of the ALE code and the constitutive equations for simulating a processing-like flow. The polymers were extruded from long (L/D=30) and short (L/D=10) capillaries dies at 190 degrees C. ALE simulations were performed for the same extrusion conditions and the simulated extrudate swell showed good agreement with the experimental data. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: ALE-FEM; extrudate swell; Flow birefringence; MultiPass Rheometer; PSD; PTT; XPP

First total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one: a cancer chemopreventive agent - Borikar, Sanjay P.; Paul, Vincent; Puranik, Vedavati G.; Sathe, Vilas T.; Lagunas-Rivera, Selene; Ordonez, Mario (Synthesis-Stuttgart, 2011)
The first total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one, a newly discovered natural product with anticancer property is described by two different routes. A sequence involving an incorporation of a methyl group via a Gilman reagent and a chemoselective reduction of a cyclic anhydride functionality are the key steps. The methods proposed start from easily available starting materials and allow ready preparation of the final compound in good overall yield.
Keywords: Allium cepa; chemopreventive; Gilman reagent; selective; synthesis

From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.

Immobilization of conidiobolus coronatus alkaline protease on waste fungal biomass - Shankar, Shiv; Laxman, Ryali Seeta (Environmental Engineering and Management Journal, 2011)
Alkaline protease from Conidiobolus coronatus which is optimally active at pH 10 and 40 degrees C finds application in leather and detergent industries as well as for recovery of silver from waste photographic films. The protease was immobilized in Ca-alginate, polyacrylamide gel and alkali treated waste fungal biomass (ATWFB). ATWFB was found to be most suitable among the matrices tested. Glutaraldehyde marginally increased the binding to ATWFB. Binding of protease to ATWFB seems to be through adsorption as confirmed by FTIR spectra. Though temperature optima of free and immobilized proteases were identical, optimum pH of the immobilized enzyme shifted to 11 from 10. Temperature stability of the protease increased after immobilization. Immobilized protease could be reused 3 times with marginal loss in activity.
Keywords: Alkaline Protease; Conidiobolus coronatus; fungal biomass; Immobilization

Influence of carbon-based nanofillers on the melt flow singularity of linear polyethylene - Xu, Han; Lele, Ashish K.; Rastogi, Sanjay (Polymer, 2011)
A quantitative power law relationship between molecular weight and flow criticalities is uncovered that links stick-slip theory with the melt flow singularity observed during capillary flow. The singularity arises from decrease in pressure during melt flow of linear polyethylene through capillary die in a narrow temperature window. The molecular origin of the window effect is attributed to slip flow arising from disengagement of chains adsorbed to melt-wall interface from free chains in melt. Considering the similar molecular configuration of the linear polyethylene and carbon nanotubes (CNTs), the stretched chain conformation of the adsorbed chains in the presence of CNTs is influenced. The potential to broaden the window temperature interval in the presence of CNTs is explored. For the study, multi-walled carbon nanotubes (MWCNTs) are added in the linear polyethylene. The influence of the filler aspect ratio on the window effect is further investigated in the presence of carbon black (CBs). The presence of MWCNTs broadens the window temperature interval and increases the decrease in pressure. Contrary to MWCNTs in the presence of CBs the extrusion window narrows and reduction in the pressure-decrease occurs. It is also found that the two carbon nanofillers have a significant impact on flow-induced solidification. Both, the crystallisation rate and the onset temperature of crystallisation, increase with the loading of the two nanofillers. A closer comparison between the two carbon nanofillers at the same loading suggests that the crystallisation is more influenced in MWCNT-PE composites. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Capillary flow; Carbon fillers; Polyethylene

Influence of reactive compatibilization on the structure and properties of PP/LDH nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer International, 2011)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared by the direct melt intercalation method usingmaleic anhydride grafted polypropylene (PP-g-MAH) as a reactive compatibilizer. The compatibilization effects provided by PP-g-MAH in different weight fractions and their influence on the structure and properties of the final nanocomposites were investigated. The interactions and structural morphology of the nanocomposites were examined by Fourier transform infrared spectroscopy, X-ray diffraction and transmission electronmicroscopy. Thermal, mechanical and rheological properties of these nanocomposites were investigated as a function of compatibilizer concentration. The detailed morphological and X-ray diffraction results revealed that the degree of LDH dispersion increases as the amount of PP-g-MAH increases. Study of the linear viscoelastic properties showed that the storage modulus G' is very sensitive to the microstructure of the nanocomposite. The thermal properties of the nanocomposites were significantly influenced by the weight fraction of PP-g-MAH due to the shielding and nucleating effect of exfoliated layers. Both the tensile strength and modulus showed substantial improvements with increasing PP-g-MAH content, while the elongation at break substantially decreased, although the presence of PP-gMAH somewhat improves these values. The overall results showed that 10 wt% of compatibilizer is optimum to achieve nanocomposites with better performance. (C) 2011 Society of Chemical Industry
Keywords: compatibilization; layered double hydroxides; Nanocomposites; polypropylene; Rheology; thermomechanical properties

Lithium tetrafluoroborate catalyzed highly efficient inter- and intramolecular aza-Michael addition with aromatic amines - Lad, Uday P.; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2011)
Lithium tetrafluoroborate has been demonstrated for the first time to be an efficient catalyst in intermolecular aza-Michael addition aromatic amines to electron deficient alkenes. Suitability of the same catalyst in intramolecular aza-Michael addition leading 2-aryl-2,3-dihydroquinolin-4(1H) ones has also been described. (C) 2011 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-aryl-2; 3-dihydroquinolin-(4H)-1-ones; Anilines; Lithium tetrafluoroborate; Michael addition

Maghemite (hematite) core (shell) nanorods via thermolysis of a molecular solid of Fe-complex - Chaudhari, N. S.; Warule, S. S.; Muduli, Subas; Kale, B. B.; Jouen, Samuel; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Dalton Transactions, 2011)
An Fe-metal complex with 2'-hydroxy chalcone (2'-HC) ligands [Fe(III) (2'-hydroxy chalcone) 3] is synthesized by a chemical route and is subjected to different thermal treatments. Upon thermolysis in air at 450 degrees C for 3 h the complex yields maghemite (gamma-Fe(2)O(3)) nanorods with a thin hematite (alpha-Fe(2)O(3)) shell. X-Ray diffraction (XRD), Mossbauer spectroscopy, diffuse reflectance spectroscopy (UV-DRS), high resolution transmission electron microscopy (HR-TEM), field emission scanning electron microscopy (FE-SEM) and vibrating sample magnetometry (VSM) are used to characterize the samples. The stability of the ligand and the Fe-complex is further examined by using thermogravimmetric/differential thermal analysis (TGA/DTA). We suggest a residual ligand controlled mechanism for the formation of an anisotropic nanostructure in a crumbling molecular solid undergoing ligand decomposition. Since the band gap of iron oxide is in the visible range, we explored the use of our core shell nano-rod sample for photocatalytic activity for H(2) generation by H(2)S splitting under solar light. We observed high photocatalytic activity for hydrogen generation (75 ml h(-1)).

Magnetite/CdTe magnetic-fluorescent composite nanosystem for magnetic separation and bio-imaging - Kale, Anup; Kale, Sonia; Yadav, Prasad; Gholap, Haribhau; Pasricha, Renu; Jog, Jyoti Prakash; Lefez, Benoit; Hannoyer, Beatrice; Shastry, Padma; Ogale, Satishchandra B. (Nanotechnology, 2011)
A new synthesis protocol is described to obtain a CdTe decorated magnetite bifunctional nanosystem via dodecylamine (DDA) as cross linker. High resolution transmission electron microscopy (HRTEM), energy-dispersive x-ray spectroscopy (EDAX), vibrating sample magnetometry (VSM), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS) and fluorescence microscopy are used to characterize the constitution, size, composition and physical properties of these superparamagnetic-fluorescent nanoparticles. These CdTe decorated magnetite nanoparticles were then functionalized with anti-epidermal growth factor receptor (EGFR) antibody to specifically target cells expressing this receptor. The EGFR is a transmembrane glycoprotein and is expressed on tumor cells from different tissue origins including human leukemic cell line Molt-4 cells. The magnetite-CdTe composite nanosystem is shown to perform excellently for specific selection, magnetic separation and fluorescent detection of EGFR positive Molt-4 cells from a mixed population. Flow cytometry and confocal laser scanning microscopy results show that this composite nanosystem has great potential in antibody functionalized magnetic separation and imaging of cells using cell surface receptor antibody.

Nanoparticles that communicate in vivo to amplify tumour targeting - von Maltzahn, Geoffrey; Park, Ji-Ho; Lin, Kevin Y.; Singh, Neetu; Schwoeppe, Christian; Mesters, Rolf; Berdel, Wolfgang E.; Ruoslahti, Erkki; Sailor, Michael J.; Bhatia, Sangeeta N. (Nature Materials, 2011)

New CNN-type ruthenium pincer NHC complexes. synthesis and catalytic activity. mild, efficient hydrogenation of esters - Fogler, Eran; Balaraman, Ekambaram; Ben-David, Yehoshoa; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2011)
New pincer ruthenium complexes (2–6) based on the new bipyridine-NHC ligand 1 were prepared and studied, resulting in an efficient catalytic hydrogenation of esters to the corresponding alcohols under mild conditions. Reaction of the ligand 1 with RuH(Cl)CO(PPh3)3, followed by reaction with one equivalent of the base KHMDS, gave the mixed phosphine-NHC complex 2, incorporating a C–H-activated bipyridine ligand. Complex 2 has an octahedral structure containing two phosphorus atoms trans to each other, a hydride trans to the NHC ligand, and CO trans to the C–H-activated carbon of the bipyridine ligand. Using the precursor complex Ru(p-cymene)Cl2(CO), reaction with 1 followed by treatment of the intermediate product with one equivalent of KHMDS resulted in formation of the dichloride pincer complexes 3a and 3b, which are in equilibrium, as indicated by variable-temperature 1H NMR. Complex 3a is an octahedral, neutral, and symmetric complex with the CO ligand positioned trans to the central pyridine group of the pincer ligand and the two chlorides trans to each other, as indicated by single-crystal X-ray diffraction. Complex 3b is cationic, with an outer-sphere chloride. Reaction of the NHC ligand 1 with LiHMDS at low temperature followed by addition of RuH(Cl)CO(PPh3)3 resulted in the mixed phosphine-NHC complex 4, which has an octahedral structure containing phosphorus trans to the hydride, a CO trans to the NHC ligand, and an outer-sphere chloride. Chloride substitution by BArF– gave the X-ray-characterized complex 5. Deprotonation of complex 4 with KHMDS resulted in formation of the dearomatized complex 6. The in situ prepared 6 (from complex 4 and an equivalent of base) is among the best catalysts known for the hydrogenation of nonactivated esters to the corresponding alcohols under mild conditions.

Numerical and experimental studies on extrudate swell of branched polyethylene through axisymmetric and planar dies - Ganvir, Vivek; Gautham, Basavarsu P.; Thaokar, Rochish; Lele, Ashish K.; Pol, Harshwardhan (Journal of Polymer Engineering, 2011)
Extrudate swell is simulated using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation and the same has been validated by comparing the results with reported numerical and experimental studies. In the present work we compare our ALE simulations with our own experimental data on the extrudate swell of commercial grade low density polyethylene (LDPE) resin. The resins were characterized for their rheological behavior in both shear and uniaxial extension. The polymers were extruded from a capillary under isothermal conditions and the extrudates were observed on-line using a video camera. ALE simulations were performed using molecular constitutive model like eXtended Pom-Pom (XPP) for branched (LDPE). The simulated extrudate swell was a good match with the experimental data. It was found that the swell values of LPDE through planar die are higher than the axisymmetric die.
Keywords: ALE-FEM; extrudate swell; polymer flow simulations; XPP

Photocatalytic splitting of CS2 to a carbon-sulfur polymer and S8 catalyzed by a bimetallic ruthenium(II) compound with a tertiary amine binding site - towards photocatalytic splitting of CO2? - Livanov, Konstantin; Madhu, Vedichi; Balaraman, Ekambaram; Shimon, Linda J. W.; Diskin-Posner, Yael; Neumann, Ronny (Inorganic Chemistry, 2011)
The catalytic photocleavage of CS2 to S8 and a (CxSy)n polymer with visible light using a dinuclear ruthenium(II) compound with a bipyridine units for photoactivity and a vicinal tertiary amine binding site for CS2 activation was studied. The catalyst was characterized by X-ray diffraction, 1H NMR, and 13C NMR, ESI-MS and elemental analysis. CS2 photocleavage was significant (240 turnovers, 20 h) to yield isolable S8 and a (CxSy)n polymer. A mononuclear catalyst or one without an amine binding site showed significantly less activity. XPS of the (CxSy)n polymer showed a carbon/sulfur ratio ∼1.5–1.6 indicating that in part both C–S bonds of CS2 had been cleaved. Catalyst was also included within the polymer. The absence of peaks in the 1H NMR verified the (CxSy)n nature of the polymer, while 13C NMR and IR indicated that the polymer had multiple types of C–S and C–C bonds.

Poly(acrylonitrile) based ultrafiltration membranes: optimization of preparation parameters - Lohokare, Harshada R.; Bhole, Yogesh S.; Taralkar, Suyog; Kharul, Ulhas K. (Desalination, 2011)
Supported ultrafiltration (UF) membranes based on poly(acrylonitrile) were prepared while varying crucial parameters responsible for controlling membrane porosity, viz.; polymer concentration, solvent and additives in the dope solution. Insight into membrane porosity and morphology was obtained by water flux, solute rejection, bubble point, pore size distribution, SEM and AFM analyses. It was found that merely increasing polymer concentration does not necessarily reduce pore size of membranes. Among four solvents used for the dope solution preparation, N-methyl pyrrolidone was found to offer membranes with optimal combination of flux and rejection of various solutes. Some of the PAN(17) (17% w/w PAN concentration in the dope solution) membranes prepared using organic acid as the additive (citric acid, tartaric acid or maleic acid) offered 1.2-1.7 times higher flux than the membrane prepared using inorganic salt, ZnCl2 as an additive. The porosity of PAN(17) membrane prepared using CA as an additive was larger as compared to membrane prepared using ZnCl2 as an additive. Atomic force microscopy (AFM) analysis of this membrane exhibited higher surface roughness as compared to the ZnCl2 based membrane. Both these membranes exhibited bacteria (E. Coli) log reduction value (LRV) of at least 6; depicting applicability of these membrane for water disinfection. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Additive; Bacteria rejection; Poly(acrylonitrile); Pore size distribution; Ultrafiltration

Purification and characterization of an alkaline protease by a new strain of Beauveria sp - Shankar, Shiv; Rao, Mala; Laxman, Ryali Seeta (Process Biochemistry, 2011)
A fungal culture isolated from animal dung was identified as a new strain of Beauveria sp MTCC 5184 based on 18S rDNA and ITS nucleotide sequence homology. The fungal isolate secretes alkaline protease active at pH 9 and 50 degrees C. The alkaline protease from Beauveria sp (BAP) was purified to homogeneity with 10.2-folds increase in specific activity and 38.6% recovery. The molecular mass and isoelectric point of the protease were found to be 29 kDa and 9.3, respectively. The N-terminal sequence of the BAP showed only partial homology with subtilisin like proteases from other fungi. The enzyme was stable up to 40 degrees C and pH 3-11. The protease was inhibited by Cd(2+), Hg(2+) and Mn(2+). The activity was totally lost in the presence of 1 mM PMSF suggesting it to be a serine protease. The protease showed maximum activity with casein followed by haemoglobin and BSA. The purified protease is able to separate the endothelial cells and can be used in animal cell culture. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Animal cell culture; Beauveria sp; Sequence homology

Room temperature ferromagnetism in undoped and Fe doped ZnO nanorods: microwave-assisted synthesis - Limaye, Mukta V.; Singh, Shashi B.; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha K. (Journal of Solid State Chemistry, 2011)
One-dimensional (1D) undoped and Fe doped ZnO nanorods of average length similar to 1 mu m and diameter similar to 50 nm have been obtained using a microwave-assisted synthesis. The magnetization (M) and coercivity (H-c) value obtained for undoped ZnO nanorods at room temperature is similar to 5 X 10(-3) emu/g and similar to 150 Oe, respectively. The Fe doped ZnO samples show significant changes in M -H loop with increasing doping concentration. Both undoped and Fe doped ZnO nanorods exhibit a Curie transition temperature (T-c) above 390 K. Electron spin resonance and Mossbauer spectra indicate the presence of ferric ions. The origin of ferromagnetism in undoped ZnO nanorods is attributed to localized electron spin moments resulting from surface defects/vacancies, where as in Fe doped samples is explained by F center exchange mechanism. (C) 2010 Published by Elsevier Inc.
Keywords: Diluted magnetic semiconductors; Nanostructures; ZnO

Selective hydrogenation of chloronitrobenzenes with an MCM-41 supported platinum allyl complex derived catalyst - Indra, Arindam; Rajamohanan, Pattuparambil R.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2011)
A platinuin precatalyst (1) has been prepared by reacting [(eta(3)-C3H5)(4)Pt4Cl4] with surface functionalized MCM-41 with pendant -(CH2)(3)NH(CH2)(2)NH2 groups. For the hydrogenation of o-, m- and p-chloronitrobenzenes to the corresponding chloroanilines, 1 is found to be a highly active catalyst with good selectivities for them-and p-isomers. Its performance is superior to that of its palladium analogue and far superior to that of commercial (5%) Pt/C or (5%) Pt/Al2O3. Comparison of solid state and solution NMR data and other evidences indicate that on treatment with the functionalized MCM-41 support; [(eta(3)-C3H5)(4)Pt4Cl4] loses the ally! ligand. XPS data show that in the fresh catalyst Pt is present in the 2+ oxidation state. Based on these and analytical data, co-ordination by surface diamine and hydroxo groups to Pt2+ in 1 is suggested. In the used catalyst both Pt2+ and Pt are present but the amount of metallic platinum is similar to 16% of the total. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chloronitrobenzenes; Dehydrohalogenation; heterogeneous catalyst; MCM-41; Selective hydrogenation

Stereoselective synthesis and antimicrobial activity of steroidal C-20 tertiary alcohols with thiazole/pyridine side chain - Shingate, Bapurao B.; Liazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2011)
Stereoselective synthesis of novel steroidal C-20 tertiary alcohols with thiazole and pyridine side chain using Grignard reaction of steroidal ketones and thiazole/pyridine magnesium bromide have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: antibacterial activity; Antifungal activity; Grignard reaction; Steroid side chain; Steroidal ketones

Synthesis and application of a chiral diborate - Loewer, Yvonne; Weiss, Christine; Biju, Akkattu T.; Frohlich, Roland; Glorius, Frank (Journal of Organic Chemistry, 2011)
A chiral diborate with different counterions is reported whose structure was unambiguously confirmed by X-ray analysis. This chiral dianion was used in the resolution of trans-1,2-diamines and also as a chiral shift reagent for NMR analysis of triphenylphosphonium salts.

Alumina supported carbon composite material with exceptionally high defluoridation property from eggshell waste - Lunge, Sneha; Thakre, Dilip; Kamble, Sanjay; Labhsetwar, Nitin K.; Rayalu, Sadhana (Journal of Hazardous Materials, 2012)
A new alumina supported carbon composite material called ``Eggshell Composite'' (EC) was synthesized from eggshell waste as calcium source for selective fluoride adsorption from water. The effect of various synthesis parameters like eggshell (ES): Eggshell membrane (ESM) ratio, aluminium loading, mixing time and calcinations temperature to optimize the synthesis conditions for selective fluoride removal has been studied. It was observed that the synthesis parameters have significant influence on development of EC and in turn on fluoride removal capacity. EC synthesized was characterized for elemental composition, morphology, functionality and textural properties. Results showed that EC obtained from eggshell modified with alumina precursor is more selective and efficient for fluoride removal. Langmuir and Freundlich isotherm were used to obtain ultimate fluoride removal capacity. The calcium and alumina species in EC shows synergistic effect in fluoride adsorption process. Fluoride sorption studies were carried out in synthetic, groundwater and wastewater. EC proved to be a potential, indigenous and economic adsorbent for fluoride removal. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Composite material; Eggshell; Eggshell membrane; Fluoride adsorption; Langmuir

Antagonism of microRNA function in zebrafish embryos by using locked nucleic acid enzymes (LNAzymes) - Suryawanshi, Hemant; Lalwani, Mukesh Kumar; Ramasamy, Soundhar; Rana, Rajiv; Scaria, Vinod; Sivasubbu, Sridhar; Maiti, Souvik (Chembiochem, 2012)
MicroRNAs (miRNAs) have crucial functions in many cellular processes, such as differentiation, proliferation and apoptosis; aberrant expression of miRNAs has been linked to human diseases, including cancer. Tools that allow specific and efficient knockdown of miRNAs would be of immense importance for exploring miRNA function. Zebrafish serves as an excellent vertebrate model system to understand the functions of miRNAs involved in a variety of biological processes. We designed and employed a strategy based on locked nucleic acid enzymes (LNAzymes) for in vivo knockdown of miRNA in zebrafish embryos. We demonstrate that LNAzyme can efficiently knockdown miRNAs with minimal toxicity to the zebrafish embryos.
Keywords: enzymes; locked nucleic acids; microRNA; morpholino; zebrafish

Cholesterol-tethered platinum II-based supramolecular nanoparticle increases antitumor efficacy and reduces nephrotoxicity - Sengupta, Poulomi; Basu, Sudipta; Soni, Shivani; Pandey, Ambarish; Roy, Bhaskar; Oh, Michael S.; Chin, Kenneth T.; Paraskar, Abhimanyu S.; Sarangi, Sasmit; Connor, Yamicia; Sabbisetti, Venkata S.; Kopparam, Jawahar; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Nanoscale drug delivery vehicles have been harnessed extensively as carriers for cancer chemotherapeutics. However, traditional pharmaceutical approaches for nanoformulation have been a challenge with molecules that exhibit incompatible physicochemical properties, such as platinum-based chemotherapeutics. Here we propose a paradigm based on rational design of active molecules that facilitate supramolecular assembly in the nanoscale dimension. Using cisplatin as a template, we describe the synthesis of a unique platinum (II) tethered to a cholesterol backbone via a unique monocarboxylato and O -> Pt coordination environment that facilitates nanoparticle assembly with a fixed ratio of phosphatidylcholine and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine- N-[amino (polyethylene glycol)-2000]. The nanoparticles formed exhibit lower IC50 values compared with carboplatin or cisplatin in vitro, and are active in cisplatin-resistant conditions. Additionally, the nanoparticles exhibit significantly enhanced in vivo antitumor efficacy in murine 4T1 breast cancer and in K-Ras(LSL/+/)Pten(fl/fl) ovarian cancer models with decreased systemic- and nephro-toxicity. Our results indicate that integrating rational drug design and supramolecular nanochemistry can emerge as a powerful strategy for drug development. Furthermore, given that platinum-based chemotherapeutics form the frontline therapy for a broad range of cancers, the increased efficacy and toxicity profile indicate the constructed nanostructure could translate into a nextgeneration platinum-based agent in the clinics.
Keywords: chemotherapy; nanomedicine

Comparative genomics of the apicomplexan parasites toxoplasma gondii and neospora caninum: coccidia differing in host range and transmission strategy - Reid, Adam James; Vermont, Sarah J.; Cotton, James A.; Harris, David; Hill-Cawthorne, Grant A.; Koenen-Waisman, Stephanie; Latham, Sophia M.; Mourier, Tobias; Norton, Rebecca; Quail, Michael A.; Sanders, Mandy; Shanmugam, Dhanasekaran; et al. (Plos Pathogens, 2012)
Toxoplasma gondii is a zoonotic protozoan parasite which infects nearly one third of the human population and is found in an extraordinary range of vertebrate hosts. Its epidemiology depends heavily on horizontal transmission, especially between rodents and its definitive host, the cat. Neospora caninum is a recently discovered close relative of Toxoplasma, whose definitive host is the dog. Both species are tissue-dwelling Coccidia and members of the phylum Apicomplexa; they share many common features, but Neospora neither infects humans nor shares the same wide host range as Toxoplasma, rather it shows a striking preference for highly efficient vertical transmission in cattle. These species therefore provide a remarkable opportunity to investigate mechanisms of host restriction, transmission strategies, virulence and zoonotic potential. We sequenced the genome of N. caninum and transcriptomes of the invasive stage of both species, undertaking an extensive comparative genomics and transcriptomics analysis. We estimate that these organisms diverged from their common ancestor around 28 million years ago and find that both genomes and gene expression are remarkably conserved. However, in N. caninum we identified an unexpected expansion of surface antigen gene families and the divergence of secreted virulence factors, including rhoptry kinases. Specifically we show that the rhoptry kinase ROP18 is pseudogenised in N. caninum and that, as a possible consequence, Neospora is unable to phosphorylate host immunity-related GTPases, as Toxoplasma does. This defense strategy is thought to be key to virulence in Toxoplasma. We conclude that the ecological niches occupied by these species are influenced by a relatively small number of gene products which operate at the host-parasite interface and that the dominance of vertical transmission in N. caninum may be associated with the evolution of reduced virulence in this species.

Confinement of zinc oxide nanoparticles in ordered mesoporous silica MCM-41 - Lihitkar, P. B.; Violet, Samuel; Shirolkar, Mandar; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Materials Chemistry and Physics, 2012)
Mesoporous silica (MS) and zinc loaded MS composites have been synthesized and characterized using high resolution transmission electron microscopy, X-ray diffraction, UV-visible spectroscopy, photoluminescence spectroscopy, N-2 adsorption-desorption isotherms, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Thermal treatment of the zinc loaded MS composite lead to the formation of ZnO-MS composite. The well ordered uniform pore structure of MS (pore size similar to 3.4 nm) is found to remain stable even after 30% Zn loading albeit decrease in the pore size 1.2 nm indicates the formation of ZnO inside the pores. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Defect; Energy spectroscopy for chemical analysis (ESCA); Mesoporous; Photoluminescence spectroscopy; Surface properties

Covalently anchored ruthenium-phosphine complex on mesoporous organosilica: catalytic applications in hydrogenation reactions - Sisodiya, Sheetal; Lazar, Anish; Shylesh, Sankaranarayanapillai; Wang, Lei; Thiel, Werner R.; Singh, Anand Pal (Catalysis Communications, 2012)
New heterogeneous catalysts for alkene hydrogenation reactions were prepared by the immobilization of trimethoxysilane functionalized triphenylphosphine eta(6)-p-cymene ruthenium complex on mesoporous organosilica (PMO-Ru). Characterization techniques confirmed the structural integrity of the organosilica material and proved the successful anchoring of ruthenium complex. Catalytic activity and stability of PMO-Ru sample investigated in the hydrogenation of various olefins showed higher activity than a neat and MCM-41 supported ruthenium catalyst. High catalytic activity and stability of organosilica supported ruthenium catalyst are attributed to the hydrophobic environments and to the unique structural features imparted from the presence of organic groups in the framewall positions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Heterogenization; Hydrogenation; Organosilica; ruthenium; Triphenyl phosphine

Deposition-precipitation versus anionic-exchange Au/Al2O3 catalysts: a comparative investigation towards the selective reduction of NOx - Nguyen, D. L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Catalysis Communications, 2012)
Catalytic properties of supported gold catalysts on gamma-Al2O3 prepared by a conventional deposition-precipitation method were compared with those obtained by anionic-exchange for the reduction of NOx by hydrocarbon under lean conditions that simulate Diesel engine exhaust gas. Interestingly, a catalytic activity enhancement is observed after thermal ageing under reactive conditions at 500 degrees C on anionic-exchanged samples which make them suitable for practical developments. On the other hand, the reverse trend is observed on the solids prepared by deposition-precipitation which deactivate at low temperature. Such changes in catalytic properties have been tentatively explained on the basis of textural and structural modifications taking place during thermal ageing under wet atmosphere. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Anionic-exchange; Au catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Effect of alkali pretreatment on the structural properties and enzymatic hydrolysis of corn cob - Sahare, Padmavati; Singh, Rajkumar; Laxman, Ryali Seeta; Rao, Mala (Applied Biochemistry and Biotechnology, 2012)
An effective alkali pretreatment which affects the structural properties of cellulose (corn cob) has been studied. The pretreatment of corn cob was carried out with different combinations of alkali at varying temperatures. The most effective pretreatment of corn cob was achieved with 1 % alkali at 50 A degrees C in 4 h. The crystallinity index (CrI) and specific surface area (SSA) of untreated corn cob was 39 % and 0.52 m(2)/g wherein after alkali pretreatment CrI decreased to 15 % and SSA increased to 3.32 m(2)/g. The fungal organism was identified as Penicillium pinophilum on the basis of ITS sequence. At 5 % substrate concentration using a complete cellulase from Penicillium pinophilum the hydrolysis of untreated corn cob with 5, 10 and 20 FPU/g enzyme loadings were 11 %, 13 % and 16 %, whereas after alkali treatment the hydrolysis increased to 78 %, 90 % and 100 %, respectively. Further hydrolytic potential of commercial cellulases viz. Accellerase (TM) 1,000, Palkofeel-30 and Palkocel-40 were investigated under similar conditions.
Keywords: Corn cob; Crystallinity index; Enzymatic hydrolysis; Penicillium pinophilum; Specific surface area

Epitaxial magnetic oxide nanocrystals via phase decomposition of bismuth perovskite precursors - Bogle, Kashinath A.; Cheung, Jeffrey; Chen, Yong-Lun; Liao, Sheng-Chieh; Lai, Chih-Hung; Chu, Ying-Hao; Gregg, John M.; Ogale, Satishchandra B.; Valanoor, Nagarajan (Advanced Functional Materials, 2012)
The phase instability of bismuth perovskite (BiMO3), where M is a ferromagnetic cation, is exploited to create self-assembled magnetic oxide nanocrystal arrays on oxide supports. Conditions during pulsed laser deposition are tuned so as to induce complete breakdown of the perovskite precursor into bismuth oxide (Bi2O3) and metal oxide (M-Ox) pockets. Subsequent cooling in vacuum volatizes the Bi2O3 leaving behind an array of monodisperse nanocrystals. In situ reflective high energy electron diffraction beam is exploited to monitor the synthesis in real-time. Analysis of the patterns confirms the phase separation and volatization process. Successful synthesis of M-Ox, where M = Mn, Fe, Co, and Cr, is shown using this template-free facile approach. Detailed magnetic characterization of nanocrystals is carried out to reveal the functionalities such as magnetic anisotropy as well as larger than bulk moments, as expected in these oxide nanostructures.
Keywords: Bi2O3 evaporation; bismuth perovskites; epitaxial nanostructures; magnetic oxides; phase separation

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

From small aromatic molecules to functional nanostructured carbon by pulsed laser-induced photochemical stitching - Gokhale, R. R.; Thakare, V. P.; Warule, S.; Lefez, Benoit; Hannoyer, Beatrice; Jog, Jyoti Prakash; Ogale, S. B. (AIP Advances, 2012)
A novel route employing UV laser pulses (KrF Excimer, 248 nm) to cleave small aromatic molecules and stitch the generated free radicals into functional nanostructured forms of carbon is introduced. The process differs distinctly from any strategies wherein the aromatic rings are broken in the primary process. It is demonstrated that this pulsed laser-induced photochemical stitching (PLPS) process when applied to routine laboratory solvents (or toxic chemical wastes when discarded) Chlorobenzene and o-Dichlorobenzene yields Carbon Nanospheres (CNSs) comprising of graphene-like sheets assembled in onion-like configurations. This room temperature process implemented under normal laboratory conditions is versatile and clearly applicable to the whole family of haloaromatic compounds without and with additions of precursors or other nanomaterials. We further bring out its applicability for synthesis of metal-oxide based carbon nanocomposites. Copyright 2012 Author(s). This article is distributed under a Creative Commons Attribution 3.0 Unported License. [http://dx.doi.org/10.1063/1.4721268]

Kinetic studies of amino acid-based surfactant binding to DNA - Santhiya, Deenan; Dias, Rita S.; Dutta, Sounak; Das, Prasanta Kumar; Miguel, Maria G.; Lindman, Bjorn; Maiti, Souvik (Journal of Physical Chemistry B, 2012)
In this work, the binding kinetics of amino acid-based surfactants, presenting different linkers and head groups, with calf thymus (CT)-DNA was studied using stopped-flow fluorescence spectroscopy. The kinetic studies were carried out as a function of Na+ concentration and surfactant-to-DNA charge ratio. The surfactant binding on DNA took place in two consecutive steps, for which the corresponding first and second relative rate constants (k(1) and k(2)) were determined. The fast step was attributed to the surfactant binding to DNA and micelle formation in its vicinity, the slower step to DNA condensation and possible rearrangement of the surfactant aggregates. In general, both relative rate constants increase with surfactant concentration and decrease with the ionic strength of the medium. The architecture of the surfactant was found to have a significant impact on the kinetics of the DNA surfactant complexation. Surfactants with amide linkers showed larger relative rate constants than those with ester linkers. The variation of the relative rate constants with the head groups of the surfactants, alanine and proline, was found to be less obvious, being partially dependent on the surfactant concentration.

Laser synthesized super-hydrophobic conducting carbon with broccoli-type morphology as a counter-electrode for dye sensitized solar cells - Gokhale, Rohan; Agarkar, Shruti A.; Debgupta, Joyashish; Shinde, Deodatta; Lefez, Benoit; Banerjee, Abhik; Jog, Jyoti Prakash; More, Mahendra A.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Nanoscale, 2012)
A laser photochemical process is introduced to realize superhydrophobic conducting carbon coatings with broccoli-type hierarchical morphology for use as a metal-free counter electrode in a dye sensitized solar cell. The process involves pulsed excimer laser irradiation of a thin layer of liquid haloaromatic organic solvent o-dichlorobenzene (DCB). The coating reflects a carbon nanoparticle-self assembled and process-controlled morphology that yields solar to electric power conversion efficiency of 5.1% as opposed to 6.2% obtained with the conventional Pt-based electrode.

Mn(III) based binapthyl schiff base complex hetrogenized over organo-modified SBA-15: synthesis, characterization and catalytic application - Sharma, Priti; Lazar, Anish; Singh, A. P. (Applied Catalysis A-General, 2012)
A heterogenized organocatalyst was synthesized by the covalent anchoring; of the complex chloro (S,S)(-)[N-3-tert-butyl-5-chloromethyl salicylidene]-N'-[3',5'-di-tert-butyl salicylidene] 1,1'-binapthyl-2,2'-diamine manganese(III) over modified mesoporous surface of SBA-15 through the reactive 3-aminopropyl trimethoxysilane (3-APTMS) group. The surface properties of the functionalized catalyst were analyzed by a series of characterization techniques such as elemental analysis, XRD, N-2 sorption measurement isotherm, FT-IR, TGA-DTA, XPS, and solid state C-13 NMR. The XRD and N-2 sorption measurement, UV reflectance and CP MAS NMR spectroscopy (C-13 and Si-29) of the catalyst confirmed the structural integrity of the mesoporous hosts and the spectroscopic characterization technique proved the successful anchoring of the metal complex over the modified mesoporous support. The screening of the catalyst Mn(III)-L-SBA-15 and neat Mn(III)-L complexes was done in the oxidation reaction of thioanisole (methyl phenyl sulfide) by using TBHP as an oxidant. Mn(III)-L-SBA-15 catalyst shows higher activities and turnover number (TON) and exhibit enhanced enantiomeric excess comparable to homogeneous catalyst [Mn(III)-L]. [Mn(III)-L-SBA-15] catalyst was found more active than homogeneous catalyst [Mn(III)-L]; Moreover bulkier alkene like 1,2-dihydronapthalene was also efficiently epoxidised with the synthesized supported catalyst. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Binaphthyl ligand; Chiral Schiff-base; Immobilization; Post grafting synthesis

MOF derived porous carbon-Fe3O4 nanocomposite as a high performance, recyclable environmental superadsorbent - Banerjee, Abhik; Gokhale, Rohan; Bhatnagar, Sumit; Jog, Jyoti Prakash; Bhardwaj, Monika; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Materials Chemistry, 2012)
A high surface area carbon composite with Fe3O4 nanoparticles is synthesized by pyrolysis of an iron containing Metal Organic Framework (MOF). The composite can be prepared by annealing the MOF at different temperatures (500 degrees C and 600 degrees C), each case exhibiting unique properties in terms of the hydrophobic behaviour and surface area, resulting in specific applicability domains. We highlight the exceptional behaviour of this material as a magnetically separable and recyclable superadsorbent for removal and recovery of environmental pollutants (oil/hydrocarbon and dye/phenol).

Multiple H2 occupancy of cages of clathrate hydrate under mild condition - Lu, Hailong; Wang, Jianwei; Liu, Changling; Ratcliffe, Christopher I.; Becker, Udo; Kumar, Rajnish; Ripmeester, John A. (Journal of the American Chemical Society, 2012)
Experiments were carried out by reacting H(2) gas with N(2) hydrate at a temperature of 243 K and a pressure of 15 MPa. The characterizations of the reaction products indicated that multiple H(2) molecules can be loaded into both large and small cages of structure II clathrate hydrates. The realization of multiple H(2) occupancy of hydrate cages under moderate conditions not only brings new insights into hydrogen clathrates but also refreshes the perspective of clathrate hydrates as hydrogen storage media.

One-pot sol-gel preparation for efficient cobalt-molybdenum-titania hydrotreating catalysts - Nguyen, D. L.; Gillot, S.; Souza, D. O.; Blanchard, P.; Lamonier, Carole; Berrier, E.; Kotbagi, T. V.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Cristol, S.; Payen, E.; Lancelot, Christine (Chemcatchem, 2012)
Titania-based hydrodesulfurization catalysts were prepared by using a one-pot solgel method with the titanium peroxo complex as titanium precursor and molybdenum and cobalt precursors dissolved in the aqueous hydrogen peroxide solution used during synthesis. Catalysts with MoO3 loadings varying from 5 to 40 wt?% and a Co/Mo atomic ratio of 0.5 were prepared. Solids with molybdenum loadings below 20 wt?% MoO3 demonstrated poor hydrodesulfurization activity for the model compound thiophene. This was attributed to the presence of a large amount of embedded cobalt and molybdenum species in the titania matrix. A significant increase in the catalytic activity was observed for solids containing 20 and 25 wt?% of MoO3 on which active species appeared to be accessible on the titania surface. Furthermore, the highest conversion obtained on these solgel solids was superior to the highest conversion obtained on reference catalysts prepared through the impregnation of ammonium heptamolybdate and cobalt nitrate on commercial titania.
Keywords: cobalt; heterogeneous catalysis; Molybdenum; sol-gel process; titanium

Photocatalytic degradation of phenolics by N-doped mesoporous titania under solar radiation - Mangrulkar, Priti A.; Kamble, Sanjay P.; Joshi, Meenal M.; Meshram, Jyotsna S.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Photoenergy, 2012)
In this study, nitrogen-doped mesoporous titania was synthesized by templating method using chitosan. This biopolymer chitosan plays the dual role of acting as a template (which imparts mesoporosity) and precursor for nitrogen. BET-SA, XRD, UV-DRS, SEM, and FTIR were used to characterize the photocatalyst. The doping of nitrogen into TiO2 lattice and its state was substantiated and measured by XPS. The photocatalytic activity of the prepared N-doped mesoporous titania for phenol and o-chlorophenol degradation was investigated under solar and artificial radiation. The rate of photocatalytic degradation was observed to be higher for o-chlorophenol than that of phenol. The photodegradation of o-chlorophenol was 98.62% and 72.2%, while in case of phenol, degradation to the tune of 69.25% and 30.58% was achieved in solar and artificial radiation. The effect of various operating parameters, namely, catalyst loading, pH, initial concentration and the effect of coexisting ions on the rate of photocatalytic degradation were studied in detail.

Purification and biochemical characterization of endoglucanase from Penicillium pinophilum MS 20 - Pol, Dipali; Laxman, Ryali Seeta; Rao, Mala (Indian Journal of Biochemistry & Biophysics, 2012)
Cellulases find increasing prominence in sustainable production of fuel and feedstock from lignocellulosic biomass. The purification and biochemical characterization of individual components of cellulase complex is important to understand the mechanism of their action for the solubilization of crystalline cellulose. In this study, an extra-cellular endoglucanase isolated from culture filtrate of Penicillium pinophilum MS 20 was purified to homogeneity by ammonium sulphate precipitation, ion-exchange chromatography and gel filtration. The purified endoglucanase (specific activity 69 U/mg) was a monomeric protein with molecular mass of 42 kDa, as determined by SDS-PAGE. The endoglucanase was active over a broad range of pH (4-7) with maximum activity at pH 5 and showed optimum temperature of 50 degrees C. It retained 100% activity at 50 degrees C for 6 h and half- lives of 4 h and 3 h at 60 degrees C and 70 degrees C, respectively. The kinetic constants for the endoglucanase determined with carboxymethyl cellulose as substrate were V-max of 72.5 U/mg and apparent K-m of 4.8 mg/ml. The enzyme also showed moderate activity towards H3PO4 swollen cellulose and p-nitrophenyl beta-D-glucoside, but no activity towards filter paper, Avicel and oat spelt xylan. The activity was positively modulated by 47, 32 and 25% in the presence of Co2+, Zn2+ and Mg2+, respectively to the reaction mixture. The wide pH stability (4-7) and temperature stability up to 50 degrees C of endoglucanase makes the enzyme suitable for use in cellulose saccharification at moderate temperature and pH.
Keywords: Biochemical properties; Carboxymethyl cellulose; Endoglucanase; Penicillium pinophilum MS 20; Purification

Rapid self-healing hydrogels - Phadke, Ameya; Zhang, Chao; Arman, Bedri; Hsu, Cheng-Chih; Mashelkar, Raghunath Anant; Lele, Ashish K.; Tauber, Michael J.; Arya, Gaurav; Varghese, Shyni (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Synthetic materials that are capable of autonomous healing upon damage are being developed at a rapid pace because of their many potential applications. Despite these advancements, achieving self-healing in permanently cross-linked hydrogels has remained elusive because of the presence of water and irreversible cross-links. Here, we demonstrate that permanently cross-linked hydrogels can be engineered to exhibit self-healing in an aqueous environment. We achieve this feature by arming the hydrogel network with flexible-pendant side chains carrying an optimal balance of hydrophilic and hydrophobic moieties that allows the side chains to mediate hydrogen bonds across the hydrogel interfaces with minimal steric hindrance and hydrophobic collapse. The self-healing reported here is rapid, occurring within seconds of the insertion of a crack into the hydrogel or juxtaposition of two separate hydrogel pieces. The healing is reversible and can be switched on and off via changes in pH, allowing external control over the healing process. Moreover, the hydrogels can sustain multiple cycles of healing and separation without compromising their mechanical properties and healing kinetics. Beyond revealing how secondary interactions could be harnessed to introduce new functions to chemically crosslinked polymeric systems, we also demonstrate various potential applications of such easy-to-synthesize, smart, self-healing hydrogels.
Keywords: adhesives; biomimetic materials; Hydrophobicity; molecular dynamics; smart materials

Selective recognition of fluoride and acetate by a newly designed ruthenium framework: experimental and theoretical investigations - Kundu, Tanaya; Chowdhury, Abhishek Dutta; De, Dipanwita; Mobin, Shaikh M.; Puranik, Vedavati G.; Datta, Anindya; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
{An effective anion sensor, [Ru-II(bpy)(2)(H2L-)](+) (1(+)), based on a redox and photoactive {Ru-II(bpy)(2)} moiety and a new ligand (H3L = 5-(1H-benzo[d]imidazol-2-yl)-1H-imidazole-4-carboxylic acid), has been developed for selective recognition of fluoride (F-) and acetate (OAc-) ions. Crystal structures of the free ligand, H3L and [1](ClO4) reveal the existence of strong intramolecular and intermolecular hydrogen bonding interactions. The structure of [1](ClO4) shows that the benzimidazole N-H of H2L- is hydrogen bonded with the pendant carboxylate oxygen while the imidazole N-H remains free for possible hydrogen bonding interaction with the anions. The potential anion sensing features of 1(+) have been studied by different experimental and theoretical (DFT) investigations using a wide variety of anions, such as F-, Cl-, Br-, I-, HSO4-, H2PO4-, OAc- and SCN-. Cyclic voltammetry and differential pulse voltammetry established that 1(+) is an excellent electrochemical sensor for the selective recognition kof F- and OAc- anions. 1(+) is also found to be a selective colorimetric sensor for F- or OAc- anions where the MLCT band of the receptor at 498 nm is red shifted to 538 nm in the presence of one equivalent of F- or OAc- with a distinct change in colour from reddish-orange to pink. The binding constant between 1(+) and F- or OAc- has been determined to be logK = 7.61 or 7.88, respectively, based on spectrophotometric titration in CH3CN. The quenching of the emission band of 1(+) at 716 nm (lambda(ex) = 440 nm

Self photostabilizing UV-durable MWCNT/polymer nanocomposites - Lonkar, Sunil P.; Kushwaha, Omkar S.; Leuteritz, Andreas; Heinrich, Gert; Singh, R. P. (RSC Advances, 2012)
A potentially active hindered amine light stabilizer (HALS) was successfully anchored onto multiwalled carbon nanotubes (MWCNTs) and used as a light-stabilizing yet reinforcing multifunctional nanofiller to obtain UV-durable polymer nanocomposites. The influence of such light stabilizing MWCNTs on the photo-oxidation behaviour and structure-properties of polypropylene (PP) was studied. The composites were prepared by solution mixing of MWCNTs followed by melt compounding with polypropylene (PP). The resulting composite exhibits excellent UV-durability showing an almost 20 fold increase in the induction period of photo-oxidation. Moreover, the hydrophobic HALS was found to be compatibilizing enough to achieve homogeneous dispersion of exfoliated nanotubes into a polymer matrix. The rheological characterizations predict the formation of a percolated network structure. The obtained nanocomposites present markedly improved mechanical properties which underline the reinforcing ability of functionalized MWCNTs. Overall combination of HALS and MWCNTs offers an attractive route to combine multifunctionality into new hybrid UV-durable polymer nanocomposites. Such materials may possess great potential for outdoors high performance applications.

Strong metal-metal coupling in mixed-valent intermediates [Cl(L)Ru(mu-tppz)Ru(L)Cl](+), L = beta-diketonato ligands, tppz=2,3,5,6-tetrakis(2-pyridyl)pyrazine - Kundu, Tanaya; Schweinfurth, David; Sarkar, Biprajit; Mondal, Tapan Kumar; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
Five diruthenium(II) complexes [Cl(L)Ru(mu-tppz)Ru(L)Cl](1-5) containing differently substituted beta-diketonato derivatives (1: L = 2,4-pentanedionato; 2: L = 3,5-heptanedionato; 3: L = 2,2,6,6-tetramethyl-3,5-heptanedionato; 4: L = 3-methyl-2,4-pentanedionato; 5: L = 3-ethyl-2,4-pentanedionato) as ancillary ligands (L) were synthesized and studied by spectroelectrochemistry (UV-Vis-NIR, electron paramagnetic resonance (EPR)). X-ray structural characterisation revealed anti (1, 2, 5) or syn (3) configuration as well as non-planarity of the bis-tridentate tppz bridge and strong d pi(Ru-II) -> pi*(pyrazine, tppz) back-bonding. The widely separated one-electron oxidation steps, (RuRuII)-Ru-II/(RuRuIII)-Ru-II and (RuRuIII)-Ru-II/(RuRuIII)-Ru-III, result in large comproportionation constants (K-c) of >= 10(10) for the mixed-valent intermediates. The syn-configurated 3(n) exhibits a particularly high K-c of 10(12) for n = 1+, accompanied by density functional theory (DFT)-calculated minimum Ru-N bond lengths for this (RuRuIII)-Ru-II intermediate. The electrogenerated mixed-valent states 1(+)-5(+) exhibit anisotropic EPR spectra at 110 K with average values < g > of 2.304-2.234 and g anisotropies Delta g = g(1)-g(3) of 0.82-0.99. Metal-to-metal charge transfer (MMCT) absorptions occur for 1(+)-5(+) in the NIR region at 1660 nm-1750 nm (epsilon approximate to 2700 dm(3) mol(-1) cm(-1), Delta nu(1/2) approximate to 1800 cm(-1)). DFT calculations of 1(+) and 3(+) yield comparable Mulliken spin densities of about 0.60 for the metal ions, corresponding to valence-delocalised situations (Ru-2.5)(2). Rather large spin densities of about -0.4 were calculated for the tppz bridges in 1(+) and 3(+). The calculated electronic interaction values (V-AB) for 1(+)-5(+) are about 3000 cm(-1), comparable to that for the Creutz-Taube ion at 3185 cm(-1). The DFT calculations predict that the (RuRuIII)-Ru-III forms in 12(+)-52(+) prefer a triplet (S = 1) ground state with Delta E (S = 0 - S = 1) similar to 5000 cm(-1). One-electron reduction takes place at the tppz bridge which results in species [Cl(L)Ru-II(mu-tppz(.-)) Ru-II(L)Cl](-) (1(.-)-3(.-), 5(.-)) which exhibit free radical-type EPR signals and NIR transitions typical of the tppz radical anion. The system 4(n) is distinguished by lability of the Ru-Cl bonds.

Synthesis and characterization of a new diol-functionalized s-triazine-based polymerizable hindered amine light stabilizer - Mehare, Rupali S.; Lonkar, Sunil P.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2012)
A new diol-functionalized triazine-based polymerizable hindered amine light stabilizer (HALS) was synthesized in two steps. First, selective synthesis of an s-triazine containing two HALS moieties as substituents was accomplished by using phase-transfer catalysis. This step required the establishment of optimum reaction conditions (type of two-phase system, best solvent, and catalyst). In the second step, the substituted triazine was treated with diethanolamine to introduce polymerizable diol functionality. The resulting product should act as a light stabilizer, since it contains two HALS moieties anchored to a thermally stable s-triazine unit. Moreover, incorporation of the diol into a polymeric material might be expected to impart prolonged stability in weathering environments. Characterization of the diol was accomplished by using Fourier transform infrared spectroscopy (FTIR), `H NMR, and mass spectrometry. J. VINYL ADDIT. TECHNOL., 18:204208, 2012. (c) 2012 Society of Plastics Engineers

Synthesis, characterization, and magnetic studies of coordination polymers with Co(II) and Mn(II) ions - Ahmad, Musheer; Das, Raja; Lama, Prem; Poddar, Pankaj; Bharadwaj, Parimal K. (Crystal Growth & Design, 2012)
{An ether bridged tricarboxylic acid ligand, 5-(4-carboxybenzyloxy)isophthalic acid (p-cbiaH(3)) has been used to construct three coordination polymers with Co(II) salts in presence of different nitrogen donor ligands such as 1,4-bis(4-pyridinylmethyl)piperazine (bpmp), dipyridine-4-yl-diazene (dpd), and 4,4'-bipyridine (bpy). The products formed under hydrothermal conditions are formulated as {[Co-3(p-cbia)(2)(bpmp)(2)(H2O)(6)]center dot 10H(2)O}(n) (1), {[Co-2(p-cbiaH)(2)(dpd)(H2O)(2)]\

Thermal, mechanical, and rheological characterization of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer Engineering and Science, 2012)
Polypropylene (PP)/organomodified layered double hydroxide (LDH) nanocomposites were prepared in order to examine the influence of LDH content on thermal, mechanical, and rheological properties. The nanostructure examinations by X-ray diffraction (XRD) and transmission electron microscopy (TEM) confirmed the exfoliated/intercalated dispersion of LDH. Incorporation of the LDH resulted in a noteworthy improvement in the thermal stability of PP. It was shown that the addition of LDH contributed to the reinforcement effect by increasing the elastic modulus. The mechanical performance, as evaluated by stressstrain curves, reveal that PP/LDH hybrid materials showed significant contribution toward increment in elastic modulus, tensile strength but at the expense of impact strength. The rheological response showed a strong influence of LDH particles on the flow behavior of the PP/LDH melt which resulted in enhancement of storage, loss of moduli, and complex viscosity of nanocomposites. Therefore, the nanocomposites have higher moduli but better processibility compared with pure PP. Overall, the results indicated that the LDH particles in nanometer size might act as potential reinforcing agent for polypropylene. POLYM. ENG. SCI., 52:20062014, 2012. (c) 2012 Society of Plastics Engineers

Transesterification of diethyl oxalate with phenol over sol-gel MoO3/TiO2 catalysts - Kotbagi, Trupti; Duy Luan Nguyen; Lancelot, Christine; Lamonier, Carole; Thavornprasert, Kaew-Arpha; Zhu Wenli; Capron, Mickael; Jalowiecki-Duhamel, Louise; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck (Chemsuschem, 2012)
The transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in the liquid phase over very efficient MoO3/TiO2 solid-acid solgel catalysts. A selectivity of 100?% with a remarkable maximum yield of 88?% were obtained, which opens the route to downstream phosgene-free processes for the synthesis of polycarbonates. Interpretation of the results of various acidity measurements (NH3 and pyridine desorption, methanol oxidation as a probe reaction) allowed us to identify the catalytic sites as Lewis acid sites.
Keywords: heterogeneous catalysis; Lewis acids; Oxidation; sol-gel processes; transesterification

Alishewanella solinquinati sp nov., isolated from soil contaminated with textile dyes - Kolekar, Yogesh M.; Pawar, Shrikant P.; Adav, Sunil S.; Zheng, Liu-Qiang; Li, Wen-Jun; Shouche, Yogesh S.; Dastager, Syed Gulam; Kodam, Kisan M. (Current Microbiology, 2013)
A novel Gram-negative, motile, rod-shaped, facultative anaerobic bacterial strain, KMK6(T), was isolated from soil contaminated with textile dyes from an industrial estate located at Ichalkaranji, Maharashtra, India, and its taxonomical position was established by using a polyphasic approach. The major cellular fatty acids included C-17:1 omega 8c, summed feature 3 (C-16:1 omega 7c and/or iso-C-15:0 2-OH), C-17:0, C-16:0,C- and C-18:1 omega 7c. The DNA G+C content of strain KMK6(T) was 48.8 mol %. 16S rRNA gene sequence analysis confirmed its placement in the genus Alishewanella, and exhibited sequence similarity levels of below 97 % to the type strains of validly published Alishewanella species. On the basis of genotypic and phenotypic evidence, strains KMK6(T) is considered to be a novel species of the genus Alishewanella, for which we propose that strain KMK6(T) (=NCIM 5295(T) =BCRC 17848(T)) is assigned to a novel species, Alishewanella solinquinati sp. nov.

Alterations in the helicoverpa armigera midgut digestive physiology after ingestion of pigeon pea inducible leucine aminopeptidase - Lomate, Purushottam R.; Jadhav, Bhakti R.; Giri, Ashok P.; Hivrale, Vandana K. (Plos One, 2013)
Jasmonate inducible plant leucine aminopeptidase (LAP) is proposed to serve as direct defense in the insect midgut. However, exact functions of inducible plant LAPs in the insect midgut remain to be estimated. In the present investigation, we report the direct defensive role of pigeon pea inducible LAP in the midgut of Helicoverpa armigera (Lepidoptera: Noctuidae) and responses of midgut soluble aminopeptidases and serine proteinases upon LAP ingestion. Larval growth and survival was significantly reduced on the diets supplemented with pigeon pea LAP. Aminopeptidase activities in larvae remain unaltered in presence or absence of inducible LAP in the diet. On the contrary, serine proteinase activities were significantly decreased in the larvae reared on pigeon pea LAP containing diet as compared to larvae fed on diet without LAP. Our data suggest that pigeon pea inducible LAP is responsible for the degradation of midgut serine proteinases upon ingestion. Reduction in the aminopeptidase activity with LpNA in the H. armigera larvae was compensated with an induction of aminopeptidase activity with ApNA. Our findings could be helpful to further dissect the roles of plant inducible LAPs in the direct plant defense against herbivory.

Ascertaining universal features of yielding of soft materials - Kamble, Samruddhi; Pandey, Anurag; Rastogi, Sanjay; Lele, Ashish K. (Rheologica Acta, 2013)
Many metastable complex fluids, when subjected to oscillatory shear flow of increasing strain amplitude at constant frequency, are known to show a characteristic nonlinear rheological response which consists of a monotonic decrease in the elastic modulus and a nonmonotonic change in the loss modulus. In particular, the loss modulus increases from its low strain value, crosses the elastic modulus, and then decreases with further increase in the strain amplitude. Miyazaki et al. (Europhys Lett 75:915-921, 2006) proposed a qualitative argument to explain the origin of the nonmonotonic nature of the loss modulus and suggested that in fact this response could be universal to all complex fluids if they are probed in a certain frequency window in which the fluid is dominantly elastic in the small strain limit. In this letter, we confirm their hypothesis by showing that a wide variety of complex fluids, irrespective of their thermodynamic state under quiescent conditions, indeed show the aforementioned characteristic nonlinear response. We also show that the maximum relative dissipation during yielding occurs when the imposed frequency resonates with the characteristic beta relaxation frequency of the fluid.
Keywords: Colloidal suspensions; Entangled melts; Gels; Glasses; Microgels; Rheology; Yielding

Band-like transport in high mobility unencapsulated single-layer MoS2 transistors - Jariwala, Deep; Sangwan, Vinod K.; Late, Dattatray J.; Johns, James E.; Dravid, Vinayak P.; Marks, Tobin J.; Lauhon, Lincoln J.; Hersam, Mark C. (Applied Physics Letters, 2013)
Ultra-thin MoS2 has recently emerged as a promising two-dimensional semiconductor for electronic and optoelectronic applications. Here, we report high mobility (>60 cm(2)/Vs at room temperature) field-effect transistors that employ unencapsulated single-layer MoS2 on oxidized Si wafers with a low level of extrinsic contamination. While charge transport in the sub-threshold regime is consistent with a variable range hopping model, monotonically decreasing field-effect mobility with increasing temperature suggests band-like transport in the linear regime. At temperatures below 100 K, temperature-independent mobility is limited by Coulomb scattering, whereas, at temperatures above 100 K, phonon-limited mobility decreases as a power law with increasing temperature. (C) 2013 AIP Publishing LLC.

Carrier free co-immobilization of alpha amylase, glucoamylase and pullulanase as combined cross-linked enzyme aggregates (combi-CLEAs): a tri-enzyme biocatalyst with one pot starch hydrolytic activity - Talekar, Sachin; Pandharbale, Amol; Ladole, Mayur; Nadar, Shamraja; Mulla, Mosin; Japhalekar, Kshitija; Pattankude, Kishori; Arage, Devika (Bioresource Technology, 2013)
A tri-enzyme biocatalyst ``combi-CLEAs'' with starch hydrolytic activity was prepared from commercially available alpha amylase, glucoamylase and pullulanase preparations by aggregating enzymes with ammonium sulphate followed by cross-linking formed aggregates for 4.5 h with 40 mM glutaraldehyde. The effects of precipitant type and cross-linking were studied and the biocatalyst was characterized. Scanning electron microscopy analysis showed that tri-enzyme biocatalyst was of spherical structure. For one pot starch hydrolytic activity, shift in optimum pH from 6 to 7 and temperature from 65 to 75 degrees C were observed after co-immobilization of enzymes. After one pot starch hydrolysis reaction in batch mode, 100%, 60% and 40% conversions were obtained with combi-CLEAs, separate CLEAs mixture and free enzyme mixture, respectively. Co-immobilization also enhanced the thermal stability of enzymes. Finally, the catalytic activity of enzymes in combi-CLEAs during one pot starch hydrolysis was well maintained up to five cycles without performance changes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Alpha amylase; Combined cross-linked enzyme aggregates (combi-CLEAs); Glucoamylase; One pot starch hydrolysis; Pullulanase

Catalytic dehydration of lactic acid to acrylic acid using calcium hydroxyapatite catalysts - Ghantani, Vidhya C.; Lomate, Samadhan T.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Green Chemistry, 2013)
A series of calcium hydroxyapatite (HAP) catalysts were synthesised with a Ca/P ratio ranging from 1.3 to 1.89 by a co-precipitation method that involved changing the pH of the calcium and phosphorous precursors. The physicochemical characterization by XRD, SEM, BET surface area and CO2 and NH3-TPD techniques confirmed the hydroxyapatite formation. These HAP catalysts were used for the vapour phase dehydration of lactic acid to acrylic acid. The HAP catalyst with a Ca/P ratio of 1.3 was found to be the most efficient catalyst among the synthesised series, which gave 100% conversion of lactic acid and 60% selectivity towards acrylic acid at 375 degrees C when a 50% (w/w) aqueous solution of lactic acid was used. The higher selectivity towards acrylic acid has been correlated to the increased acidity and reduced basicity of the HAP catalyst with a Ca/P ratio of 1.3 compared to the other HAP catalysts. The catalyst was found to be very stable and no deactivation was observed even after 300 h of reaction time. In situ FTIR studies were performed for understanding the mechanistic aspects and showed the formation of calcium lactate as an intermediate species during the dehydration of lactic acid to acrylic acid.

Catalytic transformation of alcohols to carboxylic acid salts and H2 using water as the oxygen atom source - Balaraman, Ekambaram; Khaskin, Eugene; Leitus, Gregory; Milstein, David (Nature Chemistry, 2013)
The oxidation of alcohols to carboxylic acids is an important industrial reaction used in the synthesis of bulk and fine chemicals. Most current processes are performed by making use of either stoichiometric amounts of toxic oxidizing agents or the use of pressurized dioxygen. Here, we describe an alternative dehydrogenative pathway effected by water and base with the concomitant generation of hydrogen gas. A homogeneous ruthenium complex catalyses the transformation of primary alcohols to carboxylic acid salts at low catalyst loadings (0.2 mol%) in basic aqueous solution. A consequence of this finding could be a safer and cleaner process for the synthesis of carboxylic acids and their derivatives at both laboratory and industrial scales.

Characterisation and determination of in vitro antioxidant potential of betalains from talinum triangulare (Jacq.) willd. - Swarna, J.; Lokeswari, T. S.; Smita, M.; Ravindhran, R. (Food Chemistry, 2013)
Talinum triangulare (Jacq.) Willd is an erect, succulent, perennial herb belonging to the family Portulacaceae. Under extreme environmental conditions, the plant produces betalain pigments which get accumulated in the stem region. Hence, in the present study, the betaxanthin and betacyanin patterns from different samples of T. triangulare have been investigated by applying high-performance liquid chromatography photo-diode array detection (HPLC-PDA) coupled with positive ion electro-spray mass spectrometry. Two betacyanins and two betaxanthins were identified in aqueous methanolic extract of flower, stem and leaf. Betanin, isobetanin, immonium conjugates of betalamic acid with dopamine and tyrosine were elucidated. The total betalain content was estimated by photometric analysis. In vitro antioxidant activity for the betalain extract determined by various methods revealed potent scavenging ability. The current work may possibly be considered beneficial in utilisation of the plant T. triangulare as a natural colourant in food and beverage industries. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Antioxidant; Betalains; HPLC-MS; Portulacaceae; Waterleaf

Characterization of a chemostable serine alkaline protease from Periplaneta americana - Sanatan, Prashant T.; Lomate, Purushottam R.; Giri, Ashok P.; Hivrale, Vandana K. (BMC Biochemistry, 2013)
Background: Proteases are important enzymes involved in numerous essential physiological processes and hold a strong potential for industrial applications. The proteolytic activity of insects' gut is endowed by many isoforms with diverse properties and specificities. Thus, insect proteases can act as a tool in industrial processes. Results: In the present study, purification and properties of a serine alkaline protease from Periplaneta americana and its potential application as an additive in various bio-formulations are reported. The enzyme was purified near to homogeneity by using acetone precipitation and Sephadex G-100 gel filtration chromatography. Enzyme activity was increased up to 4.2 fold after gel filtration chromatography. The purified enzyme appeared as single protein-band with a molecular mass of similar to 27.8 kDa in SDS-PAGE. The optimum pH and temperature for the proteolytic activity for purified protein were found around pH 8.0 and 60 degrees C respectively. Complete inhibition of the purified enzyme by phenylmethylsulfonyl fluoride confirmed that the protease was of serine-type. The purified enzyme revealed high stability and compatibility towards detergents, oxidizing, reducing, and bleaching agents. In addition, enzyme also showed stability towards organic solvents and commercial detergents. Conclusion: Several important properties of a serine protease from P. Americana were revealed. Moreover, insects can serve as excellent and alternative source of industrially important proteases with unique properties, which can be utilized as additives in detergents, stain removers and other bio-formulations. Properties of the P. americana protease accounted in the present investigation can be exploited further in various industrial processes. As an industrial prospective, identification of enzymes with varying essential properties from different insect species might be good approach and bioresource.
Keywords: Chemostability; Industrial catalyst; Insect proteases; Periplaneta americana; Serine alkaline protease

Chemically stable multilayered covalent organic nanosheets from covalent organic frameworks via mechanical delamination - Chandra, Suman; Kandambeth, Sharath; Biswal, Bishnu P.; Lukose, Binit; Kunjir, Shrikant M.; Chaudhary, Minakshi V.; BabaRao, Ravichandar; Heine, Thomas; Banerjee, Rahul (Journal of the American Chemical Society, 2013)
A series of five thermally and chemically stable functionalized covalent organic frameworks (COFs), namely, TpPa-NO2, TpPa-F-4, TpBD-(NO2)(2), TpBD-Me-2, and TpBD-(OMe)(2) were synthesized by employing the solvothermal aldehyde-amine Schiff base condensation reaction. In order to complete the series, previously reported TpPa-1, TpPa-2, and TpBD have also been synthesized, and altogether, eight COFs were fully characterized through powder X-ray diffraction (PXRD), Fourier transform IR (FT-IR) spectroscopy, C-13 solid-state NMR spectroscopy, and thermogravimetric analysis. These COFs are crystalline, permanently porous, and stable in boiling water, acid (9 N HCl), and base (3 N NaOH). The. synthesized COFs (all eight) were successfully delaminated using a simple, safe, and environmentally friendly mechanical grinding route to transform into covalent organic nanosheets (CONs) and were well characterized via transmission electron microscopy and atomic force microscopy. Further PXRD and FT-IR analyses confirm that these CONs retain their structural integrity throughout the delamination process and also remain stable in aqueous, acidic, and basic media like the parent COFs. These exfoliated CONs have graphene-like layered morphology (delaminated layers), unlike the COFs from which they were synthesized.

Chiral (VO)-O-IV-Sal-Indanol complex over modified SBA-15: an efficient, reusable enantioselective catalyst for asymmetric sulfoxidation reaction - Lazar, Anish; Sharma, Priti; Singh, A. P. (Microporous and Mesoporous Materials, 2013)
A reusable, mesoporous, heterogeneous vanadium complex, (VO)-O-IV-Sal-Ind-SBA-15 has been synthesized first time from (1R,2S)-(+)-Cis-1-amino-2-indanol for enantioselective sulfoxidation reaction. The physico-chemical properties of the functionalized catalyst were analyzed by a series of characterization techniques like XRD, N-2 sorption measurement isotherm, TEM, FT-IR, XPS, EPR, DRS UV-Visible, ICP-OES and solid & liquid state C-13, Si-29 and V-51 NMR spectroscopy. Powder X-ray diffraction patterns, TEM and N-2 physisorption analysis confirmed the retention of mesoporous structure after various modifications. Solid-state NMR (C-13 CP-MAS NMR, Si-29 MAS NMR) and FT-IR analysis certified the integrity of organo-catalyst residing inside the pore channels of the mesoporous support. Further, XPS, EPR, V-51 NMR and DRS UV-Visible analyses help to find out the oxidation state and coordination environment of vanadium in (VO)-O-IV-Sal-Ind-SBA-15. Catalytic evaluation in asymmetric sulfoxidation reaction of sulfides indicated that VOIV-Sal-Ind-SBA-15 exhibited higher catalytic activity, stability, reusability and comparable enantioselectivity than SBA-15, PrNH2-SBA-15, neat (VO)-O-IV-Sal-Indanol complex and without catalyst. The effect of different catalysts, temperature, solvents and substrates on sulfoxidation reaction were examined in order to optimize the conversion and enantioselectivity of thioanisoles to sulfoxides. Crown Copyright (C) 2012 Published by Elsevier Inc. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric sulfoxidation; Heterogeneous vanadium complex; Mesoporous; Thioanisole

Clay entrapped Cu(OH)(x) as an efficient heterogeneous catalyst for ipso-hydroxylation of arylboronic acids - Dar, Bashir Ahmad; Bhatti, Prince; Singh, A. P.; Lazar, Anish; Sharma, Parduman R.; Sharma, Meena; Singh, Baldev (Applied Catalysis A-General, 2013)
A remarkably active, selective and stable montmorilonite-KSF entrapped Cu(OH)(x) catalyst, has been prepared for the ipso-hydroxylation of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst shows excellent reusability without leaching and any significant loss in catalytic activity. The catalyst was characterized using, XRD, SEM, TPR, IR, XPS and BET surface area measurement techniques. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: clay; Copper; heterogeneous catalysis; Phenols; Water chemistry

Compensatory proteolytic responses to dietary proteinase inhibitors from Albizia lebbeck seeds in the helicoverpa armigera larvae - Hivrale, Vandana K.; Lomate, Purushottam R.; Basaiyye, Shriniwas S.; Kalve, Neeta D. (Arthropod-Plant Interactions, 2013)
Plant proteinase inhibitors (PIs) have been shown to reduce the growth rates in larvae of numerous insect species. On the other hand, insects can also regulate their proteinases against plant PIs. In the present study, we report the compensatory activities of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) gut proteinases against the PIs of Albizia lebbeck seeds. Total of ten proteinase inhibitor bands were detected in the seed extract of A. lebbeck. Bioassays were conducted by feeding H. armigera larvae on diet containing partially purified PIs from A. lebbeck seeds. Results show that larval growth and survival was significantly reduced by A. lebbeck PIs. We found that higher activity H. armigera gut proteinase (HGP) isoforms observed in the midgut of control larvae were inhibited in the midgut of larvae fed on test diet. Some HGP isoforms were induced in the larvae fed on PI containing test diet; however, these isoforms showed lower activity in the larvae fed on control diet. Aminopeptidase activities were significantly increased in the midgut of larvae fed on test diet. A population of susceptible and resistant enzymes was observed in the midgut of H. armigera, when fed on diet containing PIs from A. lebbeck seeds. Our initial observations indicate that H. armigera can regulate its digestive proteinase activity against non-host plant PIs, too. It is important to study the exact biochemical and molecular mechanisms underlying this phenomenon in order to develop PI-based insect control strategies.
Keywords: Albizia lebbeck; Helicoverpa armigera; Midgut proteinases; Proteinase inhibitors; regulation

Copolymerization of ethylene with unsaturated alcohols and methylmethacrylate using a silylated alpha-diimine nickel catalyst: molecular modeling and photodegradation studies - Matos, Ines; Fernandes, Susete N.; Liu, Hua-Rong; Tevtia, Amit K.; Singh, R. P.; Manda, Lemos; Lemos, Francisco; Marques, Maria M. (Journal of Applied Polymer Science, 2013)
In this article, the experimental results obtained in the copolymerization of ethylene with polar monomers using a silylated -diimine nickel catalyst are described and compared with those obtained with a non-silylate similar one. The results show that the introduction of a siliyl group in the para-position of the imine moiety turns the catalyst less sensitive toward polar functionalities. However, the reactivity observed in copolymerization reactions was found to be reduced both the global polymerization and incorporation rates. Molecular modeling calculation allowed us to understand both the preferred insertion mode and the intermediate product structures for E/MMA copolymerization. Photodegradation studies showed that the presence of polar groups in the copolymers increases their rate of oxidation and turn them more easily degradable. The stabilization performed by Tinuvin 770 showed that for long-exposure times, it is not very effective regardless it is only mixed or grafted to the copolymer. (c) 2012 Wiley Periodicals, Inc.
Keywords: ageing; copolymers; Degradation; grafting

Dehydration of fructose to 5-hydroxymethyl furfural over ordered AlSBA-15 catalysts - Lucas, Nishita; Kokate, Ganesh; Nagpure, Atul; Chilukuri, Satyanarayana V. (Microporous and Mesoporous Materials, 2013)
5-Hydroxymethyl furfural is an important platform chemical. It is successfully synthesized from renewable carbohydrates using mesoporous AlSBA-15 catalysts under biphasic conditions. Fine tuning of the catalyst acidity is important to drive the reaction to give good yields of furan compound. Al-SBA-15 catalysts with different Si/Al ratios were prepared and characterized by XRD, Al-27 MASNMR, SEM, TEM, N-2 sorption, ICP-OES and TPD of ammonia. Results show that part of aluminium is substituted into tetrahedral positions. The catalyst with lower acid site density but medium to strong acid strength favours selective formation of HMF. Under the optimized conditions, HMF selectivity was as high as 88% at 59 mol% conversion of fructose. Leaching of part of aluminium occurs under hydrothermal conditions, if solvent mixtures containing water are used, while activity can be retained if DMSO is used as solvent. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Acidity; AlSBA-15; dehydration; fructose; Hydroxymethyl furfural

Diethylamine: a smart organocatalyst in eco-safe and diastereoselective synthesis of medicinally privileged 2-amino-4H-chromenes at ambient temperature - Kulkarni, Makarand A.; Pandit, Kapil S.; Desai, Uday V.; Lad, Uday P.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
Diethylamine has been demonstrated to be an efficient organocatalyst in the diastereoselective synthesis of Bcl-2 protein antagonist (HA-14-1) and of its structural analogues by one-pot condensation between salicylaldehyde and three different C-H acids, viz, ethyl cyanoacetate, phenylsulfonyl acetonitrile, and malononitrile. Easy commercial availability of the catalyst at extremely low cost and avoidance of conventional work-up as well as purification procedures qualifies this scalable protocol for a ``near-ideal synthesis''. (c) 2013 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: 2-amino-4H-chromenes; Active methylene compounds (C-H acids); diethylamine; multicomponent reactions; organocatalyst

Enhanced field-emission behavior of layered MoS2 sheets - Kashid, Ranjit V.; Late, Dattatray J.; Chou, Stanley S.; Huang, Yi-Kai; De, Mrinmoy; Joag, Dilip S.; More, Mahendra A.; Dravid, Vinayak P. (Small, 2013)
Field emission studies are reported for the first time on layered MoS2 sheets at the base pressure of approximate to 1 x 10(-8) mbar. The turn-on field required to draw a field emission current density of 10 A/cm(2) is found to be 3.5 V/m for MoS2 sheets. The turn-on values are found to be significantly lower than the reported MoS2 nanoflowers, graphene, and carbon nanotube-based field emitters due to the high field enhancement factor (approximate to 1138) associated with nanometric sharp edges of MoS2 sheet emitter surface. The emission current-time plots show good stability over a period of 3 h. Owing to the low turn-on field and planar (sheetlike) structure, the MoS2 could be utilized for future vacuum microelectronics/nanoelectronic and flat panel display applications.

Enhancement of chemical stability and crystallinity in porphyrin-containing covalent organic frameworks by intramolecular hydrogen bonds - Kandambeth, Sharath; Shinde, Digambar Balaji; Panda, Manas K.; Lukose, Binit; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: covalent organic frameworks; hydrogen bonds; mesoporous materials; porphyrinoids; tautomerism

Enzymatic degumming of silk with microbial proteases - More, Shivaji V.; Khandelwal, Harish B.; Joseph, M. A.; Laxman, Ryali Seeta (Journal of Natural Fibers, 2013)
Degumming of Chinese bivoltine silk with alkaline proteases from various microbial sources was investigated and compared with commercial enzymes. Among the proteases tested, two fungal and two actinomycete proteases were promising, which showed weight loss similar to conventional method (19.58% to 21.78%). Conidiobolus brefeldianus and BOA-2 proteases were best enzymes, which showed weight loss similar to conventional method with low enzyme concentrations and in shorter time. No significant differences were found in tensile strength or elongation at break by enzymatic degumming indicating that there was no damage to the fiber. Scanning electron micrographs showed the sericin deposits were removed and the fibers were separated.
Keywords: Alkaline Protease; bivoltine; degumming; microbial; Silk; weight loss

Green synthesis of silver nanoparticles using sunlight - Bhaduri, Gaurav A.; Little, Ross; Khomane, Ramdas B.; Lokhande, Suhas U.; Kulkarni, Bhaskar D.; Mendis, Budhika G.; Siller, Lidija (Journal of Photochemistry and Photobiology A-Chemistry, 2013)
Silver nanoparticles (AgNPs) are currently among the most widely used man-made nanomaterials, present in a huge range of consumer products. Here we report a simple `green' method of AgNP synthesis of using an anionic surfactant without use of any additional reducing agents. It was observed that synthesis of AgNPs at room temperature (25-35 degrees C) using sodium dodecyl sulphate (SDS) and sunlight. The nanoparticles have been characterised using high-resolution transmission electron spectroscopy (HRTEM), UV-vis spectrophotometry, X-ray photoelectron spectroscopy (XPS) and Fourier Transform Infrared Spectroscopy (FTIR) and are found to have an average diameter of 30 nm. The nanoparticles are water soluble and the nature of the process is amenable to scaling up. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: photochemistry; silver nanoparticles; Sodium dodecyl sulphate; XPS

HBGS (hydrate based gas separation) process for carbon dioxide capture employing an unstirred reactor with cyclopentane - Ho, Leong Chuan; Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
The effect of CP (cyclopentane) as a promoter/additive, in the HBGS (hydrate based gas separation) process for pre-combustion gas mixture was investigated by employing an unstirred reactor configuration. Gas uptake measurements were performed at two different temperatures (275.7 K and 285.7 K) and at an experimental pressure of 6.0 MPa to determine the kinetics of hydrate formation. Experiments were conducted with three different volumes (7.5, 15 and 22 ml) of CP and based on induction time and the rate of hydrate growth, 15 ml of CP was determined to be the optimal volume for carbon dioxide capture at 6.0 MPa and 275.7 K. In addition, the effect of a kinetic promoter, SDS (sodium dodecyl sulfate), was investigated. Surprisingly, no improvement in kinetic performance was observed at 6.0 MPa and 275.7 K in the presence of SDS and CP. From the study, it was found that at the optimal 15 ml CP (CP layer thickness of 1.8 mm), the average composition of carbon dioxide in the hydrate phase was 90.36 mol% with a separation factor of 17.82. Furthermore, the unstirred reactor also yielded better kinetic performance over the stirred tank reactor with the unstirred reactor having a 2.28 times higher average gas uptake. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Cyclopentane; Gas hydrates; Gas separation; Pre-combustion; Unstirred reactor

Hydrate phase equilibrium of ternary gas mixtures containing carbon dioxide, hydrogen and propane - Babu, Ponnivalavan; Yang, Ting; Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Journal of Chemical Thermodynamics, 2013)
Hydrate phase equilibrium of the ternary guest mixtures containing carbon dioxide, hydrogen and propane at two different compositions were determined. Addition of mole composition of 2.5% propane to the fuel gas (CO2 (40%)/H-2 (60%)) mixture reduces the hydrate formation conditions by 66% at the temperature of 278.4 K. A Clausius-Clapeyron plot for the experimental results was plotted and from the slope, the enthalpy of hydrate dissociation was calculated. The enthalpy of dissociation of the mixed hydrate formed from a ternary gas mixture containing mole composition 38.1% CO2, 59.4% H-2 and 2.5% C3H8 was found to be 110 kJ.mol(-1) and hence it was concluded that the mixed hydrate formed structure II (sII) hydrates. Whereas for the ternary gas mixture containing mole composition 80.0% CO2, 18.8% H-2, and 1.2% C3H8, the enthalpy of dissociation of the mixed hydrate was found to be 78 kJ.mol(-1) and hence we believe the mixed hydrate formed structure I (sI) hydrate. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Phase equilibrium; Pre-combustion; Thermodynamics

Hydroxyapatite supported palladium catalysts for suzuki-miyaura cross-coupling reaction in aqueous medium - Indra, Arindam; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Catalysis Science & Technology, 2013)
Supported palladium catalyst 1 has been prepared by the immobilisation of [Pd(COD)Cl-2] (COD = 1,5-cyclooctadiene) on hydroxyapatite. Catalyst 2 has been prepared by subsequent reduction of catalyst 1 with sodium borohydride in ethanol. Under similar reaction conditions, catalyst 1 with Pd2+, is found to be almost five times more active than 2. Using 1 as the catalyst and water as the solvent, reaction conditions for Suzuki-Miyaura cross-coupling reactions have been optimised under aerobic conditions. The best catalytic activities are observed in the presence of potassium carbonate as the base and tetrabutylammonium bromide as a promoter. Catalyst 1 has been tested for catalytic cross-coupling reactions with sixteen different, electronically neutral, electron rich, electron poor and sterically hindered aryl boronic acids, and several different aryl halides including aryl chlorides. More than thousand turnovers and high selectivities to the hetero-coupled products have been observed in most cases. For many substrates the turnovers with 1 are notably more than what has been reported with other supported catalysts in water. The recyclability and scale-up potential of catalyst 1 have been tested and found to be satisfactory. A negligible drop in activity is observed over ten recycles with an accumulated turnover number of similar to 30000.

Imprinted electrodes for enhanced light trapping in solution processed solar cells - Mihi, Agustin; Beck, Fiona J.; Lasanta, Tania; Rath, Arup Kumar; Konstantatos, Gerasimos (Advanced Materials, 2013)

Influence of contact medium and surfactants on carbon dioxide clathrate hydrate kinetics - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Fuel, 2013)
Carbon dioxide (CO2) hydrate formation kinetic was investigated in a fixed bed crystallizer at constant pressure (3.55 MPa) and temperature (274 K). Porous media of three different silica gels were used, with a mesh size of 60-120, 100-200 and 230-400 having different surface area. The observed trends indicate that silica gel with larger surface area leads to higher gas consumption as well as reduces the induction time. The effect of pore diameter and particle size distribution has already been reported in a previous study [1]. In this study the effect of additives on hydrate formation kinetics were also investigated. The additives studied were nonionic surfactant Tween-80 (T-80), cationic dodecyltrimethylammonium chloride (DTACl) and anionic Sodium Dodecyl Sulphate (SDS). Out of the three surfactants used in this study, SDS was found to be most effective in enhancing the rate of hydrate formation as well as reducing the induction time. The current result shows significant improvement in water to hydrate conversion in silica gel media compared to quiescent water or surfactant-water system under similar conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrate; kinetics; Silica gel; Surfactants

Mechanistic approach for expeditious and solvent-free synthesis of alpha-hydroxy phosphonates using potassium phosphate as catalyst - Kulkarni, Makarand A.; Lad, Uday P.; Desai, Uday V.; Mitragotri, Satish D.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
An extremely simple, high yielding, highly rapid and solvent-free protocol has been described for hydrophosphylation of aldehydes using potassium phosphate as catalyst. Easy commercial availability of the reusable catalyst, operational simplicity at ambient temperature and avoidance of conventional work-up as well as purification procedure makes this solvent-free protocol a near-ideal synthesis. (C) 2012 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: alpha-hydroxy phosphonates; Hydrophosphylation; Potassium phosphate; Solvent-free

Mechanochemical synthesis of chemically stable isoreticular covalent organic frameworks - Biswal, Bishnu P.; Chandra, Suman; Kandambeth, Sharath; Lukose, Binit; Heine, Thomas; Banerjeet, Rahul (Journal of the American Chemical Society, 2013)
Three thermally and chemically stable isoreticular covalent organic frameworks (COFs) were synthesized via room-temperature solvent-free mechanochemical grinding. These COFs were successfully compared with their solvothermally synthesized counterparts in all aspects. These solvent-free mechanochemically synthesized COFs have moderate crystallinity with remarkable stability in boiling water, acid (9 N HCl), and base [TpBD (MC) in 3 N NaOH and TpPa-2 (MC) in 9 N NaOH]. Exfoliation of COF layers was simultaneously observed with COF formation during mechanochemical synthesis. The structures thus obtained seemed to have a graphene-like layered morphology (exfoliated layers), unlike the parent COFs synthesized solvothermally.

Medium pressure hydrate based gas separation (HBGS) process for pre-combustion capture of carbon dioxide employing a novel fixed bed reactor - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (International Journal of Greenhouse Gas Control, 2013)
This work presents an effective medium pressure hydrate based gas separation (HBGS) process for pre-combustion carbon dioxide capture in a novel fixed bed column. 2.5 mol% propane was added to the fuel gas mixture as an additive to decrease the operating pressure of the HBGS process. Hydrate formation kinetics was investigated at three different pressures (4.5, 5.5 and 6.0 MPa respectively) and at 274.15 K. The performance of silica sand and silica gel as a medium was evaluated. In silica sand bed, multiple nucleation events were observed. In silica gel bed, the gas uptake and water conversion to hydrates was significantly low at any given driving force than that obtained in silica sand bed. Experiments at different water saturation levels (50, 75 and 100%) in silica sand bed were investigated at 6.0 MPa and 274.15 K. It was found that at 50% water saturation, gas consumed for hydrate formation and water conversion to hydrates was almost three times that at 100% saturation. Water to hydrate conversions of up to 64.3% was achieved after 4 h of hydrate formation for the 50% water saturated silica sand bed. Our study presents an opportunity to scale up the HBGS process for CO2 capture with enhanced kinetics by employing a fixed bed reactor configuration. Decomposition experiments at a driving force of Delta T of 10 K and 23K were carried out to recover the gas consumed for hydrate formation and it was found that Delta T of 23 K was sufficient to recover the hydrated gas. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Pre-combustion; Separation

Molecular insights into resistance mechanisms of lepidopteran insect pests against toxicants - Dawkar, Vishal V.; Chikate, Yojana R.; Lomate, Purushottam R.; Dholakia, Bhushan B.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Proteome Research, 2013)
Insect pests remain a major reason for crop loss worldwide despite extensive use of chemical insecticides. More than B 50% of all insecticides are organophosphates, followed by synthetic pyrethroids, organochlorines, carbamates, and biopesticides, and their continued use may have many environmental, agricultural, medical, and socioeconomic issues. Importantly, only a countable number of insects have acquired the status of crop pests, mostly due to monoculture of crop plants and polyphagous nature of the insects. We focus on A adaptations of Lepidopteran insects to phytochemicals and synthetic pesticides in native and modern agricultural systems. Because of heavy use of chemical insecticides, a strong selection pressure is imposed on insect populations, resulting in the emergence of resistance against candidate compound(s). Current knowledge suggests that insects generally implement a three-tier system to overcome the effect of toxic compounds at physiological, biochemical, and genetic levels. Furthermore, we have discussed whether the adaptation to phytochemicals provides an advantage to the insect while encountering synthetic insecticide molecules. Specific metabolic pathways employed by insects to convert deterrents into less toxic forms or their removal from the system are highlighted. Using the proteomics approach, insect proteins interacting with insecticides can be identified, and their modification in resistant insects can be characterized. Also, systems biology studies can offer useful cues to decipher the molecular networks participating in the metabolism of detrimental compounds.
Keywords: field crops; insect-pests; insecticide; Lepidoptera; proteomics; resistance mechanisms

Molecular mapping of leaf rust resistance gene Lr15 in hexaploid wheat - Dholakia, Bhushan B.; Rajwade, A. V.; Hosmani, P.; Khan, R. R.; Chavan, S.; Reddy, D. M. R.; Lagu, Meena D.; Bansal, Urmil K.; Saini, R. G.; Gupta, V. S. (Molecular Breeding, 2013)
Leaf rust is a widespread and commonly occurring rust disease of wheat. Genetic resistance is the most economical method of reducing losses due to leaf rust. Lr15 has been shown to be present on wheat chromosome 2D and is reported to be a seedling resistance gene. However, tightly linked markers associated with Lr15 have not been reported to date. To identify molecular markers linked to Lr15, an F-2 mapping population of Thatcher x Thatcher-Lr15 was generated. Available wheat simple sequence repeat markers were utilized in parental screening and polymorphic markers were used to analyze the entire population of 221 plants. Phenotypic evaluations of the F-2-derived F-3 progenies with Puccinia triticina Eriks. pathotype 162A (93R15) confirmed the monogenic inheritance of Lr15. The linkage group representing chromosome 2DS was constructed at LOD 4.0 which revealed the closest flanking markers Xgwm4562 and Xgwm102 at a distance of 3.1 and 9.3 cM, respectively. Furthermore, utilization of these flanking markers in combination has successfully identified wheat lines with or without Lr15. These markers could potentially be useful in gene pyramiding with other genes to enhance rust resistance in wheat.
Keywords: Disease resistance; Leaf rust; Marker-assisted selection; Simple sequence repeat; Wheat

Morphology of carbon dioxide-hydrogen-cyclopentane hydrates with or without sodium dodecyl sulfate - Lim, Yu-An; Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Crystal Growth & Design, 2013)
In this study, effects of cyclopentane (CP) and sodium dodecyl sulfate (SDS) on the hydrate formation morphology were investigated. A gas mixture of 40.0 mol % carbon dioxide and 60.0 mol % hydrogen was used in an unstirred system with subcooling as the driving force. Experimental pressure is at 6.0 MPa and experimental temperatures used are at 275.65 and 277.65 K (Delta T = 15.15 and 13.15 K). Formation of hydrates started at the cyclopentane-liquid water interface. Cloud-like, equiaxed skewed dendritic, equiaxed orthogonal dendritic, long dendritic, and cactus-like crystals could be observed for the experiments in the absence of surfactants. Rapid hydrate formation was observed for the experiments with 0.9 mL CP with or without the presence of surfactants compared to the experiments with 0.45 mL CP system at the same experimental conditions. The addition of SDS had led to a change in the hydrate crystal morphology, forming fiber-like crystals from the hydrate layer. Hydrates had also shown affinity to metal surfaces and tend to grow rapidly because of better heat transfer capacity. Gas uptake measurements were found to correlate well with the morphological observations. On the basis of the morphological observations, the mechanism of the CO2-H-2-CP system in an unstirred system is presented.

Morphology, polymorphism, and metal ion adsorption studies of electrospun nanofibers based on pvdf and organically modified layered double hydroxide - Birajdar, Mallinath S.; Wanjale, Santosh D.; Lonkar, Sunil P. (Journal of Applied Polymer Science, 2013)
Nonwoven nanofiber mats of polyvinylidene fluoride (PVDF) with modified layered double hydroxide (MLDH) were prepared by electrospinning. The fiber morphology was studied using scanning electron microscopy. X-ray diffraction and FTIR spectroscopy was used to characterize the polymorphism in electrospun mats. Fibers of diameter in the range 80-800 nm with beads of about 2-3 mu m size were observed for pure PVDF, while in case of PVDF/MLDH nanocomposites the number and size of beads were found to be significantly reduced. Uniform and fine nanofibers were obtained at lower content of MLDH, but slightly rough surface was seen for higher content. FTIR and X-ray diffraction patterns signify various crystalline forms of electrospun PVDF. The content of polar -crystalline phase of PVDF, which exhibit piezo and ferroelectric properties was found to be enhanced significantly due to reinforcement of MLDH. Use of these nanofiber mats for heavy metal Cu (II) removal was explored. (c) 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 4508-4515, 2013
Keywords: Adsorption; electrospinning; fibers

Necking in extrusion film casting: the role of macromolecular architecture - Pol, Harshawardhan V.; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Journal of Rheology, 2013)
Extrusion film casting (EFC) is used on an industrial scale to produce several thousand tons of polymer films and coatings. While significant research has been carried out on necking of films of viscoelastic melts in EFC, the influence of macromolecular chain architecture on the necking behavior is not yet fully understood. In the present research, we have explored experimentally and theoretically the effects of long chain branching and molecular weight distribution on the extent of necking during EFC. Polyethylenes of essentially linear architecture but having narrow and broad molecular weight distributions, and polyethylenes having long chain branching were used for experimental studies. The EFC process was analyzed using the one-dimensional flow model of Silagy et al. [Polym. Eng. Sci. 36(21), 2614-2625 (1996)] in which multimode molecular constitutive equations namely the ``extended pom-pom'' equation (for long chain branched polymer melts) and the ``Rolie-Poly (Rouse linear entangled polymers)'' equation (for linear polymer melts) were incorporated. We show that the model qualitatively captures the salient features of the experimental data thereby elucidating the role of chain architecture on the extent of necking. (C) 2013 The Society of Rheology. [http://dx.doi.org/10.1122/1.4788911]

New porous material to enhance the kinetics of clathrate process: application to precombustion carbon dioxide capture - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Environmental Science & Technology, 2013)
In this work, the performance of a new porous medium, polyurethane (PU) foam in a fixed bed reactor for carbon dioxide separation from fuel gas mixture using the hydrate based gas separation process is evaluated. The kinetics of hydrate formation in the presence of 2.5 mol % propane as thermodynamic promoter was investigated at 4.5, 5.5, and 6.0 MPa and 274.2 K. Significantly higher gas consumption and water conversion to hydrate was achieved when PU foam was employed. PU foam as a porous medium can help convert 54% of water to hydrate in two hours of hydrate formation. In addition the induction times were very low (<3.67 min at 6.0 MPa). A normalized rate of hydrate formation of 64.48 (+/- 3.82) mol.min(-1).m(-3) was obtained at 6.0 MPa and 274.2 K. Based on a morphological study, the mechanism of hydrate formation from water dispersed in interstitial pore space of the porous medium is presented. Finally, we propose a four step operation of the hydrate based gas separation process to scale up.

New receptor with a FRET based fluorescence response for selective recognition of fumaric and maleic acids in aqueous medium - Reddy, Upendar G.; Lo, Rabindranath; Roy, Sovan; Banerjee, Tanmay; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2013)
Preferential binding of a new reagent to fumaric acid could be utilized for its estimation in aqueous medium and in commercial fruit juice.

N-Heterocyclic carbene catalyzed esterification of aromatic aldehydes with alcohols under aerobic conditions - Kiran, I. N. Chaithanya; Lalwani, Komal G.; Sudalai, Arumugam (RSC Advances, 2013)
A simple, organocatalytic procedure for the direct oxidative esterification of a variety of aromatic aldehydes with alcohols has been described that affords the corresponding aromatic esters in high yields. The method employs N-heterocyclic carbenes as catalysts and molecular O-2 as an oxidant under ambient conditions.

One pot solvent free synthesis and in vitro antitubercular screening of 3-aracylphthalides against mycobacterium tuberculosis - Limaye, Rohan A.; Kumbhar, Virendra B.; Natu, Arun D.; Paradkar, Madhusudan V.; Honmore, Varsha S.; Chauhan, Rubia R.; Gample, Suvarna P.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2013)
One pot synthesis of 3-Aracylphthalide was accomplished in good yield by reacting 2-carboxy benzaldehyde with various aromatic methyl ketones in presence of methane sulphonic acid. Various phthalides thus obtained were characterized with spectral techniques. These phthalides were subjected to in vitro antitubercular screening against Mycobacterium tuberculosis H37Ra (MTB) by using XRMA protocol. Among the phthalides screened, four exhibited half maximal inhibitory concentration (IC50) in the range of 0.81-1.24 mu g/ml thereby providing potential lead compounds for future drug discovery studies. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 3-Aracylphthalide; Antitubercular activity; Methane sulphonic acid; One pot synthesis

One-pot migration-formylation of benzyl aryl ethers under duff reaction condition - Chavan, Subhash P.; Lasonkar, Pradeep B. (Tetrahedron Letters, 2013)
A one-pot migration-formylation of benzyl aryl ethers under Duff reaction condition is described. The reaction was performed with HMTA (hexamethylene tetramine) and TFA (trifluoroacetic acid). Under the optimal reaction conditions, a variety of Bn and PMB ethers underwent ortho rearrangement. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzyl aryl ethers; Duff reaction; Hexamethylene tetramine; One-pot; ortho Rearrangement

PNN-Ru pincer complexes based on phosphinated 2,2’-dipyridinemethane- and 2,2’-oxobispyridine. metal-ligand cooperation in cyclometallation and catalysis - Barrios-Francisco, Rigoberto; Balaraman, Ekambaram; Diskin-Posner, Yael; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2013)
The synthesis of novel PNN ruthenium pincer complexes based on 2,2′-dipyridinemethane phosphine derivatives, as well as on 2,2′-oxobispyridine phosphine ligands, and their reactivity toward dearomatization and cyclometalation are described. The dearomatized compounds 7a,b undergo cyclometalation to yield complexes 8a,b. In order for cyclometalation to proceed, the coordination sphere around the Ru center has to rearrange, and this depends on the flexibility of the system, showing that the cyclometalation is qualitatively faster in the case of the dimethyl derivative 7a than in the case of the spyrocyclopentyl derivative 7b. The cyclometalation occurs diastereoselectively and leads to only one diastereomer of the cyclometalated compounds. In the case of the 2,2′-oxobispyridine complex 6c, the dearomatized complex was too unstable to be isolated; however it was possible to isolate and characterize a stable dicarbonyl-dearomatized ruthenium(II) complex, 9c, when the deprotonation was performed under a CO atmosphere. Dearomatization of 6a under CO also led to dicarbonyl-dearomatized ruthenium(II) complex 9a, which slowly rearranged into the dicarbonyl-aromatized ruthenium(0) complex 10a. These complexes were tested in catalytic alcohol–amine coupling, esterification of primary alcohols, and hydrogenation of secondary amides. Moderate activity was observed in hydrogenation of amides to alcohols and amines and low activity in the other transformations, owing mainly to the formation of stable cyclometalated compounds.

Poly-L-arginine grafted silica mesoporous nanoparticles for enhanced cellular uptake and their application in DNA delivery and controlled drug release - Kar, Mrityunjoy; Tiwari, Neha; Tiwari, Mitali; Lahiri, Mayurika; Sen Gupta, Sayam (Particle & Particle Systems Characterization, 2013)
Mesoporous silica nanoparticles (MSNs), that are capable of delivering gene and drugs to organisms in an effective and selective way have attracted much attention lately for its potential in the treatment of cancer. However, the successful application of MSNs for delivery of plasmid DNA or drugs requires surface modification of the silica with positively charged functional groups so that it binds to the negatively charged nucleic acids and also helps it penetrate through the cell membrane. We report for the first time the synthesis of a hybrid MSN where the cell penetrating cationic polypeptide poly-L-arginine synthesized by NCA polymerization is grafted onto the external surface of MSN using click chemistry. These poly-L-arginine grafted MSNs show low cytotoxity (85% cell viability at 100 g/mL MSN concentration) and high cellular uptake by both HeLa and A549 (>90%). The poly-L-arginine grafted MSNs were used effectively to deliver mCherry DNA plasmid into cells leading to expression of the protein mCherry inside the cells (transfection efficiency 60%). In contrast, poly-L-arginine grafted non-porous silica nanoparticles were unable to express the protein mCherry inside the cells although their uptake into the cells was as efficient as with poly-L-arginine grafted MSNs. We also show preliminary results to demonstrate that these hybrid MSNs can be used as a delivery vehicle for the anticancer drug Doxorubicin towards cancerous cells HeLa and A549. The biocompatibility of poly-L-arginine and its cell penetrating ability are expected to make these MSN conjugates very useful carriers for the delivery of genes and drugs into cancer cells.

Pre-combustion capture of carbon dioxide in a fixed bed reactor using the clathrate hydrate process - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
Hydrate based gas separation (HBGS) process with silica sand and silica gel as contact medium was employed to capture CO2 from fuel gas mixture. Gas uptake measurement at three different pressures (7.5, 8.5 and 9.0 MPa) and 274.15 K were conducted for hydrate formation kinetics and overall conversion of water to hydrate, rate of hydrate formation were determined. Water conversion of up to 36% was achieved with silica sand bed compared to 13% conversion in the silica gel bed. Effect of driving force on the rate of hydrate formation and gas consumption was significant in silica sand bed whereas it was found to be insignificant in silica gel bed. Hydrate dissociation experiments by thermal stimulation (at constant pressure) alone and a combination of depressurization and thermal stimulation were carried out for complete recovery of the hydrated gas. A driving force of 23 K was found to be sufficient to recover all the hydrated gas within 1 h. This study indicates that silica sand can be an effective porous media for separation of CO2 from fuel gas when compared to silica gel. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrates; Gas separation; Global warming; Pre-combustion

Promising stability of gold-based catalysts prepared by direct anionic exchange for DeNO (x) applications in lean burn conditions - Nguyen, D. -L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Topics in Catalysis, 2013)
Supported gold catalysts on gamma-Al2O3 have been investigated in the catalytic reduction of NO (x) in simulated Diesel exhaust gas conditions. Different parameters have been examined essentially the mode of gold incorporation via classical deposition-precipitation and anionic exchange methods and the nature of the pre-activation thermal treatment. The resistance to thermal ageing under reactive conditions at 500 A degrees C was found completely different with a significant rate enhancement on anionic-exchange samples. Further comparisons also show that the nature of the pre-activation thermal treatment influences the extent of surface reconstructions during thermal ageing with a detrimental effect of reductive pre-treatment on the catalytic performances.
9th International Congress on Catalysis and Automotive Pollution Control (CAPoC), Brussels, BELGIUM, AUG 29-31, 2012
Keywords: Anionic-exchange; Au/Al2O3 catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Rheology and microstructural studies of regenerated silk fibroin solutions - Nisal, Anuya; Kalelkar, Chirag; Bellare, Jayesh R.; Lele, Ashish K. (Rheologica Acta, 2013)
Regenerated silk fibroin solutions (RSF) are produced by dissolving degummed silk fibers in water. We have observed that RSF solutions at a concentration less than 15 % by weight exhibit an unusual gel-like response in conventional shear rheology measurements. At higher concentrations, the response is predominantly viscous (or liquid-like). We have probed this counterintuitive behavior of silk fibroin solutions by using microrheology, and interfacial rheometry. Scattering techniques were also used to understand the microstructure of RSF solutions as a function of the concentration. Our studies suggest that the gel-like response of the RSF solution may result from the formation of an interfacial film at the air-solution interface, which dominates the bulk rheological response.
Keywords: Interfacial rheology; Microrheology; Rheology; Silk

Sensing behavior of atomically thin-layered MoS2 transistors - Late, Dattatray J.; Huang, Yi-Kai; Liu, Bin; Acharya, Jagaran; Shirodkar, Sharmila N.; Luo, Jiajun; Yan, Aiming; Charles, Daniel; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ACS Nano, 2013)
Most of recent research on layered chalcogenides is understandably focused on single atomic layers. However, it is unclear if single-layer units are the most ideal structures for enhanced gas solid interactions. To probe this issue further, we have prepared large-area MoS2 sheets ranging from single to multiple layers on 300 nm SiO2/Si substrates using the micromechanical exfoliation method. The thickness and layering of the sheets were identified by optical microscope, invoking recently reported specific optical color contrast, and further confirmed by AFM and Raman spectroscopy. The MoS2 transistors with different thicknesses were assessed for gas-sensing performances with exposure to NO2, NH3, and humidity in different conditions such as gate bias and light Irradiation. The results show that, compared to the single-layer counterpart, transistors of few MoS2 layers exhibit excellent sensitivity, recovery, and ability to be manipulated by gate bias and green light. Further, our ab initio DFT calculations on single-layer and bilayer MoS2 show that the charge transfer is the reason for the decrease in resistance in the presence of applied field.

Simple synthesis of the novel antihistaminic drug olopatadine hydrochloride - Chavan, Subhash P.; Lasonkar, Pradeep B. (Synthesis-Stuttgart, 2013)
A new alternative route for the synthesis of olopatadine is described. The present strategy involves a Lewis acid mediated ring opening of a cyclic ether to introduce 3-(dimethylamino)propylidene group as the side chain.
Keywords: antihistaminic drugs; chelates; Lewis acids; spiro compounds; zinc

Stepwise metal-ligand cooperation via a reversible aromatization-deconjugation-sequence in ruthenium complexes with a tetradentate phenanthroline-based ligand - Langer, Robert; Fuchs, Ido; Vogt, Matthias; Balaraman, Ekambaram; Diskin-Posner, Yael; Shimon, Linda J. W.; Ben-David, Yehoshoa; Milstein, David (Chemistry - A European Journal, 2013)
The synthesis and reactivity of ruthenium complexes containing the tetradentate phenanthroline-based phosphine ligand 2,9-bis((di-tert-butylphosphino)methyl)-1,10-phenanthroline (PPhenP) is described. The hydrido chloro complex [RuHCl(PPhenP)] (2) undergoes facile dearomatization upon deprotonation of the benzylic position, to give [RuH(PPhenP-H)] (4). Addition of dihydrogen to 4 causes rearomatization of the phenanthroline moiety to trans-[Ru(H)2(PPhenP)] (5), followed by hydrogenation of an aromatic heterocycle in the ligand backbone, to give a new dearomatized and deconjugated complex [RuH(PPhenP*-H)] (6). These aromatization/deconjugation steps of the coordinated ligand were demonstrated to be reversible and operative in the dehydrogenation of primary alcohols without the need for a hydrogen acceptor. This aromatization/deconjugation sequence constitutes an unprecedented mode of a stepwise cooperation between the metal center and the coordinated ligand.

Superior field emission properties of layered WS2-RGO nanocomposites - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Scientific Reports, 2013)
We report here the field emission studies of a layered WS2-RGO composite at the base pressure of similar to 1 x 10(-8) mbar. The turn on field required to draw a field emission current density of 1 mu A/cm(2) is found to be 3.5, 2.3 and 2 V/mu m for WS2, RGO and the WS2-RGO composite respectively. The enhanced field emission behavior observed for the WS2-RGO nanocomposite is attributed to a high field enhancement factor of 2978, which is associated with the surface protrusions of the single-to-few layer thick sheets of the nanocomposite. The highest current density of similar to 800 mu A/cm(2) is drawn at an applied field of 4.1 V/mu m from a few layers of the WS2-RGO nanocomposite. Furthermore, first-principles density functional calculations suggest that the enhanced field emission may also be due to an overalp of the electronic structures of WS2 and RGO, where graphene-like states are dumped in the region of the WS2 fundamental gap.

Synthesis, structures, and dearomatization by deprotonation of iron complexes featuring bipyridine-based PNN pincer ligands - Zell, Thomas; Langer, Robert; Iron, Mark A.; Konstantinovski, Leonid; Shimon, Linda J. W.; Diskin-Posner, Yael; Leitus, Gregory; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Inorganic Chemistry, 2013)
The synthesis and characterization of new iron pincer complexes bearing bipyridine-based PNN ligands is reported. Three phosphine-substituted pincer ligands, namely, the known tBu-PNN (6-((di-tert-butylphosphino)methyl)-2,2′-bipyridine) and the two new iPr-PNN (6-((di-iso-propylphosphino)methyl)-2,2′-bipyridine) and Ph-PNN (6-((diphenylphosphino)methyl)-2,2′-bipyridine) ligands were synthesized and studied in ligation reactions with iron(II) chloride and bromide. These reactions lead to the formation of two types of complexes: mono-chelated neutral complexes of the type [(R-PNN)Fe(X)2] and bis-chelated dicationic complexes of the type [(R-PNN)2Fe]2+. The complexes [(R-PNN)Fe(X)2] (1: R = tBu, X = Cl, 2: R = tBu, X = Br, 3: R = iPr, X = Cl, and 4: R = iPr, X = Br) are readily prepared from reactions of FeX2 with the free R-PNN ligand in a 1:1 ratio. Magnetic susceptibility measurements show that these complexes have a high-spin ground state (S = 2) at room temperature. Employing a 2-fold or higher excess of iPr-PNN, diamagnetic hexacoordinated dicationic complexes of the type [(iPr-PNN)2Fe](X)2 (5: X = Cl, and 6: X = Br) are formed. The reactions of Ph-PNN with FeX2 in a 1:1 ratio lead to similar complexes of the type [(Ph-PNN)2Fe](FeX4) (7: X = Cl, and 8: X = Br). Single crystal X-ray studies of 1, 2, 4, 6, and 8 do not indicate electron transfer from the FeII centers to the neutral bipyridine unit based on the determined bond lengths. Density functional theory (DFT) calculations were performed to compare the relative energies of the mono- and bis-chelated complexes. The doubly deprotonated complexes [(R-PNN*)2Fe] (9: R = iPr, and 10: R = Ph) were synthesized by reactions of the dicationic complexes 6 and 8 with KOtBu. The dearomatized nature of the central pyridine of the pincer ligand was established by X-ray diffraction analysis of single crystals of 10. Reactivity studies show that 9 and 10 have a slightly different behavior in protonation reactions.

Ultrasound promoted efficient and green protocol for the expeditious synthesis of 1, 4 disubstituted 1, 2, 3-triazoles using Cu(II) doped clay as catalyst - Dar, Bashir Ahmad; Bhowmik, Amrita; Sharma, Amit; Sharma, Parduman R.; Lazar, Anish; Singh, A. P.; Sharma, Meena; Singh, Baldev (Applied Clay Science, 2013)
Cu(II) doped clay catalyst has been prepared by an easy technique from inexpensive starting materials and investigated for the one pot synthesis of 1, 4-disubstituted 1, 2, 3-triazoles via Huisgen [3 + 2] cycloaddition under ultrasonic irradiation at room temperature. The catalyst is highly active, selective, and stable and can be reused several times. The prepared catalyst has been characterized by XRD, BET-SA, H-2-TPR, SEM and XPS techniques. This transformation is fast, efficient and does not require nitrogen atmosphere or anoxic conditions and additive. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Catalyst support; Copper catalyst; Crystallization; selectivity; Sustainability

Acid-base cooperative catalysis over mesoporous nitrogen-rich carbon - Goyal, Reena; Sarkar, Bipul; Lucas, Nishita; Bordoloi, Ankur (ChemCatChem, 2014)
WOx nanoclusters (2-3 nm) embedded on a mesoporous nitrogen-rich carbon material were synthesized by using novel methodology. This material was very effectively capitalized as a new carbon-based acid-base cooperative catalyst for sequential acetal hydrolysis and Knoevenagel condensation reactions. The protocol was also explored for the nitroaldol condensation reaction.
Keywords: cooperative catalysts; Knoevenagel condensation; mesoporous materials; Nanostructures; nitro aldol reaction

Antimicrobial activity of ZnO nanoparticles against pathogenic bacteria and fungi - Navale, G. R.; Thripuranthaka, M.; Late, Dattatray J.; Shinde, Sandip S. (JSM Nanotechnology and Nanomedicine, 2014)

Arthrobacter enclensis sp. nov., isolated from sediment sample - Dastager, Syed Gulam; Qin, Liu; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)
A novel bacterial strain designated as NIO-1008(T) was isolated from marine sediments sample in Chorao Island India. Cells of the strains were gram positive and non-motile, displayed a rod-coccus life cycle and formed cream to light grey colonies on nutrient agar. Strain NIO-1008(T) had the chemotaxonomic markers that were consistent for classification in the genus Arthrobacter, i.e. MK-9(H-2) (50.3 %), as the major menaquinone, and the minor amount of MK-7 (H-2-27.5 %), MK-8 (H-4-11.6 %) and MK-8 (H-2-10.4 %). anteiso-C-15:0, iso-C-15:0, iso-C-16:0 and C-15:0 were the predominant fatty acids. Galactose, glucose and rhamnose are the cell-wall sugars, and DNA G+C content was 61.3 mol%. Phylogenetic analysis, based on 16S rRNA gene sequencing, showed that the strains were most similar to Arthrobacter equi IMMIB L-1606(T), Arthrobacter chlorophenolicus DSM 12829(T), Arthrobacter defluvii KCTC 19209(T) and Arthrobacter niigatensis CCTCC AB 206012(T) with 98.5, 98.4, 98.0 and 97.8 %, respectively, and formed a separate lineage. Combined phenotypic data and DNA-DNA hybridization data supported the conclusion that strains NIO-1008(T) represent a novel species within the genus Arthrobacter, for which the name Arthrobacter enclensis sp. nov., is proposed. The type strain is NIO-1008(T) = (NCIM 5488(T) = DSM 25279(T)).
Keywords: Arthrobacter; Chorao Island; Marine sediment; Polyphasic

Arthrobacter enclensis sp. nov., isolated from sediment sample (vol 196, pg 775, 2014) - Dastager, Syed Gulam; Liu, Qing; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)

Back-to-back MOS–Schottky (Pt–SiO2–Si–C–Pt) nano-heterojunction device as an efficient self-powered photodetector: one step fabrication by pulsed laser deposition - Shaikh, P. A.; Thakare, V. P.; Late, D. J.; Ogale, S. (Nanoscale, 2014)
An efficient self-powered photodetector design involving a C–Si hetero-interface with back-to-back MOS–Schottky (Pt–SiO2–Si–C–Pt) device action is presented. Pulsed laser deposition of a carbon thin film is used which dynamically removes the native surface oxide to form the desired Schottky interface. The combined device action yields two orders of magnitude photoresponse at zero bias.

Clay encapsulated Cu(OH)(x) promoted homocoupling of arylboronic acids: an efficient and eco-friendly protocol - Dar, Bashir Ahmad; Singh, Snehil; Pandey, Nalini; Singh, A. P.; Sharma, Priti; Lazar, Anish; Sharma, Meena; Vishwakarma, Ram A.; Singh, Baldev (Applied Catalysis A-General, 2014)
Cu(OH)(x) has been encapsulated over montmorillonite-KSF by simple ologomeric deposition strategy. The resulting catalyst has been employed for selective homocoupling of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst is easy to recover and shows excellent reusability without losing its activity. Techniques like XRD, SEM, TPR, IR, BET surface area measurement and XPS were used to characterize the catalyst. The present method promises for the simple and clean homocoupling of arylboronic acids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biaryls; clay; Copper; Heterogenous catalyst; Homocoupling

Design and synthesis of 3D porous diamondoid frameworks by cocrystallization - Tothadi, Srinu; Little, Marc A.; Hasell, Tom; Briggs, Michel E.; Chong, Samantha Y.; Cooper, Andrew I. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: cocrystals; crystal engineering; Porous Organic Cages

Determination of carrier lifetime and mobility in colloidal quantum dot films via impedance spectroscopy - Rath, Arup Kumar; Lasanta, Tania; Bernechea, Maria; Diedenhofen, Silke L.; Konstantatos, Gerasimos (Applied Physics Letters, 2014)
Impedance Spectroscopy (IS) proves to be a powerful tool for the determination of carrier lifetime and majority carrier mobility in colloidal quantum dot films. We employ IS to determine the carrier lifetime in PbS quantum dot Schottky solar cells with Al and we verify the validity of the technique via transient photovoltage. We also present a simple approach based on an RC model that allows the determination of carrier mobility in PbS quantum dot films and we corroborate the results via comparison with space charge limited measurements. In summary, we demonstrate the potential of IS to characterize key-to-photovoltaics optoelectronic properties, carrier lifetime, and mobility, in a facile way. (C) 2014 AIP Publishing LLC.

Dimorphism and hydrocarbon metabolism in Yarrowia lipolytica var. indica - Palande, A. S.; Kulkarni, S. V.; Leon-Ramirez, C.; Campos-Gongora, E.; Ruiz-Herrera, J.; Deshpande, Mukund V. (Archives of Microbiology, 2014)
Yarrowia lipolytica is able to metabolize high Mr hydrophobic natural compounds such as fatty acids and hydrocarbons. Characteristically, strains of Y. lipolytica can grow as populations with variable proportions of yeast and filamentous forms. In the present study, we describe the dimorphic characteristics of a variant designated as Y. lipolytica var. indica isolated from petroleum contaminated sea water and the effect of cell morphology on hydrocarbon metabolism. The variant behaved as a yeast monomorphic strain, under conditions at which terrestrial Y. lipolytica strain W29 and its derived strains, grow as almost uniform populations of mycelial cells. Using organic nitrogen sources and N-acetylglucosamine as carbon source, var. indica was able to form mycelial cells, the proportion of which increased when incubated under semi-anaerobic conditions. The cell surface characteristics of var. indica and W29 were found to be different with respect to contact angle and percent hydrophobicity. For instance, percent hydrophobicity of var. indica was 89.93 +/- A 1.95 while that of W29 was 70.78 +/- A 1.1. Furthermore, while all tested strains metabolize hydrocarbons, only var. indica was able to use it as a carbon source. Yeast cells of var. indica metabolized hexadecane with higher efficiency than the mycelial form, whereas the mycelial form of the terrestrial strain metabolized the hydrocarbon more efficiently, as occurred with the mycelial monomorphic mutant AC11, compared to the yeast monomorphic mutant AC1.
Keywords: Hexadecane metabolism; Yarrowia lipolytica; Yeast-mycelium transition

Emulsion ionic liquid membranes (EILMs) for removal of Pb(II) from aqueous solutions - Lende, Avinash B.; Dinker, Manish K.; Bhosale, Vikas K.; Kamble, Sanjay P.; Meshram, Pawan D.; Kulkarni, Prashant S. (RSC Advances, 2014)
Ionic liquids (ILs) are playing increasingly important roles in the membrane separation processes. The present manuscript discusses the removal of Pb(II) ions from aqueous solution using an emulsion ionic liquid membrane (EILM) process. Initially, the emulsion liquid membrane (ELM) was prepared by stirring strip phase (sulphuric acid) and organic phase (surfactant: span 80, extractant: D2EHPA, diluent: hexane) together under high speed agitation. Note that, the parameters of the ELM process such as emulsification speed, pH of the feed phase, treat ratio, extractant and surfactant concentrations were studied for the maximum removal of Pb(II) ions. The role of IL was explored by adding hydrophobic IL, octylmethylimidazole hexafluorophosphine ([OMIM][PF6]), in the organic phase. The performance of ELM with and without IL was compared on the basis of stability, enrichment factor and the removal efficiency for Pb(II). The results showed that the percentage of Pb(II) extraction was complete by the emulsion membrane with IL (EILM) in comparison to the 97% achieved by neat ELM. Further, the stability and the enrichment factor of the EILM were found to be 2-3 times greater than that of the ELM. The FT-IR spectroscopic analysis revealed that bond interactions between IL and membrane phase components avoided the coalescence of internal phase droplets and enhanced the emulsion stability. The results obtained in this work support the use of the IL [OMIM][PF6] as both a stabilizer and carrier for the overall improvement of the ELM process.

Enhanced field emission properties of doped graphene nanosheets with layered SnS2 - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Applied Physics Letters, 2014)
We report here our experimental investigations on p-doped graphene using tin sulfide (SnS2), which shows enhanced field emission properties. The turn on field required to draw an emission current density of 1 mu A/cm(2) is significantly low (almost half the value) for the SnS2/reduced graphene oxide (RGO) nanocomposite (2.65 V/mu m) compared to pristine SnS2 (4.8 V/mu m) nanosheets. The field enhancement factor beta (similar to 3200 for the SnS2 and similar to 3700 for SnS2/RGO composite) was calculated from Fowler-Nordheim (F-N) plots, which indicates that the emission is from the nanometric geometry of the emitter. The field emission current versus time plot shows overall good emission stability for the SnS2/RGO emitter. The magnitude of work function of SnS2 and a SnS2/graphene composite has been calculated from first principles density functional theory (DFT) and is found to be 6.89 eV and 5.42 eV, respectively. The DFT calculations clearly reveal that the enhanced field emission properties of SnS2/RGO are due to a substantial lowering of the work function of SnS2 when supported by graphene, which is in response to p-type doping of graphene. (C) 2014 AIP Publishing LLC.

Enhanced kinetics for the clathrate process in a fixed bed reactor in the presence of liquid promoters for pre-combustion carbon dioxide capture - Babu, Ponnivalavan; Ho, Chie Yin; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
In this work, we present enhanced kinetics of hydrate formation for the clathrate process in the presence of two liquid promoters namely THF (tetrahydrofuran) and TBAB (tetra-n-butyl ammonium bromide) in a FBR (fixed bed reactor) for pre-combustion capture of CO2. Silica sand was used as a medium to capture CO2 from CO2/H-2 gas mixture by hydrate crystallisation. Experiments were performed at different temperatures (274.2 K and 279.2 K) and 6.0 MPa to determine the total gas uptake, induction time and rate of hydrate formation. The observed trends indicated that higher driving force resulted in higher gas consumption and significantly reduced induction time. For the same driving force, higher gas consumption and shorter induction time was achieved by THF as compared to TBAB. 5.53 mol% THF attained higher gas consumption than 1.0 mol% THF whereas 3.0 mol% TBAB attained lower gas consumption than 0.3 mol% TBAB. A highest gas uptake of 51.95 (+/- 5.183) mmol of gas/mol of water and a highest rate of 51.21(+/- 8.91) mol.min(-1).m(-3) were obtained for 5.53 mol% THF at 6.0 MPa and 279.2 K. Overall, this study indicated better hydrate formation kinetics with the use of THF in an FBR configuration for CO2 capture from a fuel gas mixture. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Fixed bed reactor; Gas hydrates; Pre-combustion capture; Promoters

Enhancement in the field emission behavior of graphene in N-2/O-2 high vacuum ambience - Suryawanshi, S. R.; Kolhe, Pankaj S.; Gavhane, D. S.; Patil, S. S.; Chavan, P. G.; More, Mahendra A.; Late, Dattatray J. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Herein we report, pressure dependent field emission (FE) behaviour of a few-layer graphene emitter. Gas dependent FE properties have been investigated in ultra high vacuum (UHV), as well as in N-2 and O-2 ambience at base pressure similar to 1x10(-6) torr. Interestingly, the graphene emitter when operated in N-2/O-2 ambience exhibits lower turn-on field and higher emission current density, as compared to the UHV conditions. The emission current stability investigated at preset value of similar to 1 mu A over the period of more than 2 hrs is found better in the N2 ambience and is characterized by fewer fluctuations, in contrast to the behaviour in the O-2 ambience. The observed enhanced electron emission behavior in N-2/O-2 ambience is attributed to modulation of the work function of graphene emitter.
27th International Vacuum Nanoelectronics Conference (IVNC), Engelberg, SWITZERLAND, JUL 06-10, 2014
Keywords: graphene; Pressure Dependent Field Emission

Evaluation of genetic variability in Symplocos laurina Wall. from two biodiversity hotspots of India - Bhagwat, Rasika M.; Banu, Sofia; Dholakia, Bhushan B.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, Vidya S. (Plant Systematics and Evolution, 2014)
Symplocos laurina Wall., an important medicinal tree species, is one of the pioneering plants for establishment of shola forest ecosystem. We analyzed 208 accessions of S. laurina from 13 populations belonging to three ecoregions in India namely, Western Ghats, Eastern Ghats and Northeast India, to comment on the genetic diversity and population structure of the species. Of the 100 inter simple sequence repeat primers screened, eight were selected based on their clear and reproducible polymorphic patterns. These eight ISSR primers produced on an average 1,014 bands from 208 accessions, of which 6.58 % were rare bands, 55.96 % were shared bands and 37.46 % were similar bands. The primers, UBC835 and UBC880, amplified the highest number of polymorphic loci (16), while the primer UBC852 amplified the least number of amplicons (9). The values for total genetic diversity (H-T) and the average heterozygosity (H-S) were 0.3407 and 0.2263, respectively; while the coefficient of genetic differentiation (G(ST)) was 0.3358. Within-population variance was higher (68 %) than among-population variance (17 %), indicating high intra-population genetic diversity. These populations were grouped according to their geographical location in cluster analysis. Mantel test also showed significant positive correlation between genetic and geographical distances. The present study revealed the importance of the Palghat gap in South India in shaping the distribution of genetic diversity in S. laurina.
Keywords: Biodiversity hotspots; Genetic diversity; ISSR; Palghat gap; Symplocos laurina

Facile and convenient synthesis of (+/-)-Biotin via MgCl2/Et3N-mediated C-C coupling and mitsunobu reaction - Chavan, Subhash P.; Chavan, Prakash N.; Lasonkar, Pradeep B.; Khairnar, Lalit B.; Kadam, Appasaheb L. (Synlett, 2014)
A synthesis of (+/-)-biotin is described starting from simple starting materials viz. cyclohexanone and amino malonic acid ester. The key steps involved are MgCl2/Et3N coupling of amino malonic acid ester derivative and acid chloride, Mitsunobu reaction, ozonolysis, Staudinger reduction, novel urea formation, and subsequent dibenzylation. This approach is economical and involves high-yielding steps and simple reaction conditions.
Keywords: Appel reaction; biotin; Mitsunobu reaction; Ozonolysis; Staudinger reduction

Fictibacillus enclensis sp nov., isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Srinivasan, Krishnamurthi; Tang, Shan-Kun; Lee, Jae-Chan; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel Gram-positive strain, designated NIO-1003(T), was isolated from a marine sediment sample collected from the Chorao Island, Goa Provence, India. Strain NIO-1003(T) was found to be strictly aerobic, motile, endospore-forming rods. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1003(T) belongs to the genus Fictibacillus and to be most closely related to Fictibacillus rigui KCTC 13278(T), Fictibacillus solisalsi KCTC 13181(T) and Fictibacillus barbaricus DSM 14730(T) with 98.2, 98.0 and 97.2 % similarity and 25, 28, 39 nucleotide differences respectively. Strain NIO-1003(T) was characterized by having cell-wall peptidoglycan based on meso-diaminopimelic acid and MK-7 as the predominant menaquinone. The polar lipid profile exhibited the major compounds diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. In addition, minor amounts of an aminophospholipid were detected. The major fatty acids were identified as ai-C-15:0, iso-C-15:0, ai-C-17:0 and C-16:0, supporting the grouping of strain NIO-1003(T) into the family Bacillaceae. The DNA G+C content of strain NIO-1003(T) was determined to be 42.6 mol%. On the basis of phenotypic properties, phylogeny and DNA-DNA hybridisation analysis, strain NIO-1003(T) is considered to represent a novel species of the genus Fictibacillus for which the name Fictibacillus enclensis sp. nov. is proposed. The type strain is NIO-1003(T) (= NCIM 5458(T) = DSM 25142(T)).
Keywords: Chorao Island; Fictibacillus sp.; Polyphasic taxonomy

Field emission properties of ZnO nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Chakravarty, Disha; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
{Electron emission properties of electrodeposited ZnO nanosheet arrays grown on Indium tin oxide coated glass substrates have been studied. Influence of oxygen vacancies on electronic structures and field emission properties of ZnO nanosheets are investigated using density functional theory. The oxygen vacancies produce unshared d electrons which form an impurity energy state; this causes shifting of Fermi level towards the vacuum, and so the barrier energy for electron extraction reduces. The ZnO nanosheet arrays exhibit a low turn-on field of 2.4 V/mu m at 0.1 mu A/cm(2) and current density of 50.1 mu A/cm(2) at an applied field of 6.4 V/mu m with field enhancement factor

First iodocyclization reaction of allene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Jadhav, Amol R.; Lahore, Santosh V.; Kahar, Nilesh M.; Joshi, Rohini R.; Joshi, Ramesh A.; Koketsu, Mamoru (Tetrahedron Letters, 2014)
The regioselective iodocyclization reaction of allene-thioureas is described, for the first time, for the synthesis of bicyclic beta-lactams. The substitution at the allenyl part heavily influenced the iodocyclization reaction. The iodocyclization reaction of the unsubstituted allene-thioureas afforded six-membered 3-thia-1-dethiacephems whereas, the substituted allene-thiourea afforded seven-membered thiazepines along with five-membered isopenams. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Allene; beta-Lactams; Iodocyclization; Regioselective; thiourea

Graphene quantum dots conjugated albumin nanoparticles for targeted drug delivery and imaging of pancreatic cancer - Nigam, Preeti; Waghmode, Shobha; Louis, Michelle; Wangnoo, Shishanka; Chavan, Pooja; Sarkar, Dhiman (Journal of Materials Chemistry B, 2014)
Pancreatic cancer is considered to be the deadliest of all cancers due to its poor prognosis and resistance to conventional therapies. In this study, the potential of hyaluronic acid functionalized and green fluorescent graphene quantum dot (GQD)-labeled human serum albumin nanoparticles for pancreatic cancer specific drug delivery and bioimaging was explored. GQDs with tunable fluorescence properties and biocompatibility have attracted much more interest in recent years as compared to their metal semiconductor counterparts. We adopted lawsone (2-hydroxy-1,4-naphthoquinone) as a novel reducing agent for the synthesis of quantum dots and, in addition to excellent fluorescence of the synthesized GQDs, a good quantum yield of similar to 14% was also obtained. Gemcitabine, the most preferred drug for pancreatic cancer treatment, was encapsulated in albumin nanoparticles, and it was observed that our nanoformulation significantly enhanced the bioavailability and sustained release property of the drug to pancreatic cancer cells in vitro. Moreover, the GQD-mediated bioimaging was excellent and enhanced the efficacy of our system as a drug delivery vehicle.

Hydrogen storage in clathrate hydrates: Current state of the art and future directions - Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Applied Energy, 2014)
Hydrogen is looked upon as the next generation clean energy carrier, search for an efficient material and method for storing hydrogen has been pursued relentlessly. Improving hydrogen storage capacity to meet DOE targets has been challenging and research efforts are continuously put forth to achieve the set targets and to make hydrogen storage a commercially realizable process. This review comprehensively summarizes the state of the art experimental work conducted on the storage of hydrogen as hydrogen clathrates both at the molecular level and macroscopic level. It identifies future directions and challenges for this exciting area of research. Hydrogen storage capacities of different clathrate structures - sI, sII, sH, sVI and semi clathrates have been compiled and presented. In addition, promising new approaches for increasing hydrogen storage capacity have been described. Future directions for achieving increased hydrogen storage and process scale up have been outlined. Despite few limitations in storing hydrogen in the form of clathrates, this domain receives prominent attention due to more environmental-friendly method of synthesis, easy recovery of molecular hydrogen with minimum energy requirement, and improved safety of the process. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Clathrates; Gas hydrates; Hydrogen hydrates; Hydrogen storage; Promoters; Storage capacity

Identification and expression profiling of helicoverpa armigera microRNAs and their possible role in the regulation of digestive protease genes - Lomate, Purushottam R.; Mahajan, Neha S.; Kale, Sandip M.; Gupta, Vidya S.; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2014)
The present investigation is an effort to determine the possible roles of microRNAs (miRNAs) in the regulation of protease gene expression in Helicoverpa armigera upon exposure to plant protease inhibitors (PIs). Using Illumina platform, deep sequencing of 12 small RNA libraries was performed from H. armigera larvae fed on artificial diet (AD) or recombinant Capsicum annuum PI-7 (rCanPI-7) incorporated diet, at various time intervals (0.5, 2, 6, 12, 24, and 48 h). Sequencing data were analyzed with miRDeep2 software; a total of 186 unique miRNAs were identified from all the 12 libraries, out of which 96 were conserved while 90 were novel. These miRNAs showed all the conserved characteristics of insect miRNAs. Homology analysis revealed that most of the identified miRNAs were insect-specific, and more than 50 miRNAs were Lepidoptera-specific. Several candidate miRNAs (conserved and novel) were differentially expressed in rCanPI-7 fed larvae as compared to the larvae fed on AD. H. armigera miRNAs were found to have target sites in several protease genes as well as in protease regulation related genes such as serine PI and immune reactive PI. As expected, negative correlation in the relative abundance miRNAs and their target mRNAs was evident from qualitative real time polymerase chain reaction analysis. The investigation revealed potential roles of miRNAs in H. armigera protease gene regulation. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Deep sequencing; Helicoverpa armigera; miRNAs; Protease gene regulation; Protease inhibitors

Impact of experimental pressure and temperature on semiclathrate hydrate formation for pre-combustion capture of CO2 using tetra-n-butyl ammonium nitrate - Babu, Ponnivalavan; Datta, Stuti; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
TBANO(3) (tetra-n-butyl ammonium nitrate) is a promising liquid phase promoter for capturing CO2 via HBGS (hydrate based gas separation) technology. In this study, the impact of experimental pressure and temperature on formation of mixed CO2-H-2-TBANO(3) semiclathrate hydrate for the optimum 1.0 mol% TBANO(3) reported by Babu et al. [1] was investigated. Experimental pressures of 3.0, 4.5 and 6.0 MPa and temperatures of 274.2, 276.2 and 278.2 K were employed. Irrespective of the experimental pressure, shorter induction time was observed for experiments conducted at 274.2 K when compared to the experiments at other temperatures. At a given pressure, the total gas uptake increased with increase in experimental temperature. Similarly at a given temperature, the total gas uptake increases with an increase in pressure. Higher rate of hydrate formation was observed at experimental pressure of 6.0 MPa than at 3.0 and 4.5 MPa irrespective of the experimental temperature. The CO2 composition in hydrate was between 87.5 and 93.2 mol%. Finally, the gas consumption for 1.0 mol% TBANO(3) as promoter was much higher than other promoters of quaternary salts like tetra-n-butyl ammonium bromide and tetra-n-butyl ammonium fluoride at comparable concentration and driving force. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Semi-clathrates

Impact of fly ash impurity on the hydrate-based gas separation process for carbon dioxide capture from a flue gas mixture - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2014)
The hydrate-based gas separation (HBGS) process for gas mixtures of CO2 + N-2 (flue gas) and CO2 + H-2 (fuel gas) has proven to be very efficient and highly selective for CO2 capture. In addition to CO2 and N-2, flue gas from coal-based thermal power stations can contain impurities such as nitrogen oxides (NOx), sulfur oxides (SOx), and fly ash. In this work, the impact of fly ash on the HBGS process efficiency was investigated. Tetrahydrofuran (THF, 1 mol %) was used as a thermodynamic promoter, and sodium dodecyl sulfate (SDS) and sodium dodecyl benzenesulfonate (SDBS) (anionic surfactants) were used as kinetic promoters. Whereas the use of THF in the HBGS process reduces the operating pressure significantly, both SDS and SDBS were found to enhance the rate of hydrate formation. It was observed that the hydrate equilibrium conditions did not change in the presence of fly ash. However, the presence of fly ash enhanced the separation efficiency of the HBGS process by reducing the induction time and increasing the kinetics of hydrate formation. Therefore, the presence of fly ash in a flue gas mixture is not detrimental to the HBGS process, which is a positive factor for the capture and geological sequestration of CO2 in the form of gas hydrates.

Impact of pressure and temperature on tetra-n-butyl ammonium bromide semi-clathrate process for carbon dioxide capture - Babu, Ponnivalavan; Chin, Weng Inn; Kumar, Rajnish; Linga, Praveen (International Conference on Applied Energy, ICAE2014, 2014)
The pre-combustion capture of CO2 in an IGCC power plant employing the hydrate based gas separation (HBGS) process is a novel method currently receiving attention around the world. Tetra-n-butyl ammonium bromide (TBAB) is a promoter that has been shown to improve the efficiency of hydrate formation. In this study, the effect of temperature and pressure on 0.3 mol% TBAB solution is investigated. The induction time for the experiments conducted at 6.0 MPa and 274.8 K was found to be lower, while nucleation became increasingly random as temperature is increased and pressure is reduced. Total gas uptake and normalized rate of hydrate formation (NR5) is also the highest for the experiments conducted at 6.0 MPa and 274.8 K. However, it was found that the hydrate phase CO2 composition remains relatively constant at both reduced temperatures and pressures. (C) 2014 The Authors. Published by Elsevier Ltd.
6th International Conference on Applied Energy (ICAE), Taipei, TAIWAN, MAY 30-JUN 02, 2014
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; Promoters; tetra-n-butyl ammonium bromide

In situ characterisation of nanoscale electromechanical properties of quasi-two-dimensional MoS2 and MoO3, arXiv preprint arXiv - Walia, Sumeet; Nili, Hussein; Balendhran, Sivacarendran; Late, Dattatray J.; Sriram, Sharath; Bhaskaran, Madhu (Condensed Matter Materials Science, 2014)
Precise manipulation of electronic band structures of two-dimensional (2D) transition metal dichalcogenides and oxides (TMD&Os) via localised strain engineering is an exciting avenue for exploiting their unique characteristics for electronics, optoelectronics, and nanoelectromechanical systems (NEMS) applications. This work experimentally demonstrates that mechanically-induced electrical transitions can be engineered in quasi-2D molybdenum disulphide (MoS2) and molybdenum trioxide (MoO3) using an in situ electrical nanoindentation technique. It is shown that localised strains on such quasi-2D layers can induce carrier transport alterations, thereby changing their electrical conduction behaviour. Such strain effects offer a potential tool for precisely manipulating the electronic transport properties of 2D TMD&Os, and understanding the interactions of the atomic electronic states in such layered materials.

Influence of method of preparation on the activity of La-Ni-Ce mixed oxide catalysts for dry reforming of methane - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Surendar, M.; Lingaiah, N.; Rao, K. S. Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (RSC Advances, 2014)
La-Ni-x-Ce1-x mixed oxide catalysts were prepared by a sol-gel method varying the Ni composition (0 <= x <= 1). The catalysts were characterized by X-ray diffraction (XRD), inductively coupled plasma optical emission spectroscopy (ICP-OES), BET surface area, X-ray photoelectron spectroscopy (XPS), temperature-programmed reduction (TPR), H-2 chemisorption and Fourier transform infrared spectroscopy (FT-IR) techniques. CO2 reforming of methane was carried out at atmospheric pressure and 800 degrees C, maintaining a reactant CO2/CH4/N-2 ratio of 80/80/80 (total flow rate = 240 ml min(-1), GHSV of 28 800 h(-1)). The catalysts offered higher activity even at lower Ni compositions. LaNi0.4Ce0.6O3. showed the highest conversion of CH4 and CO2. The H-2/CO ratio in the syngas was stable at 0.85 +/- 0.02. The performance of the sol-gel catalysts was compared with that of the hydrothermally prepared catalysts, reported earlier. High surface area and better Ni dispersion were found to be the reasons for superior activity of the sol-gel catalysts.

Iodine-catalyzed aromatization of tetrahydrocarbazoles and its utility in the synthesis of glycozoline and murrayafoline A: a combined experimental and computational investigation - Humne, Vivek T.; Dangat, Yuvraj B.; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2014)
A new protocol for the aromatization of tetrahydrocarbazoles has been achieved using a catalytic amount of iodine, giving high yields. The role of iodine in the aromatization has been explained by DFT, and its wide scope is extended to the total synthesis of glycozoline and murrayafoline A. This method has proven to be tolerant of a broad range of functional groups.

Kocuria indica sp nov., isolated from a sediment sample - Dastager, Syed Gulam; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Lee, Jae-Chan; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2014)
An actinobacterial strain was isolated from a sediment sample from Chorao Island, in Goa province, India, and subjected to a taxonomic investigation. The isolate, designated NIO-1021(T), was a Gram-stain positive, aerobic, non-motile and coccoid. Strain NIO-1021(T) was identified as a member of the genus Kocuria by a polyphasic approach. Strain NIO-1021(T) could be differentiated from other members of the genus Kocuria on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain NIO-1021(T) to the most closely related species, Kocuria marina KCTC 9943(T), was 98.6% with 19 nt differences). Furthermore, DNA-DNA hybridization analysis revealed that the novel strain had lower relatedness with the type strains of other members of the genus Kocuria. The strain formed a monophyletic clade with K. marina with 100% bootstrap values. The major phospholipids were phosphatidylglycerol, diphosphatidylglycerol and two unidentified lipids. The predominant menaquinone was MK-7(H-2). The major fatty acids were anteiso-C-15:0, iso-C-(16:0) and anteiso-C-17:0. The DNA G+C content of strain NIO-1021(T) was 60.5 mol%. Chemotaxonomic and phylogenetic properties of the strain were consistent with its classification as representing a member of the genus Kocuria. On the basis of phenotypic, chemotypic and molecular characteristics, strain NIO-1021(T) is considered to represent a novel species of the genus Kocuria, for which the name Kocuria indica sp. nov. is proposed, with strain NIO-1021(T) (=NCIM 5455(T)=DSM 25126(T)=CCTCC AA 209050(T)) as the type strain.

Luminescence and photocatalytic studies of Sm3+ ion doped SnO2 nanoparticles - Singh, L. P.; Luwang, Meitram Niraj; Srivastava, S. K. (New Journal of Chemistry, 2014)
Sm3+ ion doped tetragonal SnO2 nanoparticles have been synthesized by the polyol method and its concentration and annealing effects on photoluminescence properties are studied. The XRD results show the changes of lattice parameters with the incorporation of the Sm3+ ion into the SnO2 host lattices. Fourier transform infrared (FTIR) data indicate the formation of a Sn-O bond and capping of the nanoparticles by ethylene glycol. The broad emission peaks observed around 350 to 550 nm are attributed to the emission from defects or traps present in the host SnO2. The typical emission peaks of the Sm3+ ion are observed and there is efficient energy transfer between the host, SnO2 and the dopant, Sm3+ ion. Further, the prepared samples are experimented towards the photocatalytic behavior on selected triphenylmethane dyes, Ethyl Violet (EV) and Brilliant Green (BG). The degradation of dyes was found to be enhancing in the presence of Sm3+ ions as it suppress the e e(CB)(-) and h(VB)(+) recombination.

Magnetic alignment of gamma (core)-alpha (shell) Fe2O3 nanorods in a solid polymer electrolyte for Li-Ion batteries - Schaetzl, Dean M.; Li, Peng; Chaudhari, Nilima; Bernstein, Gary H.; Fullerton-Shirey, Susan K. (Journal of Physical Chemistry C, 2014)
The temperature-dependent ionic conductivity and thermal properties are characterized for a solid polymer electrolyte of poly(ethylene oxide) (PEO) and LiClO4 filled with 1 wt % gamma-phase core (maghemite) and alpha-phase shell (hematite) Fe2O3 nanorods. Samples are solvent-cast in the absence and presence of a 0.5 T magnetic field, dried at room temperature under vacuum for 72 h, and measured under nitrogen. Vibrating sample magnetometry indicates that the magnetic treatment aligns the nanorods to some extent in the desired orientation normal to the electrode surface. For samples with an ether oxygen to lithium ratio (EO/Li) of 10:1, the nanorods induce sample-to-sample variability in the ionic conductivity. The magnetic treatment eliminates this variability, and differential scanning calorimetry data support the observation that the magnetic treatment increases the structural homogeneity of the electrolyte. For samples with an EO/Li of 3:1, the ionic conductivity is 3 orders of magnitude larger for samples containing 5 times more of the crystal structure, (PEO)(6)/LiClO4. This result is surprising because an inverse relationship between crystallinity and conductivity is normally observed for semicrystalline, solid polymer electrolytes. When the crystal fraction is increased by a factor of 8 via the combination of nanorods and magnetic treatment, the conductivity does not continue to increase, showing that the effect does not persist beyond a critical fraction of (PEO)(6)/LiClO4. The results demonstrate that field-effect alignment of magnetic nanorods increases the crystal fraction and homogeneity of PEO/LiClO4, but does not affect the ionic conductivity in the range of salt and nanorod concentrations investigated.

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

Methane reforming with carbon dioxide over La-Ni-x-Ce1-x mixed oxide catalysts - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Upendar, K.; Lingaiah, N.; Rao, Kamaraju Seetha Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
La-Ni-x-Ce1-x mixed oxide (0 <= x <= 1) catalysts have been hydrothermally prepared, characterized by physico-chemical techniques and evaluated for CO2 reforming of methane. High conversions are achieved for both methane and carbon dioxide over the LaNi0.6Ce0.4O3 catalyst tested under the conditions of CO2/CH4/N-2 ratio of 80/80/80. (total flow rate = 240 mL/min), space velocity of 28,800 h(-1) and at a temperature of 800 degrees C. The H-2/CO ratio in the syngas is stable at 0.93 +/- 0.02. Exchanging Ni with Ce, rather than with La as reported in the literature, appears to be a better option for the improved performance of the catalysts.
Keywords: Carbon dioxide reforming; Catalysts; Cerium; Dry reforming; Hydrothermal synthesis; Lanthanum; Methane reforming; Mixed oxides; Nickel

Microemulsion mediated synthesis of triangular shape SnO2 nanoparticles: luminescence application - Luwang, Meitram Niraj (Applied Surface Science, 2014)
The triangular prism shapes of SnO2 center dot xH(2)O nanoparticles are prepared using microemulsion route. The effect of variation of water pool value on the formation of SnO2 nanoparticles was studied. There is the quantum size effect in absorption study of SnO2 nanoparticles. With the increase of the water pool value, there is a decrease in the band edge absorption energy suggesting the weak quantum confinement effect (QCE) in SnO2 nanoparticles. Quenching effect increases with increase of water to surfactant ratio in luminescence. There is no significant effect in lifetime values for SnO2 nanoparticles in both microemulsion and powder form. SnO2 nanoparticles show green emission due to oxygen vacancy. SnO2 nanoparticles when doped with Eu3+ ions give the enhanced luminescence of Eu3+ due to the surface mediated energy transfer from SnO2 to Eu3+ ion. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: Microemulsion; Theoretical particle size calculation; Triangular nanoparticles

Modification of crystal anisotropy and enhancement of magnetic moment of Co-doped SnO2 thin films annealed under magnetic field - Loya-Mancilla, Sagrario M.; Poddar, Pankaj; Das, Raja; Ponce, Hilda E. Esparza; Templeton-Olivares, Ivan L.; Solis-Canto, Oscar O.; Ornelas-Gutierrez, Carlos E.; Espinosa-Magaa, Francisco; Olive-Mendez, Sion F. (Nanoscale Research Letters, 2014)
Co-doped SnO2 thin films were grown by sputtering technique on SiO2/Si(001) substrates at room temperature, and then, thermal treatments with and without an applied magnetic field (H-TT) were performed in vacuum at 600 degrees C for 20 min. H-TT was applied parallel and perpendicular to the substrate surface. Magnetic M(H) measurements reveal the coexistence of a strong antiferromagnetic (AFM) signal and a ferromagnetic (FM) component. The AFM component has a N,el temperature higher than room temperature, the spin axis lies parallel to the substrate surface, and the highest magnetic moment m =7 mu(B)/Co at. is obtained when H-TT is applied parallel to the substrate surface. Our results show an enhancement of FM moment per Co+2 from 0.06 to 0.42 mu(B)/Co at. for the sample on which H-TT was applied perpendicular to the surface. The FM order is attributed to the coupling of Co+2 ions through electrons trapped at the site of oxygen vacancies, as described by the bound magnetic polaron model. Our results suggest that FM order is aligned along [101] direction of Co-doped SnO2 nanocrystals, which is proposed to be the easy magnetization axis.
Keywords: Antiferromagnetism; Crystal anisotropy; Diluted magnetic oxide; Ferromagnetism; Magnetic anisotropy; Magnetic moment; Spin axis; thin film

Morphological effects of G-quadruplex stabilization using a small molecule in zebrafish - Agarwal, Tani; Lalwani, Mukesh Kumar; Kumar, Santosh; Roy, Saumya; Chakraborty, Tushar Kanti; Sivasubbu, Sridhar; Maiti, Souvik (Biochemistry, 2014)
Zebrafish (Danio rerio) embryos are transparent and advantageous for studying early developmental changes due to ex utero development, making them an appropriate model for studying gene expression changes as a result of molecular targeting. Zebrafish embryos were injected with a previously reported G-quadruplex selective ligand, and the phenotypic changes were recorded. We report marked discrepancies in the development of intersegmental vessels. In silico analysis determined that the putative G-quadruplex motif occur in the upstream promoter region of the Cdh5 (N-cadherin) gene. A real-time polymerase chain reaction-based investigation indicated that in zebrafish, CDH-2 (ZN-cad) was significantly downregulated in the ligand-treated embryos. Biophysical characterization of the interaction of the ligand with the G-quadruplex motif found in this promoter yielded strong binding and stabilization of the G-quadruplex with this ligand. Hence, we report for the first time the phenotypic impact of G-quadruplex targeting with a ligand in a vertebrate organism. This study has unveiled not only G-quadruplex targeting in non-human animal species but also the potential that G-quadruplexes can provide a ready tool for understanding the phenotypic effects of targeting certain important genes involved in differentiation and developmental processes in a living eukaryotic organism.

MoS2 nanoparticles and h-BN nanosheets from direct exfoliation of bulk powder: one-step synthesis method - Thripuranthaka, M.; Rout, Chandra Sekhar; Late, Dattatray J. (Materials Research Express, 2014)
We report facile synthesis of MoS2 nanoparticles and h-BN nanosheets using ultrasonication method in suitable solvents such as N-Methyl-2-pyrrolidone and ethylene glycol, respectively. The average size of MoS2 nanoparticles observed from TEM analysis were 4-5 nm and about a few hundreds of nm for h-BN nanosheets. Raman spectroscopy carried out on nanoparticle samples confirms the formation of MoS2 nanoparticles and h-BN nanosheets. UV-vis absorption and photoluminescence (PL) measurements carried out on the products show typical absorption and luminescence spectra of MoS2 and h-BN. Further, we attempted to decorate gold nanoparticles on nanosheets of MoS2 and h-BN which show subsequent change in Raman spectra due to charge transfer interaction.
Keywords: h-BN; MoS2; Nanoparticles; nanosheets; Optical properties

Nanodiamond particles/reduced graphene oxide composites as efficient supercapacitor electrodes - Wang, Qi; Plylahan, Nareerat; Shelke, Manjusha V.; Devarapalli, Rami Reddy; Li, Musen; Subramanian, Palaniappan; Djenizian, Thierry; Boukherroub, Rabah; Szunerits, Sabine (Carbon, 2014)
The paper reports on the preparation of reduced graphene oxide (rGO) modified with nanodiamond particles composites by a simple solution phase and their use as efficient electrode in electrochemical supercapacitors. The technique relies on heating aqueous solutions of graphene oxide (GO) and nanodiamond particles (NDs) at different ratios at 100 degrees C for 48 h. The morphological properties, chemical composition and electrochemical behavior of the resulting rGO/NDs nanocomposites were investigated using UV/vis spectrometry, Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, transmission electron microscopy (TEM) and electrochemical means. The electrochemical performance, including the capacitive behavior of the rGO/NDs composites were investigated by cyclic voltammetry and galvanostatic charge/discharge curves at 1 and 2 A g(-1) in 1 M H2SO4. The rGO/ND matrix with 10/1 ratio displayed the best performance with a specific capacitance of 186 +/- 10 F g (-1) and excellent cycling stability. (C) 2013 Elsevier Ltd. All rights reserved.

Negative infrared photocurrent response in layered WS2/reduced graphene oxide hybrids - Ratha, Satyajit; Simbeck, Adam J.; Late, Dattatray J.; Nayak, Saroj K.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
We report high performance IR photocurrent response of two-dimensional hybrid materials consisting of layered WS2 nanosheets and reduced graphene oxide (RGO). Comparative photocurrent response studies of WS2 nanosheets, RGO, and WS2/RGO hybrids were carried out by performing current-voltage (I-V) and time-dependent current measurements with a laser excitation source having a wavelength of 808 nm. The experimental investigations indicate that WS2/RGO hybrids show negative photocurrent response, whereas WS2 and RGO show positive photocurrent response. The negative photocurrent response of the WS2/RGO hybrids is explained using a band alignment diagram and attributed to a charge transfer mechanism between WS2 and RGO. This analysis is further corroborated by first-principles density functional calculations. The fabricated device based on WS2/RGO hybrids shows a photosensitivity R-lambda of about 6 AW(-1) and a quantum efficiency eta of similar to 924%, which demonstrates high sensitivity of the hybrid material towards IR detection. WS2/RGO hybrids are therefore promising candidates for potential applications in optoelectronic circuits and low cost, high performance, and reliable photodetectors. (C) 2014 AIP Publishing LLC.

Nonisothermal analysis of extrusion film casting process using molecular constitutive equations - Pol, Harshawardhan; Banik, Sourya; Azad, Lal Busher; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Rheologica Acta, 2014)
Extrusion film casting (EFC) is a commercially important process that is used to produce several thousand tons of polymer films and coatings. In a recent work, we demonstrated the influence of polymer chain architecture on the extent of necking in an isothermal film casting operation (Pol et al., J Rheol 57:559-583, 2013). In the present research, we have explored experimentally and theoretically the effects of long-chain branching on the extent of necking during nonisothermal film casting conditions. Polyethylenes of linear and long-chain branched architectures were used for experimental studies. The EFC process was analyzed using the 1-D flow model of Silagy et al. (Polym Eng Sci 36:2614-2625, 1996) in which the energy equation was introduced to model nonisothermal effects, and two multimode constitutive equations, namely the ``extended pom-pom'' (XPP, for long-chain branched polymer melts) equation and the ``Rolie-Poly stretch version'' (RP-S, for linear polymer melts) equation, were incorporated to account for the effects of polymer chain architecture. We show that the model does a better job of capturing the qualitative features of the experimental data, thereby elucidating the role of chain architecture and nonisothermal conditions on the extent of necking.
Keywords: Branched; Extrusion; Film; Linear; Necking; Nonisothermal; Polyethylene

Novel catalysts for valorization of biomass to value-added chemicals and fuels - Lucas, Nishita; Kanna, Narasimha Rao; Nagpure, Atul S.; Kokate, Ganesh; Chilukuri, Satyanarayana V. (Journal of Chemical Sciences, 2014)
Key furan compounds such as 5-hydroxymethylfurfural (HMF), 2,5-furandicarboxylic acid (FDCA) and 2,5-dimethylfuran (DMF) were synthesized from renewable feedstocks. Dehydration of fructose was carried out in biphasic conditions employing several solid acid catalysts by targeting selective formation of HMF. Its selectivity is linearly dependent on total acidity clearly revealing that lower acidity favours selective formation of HMF. Oxidation and hydrogenolysis of HMF has been explored using 2 wt% Ru-K-OMS-2. The catalysts used for each transformation were subjected to detailed characterization using XRD, BET surface area, temperature-programmed desorption and transmission electron microscopy. The effect of various reaction parameters was also investigated for obtaining high yields of desired chemical intermediates. High FDCA yields of 93.4 mol% and 66 mol% were achieved in alkaline and base-free conditions, respectively. The 2 wt% Ru-K-OMS-2 is a versatile catalyst as it also catalyses HMF hydrogenolysis giving 33 mol% of DMF. Thus, utility of various novel materials as catalysts has been demonstrated in the multistep transformations of hexoses to furan-based fuels and chemicals.
21st National Symposium on Catalysis (CATSYMP), CSIR Indian Inst Chem Technol, Hyderabad, INDIA, FEB 11-13, 2013
Keywords: 2; 5-dimethylfuran; 5-furan dicarboxylic acid; 5-hydroxymethyl furfural; dehydration; fructose

Novel synthesis and characterization of CuO nanomaterials: biological applications - Devi, Ayekpam Bimolini; Moirangthem, Dinesh Singh; Talukdar, Narayan Chandra; Devi, M. Damayanti; Singh, N. Rajen; Luwang, Meitram Niraj (Chinese Chemical Letters, 2014)
CuO nanoparticles were synthesized at a relatively low temperature (80 degrees C) for 2 h using polyethylene glycol-glycerol mixture which acts as a capping agent. A detailed characterization of the synthesized nanomaterials were performed utilizing X-ray diffraction (XRD), infra-red spectroscopy (IR), thermogravimetric analysis (TGA-DTA), transmission electron microscopy (TEM), photoluminescence (PL) by studying its crystalline phase, vibrational mode, thermal analysis, morphology and photoluminescence properties. The effect of annealing on the as-prepared nanoparticles were studied and compared with their corresponding bulk counterpart. The synthesized nanoparticles have been screened for in vitro cytotoxicity (IC50) studies against the human cervical adenocarcinoma cell line (HeLa) using MTT assay methods. The as-prepared nanoparticle inhibits the proliferation of this HeLa cell. The standard disc diffusion method has been used to study the antibacterial activity of the samples against the human pathogenic bacteria Escherichia coli (MTCC 729), Proteus mirabilis (MTCC 425) and Klebsiella pneumoniae subsp. pneumoniae (MTCC 432). The results have been compared with the positive control antibiotic gentamycin. The synthesized nanoparticles would provide a potential alternative to antibiotics for controlling some of the microorganisms causing urolithiasis. (C) 2014 Meitram Niraj Luwang. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Annealing; Antibacterials; CuO nanoparticles; Cytotoxicity; HeLa cell lines

Photosensitive field emission study of SnS2 nanosheets (27th International Vacuum Nanoelectronics Conference ) - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (2014 27TH International Vacuum Nanoelectronics Conference (IVNC), 2014)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to Field Emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solution are used. The FE study is carried out in all metal Ultra High Vacuum (UHV) chamber in planar diode configuration at a base pressure of similar to 10(-8) torr. A maximum current density of 110 mu A/cm(2) was attainable. The turn on field required to draw a current density of 1 mu A/cm(2) is found to be 2.6 V/mu m. A separate study was carried out to investigate the photosensitivity of the emitter by illuminating the specimen under visible light. In dark, the FN plot is non-linear, indicative of semiconductor nature of the emitter. However, on illumination, the FN plot is observed to be linear. This remarkable change can be explained by the photoconductivity imparted on illumination. The field at the tip is high in presence of light, than in dark, due to enhanced conductivity. It is also observed that on switching ON the light, the FE current increases almost instantaneously. Repetitive switching is observed at a fixed applied voltage, generating current pulses. The visible light soaking of the sample is carried out by illuminating the lamp for more than 100 minutes, where the current seems to saturate. On switching off the lamp the emission current decayed almost to its initial value exponentially. The photosensitivity has been studied for different wavelengths in the visible spectra. The maximum photosensitive field emission is observed for green filter. With this photoresponse, it is envisaged that SnS2 nanosheets are a potential candidate for optoelectronic applications of field emitters.
Keywords: field emission; photosensitivity; Photoswitching

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film

Pyrene based conjugated materials: synthesis, characterization and electroluminescent properties - Salunke, Jagadish K.; Sonar, Prashant; Wong, F. L.; Roy, V. A. L.; Lee, C. S.; Wadgaonkar, Prakash P. (Physical Chemistry Chemical Physics, 2014)
In this work, three novel pyrene cored small conjugated molecules, namely 1,3,6,8-tetrakis(6-(octyloxy)naphthalene-2-yl) pyrene (PY-1), 1,3,6,8-tetrakis((E)-2-(6-(n-octyloxy) naphthalene-2-yl) vinyl) pyrene (PY-2) and 1,3,6,8-tetrakis((6-(n-octyloxy) naphthalene-2-yl) ethynyl) pyrene (PY-3) have been synthesized by Suzuki, heck and Sonogashira organometallic coupling reactions, respectively. The effects of single, double and triple bonds on their optical, electrochemical, and thermal properties are studied in detail. These all materials are fluorescent and they have been used in organic light-emitting diodes (OLEDs) and their electroluminescent properties have been studied.

Remote trap passivation in colloidal quantum dot bulk nano-heterojunctions and its effect in solution-processed solar cells - Rath, Arup Kumar; Pelayo Garcia de Arquer, F.; Stavrinadis, Alexandros; Lasanta, Tania; Bernechea, Maria; Diedenhofen, Silke L.; Konstantatos, Gerasimos (Advanced Materials, 2014)
More-efficient charge collection and suppressed trap recombination in colloidal quantum dot (CQD) solar cells is achieved by means of a bulk nano-heterojunction (BNH) structure, in which p-type and n-type materials are blended on the nanometer scale. The improved performance of the BNH devices, compared with that of bilayer devices, is displayed in higher photocurrents and higher open-circuit voltages (resulting from a trap passivation mechanism).

Roseovarius azorensis sp nov., isolated from seawater at espalamaca, azores - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Thi-Nhan Khieu; Chu Ky Son; Li, Wen-Jun; Colaco, Ana (Antonie van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A Gram-negative, motile, non-spore forming, rod shaped aerobic bacterium, designated strain SSW084(T), was isolated from a surface seawater sample collected at Espalamaca (38A degrees 33'N; 28A degrees 39'W), Azores. Growth was found to occur from 15 to 40 A degrees C (optimum 30 A degrees C), at pH 7.0-9.0 (optimum pH 7.0) and with 25-100 % seawater or 0.5-7.0 % NaCl in the presence of Mg2+ and Ca2+; no growth was found with NaCl alone. Colonies on seawater nutrient agar were observed to be punctiform, white, convex, circular, smooth, and translucent. Strain SSW084(T) did not grow on Zobell marine agar and tryptic soy agar even when seawater supplemented. The major respiratory quinone was found to be Q-10 and the G + C content was determined to be 61.9 mol%. Phylogenetic analysis based on the 16S rRNA gene sequence indicated that strain SSW084(T) belongs to the genus Roseovarius and that its closest neighbours are Roseovarius tolerans EL-172(T), Roseovarius mucosus DFL-24(T) and Roseovarius lutimaris 112(T) with 95.7, 95.4 and 95.3 % sequence similarity respectively. The remaining species of Roseovarius showed < 95 % similarity. The polar lipids of strain SSW084(T) were determined to be phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine, an unidentified lipid and one unidentified aminolipid. The major fatty acids identified were identified as C-18:1 omega 7c (52.5 %) and C-16:0 (13.8 %). On the basis of phenotypic, molecular and chemotaxonomic characteristics, strain SSW084(T) is considered to represent a novel species of the genus Roseovarius, for which Roseovarius azorensis sp. nov is proposed. The type strain is SSW084(T) (=KCTC 32421(T) = MTCC 11812(T)).
Keywords: Espalamaca; Polyphasic taxonomy; Roseovarius azorensis sp nov; Seawater

Scaling behavior of resistive switching in epitaxial bismuth ferrite heterostructures - Rana, Abhimanyu; Lu, Haidong; Bogle, Kashinath A.; Zhang, Qi; Vasudevan, Rama; Thakare, Vishal; Gruverman, Alexei; Ogale, Satishchandra; Valanoor, Nagarajan (Advanced Functional Materials, 2014)
Resistive switching (RS) of (001) epitaxial multiferroic BiFeO3/La0.67Sr0.33MnO3/SrTiO3 heterostructures is investigated for varying lengths scales in both the thickness and lateral directions. Macroscale current-voltage analyses in conjunction with local conduction atomic force microscopy (CAFM) reveal that whilst both the local and global resistive states are strongly driven by polarization direction, the type of conduction mechanism is different for each distinct thickness regime. Electrode-area dependent studies confirm the RS is dominated by an interface mechanism and not by filamentary formation. Furthermore, CAFM maps allow deconvolution of the roles played by domains and domain walls during the RS process. It is shown that the net polarization direction, and not domain walls, controls the conduction process. An interface mechanism based on barrier height and width alteration due to polarization reversal is proposed, and the role of electronic reconstruction at the interface is further investigated.

Sequential electrochemical unzipping of single-walled carbon nanotubes to graphene ribbons revealed by in situ Raman spectroscopy and imaging - John, Robin; Shinde, Dhanraj B.; Liu, Lili; Ding, Feng; Xu, Zhiping; Vijayan, Cherianath; Pillai, Vijayamohanan K.; Pradeep, Thalappil (ACS Nano, 2014)
We report an in situ Raman spectroscopic and microscopic investigation of the electrochemical unzipping of single-walled carbon nanotubes (SWNTs). Observations of the radial breathing modes (RBMs) using Raman spectral mapping reveal that metallic SWNTs are opened up rapidly followed by gradual unzipping of semiconducting SWNTs. Consideration of the resonant Raman scattering theory suggests that two metallic SWNTs with chiralities (10,4) and (12, 0) get unzipped first at a lower electrode potential (036 V) followed by the gradual unzipping of another two metallic tubes, (9, 3) and (10, 1), at a relatively higher potential (1.16 V). The semiconducting SWNTs with chiralities (11, 7) and (12, 5), however, get open up gradually at +/- 1.66 V. A rapid decrease followed by a subsequent gradual decrease in the metallicity of the SWNT ensemble as revealed from a remarkable variation of the peak width of the G band complies well with the variations of RBM. Cyclic voltammetry also gives direct evidence for unzipping in terms of improved capacitance after oxidation followed by more important removal of oxygen functionalities during the reduction step, as reflected in subtle changes of the morphology confirming the formation of graphene nanoribbons. The density functional-based tight binding calculations show additional dependence of chirality and diameter of nanotubes on the epoxide binding energies, which is in agreement with the Raman spectroscopic results and suggests a possible mechanism of unzipping determined by combined effects of the structural characteristics of SWNTs and applied field.
Keywords: density functional-based tight binding calculations; Electrochemistry; graphene; Raman spectral mapping; single-walled carbon nanotubes

Single-layer MoSe2 based NH3 gas sensor - Late, Dattatray J.; Doneux, Thomas; Bougouma, Moussa (Applied Physics Letters, 2014)
High performance chemical sensor is highly desirable to detect traces of toxic gas molecules. Two dimensional (2D) transition metal dichalcogenides (TMDC) semiconducting materials has attracted as high performance gas sensor device applications due to unique properties such as high surface to volume ratio. Here, we describe the utilization of single-layer MoSe2 as high-performance room temperature NH3 gas sensors. Our single-layer MoSe2 based gas sensor device shows comprehensible detection of NH3 gas down to 50 ppm. We also confirmed gas sensing measurement by recording the Raman spectra before and after exposing the device to NH3 gas, which subsequently shows the shift due to charger transfer and analyte gas molecule adsorption on surface of single-layer MoSe2 nanosheet. Our investigations show the potential use of single-layer and few layer thick MoSe2 and other TMDC as high-performance gas sensors. (C) 2014 AIP Publishing LLC.

Subtilase from Beauveria sp.: conformational and functional investigation of unusual stability - Dalal, Sayli A.; More, Snehal V.; Shankar, Shiv; Laxman, Ryali Seeta; Gaikwad, Sushama M. (European Biophysics Journal With Biophysics Letters, 2014)
Retention of total activity of the subtilisin-like serine protease from Beauveria sp. MTCC 5184 (Bprot) in the vicinity of (1) 3 M GdnHCl for 12 h, (2) 50 % methanol and dimethyl sulfoxide each for 24 h, and (3) proteolytic enzymes (trypsin, chymotrypsin, and proteinase K) for 48 h led to expect the enzyme to be a kinetically stable protein. Also, the structure of the protein was stable at pH 2.0. Biophysical characterization and conformational transitions were monitored using steady-state and time-resolved fluorescence, FTIR, and CD spectroscopy. Single tryptophan in the protein exists as two conformers, in hydrophobic and polar environment. The secondary structure of Bprot was stable in 3 M GdnHCl as seen in far-UV CD spectra. The active fraction of Bprot obtained from size-exclusion chromatography in the presence of GdnHCl (1.0-3.0 M) eluted at reduced retention time. The peak area of inactive or denatured protein with the same retention time as that of native protein increased with increasing concentration of denaturant (1.0-4.0 M GdnHCl). However, the kinetics of GdnHCl-induced unfolding as studied from intrinsic fluorescence revealed k (unf) of native protein to be 5.407 x 10(-5) s(-1) and a half-life of 3.56 h. The enzyme is thermodynamically stable in spite of being resistant to the denaturant, which could be due to the effect of GdnHCl imparting rigidity to the active fraction and simultaneously unfolding the partially unfolded protein that exists in equilibrium with the folded active protein. Thermal and pH denaturation of Bprot exhibited interesting structural transitions.
Keywords: Beauveria; Chemical denaturation; Conformational transitions; Serine protease; Subtilase; Thermal denaturation; Thermodynamic stability

Synthesis and characterization of 3-[N,N `-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15: a highly stable and reusable catalyst for epoxidation and sulfoxidation reactions - Lazar, Anish; Thiel, Werner R.; Singh, A. P. (RSC Advances, 2014)
The efficient and reusable oxidation catalyst 3-[N,N'-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15 has been synthesized by the anchoring of the 3-[N,N-bis-3-(salicylidenamino)ethyltriamine] ligand (L or Salpr) on the inner surfaces of organofunctionalized SBA-15 and subsequent complexation with Mo(VI) O-2(acac)(2). The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2-sorption measurements, TG & DTA, solid state C-13, Si-29 NMR spectroscopy, FT-IR, Raman spectroscopy, XPS, DRS UV-Vis spectroscopy, SEM and TEM. XRD and N-2 sorption analyses helped to find out the morphological and textural properties of the synthesized catalysts and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The (100), (110) and (200) reflections in SBA-15 provide hints of a good structural stability, the existence of long range ordering and a high pore wall thickness. TG and DTA results reveal that the thermal stability of (L)Mo(VI)O-2@SBA-15 was maintained up to 300 degrees C. The organic moieties anchored over the surface of the SBA-15 support were determined by solid state C-13 NMR and FT-IR spectroscopy. Further, solid state Si-29 NMR spectroscopy provides the information about the degree of functionalization of the surface silanol groups with the organic moiety. The electronic environment and the oxidation state of the molybdenum site in (L)Mo(VI)O-2@SBA-15 were monitored by Raman spectroscopy, XPS and DRS UV-Vis techniques. Moreover, the morphology and topographic information of the synthesized catalysts were confirmed by SEM and TEM imaging. The synthesized catalysts were evaluated in epoxidation and sulfoxidation reactions, and the results show that (L)Mo(VI)O-2@SBA-15 exhibits high conversion and selectivity towards epoxidation and sulfoxidation reactions in combination with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity. In addition, Sheldon's hot filtration test was also carried out.

Systematic evaluation of tetra-n-butyl ammonium bromide (TBAB) for carbon dioxide capture employing the clathrate process - Babu, Ponnivalavan; Chin, Weng Inn; Kumar, Rajnish; Linga, Praveen (Industrial & Engineering Chemistry Research, 2014)
Hydrate based gas separation (HBGS) process for the precombustion capture of CO2 from a fuel gas mixture is a novel method being investigated among the carbon capture and sequestration techniques to reduce CO2 emissions. The efficiency of the HGBS process can be improved by using promoters that reduce the formation pressure of mixed gas hydrates. In this study the effect of tetra-n-butyl ammonium bromide (TBAB) was systematically investigated at a constant temperature of 279.2 K and pressure of 6.0 MPa for different TBAB concentrations of 0.3, 1.0, 1.5, 2.0, and 3.0 mol %, respectively. The 0.3 mol % solutions had a relatively longer average induction time of 20.1 min but exhibited the highest total normalized gas uptake of 0.0104 (+/- 0.0004) mol of gas/mol of water and highest separation factor of 41.51 (+/- 6.391). On the other hand, the 1.0 mol % solution had very short average induction time (<0.5 min) and it had the highest hydrate growth rate of 60.8 (+/- 9.89) mol of gas. min(-1).m(-3), with the separation factor of 13.78 (+/- 3.30). Gas solubility measurements and microscopic images of the hydrate formation were also presented to provide greater insights into the effect of TBAB concentration on the gas uptake.

Temperature Dependent Phonon Shifts in Single-Layer WS2 - Thripuranthaka, M.; Late, Dattatray J. (Acs Applied Materials & Interfaces, 2014)
Atomically thin two-dimensional tungsten disulfide (WS2) sheets have attracted much attention due to their potential for future nanoelectronic device applications. We report first experimental investigation on temperature dependent Raman spectra of single-layer WS2 prepared using micromechanical exfoliation. Our temperature dependent Raman spectroscopy results shows that the E-2g(1) and A(1g) modes of single-layer WS2 soften as temperature increases from 77 to 623 K. The calculated temperature coefficients of the frequencies of 2LA(M), E-2g(1), A(1g), and A(1g)(M) + LA(M) modes of single-layer WS2 were observed to be -0.008, -0.006, -0.006, and -0.01 cm(-1) K-1, respectively. The results were explained in terms of a double resonance process which is active in atomically thin nanosheet. This process can also be largely applicable in other emerging single-layer materials.
Keywords: layered materials; phonon vibrations; Raman spectroscopy; thermal effect; WS2

Temperature dependent Raman spectroscopy of chemically derived few layer MoS2 and WS2 nanosheets - Thripuranthaka, M.; Kashid, Ranjit V.; Rout, Chandra Sekhar; Late, Dattatray J. (Applied Physics Letters, 2014)
We have systematically investigated the temperature dependent Raman spectroscopy behavior of a few layered MoS2 and WS2 nanosheets synthesized using simple hydrothermal method. Our result reveals A(1g) and E-2g(1) modes soften as temperature increases from 77 K to 623 K. This behavior can be explained in terms of a double resonance process which is active in single-and few layer thick nanosheets. The frequency shifts and peak broadening can provide unambiguous, nondestructive, and accurate information of a few layered MoS2 and WS2. This mechanism can also be applicable in characterizing the structural, optical, electronic, and vibrational properties of other emerging layered materials. (c) 2014 AIP Publishing LLC.

Temperature dependent Raman spectroscopy of chemically derived few layer MoS2 and WS2 nanosheets (vol 104, 081911, 2014) - Thripuranthaka, M.; Kashid, Ranjit V.; Rout, Chandra Sekhar; Late, Dattatray J. (Applied Physics Letters, 2014)

Thermal expansion, anharmonicity and temperature-dependent Raman spectra of single- and few-layer MoSe2 and WSe2 - Late, Dattatray J.; Shirodkar, Sharmila N.; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ChemPhysChem, 2014)
We report the temperature-dependent Raman spectra of single-and few-layer MoSe2 and WSe2 in the range 77-700 K. We observed linear variation in the peak positions and widths of the bands arising from contributions of anharmonicity and thermal expansion. After characterization using atomic force microscopy and high-resolution transmission electron microscopy, the temperature coefficients of the Raman modes were determined. Interestingly, the temperature coefficient of the A(2u)(2) mode is larger than that of the A(1g) mode, the latter being much smaller than the corresponding temperature coefficients of the same mode in single-layer MoS2 and of the G band of graphene. The temperature coefficients of the two modes in single-layer MoSe2 are larger than those of the same modes in single-layer WSe2. We have estimated thermal expansion coefficients and temperature dependence of the vibrational frequencies of MoS2 and MoSe2 within a quasi-harmonic approximation, with inputs from first-principles calculations based on density functional theory. We show that the contrasting temperature dependence of the Raman-active mode A(1g) in MoS2 and MoSe2 arises essentially from the difference in their strainphonon coupling.

Thermodynamic and kinetic verification of tetra-n-butyl ammonium nitrate (TBANO(3)) as a promoter for the clathrate process applicable to precombustion carbon dioxide capture - Babu, Ponnivalavan; Yao, Minghuang; Datta, Stuti; Kumar, Rajnish; Linga, Praveen (Environmental Science & Technology, 2014)
In this study, tetra-n-butyl ammonium nitrate (TBANO(3)) is evaluated as a promoter for precombustion capture of CO2 via hydrate formation. New hydrate phase equilibrium data for fuel gas (CO2/H-2) mixture in presence of TBANO(3) of various concentrations of 0.5, 1.0, 2.0, 3.0, and 3.7 mol % was determined and presented. Heat of hydrate dissociation was calculated using Clausius-Clapeyron equation and as the concentration of TBANO(3) increases, the heat of hydrate dissociation also increases. Kinetic performance of TBANO(3) as a promoter at different concentrations was evaluated at 6.0 MPa and 274.2 K. Based on induction time, gas uptake, separation factor, hydrate phase CO2 composition, and rate of hydrate growth, 1.0 mol % TBANO(3) solution was found to be the optimum concentration at the experimental conditions of 6.0 MPa and 274.2 K for gas hydrate formation. A 93.0 mol % CO2 rich stream can be produced with a gas uptake of 0.0132 mol of gas/mol of water after one stage of hydrate formation in the presence of 1.0 mol % TBANO(3) solution. Solubility measurements and microscopic images of kinetic measurements provide further insights to understand the reason for 1.0 mol % TBANO(3) to be the optimum concentration.

Unusual behavior of propane as a co-guest during hydrate formation in silica sand: potential application to seawater desalination and carbon dioxide capture - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Chemical Engineering Science, 2014)
We report an unusual behavior of hydrate formation in silica sand with gas mixtures containing propane as a co-guest. Based on morphology study we observed that propane as a co-guest has the ability to draw water dispersed in silica sand to the hydrate formation region and showed a tendency to result in drastic hydrate growth due to the migration of water molecules to the gas phase region. Hydrate nucleation occurred in the interstitial pore space between the silica sand particles and hydrate growth occurred in the gas phase above the silica sand bed and to sustain the hydrate growth, dispersed water was drawn towards the hydrate growth front. In addition, we elucidated the effect of sand bed height to maximize the growth rates utilizing this behavior that results in enhanced kinetics. We propose conceptual designs for utilizing this behavior of propane as a co-guest in sand for seawater desalination and an innovative approach to simultaneously capture carbon dioxide and desalinate seawater. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Desalination; Enhanced kinetics; Gas hydrates; Propane hydrate: pre-combusuon capture

Unusual morphologies of reduced graphene oxide and polyaniline nanofibers-reduced graphene oxide composites for high performance supercapacitor applications - Diggikar, Rahul S.; Late, Dattatray J.; Kale, Bharat B. (RSC Advances, 2014)
Herein, we have demonstrated the nanostructured rose flowers, sheets, rods and ferns of reduced graphene oxide by using oxalic acid as a reducing agent. The various morphologies of reduced graphene oxide were obtained by time dependent reduction of graphene oxide. The composites of reduced graphene oxide based polyaniline nanofibers, flower bouquet, and honeycombs were grown at a moderate temperature (60 degrees C) by in situ polymerization of aniline. The structural characterization of composites was performed by using X-ray diffraction, and the existence of reduced graphene oxide in different size, shape and thickness was confirmed by Raman spectroscopy and transmission electron microscopy study. The electrochemical study of reduced graphene oxides and their composites with polyaniline nanostructures was performed. The composite of honeycomb reduced graphene oxide-polyaniline nanofibers showed enhancement in the electrochemical performance (specific capacitance: 470 F g(-1)) compared to earlier reports. Such type of composites will be a potential contender for super capacitors.

Unusual, selective, reductive, deoxygenation of cyclopentenone alcohols - Bavikar, Suhas R.; Lasonkar, Trupti P.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2014)
A selective, reductive, deoxygenation of 2-aryl-4-hydroxycyclopent-2-en-1-ones to afford 2-aryl-cyclopent-2-en-1-ones was achieved by NaBH4-CeCl3 in methanol. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cyclopentenone alcohol; Enone; Luche reduction; Reductive deoxygenation

Uptake of Azo dyes into silk glands for production of colored silk cocoons using a green feeding approach - Nisal, Anuya; Trivedy, Kanika; Mohammad, Hasan; Panneri, Suyana; Sen Gupta, Sayam; Lele, Ashish K.; Manchala, Ramesh; Kumar, Nirmal S.; Gadgil, Mugdha; Khandelwal, Harish B.; More, Snehal; Laxman, Ryali Seeta (ACS Sustainable Chemistry & Engineering, 2014)
Dyeing of textile fabrics is considered to be one of the most polluting industries today, and there is a need to develop green processes that can reduce this pollution. A promising technology that can potentially cleanup the dyeing of silk fibers that are widely used for textile applications would involve the generation of intrinsically colored silk cocoons. This can be achieved by feeding of Bombyx mori silkworm larvae with a modified feed of mulberry leaves containing a sprayed dye solution. This process significantly reduces the need for treating toxic dye effluents that are generated in traditional dyeing processes. In this report, we have evaluated a set of seven different azo dyes that are used in the textile industry for dyeing to produce intrinsically dyed silk. The dyes used in the study had similar chemical structures with systematically varying partition coefficients. The results suggest that while some dyes produced intrinsically colored silk other did not. Careful evaluation of the physical properties of these related azo dyes suggest that the balance of hydrophobic and hydrophilic character is necessary for diffusion of the dye from the alimentary canal of the silkworm larva into the hemolymph and later into the silk glands. The partition coefficient of the dye also determines the preferential association of the dye with either sericin or fibroin protein in the silkworm gland and finally into the cocoon. These insights are extremely important in development of novel dye molecules that can be successfully fed to Bombyx mori silkworm larvae for producing intrinsically colored silk of various colors and shades.
Keywords: Azo dyes; Biochemical pathways; Color silk; Dye uptake; `' Green `' silk

3D Hetero-architecture of GdB6 nanoparticles on lessened cubic Cu2O nanowires: enhanced field emission behaviour - Suryawanshi, Sachin R.; Singh, Anil K.; Deo, Meenal S.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (CrystEngComm, 2015)
The field emission properties (FE) of a heteroarchitecture comprised of gadolinium hexaboride nanoparticles uniformly decorated over Cu2O nanoneedles (GdB6/Cu2O) have been investigated at the base pressure of similar to 1 x 10(-8) mbar. Under the optimized pulsed laser deposition (PLD), a well-adhered coating of GdB6 nanoparticles on chemically synthesized cuprous oxide (Cu2O) nanoneedles has been obtained. A plausible growth mechanism of the hierarchical assembly of GdB6 nanoparticles on the Cu2O nanoneedles is explained on the basis of structural analysis carried out using SEM and TEM. A low turn-on field of similar to 2.3 V mu m(-1) (to draw an emission current density similar to 1 mu A cm(-2)) is observed along with stable emission current at the preset value of similar to 2 mu A over 4 h. The enhanced emission behaviour of the GdB6/Cu2O heteroarchitecture, in contrast to the pristine Cu2O nanoneedles, is attributed to its high aspect ratio and low work function. The observed FE results demonstrate GdB6/Cu2O heteroarchitecture as a potential candidate for application in various vacuum nano/microelectronic devices.

Advances in molecular quantum chemistry contained in the Q-Chem 4 program package - Shao, Yihan; Gan, Zhengting; Epifanovsky, Evgeny; Gilbert, Andrew T. B.; Wormit, Michael; Kussmann, Joerg; Lange, Adrian W.; Behn, Andrew; Deng, Jia; Feng, Xintian; Ghosh, Debashree (Molecular Physics, 2015)
A summary of the technical advances that are incorporated in the fourth major release of the Q-Chem quantum chemistry program is provided, covering approximately the last seven years. These include developments in density functional theory methods and algorithms, nuclear magnetic resonance (NMR) property evaluation, coupled cluster and perturbation theories, methods for electronically excited and open-shell species, tools for treating extended environments, algorithms for walking on potential surfaces, analysis tools, energy and electron transfer modelling, parallel computing capabilities, and graphical user interfaces. In addition, a selection of example case studies that illustrate these capabilities is given. These include extensive benchmarks of the comparative accuracy of modern density functionals for bonded and non-bonded interactions, tests of attenuated second order Moller-Plesset (MP2) methods for intermolecular interactions, a variety of parallel performance benchmarks, and tests of the accuracy of implicit solvation models. Some specific chemical examples include calculations on the strongly correlated Cr-2 dimer, exploring zeolite-catalysed ethane dehydrogenation, energy decomposition analysis of a charged ter-molecular complex arising from glycerol photoionisation, and natural transition orbitals for a Frenkel exciton state in a nine-unit model of a self-assembling nanotube.

Arsenic detection in water: YPO4:Eu3+ nanoparticles - Ghosh, Debasish; Luwang, Meitram Niraj (Journal of Solid State Chemistry, 2015)
This work reports on the novel technique of detection of arsenic in aqueous solution utilising the luminescence properties of lanthanide doped nanomaterials. Eu3+ (5%) doped YPO(4)nanorodswere utilised for the said experiment. Co-precipitation method was used for the synthesis of the materials and characterised them with different instrumental techniques like X-ray diffraction (XRD), Infra-red (IR), UV-absorption, scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS) and photoluminescence studies. This nanoparticle can adsorb both arsenic and arsenious acids. We studied the effect of arsenic adsorption on the luminescence behaviour of the nanoparticles. Arsenic acid enhanced the luminescence intensity whereas arsenious acid quenched the luminescence. This luminescence enhancement or quenching is related with arsenic concentration. This relation of luminescence property with concentration of arsenic can be used to detect arsenic in industrial waste. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Arsenic detection; Luminescence; Nanomaterials

Biophysicochemical characterization of an alkaline protease from beauveria sp. MTCC 5184 with multiple applications - Shankar, Shiv; Laxman, Ryali Seeta (Applied Biochemistry and Biotechnology, 2015)
This study illustrates the biophysicochemical properties of an alkaline protease, BAP (Beauveria sp. alkaline protease) from Beauveria sp. MTCC 5184. This protease exhibited maximum activity at 50 degrees C, pH 9.0, and stability in a broad pH range, in the presence of organic solvents, denaturants, as well as detergents. Wash performance studies revealed that BAP was able to remove blood clots/stains from blood-soaked cloth. Peptide mass fingerprinting results demonstrated partial homology of BAP with subtilisin-like proteinase. BAP showed catalytic activity against natural as well as synthetic substrates. Active site characterization of BAP confirmed the involvement of serine, tryptophan, and aspartic acid in catalytic activity. Detailed kinetic and thermodynamic studies of BAP demonstrated that the activation energy (Ea) for casein hydrolysis was 82.55 kJ/M, the specificity constant (Kcat/K-m), and the values of Delta G (change in Gibbs free energy) decreased with increase in temperature, whereas Delta H (change in enthalapy) and Delta S (change in entropy) were constant. The results of the present study indicate that BAP has potential for applications as detergent additive, in peptide synthesis, and in basic research.
Keywords: Active site; Alkaline Protease; Beauveria sp; Organic solvent; Substrate kinetics

Black phosphorous nanosheets: prospective field emitter - Late, Dattatray J.; Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We report for the first time field electron emission investigations on few layered black phosphorous nanosheets emitter's synthesized using chemical method with thickness similar to 2-5 nm. The turn-on electric field required to draw an emission current density of similar to 10 mu A/cm(2) was found to be similar to 4.2 V/mu m. Furthermore, a few layer black phosphorous nanosheets emitter deliver an large emission current density of similar to 170 mu A/cm(2) at an applied field of similar to 7.5 V/mu m. The emission current versus time plot measured at the preset current values of similar to 5 mu A shows field emission current fluctuations within +/- 10% of the average value indicating the well stable nature of black phosphorous field emitter. Thus, the two dimensional black phosphorous nanosheets synthesized using simple electrochemical exfoliation method can be realized and utilized for the next generation micro/nanoelectronics and flat panel field emission based display applications.

Carboxymethyl cellulose based multifunctional targeted drug delivery platform for pancreatic cancer: nanotheranostic potential and biocompatibility analysis - Joshi, Preeti Nigam; Wangnoo, Shishanka; Louis, Michelle (World Journal of Pharmaceutical Sciences, 2015)

Cell line development for biomanufacturing processes: recent advances and an outlook - Le, Huong; Vishwanathan, Nandita; Jacob, Nitya M.; Gadgil, Mugdha; Hu, Wei-Shou (Biotechnology Letters, 2015)
At the core of a biomanufacturing process for recombinant proteins is the production cell line. It influences the productivity and product quality. Its characteristics also dictate process development, as the process is optimized to complement the producing cell to achieve the target productivity and quality. Advances in the past decade, from vector design to cell line screening, have greatly expanded our capability to attain producing cell lines with certain desired traits. Increasing availability of genomic and transcriptomic resources for industrially important cell lines coupled with advances in genome editing technology have opened new avenues for cell line development. These developments are poised to help biosimilar manufacturing, which requires targeting pre-defined product quality attributes, e.g., glycoform, to match the innovator's range. This review summarizes recent advances and discusses future possibilities in this area.
Keywords: Biomanufacturing; Biosimilars; Cell line development; CHO cells genomics; Genome editing; Transcriptomics

Chromerid genomes reveal the evolutionary path from photosynthetic algae to obligate intracellular parasites - Woo, Yong H.; Ansari, Hifzur; Otto, Thomas D.; Klinger, Christen M.; Kolisko, Martin; Michalek, Jan; Saxena, Alka; Shanmugam, Dhanasekaran; Tayyrov, Annageldi; Veluchamy, Alaguraj; Ali, Shahjahan; Bernal, Axel; et al. (Elife, 2015)
The eukaryotic phylum Apicomplexa encompasses thousands of obligate intracellular parasites of humans and animals with immense socio-economic and health impacts. We sequenced nuclear genomes of Chromera velia and Vitrella brassicaformis, free-living non-parasitic photosynthetic algae closely related to apicomplexans. Proteins from key metabolic pathways and from the endomembrane trafficking systems associated with a free-living lifestyle have been progressively and non-randomly lost during adaptation to parasitism. The free-living ancestor contained a broad repertoire of genes many of which were repurposed for parasitic processes, such as extracellular proteins, components of a motility apparatus, and DNA-and RNA-binding protein families. Based on transcriptome analyses across 36 environmental conditions, Chromera orthologs of apicomplexan invasion-related motility genes were co-regulated with genes encoding the flagellar apparatus, supporting the functional contribution of flagella to the evolution of invasion machinery. This study provides insights into how obligate parasites with diverse life strategies arose from a once free-living phototrophic marine alga.

Citreicella manganoxidans sp nov., a novel manganese oxidizing bacterium isolated from a shallow water hydrothermal vent in Espalamaca (Azores) - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A Gram-stain negative, non-motile, non-spore forming, aerobic and rod or narrow lemon-shaped bacterial strain, VSW210(T), was isolated from surface seawater in a shallow water hydrothermal vent region in Espalamaca (Azores). Strain VSW210(T) was found to grow optimally at 30 A degrees C, at pH 7 and in the presence of 2-6 % (w/v) NaCl. A neighbour-joining phylogenetic tree based on 16S rRNA gene sequences revealed that strain VSW210(T) clusters with the type strain Citreicella marina CK-I3-6(T) (sequence similarity value of 99.6 %), but DNA-DNA hybridization showed DNA-DNA relatedness between the strain VSW210(T) and C. marina CK-I3-6(T) to be 55.8 +/- A 3.2 %. The DNA G+C content of strain VSW210(T) was determined to be 67.4 mol%. The cellular fatty acid profiles of strain VSW210(T) was found to contain C-18:1 omega 7c (80.1 %) and C-16:0 (9.2 %). The major polar lipids in strain VSW210(T) were identified as phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and an unidentified phospholipid. Strain VSW210(T) was found to be able to oxidize soluble Mn(II) to insoluble MnO2, which was confirmed with LBB staining. Differential phenotypic properties and genetic uniqueness revealed that this strain VSW210(T) is distinguishable from other species of the genus Citreicella. On the basis of the data presented, strain VSW210(T) is considered to represent a novel species of the genus Citreicella, for which the name Citreicella manganoxidans sp. nov. is proposed. The type strain is VSW210(T) (=KCTC 32497(T) = MCC 2286(T)).
Keywords: Azores; Citreicella manganoxidans sp nov; Hydrothermal vent; Polyphasic taxonomy; Seawater

Combined experimental and theoretical study of the structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 - Jana, Manoj K.; Singh, Anjali; Late, Dattatray J.; Rajamathi, Catherine R.; Biswas, Kanishka; Felser, Claudia; Waghmare, Umesh V.; Rao, C. N. R. (Journal of Physics-Condensed Matter, 2015)
The recent discovery of non-saturating giant positive magnetoresistance has aroused much interest in Td-WTe2. We have investigated structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 experimentally and theoretically. Spin-orbit coupling is found to govern the semi-metallic character of Td-WTe2 and its structural link with the metallic 1 T form provides an understanding of its structural stability. There is a metal-to-insulator switch-over in the electrical conductivity and a change in the sign of the Seebeck coefficient around 373 K. Lattice vibrations of Td-WTe2 have been analyzed using first-principles calculations. Out of the 33 possible zone-center Raman active modes, five distinct Raman bands are observed around 112, 118, 134, 165 and 212 cm(-1) in bulk Td-WTe2. Based on symmetry analysis and calculated Raman tensors, we assign the intense bands at 165 cm(-1) and 212 cm(-1) to the A(1)' and A(1)'' modes, respectively. Most of the Raman bands stiffen with decreasing thickness, and the ratio of the integrated intensities of the A(1)'' to A(1)' bands decreases in the few-layer sample, while all the bands soften in both the bulk and few-layer samples with increasing temperature.
Keywords: Raman spectroscopy; Td-structure; tungsten ditelluride

Design and synthesis of a focused library of diamino triazines as potential mycobacterium tuberculosis DHFR inhibitors - Lele, Arundhati C.; Raju, Archana; Khambete, Mihir P.; Ray, M. K.; Rajan, M. G. R.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Degani, Mariam S. (ACS Medicinal Chemistry Letters, 2015)
We report design of a series of 2,4-diamino triazines as Mycobacterium tuberculosis (Mtb) dihydrofolate reductase inhibitors. The synthesized compounds were evaluated against Mtb (H(37)Rv and Dormant stage H37Ra), their cytotoxicity was assessed (HepG2 and A549 cell lines), and selectivity toward Mtb was evaluated by testing against other bacterial strains. Some derivatives showed promising activity along with low cytotoxicity. The most potent compound in the whole cell assay (MIC 0.325 mu M against H(37)Rv) showed selectivity in the enzyme assay and exhibited synergy with second line anti-TB agent p-amino salicylic acid. This study therefore provides promising molecules for further development as antituberculosis DHFR inhibitors.
Keywords: Diamino triazine; dihydrofolate reductase; enzyme assay; molecular modeling; Mycobacterium tuberculosis; selectivity; synergy

Eco-friendly enzymatic dehairing of skins and hides by C-brefeldianus protease - Khandelwal, Harish B.; More, Snehal V.; Kalal, K. M.; Laxman, Ryali Seeta (Clean Technologies and Environmental Policy, 2015)
Alkaline protease from Conidiobolus brefeldianus was efficient in unhairing various types of skins and hides. The crude protease preparation was active toward keratin-azure, elastin-orcin, azocasein, and azocoll, but did not show true collagenase activity. In addition, the crude enzyme exhibited other enzyme activities such as chondroitinase, laminarase, and chitinase. Complete hair removal of skin/hide by the protease achieved in 16-18 h. The dehaired pelt showed smooth and white appearance due to hair removal along with epidermal layer. In addition, the grain was clean and without damage in enzymatically dehaired pelts. The microscopic observation of the cross-section of dehaired goat skin and cow hide showed absence of epidermis, hair shaft with empty follicles. Enzymatic dehairing resulted in complete and uniform fiber opening in the dermis and corium region. Physical properties viz. tensile strength, elongation, and tear strength of dyed crust of enzymatically and conventionally dehaired pelts were comparable. Results were also validated on large scale with goat skins and cow hides.
Keywords: Alkaline Protease; Conidiobolus brefeldianus; Cow hides; Dehaired pelts; Enzymatic dehairing; Sheep skins

Ecological turmoil in evolutionary dynamics of plant-insect interactions: defense to offence - Mishra, Manasi; Lomate, Purushottam R.; Joshi, Rakesh S.; Punekar, Sachin A.; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
Available history manifests contemporary diversity that exists in plant-insect interactions. A radical thinking is necessary for developing strategies that can co-opt natural insect-plant mutualism, ecology and environmental safety for crop protection since current agricultural practices can reduce species richness and evenness. The global environmental changes, such as increased temperature, CO (2) and ozone levels, biological invasions, land-use change and habitat fragmentation together play a significant role in re-shaping the plant-insect multi-trophic interactions. Diverse natural products need to be studied and explored for their biological functions as insect pest control agents. In order to assure the success of an integrated pest management strategy, human activities need to be harmonized to minimize the global climate changes. Plant-insect interaction is one of the most primitive and co-evolved associations, often influenced by surrounding changes. In this review, we account the persistence and evolution of plant-insect interactions, with particular focus on the effect of climate change and human interference on these interactions. Plants and insects have been maintaining their existence through a mutual service-resource relationship while defending themselves. We provide a comprehensive catalog of various defense strategies employed by the plants and/or insects. Furthermore, several important factors such as accelerated diversification, imbalance in the mutualism, and chemical arms race between plants and insects as indirect consequences of human practices are highlighted. Inappropriate implementation of several modern agricultural practices has resulted in (i) endangered mutualisms, (ii) pest status and resistance in insects and (iii) ecological instability. Moreover, altered environmental conditions eventually triggered the resetting of plant-insect interactions. Hence, multitrophic approaches that can harmonize human activities and minimize their interference in native plant-insect interactions are needed to maintain natural balance between the existence of plants and insects.
Keywords: Climatic change; Co-evolution; Ecosystem; Human interference; Plant-insect interaction

Electrochemically exfoliated black phosphorus nanosheets - prospective field emitters - Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
Herein we report field emission (FE) investigations on an electrochemically exfoliated few-layered black phosphorus nanosheet emitter at a base pressure of approximately 1x10(-8) mbar. The turn-on electric field required to draw an emission current density of approximately 10 A/cm(2) is found to be about 4.2 V/m. Furthermore, few-layered black phosphorus nanosheet emitters deliver an emission current density of about 170 A/cm(2) at an applied field of about 7.5 V/m. The emission current vs. time plot measured at preset current values of about 5 A shows emission current fluctuations within +/- 10% of the average value, indicating the highly stable nature of the black phosphorus field emitter. Thus, the 2D black phosphorus nanosheets synthesized using the simple electrochemical exfoliation method can be utilized for micro/nanoelectronics and flat panel FE display applications.
Keywords: field emission; Layered compounds; Nanostructures; Phosphorus

Emerging energy applications of two-dimensional layered materials - Late, Dattatray J.; Rout, Chandra Sekhar; Chakravarty, Disha; Ratha, Satyajit (Canadian Chemical Transactions, 2015)
Atomically thin semiconducting transition metal dichalcogenides (TMDCs) layered materials have recently been emerged as an exciting area of research due to accessibility for easy synthesis using various chemical and physical methods. These two-dimensional (2D) layered materials with single layer have direct and wide band gap due to which, they are more suitable for nanoelectronics and optoelectronics device applications. Here, we present a review of the energy related aspects of atomically thin layered materials like MoS2, WS2, MoSe2, WSe2, InSe, GaSe, GaTe, MoTe2, WTe2 etc. for supercapacitor, solar cell, lithium ion battery and water splitting application. By significantly assessing various materials and comparing their performances with challenging technology, the advantages and disadvantages of this promising area of energy materials are recognized, which may provide guidelines for future progress.

Enhanced carbon dioxide hydrate formation kinetics in a fixed bed reactor filled with metallic packing - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Chemical Engineering Science, 2015)

Enhanced electron field emission from NiCo2O4 nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Materials Research Express, 2015)
Electron emission properties of electrodeposited spinel NiCo2O4 nanosheet arrays grown on Ni foam have been studied. The work function of NiCo2O4 was calculated by density functional theory using the plane-wave basis set and used to estimate the field enhancement factor. The NiCo2O4 nanosheet arrays exhibited a low turn-on field of 1.86 V mu m(-1) at 1 mu A cm(-2) and current density of 686 mu A cm(-2) at 3.2 V mu m(-1), with field enhancement factor beta = 1460 and good field emission current stability. The field emission properties of the NiCo2O4 nanosheet arrays showed enhanced performance compared to chemically prepared NiCo2O4 nanosheets. Hence, the nanosheet arrays have great potential as robust high performance vertical structure electron emitters for future flat panel displays and vacuum electronic device applications.
Keywords: Density functional theory; field emission; nanosheets; NiCo2O4; spinel

Enhanced field emission of plasma treated multilayer graphene - Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2015)
Electron emission properties of multilayer graphene (MLG) prepared by a facile exfoliation technique have been studied. Effect of CO2 Ar, N-2, plasma treatment was studied using Raman spectroscopy and investigated for field emission based application. The CO2 plasma treated multilayer graphene shows an enhanced field emission behavior with a low turn on field of 0.18 V/mu m and high emission current density of 1.89 mA/cm(2) at an applied field of 0.35 V/mu m. Further the plasma treated MLG exhibits excellent current stability at a lower and higher emission current value. (C) 2015 AIP Publishing LLC.

Exfoliation of bulk inorganic layered materials into nanosheets by the rapid quenching method and their electrochemical performance - Chakravarty, Disha; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report herein the results of our investigations on the synthesis of transition-metal dichalcogenide (TMDC) semiconductor layered materials of MoS2, WS2, MoSe2, and WSe2 by the rapid quenching method. The bulk powders were added to deionized water in a polypropylene tube and subsequently flushed with argon gas. Thirty rapid freezing (30 s in a liquid nitrogen bath) and heating (20 min in an oil bath at 60 degrees C) cycles were then carried out. The reaction product was obtained in a yield in excess of 60 wt.-%, which indicates that the method can be utilized on an industrial scale for the production of 2D nanosheets. The as-synthesized products were then characterized by TEM, which revealed nanosheet-like morphologies. Raman spectroscopy confirmed the high quality of the nanosheet samples. The exfoliated samples also showed good electrochemical performance. Of the TMDC samples investigated, the WSe2 nanosheets were found to give the best performance due to their uniform morphology, large surface area, and fewest number of defects.
Keywords: chalcogenides; Electrochemistry; Layered compounds; Molybdenum; Nanostructures; Tungsten

Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).

Extrusion film casting of long chain branched polypropylene - Chikhalikar, Kalyani; Banik, Sourya; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Doshi, Pankaj; Pol, Harshawardhan; Lele, Ashish K. (Polymer Engineering and Science, 2015)
Extrusion film casting (EFC) is an important melt processing operation which is extensively used to make polypropylene (PP) films. Linear PP shows significant amount of necking and draw resonance during EFC. One of the ways to reduce necking is to introduce long chain branches (LCB) on the polymer backbone. The long branches impart extensional strain hardening behavior thereby stabilizing the melt flow. In this work, we investigate the influence of long chain branching in polypropylene on the extent of necking in the EFC process. Laboratory scale EFC experiments were performed on homopolymer PP of linear and long chain branched architectures. Simulations of the EFC process were carried out using the one-dimensional flow model of Silagy et al., Polym. Eng. Sci.,36, 2614 (1996) into which we incorporate two different multi-mode molecular constitutive equations namely, the eXtended Pom-Pom' equation (XPP, for long chain branched PP) and the Rolie-Poly' equation (RP-S, for linear PP). Our experimental data confirm that presence of long chain branching in PP reduces the extent of necking and our numerical predictions show qualitative agreement with experimental data, thereby elucidating the role of chain architecture on the extent of necking. POLYM. ENG. SCI., 55:1977-1987, 2015. (c) 2014 Society of Plastics Engineers

Facile synthesis of Ag nanowire-rGO composites and their promising field emission performance - Samantara, Aneeya K.; Mishra, Dillip Kumar; Suryawanshi, Sachin R.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Jena, Bikash Kumar; Rout, Chandra Sekhar (RSC Advances, 2015)
Crystalline, ultra long silver nanowires (Ag NWs), few-layered rGO (reduced graphene oxide) and their rGO-Ag NW nanocomposite have been synthesized using a polyol reflux technique under optimized experimental conditions. The field emission performance of the rGO-Ag NW nanocomposite, rGO and Ag NW emitters was investigated. The turn on field required to draw an emission current density of similar to 1 mA cm(-2) was found to be similar to 5.00, 3.92 and 2.40 V mu m(-1) for the Ag NW, rGO and rGO-Ag NW nanocomposite emitters, respectively. The combined contribution of the sharp edges of the thin graphene sheets and high aspect ratio of the Ag nanowires, and their synergetic effect in the rGO-Ag NW nanocomposite, are responsible for the enhanced field emission behavior. First-principles density functional calculations show that the enhanced field emission may also be due to the overlapping of the electronic structures of the Ag NWs and rGO nanosheets.

Field emission properties of spinel ZnCo2O4 microflowers - Ratha, Satyajit; Khare, Ruchita T.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2015)
ZnCo2O4 microflowers were synthesized by a simple low temperature hydrothermal route. A single three-dimensional microflower consists of hundreds of self-assembled petals, with a thickness of several nanometers. These microflowers have exceptionally thin edges with a few petal layers. The ZnCo2O4 microflowers appeared to be stable and good field emitters.

First enantioselective synthesis of surinamensinol B and a non-natural polysphorin analogue by a two-stereocentered hydrolytic kinetic resolution - Lalwani, Komal G.; Sudalai, Arumugam (European Journal of Organic Chemistry, 2015)
An efficient and economical approach to the synthesis of antitumor and anti-inflammatory surinamensinol B (1) and antimalarial polysphorin analogue 2 has been achieved with high enantiomeric purity (96% ee) by starting from commercially available 3,4,5-trimethoxybenzaldehyde. The key steps of the strategy include a Co-catalyzed two-stereocentered hydrolytic kinetic resolution (HKR) of racemic 2[( methoxymethoxy)(3,4,5-trimethoxyphenyl)methyl] oxirane (13) as the chiral inducing step followed by a Mitsunobu reaction. Chiral epoxide 14 and chiral diol 15 were utilized in the syntheses of both compounds.
Keywords: Biological activity; Enantioselectivity; Kinetic resolution; Natural products; Total synthesis

First regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles - Rode, Navnath D.; Sonawane, Amol D.; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P. (Tetrahedron Letters, 2015)
The regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles is described for the first time. The iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles using molecular iodine afforded diiodo-compound which on Cul-catalyzed intramolecular C-N coupling reaction gave six-membered 2-aryl-51141,2,4]triazolo[5,1-b][1,3]thiazines, whereas, the five membered 3-aryl-5,6-dihydrothiazolo[2,3-c][1,2,4]triazoles were obtained exclusively when the iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles was carried out using NIS. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Iodocyclization; Regloselective; Thiazine; Triazole

Gelation landscape engineering using a multi-reaction supramolecular hydrogelator system - Foster, Jamie S.; Zurek, Justyna M.; Almeida, Nuno M. S.; Hendriksen, Wouter E.; le Sage, Vincent A. A.; Lakshminarayanan, Vasudevan; Thompson, Amber L.; Banerjee, Rahul; Eelkema, Rienk; Mulvana, Helen; Paterson, Martin J.; van Esch, Jan H.; et al. (Journal of the American Chemical Society, 2015)
Simultaneous control of the kinetics and thermodynamics of two different types of covalent chemistry allows pathway selectivity in the formation of hydrogelating molecules from a complex reaction network. This can lead to a range of hydrogel materials with vastly different properties, starting from a set of simple starting compounds and reaction conditions. Chemical reaction between a trialdehyde and the tuberculosis drug isoniazid can form one, two, or three hydrazone connectivity products, meaning kinetic gelation pathways can be addressed. Simultaneously, thermodynamics control the formation of either a keto or an enol tautomer of the products, again resulting in vastly different materials. Overall, this shows that careful navigation of a reaction landscape using both kinetic and thermodynamic selectivity can be used to control material selection from a complex reaction network.

Graphene nanoribbons as prospective field emitter - Khare, Ruchita T.; Shinde, Dhanraj B.; Bansode, Sanjeewani; More, Mahendra A.; Majumder, Mainak; Pillai, Vijayamohanan K.; Late, Dattatray J. (Applied Physics Letters, 2015)
Field emission characteristics of graphene nanoribbons (GNRs) synthesized by unzipping of multiwall carbon nanotubes using a facile hydrothermal route have been investigated at a base pressure of 1 x 10(-8) mbar. The values of turn-on field, required to draw an emission current densities of 1 and 10 mu A/cm(2), are found to be 2.8 and 5.8 V/mu m, respectively, and a maximum emission current density of 500 mu A/cm(2) has been drawn at an applied field of 9.8 V/mu m. The emission current stability of the GNRs emitter was studied at preset values of 1 and 10 mu A over a period of 3 h, and is found to be excellent. The field emission results demonstrated herein suggest that GNRs based field emitters can open up many opportunities for their potential utilization as large area field emitters in various vacuum micro-nanoelectronic devices such as flexible field emission displays, portable X-ray, and microwave tubes. (C) 2015 AIP Publishing LLC.

Graphene quantum dots as enhanced plant growth regulators: effects on coriander and garlic plants - Chakravarty, Disha; Erande, Manisha B.; Late, Dattatray J. (Journal of the Science of Food and Agriculture, 2015)
BACKGROUNDWe report investigations on the use of graphene quantum dots for growth enhancement in coriander (Coriandrum sativam L.) and garlic (Allium sativum) plants. The as-received seeds of coriander and garlic were treated with 0.2 mg mL(-1) of graphene quantum dots for 3 h before planting. RESULTSGraphene quantum dots enhanced the growth rate in coriander and garlic plants, including leaves, roots, shoots, flowers and fruits, when the seeds were treated with graphene quantum dots. CONCLUSIONOur investigations open up the opportunity to use graphene quantum dots as plant growth regulators that can be used in a variety of other food plants for high yield. (c) 2015 Society of Chemical Industry
Keywords: farming; food; graphene quantum dots; nanotechnology; plant growth regulator

Green synthesis of silver nanoribbons from waste X-ray films using alkaline protease - Shankar, Shiv; Prasad, R. G. S. V.; Selvakannan, P. R.; Jaiswal, Lily; Laxman, Ryali Seeta (Materials Express, 2015)
This work illustrates a facile approach to synthesize silver nanoribbons from waste X-ray films using alkaline protease from Beauveria sp. MTCC 5184 (BAP). The green synthesized nanoribbons have been characterized by UV-Vis spectroscopy, TEM, and FTIR. The UV-visible spectra gave maximum absorbance at 400 nm. TEM micrograph showed well-dispersed silver nanoribbons with an average length of 200-400 nm. FTIR result demonstrated the respective bands of the silver nanoribbons and proteins. XRD data revealed crystalline nature of silver nanoribbons dominated with (111) facets. In vitro antibacterial activity in terms of minimum inhibitory concentrations (MIC) and minimum bactericidal concentration (MBC) showed 8/16 mu g/mL (MIC/MBC) against Staphylococcus aureus ATCC 29213 and 4/8 mu g/mL (MIC/MBC) against Escherichia coli ATCC 25922. The green synthesized silver nanoribbons showed excellent biocompatibility up to 40 mu g/mL concentrations on mouse fibroblast cell line (L929).
Keywords: Alkaline Protease; Characterization; Cytotoxicity; Silver Nanoribbons; Waste X-ray Film

Heterogeneously catalyzed strategies for the deconstruction of high density polyethylene: plastic waste valorisation to fuels - Burange, Anand S.; Gawande, Manoj B.; Lam, Frank L. Y.; Jayaram, Radha V.; Luque, Rafael (Green Chemistry, 2015)
The plastic industry generates enormous quantities of plastics at projected rates (both production and consumption) which can significantly threaten our environment in terms of plastic waste generation. High density polyethylene (HDPE) is one of the main fractions of municipal solid waste which has a remarkable potential to be valorised into fuels (e.g. bio-oils). Catalytic degradation is an innovative alternative process to transform plastic waste into such value added products. This mini review was aimed to discuss the most relevant and recent catalysts developed for the catalytic degradation of HDPE including metal oxides, sulphated metal oxides, zeolites, nanostructured zeolites, molecular sieves, fluid catalytic cracking (FCC) catalysts, metal carbonates and mesoporous materials for the production of chemicals and fuels (e.g. diesel and gasolines). Activities and selectivities as well as important effects of additives, particle size, catalyst to polymer ratios and also recent approaches for waste management will be discussed.

High performance single crystalline PbWO4 nanorod field effect transistor - Walke, Pravin S.; Patil, Vandana B.; Mulla, Imtiaz S.; Late, Dattatray J. (Journal of Materials Science-Materials in Electronics, 2015)
The highly crystalline PbWO4 nanorods were synthesized using simple co-precipitation method which has application in field effect transistor. The synthesized PbWO4 nanorods were characterized by XRD, Raman spectroscopy, TEM and HRTEM indicating highly crystalline nature. Field effect transistor was fabricated on pre-patterned 300 nm SiO2/Si substrates using photolithography technique with channel length 1 A mu m and width 20 A mu m. Thin film (similar to 100 nm) was made up of PbWO4 nanorods by spin coating on the pre-patterned device used as channel layer. The field effect mobility was observed to be 4.7 cm(2) V-1 s(-1) and I-ON/OFF ratio similar to 10(3) which is far better than the organic molecules due to single crystalline nature and rod like morphology of the PbWO4 providing direct path for charges to transport towards channel.

Hydrogen production by the water-gas shift reaction using CuNi/Fe2O3 catalyst - Jha, Ajay; Jeong, Dae-Woon; Shim, Jae-Oh; Jang, Won-Jun; Lee, Yeol-Lim; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Science & Technology, 2015)
Incorporation of both Cu and Ni together into the crystalline lattice of Fe2O3 results in a significant increase in the catalytic activity and also suppresses the methanation reaction in the high-temperature water-gas shift (HT-WGS) reaction. CuNi/Fe2O3 exhibited the highest CO conversion with negligible CH4 selectivity at the extremely high GHSV of 101 000 h(-1) (X-CO = 85% at 400 degrees C). The high activity of CuNi/Fe2O3 catalyst is mainly due to the increase in the lattice strain and the decrease in the binding energy of lattice oxygen. In addition, X-ray photoelectron spectroscopy (XPS) results provide direct evidence for the formation of surface CuNi alloy, which plays a critical role in suppressing the methanation reaction. The detailed characterization by powder X-ray diffraction (XRD), XPS, BET, and H-2 temperature-programmed reduction (TPR) techniques was used to understand the role of dopants on host iron oxides in the enhancement of catalytic activity for HT-WGS reaction.

Impedimetric humidity sensor based on ?-Fe2O3 nanoparticles - Patil, U. V.; Rout, C. S.; Late, Dattatray J. (Advanced Device Materials, 2015)
Humidity sensing characteristics of thick-film sensors based on α-Fe2O3 nanoparticles synthesized by hydrothermal method have been reported. The as-synthesized α-Fe2O3 nanoparticles were characterized by using XRD, Raman spectroscopy, TEM and HRTEM. Our TEM result depicts that the size of α-Fe2O3 nanoparticles were in the range of 20–30 nm with highly crystalline nature. For humidity sensing experiment, the sensitivity of our α-Fe2O3 nanoparticles-based sensor device was found to be ∼99% and the fastest response times were noted, which indicate that the α-Fe2O3 nanoparticle-based humidity sensor device has more future prospects and demand. The humidity sensing properties of α-Fe2O3 nanoparticles seem to be associated to the sorption sites for the water molecules at the nanoparticles interfaces.

Influence of macromolecular architecture on necking in polymer extrusion film casting process - Pol, Harshawardhan V.; Banik, Sourya; Azad, Lal Busher; Thete, Sumeet; Doshi, Pankaj; Lele, Ashish (30th International Conference of the Polymer-Processing-Society (PPS), 2015)
Extrusion film casting (EFC) is an important polymer processing technique that is used to produce several thousand tons of polymer films/coatings on an industrial scale. In this research, we are interested in understanding quantitatively how macromolecular chain architecture (for example long chain branching (LCB) or molecular weight distribution (MWD or PDI)) influences the necking and thickness distribution of extrusion cast films. We have used different polymer resins of linear and branched molecular architecture to produce extrusion cast films under controlled experimental conditions. The necking profiles of the films were imaged and the velocity profiles during EFC were monitored using particle tracking velocimetry (PTV) technique. Additionally, the temperature profiles were captured using an IR thermography and thickness profiles were calculated. The experimental results are compared with predictions of one-dimensional flow model of Silagy et al(1) wherein the polymer resin rheology is modeled using molecular constitutive equations such as the Rolie-Poly (RP) and extended Pom Pom (XPP). We demonstrate that the 1-D flow model containing the molecular constitutive equations provides new insights into the role of macromolecular chain architecture on film necking. D-1. Silagy, Y. Demay, and J-F. Agassant, Polym. Eng. Sci., 36, 2614 (1996).

Insights into the molecular dynamics in polysulfone polymers from C-13 solid-state NMR experiments - Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Anto, Ralf; Bulakh, Neelima N.; Lele, Ashish K.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry B, 2015)
The molecular and segmental motions in three different grades of ductile polysulfone polymers; poly(ether sulfone) (PESU), polysulfone (PSU), and poly(phenyl sulfone) (PPSU) are probed using C-13 solid-state NMR experiments. Polarization inversion spin exchange at magic angle (PISEMA) experiments indicates that the phenyl rings in the polymers are undergoing pi-flip motions on the order of 100 kHz. The temperature dependent PISEMA experiments show that the fraction of mobile regions that undergoes aromatic pi-flips is higher in PPSU than in the other two polymers. The center band only detection of exchange (CODEX) experiments was carried out and was unable to detect any slow segmental motions in the chains. A combination of C-13 spin-lattice relaxation time (T-1) and T-1-filtered PISEMA experiments show that the mobile regions in all the polymers are dynamically heterogeneous.

Long chain branched impact copolymer of polypropylene: microstructure and rheology - Chikhalikar, Kalyani; Deshpande, Anushree; Pol, Harshawardhan; Dhoble, Deepa Arun; Jha, Saroj; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Lele, Ashish K. (Polymer Engineering and Science, 2015)
A biphasic impact copolymer of polypropylene (ICP) was modified with peroxide by reactive extrusion process resulting in reduced melt flow index, improved melt strength, and higher die swell. The polymers were for the first time subjected to systematic rheological and microstructural characterization in an effort to understand their structure-property relations. In shear rheological tests, the modified ICP displayed higher flow activation energy, reduced values of loss tangent and nearly equal frequency dependence of storage and loss modulli. The modified ICP also showed strain hardening behaviour in uniaxial extensional rheology and higher crystallization temperature in differential scanning calorimetry (DSC). All these are definitive indications of the presence of long chain branches (LCB). Fitting the rheological data of modified ICPs with the eXtended Pom Pom (XPP) model indicated the presence of LCB on the higher molecular weight fraction in the polymer, a result which was corroborated with multi-detector high temperature gel permeation chromatography (HT-GPC). More importantly, the matrix and rubber phases of the ICP were separately characterized for presence of long chain branching by rheology, DSC and HT-GPC. The results indicate that while LCB existed in the matrix phase, microgels were present in both phases indicating that the reaction with peroxide occurred in both phases. POLYM. ENG. SCI., 55:1463-1474, 2015. (c) 2014 Society of Plastics Engineers

Microwave and hydrothermal syntheses of WSe2 micro/nanorods and their application in supercapacitors - Chakravarty, Disha; Late, Dattatray J. (RSC Advances, 2015)
WSe2 micro/nanorods were synthesized using one step microwave and hydrothermal methods. The as synthesized micro/nanorod samples of WSe2 were characterized using various characterization techniques such as SEM, TEM, Raman spectroscopy, X-ray diffraction, UV-visible and PL spectroscopy. The as synthesized samples were also tested for their applicability to use as cathode materials for supercapacitor applications. The WSe2 samples prepared by the microwave and hydrothermal methods (with use of tungstic acid as precursor) show noteworthy performance towards supercapacitor application. Our work opens a new avenue to use these simple methods to prepare various morphologies of inorganic nanomaterials and utilize them for various energy and nanoelectronics applications.

Microwave-assisted synthesis of few-layered TaTe2 and its application as supercapacitor - Chakravarty, Disha; Kumar, Praveen; Ugale, Vaishali S.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report a simple and rapid microwave-assisted synthesis of tantalum telluride (TaTe2) nanosheets. The ratio of tantalum pentachloride (TaCl5) and elemental tellurium (Te) powder were adjusted in the presence of NaBH4 in such a way as to obtain the TaTe2 nanosheet. The samples were characterized by various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), UV/Vis spectroscopy, photoluminescence (PL) spectroscopy, and XRD. Our SEM, TEM, and AFM results show the formation of sheet-like morphology, while the XRD data confirms the high crystalline quality and stable phase of the TaTe2 formed. The supercapacitor cells were fabricated by using TaTe2 nanosheets as anode material, platinum metal wire as a counterelectrode, and Ag/AgCl as reference electrode. The calculated coulombic efficiency is more than 95%, while the cycle-to-cycle decrease in capacity is less than 5%. The maximum discharge or charging capacity is below 2.4 Wh/kg, which is an ideal characteristic for achieving supercapacitor behavior.
Keywords: Microwave chemistry; Nanostructures; Supercapacitors; Tantalum; Tellurium

Modular synthesis of biaryl-substituted phosphine ligands: application in microwave-assisted palladium-catalyzed C-N cross-coupling reactions - Singh, Chandani; Rathod, Jayant; Jha, Vishwajeet; Panossian, Armen; Kumar, Pradeep; Leroux, Frederic R. (European Journal of Organic Chemistry, 2015)
Biaryl-substituted monophosphine-based ligands have been synthesized by transition-metal-free ARYNE cross-coupling reaction of aryllithiums with 1,2-dibromobenzene and subsequent regioselective functionalization through bromine-lithium interconversion. These ligands were employed in palladium-catalyzed C-N bond-forming reactions. The reaction was found to be general with wide substrate applicability. A wide variety of both primary and secondary amines were successfully coupled with an array of differently substituted halobenzenes under microwave irradiation to give the expected products in good to excellent yields. A number of biaryl-substituted phosphine ligands screened for the coupling reaction showed that steric bulk and the electronic properties of substituents on phosphorus play a crucial role in governing the catalytic activity of C-N cross-coupling reactions.
Keywords: Biaryls; Cross-coupling; Homogeneous catalysis; Microwave chemistry; Palladium; Phosphines; synthetic methods

Molecular sieves and ultrasound-assisted synthesis of novel 1,3,4-oxadiazole-2-thiones derivatives as potential antifungal agents - Nikalje, Anna Pratima G.; Nimbalkar, Ms Urja D.; Tupe, Santosh; Vazquez, Julio A. Seijas; Tato, Maria Pilar Vazquez (19TH INTERNATIONAL ELECTRONIC CONFERENCE ON SYNTHETIC ORGANIC CHEMISTRY, 2015)
In the category of microorganism, fungi are considered as the special class of microbes responsible for opportunistic pathogenic infections in humans species. Due to the side effects of commercially available antifungal drugs and the emergence of new drug resistant fungal species in the past few years, has forced the researchers to search for novel and efficient antifungal drug molecules. The 1,3,4-oxadiazoles scaffold is associated with diverse biological activities. The multipurpose use of the Mannich bases in pharmaceutical chemistry promote us to prepare a new series of 5-(4-(benzyloxy)substituted phenyl)-3-((phenyl amino)methyl)-1,3,4oxadiazole-2(3H)-thione as antifungal agents. Herein, we report molecular sieves and ultrasound assisted synthesis of novel series of Mannich bases of the 5-substituted 1,3,4-oxadiazole-2-thiones by amino methylation with paraformaldehyde and substituted primary / secondary amines and their evaluation for antifungal activity. The structures of the newly synthesized compounds were determined by IR, NMR and Mass spectral study. The synthesized compounds exhibited interesting moderate to excellent antifungal activity against Candida albicans (NCIM 3557), Candida albicans(NCIM3471), Candida glabrata(NCIM3237), Cryptococcus neoformans (NCIM 3542), Cryptococcus neoformans(NCIM 3378), Aspergillus fumigates(NCIM 902), Aspergillus niger(NCIM 628) using Flucanazole as a standard reference drug. The synthesised compounds 6d, 6f,6g, 6h and 6j exhibited promising antifungal activity as antifungal agents.
Keywords: 1; 3; 4-oxadiazoles; Antifungal activity; Mannich reaction; Molecular sieves; Ultrasound -assisted

Nanostructured 2D MoS2 honeycomb and hierarchical 3D CdMoS4 marigold nanoflowers for hydrogen production under solar light - Kadam, Sunil R.; Late, Dattatray J.; Panmand, Rajendra P.; Kulkarni, Milind V.; Nikam, Latesh K.; Gosavi, Suresh W.; Park, Chan J.; Kale, Bharat B. (Journal of Materials Chemistry A, 2015)
Unique two dimensional (2D) honeycomb layered MoS2 nanostructures and hierarchical 3D marigold nanoflowers of CdMoS4 were designed using a template free and facile solvothermal method. The MoS2 structure is depicted with a sheet like morphology with lateral dimensions of 5-10 mu m and a thickness of similar to 200 nm and a honeycomb nanostructure architecture produced via the self-assembling of vertically grown thin hexagonal nanosheets with a thickness of 2-3 nm. The 3D CdMoS4 marigold nanoflower architecture comprised thin nanopetals with lateral dimensions of 1-2 mu m and a thickness of a few nm. The CdMoS4 and MoS2 structures displayed hydrogen ( H-2) production rates of 25 445 and 12 555 mu mol h(-1) g(-1), respectively. The apparent quantum yields of hydrogen production were observed to be 35.34% and 17.18% for CdMoS4 and MoS2, respectively. The 3D nanostructured marigold flowers of CdMoS4 and honeycomb like 2D nanostructure of MoS2 were responsible for higher photocatalytic activity due to inhibition of the charge carrier recombination. The prima facie observation of H-2 production showed that the ternary semiconductor confers enhanced photocatalytic activity for H-2 generation due to its unique structure. Such structures can be designed and implemented in other transition metal dichalcogenide based ternary materials for enhanced photocatalytic and other applications.

Nioella nitratireducens gen. nov., sp nov., a novel member of the family Rhodobacteraceae isolated from Azorean Island - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Khieu, Thi-Nhan; Son, Chu Ky; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel Gram-negative, non-spore forming, rod-shaped aerobic bacterium, designated SSW136(T), was isolated from a surface seawater sample collected at Espalamaca (in Faial Island), Azores. Growth was found to occur from 10 to 37 A degrees C, pH 6.0-8.0, and with 2-11 % of NaCl. 16S rRNA gene sequence indicated that the strain SSW136(T) belongs to the family Rhodobacteraceae. Strain SSW136(T) exhibited 96.3, 95.9, 95.7 and 95.5 sequence similarity to the type strains Oceanicola litoreus M-M22(T), Roseovarius aestuarii SMK-122(T), Marivita geojedonensis DPG-138(T), and Pseudoruegeria aquimaris SW-255(T) respectively. Neighbour-joining and maximum-parsimony phylogenetic trees based on 16S rRNA gene sequences revealed that strain SSW136(T) was affiliated to the family Rhodobacteraceae and formed a separate branch. The G+C content was 63.5 mol%. The major respiratory quinone was found to be Q-10. The polar lipids of strain SSW136(T) consisted of phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, two unidentified aminolipids and three unidentified phospholipids. The major fatty acids were C-18:1 omega 7c (46.5 %), Cyclo-C-19:0 omega 8c (16.0 %) and C-16:0 (12.8 %). On the basis of the morphological, genotypic, chemotaxonomic characteristics and low DNA-DNA relatedness, strain SSW136(T) is proposed to represent a novel genus and novel species, Nioella nitratireducens gen. nov., sp. nov., in the family Rhodobacteraceae. The type strain is SSW136(T) (=KCTC 32417(T) = NCIM 5499(T)).
Keywords: Espalamaca; Nioella nitratireducens; Novel genus and species; Polyphasic taxonomy; Seawater

Nonomuraea indica sp nov., novel actinomycetes isolated from lime-stone open pit mine, India - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Li, Jie; Nie, Guo-Xing; Tang, Shu-Kun; Al Ruwaili, Jamal; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (Journal of Antibiotics, 2015)
A Gram-positive, aerobic, nonmotile actinomycete strain designated DRQ-2(T) was isolated from the soil sample collected from limestone open pit mine from the Gulbarga region, Karnataka province, India. Strain DRQ-2(T) was identified as a member of the genus Nonomuraea by a polyphasic approach. Strain DRQ-2(T) could be differentiated from other members of the genus Nonomuraea on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain DRQ-2(T) showed highest sequence similarity to Nonomuraea muscovyensis DSM 45913(T) (99.1%), N. salmonea DSM 43678(T) (98.2%) and N. maheshkhaliensis JCM 13929(T) with 98.0%, respectively. Chemotaxonomic properties showing predominant menaquinones of MK-9 (H-4), MK-9(H-2) and MK-9(H-6), major polar lipids comprised diphosphatidylglycerol, phosphatidylmono methyl ethanolamine (PME), phosphatidylethanolamine (PE), hydroxy-PME (OH-PME), hydroxy PE (OH-PEE), phosphatidylglycerol (PG), ninhydrin-positive phosphoglycolipid and unknown phospholipid, fatty acids with major amounts of i-C-16:0, ai-C-15:0 and ai-C-17:0 supported allocation of the strain to the genus Nonomuraea. Results of DNA-DNA hybridization and physiological tests allowed genotypic and phenotypic differentiation of strain DRQ-2(T) from closely related species. The genomic DNA G+C content of the organism was 72.5 mol%. On the basis of phenotypic, chemotypic and molecular characteristics, strain DRQ-2(T) represents a novel species of the genus Nonomuraea, for which the name N. indica sp. nov. is proposed, with type strain DRQ-2(T) (= NCIM 5480(T) = CCTCC AA 209050(T)).

One-pot synthesis of 2-thenoyltrifluoroacetone surface functionalised SrF2:Eu3+ nanoparticles: trace level detection of water - Ghosh, Debasish; Luwang, Meitram Niraj (RSC Advances, 2015)
This work reports the one pot synthesis of 2-thenoyltrifluoroacetone (TTA) surface functionalised SrF2:Eu3+ nanoparticles. The nanoparticles were characterised by X-ray diffraction (XRD), infra-red (IR), UV-absorption, transmission electron microscopy (TEM), and photoluminescence studies. Sensitization of Eu3+ ion by TTA in SrF2 nanoparticle matrix gives an enhanced luminescence in dry aprotic solvents like tetrahydrofuran (THF), acetonitrile (AN), dichloromethane (DCM) etc. We studied the effect of trace quantity of water on luminescence of the particles in THF solvent. Even a trace level of water content in the solvent is able to quench the luminescence significantly and quenching enhances with addition of more and more water. This approach of luminescence quenching strategy of detecting a minute trace level of water molecules has a potential application in the estimation of water in various dry organic solvents like THF.

One-pot thermal evaporation synthesis of CdS-RGO hetrostructure and its field emission study - Bansode, Sanjeewani R.; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J. (2015 28TH International Vacuum Nanoelectronics Conference (IVNC), 2015)
CdS-RGO heterostructure was synthesized by thermal evaporation method. The as-synthesized CdS-RGO heterostructure was characterized using X-ray Diffraction, SEM, and EADX, before field emission (FE) studies. The FE characteristics of a planar emitter made up of as-synthesized CdS-RGO heterostructures were measured at the base pressure 1x10(-8) mbar. The synthesized CdS-RGO heterostructure emitter is found to deliver a current density similar to 70 mu A/cm(2) at an applied electric field of similar to 4.7 V/mu m. Moreover, the nanocomposite shows excellent emission stability without significant current degradation making CdS-RGO heterostructure as a promising electron source for practical applications in various vacuum nano-microelectronic devices.

Organocatalytic [4+1]-annulation approach for the synthesis of densely functionalized pyrazolidine carboxylates - Lalwani, Komal G.; Aher, Ravindra D.; Sudalai, Arumugam (RSC Advances, 2015)
A novel one-pot [4+1]-annulation process for the asymmetric synthesis of densely functionalized pyrazolidine carboxylates is described. The in situ generated gamma-hydrazino-alpha,beta-unsaturated ester obtained via proline catalysis acts as a four-atom component, and Corey's sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrazolidine carboxylate units in a highly enantio- and diastereoselective fashion.

Organocatalytic enantioselective direct vinylogous michael addition of alpha,beta-unsaturated gamma-butyrolactam to beta-acyl acrylates and 1,2-diacylethylenes - Chen, Yi-Ru; Das, Utpal; Liu, Meng-Hsien; Lin, Wenwei (Journal of Organic Chemistry, 2015)
A highly efficient Michael addition of alpha,beta-unsaturated gamma-butyrolactam to various beta-acyl acrylates and ene-diones to provide synthetically useful compounds was developed. The products were obtained with high diastereo- and enantioselectivities (up to >25:1 dr and 99% ee) containing adjacent tertiary stereocenters.

Oxidative and membrane stress-mediated antibacterial activity of WS2 and rGO-WS2 nanosheets - Navale, Govinda R.; Rout, Chandra Sekhar; Gohil, Kushal N.; Dharne, Mahesh S.; Late, Dattatray J.; Shinde, Sandip S. (RSC Advances, 2015)
Graphene-based materials have strong cytotoxic attributes against bacteria due to their unique physicochemical properties. We examined the antibacterial activities of nanosheets of the graphene analogue tungsten disulphide (WS2) and a composite of reduced graphene oxide-tungsten disulphide (rGO-WS2), comparing them with reduced graphene oxide (rGO) by a time and concentration dependent viability assay and growth curve studies against four bacterial strains: Gram negative Escherichia coli (E. coli) and Salmonella typhimurium (S. typhimurium), and Gram positive Bacillus subtilis (B. subtilis) and Staphylococcus epidermidis (S. epidermidis). The nanosheets of the rGO-WS2 composite caused a more significant retardation in bacterial growth and inhibitory effect on the tested bacterial strains than WS2, followed by rGO. The tested E. coli and B. subtilis strains were more susceptible than the other strains. A mechanistic study revealed that rGO and WS2 did not produce the superoxide anion (O-2(-)) or reactive oxygen species (ROS), but the nanocomposite of rGO-WS2 did produce both. However, all these materials did oxidize glutathione, which serves as a redox state mediator in bacteria. We conclude that the antimicrobial mechanism is due to the combined effect of initial cell deposition on the rGO-WS2 materials, the membrane stress due to direct contact with the nanosheets, and the produced superoxide anion-independent oxidation mechanisms. The beneficial aspects of the physicochemical properties of rGO-WS2, such as its size and conductivity, can be precisely customized to reduce its health and environmental risk factors.

p-Aminobenzoic acid (pABA) sensitization of LaF3:Tb3+ nanoparticles and its applications in the detection of explosive materials - Ghosh, Debasish; Luwang, Meitram Niraj (RSC Advances, 2015)
This work reports the utilization of water dispersible terbium (Tb3+) doped spherical LaF3 nanoparticles (similar to 5 nm) surface functionalised with p-aminobenzoic acid (pABA) for the detection of aromatic nitro explosives. The functionalised nanoparticles show remarkable sensitivity to a number of highly electron deficient aromatic nitro compounds like picric acid (PA), 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (2,4-DNT), 2,4-dinitrophenol (2,4-DNP) etc. All of these nitro compounds can be detected easily at ppm level using this luminescence quenching technique whereas in the case of TNT it can detect concentrations as low as 50 ppb. This novel approach of utilising the Tb3+ doped NPs sensitised by pABA has potential application in the detection of explosive materials.

Perspective on atomically thin 2d inorganic layered materials for biosensor - Late, Dattatray J.; Rout, C. S.; Chakravarty, Disha; Ratha, S. (Journal of Nanomedicine Research, 2015)

Photosensitive field emission study of SnS2 nanosheets - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2015)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to field emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solutions are used. The FE study is carried out in a planar diode configuration at a base pressure of similar to 10(-8) mbar. The emission photosensitivity is also investigated by illuminating the specimen with a visible light source. In dark, the turn on field, the electric field required to obtain a current density of 1 mu A/cm(2), is found to be 5.9 V/mu m. Upon illumination, the emitter with visible light, it is found to reduce to 5.0 V/mu m. A significant change in the nature of the Fowler-Nordheim plot with light illumination is also observed and has been explained on the basis of photoconductivity. Repetitive switching ON and OFF the light source, at a fixed applied voltage, is found to generate current pulses. The photosensitivity is also studied with various color filters. With the photoswitching and the enhanced field emission properties, it is envisaged that SnS(2)NSs possess a potential for optoelectronic applications of field emitters. (C) 2014 American Vacuum Society.

Porous poly(ethylene glycol)-polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Torris, Arun A. T.; Lele, Ashish K.; Badiger, Manohar V. (Polymer International, 2015)
We report the synthesis of porous poly(ethylene glycol)-polyurethane (PEG-PU) hydrogels using PEG-4000 as a soft segment and 4,4-methylenebis(cyclohexylisocyanate) as a hard segment. The degree of swelling in the hydrogels could be controlled by varying the amount of crosslinking agent, namely 1,2,6-hexanetriol. Structural characterization of the hydrogels was performed using solid-state C-13 NMR and Fourier transform infrared spectroscopy. Wide-angle X-ray diffraction studies revealed the existence of crystalline domains of PEG and small-angle X-ray scattering studies showed the presence of lamellar microstructures. For generating a porous structure in the hydrogels, cryogenic treatment with lyophilization was used. Scanning electron microscopy and three-dimensional micro-computed tomography imaging of the hydrogels indicated the presence of interconnected pores. The mechanical strength of the hydrogels and xerogels was measured using dynamic mechanical analysis. The observed dynamic storage moduli (E) for the equilibrium swollen and dry gels were found to be 0.15 and 4.2 MPa, respectively. Interestingly, the porous PEG-PU xerogel also showed E of 5.6 MPa indicating a similar mechanical strength upon incorporating porosity into the gel matrix. Finally, preliminary cytocompatibility studies showed the ability of cells to proliferate in the hydrogels. These gels show promise for applications as scaffolds and implants in tissue engineering. (c) 2014 Society of Chemical Industry
Keywords: hydrogels; permeability; poly(ethylene glycol); polyurethane; porosity

Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.

Rapid characterization of oxidative deterioration in edible oil by optical photospectrometry - More, Pravin S.; Shelke, Anil V.; Late, Dattatray J. (Journal of Food and Dairy Technology, 2015)
This research work aimed to investigate the kinetic reaction of reused cooking oil and find the optimum conditions of its process. The feedstock was collected from the commercially available sunflower oil. Our investigation shows that the kinetic reaction of reused sunflower oil (auto-oxidation) obtained in terms of variation of absorption coefficient of unexposed sunflower as 0.05 while the exposed sunflower had 0.075. The optimum condition from optical absorption spectroscopy investigations were obtained as 0.267 for unexposed sunflower oil and 0.194 for exposed sunflower oil at room temperature. Furthermore, our FTIR spectroscopic results obtained are accurate and precise enough for such detection such as free fatty acid (FFA ~ 26%), acid ~ 53% and saponification ~ 192% get reduce in exposed oil was investigated.

Rational drug design, synthesis and biological evaluation of dihydrofolate reductase inhibitors as antituberculosis agents - Tawari, Nilesh R.; Bag, Seema; Raju, Archana; Lele, Arundhati C.; Bairwa, Ranjeet; Ray, Mukti Kanta; Rajan, M. G. R.; Nawale, Laxman U.; Sarkar, Dhiman; Degani, Mariam S. (Future Medicinal Chemistry, 2015)
Background: A series of 2,4-diamino-s-triazines was designed, with potential for activity against Mycobacterium tuberculosis (Mtb) dihydrofolate reductase enzyme, on the basis of virtual screening results and structure-based drug design. Results: The compounds were evaluated against Mtb (H(37)Rv) and their cytotoxicity was assessed using VERO cell lines. Of particular note, two compounds were found to have the most promising antituberculosis activity (6b minimum inhibitory concentration: 1.76 mu M and 6i minimum inhibitory concentration: 1.57 mu M) along with low cytotoxicity (CC50 : > 300 mu M). The enzyme assay results of these two indicated significant inhibition of Mtb dihydrofolate reductase along with selectivity. Selected derivatives were tested against dormant tubercle bacilli in vivo and ex vivo indicating potential inhibition. Conclusion: This study provides promising antituberculosis dihydrofolate reductase inhibitors that can act as potential leads for further development.

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR

Recent developments in 2D layered inorganic nanomaterials for sensing - Kannan, Padmanathan Karthick; Late, Dattatray J.; Morgan, Hywel; Rout, Chandra Sekhar (Nanoscale, 2015)
Two dimensional layered inorganic nanomaterials (2D-LINs) have recently attracted huge interest because of their unique thickness dependent physical and chemical properties and potential technological applications. The properties of these layered materials can be tuned via both physical and chemical processes. Some 2D layered inorganic nanomaterials like MoS2, WS2 and SnS2 have been recently developed and employed in various applications, including new sensors because of their layer-dependent electrical properties. This article presents a comprehensive overview of recent developments in the application of 2D layered inorganic nanomaterials as sensors. Some of the salient features of 2D materials for different sensing applications are discussed, including gas sensing, electrochemical sensing, SERS and biosensing, SERS sensing and photodetection. The working principles of the sensors are also discussed together with examples.

Reduction of graphene oxide by 100 MeV Au ion irradiation and its application as H2O2 sensor - Hareesh, K.; Joshi, R. P.; Shateesh, B.; Asokan, K.; Kanjilal, D.; Late, Dattatray J.; Dahiwale, S. S.; Bhoraskar, Vasant N.; Haram, Santosh K.; Dhole, Sanjay D. (Journal of Physics D-Applied Physics, 2015)
Graphene oxide (GO) synthesized from a modified Hummer's method was reduced (referred, rGO) by using 100 MeV Au ion species and its response to the sense H2O2 was investigated. The changes in the atomic composition and structural properties of rGO after irradiation were studied using x-ray diffraction, Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy. These results suggested that the removal of the oxygen-containing functional groups and the improvement of the electrochemical performance of reduced graphene oxide (rGO) after ion irradiation. Raman spectroscopic results revealed the increase in the disorder parameter (I-D/I-G) after Au ion irradiation and also the formation of a large number of small sp(2) domains due to the electronic energy loss of ion beam. The resultant rGO was investigated for H2O2 sensing using electrochemical techniques and it showed a good response.
Keywords: electronic energy loss; GO; ion beam irradiation; reduction

Renewable fuels from biomass-derived compounds: Ru-containing hydrotalcites as catalysts for conversion of HMF to 2,5-dimethylfuran - Nagpure, Atul S.; Venugopal, Ashok Kumar; Lucas, Nishita; Manikandan, Marimuthu; Thirumalaiswamy, Raja; Chilukuri, Satyanarayana V. (Catalysis Science & Technology, 2015)
Production of transportation fuels from renewable biomass is hugely important considering the current ecological concerns over CO2 built up in the atmosphere. Ruthenium-containing hydrotalcite (HT) catalysts were applied for the selective hydrogenolysis of biomass-derived 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF). Structural and morphological features of the catalysts were examined using various physico-chemical characterization techniques. The influence of various reaction parameters, such as reaction temperature, solvent, Ru content of the catalyst, etc., was investigated with respect to HMF conversion and DMF yield. The study clearly shows that well-dispersed Ru nanoparticles are highly active and selective in the conversion of HMF to DMF. A catalyst containing only 0.56 wt% Ru converted 100 mol% HMF to yield 58 mol% DMF. This catalyst was found to be recyclable as the activity was retained even after five cycles of reaction. 2-Propanol was found to be a good solvent as it helped to improve DMF yield through transfer hydrogenation. Based on the results of the investigations, a reaction pathway for the conversion of HMF to DMF was proposed for the present Ru-based catalyst system.

Reversed reactivity of anilines with alkynes in the rhodium-catalysed C-H activation/carbonylation tandem - Midya, Siba Prasad; Sahoo, Manoj Kumar; Landge, Vinod Gokulkrishna; Rajamohanan, P. R.; Balaraman, Ekambaram (Nature Communications, 2015)
Development of multicatalytic approach consisting of two or more mechanistically distinct catalytic steps using a single-site catalyst for rapid and straightforward access of structurally complex molecules under eco-benign conditions has significance in contemporary science. We have developed herein a rhodium-catalysed C-H activation strategy which uses an unprotected anilines and an electron-deficient alkynes to C-C bonded products as a potential intermediate in contrast to the archetypical C-N bonded products with high levels of regioselectivity. This is followed by carbonylation of C-H bond activated intermediate and subsequent annulation into quinolines has been described. This rhodium-catalysed auto-tandem reaction operates under mild, environmentally benign conditions using water as the solvent and CO surrogates as the carbonyl source with the concomitant generation of hydrogen gas. The strategy may facilitate the development of new synthetic protocols for the efficient and sustainable production of chemicals in an atom-economic way from simple, abundant starting materials.

Review of the hydrate based gas separation (HBGS) process for carbon dioxide pre-combustion capture - Babu, Ponnivalavan; Linga, Praveen; Kumar, Rajnish; Englezos, Peter (Energy, 2015)
In this work, a systematic review of the literature work done so far on the use of hydrate crystallization as a basis to develop data for the hydrate based gas separation (HBGS) process for the capture of CO2 from fuel gas mixtures is presented. Such a gas mixture may arise in integrated gasification combined cycle (IGCC) power plants. A thorough assessment of the thermodynamic, kinetic factors and economic aspects of the HBGS process and critical comments are presented. Compared with competing technologies, high CO2 capacity and the use of water as a solvent are key advantages for the HBGS process for CO2 capture. Furthermore, in this review, a snapshot of the current state-of-the-art is presented and further research and development opportunities and pathways for commercializing the HBGS process for pre-combustion capture of CO2 from IGCC power plants are discussed. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; IGCC plants; Pre-combustion capture

Short enantioselective synthesis of ephedrine, amphetamine and their analogues via two stereocentered Co(III)-catalyzed hydrolytic kinetic resolution of racemic syn-benzyloxy epoxide - Lalwani, Komal G.; Sudalai, Arumugam (Tetrahedron Letters, 2015)
An efficient route for the synthesis of 6 drugs belonging to phenethylamine and amphetamine classes in excellent overall yields and high optical purity has been described. The strategy involves introduction of stereogenic centers by means of two-stereocentered Co(III)-catalyzed hydrolytic kinetic resolution (HKR) of racemic syn-benzyloxy epoxide followed by Pd-catalyzed regioselective cationic hydrogenation of amino alcohols as the key reactions. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Amphetamine; Cationic hydrogenation; Hydrolytic kinetic resolution; Phenethylamine; Stereogenic centers

Single-layer graphene doping through molecular interaction: field-effect transistor and atomic force microscopy investigations - Late, Dattatray J. (Advanced Device Materials, 2015)
The single-layer graphene has attracted considerable attention for the promising applications in new generation nanoelectronics and optoelectronics devices because of the high deal carrier mobility. Present investigations deal with the effect of chemical/molecular doping with varying the concentration of strong electron acceptor molecule such as tetracyanoethylene (TCNE) on transfer characteristics of single-layer graphene transistor. The Dirac point shift toward the positive gate voltage as a function of increasing concentration of TCNE molecules clearly indicates that the graphene is P-type doped. Our results indicate that the fermi energy level can be controlled by the amount of molecular doping in order to obtain graphene transistors with tunable Dirac points, which can be easily configured into functional nanoelectronic devices.

Spectral analysis of the emission current noise exhibited by few layer WS2 nanosheets emitter - Suryawanshi, Sachin R.; Kolhe, Pankaj S.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Ultramicroscopy, 2015)
Spectral analysis of the field emission (FE) current fluctuations has been carried out at the base pressure similar to 1 x 10(-8) mbar. The emission current stability investigated at preset value of 2 mu A is characterized by `step like fluctuation. The spectral analysis performed on a FFT (Fast Fourier Transform) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha as similar to 1.05. The estimated value of alpha implies that the current fluctuations are mainly due the various processes occurring on atomic scale like adsorption, migration, and/or desorption of the residual gas species on the emitter surface. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Current fluctuations; field emission; Noise; WS2 nanosheets

Stable field emission from layered MoS2 nanosheets in high vacuum and observation of 1/f noise - Kashid, Ranjit V.; Joag, Pracheetee D.; Thripuranthaka, M.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Nanomaterials and Nanotechnology, 2015)
Field emission and current noise of hydrothermally synthesized MoS2 nanosheets are investigated in ultra-high-vacuum and industrially suited high-vacuum conditions. The study reveals that the emission turn-on field is pressure dependent. Moreover, the MoS2 nanosheets exhibit more stable field-electron emission in high-vacuum than in ultra-high-vacuum conditions. The investigations on field-emission current fluctuations show features of 1/f-type noise in ultra-high-vacuum and high-vacuum conditions, attributed to adsorption and desorption processes. The post-field-emission results indicate the MoS2 nanosheets are a robust field emitter in high-vacuum conditions.
Keywords: Electron emission; layered materials; MoS2; Noise measurement; Raman spectroscopy

Star telechelic poly(L-lactide) ionomers - Kulkarni, Amruta; Lele, Ashish K.; Sivaram, Swaminathan; Rajamohanan, P. R.; Velankar, Sachin; Chatterji, Apratim (Macromolecules, 2015)
Poly(L-lactide) (PLA), a biodegradable and biorenewable polymer, has many excellent properties that are equivalent to those of petroleum-derived plastics such as polystyrene, aromatic polyesters, etc. However, a major disadvantage of PLA which limits its processability is its poor melt elasticity. In this work we explore the possibility of improving the viscoelastic properties of PLA melt by incorporating ionic groups on the polymer. Specifically, we demonstrate the synthesis of star telechelic PLA anionomers by a three-step procedure involving synthesis of Star PIA, converting the hydroxyl end groups into carboxylic acid end groups, and finally converting these into ionic groups. Rheology data showed a dramatic increase in the elasticity of the star telechelic ionomer melts relative to the Star PLA melts. The viscoelasticity of star telechelic ionomers melts could be modulated by varying the number of ionic groups per molecule.

Structural features of diverse Pin-II proteinase inhibitor genes from capsicum annuum - Mahajan, Neha S.; Dewangan, Veena; Lomate, Purushottam R.; Joshi, Rakesh S.; Mishra, Manasi; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
The proteinase inhibitor (PI) genes from Capsicum annuum were characterized with respect to their UTR, introns and promoter elements. The occurrence of PIs with circularly permuted domain organization was evident. Several potato inhibitor II (Pin-II) type proteinase inhibitor (PI) genes have been analyzed from Capsicum annuum (L.) with respect to their differential expression during plant defense response. However, complete gene characterization of any of these C. annuum PIs (CanPIs) has not been carried out so far. Complete gene architectures of a previously identified CanPI-7 (Beads-on-string, Type A) and a member of newly isolated Bracelet type B, CanPI-69 are reported in this study. The 5' UTR (untranslated region), 3'UTR, and intronic sequences of both the CanPI genes were obtained. The genomic sequence of CanPI-7 exhibited, exon 1 (49 base pair, bp) and exon 2 (740 bp) interrupted by a 294-bp long type I intron. We noted the occurrence of three multi-domain PIs (CanPI-69, 70, 71) with circularly permuted domain organization. CanPI-69 was found to possess exon 1 (49 bp), exon 2 (551 bp) and a 584-bp long type I intron. The upstream sequence analysis of CanPI-7 and CanPI-69 predicted various transcription factor-binding sites including TATA and CAAT boxes, hormone-responsive elements (ABRELATERD1, DOFCOREZM, ERELEE4), and a defense-responsive element (WRKY71OS). Binding of transcription factors such as zinc finger motif MADS-box and MYB to the promoter regions was confirmed using electrophoretic mobility shift assay followed by mass spectrometric identification. The 3' UTR analysis for 25 CanPI genes revealed unique/distinct 3' UTR sequence for each gene. Structures of three domain CanPIs of type A and B were predicted and further analyzed for their attributes. This investigation of CanPI gene architecture will enable the better understanding of the genetic elements present in CanPIs.
Keywords: CanPI; Capsicum; Gene architecture; Promoter; Proteinase inhibitor

Synthesis and antifungal potential of 1,2,3-triazole and 1,2,4-triazole thiol substituted strobilurin derivatives - Chaudhary, Preeti M.; Tupe, Santosh G.; Jorwekar, Shweta U.; Sant, Duhita G.; Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Deshpande, Mukund V. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
beta-Methoxyacrylate group is an important pharmacophore of commercially used strobilurin fungicides. In the present study, a total of seventeen 1,2,4-triazole thiols 8a-h and 1,2,3-triazole substituted 10a-i strobilurin derivatives have been synthesized. 1,2,4-Triazole thiol substituted strobilurin derivatives 8a-h have been found to inhibit the growth of plant pathogens such as Fusarium oxysporum, Magnaporthe grisea, Drechslera oryzae and human pathogens Aspergillus fumigatus and different strains of Cryptococcus neoformans, with MIC in the range of 16-256 mu g/mL. In case of Candida albicans tested strain, the MIC is > 256 mu g/mL. p-Chlorophenyl substituted 1,2,4-triazole thiol strobiulrin derivative 8e is the most potent inhibitor with MIC of 16-64 mu g/mL against most of the tested pathogens. Antifungal action of the compounds is due to inhibition of mitochondrial respiration. In the resazurin reduction assay, EC50 for inhibition of RZ reduction in D. oryzae by azoxystrobin and 8e are 3.42 +/- 0.03 mu g/mL and 3.63 +/- 0.21 mu g/mL, respectively; while in case of C. neoformans, EC50,, of azoxystrobin and 8e are between 0.65-0.85 mu g/mL. In a non-pathogenic model Benjaminiella poitrasii, though the MIC for all the synthesized compounds 8a-h and 10a-i are > 256 mu g/ml, yeast to hypha transition is inhibited in the range of 21-75% at 4 mu g/mL concentration while EC50 for inhibition of RZ reduction by azoxystrobin and 8e are 31.5 +/- 0.4 mu g/mL and 17.95 +/- 0.7 mu g/mL, respectively. The 50% germ tube formation inhibition in case of C. albicans is observed at 108.49 mu g/mL. 1,2,4-Triazole thiol substituted strobilurin derivatives hold promise for the control of pathogenic fungi in agriculture and health care.
Keywords: 1; 2; 3-triazole strobilurin; 4-triazole thiol strobilurin; antifungal; Strobilurin; Y-H transition inhibition

Synthesis of GdB6 nanostructures using nanosecond (Nd: YAG) laser: field emission investigation - Suryawanshi, S. R.; Late, Dattatray J.; More, Mahendra A.; Singh, Anil K.; Sinha, S. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We herein report field emission characteristics of GdB6 nanostructures grown directly on a pellet via laser processing (laser fluence similar to 6 J/cm(2)). The laser processed GdB6 pellet was characterized by X-ray diffraction, which revealed no change in phase upon laser processing. The values of the turn-on field required to draw emission current density of 1 mu A/cm(2) is found to be similar to 2.95 V/mu m, for the laser processed GdB6 emitter. Furthermore, the Fowler-Nordheim (F-N) plot exhibits non-linear behavior over the entire range of applied field and the field enhancement factor (beta) calculated from slope of the F-N plot (low field region) was found to be similar to 543. The emission current stability over a period of 3h was observed to be fairly good. The observed results demonstrate that laser processing can be efficiently used to make GdB6 nanostructure emitter having potential for practical applications.

Temperature dependent phonon shifts in few-layer black phosphorus - Late, Dattatray J. (ACS Applied Materials & Interfaces, 2015)
Atomically thin two-dimensional (2D) sheets of black phosphorus have attracted much attention due to their potential for future nanoelectronic and photonics device applications. Present investigations deal with the temperature dependent phonon shifts in a few-layer black phosphorus nanosheet sample prepared using micromechanical exfoliation on a 300 nm SiO2/Si substrate. The temperature dependent Raman spectroscopy experiments were carried out on a few-layer black phosphorus sample, which depicts softening of Ag-1 B-2g, and A(g)(2) modes as temperature increases from 77 to 673 K. The calculated temperature coefficients for Ag-1, B-2g, and A(g)(2) modes of the few-layer black phosphorus nanosheet sample were observed to be -0.01, -0.013, and -0.014 cm(-1) K-1, respectively. The temperature dependent softening modes of black phosphorus results were explained on the basis of a double resonance process which is more active in an atomically thin sample. This process can also be fundamentally pertinent in other promising and emerging 2D ultrathin layer and heterostructured materials.
Keywords: black phosphorus; layered materials; phonon vibrations; Raman spectroscopy; thermal effect

Temperature-dependent raman spectroscopy of titanium trisulfide (TiS3) nanoribbons and nanosheets - Pawbake, Amit S.; Island, Joshua O.; Flores, Eduardo; Ramon Ares, Jose; Sanchez, Carlos; Ferrer, Isabel J.; Jadkar, Sandesh R.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2015)
Titanium trisulfide (TiS3) has recently attracted the interest of the 2D community because it presents a direct bandgap of similar to 1.0 eV, shows remarkable photoresponse, and has a predicted carrier mobility up to 10000 cm(2) V-1 s(-1). However, a study of the vibrational properties of TiS3, relevant to understanding the electron-phonon interaction that can be the main mechanism limiting the charge carrier mobility, is still lacking. In this work, we take the first steps to study the vibrational properties of TiS3 through temperature-dependent Raman spectroscopy measurements of TiS3 nanoribbons and nanosheets. Our investigation shows that all the Raman modes linearly soften (red shift) as the temperature increases from 88 to 570 K due to anharmonic vibrations of the lattice, which also includes contributions from the lattice thermal expansion. This softening with the temperature of the TiS3 modes is more pronounced than that observed in other 2D semiconductors, such as MoS2, MoSe2, WSe2, and black phosphorus (BP). This marked temperature dependence of the Raman spectra could be exploited to determine the temperature of TiS3 nanodevices by using Raman spectroscopy as a noninvasive and local thermal probe. Interestingly, the TiS3 nanosheets show a stronger temperature dependence of the Raman modes than the nanoribbons, which we attribute to lower interlayer coupling in the nanosheets.
Keywords: 2D semiconductors; layered materials; Raman spectroscopy; thermal effect; TiS3 nanoribbons; TiS3 nanosheets

Transition metal di-chalcogenides and their nanocomposite prospective field emitters - Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J. (2015 28TH International Vacuum Nanoelectronics Conference (IVNC), 2015)
Layered structured transition metal di-chalcogenides has attracted researchers as a substitute of graphene and its forms for various applications. In an attempt to explore field emission properties of these graphene analogues, synthesis and field emission behaviour of a few layered transition metal di-chalcogenides (TMDs) VS2, MoS2, MoO3 have been investigated at a base pressure of 1x 10(-8) mbar. Furthermore, to improve the field emission properties, composites with RGO and respective oxides were synthesized and compared with the pristine ones. The TMDs and their composites is synthesized employing hydrothermal synthesis route. The preliminary results show that these TMD's and their composites, when synthesized in a controlled manner, can serve as potential field emitters for future field emission based devices.

Transition-metal-catalyzed hydrogen-transfer annulations: access to heterocyclic scaffolds - Nandakumar, Avanashiappan; Midya, Siba Prasad; Landge, Vinod Gokulkrishna; Balaraman, Ekambaram (Angewandte Chemie-International Edition, 2015)
The ability of hydrogen-transfer transition-metal catalysts, which enable increasingly rapid access to important structural scaffolds from simple starting materials, has led to a plethora of research efforts on the construction of heterocyclic scaffolds. Transition-metal-catalyzed hydrogen-transfer annulations are environmentally benign and highly atom-economical as they release of water and hydrogen as by-product and utilize renewable feedstock alcohols as starting materials. Recent advances in this field with respect to the annulations of alcohols with various nucleophilic partners, thus leading to the formation of heterocyclic scaffolds, are highlighted herein.

Ultra-thin V2O5 nanosheet based humidity sensor, photodetector and its enhanced field emission properties - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
We report the synthesis of V2O5 nanosheets by a simple hydrothermal method. The as synthesized V2O5 nanosheets were characterized by Raman spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM) and UV-Vis spectroscopy. The humidity sensing behaviors were investigated in the range of 11-97% relative humidity (RH) at room temperature. The maximum sensitivity of 45.3%, response time of similar to 4 min and recovery time of similar to 5 min were observed for the V2O5 nanosheet based sensor. We also demonstrated the V2O5 nanosheets as an ultra-violet photodetector with a sensing response time of similar to 65 s and recovery time of similar to 75 s with a maximum photoresponsivity of similar to 6.2%. Further, we have also carried out field emission (FE) investigations of V2O5 nanosheets under a planar ``Diode'' assembly in an ultrahigh vacuum (UHV) chamber at a base pressure of similar to 1 x 10(-8) mbar. The turn on fields required to draw field emission current densities of 1 mu A cm(-2) and 10 mu A cm(-2) are found to be 1.15 V mu m(-1) and 1.72 V mu m(-1), respectively. We achieved a maximum field emission current density of 1.532 mA cm(-2) at an applied electric field of 3.2 V mu m(-1). The field enhancement factors calculated from the slope of the Fowler-Nordheim (F-N) plot are found to be 8530 and 3530 at low field and high field regions, respectively. Our results open up several avenues towards the successful utilization of V2O5 nanosheets and other metal oxide nanosheets for various nanoelectronics device applications including sensors, photodetector and flat panel displays.

Vapour-liquid-solid growth of one-dimensional In2Se3 nanostructures and their promising field emission behaviour - Suryawanshi, Sachin R.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
Single crystalline ultra long In2Se3 nanowires have been grown by employing a single step facile thermal evaporation route under optimized conditions on Au/Si wafers, and morphology dependent field emission investigations on the In2Se3 nanostructure at the base pressure -1 x 10(-8) mbar are explored. In addition, structural and morphological analysis of as-synthesized In2Se3 nanostructures has been carried out using XRD, SEM and TEM. A plausible explanation of the vapor-solid-liquid (VLS) growth mechanism based on the experimental results and reported literature has been presented. Furthermore, field emission measurements demonstrate remarkably enhanced emission behaviour, which is explained on the basis of the field enhancement factor and aspect ratio of the nanostructures. The synthesized In25e3 nanowire emitter delivers a very high current density of -1.2 mA cm(-2) at an applied electric field of -6.33 cm(-1). The present results demonstrate In2Se3 as an important candidate for potential applications in nano/micro-electronic devices.

Vitellibacter nionensis sp nov., isolated from a shallow water hydrothermal vent - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Thi-Nhan Khieu; Chu Ky Son; Li, Wen-Jun; Colaco, Ana (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel, Gram-stain-negative, non-motile, rod-shaped yellow bacterium, designated VBW088(T) was isolated from a shallow water hydrothermal vent in Espalamaca in the Azores. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain VBW088(T) clustered with three type strains of species of the genus Vitellibacter and exhibited a sequence similarity of 97.3% with Vitellibacter soesokkakensis RSSK-12(T). However, strain VBW088(T) and V. soesokkakensis RSSK-12(T) exhibited low DNA-DNA relatedness (12.7 +/- 3.5 %). Strain VBW088(T) was positive for catalase and oxidase. Growth occurred at 10-37 degrees C, with the optimum at 80 degrees C, and at pH 6.0-8.0 (optimum pH 6.0) and in up to 5% (w/v) NaCl with optimum growth at 1-2% (w/v) NaCl. The major fatty acids (>10%) were iso-C-15:0 (33.5%) and iso-C-17:0 3-OH (32.0%). The polar lipids detected in strain VBW088(T) consisted of phosphatidylethanolamine, one unidentified aminolipid and three unidentified phospholipids. The DNA G+C content of strain VBW088(T) was 36.7 mol%. On the basis of phylogenetic inference, DNA-DNA relatedness, chemotaxonomic analysis and physiological data, the isolate represents a novel species of the genus Vitellibacter, for which the name Vitellibacter nionensis sp. nov. is proposed, with the type strain as VBW088(T). (=KCTC 32420(T)=MCC 2354(T)).

Well-defined palladium(II) complexes for ligand enabled C(sp3)-alkynylation - Landge, Vinod Gokulkrishna; Sahoo, Manoj Kumar; Midya, Siba Prasad; Jaiswal, Garima; Balaraman, Ekambaram (Dalton Transactions, 2015)
The first example of ligand-enabled C(sp3)-alkynylation of 8-methylquinoline is reported. The reaction is catalysed by well-defined Pd(II) complexes. The present C(sp3)-alkynylation has a broad substrate scope as well as functional group tolerance and proceeds efficiently under mild conditions.

Actinorectispora indica gen. nov., sp nov isolated from soil, a member of the family pseudonocardiaceae - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Al Ruwaili, Jamal; Hozzein, Wael N.; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2016)
The taxonomic positions of three Gram-stain-positive, aerobic strains, designated YIM 75722, 75726 and 75728(T), and isolated from a soil sample collected from Kurnool of Andhra Pradesh province, India, were assessed using a polyphasic approach. Growth was observed at pH 7.0-10.0 (optimum pH 7.0), 15-28 degrees C (optimum 28 degrees C) and 0-8% (w/v) NaCl (grew without NaCl). Strains showed cylindrical spores with straight-chain morphology on aerial mycelium, but did not reveal sporangium-like structures or fragmentation of the substrate mycelium. Whole-cell hydrolysates of all strains contained galactose and ribose as the diagnostic sugars and meso-diaminopimelic acid as the diamino acid. The predominant menaquinone was MK-9(H-4); MK-9 (H-6) and MK-10 (H-4) were present in smaller amounts. The phospholipid pattern consisted mainly of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylcholine. The major fatty acids were i-C-15: 0, ai-C-15: 0, i-C-17 : 0 and ai-C-17 : 0. The genomic DNA G+C content was 68.0 mol%. Phylogenetic analysis, based on 16S rRNA gene sequences, revealed that strain YIM 75728(T) should be placed within the family Pseudonocardiaceae, in which the strain formed a distinct lineage. The combination of phylogenetic analysis, phenotypic characteristics and chemotaxonomic data support the conclusion that strain YIM 75728(T) represents a novel species of a novel genus of the family Pseudonocardiaceae for which the name Actinorectispora indica gen. nov., sp. nov., is proposed. Strain YIM 75728(T) (=DSM 45410(T)=CCTCC AA 209065(T)) is the type strain of Actinorectispora indica. Strain YIM 75728(T) was considered as the type strain over the other two strains based on the highest sequence read length of the strain.

Ammonium catalyzed cyclitive additions: evidence for a cation-pi interaction with alkynes - Nagy, Edith; St Germain, Elijah; Cosme, Patrick; Maity, Pradip K.; Terentis, Andrew C.; Lepore, Salvatore D. (Chemical Communications, 2016)
The addition of carbamate nitrogen to a non-conjugated carbon-carbon triple bond is catalyzed by an ammonium salt leading to a cyclic product. Studies in homogeneous systems suggest that the ammonium agent facilitates nitrogen-carbon bond formation through a cation-p interaction with the alkyne unit that, for the first time, is directly observed by Raman spectroscopy.

Architecture of 2D MoS2 nanosheets and 3D CdMoS4 marigold flowers: consequence of annealing on field emission performance - Kadam, Sunil R.; Suryawanshi, Sachin R.; Panmand, Rajendra P.; Mate, Vivek R.; More, Mahendra A.; Late, Dattatray J.; Kale, Bharat B. (Microporous and Mesoporous Materials, 2016)
Herein, we report the field electron emission investigations on template free solvothermally synthesized layered MoS2 nanosheets as well as novel phase of CdMoS4 nanoflowers at the base pressure of similar to 1 x 10(-8) mbar. The turn-on field, threshold field and maximum emission current densities for both MoS2 and CdMoS4 are strongly influenced by thermal annealing in inert atmosphere. The turn on field, required to draw emission current density of 1 mu A/cm(2) is found to be 5.8 and 3.2 V/mu m for pristine and annealed MoS2 at 400 degrees C. In case of as prepared and annealed CdMoS4 sample the turn on field values are found to be similar to 6.2 and 5.0 V/mu m, respectively. The emission current versus time (I-t) plot measured at the preset current values of similar to 1 mu A for pristine and annealed sample indicates stable operation of the emitter. The emission current fluctuations for annealed sample are observed to be less as compared with the pristine sample due to conditioning of the emitter, thereby showing highly stable nature of emitter. Thus, the present result demonstrates the potential of annealed MoS2 nanosheets and CdMoS4 nanoflowers as an emerging materials for micro/nanoelectronics and flat panel field emission display applications. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: field emission; MoS2 and CdMoS4; Nanoflowers; nanosheets

Atomically thin WS2 nanosheets based gas sensor - Late, D. J.; Kanawade, R. V.; Kannan, P. K.; Rout, C. S. (Sensor Letters, 2016)
We report here the UV light and NO2 gas sensing properties of atomically thin few-layered WS2 nanosheets synthesized by a simple hydrothermal method. For the UV sensor, the response time was observed to be <15 s whereas the recovery time was <56 s. The Few layered WS2 nanosheets sensor devices were also tested for different concentration of NO2 gas at room temperature and 100 °C. The response time was observed to be <60 s whereas recovery time was >10 min. Further, the response and recovery time can be shortened by UV illumination or by removing the absorbed gas by heating the device at higher temperature. Our results open up the new avenues for gas sensors based on two-dimensional inorganic layered materials.

Biosurfactant as a promoter of methane hydrate formation: thermodynamic and kinetic studies - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Balomajumder, Chandrajit; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Scientific Reports, 2016)
Natural gas hydrates (NGHs) are solid non-stoichiometric compounds often regarded as a next generation energy source. Successful commercialization of NGH is curtailed by lack of efficient and safe technology for generation, dissociation, storage and transportation. The present work studied the influence of environment compatible biosurfactant on gas hydrate formation. Biosurfactant was produced by Pseudomonas aeruginosa strain A11 and was characterized as rhamnolipids. Purified rhamnolipids reduced the surface tension of water from 72 mN/m to 36 mN/m with Critical Micelle Concentration (CMC) of 70 mg/l. Use of 1000 ppm rhamnolipids solution in C type silica gel bed system increased methane hydrate formation rate by 42.97% and reduced the induction time of hydrate formation by 22.63% as compared to water saturated C type silica gel. Presence of rhamnolipids also shifted methane hydrate formation temperature to higher values relative to the system without biosurfactant. Results from thermodynamic and kinetic studies suggest that rhamnolipids can be applied as environment friendly methane hydrate promoter.

Catalytic activity of bare and porous palladium nanostructures in the reduction of 4-nitrophenol - Kalekar, Ajit M.; Sharma, Kiran Kumar K.; Luwang, Meitram Niraj; Sharma, Geeta K. (RSC Advances, 2016)
The catalytic activity of bare and porous palladium nanostructures viz. palladium nanoballs (PdNBs) and palladium urchins (Pdurc) synthesized in surfactant based liquid crystalline mesophase have been investigated in the reduction of 4-nitrophenol. The loading of PdNBs and Pdurc nanocatalyst in the reaction are optimized to 1.57 x 10(-4) mol% and 1.57 x 10(-3) mol% respectively. The surface area normalized rate constant obtained at 303 K for PdNBs (0.74 +/- 0.03) s(-1) m(-2) L and Pdurc (0.41 +/- 0.05) s(-1) m(-2) L is the highest, considering the low palladium loading used in the reaction. The specific surface area determined for the PdNBs and Pdurc are 153 m(2) g(-1) and 27 m(2) g(-1) respectively. The high surface area of PdNBs nanostructure is consistent with the highest catalytic activity. The palladium nanostructure catalyzed reaction lacks induction time (t(0)), indicating the influence of porosity in the Langmuir-Hinshelwood mechanism. Besides, PdNBs and Pdurc exhibited thermal stability and structural integrity with good conversion of the substrate (>97%) even up to five consecutive reactions. The mechanistic insight of the bare and porous palladium nanostructures presented in this study is significant for the development of stable and efficient palladium metal based nanocatalyst.

Chromium free high temperature water-gas shift catalyst for the production of hydrogen from waste derived synthesis gas - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Jang, Won-Jun; Shim, Jae-Oh; Jeon, Kyung-Won; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Applied Catalysis A-General, 2016)
A comparative study between monometallic (Me-CeO2, Me =Zn, Cu, Fe and Co) and Ni-doped bimetallic (Me-Ni-CeO2) catalysts has been performed in the high temperature water-gas shift (HT-WGS) reaction using waste derived synthesis gas. Experimental results revealed that Me-Ni-CeO2 exhibited higher catalytic performance than simple Me-CeO2 catalysts. Within the Me-Ni-CeO2 series, Co-Ni-CeO2 exhibited excellent and stable catalytic performance (CO conversion > 90%) at a very high GHSV of 143,000 h(-1). The existence of high" concentration of Ce3+ ions and oxygen vacancies on the catalyst surface were responsible for the increased WGS activity of Co-Ni-CeO2. In addition, Co-Ni-CeO2 maintains a stable performance for 50 h. However, commercial Fe2O3-Cr2O3 catalyst showed a steep decline from their initial CO conversion values 15-10% within 5 h. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeO2; Co-Ni-CeO2; Lattice strain; oxygen vacancies; Water-gas shift

Classification and study of near-surface region of active material for gas detection using x-ray photoelectron spectroscopy - More, Pravin S.; Late, Dattatray J.; Kondawar, Subhash B. (Advanced Materials Letters, 2016)
We report investigations on resistive material SnO2: Cu (9 wt. %) evaluated and optimized for the application of gas sensor. SnO2: Cu has been thoroughly characterized by using X-ray photoelectron spectroscopy (XPS). The deconvolution of XPS spectra confirms the existing surface reactive species in the form of states of the metal orbital and the presence of multiple pathways for the detection of CO vis-à-vis sintering temperature effect. Enhanced CO pickup at the sintering temperature of 650 0C (wide range and low sensitivity) and 750 0C (short range and high sensitivity) has been observed. The CO sensing and XPS data correlates well along with the nonconventional use of variation in average XPS background intensity of general scan seems to be related to optimized sensitivity conditions of various gases. Copyright © 2016 VBRI Press.

Cobalt-catalyzed bis-alkynylation of amides via double C–H bond activation - Landge, Vinod Gokulkrishna; Jaiswal, Garima; Balaraman, Ekambaram (Organic Letters, 2016)
The first example of cobalt-catalyzed selective bis-alkynylation of amides via double C–H bond activation with the directing assistance of a removable bidentate auxiliary is reported. The developed alkynylation strategy is simple, efficient, and tolerant of various functional groups including ether, amine, halides, and heterocyclic motifs. The reaction can be scaled up under mild conditions.

Concise enantioselective synthesis of (+)-L-733,060 and (+)-T-2328 via sequential proline catalysis - Lalwani, Komal G.; Sudalai, Arumugam (Synlett, 2016)
A new, sequential proline-catalyzed approach to the synthesis of (+)-L-733,060 and (+)-T-2328 in high optical purity (93% ee) is described starting from phenyl N-Boc imine. The strategy involves proline-catalyzed Mannich reaction of an arylimine with acetaldehyde followed by -aminoxylation/Wittig olefination in a sequential fashion as the key steps.
Keywords: Aminoxylation; imine; Mannich reaction; olefination; sequential

Correlating the role of hydrophilic/hydrophobic nature of Rh(I) and Ru(II) supported organosilica/silica catalysts in organotransformation reactions - Lazar, Anish; George, Shoy C.; Jithesh, P. R.; Vinod, C. P.; Singh, A. P. (Applied Catalysis A-General, 2016)
Highly reactive and hydrophobic triphenyl phosphine based rhodium(I) and ruthenium(II) organometallic complexes over benzene containing periodic mesoporous organosilica (PMOB) have been synthesized. This has been achieved by the immobilization of neat metal complexes like RhCl(PPh3)(3) [Wilkinson catalyst], RuHCl(CO)(PPh3)(3) and RuCl2(PPh3)(3) over aminofunctionalized PMOB to get RhCl(PPh3)(2)-PrNH2PMOB, RuHCl(CO)(PPh3)(2)-PrNH2PMOB and RuCl2(PPh3)(3)-PrNH2PMOB, respectively. The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption analyses, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, SEM, TEM and contact angle measurements. The XRD and N-2 sorption analyses showed excellent textural properties with ordered mesoporous channel structure of all synthesized catalysts. The organic moieties anchored in PMOB were confirmed by C-13 CPMAS NMR and Fr-IR spectroscopy with Si-29 CPMAS NMR spectroscopy providing the information about the degree of functionalization of surface silanol groups with organic moiety. The Rh(I) and Ru(II) complexes supported on MCM-41/SBA-15/PMOE (ethane-PMO) were synthesized, and their catalytic activities in hydrogenation and sulfoxidation reactions were compared with Rh(I) and Ru(II) complexes supported on PMOB. The results show that PMOB based catalysts exhibit higher activities and selectivities than MCM-41/SBA-15/PMOB supported catalysts, neat homogeneous complexes and without catalyst. The better catalytic performance of PMOB based catalyst is attributed to the hydrophobic nature and high surface area of the PMOB support. The recycling studies of anchored catalysts show no major deactivation of the catalyst. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Hydrogenation and sulfoxidation; Hydrophobic; Periodic mesoporous organosilica

Crystallization kinetics for carbon dioxide gas hydrate in fixed bed and stirred tank reactor - Kumar, Asheesh; Khatri, Dishant; Lee, Ju Dong; Kumar, Rajnish (Korean Journal of Chemical Engineering, 2016)
The phase change from germ nuclei to growth nuclei and subsequent volume transformation in a crystallization process was modeled by Avrami equations. The phase change during the hydrate formation was fitted with the classical Avrami model by utilizing gas uptake data. The idea is to understand the difference in growth behavior of hydrate crystals when in small pores compared to a stirred tank reactor which does not pose any physical restrictions to hydrate growth. The parameters n and k of the Avrami equation were determined explicitly for CO2 hydrate formation.
Keywords: Avrami Equation; CO2 Capture & Sequestration; Fixed Bed; Gas hydrates; kinetics

Design and fabrication of mechanically strong nano-matrices of linseed oil based polyesteramide blends - Killi, Naresh; Dhakare, Runali Arjun; Singam, Amarnath; Lokanadham, Metta; Chitikeshi, Harshavardhan; Gundloori, Rathna Venkata Naga (Medchemcomm, 2016)
New nanomaterials of bio-origin with improved mechanical properties are in demand for biomedical application. Therefore, we propose to design and fabricate bioactive nano-matrices with good mechanical strength using polyesteramides derived from linseed oil. Polyesteramide was synthesized from linseed oil and blended with poly(L-lactide) and human serum albumin to enhance the mechanical strength, biodegradation, biocompatibility and hydrophilicity. The various blend solutions with and without drugs (triclosan and metronidazole) were electrospun into non-woven nano-matrices. The morphology of the nano-matrices represented smooth and fine nanofibers with the diameter ranging from 300 to 400 nm. Drug binding efficiency, cytotoxicity, hydrophilicity, thermal and mechanical studies indicated their suitability as biomaterials. To demonstrate their utility, the drug release kinetics and antibacterial properties were evaluated. The metronidazole loaded nano-matrices showed drug release up to 8 h, beyond which no release was observed until 72 h. Antibacterial studies were done using the drugs triclosan and metronidazole. The antibacterial activity of the drug loaded nanofiber mats increased with the increase in drug concentration. The uniqueness of the developed nano-matrices of polyesteramide blends is that their mechanical strength is 3-fold higher than that of the nano-matrices of poly(L-lactide), which is one of the essential features of these nano-matrices to be used as a biomaterial for biomedical applications.

Editorial: actinobacteria in special and extreme habitats: diversity, function roles, and environmental adaptations - Qin, Sheng; Li, Wen-Jun; Dastager, Syed Gulam; Hozzein, Wael N. (Frontiers in Microbiology, 2016)
Keywords: actinobacteria; activities; diversity; environmental adaptation; omics technologies; special and extreme environments

Effect of additives on formation and decomposition kinetics of methane clathrate hydrates: application in energy storage and transportation - Kumar, Asheesh; Kushwaha, Omkar Singh; Rangsunvigit, Pramoch; Linga, Praveen; Kumar, Rajnish (Canadian Journal of Chemical Engineering, 2016)
Methane gas storage and transportation via clathrate hydrates is proposed to be a potential solution for large-scale energy storage. In this work, we study the formation and decomposition kinetics of methane hydrates (MH) in a laboratory-scale unstirred crystallizer. The present investigation demonstrates comparative studies of hydrate formation and dissociation kinetics in the presence of tetrahydrofuran (55.6 and 27.8mmol/mol, 5.56 and 2.78mol% THF) and sodium dodecyl sulphate (1mg/g, 0.1wt% SDS). Moreover, the storage capacity and hydrate formation kinetics in both the systems are discussed. In a recent work, enhanced methane hydrate growth in the presence of THF at close to atmospheric conditions was demonstrated. The emphasis of the current work is to study the stability of hydrates to understand dissociation kinetics by measuring the rate of hydrate decomposition at different temperatures. Hydrate stability measurements were performed at -8, -3, 2, 10, and 20 degrees C to study the decomposition rates of MH and self-preservation in presence of the two additives THF and SDS.

Effect of number of branches on the performance of fractal impeller in a stirred tank: mixing and hydrodynamics - Mule, Gunwant M.; Lohia, Rajat; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2016)
Number of blades of an impeller, impeller design and its positioning in a stirred tank is known to affect the mixing in a stirred tank reactor. The extent of non-uniformity in mixing from conventional impellers can be reduced significantly using a space-filling impeller like a fractal impeller. In this work, we report the effect of number of branches (and hence the number of blades) of fractal impeller on power consumption, mixing and hydrodynamics. Velocity measurements were carried out using ultrasonic velocity profiler (UVP). Measurements showed that the performance of fractal impeller with different configuration is equivalent, however, better than standard impellers in terms of mixing achieved per unit power consumption. No significant difference was observed in radial and axial mean velocity profiles for three different configurations. However, the tangential velocity was found higher for four branches than two and three branches FL Two distinct circulation loops were observed in upper as well as lower half of the vessel in r-z plane. Strong tangential flow throughout the baffled vessel helps to achieve good mixing even at low rotational speeds. (C) 2016 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Fractal impeller; Number of branches; UVP; Tangential velocity; Mixing

Effect of plasma treatment on multilayer graphene: X-ray photoelectron spectroscopy, surface morphology investigations and work function measurements - Patil, Urmila V.; Pawbake, Amit S.; Machuno, Luis G. B.; Gelamo, Rogerio V.; Jadkar, Sandesh R.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report here the effect of plasma treatment on multilayer graphene samples as determined by X-ray photoelectron spectroscopy and surface morphology studies with atomic force microscopy, scanning electron microscopy and transmission electron microscopy. The plasma treatment was modified to introduce controlled levels of defects and functionalities to the graphene samples to give tunable properties. The elemental composition and structure were investigated by XPS and micro Raman spectroscopy. The XPS study showed that there was a slight variation in the sp(2)/sp(3) hybridization ratio between the plasma-treated samples and the pristine sample. Kelvin probe measurements were carried out on all the multilayer graphene samples and indicated a slight variation in the work function of the graphene samples after plasma treatment.

Effect of plug temperature on the strain and thickness distribution ofcomponents made by plug assist thermoforming - Marathe, D.; Rokade, D.; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Gupta, S.; Kulkarni, S.; Juvekar, Vinay A.; Lele, Ashish K. (International Polymer Processing, 2016)
Plug temperature is a key parameter affecting the thickness distribution of thermoplastic components made by plug assist thermoforming. For a specified pair of plug and plastic sheet, the variation in plug temperature can alter the coefficient of friction (COF) between the pair. We show here how the temperature dependence of COF influences the nature and extent of biaxial stretching of the sheet and consequently the thickness distribution of the thermoformed component. In the present study, high impact polystyrene (HIPS) sheets were thermoformed into axisymmetric cups using a plug-assist process in which the aluminum plug temperature (T-plug) was varied from ambient to above the glass transition temperature of HIPS (similar to 100 degrees C). Biaxial strain maps on the surfaces of the formed cups were measured and quantified using Grid Strain Analysis (GSA). Thickness distributions of the cups were also measured. Temperature dependent COF between HIPS and aluminum was determined independently using a rotational rheometer. The measured COF was low for T < 100 degrees C, whereas it increased appreciably at and above 100 degrees C. We conclude that when T-plug < 100 degrees C the HIPS sheet slips on the plug during forming, and this results in biaxial stretching of the base and walls of the formed cup. In contrast for T-plug > 100 degrees C, a significant reduction in the magnitude of slip is expected. Here the sheet is gripped at the clamp and by the plug during forming which causes reduced biaxial stretching of the base and increased uniaxial stretching of the walls of the cup. Simulations of plug-assist thermoforming using a temperature dependent COF showed qualitative agreement with the GSA data thereby supporting our inferences.

Electronic structure and properties of layered gallium telluride - Shenoy, U. Sandhya; Gupta, Uttam; Narang, Deepa S.; Late, Dattatray J.; Waghmare, Umesh V.; Rao, C. N. R. (Chemical Physics Letters, 2016)
Layer-dependent electronic structure and properties of gallium monochalcogenides, GaX where X=S, Se, Te, have been investigated using first-principles calculations based on various functionals, with a motivation to assess their use in photocatalytic water splitting. Since hydrogen evolution by water splitting using visible light provides a promising way for solar energy conversion, both theoretical and experimental studies have been carried out on the photochemical hydrogen evolution by GaTe. We also present the Raman spectra of GaTe examined by both theory and experiment. (C) 2016 Elsevier B.V. All rights reserved.

Enhanced clathrate hydrate formation kinetics at near ambient temperatures and moderate pressures: Application to natural gas storage - Veluswamy, Hari Prakash; Kumar, Sharad; Kumar, Rajnish; Rangsunvigit, Pramoch; Linga, Praveen (Fuel, 2016)
SNG (solidified natural gas) technology via clathrate hydrates is a potential method for large scale stationary storage of natural gas. Clathrate hydrate formation kinetics in presence of methane and 5.6 mol% tetrahydrofuran (THF) was investigated in an unstirred reactor configuration at moderate pressure and temperature conditions. It is well known that the presence of THF generally improves the thermodynamic stability of the resulting hydrate. In order to study the scale-up potential of this approach, kinetics of hydrate growth at temperatures close to ambient conditions and moderate pressures is required. Hydrate formation experiments were performed at three different temperatures - 283.2 K, 288.2 K and 293.2 K and at experimental pressures of 7.2 MPa, 5.0 and 3.0 MPa. Further, we report a synergistic effect of kinetic promotion of mixed methane hydrate formation by coupling THF and sodium dodecyl sulfate (SDS) at 293.2 K. For the first time, we observe rapid mixed methane/THF hydrate formation kinetics at 293.2 K in presence of just 100 ppm sodium dodecyl sulfate surfactant with methane gas uptake of 3.45 (+/- 0.17) kmol/m(3) of water in 1 h. This is also the first study to demonstrate such rapid hydrate formation kinetics with significant methane storage capacity at temperature of 293.2 K (closer to the ambient temperature). Further, substantial methane gas uptake of 3.52 (+/- 0.13) kmol/m(3) of water is possible even at reduced experimental pressure of 3.0 MPa and 283.2 K in 2 h. Minimal energy requirement in an unstirred reactor for mixed methane/THF hydrate formation storage can propel the SNG technology for large scale commercial deployment. Further improvement in the process can be achieved by optimizing the cooling requirement through innovative reactor design and operating the process in a semi-batch or continuous mode. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Methane hydrates; Natural gas storage; Rapid kinetics; surfactant; Tetrahydrofuran; Unstirred reactor

Enhanced field emission behavior of layered MoSe2 - Suryawanshi, Sachin R.; Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; More, Mahendra A.; Late, Dattatray J. (Materials Research Express, 2016)
Herein, we report one step facile chemical vapor deposition method for synthesis of single-layer MoSe2 nanosheets with average lateral dimension similar to 60 mu m on 300 nm SiO2/Si and n-type silicon substrates and field emission investigation of MoSe2/Si at the base pressure of similar to 1 x 10(-8) mbar. The morphological and structural analyses of the as-deposited single-layer MoSe2 nanosheets were carried out using an optical microscopy, Raman spectroscopy and atomic force microscopy. Furthermore, the values of turn-on and threshold fields required to extract an emission current densities of 1 and 10 mu A cm(-2), are found to be similar to 1.9 and similar to 2.3 V mu m(-1), respectively. Interestingly, the MoSe2 nanosheet emitter delivers maximum field emission current density of similar to 1.5 mA cm(-2) at a relatively lower applied electric field of similar to 3.9 V mu m(-1). The long term operational current stability recorded at the preset values of 35 mu A over 3 hr duration and is found to be very good. The observed results demonstrates that the layered MoSe2 nanosheet based field emitter can open up many opportunities for their potential application as an electron source in flat panel display, transmission electron microscope, and x-ray generation. Thus, the facile one step synthesis approach and robust nature of single-layer MoSe2 nanosheets emitter can provide prospects for the future development of practical electron sources.
Keywords: atomically thin nanosheets; chemical vapor deposition; field emission; layered MoSe2

Evaluation of uttroside B, a saponin from Solanum nigrum Linn, as a promising chemotherapeutic agent against hepatocellular carcinoma - Nath, Lekshmi R.; Gorantla, Jaggaiah N.; Thulasidasan, Arun Kumar T.; Vijayakurup, Vinod; Shah, Shabna; Anwer, Shabna; Joseph, Sophia M.; Antony, Jayesh; Veena, Kollery Suresh; Sundaram, Sankar; Marelli, Udaya K.; Lankalapalli, Ravi S.; et al. (Scientific Reports, 2016)
We report, for the first time, the remarkable efficacy of uttroside B, a potent saponin from Solanum nigrum Linn, against liver cancer. The compound has been isolated and characterized from the leaves of Solanum nigrum Linn, a plant widely used in traditional medicine and is a rich resource of several anticancer molecules. Uttroside B, that comprises of beta-D-glucopyranosyl unit at C-26 of the furostanol and beta-lycotetraosyl unit at C-3, is ten times more cytotoxic to the liver cancer cell line, HepG2 (IC50: 0.5 mu M) than sorafenib (IC50: 5.8 mu M), the only FDA-approved drug for liver cancer. Moreover, it induces cytotoxicity in all liver cancer cell lines, irrespective of their HBV status, while being non-toxic to normal immortalized hepatocytes. It induces apoptosis in HepG2 cells by down-regulating mainly the activation of MAPK and mTOR pathways. The drastic reduction in HepG2-xenograft tumor size achieved by uttroside B in NOD-SCID mice and substantiation of its biological safety through both acute and chronic toxicity studies in Swiss albino mice warrants clinical validation of the molecule against hepatic cancer, for which, the chemotherapeutic armamentarium currently has limited weapons.

Exfoliated 2D black phosphorus nanosheets: field emission studies - Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2016)
A few layer black phosphorus (BP) nanosheets are obtained by micromechanical cleavage from a bulk BP crystal. In a typical exfoliation procedure, a layer of BP is peeled off from bulk crystal with the help of Scotch tape and transferred onto SiO2/Si and pristine Si substrates. The morphological and structural analyses of the samples were carried out using an optical microscopy, a transmission electron microscopy, and a Raman spectroscopy. Field emission investigations on a few layered BP nanosheets on Si substrate were carried out at the base pressure of 1 x 10(-8) mbar. The turn-on value, corresponding to emission current density of similar to 1 mu A/cm(2), is found to be similar to 5.1V/mu m for BP nanosheets/Si emitter and high field enhancement factor (beta) similar to 1164, attributed to atomically thin/sharp edges of the BP nanosheets. The emission current shows good stability at a preset value of similar to 5 mu A over a period of more than 8 h. The present results demonstrate the potential of the mechanically exfoliated BP nanosheets/Si field emitter for the development of practical electron sources. (C) 2016 American Vacuum Society.

Expedient cobalt-catalyzed C–H alkynylation of (enantiopure) benzylamines - Landge, Vinod Gokulkrishna; Midya, Siba Prasad; Rana, Jagannath; Shinde, Dinesh R.; Balaraman, Ekambaram (Organic Letters, 2016)
A unified strategy for cobalt-catalyzed ortho-C-H bond alkynylation of benzylamines is reported. Simple, commercially available CoBr2 was used as a cobalt source. The developed alkynylation strategy is robust and efficient and has a broad substrate scope including 1 degrees, 2 degrees, and 3 degrees benzylamines. The mechanistic study shows that C-H bond cleavage is reversible, and the kinetic study illustrates that the rate of reaction depends solely on the catalyst.
Keywords: Terminal Alkynes; Bond Activation; Directed Functionalization; Aminoquinoline Benzamides; Ortho-C(Sp(2))-H Bonds; Mechanistic Insights; Selective Access; Carbon-Hydrogen; Nickel; Annulation

Experimental investigation to elucidate why tetrahydrofuran rapidly promotes methane hydrate formation kinetics: applicable to energy storage - Kumar, Asheesh; Daraboina, Nagu; Kumar, Rajnish; Linga, Praveen (Journal of Physical Chemistry C, 2016)
Methane storage as SNG (solidified natural gas) in the form of clathrate hydrates is an emerging, economically feasible and environmentally benign technology for large scale storage. Mixed tetrahydrofuran (THF)-methane (CH4) hydrates offer a paradigm shift to milder storage conditions and faster hydrate formation kinetics, providing a promising scenario to scale up the SNG technology. In this work, we synthesize mixed THF-CH4 hydrates in a high pressure microdifferential scanning calorimeter (HP mu-DSC) to elucidate the two-step hydrate formation mechanism of mixed THF-CH4 hydrate identifying the synergism between THF and CH4. Heat flow change during hydrate formation and dissociation of mixed THF-CH4 hydrates formed in the presence of 5.56 mol % THF (stoichiometric composition) were monitored. The two step-mechanism of mixed THF-CH4 hydrate formation was further confirmed by the pressure-temperature profile and visual observations with a sample volume scale -up of about 350 times that of mu-DSC experiments.

Facile approach towards fabrication of GdB6-ZnO heteroarchitecture as high currentdensity cold cathode - Suryawanshi, Sachin R.; Mistari, Chetan D.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Chemistryselect, 2016)
Three dimensional (3D) GdB6-ZnO heteroarchitecture comprised of thin coating of GdB6 on self aligned ZnO urchins with pointed apex has been synthesized employing optimized Pulsed Laser Deposition (PLD) technique. The self aligned ZnO urchins on Zn substrate were obtained using hydrothermal route. The as-synthesized GdB6-ZnO heteroarchitecture was characterized using XRD, SEM, TEM XPS, and UPS in order to reveal its structural, morphological, chemical, and electronic properties. Interestingly, the GdB6-ZnO heteroarchitecture exhibits superior field emission (FE) behviour in contrast to the pristine ZnO urchins envisaged by extraction of very high emission current density of similar to 4.6 mA/cm(2) at an applied field of similar to 4.5 V/mm, against similar to 1.5 mA/cm(2) at an applied field of similar to 5.6 V/mm from the pristine ZnO urchins emitter. Furthermore, the GdB6-ZnOemitter exhibits good emission stability at pre-set value of similar to 5 mA over duration of more than 3 hours. The superior FE behaviour of the GdB6-ZnO is attributed to low work-function of GdB6 and presence of nanometric protrusions on the emitter surface, further enhancing the aspect ratio provided by the ZnO urchins. The present results demonstrate a facile approach towards fabrication of high current density cold cathodes due to rare earth hexaborides via designing hetero-architectures comprised of their well adherent ultrathin coating on high aspect ratio metal oxide nanostructures.

Field emission investigation of composites of polypyrrole with graphene oxide, reduced graphene oxide and graphene nanoribbons - Harpale, Kashmira; Bansode, Sanjeewani; More, Mahendra; Late, D. J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The monomer pyrrole has been polymerized by chemical route in the presence of graphene oxide (GO), reduced graphene oxide (rGO) and graphene nanoribbons (GNR) separately to prepare nanocomposites as Polypyrrole-GO (PGO), PPy-rGO (PRGO), PPy-GNR (PGNR), respectively. The morphological, chemical and structural characterization of the as-synthesized products was carried out using scanning electron microscopy (SEM), Raman and fourier transform infrared (FTIR) spectroscopy. Field emission (FE) studies of PGO, PRGO, PGNR emitters were performed at the base pressure of 1x10(-8) mbar in planar `diode' configuration. Onset and threshold field values corresponding to emission current densities of 1 and 100 mu A/cm(2) are observed to be 1.5 and 2.3V/mu m for PGO, 1.4 and 2.2 V/mu m for PRGO and lowest for PGNR as 0.9 and 1.2V/mu m, respectively. The maximum emission current density of 2.5 mA/cm(2) drawn for PGO at the applied electric field of 3.2V/mu m, 1.2 mA/cm(2) at 3.6V/mu m from the PRGO and 8 mA/cm(2) at the field of 2.2 V/mu m from the PGNR emitters. An emission current versus time (I-t) plot shows stable emission behavior for the preset current values.
Keywords: field emission; FTIR; polypyrrole; Raman

Field emission properties of highly ordered low-aspect ratio carbon nanocup arrays - Gupta, Bipin Kumar; Kedawat, Garima; Kumar, Pawan; Singh, Satbir; Suryawanshi, Sachin R.; Agrawal, Neetu; Gupta, Govind; Kim, Ah Ra; Gupta, R. K.; More, Mahendra A.; Late, Dattatray J.; Hahm, Myung Gwan (RSC Advances, 2016)
Herein, we design and develop a field emission device utilizing highly porous carbon nanocup (CNC) films. These three-dimensional (3D) low-aspect ratio CNC structures were fabricated by a combination of anodization and chemical vapor deposition techniques. The low turn-on fields of 2.30 V mu m(-1) were observed to draw an emission current density of 1 mu A cm(-2) and a maximum emission current density of similar to 1.802 mA cm(-2) drawn at an applied field of similar to 4.20 V mu m(-1). The enhanced field emission behavior observed from the CNC films is attributed to an excellent field enhancement factor of 1645. The observed field emission properties of CNC arrays are attributed to a synergistic combination of high aspect ratio, nano-sized radius of curvature, highly organized distribution of the emitters over the whole area of specimen and lower screening effect of the CNC arrays. These observations shed light on the effect of the stacking carbon layers of CNC on their electronic properties and open up possibilities to integrate new morphologies of graphitic carbon in nanotechnology applications. Thus, the low turn on field, high emission current density and better emission current stability enable CNC based future field emission applications.

Fusarium oxysporum mediates systems metabolic reprogramming of chickpea roots as revealed by a combination of proteomics and metabolomics - Kumar, Yashwant; Zhang, Limin; Panigrahi, Priyabrata; Dholakia, Bhushan B.; Dewangan, Veena; Chavan, Sachin G.; Kunjir, Shrikant M.; Wu, Xiangyu; Li, Ning; Rajmohanan, Pattuparambil R.; Kadoo, Narendra Y.; Giri, Ashok P.; et al. (Plant Biotechnology Journal, 2016)
Molecular changes elicited by plants in response to fungal attack and how this affects plant-pathogen interaction, including susceptibility or resistance, remain elusive. We studied the dynamics in root metabolism during compatible and incompatible interactions between chickpea and Fusarium oxysporum f. sp. ciceri (Foc), using quantitative label-free proteomics and NMR-based metabolomics. Results demonstrated differential expression of proteins and metabolites upon Foc inoculations in the resistant plants compared with the susceptible ones. Additionally, expression analysis of candidate genes supported the proteomic and metabolic variations in the chickpea roots upon Foc inoculation. In particular, we found that the resistant plants revealed significant increase in the carbon and nitrogen metabolism; generation of reactive oxygen species (ROS), lignification and phytoalexins. The levels of some of the pathogenesis-related proteins were significantly higher upon Foc inoculation in the resistant plant. Interestingly, results also exhibited the crucial role of altered Yang cycle, which contributed in different methylation reactions and unfolded protein response in the chickpea roots against Foc. Overall, the observed modulations in the metabolic flux as outcome of several orchestrated molecular events are determinant of plant's role in chickpea-Foc interactions.
Keywords: Chickpea; fusarium oxysporum; Metabolomics; NMR; plant-pathogen interaction; proteomics

Glucose sensing and low-threshold field emission from MnCo2O4 nanosheets - Naik, Kusha Kumar; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2016)
Manganese cobalt oxide (MnCo2O4) nanosheets were grown on nickel (Ni) foam by a simple electrodeposition method. The as-synthesized nanosheets were characterized using X-ray diffraction and scanning electron microscopy. The Ni foam supports the growth of MnCo2O4 nanosheets without any aggregation, thereby increasing its catalytic and electronic properties. The electrochemical studies show that MnCo2O4 exhibits excellent electrocatalytic activity towards glucose sensing applications. The MnCo2O4 based glucose sensor shows a good sensitivity value of 8.2 mA mM(-1) cm(-2), with a response time of 19 s. In addition to this, field emission studies of as-synthesized MnCo2O4 reveal a low turn-on field value of 1.9 V mm(-1) and good emission current stability, demonstrating MnCo2O4 nanosheets as a good field emitter material.

High performance humidity sensor and photodetector based on SnSe nanorods - Pawbake, Amit S.; Jadkar, Sandesh R.; Late, Dattatray J. (Materials Research Express, 2016)
Tin selenide (SnSe) nanorods were synthesized using a. one-step solvothermal route and. their. humidity sensing and photodetection performance at room temperature were investigated. The results depict. that SnSe nanorod-based humidity and photosensors have. good long-term stability, are. highly sensitive and have. fast response and recovery times. In the. case of the. humidity sensor it was observed that the resistance of the films decreased. with increasing relative humidity (RH). The humidity sensing behaviors were investigated in the range. 11-97% RHat room temperature. A. response time of similar to 68 s and recovery time of similar to 149 s were observed for. the humidity sensor. The photosensing behavior showed. typical response/recovery times of similar to 3 s with highly reproducible behavior.

Highly transparent wafer-scale synthesis of crystalline WS2 nanoparticle thin film for photodetector and humidity-sensing applications - Pawbake, Amit S.; Waykar, Ravindra G.; Late, Dattatray J.; Jadkar, Sandesh R. (ACS Applied Materials & Interfaces, 2016)
In the present investigation, we report a one-step synthesis method of wafer-scale highly crystalline tungsten disulfide (WS2) nanoparticle thin film by using a modified hot wire chemical vapor deposition (HW-CVD) technique. The average size of WS2 nanoparticle is found to be 25-40 nm over an entire 4 in. wafer of quartz substrate. The low-angle XRD data of WS2 nanoparticle shows the highly crystalline nature of sample along with orientation (002) direction. Furthermore, Raman spectroscopy shows two prominent phonon vibration modes of E12g and A1g at similar to 356 and similar to 420 cm(-1), respectively, indicating high purity of material. The TEM analysis shows good crystalline quality of sample. The synthesized WS2 nanoparticle thin film based device shows good response to humidity and good photosensitivity along with good long-term stability of the device. It was found that the resistance of the films decreases with increasing relative humidity (RH). The maximum humidity sensitivity of 469% along with response time of similar to 12 s and recovery time of similar to 13 s were observed for the WS2 thin film humidity sensor device. In the case of photodetection, the response time of similar to 51 s and recovery time of similar to 88 s were observed with sensitivity similar to 137% under white light illumination. Our results open up several avenues to grow other transition metal dichalcogenide nanoparticle thin film for large-area nanoelectronics as well as industrial applications.
Keywords: chemical vapor deposition; humidity sensor; nanoparticle; photosensor; thin film; tungsten disulfide

Humidity sensing and photodetection behavior of electrochemically exfoliated atomically thin-layered black phosphorus nanosheets - Erande, Manisha B.; Pawar, Mahendra S.; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2016)
Recent investigations on two-dimensional black phosphorus material mainly highlight work on few atomic layers and multilayers. It is still unknown if the black phosphorus atomically thin sheet is an ideal structure for the enhanced gas solid interactions due to its large surface area. To further investigate this concern, we have synthesized few atomic layer thick nanosheets of black phosphorus using an electrochemical exfoliation method. The surface morphology and thickness of the nanosheet were identified using AFM, TEM, and Raman spectroscopy. The black phosphorus nanosheet thick film device was used for the gas sensing application with exposure to different humidites. Further, the few layer black phosphorus nanosheet based transistor shows good mobility and on/off ratio. The UV light irradiation on the black phosphorus nanosheet shows good response time. The overall results show that the few layer thick film of black phosphorus nanosheets sample exhibits creditable sensitivity and better recovery time to be used in humidity sensor and photodetector applications.
Keywords: black phosphorus; electrochemical exfoliation; humidity sensor; photodetector

Immobilization of pectinase on reusable polymer support for clarification of apple juice - Rajdeo, Kishor; Harini, Tirunagari; Lavanya, Kuna; Fadnavis, Nitin W. (Food and Bioproducts Processing, 2016)
Pectinase (E.C.3.2.1.15) was successfully immobilized on recyclable polymer matrix. The immobilization matrix was prepared by reaction of polyethyleneimine (mol. wt. 70,000) with epoxy-activated acrylate copolymer DILBEAD-VWR. The enzyme pectinase was first adsorbed on the polymer at pH 7.0 via ion exchange and then stabilized by crosslinking with dextran aldehyde. While the free enzyme shows a pH-optimum of 5.0, the immobilized enzyme exhibited high level of activity in a broad pH range of pH 3.0-7.0. Although the thermal stability of free and immobilized enzymes was similar, at room temperature, the immobilized enzyme could be recycled more than 10 times with loss of less than 5% of its activity during clarification of apple juice. On the eventual loss of enzyme activity, the immobilized enzyme and dextran aldehyde can be easily removed from the polymer by a simple treatment with 1N HCl and the polymer can be reused for immobilization of a fresh batch of enzyme. This support also can be reused several times, making the process economically attractive. The properties of apple juice treated with immobilized enzyme were similar to those of that treated with free pectinase. (C) 2016 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Apple juice; Dextran aldehyde; Immobilization; Pectinase; Polyethyleneimine; Polymer

In situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.

Isolation and characterization of new lignin streams derived from extractive-ammonia (EA) pretreatment - Sousa, Leonardo da Costa; Foston, Marcus; Bokade, Vijay V.; Azarpira, Ali; Lu, Fachuang; Ragauskas, Arthur J.; Ralph, John; Dale, Bruce E.; Balan, Venkatesh (Green Chemistry, 2016)
One of the key challenges facing lignin conversion to fuels and chemicals is related to the level of carbohydrate and ash impurities found in extracted lignin. Structural modifications of lignin may also occur as a result of biomass pretreatment and harsh lignin extraction protocols. Extractive-Ammonia (EA) is a new pretreatment technology that uses liquid ammonia to cleave lignin-carbohydrate complexes, decrystallize cellulose, solubilize lignin, and selectively extract Lignin from lignocellulosic biomass, enabling better utilization of both lignin and carbohydrate components in a biorefinery. The EA-based biorefinery produces two different lignin-rich streams, with different properties, that could potentially be upgraded to fuels and chemicals using green processes. In this work, a water/ethanol-based fractionation method was developed to enrich the ammonia-soluble extractives, resulting in a major product stream containing 92% lignin. Detailed characterization of the various streams resulting from EA treatment, including compositional analysis, structural characterization by nuclear magnetic resonance (NMR) spectrometry, elemental analysis, molecular weight analysis, and thermo-gravimetric analysis provides a broad evaluation of the EA derived lignin product stream structures and properties, assessing their potential for commercial applications. In summary, EA-derived lignins preserve much of lignin's functionality, including the sensitive (3-aryl ether units. Nitrogen incorporation was observed in the lignin-rich streams, notably due to the presence of hydroxycinnamoyl amides formed during ammonia pretreatment.

Large area chemical vapor deposition of monolayer transition metal dichalcogenides and their temperature dependent Raman spectroscopy studies - Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; Late, Dattatray J. (Nanoscale, 2016)
We investigate the growth mechanism and temperature dependent Raman spectroscopy of chemical vapor deposited large area monolayer of MoS2, MoSe2, WS2 and WSe2 nanosheets up to 70 mu m in lateral size. Further, our temperature dependent Raman spectroscopy investigation shows that softening of Raman modes as temperature increases from 80 K to 593 K is due to the negative temperature coefficient and anharmonicity. The temperature dependent softening modes of chemical vapor deposited mono-layers of all TMDCs were explained on the basis of a double resonance phonon process which is more active in an atomically thin sample. This process can also be fundamentally pertinent in other emerging two-dimensional layered and heterostructured materials.

Laser exfoliation of 2D black phosphorus nanosheets and their application as a field emitter - Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2016)
Highly crystalline two dimensional (2D) few layered black phosphorus (BP) nanosheets have been synthesized via a one step facile laser irradiation technique under optimized experimental conditions. The field emission investigations on the few layered black phosphorus nanosheets were carried out at the base pressure 1 x 10(-8) mbar. The morphological, elemental, optical, and structural analysis of the as-synthesized black phosphorus sample was carried out using SEM, AFM, EDAX, TEM, and Raman spectroscopy. The turn-on values of the BP nanosheets emitter were found to be significantly lower than that of earlier reports of BP nanosheets, graphene, and carbon nanotubes based field emitters due to the high field enhancement factor (beta) similar to 2986 associated with atomically thin/sharp edges of the BP nanosheets emitter. The emission current versus time plot depicts the good emission current stability with a pre-set value of 1 mu A for similar to 5 h duration. Our facile synthesis approach and the robust field emitter nature of the BP nanosheets makes them a potential candidate for a practical electron source in vacuum micro/nanoelectronic devices.

Liquid exfoliation of black phosphorus nanosheets and its application as humidity sensor - Late, Dattatray J. (Microporous and Mesoporous Materials, 2016)
The bulk crystal of black phosphorus was exfoliated by liquid exfoliation method for a duration of 8 h using N-Methyl-2-Pyrrolidone as the solvent. The exfoliated sample was centrifuged at different rpm such as 3000, 5000 and 10,000 to separate out the 2D black phosphorus nanosheets with different thickness and length. The as synthesized black phosphorus nanosheets collected at these rpm values were characterized with TEM, AFM, Raman spectroscopy and Vis-NIR spectroscopy. Further, we investigated the humidity sensing behaviour of the devices fabricated by using these samples. The results obtained show that the device fabricated with black phosphorus nanosheets and nanoparticles obtained by filtration of the sample collected after 10,000 rpm exhibited better performance as compared to the nanosheets collected at 3000 and 5000 rpm. The response and recovery times of devices are found to be promising and better than those of the black phosphorus gas sensor reported earlier. The present investigations open up a new avenue for further studies in improving the performance of black phosphorus nanosheets based gas sensing devices. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: black phosphorus; Humidity sensors; Liquid exfoliation; nanosheets

Low frequency noise and photo-enhanced field emission from ultrathin PbBi2Se4 nanosheets - Suryawanshi, Sachin R.; Guin, Satya N.; Chatterjee, Arindom; Kashid, Vikas; More, Mahendra A.; Late, Dattatray J.; Biswas, Kanishka (Journal of Materials Chemistry C, 2016)
Atomically thin two-dimensional layered materials have gained wide interest owing to their novel properties and potential for applications in nanoelectronic and optoelectronic devices. Here, we present the spectral analysis and photo-enhanced field emission studies of a layered intergrowth PbBi2Se4 nanosheet emitter, performed at the base pressure of similar to 1 x 10(-8) mbar. The emitter shows a turn-on field value of similar to 4.80 V mu m(-1), corresponding to an emission current density of similar to 1 mu A cm(-2). Interestingly, when the cathode was illuminated with visible light, it exhibited a lower turn-on field of B3.90 V mm(-1), and a maximum emission current density of similar to 893 mu A cm(-2) has been drawn at an applied electric field of similar to 8.40 V mu m(-1). Furthermore, the photo-enhanced emission current showed reproducible, step-like switching behavior in synchronous with ON-OFF switching of the illumination source. The emission current-time plots reveal excellent stability over a duration of similar to 6 h. Low-frequency noise is a significant limitation for the performance of nanoscale electronic devices. The spectral analysis performed on a Fast Fourier Transform (FFT) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha similar to 0.99. The low frequency noise, photo-enhanced field emission, and reproducible switching behavior characterized with very fast rise and fall times propose the layered PbBi2Se4 nanosheet emitter as a new promising candidate for novel vacuum nano-optoelectronic devices.

Low turn-on field and high field emission current density from Ag/TiO 2 nanocomposite - Patil, Girish P.; Deore, Amol B.; Bagal, Vivekanand S.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Chemical Physics Letters, 2016)
High current density of 1.24 mA/cm2 was drawn at an applied field of 4.4 V/μm from Ag/TiO2 nanocomposite. Also the turn-on field has been reduced from 3.9 V/μm to 2.7 V/μm for the emission current density of 10 μA/cm2. Ag/TiO2 nanocomposite was synthesized by using UV-switchable reducing agent. TiO2 nanotube wall was decorated by Ag nanoparticles with average diameter of 17 nm. To the best of our knowledge this is the first report on the field emission studies of Ag/TiO2 nanocomposite. Simple synthesis route coupled with superior field emission properties indicate the possible use of Ag/TiO2 nanocomposite for micro/nanoelectronic devices.

Next-generation ammonia pretreatment enhances cellulosic biofuel production - Sousa, Leonardo da Costa; Jin, Mingjie; Chundawat, Shishir P. S.; Bokade, Vijay V.; Tang, Xiaoyu; Azarpira, Ali; Lu, Fachuang; Avci, Utku; Humpula, James; Uppugundla, Nirmal; Gunawan, Christa; Pattathil, Sivakumar; et al. (Energy & Environmental Science, 2016)
A new liquid ammonia pretreatment methodology called Extractive Ammonia (EA) was developed to simultaneously convert native crystalline cellulose I-beta (CI) to a highly digestible cellulose IIII (CIII) allomorph and selectively extract up to B45% of the lignin from lignocellulosic biomass with near-quantitative retention of all polysaccharides. EA pretreated corn stover yielded a higher fermentable sugar yield compared to the older Ammonia Fiber Expansion (AFEX) process while using 60% lower enzyme loading. The EA process preserves extracted lignin functionalities, offering the potential to co-produce lignin-derived fuels and chemicals in the biorefinery. The single-stage EA fractionation process achieves high biofuel yields (18.2 kg ethanol per 100 kg untreated corn stover, dry weight basis), comparable to those achieved using ionic liquid pretreatments. The EA process achieves these ethanol yields at industrially-relevant conditions using low enzyme loading (7.5 mg protein per g glucan) and high solids loading (8% glucan, w/v).

Nickel-catalyzed direct alkynylation of C(sp2)-H bonds of amides: an “inverse sonogashira strategy” to ortho-alkynylbenzoic acids. just accepted - Landge, Vinod Gokulkrishna; Shewale, Chinmay H.; Jaiswal, Garima; Sahoo, Manoj Kumar; Midya, Siba Prasad; Balaraman, Ekambaram (Catalysis Science & Technology, 2016)
Nickel-catalyzed direct alkynylation of C(sp2)–H bonds of amides using commercially available, inexpensive 8-aminoquinoline as a removable bidentate directing group is described. The present ortho-alkynylation has a broad substrate scope, functional group tolerance and high regiocontrol, and can be scaled up. The efficiency and selectivity of this strategy provide sustainable routes to a diverse array of ortho-alkynylbenzoic acids under Ni(II)-catalyzed conditions.

Nitrogen doping in oxygen-deficient Ca2Fe2O5: a strategy for efficient oxygen reduction oxide catalysts - Jijil, Chamundi P.; Lokanathan, Moorthi; Chithiravel, Sundaresan; Nayak, Chandrani; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Babu, P. D.; Kakade, Bhalchandra A.; Devi, R. Nandini (ACS Applied Materials and Interfaces, 2016)

Observation of enhanced field emission properties of Au/TiO2 nanocomposite - Patil, Girish P.; Bagal, Vivekanand S.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Applied Physics A-Materials Science & Processing, 2016)
Simple and low-cost method of thermal annealing was used to decorate Gold (Au) nanoparticles on aligned TiO2 nanotubes. The aligned TiO2 nanotubes were decorated by Au nanoparticles with an average diameter of 9, 18 and 28 nm (aligned TiO2 nanotubes referred as specimen A and TiO2 nanotubes decorated by Au nanoparticles with average diameter of 9, 18 and 28 nm are referred as specimen B, C and D, respectively). The detailed characterization such as structural, morphological and elemental analysis of TiO2 and Au/TiO2 nanocomposite have been carried out using X-ray diffraction, field emission scanning electron microscope, transmission electron microscope, X-ray photoelectron spectroscopy and Raman spectroscopy. Furthermore, the meticulous comparative field emission characteristics of the aligned TiO2 nanotubes and Au/TiO2 nanocomposite have been performed. The turn-on field defined for the current density of 10 mu A/cm(2) has been found to be 3.9, 2.8, 3.2 and 3.7 V/mu m for specimen A, B, C and D, respectively. The observed low turn-on field of specimen B has been found to be superior than the other semiconducting nanocomposites reported in the literature. The emission current stability over a period of 3 h is found to be better for all the specimens. To the best of our knowledge, a systematic field emission study of Au/TiO2 nanocomposite has not been explored. The observed superior field emission study of Au/TiO2 nanocomposite indicates their possible use in micro/nanoelectronic devices.

Olfactory stimulation of apis cerana indica towards different doses of volatile constituents: SEM and EAG approaches - Bhowmik, Biswanath; Lakare, Sachin; Sen, Ayalokiteswar; Bhadra, Kakali (Journal of Asia-Pacific Entomology, 2016)
Morphological and peripheral olfactory responses of antennal chemosensilla of Apis cerana indica, worker honeybee, to commonly occurring plant volatiles were recorded using SEM and EAG techniques, respectively. The antennae of A. cerana indica reveal the predominance of olfactory sensilla besides gustatory and mechanoreceptor cells. Ten different types of olfactory sensilla including sensilla basiconica, placodea type A and B, chaetica, coeloconica, coelocapitula, trichodea type A, B, C and D were reported. Of these, trichodea B and placodea A types were reported to be maximum. Responses to 47 commonly occurring plant volatiles (including 10 aromatic, 12 aliphatic, 04 green leaf volatile, 10 hydrocarbon monoterpene, 08 oxygenated monoterpenes and 03 sesquiterpenes compounds) were shown to elicit the response. Normalized EAG response, relative to the standard 1-hexanol, reveal significant differences between the chemicals and were concentration dependent. At 0.1 mg/mL dose, the largest amplitude was obtained with p-cymene (119.74 +/- 6.94) followed by cinnamaldehyde (97.07 +/- 4.94) and veratrol (92.99 +/- 7.82). Furthermore, at 1.0 mg/mL, maximum stimulation was reported with cinnamaldehyde (92.02 +/- 4.26) followed by phenethyl alcohol (86.02 +/- 2.63), benzyl alcohol (70.53 +/- 2.47), 2-heptanone (67.71 +/- 5.02) and 1-heptanol (67.56 +/- 2.8). Again, amplitude of the response was found to be maximum with cinnamaldehyde (115.59 +/- 6.73) followed by 1-heptanol (105.69 +/- 2.45) and citral (100.78 +/- 4.93) at 5.0 mg/mL, whereas, at 10.0 mg/mL, phenethyl alcohol (93.45 +/- 1.87) and 2-heptanone (93.14 +/- 1.85) showed highest stimulation followed by 2-pentanone (92.22 +/- 0.43). These documentations provide valuable information regarding how diversity in chemoreceptive antennal sensilla reveals better ability to sense a diversity of odors that are important cues to help honeybee distinguish among species of various flowering plants. (C) 2016 Korean Society of Applied Entomology, Taiwan Entomological Society and Malaysian Plant Protection Society. Published by Elsevier B.V. All rights reserved.

Organocatalytic route to enantioselective synthesis of ceramide trafficking inhibitor HPA-12 - Lalwani, Komal G.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A new organocatalytic approach to the synthesis of ceramide trafficking inhibitor HPA-12 has been described starting from phenacyl bromide. The strategy involves chiral CBS reduction of gamma-ketoester and proline-catalyzed alpha-amination reaction of aldehyde followed by reduction as the key chirality inducing steps. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; CBS reduction; Ceramide; Organocatalytic; Proline

Organofunctionalization of vanadium(III) acetylacetonate complex over aminofunctionalized SBA-15 for sulfoxidation reactions - Lazar, Anish; Sanjush, K. S.; Singh, A. P. (Advanced Porous Materials, 2016)
Recyclable SBA-15 supported aminopropyl vanadium(III) acetylacetonate heterogeneous catalyst has been synthesized by covalent anchoring of vanadium(III) acetylacetonate over aminofunctionalized SBA-15 via. post grafting method, V(III)(acac)3NH2@SBA-15. The synthesized catalyst was characterized by elemental analysis, ICP-OES, XRD, N2 sorption analysis, FT-IR, 29Si NMR spectroscopy, XPS, SEM and TEM. The percentage of nitrogen and vanadium in V(III)(acac)3NH2@SBA-15 was determined by elemental analysis and ICP-OES, respectively. XRD and N2 sorption analyses provide the information about the structural integrity (Mesoporous structure) and textural properties of all synthesized catalysts. The presence and degree of organofunctionalization on SBA-15 were monitored by FT-IR and 29Si NMR spectroscopy, respectively. Moreover, the oxidation state and the chemical environment of vanadium metal in V(III)(acac)3NH2@SBA-15 were revealed by XPS spectroscopy. Eventually, the morphology and topographic information of the synthesized catalysts were confirmed by SEM and TEM imaging. The synthesized catalyst was evaluated in oxidation of various sulfides and the results show that V(III)(acac)3NH2@SBA-15 catalyst exhibits higher conversion and selectivity towards the sulfoxidation reaction compared to the neat V(III)(acac)3 complex and blank reaction. The synthesized catalyst was recycled four times.

Phenothiazine and carbazole substituted pyrene based electroluminescent organic semiconductors for OLED devices - Salunke, Jagadish K.; Wong, F. L.; Feron, Krishna; Manzhos, Sergei; Lo, Ming Fai; Shinde, Durgaprasad; Patil, Abhijeet; Lee, C. S.; Roy, V. A. L.; Sonar, Prashant; Wadgaonkar, Prakash P. (Journal of Materials Chemistry C, 2016)
Due to their easy availability, low cost and opportunities for exploiting reactions of bromo substituents, 1,3,6,8-tetrabromopyrene has attracted major attention in the organic electronics community for designing and constructing novel classes of pyrene based organic semiconducting functional materials. In the present work, 1,3,6,8-tetrabromo pyrene was transformed into the corresponding tetrasubstituted carbazole and phenothiazine derivatives using the classical Suzuki coupling reaction. These newly synthesized materials with a carbazole substituent (PY-CA) and a phenothiazine substituent (PY-PH) were characterised thoroughly and were successfully used as an active light-emitting layer in organic light emitting diodes which resulted in blue and green emission with promising device performance. PY-CA exhibited the maximum brightness at around 2500 cd m(-2) and the power efficiency of 1.5 lm W-1 while that of PY-PH exhibited 2116 cd m(-2) and 0.45 lm W-1 respectively.

Phenylacetylene hydrogenation on Au@Ni bimetallic core-shell nanoparticles synthesized under mild conditions - Vysakh, A. B.; Lazar, Anish; Yadukiran, V.; Singh, A. P.; Vinod, C. P. (Catalysis Science & Technology, 2016)
The synthesis of Au@Ni bimetallic core-shell nanoparticles through an energy efficient (lower temperature) route in oleylamine following a sequential reduction strategy is reported. The method is found to be useful for the synthesis of a very thin nickel shell (2 nm) over a gold core (15 nm). Synergistic effects are observed in catalyzing phenylacetylene hydrogenation under different solvent conditions.

PolyHIPE derived freestanding 3D carbon foam for cobalt hydroxide nanorods based highperformance supercapacitor - Patil, Umakant M.; Ghorpade, Ravindra V.; Nam, Min Sik; Nalawade, Archana C.; Lee, Sangrae; Han, Haksoo; Jun, Seong Chan (Scientific Reports, 2016)
The current paper describes enhanced electrochemical capacitive performance of chemically grown Cobalt hydroxide (Co(OH)(2)) nanorods (NRs) decorated porous three dimensional graphitic carbon foam (Co(OH)(2)/3D GCF) as a supercapacitor electrode. Freestanding 3D porous GCF is prepared by carbonizing, high internal phase emulsion (HIPE) polymerized styrene and divinylbenzene. The PolyHIPE was sulfonated and carbonized at temperature up to 850 degrees C to obtain graphitic 3D carbon foam with high surface area (389 m(2) g(-1)) having open voids (14 mu m) interconnected by windows (4 mu m) in monolithic form. Moreover, entangled Co(OH)(2) NRs are anchored on 3D GCF electrodes by using a facile chemical bath deposition (CBD) method. The wide porous structure with high specific surface area (520 m(2) g(-1)) access offered by the interconnected 3D GCF along with Co(OH)(2) NRs morphology, displays ultrahigh specific capacitance, specific energy and power. The Co(OH)(2)/3D GCF electrode exhibits maximum specific capacitance about similar to 1235 F g(-1) at similar to 1 Ag-1 charge-discharge current density, in 1 M aqueous KOH solution. These results endorse potential applicability of Co(OH)(2)/3D GCF electrode in supercapacitors and signifies that, the porous GCF is a proficient 3D freestanding framework for loading pseudocapacitive nanostructured materials.

Production of bikaverin by a Fusarium fujikuroi mutant in submerged cultures - Lale, Geetanjali; Gadre, R. V. (AMB Express, 2016)
A variety of mutants having different colony characteristics, morphology and soluble pigmentation were generated from Fusarium fujikuroi by exposure to UV radiation. Mutants were selected that formed dry, compact, small colonies with reddish-violet pigment on regeneration agar plates. The production of bikaverin by Mut-4 was examined in shake flasks in media with different nitrogen and carbon sources. The optimal C: N ratio for the maximal bikaverin production by Mut-4 was 150: 1. It produced still higher bikaverin (6.3 g l(-1)) in a medium containing defatted cottonseed meal as nitrogen source, in combination with glucose. Bikaverin produced was extracted, purified and characterized by UV-visible and NMR spectroscopy. Bikaverin production in the present investigation was substantially higher than that reported by earlier investigators in submerged and solid-state fermentations.
Keywords: Bikaverin; Fusarium fujikuroi; Gibberella fujikuroi; Pigment production; Submerged cultures

Pulsed laser-deposited nanocrystalline GdB6 thin films on W and Re as field emitters - Suryawanshi, Sachin R.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Applied Physics A-Materials Science & Processing, 2016)
Gadolinium hexaboride (GdB6) nanocrystalline thin films were grown on tungsten (W), rhenium (Re) tips and foil substrates using optimized pulsed laser deposition (PLD) technique. The X-ray diffraction analysis reveals formation of pure, crystalline cubic phase of GdB6 on W and Re substrates, under the prevailing PLD conditions. The field emission (FE) studies of GdB6/W and GdB6/Re emitters were performed in a planar diode configuration at the base pressure similar to 10(-8) mbar. The GdB6/W and GdB6/Re tip emitters deliver high emission current densities of similar to 1.4 and 0.811 mA/cm(2) at an applied field of similar to 6.0 and 7.0 V/mu m, respectively. The Fowler-Nordheim (F-N) plots were found to be nearly linear showing metallic nature of the emitters. The noticeably high values of field enhancement factor (beta) estimated using the slopes of the F-N plots indicate that the PLD GdB6 coating on Wand Re substrates comprises of high-aspect-ratio nanostructures. Interestingly, the GdB6/W and GdB6/Re planar emitters exhibit excellent current stability at the preset values over a long-term operation, as compared to the tip emitters. Furthermore, the values of workfunction of the GdB6/W and GdB6/Re emitters, experimentally measured using ultraviolet photoelectron spectroscopy, are found to be same, similar to 1.6 +/- 0.1 eV. Despite possessing same workfunction value, the FE characteristics of the GdB6/W emitter are markedly different from that of GdB6/Re emitter, which can be attributed to the growth of GdB6 films on W and Re substrates.

Purification and characterization of an extracellular beta-xylosidase from Pseudozyma hubeiensis NCIM 3574 (PhXyl), an unexplored yeast - Mhetras, Nutan; Liddell, Susan; Gokhale, Digambar (AMB Express, 2016)
This paper reports on the production of beta-xylosidase from an unexplored yeast, Pseudozyma hubeinsis. The expression of this enzyme could be induced by beech wood xylan when the yeast was grown at 27 degrees C. The enzyme was purified to homogeneity as a glycoprotein with 23 % glycosylation. The purification protocol involved ammonium sulphate precipitation, QAE-Sephadex A50 ion exchange chromatography and sephacryl-200 column chromatography which resulted in 8.3-fold purification with 53.12 % final recovery. The purified enzyme showed prominent single band on SDS-PAGE. It is a monomeric protein of 110 kDa molecular weight confirmed by SDS-PAGE followed by MALDI-TOF mass spectrometry (112.3 kDa). The enzyme was optimally active at 60 degrees C and pH 4.5 and stable at pH range (4-9) and at 50 degrees C for 4 h. Chemical modification studies revealed that active site of the purified enzyme comprised of carboxyl, tyrosine and tryptophan residues. The carboxyl residue is involved in catalysis and tryptophan residue is solely involved in substrate binding. The best match from the search of the NCBInr database was with gi vertical bar 808364558 glycoside hydrolase of Pseudozyma hubeiensis SY62 with 26 % sequence coverage confirming that it is a glycoside hydrolase/beta-glucosidase. From the search of customized SWISSPROT database, it was revealed that SWISSPROT does not contain any entries that are similar to the purified enzyme.

Pyramiding PvPGIP2 and TAXI-III but not PvPGIP2 and PMEI enhances resistance against fusarium graminearum - Tundo, Silvio; Kalunke, Raviraj; Janni, Michela; Volpi, Chiara; Lionetti, Vincenzo; Bellincampi, Daniela; Favaron, Francesco; D'Ovidio, Renato (Molecular Plant-Microbe Interactions, 2016)
Plant protein inhibitors counteract the activity of cell wall degrading enzymes (CWDEs) secreted by pathogens to breach the plant cell-wall barrier. Transgenic plants expressing a single protein inhibitor restrict pathogen infections. However, since pathogens secrete a number of CWDEs at the onset of infection, we combined more inhibitors in a single wheat genotype to reinforce further the cell-wall barrier. We combined polygalacturonase (PG) inhibiting protein (PGIP) and pectin methyl esterase inhibitor (PMEI), both controlling the activity of PG, one of the first CWDEs secreted during infection. We also pyramided PGIP and TAXI-M, a xylanase inhibitor that controls the activity of xylanases, key factors for the degradation of xylan, a main component of cereal cell wall. We demonstrated that the pyramiding of PGIP and PMEI did not contribute to any further improvement of disease resistance. However, the presence of both pectinase inhibitors ensured a broader spectrum of disease resistance. Conversely, the PGIP and TAXI-HI combination contributed to further improvement of Fusarium head blight (FHB) resistance, probably because these inhibitors target the activity of different types of CWDEs, i.e., PGs and xylanases. Worth mentioning, the reduction of FHB symptoms is accompanied by a reduction of deoxynivalenol accumulation with a foreseen great benefit to human and animal health.

Rapid methane hydrate formation to develop a cost effective large scale energy storage system - Veluswamy, Hari Prakash; Wong, Alison Jia Hui; Babu, Ponnivalavan; Kumar, Rajnish; Kulprathipanja, Santi; Rangsunvigit, Pramoch; Linga, Praveen (Chemical Engineering Journal, 2016)
Natural gas (NG) is the cleanest burning fossil fuel and its usage can significantly reduce CO2 emissions from power plants. With its widespread use, there is an ever increasing need to develop technologies to store NG on a large scale. NG storage via clathrate hydrates is the best option for a large scale storage system because of its non-explosive nature, mild storage conditions, high volumetric capacity and being an environmentally benign process. In this work, we demonstrate a new method to achieve rapid methane hydrate formation in an unstirred tank reactor configuration (UTR) at moderate temperature and pressure conditions employing tetrahydrofuran (THF) as a promoter. For the first time, THF is reported to act both as a thermodynamic and an excellent kinetic promoter for methane hydrate formation. We demonstrate a multi-scale experimental validation of our method to a volumetric sample scale-up factor of 120 and internal reactor diameter scale-up factor of 10. Further, new insights on the dissociation behavior of the hydrates are reported. There is a competitive edge for storing NG via clathrate hydrates compared to compressed natural gas storage both in terms of cost and safety. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Energy storage; Enhanced kinetics; Gas hydrates; Natural gas storage; Tetrahydrofuran; Unstirred tank reactor

Role of primary and secondary surfactant layers on the thermal conductivity of lauric acid coated magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (Journal of Physical Chemistry C, 2016)
Lauric (dodecanoic) acid coated magnetite nanoparticles with different amounts of primary and secondary surfactant layers on the surface of the nanoparticles have been synthesized. Two sets of the surfactant coated nanoparticles are prepared; one with a comparable amount of primary surfactant and the other with a comparable amount of secondary surfactant. Nanofluids are prepared by dispersing the surfactant coated nanoparticles in toluene. Stability of the nanofluids is found to decrease with increasing amount of secondary surfactant on the surface of the nanoparticles, due to the increased hydrophilic nature of the particles in the nonpolar solvent. Thermal conductivity and viscosity of the nanofluids are found to increase with increasing amount of the secondary surfactant layer on the surface of the nanoparticles. The enhanced thermal conductivity for fluids with particles having a larger amount of secondary surfactant is ascribed to the lower dispersibility of the particles in toluene due to the exposure of the acid group of the surfactant to the hydrophobic solvent, leading to aggregation of the particles. Only a small increase in the thermal conductivity is observed for fluids with a larger amount of primary surfactant on the surface of the nanoparticles due to the increased dispersibility owing to the large number of hydrophobic tail groups of the surfactant. A larger enhancement in the thermal conductivity is observed in the presence of a small magnetic field for the fluids containing particles with a lower amount of the secondary surfactant. The overall results suggest that the thermal conductivity of the nanofluids depend on the amount and nature of the primary and secondary surfactants on the dispersed particles which in turn determine the interaction between the base fluid and the surfactant and therefore the dispersibility and stability of the nanofluids.

Role of Rhamnolipid: A biosurfactant in methane gas hydrate formation kinetics - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Singh, Anil Kumar; Kumar, Pushpendra; Balomajumder, Chandrajit; Laik, Sukumar (Proceedings of The First International Conference on Recent Advances in Bioenergy Research, 2016)
Naturally occurring methane gas hydrate is a vast source of methane gas which is trapped in crystalline ice-like structure present in permafrost regions and under the sea in outer continental margins. It is purposed that total amount of carbon in the form of methane hydrates is almost twice the carbon content in all the fossil fuel reserves put together, and hence these are supposed to be the future potential energy resource. This paper investigates the laboratory investigations on effect of a biosurfactant rhamnolipid on methane hydrate formation kinetics. Rhamnolipid was produced by Pseudomonas aeruginosa strain A11. The presence of P. aeruginosa has been reported in Gulf of Mexico gas hydrate samples. Biosurfactant reduced the surface tension of water from 72 to 36 mN/m with CMC of 70 mg/L. The biosurfactant dose is studied at two different concentrations in the solution at 100 and 1000 ppm. Kinetic of hydrate formation and growth is compared at 0, 100, and 1000 ppm of rhamnolipid showing that rhamnolipid acts as a hydrate promoter at these concentrations. Thus, small dosages of rhamnolipids produced by P. aeruginosa strain A11 must clearly affect the gas hydrate formation kinetics in natural sites (as in Gulf of Mexico).
Keywords: Induction time; methane hydrate; Potential energy resource; Pseudomonas aeruginosa; Rhamnolipid

Selective detection of Fe3+, Cr3+ and Cu2+ in water using highly luminescent Gd2O3:Eu3+ nanoparticles - Ghosh, Debasish; Luwang, Meitram Niraj (Journal of Luminescence, 2016)
Rod shaped Eu3+ doped Gd2O3 nanoparticles were synthesised by a simple wet-chemical method followed by high temperature heating at 700 degrees C. The nanoparticles were characterised by X-ray diffraction (XRD), infra-red (IR), transmission electron microscopy (TEM), x-ray photonelectron spectroscopy (XPS), photoluminescence (PL) studies and lifetime measurement. The particles show strong host sensitised luminescence in water. Luminescence in water is selectively quenched by Fe3+, Cr3+ and Cu2+ ions. This luminescence quenching phenomenon has been utilised to detect metal ions in synthetic water and environmental water samples. Results obtained by luminescence quenching for environmental water samples are in good agreement with the results obtained from inductively coupled plasma atomic emission spectroscopy (ICP-AES) study. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Detection; Luminescence; Nanoparticles; Quenching; Sensitization

Simple, phosphine free, reusable Pd(II)-2,2 `-dihydroxybenzophenone-SBA-15 catalyst for arylation and hydrogenation reactions of alkenes - Lazar, Anish; Vinod, Chathakudath P.; Singh, Anand Pal (New Journal of Chemistry, 2016)
An efficient, simple, phosphine and co-catalyst free C-C coupling reaction heterogeneous catalyst via a post grafting method is developed and reported. A covalently anchored phosphine free Pd(II) based 2,2'-dihydroxybenzophenone (DHBP) complex over organofunctionalized SBA-15 has been synthesized by the reaction between aminofunctionalized SBA-15 (NH(2)SBA-15) and a 2,2'-dihydroxybenzophenone (DHBP) ligand, and further complexation with Pd(II)Cl-2 to get Pd(II)-DHBP@ SBA-15. The synthesized catalysts were characterized by elemental analysis, XRD, N-2 sorption analyses, TG, DTA, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. The synthesized catalysts were screened in arylation (Heck reactions) and hydrogenation reactions of alkenes, and the results show that Pd(II)-DHBP@ SBA-15 exhibits high conversion and selectivity towards arylation and hydrogenation reactions of alkenes with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity.

Single SnO2 Nanowire: field emission investigations - Joshi, D.; Joag, Dilip S.; Mulla, Imtiaz S.; Late, Dattatray J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The present work deals with the field emission study on multiple SnO2 nanowires synthesized by simple thermal evaporation method. For the realistic analysis of the Fowler Nordheim plot of the semiconducting SnO2, field emission behavior of a single nanowire is studied. A relevant model explaining the field emission mechanism from the single SnO2 nanowire is also proposed by the authors.
Keywords: SnO2 nanowire

Situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.

SnS2 nanoflakes for efficient humidity and alcohol sensing at room temperature - Bharatula, Lakshmi Deepika; Erande, Manisha B.; Mulla, Imtiaz S.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report a one step facile hydrothermal synthesis of layered SnS2 nanoflakes. The as-synthesized nanosheets are characterized using X-ray diffraction, Raman spectroscopy and Transmission Electron Microscopy (TEM). The humidity sensing behavior of SnS2 nanoflake sensor device were investigated in the range of 11-97% of relative humidity (RH) at room temperature. The response time of similar to 85 s and recovery time of similar to 6 s were observed for the SnS2 nanoflake based humidity sensor. A maximum sensitivity of 11.300% is recorded. We also investigate the SnS2 nanoflake based alcohol sensing properties towards methanol, ethanol and iso-propyl alcohol. An exclusive selectivity towards methanol with a response of 1580 is shown as compared to other analytes. The response time of similar to 67 s and recovery time of just 5 s were observed for the SnS2 nanoflake based methanol sensor.

Spatially branched CdS-Bi2S3 heteroarchitecture: single step hydrothermal synthesis approach with enhanced field emission performance and highly responsive broadband photodetection - Bankar, Prashant K.; Pawar, Mahendra S.; Pawbake, Amit S.; Warule, Sambhaji S.; Late, Dattatray J.; More, Mahendra A. (RSC Advances, 2016)
This report explores the controlled hierarchical synthesis of CdS nanostructure branches on Bi2S3 nanorod cores via a facile single step hydrothermal route. Morphological and structural studies reveal the formation of CdS-Bi2S3 heteroarchitecture with excellent stoichiometry between the constituent elements. The growth of CdS over Bi2S3 strongly depends on optimization of the reaction conditions, especially low PVP concentration. Furthermore, the as-synthesized CdS-Bi2S3 heteroarchitecture demonstrates multifunctionality in field emission and photoresponse. Interestingly, the CdS-Bi2S3 heteroarchitecture shows enhanced field emission properties such as low turn-on field (similar to 1.8 V mu m(-1) for 10 mu A cm(2)), high emission current density and better current stability in comparison to Bi2S3 and other nanostructures. The as-synthesized CdS-Bi2S3 heteroarchitecture exhibits considerable response and recovery times, similar to 207 ms and 315 ms, respectively in comparison to bare Bi2S3 nanostructures (similar to 655 ms and 678 ms). The present results demonstrate CdS-Bi2S3 heteroarchitecture as a potential candidate for future optoelectronic device applications.

Streptomyces lonarensis sp nov., isolated from lonar lake, a meteorite salt water lake in India - Sharma, Trupti K.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Shinde, Vidhya K.; Zhan, Jing; Li, Wen-Jun; Rele, Meenakshi V.; Dastager, Syed Gulam; Kumar, Lalitha Sunil (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2016)
A novel alkaliphilic actinomycete, strain NCL716(T), was isolated from a soil sample collected from the vicinity of Lonar Lake, an alkaline salt water meteorite lake in Buldhana district of Maharashtra State in India. The strain was characterised using a polyphasic taxonomic approach which confirmed that it belongs to the genus Streptomyces. Growth was observed over a pH range of 7-11 at 28 A degrees C. The cell wall was found to contain ll-diaminopimelic acid and traces of meso-diaminopimelic acid. The major fatty acid components were identified as iso-C-16:0 (46.8 %), C-17:1 (12.4 %), anteiso-C-15:0 (5.1 %) and anteiso-C-17:1 (4.8 %). The major polar lipids were identified as diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylinositol. The major menaquinones were determined to be MK-9 (H-6) (70.3 %), MK-9 (H-4) (15.5 %) and MK-9 (H-8) (7.2 %). The G+C content of the DNA of the type strain was determined to be 71.4 mol %. The 16S rRNA gene sequence has been deposited in GenBank with accession number FJ919811. Although the 16S rRNA gene sequence analysis revealed that strain NCL716(T) shares > 99 % similarity with that of Streptomyces bohaiensis strain 11A07(T), DNA-DNA hybridization revealed only 33.2 +/- A 3.0 % relatedness between them. Moreover, these two strains can be readily distinguished by some distinct phenotypic characteristics. Hence, on the basis of phenotypic and genetic analyses, it is proposed that strain NCL716(T) represents a novel species of the genus Streptomyces, for which the name Streptomyces lonarensis sp. nov., is proposed. The type strain is NCL 716(T) (=DSM 42084(T) = MTCC 11708(T) = KCTC 39684(T)).
Keywords: Alkaliphile; DDH analysis; Polyphasic taxonomy; Streptomyces lonarensis sp nov.

Studies of synergy between metal-support interfaces and selective hydrogenation of HMF to DMF in water - Goyal, Reena; Sarkar, Bipul; Bag, Arijit; Siddiqui, Nazia; Dumbre, Deepa K.; Lucas, Nishita; Bhargava, Suresh Kumar; Bordoloi, Ankur (Journal of Catalysis, 2016)
Metal-support interfaces play a very important role in heterogeneous catalysis. The interfacial interactions not only are responsible for stabilizing the necessary oxidation state to facilitate the reaction but also enhance the stability of the catalyst system. Nano dispersion of Ni on mesoporous nitrogen-rich carbon material has been achieved using two different synthesis methods. It was observed that nickel (0) gets stabilized by strong interfacial interaction with the nitrogen atoms of the support material, and the material was found to be very economic and efficient for the conversion of HMF to DMF in aqueous medium. The material shows >= 99% conversion to 5-(hydroxymethyl) furfural (HMF) within 6 h of reaction with 98.7% DMF selectivity. A unique correlation between synthesis methods and particle sizes with catalytic performance has been observed for these newly developed materials. Furthermore, a DFT calculation has been performed to predict the reaction mechanism. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: biofuels; Biomass; Hydrogenation; mesoporous carbon; Ni-CNx

Surface chemical bonds, surface-enhanced Raman scattering, and dielectric constant of SiO2 nanospheres in-situ decorated with Ag-nanoparticles by electron-irradiation - Phatangare, A. B.; Dhole, S. D.; Dahiwale, S. S.; Mathe, V. L.; Bhoraskar, S. V.; Late, Dattatray J.; Bhoraskar, V. N. (Journal of Applied Physics, 2016)
Nanostructures of dielectric materials decorated with metal nanoparticles are of great scientific interest; however, the involved synthesis methods are complicated and require multistep chemical processing, including functionalization of the dielectric surfaces. In the present work, without chemical processes, silver nanoparticles of average sizes in the range of 11 to 15 nm were in-situ synthesized and decorated on SiO2 nanospheres in a single step process by irradiating a solution (AgNO3-polyvinylpyrrolidone (PVP)-SiO2 nanospheres) with 6 MeV electrons at 1.5 x 10(15) e(-)/cm(2), 3.0 x 10(15) e(-)/cm(2), and 4.5 x 10(15) e(-)/cm(2) fluences. The electron irradiated solutions were characterized with different surface and other techniques. The results revealed that the SiO2 nanospheres were uniformly decorated with Ag nanoparticles, and the prominent chemical bonds involved were Ag-O, Si-O-Ag, and Si-Ag. Moreover, the sizes and the decoration density of Ag nanoparticles could be tailored by varying electron fluence. The Surface-enhanced Raman scattering (SERS) of 4-aminothiophenol (4-ATP) solutions was studied using substrates in the form of thin coatings of the solutions of Ag-decorated SiO2 nanospheres. The appearance of the characteristic SERS peaks of both 4-ATP and 4, 4'-dimercaptoazobenzene (4, 4'-DMAB) in Raman spectra confirmed the conversion of a fraction of 4-ATP into 4, 4'-DMAB in the presence of Ag nanoparticles. Composites in the form of thin films were synthesized from the mixture solutions of PVP and Ag-decorated SiO2 nanospheres. The dielectric constant of each thin film was higher as compared to polymers, and could be tailored by varying electron fluence used for decorating Ag nanoparticles. Published by AIP Publishing.

Surface modification of aligned CdO nanosheets and their enhanced field emission properties - Bagal, Vivekanand S.; Patil, Girish P.; Deore, Amol B.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (RSC Advances, 2016)
Porous aligned CdO nanosheets were grown on a cadmium (Cd) substrate by the simple and cost effective method of thermal annealing. Further, decoration of gold (Au) nanoparticles on the porous aligned CdO nanosheets (specimen A) was achieved by coating with a Au thin film and subsequent annealing treatment. The average diameters of decorated Au nanoparticles were found to be 15 nm, 21 nm and 28 nm for the Au thin films with 20 s, 40 s and 60 s (specimens B, C, and D) coating times. Detailed characterizations, such as structural and morphological analysis of porous CdO nanosheets and Au/CdO nanocomposite (Au decorated porous CdO nanosheets), have been carried out using a Field Emission Scanning Electron Microscope (FESEM), X-ray diffraction (XRD) and a Transmission Electron Microscope (TEM). Field emission studies of specimens A, B, C and D were carried out in the planar diode configuration. Turn-on fields of 1.9 V mu m(-1), 1.1 V mu m(-1), 2.4 V mu m(-1) and 2.8 V mu m(-1) have been found for the emission current density of 10 RA cm(-2) for specimens A, B, C and D, respectively. The observed low turn -on field of specimen B (Au diameter of 15 nm) was found to be superior to other semiconducting nanostructures reported in the literature. The field emission current stability over a period of 3 h at the preset current density of 1 RA cm(-2) is found to be excellent for all specimens. To the best of our knowledge, field emission studies along with surface modification of porous aligned CdO nanosheets have not been reported in the literature. The simple synthesis route, facile surface modification and the superior field emission results make the present emitter very suitable for micro/nano electronic devices.

Surface tailored PS/TiO2 composite nanofiber membrane for copper removal from water - Wanjale, Santosh; Birajdar, Mallinath S.; Jog, Jyoti Prakash; Neppalli, Ramesh; Causin, Valerio; Karger-Kocsis, Jozsef; Lee, Jonghwi; Panzade, Prasad (Journal of Colloid and Interface Science, 2016)
Polystyrene (PS)/TiO2 composite nanofiber membranes have been fabricated by electrospinning process for Cu2+ ions removal from water. The surface properties of the polystyrene nanofibers were modulated by introducing TiO2 nanoparticles. The contact angle of the PS nanofiber membrane was found to be decreased with increasing concentration of TiO2, depicted enhanced hydrophilicity. These membranes were highly effective in adsorbing Cu2+ ions from water. The adsorption capacity of these membranes was found to be 522 mg/g, which is significantly higher than the results reported by other researchers. This was attributed to enhanced hydrophilicity of the PS/TiO2 composite nanofiber membranes and effective adsorption property of TiO2 nanoparticles. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: electrospinning; Metal ion adsorption; Nanofiber; TiO2; Water treatment/purification

Sustainable Iron-catalyzed direct imine formation by acceptorless dehydrogenative coupling of alcohols with amines - Jaiswal, Garima; Landge, Vinod Gokulkrishna; Jagadeesan, Dinesh; Balaraman, Ekambaram (Green Chemistry, 2016)
The Acceptorless Dehydrogenative Coupling (ADC) of alcohols with amines is reported using a heterogeneous Fe-catalyst. The reaction operates under mild conditions with the liberation of dihydrogen and water as the byproducts. The developed ADC strategy is simple, efficient, exhibits wide functional group tolerance and can be scaled up. The present catalytic approach possesses a dual role; acting as a catalyst as well as being magnetically separable. The sustainable reuse of a heterogeneous iron catalyst is also shown.

Synthesis and characterization of FeTiO3 ceramics - Gambhire, Anil B.; Lande, Machhindra K.; Rathod, Sandip B.; Arbad, Balasaheb R.; Vidhate, Kaluram N.; Gholap, Ramakrishna S.; Patil, Kashinath R. (Arabian Journal of Chemistry, 2016)
Nanocrystalline FeTiO3 ceramics powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 600 degrees C for 2 h in an air. The results revealed that a pure hexagonal phase of FeTiO3 could be obtained at low temperature, 600 degrees C. The phase evolution of FeTiO3 was investigated by X-ray diffraction patterns (XRD), Fourier-transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). Particle size and morphology was studied by transmission electron microscopy (TEM). (C) 2011 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Electron microscopy; hexagonal phase; Nanoparticles; sol-gel process; Ti-O bond

Synthesis and characterization of superhydrophobic-superoleophilic surface - Mahadik, Satish A.; Pedraza, Fernado D.; Relekar, Brahmanand P.; Parale, Vinayak. G.; Lohar, Gaurav M.; Thorat, Sagar S. (Journal of Sol-Gel Science and Technology, 2016)
The binary superhydrophobic-superhydrophilic surface has been successfully achieved by a combination of nanoscale texture roughness on micro-textured cotton thread network by layer-by-layer deposition method through the single-step sol-gel route. Furthermore, microstructures with improved wettability were produced, in which silica nanotextures were grown without modifying the chemical method to form superoleophilic and superhydrophobic networks. A superoleophilic surface (oil contact angle 0A degrees) and a superhydrophobic coated cotton fabric with surface free energy of gamma (total) = 13. 23 +/- A 0.37 mJ m(-2) (water contact angle of 167 +/- A 1A degrees and a small sliding angle of 4 +/- A 1A degrees) were successfully obtained. The results were exemplified here by the creation of immiscible oils separation membranes, and the innumerable applications of this technology also include self-cleaning fabrics, antistaining fabrics, water purification, and antiwetting fabrics for military applications.
Keywords: contact angle; Layer-by-layer deposition method; sol-gel processing; Superhydrophobic-superoleophilic surface

Synthesis and self-assembly of dumbbell shaped ZnO sub-micron structures using low temperature chemical bath deposition technique - Borade, P.; Joshi, K. U.; Gokarna, A.; Lerondel, G.; Walke, P.; Late, Dattatray J.; Jejurikar, S. M. (Materials Chemistry and Physics, 2016)
We report well dispersed horizontal growth of ZnO sub-micron structures using simplest technique ever known i.e. chemical bath deposition (CBD). A set of samples were prepared under two different cases A) dumbbell shaped ZnO grown in CBD bath and B) tubular ZnO structures evolved from dumbbell shaped structures by dissolution mechanism. Single phase wurtzite ZnO formation is confirmed using X-ray diffraction (XRD) technique in both cases. From the morphological investigations performed using scanning electron microscopy (SEM), sample prepared under case A indicate formation of hex bit tool (HBT) shaped ZnO crystals, which observed to self-organize to form dumbbell structures. Further these microstructures are then converted into tubular structures as a fragment of post CBD process. The possible mechanism responsible for the self-assembly of HBT units to form dumbbell structures is discussed. Observed free excitonic peak located at 370 nm in photoluminescence (PL) spectra recorded at 18 K indicate that the micro/nanostructures synthesized using CBD are of high optical quality. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy (STEM; Microstructure; Nanostructures; Optical properties; Photoluminescence spectroscopy; Raman spectroscopy and scattering; TEM and SEM)

Synthesis of Au@Ni bimetallic core shell nanoparticle and nanochains in soyabean oil and their catalytic hydrogenation reactions - Bharathan, Vysakh A.; Yadukiran, V.; Lazar, Anish; Singh, Anand. P.; Vinod, Chathakudath P. (ChemistrySelect, 2016)
Synthesis of Au@Ni bimetallic core shell nanostructures using commercially available soya bean oil as the solvent through a sequential reduction strategy is reported. The energy efficiency and economic viability comes from the much milder temperatures and replacement of expensive and environmentally hazardous solvents like long chain organic amines and acids previously reported for synthesis. Thus, core shell nanoparticles having size regime of 10-15 nm with an excellent control over the nickel shell thickness (2 nm) over the gold core (8-10 nm) and Au@Ni nanochains is achieved. The synthesized materials are demonstrated to synergistically catalyze hydrogenation of nitro and C-C multiple bonds with much better efficiency as compared to individual nanoparticle counterparts.
Keywords: Bimetallic nanoparticles; Gold catalysis; hydrogenation reactions; synergistic effects

Synthesis of Ni-doped ZnO nanostructures by low-temperature wet chemical method and their enhanced field emission properties - Rana, Amit Kumar; Bankar, Prashant; Kumar, Yogendra; More, Mahendra A.; Late, Dattatray J.; Shirage, Parasharam M. (RSC Advances, 2016)
In this study, we report an enhancement in the field emission (FE) properties of ZnO nanostructures obtained by doping with Ni at a base pressure of similar to 1 x 10(-8) mbar, which were grown by a simple wet chemical process. The ZnO nanostructures exhibited a single-crystalline wurtzite structure up to a Ni doping level of 10%. FESEM showed a change in the morphology of the nanostructures from thick nanoneedles to nanoflakes via thin nanorods with an increase in the Ni doping level in ZnO. The turn-on field required to generate a field emission (FE) current density of 1 mu A cm(-2) was found to be 2.5, 2.3, 1.8 and 1.7 V mu mcm(-2) for ZnO (Ni0%), ZnO (Ni5%), ZnO (Ni7.5%) and ZnO (Ni10%), respectively. A maximum current density of similar to 872 mu A cm(-2) was achievable, which was generated at an applied field of 3.1 V mu m cm(-2) for a Ni doping level of 10% in ZnO. Long-term operational current stability was recorded at a preset value of 5 mA for a duration of 3 h and was found to be very high. The experimental results indicate that Ni-doped ZnO-based field emitters can open up many opportunities for their potential use as an electron source in flat panel displays, transmission electron microscopy, and the generation of X-rays. Thus, the simple low-temperature (similar to 80 degrees C) wet chemical synthesis approach and the robust nature of the ZnO nanostructure field emitter can provide prospects for the future development of cost-effective electron sources.

Temperature dependent raman spectroscopy and sensing behavior of few layer SnSe2nanosheets - Pawbake, Amit S.; Date, Abhijit; Jadkar, Sandesh R.; Late, Dattatray J. (Chemistryselect, 2016)
Two- dimensional (2D) tin diselenide (SnSe2) nanosheets were synthesized using solvothermal route in one step and perform its humidity sensing, photo sensing and temperature dependant Raman spectroscopy studies. The sensor devices based on few layer SnSe2 nanosheets were prepared and which shows fast response as well as recovery time along with good long-term stability and high sensitivity. The photo sensing behavior shows the typical response time and recovery time to be similar to 310 ms and similar to 340 ms respectively for visible light illumination. The room temperature humidity sensing behaviors were studied in the range of 11-97% relative humidity (RH). The ob-served sensitivity of similar to 81% with response time of similar to 74 sec and recovery time of similar to 30 sec were calculated for the few layer SnSe2 nanosheets based humidity sensor. The humidity sensing results confirms the high stability of the device even after six months of time. The temperature dependent Raman spectroscopy investigation in the range of 80 K to 593 K were carried out which shows the negative temperature coefficient and softening of Raman modes as we increases the temperature. The softening modes of SnSe2 nanosheets due to temperature were explained on the basis of a double resonance process which is more active in an atomically thin sample.

Temperature dependent Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets - Pawbake, Amit S.; Erande, Manisha B.; Jadkar, Sandesh R.; Late, Dattatray J. (RSC Advances, 2016)
The present investigation deals with temperature dependant Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets. The temperature dependent study illustrates that softening of the A(g)(1), B-2g and A(g)(2) modes occurs as the temperature increases from 78 K to 573 K. The calculated temperature coefficients for the A(g)(1), B-2g and A(g)(2) modes were found to be -0.028 cm(-1) K-1, -0.028 cm(-1) K-1 and -0.018 cm(-1) K-1 respectively. The observed phenomenon can be utilized for characterizing other emerging two-dimensional inorganic layered materials with atomic thickness.

Temperature-dependent phonon shifts in atomically thin MoTe2 nanosheets - Late, Dattatray J. (Applied Materials Today, 2016)
The present investigations deal with temperature-dependent Raman spectroscopy of bi-layer and few-layer molybdenum telluride (MoTe2) nanosheets prepared by micromechanical exfoliation method on a 300 nm SiO2/Si substrate. The temperature-dependent Raman spectroscopy was carried out using 633 nm laser excitation over the wider temperature range of 123-523 K. The temperature-dependent study illustrates the softening of A(1g), E-2g(1), and B-2g modes as temperature increases from 123 K to 523 K. The calculated temperature coefficients for A(1g), E-2g(1) and B-2g modes of the bi-layer MoTe2, nanosheet sample were found to be -0.00911 cm(-1) K-1, -0.01297 cm(-1) K-1 and -0.0159 cm(-1) K-1,respectively. For few-layer MoTe2 nanosheet sample, the temperature coefficient values were found to be -0.0113 cm(-1) K-1 (A(1g)), -0.0129 cm(-1) K-1 (E-2g(1)) and -0.0149 cm(-1) K-1 (B-2g), respectively. The present work highlights the temperature-dependent lattice vibration consequence of 2D MoTe2 nanosheet, which can be fundamentally pertinent in other promising and emerging 2D ultrathin layer and heterostructured materials to be used in future optoelectronic and nanoelectronic devices. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Layered material; MoTe2; Phonon vibration; Raman spectroscopy; thermal effect

Is there any real effect of low dimensional morphologies towards light harvesting? a case study of Au-rGO-TiO2 nanocomposites - Melvin, Ambrose A.; Bharad, Pradnya A.; Illath, Kavya; Lawrence, Meenu P.; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Nanotube and nanosheet morphologies have been celebrated for their electron transport properties. Present work has been explored to exploit the same by combining 1D TiO2 nanotube (1D-TN) with 2D reduced graphene oxide (rGO) along with nano gold for visible light sensitization for photocatalytic H2 generation under one sun condition and visible light (λ≥ 400 nm). Vertical and horizontal electron transport in 1D-TN and rGO, respectively, is combined with the visible light absorption capability of Au nanoparticle. H2 yield (HY) varies between 100 and 655 µmol/g.h with an apparent quantum yield between 0.45 and 3.2 %, respectively, depending on Au/rGO/1D-TN preparation method and reaction conditions. It has been demonstrated that interfacial contact between rGO/1D-TN and Au is crucial for high photocatalytic HY. Preparation method influences charge utilization, and hence HY, to a large extent. Nonetheless, the maximum HY reported in the present work is just comparable to HY reported in literature with the most commonly found spherical morphology, and this leads to a question of, is there any real influence of 1D and/or 2D materials, particularly, towards light harvesting applications?

Thickness tunable transport in alloyed WSSe field effect transistors - Karande, Shruti D.; Kaushik, Naveen; Narang, Deepa S.; Late, Dattatray; Lodha, Saurabh (Applied Physics Letters, 2016)
We report the field effect transistor characteristics of exfoliated transition metal dichalcogenide alloy tungsten sulphoselenide. WSSe is a layered material of strongly bonded S-W-Se atoms having weak interlayer van der Waals forces with a significant potential for spintronic and valleytronic applications due to its polar nature. The X-ray photoelectron spectroscopy measurements on crystals grown by the chemical vapor transport method indicate a stoichiometry of the form WSSe. We report flake thickness tunable transport mechanism with n-type behavior in thin flakes (<= 11 nm) and ambipolarity in thicker flakes. The devices with flake thicknesses of 2.4 nm-54.8nm exhibit a maximum electron mobility of similar to 50 cm(2)/V s along with an I-ON/I-OFF ratio > 10(6). The electron Schottky barrier height values of 35 meV and 52meV extracted from low temperature I-V measurements for 3.9 nm and 25.5 nm thick flakes, respectively, indicate that an increase in hole current with thickness is likely due to lowering of the bandgap through an increase in energy of the valence band maximum. Published by AIP Publishing.

Unravelling the mechanism of electrochemical degradation of PANI in supercapacitors: achieving a feasible solution - Sekar, Pandiaraj; Anothumakkool, Bihag; Vijayakumar, Vidyanand; Lohgaonkar, Apurva; Kurungot, Sreekumar (Chemelectrochem, 2016)
Herein, we have investigated the mode of electrochemical degradation of polyaniline (PANI) when it was utilized as electrodes for supercapacitors. The PANI-based electrodes in supercapacitor devices were biased at a constant potential of 0.80 V, and the performance characteristics and property changes were carefully investigated as a function of the difference in the polarity of the electrodes. Subsequent to this, the analysis of the individual electrodes [positive (POS-PANI) and negative (NEG-PANI)] shows that the degradation mainly occurs at POS-PANI in comparison to NEG-PANI. Moreover, NEG-PANI retains a maximum capacitance of 510 Fg(-1), with a low charge-transfer resistance (R-CT) of 1.84 Omega and similar redox behavior in comparison to the fresh PANI (f-PANI). In contrast to this case, POS-PANI shows significant loss in capacitance (250 Fg(-1)) and increase in R-CT (3.5 Omega) with a disappearance of the characteristic redox behavior normally displayed by PANI. Furthermore, the drastic drop in the electrical conductivity for POS-PANI (1.2 Scm(-1)) compared to f-PANI (3.4 Scm(-1) and NEG-PANI (2.4 Scm(-1)) shows that the degradation of PANI occurs mainly at the anode (POS-PANI) and, thus, contributes to reduce the net performance of the cell. Hence, to ensure this potential-induced degradation of PANI in supercapacitors and also to promote the system stability, we made an asymmetric supercapacitor (ASC) by keeping PANI as a negative electrode and using carbon as a positive electrode. The derived system is found to display stable capacitance behavior before and after the potential application, in contrast to the ASC fabricated by using conventional method, that is, by keeping PANI as the positive electrode and carbon as the negative electrode. Furthermore, the durability analysis of the prototype solid-state ASC shows an enhanced durability of 27000 cycles with excellent columbic efficiency. The findings of the present study will be helpful in the development of highly stable supercapacitors and other similar energy systems when a material like PANI should be utilized for the electrode applications.
Keywords: asymmetric supercapacitors; cycle stability; electrochemical degradation; polarization; redox chemistry

Wide band gap and conducting tungsten carbide(WC) thin films prepared by hot wire chemical vapor deposition(HW-CVD) method - Pawbake, Amit; Waykar, Ravindra; Jadhavar, Ashok; Kulkarni, Rupali; Waman, Vaishali; Date, Abhijit; Late, Dattatray J.; Pathan, Habib; Jadkar, Sandesh (Materials Letters, 2016)
In this letter, we report synthesis of tungsten carbide (WC) thin films having wide band gap(3.22-3.3 eV) with high electrical conductivity (80-1260 S/cm) by HW-CVD using heated using heated W filament and Tetra-fluoro-methane (CF4) gas. Formation of WC was confirmed by low angle XRD, Raman spectroscopy and x-ray photoelectron spectroscopy. UV-Visible spectroscopy analysis revealed that the synthesized films have high transmission at wavelength 500 nm. Electrical properties measured using Hall measurement show that these films are semiconductor. The obtained results imply that the growth of WC thin films is mainly from the atomic species(W and C) evaporated from the hot filament. The HW-CVD opens a novel route to synthesize wide band gap and conducting WC at a cost-efficient way for DSSCs and hydrogen evolution reaction (HER). (C) 2016 Elsevier B. V. All rights reserved.

Anti-microbial activity of chrysomycin a produced by streptomyces sp. against mycobacterium tuberculosis - Balaji, Muralikrishnan; Dan, Vipin Mohan; Joseph, Vinodh; Jamsheena, Vellekkatt; Ramachandran, Ranjit; Thomas, Sabu; Dastager, Syed Gulam; Kumar, K. Santhosh; Lankalapalli, Ravi Shankar; Kumar, R. Ajay (RSC Advances, 2017)
Limited efficacy of the BCG (Bacillus Calmette–Guérin) vaccine against adult tuberculosis and the emergence of resistance to existing anti-tuberculosis drugs compel discovery of novel antibiotics against Mycobacterium tuberculosis. Actinomycetes are still an attractive platform for the discovery of new antimicrobials, especially from untapped natural hotspots, despite the belief that they are an exhausted resource after repeated re-discoveries. Herein we report the isolation and identification of chrysomycin A from an actinomycete isolated from a coastal area in Kerala. We show for the first time that it has antimycobacterial activity. It was found to be bactericidal to planktonic and intracellular M. tuberculosis with an MIC of 3.125 μg mL⁻¹; it is non-hemolytic and has negligible cytotoxicity. The actinomycete that produces chrysomycin A was found to be a Streptomyces sp. through 16S rRNA gene sequencing.

Assessing therapeutic potential of molecules: molecular property diagnostic suite for tuberculosis - Gaur, A. S.; Bhardwaj, A.; Sharma, A.; John, L.; Vivek, M. R.; Tripathi, N.; Bharatam, P. V.; Kumar, R.; Janardhan, S.; Mori, A.; Banerji, A.; Lynn, A. M.; et al. (Journal of Chemical Sciences, 2017)
Abstract: Molecular Property Diagnostic Suite (MPDS TB) is a web tool (http://mpds.osdd.net) designed to assist the in silico drug discovery attempts towards Mycobacterium tuberculosis (Mtb). MPDS TB tool has nine modules which are classified into data library (1–3), data processing (4–5) and data analysis (6–9). Module 1 is a repository of literature and related information available on the Mtb. Module 2 deals with the protein target analysis of the chosen disease area. Module 3 is the compound library consisting of 110.31 million unique molecules generated from public domain databases and custom designed search tools. Module 4 contains tools for chemical file format conversions and 2D to 3D coordinate conversions. Module 5 helps in calculating the molecular descriptors. Module 6 specifically handles QSAR model development tools using descriptors generated in the Module 5. Module 7 integrates the AutoDock Vina algorithm for docking, while module 8 provides screening filters. Module 9 provides the necessary visualization tools for both small and large molecules. The workflow-based open source web portal, MPDS TB 1.0.1 can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. Graphical Abstract: SYNOPSIS: A web-based MPDS TB Galaxy tool is developed for assessing therapeutic potential of molecules. MPDS TB is categorized into Data Library, Data Processing and Data Analysis. It can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. [Figure not available: see fulltext.] © 2017, Indian Academy of Sciences.
Keywords: chemical analysis; Chemoinformatics; computational chemistry; Diagnosis; Drug discovery portal; Information analysis; Libraries; Molecular graphics; Molecules; Neglected diseases; Open science; Portals; tuberculosis; Web-based technology; Websites

Binding selectivity of vitamin K3 based chemosensors towards nickel(II) and copper(II) metal ions - Patil, Amit; Lande, Dipali N.; Nalkar, Archana; (Gejji, Shridhar P.; Chakrovorty, Debamitra; Gonnade, Rajesh; Moniz, Tania; Rangel, Maria; Pereira, Eulalia; Salunke-Gawali, Sunita (Journal of molecular Structure, 2017)
The vitamin K3 derivatives 2-methyl-3-[(pyridin-2-ylmethyl)-amino]-1,4-naphthoquinone (M-1), 2-methyl-3-[(pyridin-2-ylethyl)-amino]-1,4-naphthoquinone (M-2), 2-methyl-3-((2-(thiophen-2-yl) methyl)amino)naphthalene-1,4-dione (M-3) and 2-methyl-3-((2-(thiophen-2-yl)ethyl)amino)naphthalene-1,4-dione (M-4) have been synthesized, characterized and studied for their chemosensor abilities towards transition metal ions. Crystal structures of M-1 to M-4 revealed a variety of N-H center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions. Minor variations in such interactions by chemical stimuli such as metal ions, results in change in color that can be visualized by naked eyes. It has been shown that electronic structure and H-1 NMR, vibrational as well as electronic spectra from the density functional theory agree well with the experiments. The metal ion binding in ethanol, ethanol-water and in mild base triethylamine brings forth recognizing ability of M-1 toward Ni2+ whereas M-2 exhibits large sensing ability for Cu2+ ion. Interestingly M-1 display varying metal ion binding specificity in different solvents with the association constant in ethanol being 11,786 M-1 for Ni2+ compared to 9462 M-1 for the Cu2+. A reversal in preferential binding of M-2 with the respective association constants being 4190 M-1 and 6370 M-1 is discernible. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone Molecular-structures; Anthraquinone; Aqueous-solution; Chemosensor; Crystal-structures; Cu(II); Derivatives; DFT; Fluorometric Chemosensors; hydrogen bonding; Naphthoquinone; pi-pi stacking; Recognition; sensors

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2017)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone(A (R))-KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone-KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine-Oxone as an unprecedented catalyst-oxidant combination. [GRAPHICS] .
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

Chickpea-fusarium oxysporum interaction transcriptome reveals differential modulation of plant defense strategies - Upasani, Medha L.; Limaye, Bhakti M.; Gurjar, Gayatri S.; Kasibhatla, Sunitha M.; Joshi, Rajendra R.; Kadoo, Narendra Y.; Gupta, Vidya S. (Scientific Reports, 2017)
Fusarium wilt is one of the major biotic stresses reducing chickpea productivity. The use of wilt-resistant cultivars is the most appropriate means to combat the disease and secure productivity. As a step towards understanding the molecular basis of wilt resistance in chickpea, we investigated the transcriptomes of wilt-susceptible and wilt-resistant cultivars under both Fusarium oxysporum f.sp. ciceri (Foc) challenged and unchallenged conditions. Transcriptome profiling using LongSAGE provided a valuable insight into the molecular interactions between chickpea and Foc, which revealed several known as well as novel genes with differential or unique expression patterns in chickpea contributing to lignification, hormonal homeostasis, plant defense signaling, ROS homeostasis, R-gene mediated defense, etc. Similarly, several Foc genes characteristically required for survival and growth of the pathogen were expressed only in the susceptible cultivar with null expression of most of these genes in the resistant cultivar. This study provides a rich resource for functional characterization of the genes involved in resistance mechanism and their use in breeding for sustainable wilt-resistance. Additionally, it provides pathogen targets facilitating the development of novel control strategies.

Computational strategies to explore antimalarial thiazine alkaloid lead compounds based on an australian marine sponge plakortis lita - Lilly, Aswathy; Jisha, R. S.; Masand, Vijay H.; Gajbhiye, Jayant M.; Shibi, Indira G. (Journal of biomolecular Structure & Dynamics, 2017)
In this work, an attempt was made to propose new leads based on the natural scaffold Thiaplakortone-A active against malaria. The 2D QSAR studies suggested that three descriptors correlate with the anti-malarial activity with an R2 value of 0.814. Robustness, reliability and predictive power of the model were tested by internal validation, external validation, Y-scrambling and Applicability domain analysis. HQSAR studies were carried out as an additional tool to find the sub-structural fingerprints. The CoMFA and CoMSIA models gave Q2 values of 0.813 and 0.647, and R2ncv values of 0.994 and 0.984, respectively. Using the 2D-QSAR equation, the activity values of the seven modified compounds were calculated and it was found that three molecules showed good anti-malarial activity. Molecular docking of the 42 Thiaplakortone-A derivatives with P. falciparum calcium-dependent protein kinase 1 (PfCDPK1) was carried out to find out protein-ligand interactions. Data mining of the bioassay dataset AID: 504850 using the classifier based on Random Forest (RF) of Weka suggested that all of the eight molecules selected and three out of the seven virtual molecules were anti-malarial active. Both the virtual molecules and drug molecules were docked with CYP3A4, indicating that the virtual molecules could metabolize easily. Toxicity studies using Osiris shows that three molecules showed no toxic characters.

Control of polymerization reactors - Schurk, F. J; Deshpande, P. B; Leffew, K. W.; Nadkarni, V. M. (CRC Press, 2017)
This reference and text provides an in-depth description of developments in control techniques and their application to polymerization reactors and offers important introductory background information on polymerization reaction engineering.;Discussing modelling, identification, linear, nonlinear and multivariable schemes, Control of Polymerization Reactors: presents all available techniques that can be used to control reactors properly for optimal performance; shows how to manipulate pivotal variables that affect reactor control; examines methods for deriving dynamic process models to improve reactor efficiency; reviews reactor control problems and points out end-use properties; supplies methods for measuring process variables, and ways to estimate variables that can’t be measured; and explains how single-input, single-output (SISO) strategies can be effectively used for control.;Filled with illustrative examples to clarify concepts, including more than 730 figures, tables and equations, Control of Polymerization Reactors is intended for use as a reference for chemical, process development, process design, research and development, control systems, and polymer engineers; and polymer chemists and physicists; as well as a text for upper-level undergraduate and graduate students in polymerization reactor control courses.

Data on the effect of oral feeding of Arachidonic acid or Docosahexanoic acid on haematopoiesis in mice - Limbkar, K. (Data in Brief, 2017)
Stem cells have peculiar property to self-renew and differentiate. It is important to control their fate in safe and effective ways for their therapeutic use. The mediators of essential polyunsaturated fatty acids (PUFAs) namely Arachidonic acid (AA) and Docosahexanoic acid (DHA) are known to play a role in haematopoiesis via various metabolic pathways [1]. However the direct effect of purified AA or DHA on haematopoiesis has not been well investigated yet. We have reported that oral administration of PUFAs enhanced haematopoiesis in mice [2]. Signaling Leukocyte Antigen Molecule (SLAM) (CD48−CD150+) phenotype consists of pure population of haematopoietic stem cells (HSCs). Herein we observed higher percentage of SLAM (CD48−CD150+) phenotype in the bone marrow (BM) cells of mice fed with AA or DHA compared to PBS fed control mice. Data from engraftment study depicts that BM from AA/DHA-fed mice showed higher absolute number of donor cells in recipient mice compared to control. The enhanced hematopoiesis observed in AA/DHA-fed mice was returned to normal when the mice were kept on normal diet for six weeks (after ten days of oral feeding). We confirmed GCMS (Gas Chromatography-Mass Spectroscopy) retention times of AA and DHA by co-injecting fatty acid extract from AA or DHA fed mice with purified AA or DHA standards respectively. Representative flow cytometry profile of Lin−Sca-1+c-kit+(LSK) cells showed higher expression of CXCR4 protein and ligands of Wnt, Notch1 signaling in BM of AA/DHA-fed mice

Degradation of metaldehyde in water by nanoparticle catalysts and powdered activated carbon - Li, Zhuojun; Kim, Jong Kyu; Chaudhari, Vrushali; Mayadevi, Suseeladevi; Campos, Luiza C. (Environmental Science and Pollution Research, 2017)
Metaldehyde, an organic pesticide widely used in the UK, has been detected in drinking water in the UK with a low concentration (< 1 mu g L-1) which is still above the European and UK standard requirements. This paper investigates the efficiency of four materials: powdered activated carbon (PAC) and carbon-doped titanium dioxide nanocatalyst with different concentrations of carbon (C-1.5, C-40, and C-80) for metaldehyde removal from aqueous solutions by adsorption and oxidation via photocatalysis. PAC was found to be the most effective material which showed almost over 90% removal. Adsorption data were well fitted to the Langmuir isotherm model, giving a q (m) (maximum/saturation adsorption capacity) value of 32.258 mg g(-1) and a K-L (Langmuir constant) value of 2.013 L mg(-1). In terms of kinetic study, adsorption of metaldehyde by PAC fitted well with a pseudo-second-order equation, giving the adsorption rate constant k(2) value of 0.023 g mg(-1) min(-1), implying rapid adsorption. The nanocatalysts were much less effective in oxidising metaldehyde than PAC with the same metaldehyde concentration and 0.2 g L-1 loading concentration of materials under UV light; the maximum removal achieved by carbon-doped titanium dioxide (C-1.5) nanocatalyst was around 15% for a 7.5 ppm metaldehyde solution.

Differential rubisco content and photosynthetic efficiency of rol gene integrated Vinca minor transgenic plant: correlating factors associated with morpho-anatomical changes, gene expression and alkaloid productivity - Verma, Priyanka; Khan, Shamshad Ahmad; Masood, Nusrat; Manika, N.; Sharma, Abhishek; Verma, Neha; Luqman, Suaib; Mathur, Ajay K. (Journal of Plant Physiology, 2017)
Transgenic plants obtained from a hairy root line (PVG) of Vinca minor were characterized in relation to terpenoid indole alkaloids (TIAs) pathway gene expression and vincamine production. The hairy roots formed callus with green nodular protuberances when transferred onto agar-gelled MS medium containing 3.0 mg/l zeatin. These meristematic zones developed into shoot buds on medium with 1.0 mg/l 2, 4-dichlorophenoxyacetic acid and 40 mg/l ascorbic acid. These shoot buds subsequently formed rooted plants when shifted onto a hormone-free MS medium with 6% sucrose. Transgenic nature of the plants was confirmed by the presence of rol genes of the Ri plasmid in them. The transgenic plants (TP) had elongated internodes and a highly proliferating root system. During glass house cultivation TP consistently exhibited slower growth rate, low chlorophyll content (1.02 +/- 0.08 mg/gm fr. wt.), reduced carbon exchange rate (2.67 +/- 0.16 mu mol m(-2) s(-1)), less transpiration rate (2.30 +/- 0.20 mmol m(-2) s(-1)) and poor stomatal conductance (2.21 +/- 0.04 mmol m-2 s(-1)) when compared with non-transgenic population. The activity of rubisco enzyme in the leaves of TP was nearly two folds less in comparison to non-transgenic controls (1.80 milliunits ml(-1) mg protein-1 against 3.61 milliunits ml(-1) mg protein-1, respectively). Anatomically, the TP had a distinct tetarch arrangement of vascular bundles in their stem and roots against a typical ployarched pattern in the non-transgenic plants. Significantly, the transgenic plants accumulated 35% higher amount of total TIAs (3.10 +/- 0.21% dry wt.) along with a 0.03% dry wt. content of its vasodilatory and nootropic alkaloid vincamine in their leaves. Higher productivity of alkaloids in TP was corroborated with more than four (RQ = 4.60 +/- 0.30) and five (RQ = 5.20 +/- 0.70) times over-expression of TIAs pathway genes tryptophan decarboxylase (TDC) and strictosidine synthase (STR) that are responsible for pushing the metabolic flux towards TIAs synthesis in this medicinal herb.

Digestive ripening of Au nanoparticles by multidentate ligands - Sahu, Puspanjali; Shimpi, Jayesh; Lee, Han Ju; Lee, T. Randall; Prasad, Bhagavatula L. V (Langmuir, 2017)
The efficiency of multidentate ligands as digestive ripening agents for the preparation of monodisperse Au nanoparticles was investigated. This systematic investigation was performed using ligands possessing one, two, or three thiol moieties as ligands/digestive ripening agents. Our results clearly establish that among the different ligands, those that are monodentate and the use of temperatures in the range of 60 °C and 120 °C offer the best conditions for digestive ripening. In addition, when digestive ripening was carried out at lower temperatures (e.g., 60 °C), the nanoparticle size increased as the number of thiol groups per ligand increased. However, in the case of ligands possessing two and three thiol moieties when they are heated with polydispersed particles at higher temperatures (120 °C or 180 °C), the etching process dominates, which affects the quality of the nanoparticles in terms of their monodispersity. We conclude that the temperature-dependent strength of the interaction between the ligand headgroup and the nanoparticle surface plays a vital role in controlling the final particle sizes.

Docetaxel-titanate nanotubes enhance radiosensitivity in an androgen-independent prostate cancer model - Mirjolet, C.; Martin, E.; Boudon, J.; Loiseau, A.; Chevrier, S.; Boidot, R.; Oudot, A.; Collin, B.; Joy, P. A.; Millot, N.; Créhange, G. (International Journal of Nanomedicine, 2017)
Around 40% of high-risk prostate cancer patients who undergo radiotherapy (RT) will experience biochemical failure. Chemotherapy, such as docetaxel (DTX), can enhance the efficacy of RT. Multidrug resistance mechanisms often limit drug efficacy by decreasing intracellular concentrations of drugs in tumor cells. It is, therefore, of interest to develop nanocarriers of DTX to maintain the drug inside cancer cells and thus improve treatment efficacy. The purpose of this study was to investigate the use of titanate nanotubes (TiONts) to develop a TiONts-DTX nanocarrier and to evaluate its radiosensitizing in vivo efficacy in a prostate cancer model. In vitro cytotoxic activity of TiONts-DTX was evaluated using an MTS assay. The biodistribution of TiONts-DTX was analyzed in vivo by single-photon emission computed tomography. The benefit of TiONts-DTX associated with RT was evaluated in vivo. Eight groups with seven mice in each were used to evaluate the efficacy of the nanohybrid combined with RT: control with buffer IT injection ± RT, free DXL ± RT, TiONts ± RT and TiONts-DXL ± RT. Mouse behavior, health status and tumor volume were monitored twice a week until the tumor volume reached a maximum of 2,000 mm3. More than 70% of nanohybrids were localized inside the tumor 96 h after administration. Tumor growth was significantly slowed by TiONts-DTX associated with RT, compared with free DTX in the same conditions (P=0.013). These results suggest that TiONts-DTX improved RT efficacy and might enhance local control in high-risk localized prostate cancer.
Keywords: Docetaxel Nanocarrier; nanoparticle; Prostate Cancer; Radiosensitivity; Titanate nanotubes

Drug-triggered self-assembly of linear polymer into nanoparticles for simultaneous delivery of hydrophobic and hydrophilic drugs in breast cancer cells - Palvai, Sandeep; Anandi, Libi; Sarkar, Sujit; Augustus, Meera; Roy, Sudip; Lahiri, Mayurika; Basu, Sudipta (ACS Omega, 2017)
Breast cancer is the most devastating disease among females globally. Conventional chemotherapeutic regimen relies on the use of highly cytotoxic drugs as monotherapy and combination therapy leading to severe side effects to the patients as collateral damage. Moreover, combining hydrophobic and hydrophilic drugs create erratic biodistribution and suboptimal medicinal outcome. Hence, packaging multiple drugs of diverse mechanisms of action and biodistribution for safe delivery into tumor tissues with optimal dosages is indispensable for next-generation breast cancer therapy. To address these, in this report, we describe a unique cisplatin-triggered self-assembly of linear polymer into 3D-spherical sub 200 nm particles. These nano-particles comprise a hydrophobic (paclitaxel) and hydrophilic drug (cisplatin) simultaneously in a single particle. Molecular dynamics simulation revealed hydrophilic-hydrophilic interaction and interchain H-bonding as underlying mechanisms of self-assembly. Confocal microscopy studies evidently demonstrated that these novel nanoparticles can home into lysosomes in breast cancer cells, fragment subcellular nuclei, and prevent cell division, leading to improved breast cancer cell death compared to free drug combination. Moreover, 3D-breast tumor spheroids were reduced remarkably by the treatment of these nanoparticles within 24 h. These dual-drug-loaded self-assembled polymeric nanoparticles have prospective to be translated into a clinical strategy for breast cancer patients.

Electrochemical synthesis of a ternary transition metal sulfide nanosheets on nickel foam and energy storage application - Sahoo, Surjit; Naik, Kusha Kumar; Late, Dattatray J.; Rout, Chandra Sekhar (Journal of Alloys and Compounds, 2017)
We report growth of nickel cobalt sulfide (NCS) ultrathin nanosheets directly on Ni foam substrate by a facile and novel electrodeposition method. The as-prepared NCS sample is used as an electrode material for supercapacitor application due to their large electrochemically active surface area and interconnected nanosheet channels for the facilitation of ion transportation. The NCS nanosheets possess enhanced electrochemical performance in terms of fast and high reversible faradaic reactions characterized by prominent oxidation and reduction peaks. NCS nanosheets showed an ultrahigh specific capacitance of 1712 Fg(-1) at a current density of 1 Ag-1 with excellent cyclic stability. The excellent supercapacitor performance of NCS nanosheets can be attributed to its rich redox reactions as well as high transport rate for both electrolyte ions and electrons. (C) 2016 Elsevier B.V. All rights reserved.

Electrodeposited nickel cobalt manganese based mixed sulfide nanosheets for high performance supercapacitor application - Sahoo, S.; Mondal, R.; Late, D. J.; Rout, C. S. (Microporous and Mesoporous Materials, 2017)
Porous multi component Nickel Cobalt Manganese Sulfide (NCMS) nanosheets have been grown on Ni foam by cathodic electrodeposition method. The as-prepared NCMS nanosheets sample is used as an electrode material for supercapacitor application due to its large electrochemically active surface and high porosity structure. Moreover, NCMS nanosheets have good electrical and mechanical connections to the conductive Ni foam to achieve enhanced reaction kinetics with improved electrode integrity. The NCMS nanosheets exhibit an ultrahigh specific capacitance of 2717 Fig at a current density of 1 Aug with excellent cyclic stability and energy density of 94.07 Wh/kg. The electrodeposited NCMS nanosheets with extraordinary electrochemical performance enable the novel electrodes to hold great potential for high efficient energy storage systems.

Enhanced field emission characteristics of a 3D hierarchical Hfo2-Zno heteroarchitecture - Shisode, Raju T.; Suryawanshi, Sachin R.; Mistari, Chetan D.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Three dimensional (3D) HfO2-ZnO heteroarchitecture comprised of thin coating of HfO2 on self assembled 3D ZnO urchins with pointed apex has been synthesized using hydrothermal route followed by Pulsed Laser Deposition (PLD). The as-synthesized HfO2-ZnO heteroarchitecture was characterized using XRD, SEM, EDS, and (HR) TEM, in order to reveal its structural, morphological, and chemical properties. The HfO2-ZnO heteroarchitecture emitter exhibits superior field emission (FE) behaviour in contrast to the pristine ZnO urchins, demonstrated by delivery of high emission current density of similar to 885 mA/cm2 at an applied field of similar to 3.35 V/mm, against similar to 383 mA/cm(2) at an applied field of similar to 4.32 V/mu m for the pristine ZnO urchins emitter. Interestingly, the HfO2-ZnO heteroarchitecture emitter exhibits excellent emission current stability characterized with fewer fluctuations, owing to very good ion-bombardment resistance offered by the HfO2 coating. Furthermore, the heteroarchitecture thus obtained facilitates tailoring of the morphology with high aspect ratio and modulation of electronic properties as well, thereby enhancing the FE behaviour. Despite HfO2 being wide band gap and high-k material, the HfO2-ZnO heteroarchitecture exhibits potential as promising candidate for fabrication of high current density cold cathode
Keywords: 3D heteroarchitecture; Field Emission (FE); hydrothermal; PLD; TEM

Enhanced field emission performance of MoO3 nanorods and MoO3-rGO nanocomposite - Bankar, Prashant K.; Khandare, Lina N.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
The graphene and semiconducting hybrid based nanostructures have emerged as a new class of multifunctional materials with improved performance in comparison to the pristine semiconductors. Here, as-synthesized MoO3-reduced graphene oxide (rGO) nanocomposite emitter exhibits enhanced field emission (FE) behavior as compared to the pristine 1D MoO3 nanorods. The hydrothermally synthesized 1D MoO3 nanorods (1D) are grafted on the rGO sheet (2D) using a simple room temperature sonochemical method. The morphological and structural analysis confirms the attachment of MoO3 nanorods with rGO and the improved conductivity of the sample indicates a strong electronic interaction between them. Furthermore, the FE studies of as-synthesized MoO3 nanorods and MoO3-rGO nanocomposite emitters, carried out at a base pressure -1 x 10(-8) mbar, reveals the values of turn on field (required to draw an emission current density of 1 mu A/cm(2)) as 1.6 and 1.4 V/mu m, respectively. Interestingly, the maximum emission current density of 2810 mA/cm(2) is achieved at a lower applied field of 2.7 V/mu m from the MoO3-rGO nanocomposite emitter. The enhancement in FE performance of MoO3-rGO nanocomposite is attributed to the improved electrical conductivity, mechanical properties and higher concentration of protruding edges (emission sites). This observation can be extended to other graphene-based 1D inorganic hybrid semiconductor nanocomposites, which can provide a valuable opportunity to explore novel hybrid materials for vacuum nano-electronic devices.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, Prashant K.; Ratha, Satyajit; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of a and beta-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of beta-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of alpha and beta-NiMoO4 at a base pressure of similar to 1 x 10(-8) mbar. The obtained turn-on field at emission current density of 1 mu A/cm(2) for beta-NiMoO4 nanosheets and alpha-NiMoO4 is 1.3V/mu m and 2.2V/mu m respectively were observed. The maximum field emission current density of 1.006 mA/cm(2) at an applied electric field of 2.7V/mu m was achieved for beta-NiMoO4 nanosheets. Furthermore, we found that the beta-NiMoO4 nanosheets possess good field emission performance compared to alpha-NiMoO4. The results indicate that NiMoO4 can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase. (C) 2017 Elsevier B.V. All rights reserved.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, P. K. (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of α and β-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of β-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of α and β-NiMoO4 at a base pressure of ∼1 × 10−8 mbar. The obtained turn-on field at emission current density of 1 μA/cm2 for β-NiMoO4 nanosheets and α −NiMoO4 is 1.3 V/μm and 2.2 V/μm respectively were observed. The maximum field emission current density of 1.006 mA/cm2at an applied electric field of 2.7 V/μm was achieved for β-NiMoO4 nanosheets. Furthermore, we found that the β-NiMoO4 nanosheets possess good field emission performance compared to α-NiMoO4. The results indicate that NiMoO4can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase.
Keywords: Current stability; field emission; nanosheets; NiMoO4

Exploration of amination reactions on highly extendable active sites of Pd(II)-3-allylsalicylaldiminophenol (ASIP) complex over thiofunctionalized SBA-15 - Lazar, Anish; Vinod, C. P.; Singh, A. P. (Microporous and Mesoporous Materials, 2017)
An effective and impressive heterogeneous catalyst, Pd(II)-3-allylsalicylaldiminophenol-SBA-15, dubbed as Pd(II)ASIP@SBA-15, for amination reactions of aryl halides to synthesize secondary amines (2), has been synthesized and characterized. Pd(II)ASIP@SBA-15 has been synthesized by the covalent anchoring of 3-allylsalicylaldehyde over thiofunctionalized SBA-15, then further reaction with 2-aminophenol, followed by metallation process by using Pd(11)(OAc)(2). A specifically designed cheap and easily available organic ligand, 3-allylsalicylaldiminophenol (ASIP), was synthesized from 3-allylsalicylaldehyde and 2-aminophenol. Using this, the synthesis of Pd(II)ASIP@SBA-15 was carried out whereby the ligand providing an active co-ordination or chelating sites for palladium metal. This strategy helped in exposing the Pd(11)ASIP active sites from surface to channels of SBA-15 support during the reactions. The synthesized catalyst were characterized by CHN analysis, PXRD, Nitrogen sorption analyses, TG & DTA, FTIR, C-13 and Si-29 CPMASS NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. Pd(II)ASIP@SBA-15 catalyst was screened in heterogeneous amination reactions of aryl halides to produce N-aryl derivatives or secondary amines with high catalytic activity as revealed by turn over frequency (TOF) calculations. To explore the heterogeneous nature of catalysts, amination reactions were carried with neat Pd(II)ASIP complex and Pd(11)(OAc)(2) catalysts. The catalyst was recycled several times without much loss of activity and Sheldon hot filtration test has been performed. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Amination Reactions; heterogeneous catalysis; Reusable; Supported catalysis

Extraction of the very high tunneling current and extremely stable emission current from GdB6/W-tip source synthesized using arc plasma - Suryawanshi, Sachin R.; Kanhe, Nilesh; Mathe, Vikas L.; Phase, Deodatta M.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Herein, we report the one step arc plasma synthesis of the GdB6 (Gadolinium hexaboride) nanoparticles and its field emission (FE) characteristics on tungsten point substrate (GdB6/ W). The SEM /TEM analysis revealed the GdB6 nanoparticles on W point substrate exhibit irregular shaped, grainy, dense, course morphology, i.e. uniformly covering the entire tip substrate surface. For GdB6/W point source, the values of the turn-on and threshold fields, defined as field required to draw an emission current density similar to 1 mA/cm(2) and similar to 100 mA/cm(2), respectively are found to be similar to 2.2 and similar to 2.7 V/mm, for anodecathode separation of similar to 1 mm. Interestingly, a very high emission current density of similar to 3.5 A/cm(2) has been drawn from the GdB6/W point emitter at relatively lower applied field of similar to 6.4 V/mm. The field enhancement factor found to be similar to 10,250. The GdB6/W point electron source exhibits a good emission current stability at similar to 10 mA for a period of 6 hr. The emission current stability is enumerated in terms of standard deviation and its magnitude has been measured to be only 1.72% with respect to the average value. The superlative field emission characteristics signify the GdB6/W point electron source as potential candidates for vacuum micro/nanoelectronics device applications.
Keywords: Arc Plasma; field emission; Thin films

Heterogeneous route for transfer hydrogenation reactions of ketones using Ru(II)Cymene complex over modified benzene-organosilica (PMOB) - Lazar, Anish; Silpa, S.; Prabhakaran, Vinod C.; Singh, A. P. (Molecular Catalysis, 2017)
An inorganic-organic hybrid catalyst, Ru(II)Cym@PMOB, was synthesized by anchoring of [Ru(II)Cl-2(Pcymene)](2) complex which is derived from a reaction between hydrated ruthenium(III) trichloride and ocphellandrene over aminofunctionalized benzene-organosilica (PMOB). In the context of secondary alcohol synthesis from ketones, transfer hydrogenation (TH) reactions are convenient compared to conventional hydrogenation reactions owing to its lower activation energy and ambient pressure and mild temperature reaction" conditions. The synthesized catalysts were characterized by CHN analysis, XRD, ICP, N-2-sorption analysis, TG & DTA, FFIR,C-13 & 29Si solid NMR, UV-vis, TEM, SEM and XPS. The catalytic activities of neat [Ru(II)C-12(p-cymene)]2 complex and Ru(II)Cym@PMOB were evaluated in transfer hydrogenation (TH) of ketones (-97%) and compared with conventional hydrogenation reactions (-5%) where molecular H-2 was used. The results showed Ru(II)Cym@PMOB as highly active catalyst towards transfer hydrogenation (TH) reaction of acetophenones compared to neat [Ru(II)Cl-2(p-cymene)(12) complex. The heterogeneity of Ru(II)Cym@PMOB was confirmed by Sheldon's test. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Conventional Hydrogenation Reactions; Ru(II)Cym@PMOB; Transfer Hydrogenation Reaction; [Ru(II)Cl2(p-cymene)]2 complex

High-Performance Sensing Behavior Using Electronic Ink of 2D SnSe2 Nanosheets. - Pawar, Mahendra; Kadam, Sunil; Late, Dattatray J. (Chemistry Select, 2017)
Most of the recent research work on layered chalcogenides is understandably focused on single atomic layers. However, it is uncertain if the single layer units are most ideal structures for enhanced gas-solid interactions. To probe this concern, we have synthesized few layer thick SnSe<span style="line-height: 0; bottom: -0.25em; margin: 0px; padding: 0px 1px; border: 0px; outline: 0px; font-size: 0.688em; vertical-align: baseline; background: 0px 0px rgb(249, 249, 249); position: relative; color: rgb(51, 51, 51); font-family: "Open Sans", Arial, Helvetica, "Lucida Sans Unicode", sans-serif;">2 nanosheets ink using liquid exfoliation method. The morphology, thickness / layering and elemental analysis of the sheets were characterized by using SEM, TEM, AFM, Raman spectroscopy and by XPS. The two dimensional (2D) SnSe<span style="line-height: 0; bottom: -0.25em; margin: 0px; padding: 0px 1px; border: 0px; outline: 0px; font-size: 0.688em; vertical-align: baseline; background: 0px 0px rgb(249, 249, 249); position: relative; color: rgb(51, 51, 51); font-family: "Open Sans", Arial, Helvetica, "Lucida Sans Unicode", sans-serif;">2 nanosheets sensor device with different thicknesses was assessed for the humidity and gas sensing performances with exposure to humidity in different conditions. The results show that compared to the bulk / thicker counterpart, sensor device of few SnSe<span style="line-height: 0; bottom: -0.25em; margin: 0px; padding: 0px 1px; border: 0px; outline: 0px; font-size: 0.688em; vertical-align: baseline; background: 0px 0px rgb(249, 249, 249); position: relative; color: rgb(51, 51, 51); font-family: "Open Sans", Arial, Helvetica, "Lucida Sans Unicode", sans-serif;">2 layers exhibit excellent sensitivity, recovery and ability to be tune the sensing performance with thickness and can be used in lab on chip devices.

An innovative approach to enhance methane hydrate formation kinetics with leucine for energy storage application - Veluswamy, H. P.; Kumar, A.; Kumar, R.; Linga, P. (Applied Energy, 2017)
Natural gas storage in dathrate hydrates or solidified natural gas (SNG) offers the safest, cleanest and the most compact mode of storage aided by the relative ease in natural gas (NG) recovery with minimal cost compared to known conventional methods of NG storage. The stochastic nature of hydrate nucleation and the slow kinetics of hydrate growth are major challenges that needs to be addressed on the SNG production side. A deterministic and fast nucleation coupled with rapid crystallization kinetics would empower this beneficial technology for commercial application. We propose a hybrid combinatorial approach of methane hydrate formation utilizing the beneficial aspect of environmentally benign amino acid (leucine) as a kinetic promoter by combining stirred and unstirred reactor operation. This hybrid approach is simple, can easily be implemented and scaled-up to develop an economical SNG technology for efficient storage of natural gas on a large scale. Added benefits include the minimal energy requirement during hydrate growth resulting in overall cost reduction for SNG technology.

Interfacial-active polymer nanoparticles, their assemblies, and SERS application - Visaveliya, Nikunjkumar R.; Li, Xiang; Knauer, Andrea; Prasad, Bhagavatula L. V.; Kohler, Johann Michael (Macromolecular Chemistry and Physics, 2017)
In this work, surface-active polymer nanoparticles as well as polymer-polymer and polymer-metal nanoassembly particles are synthesized, and different parameters such as their size, morphologies, and assembling strength are studied. Nanoassembly particles are attractive because of the coupled properties with a large surface to volume ratio. A key challenge is to produce the core-shell polymer nanoparticles via single-step processes. To address this concern, here, microfluidics approach and precise interfacial reaction strategies are used, and hence different types of surface layered polymer nanoparticles are obtained in one-step processes. An inner core material is hydrophobic, whereas a hydrophilic surface layer (in situ formed during the polymerization process) swells in the aqueous environment. Moreover, three different reaction setups (batch, flow, and in situ) are applied in order to architect the nanoassembling hierarchical structures via layer-by-layer strategy. On the other side, polymer-metal nanoassembly particles as well as metal catalyzed metal deposited four layered nanoassembly particles of tuned size and compositions are produced. It is shown that these particles can be used as nanosensor particles for surface-enhanced Raman spectroscopy.

Ionic strength-dependent changes in tentacular ion exchangers with variable ligand density. II. functional properties - Shambure, Rahul; Angelo, James M.; Gillespie, Christopher M.; Phillips, Michael; Graalfs, Heiner; Lenhoff, Abraham M. (Journal of Chromatography A, 2017)
The effect of ligand density was studied on protein adsorption and transport behavior in tentacular cation-exchange sorbents at different ionic strengths. Results were obtained for lysozyme, lactoferrin and a monoclonal antibody (mAb) in order to examine the effects of protein size and charge. The combination of ligand density and ionic strength results in extensive variability of the static and dynamic binding capacities, transport rate and binding affinity of the proteins. Uptake and elution experiments were performed to quantify the transport behavior of selected proteins, specifically to estimate intraparticle protein diffusivities. The observed trend of decreasing uptake diffusivities with an increase in ligand density was correlated to structural properties of the ligand-density variants, particularly the accessible porosity. Increasing the ionic strength of the equilibration buffer led to enhanced mass transfer during uptake, independent of the transport model used, and specifically for larger proteins like lactoferrin and mAb, the most significant effects were evident in the sorbent of the highest ligand density. For lysozyme, higher ligand density leads to higher static and dynamic binding capacities whereas for lactoferrin and the mAb, the binding capacity is a complex function of accessible porosity due to ionic strength-dependent changes. Ligand density has a less pronounced effect on the elution rate, presumably due to ionic strength dependent changes in the pore architecture of the sorbents. (C) 2017 Elsevier B.V. All rights reserved.

Iron-based nanocatalyst for the acceptorless dehydrogenation reactions - Jaiswal, Garima; Landge, Vinod G.; Jagadeesan, Dinesh; Balaraman, Ekambaram (Nature Communications, 2017)
Development of sustainable catalytic systems for fundamentally important synthetic transformations and energy storage applications is an intellectually stimulating challenge. Catalytic dehydrogenation of feedstock chemicals, such as alcohols and amines to value-added products with the concomitant generation of dihydrogen is of much interest in the context of hydrogen economy and is an effective alternative to the classical oxidation reactions. Despite a number of homogeneous catalysts being identified for the acceptorless dehydrogenation, the use of high price and limited availability of precious metals and poor recovery of the catalyst have spurred interest in catalysis with more earth-abundant alternatives, especially iron. However, no report has described a reusable iron-based heterogeneous catalyst for oxidant-free and acceptorless dehydrogenation reactions. Here we replace expensive noble metal catalysts with an inexpensive, benign, and sustainable nanoscale iron catalyst for the efficient acceptorless dehydrogenation of N-heterocycles and alcohols with liberation of hydrogen gas.

Kocuria indica sp. nov., isolated from a sediment sample (vol 64, pg 869, 2014) - Dastager, Syed G.; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Lee, Jae-Chan; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2017)

Linking catalyst-coated isotropic colloids into ``active'' flexible chains enhances their diffusivity - Biswas, Bipul; Manna, Raj Kumar; Laskar, Abhrajit; Kumar, P. B. Sunil; Adhikari, Ronojoy; Kumaraswamy, Guruswamy (ACS Nano, 2017)
Active colloids are not constrained by equilibrium: ballistic propulsion, superdiffusive behavior, or enhanced diffusivities have been reported for active Janus particles. At high concentrations, interactions between active colloids give rise to complex emergent behavior. Their collective dynamics result in the formation of several hundred particle-strong flocks or swarms. Here, we demonstrate significant diffusivity enhancement for colloidal objects that neither have a Janus architecture nor are at high concentrations. We employ uniformly catalyst-coated, viz. chemo-mechanically, isotropic colloids and link them into a chain to enforce proximity. Activity arises from hydrodynamic interactions between enchained colloidal beads due to reaction-induced phoretic flows catalyzed by platinum nanoparticles on the colloid surface. This results in diffusivity enhancements of up to 60% for individual chains in dilute solution. Chains with increasing flexibility exhibit higher diffusivities. Simulations accounting for hydrodynamic interactions between enchained colloids due to active phoretic flows accurately capture the experimental diffusivity. These simulations reveal that the enhancement in diffusivity can be attributed to the interplay between chain conformational fluctuations and activity. Our results show that activity can be used to systematically modulate the mobility of soft slender bodies.
Keywords: active matter; Brownian motion; colloidal assembly; diffusivity; ice templating

Magnetic studies of SiO2 coated CoFe2O4 nanoparticles - Limaye, M.V. (Journal of Magnetism and Magnetic Materials, 2017)
Oleic acid capped CoFe2O4 nanoparticles which exhibit a high coercivity of ∼9.47 kOe at room temperature were coated with a robust coating of SiO2. We have used chemical synthesis method to obtain SiO2 coated CoFe2O4 nanoparticles with different weight percentages of CoFe2O4 in SiO2 (1.5, 3.1 and 4.8 wt.%). The morphological investigation of the coated nanoparticles by transmission electron microscopy shows that the particles are spherical with average size ∼160 nm. Infrared spectroscopy reveals that oleic acid capping on the surface of CoFe2O4 nanoparticles is retained after silica coating process. The complete coating of SiO2 on CoFe2O4 nanoparticles is confirmed by X-ray photoelectron spectroscopy as there is no signature of cobalt or iron ions on the surface. Magnetic measurements show that coercivity of SiO2 coated CoFe2O4 particles remains more or less unaffected as in CoFe2O4 nanoparticles at room temperature. In addition, the temperature dependent magnetic measurements show that at 5 K the CoFe2O4 and SiO2 coated 1.5 wt.% CoFe2O4 samples exhibit a very high value of coercivity (∼20 kOe) which is more than twice as compared to room temperature coercivity value (∼9.47 kOe). We conclude that silica coating in our study does not significantly affect the coercivity of CoFe2O4 nanoparticles.
Keywords: Coatings; coercive force; High Resolution Transmission Elctron Microscopy; infrared spectroscopy; Magnetic materials

Mapping architectural and transcriptional alterations in non-lesional and lesional epidermis in vitiligo - Singh, Archana; Gotherwal, Vishvabandhu; Junni, Paivi; Vijayan, Vinaya; Tiwari, Manisha; Ganju, Parul; Kumar, Avinash; Sharma, Pankaj; Fatima, Tanveer; Gupta, Aayush; Holla, Ananthaprasad; Kar, Hemanta K.; et al. (Scientific Reports, 2017)
In vitiligo, chronic loss of melanocytes and consequent absence of melanin from the epidermis presents a challenge for long-term tissue maintenance. The stable vitiligo patches are known to attain an irreversible depigmented state. However, the molecular and cellular processes resulting in this remodeled tissue homeostasis is unclear. To investigate the complex interplay of inductive signals and cell intrinsic factors that support the new acquired state, we compared the matched lesional and non-lesional epidermis obtained from stable non-segmental vitiligo subjects. Hierarchical clustering of genome-wide expression of transcripts surprisingly segregated lesional and non-lesional samples in two distinct clades, despite the apparent heterogeneity in the lesions of different vitiligo subjects. Pathway enrichment showed the expected downregulation of melanogenic pathway and a significant downregulation of cornification and keratinocyte differentiation processes. These perturbations could indeed be recapitulated in the lesional epidermal tissue, including blunting of rete-ridges, thickening of stratum corneum and increase in the size of corneocytes. In addition, we identify marked increase in the putrescine levels due to the elevated expression of spermine/spermidine acetyl transferase. Our study provides insights into the intrinsic self-renewing ability of damaged lesional tissue to restore epidermal functionality in vitiligo.

Mechanistic study of nucleophilic fluorination promoted by tri-tert-butanolamine - Lee, Sung-Sik; Jung, Hyun-Kyung; Shinde, Sandip S.; Lee, Sungyul (Journal of Fluorine Chemistry, 2017)
Quantum chemical study is carried out to elucidate the mechanism of S(N)2 fluorination using. CsF promoted by tri-tert-butanolamines. Focus is on the role of the hydroxyl (OH) and the amine functional groups for accelerating the reaction. Our systematic analysis indicates that the OH groups form strong interactions with the nucleophile F-. Thus, it seems that hydrogen bonding with the nucleophile may accelerate the S(N)2 processes rather than retard them, as conventional wisdom suggests. The origin of the experimentally observed improvement of the promotor efficiency in t-butanol solvent over that in CH3CN is examined. We show that the coordination of the solvent t-butanol molecule as Lewis base on the counter-cation Cs+ lowers the Gibbs free energy of activation. (C) 2017 Elsevier B.V. All rights reserved.

Micelles versus Ribbons: how congeners drive the self-assembly of acidic sophorolipid biosurfactants - Dhasaiyan, Prabhu; Griel, Patrick Le; Roelants, Sophie; Redant, Emile; Bogaert, Inge N. A. Van; Prevost, Sylvain Francois; Prasad, Bhagavatula L. V.; Baccile, Niki (ChemPhysChem, 2017)
Sophorolipids (SLs), a class of microbially derived biosurfactants, are reported by different research groups to have different self-assembled structures (either micelles or giant ribbons) under the same conditions. Here we explore the reasons behind these contradictory results and attribute these differences to the role of specific congeners that are present in minute quantities. We show that a sample composed of a majority of oleic acid (C18:1) sophorolipid in the presence of only 0.5 % (or more) of congeners with stearic acid (C18:0) or linoleic acid (C18:2) results in the formation of micelles that are stable over long periods of time. Conversely, the presence of only 10 to 15 % of congeners with a stearic acid chain gives fibrillar structures instead of micelles. To study the mechanisms responsible, oleic acid SLs devoid of any other congeners were prepared. Very interestingly, this sample can self-assemble into either micelles or fibers depending on minute modifications to the self-assembly conditions. The findings are supported by light scattering, small-angle X-ray scattering, transmission electron microscopy under cryogenic conditions, high-pressure liquid chromatography, and NMR spectroscopy.

Microwave-assisted synthesis of 5-substituted 1H-tetrazoles via [3+2] cycloaddition over a heterogeneous Cu-based catalyst: application to the preparation of N-13-labelled tetrazoles - Joshi, Sameer M.; Mane, Rasika B.; Pulagam, Krishna R.; Gomez-Vallejo, Vanessa; Llop, Jordi; Rode, Chandrashekhar (New Journal of Chemistry, 2017)
The [3+2] cycloaddition between various nitriles and sodium azide proceeds smoothly in the presence of a new Cu-II catalyst in N-methyl-2-pyrrolidone (NMP) to give the corresponding 5-substituted 1H-tetrazoles. The desired tetrazoles were obtained in high yields within 3-30 min by employing controlled microwave heating. The reaction most probably proceeds through the activation of the nitrile groups by the Cu-II species, followed by a successive [3+2] cycloaddition with the sodium azide. The good performance of the catalyst enabled the preparation of selected tetrazoles labelled with the positron emitter nitrogen-13 even under conventional heating. The short reaction time, simple work-up procedure, and recyclability of the catalyst are advantages of the method reported here.

Modular assembly of porous organic cage crystals: isoreticular quasiracemates and ternary co-crystal - Tothadi, Srinu; Little, Marc A; Hasell, Tom; Briggs, Michael E.; Chong, Samantha Y.; Liu, Ming; Cooper, Andrew I. (CrystEngComm, 2017)
Small changes in molecular structure and crystallisation conditions can have a profound effect on the crystal packing of molecules. Increasing the system complexity-for example, by introducing multiple components-greatly increases the number of potential outcomes. Hence, the rational design of porous cocrystals with multiple components is challenging. Here, we report a family of isoreticular quasiracemate crystalline phases for porous organic cages, FT-RCC3-R center dot CCX-S (where X = 1, 2, or 4), that were prepared in a modular and predictable fashion. By using directional intermolecular interactions between cages, we were able to prepare a rare ternary co-crystal, (CC3-S(0.5)CC4-S-0.5)center dot(CC13-S(0.5)CC3-S(0.25)CC4-S-0.25).
Keywords: cocrystals; Frameworks; Gas-chromatography; Halogen Bonds; Hydrogen-bonds; Molecular Cage; Nanoparticles; Pores; porosity; Separation

MoO3-rGO nanocomposites for electrochemical energy storage - Khandare, Lina; Late, Dattatray J. (Applied Surface Science, 2017)
We have synthesized the one dimensional (1D) MoO3 nanorods and MoO3-rGO nanocomposite by using sonochemical dispersion method at low temperature. The obtained products were characterized by using Raman spectroscopy, FT-IR, SEM, TEM and HR-TEM. We have demonstrated the electrochemical properties of MoO3 nanorods and MoO3-rGO nanocomposites. The specific capacitance for MoO3 nanorods and MoO3-rGO nanocomposite was calculated to be 3.3 F/g and 22.83 F/g at current density of 0.3 A/g respectively. The nanocomposite of MoO3-rGO shows the better electrochemical performance as compared to pristine MoO3 nanorods sample due to improvement in the conductivity. Our result suggests that the MoO3-rGO nanocomposites material has great potential for electrochemical energy storage and related applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Energy storage; Nanocomposites; Nanorods; Storage (materials); Temperature

Multicolour and nearly white light emission in YP0.8V0.2O4:Sm3+ nanorods: controlled energy transfer - Singh, N.S. (Journal of Alloys and Compounds, 2017)
Nanorods of YP0.8V0.2O4:Sm³⁺ have been synthesized under hydrothermal conditions. Substitution of vanadium (V⁵⁺) sites in YVO4 by phosphorus ions (P⁵⁺) has been confirmed by Fourier transform infrared spectroscopy, X-ray diffraction and transmission electron microscopy. Careful selection of Sm³⁺ concentration in YP0.8V0.2O4 enables to achieve the controlled energy transfer from the VO4³⁻ absorption to the excited states of Sm³⁺ ions. The controlled energy transfer has been confirmed from the steady state luminescence and decay lifetime studies of VO4³⁻ emission. With the controlled retention of VO4³⁻ emission, tuning of light emission from the singly (Sm³⁺) doped YP0.8V0.2O4 nanorods is realized. At a particular doping concentration of Sm³⁺ (1.25 at.%), a nearly white light emission is observed. The quantum yield of this nearly white light emission is found to be ∼28%. Tunability of the light and white light emission are supported by CIE chromaticity. The energy transfer efficiency from the VO4³⁻ absorption to the excited states of Sm³⁺ ion in YP0.8V0.2O4 reaches upto ∼86% with the doping concentration of 2.25 at.%.
Keywords: Energy Transfer; Luminescence; Multicolor; Nanorod

New pyrene cored small organic molecule with a flexible alkyl spacer: a potential solution processable blue emitter with bright photoluminescence - Valsange, Nitin G.; Wong, F. L.; Shinde, Durgaprasad; Lee, C. S.; Roy, V. A. L.; Manzhos, Sergei; Feron, K.; Chang, Samuel; Katoh, Ryuzi; Sonar, Prashant; Wadgaonkar, Prakash P. (New Journal of Chemistry, 2017)
A new pyrene cored small organic molecule viz. 1,3,6,8-tetrakis(4-((5-(9H-carbazol-9-yl) pentyl)oxy) phenyl)pyrene (PY-II) was designed and synthesized. The carbazole moiety with an alkyl spacer was introduced at 1, 3, 6 and 8 positions of the pyrene core to improve the charge transport properties and solution processability. PY-II exhibited excellent solubility in common organic solvents and high thermal stability up to 345 degrees C. The photoluminescence quantum yield (PLQY) of PY-II in solution was found to be 0.9 with bright blue emission near 450 nm which is just appropriate for the human eye. The solution processed non-doped OLED device fabricated using PY-II as an emissive layer afforded a pure blue emission with CIE coordinates of 0.16 and 0.16, a power efficiency of 0.17 lm W-1, a maximum current efficiency of 0.41 cd A(-1) and a maximum brightness of 202 cd m(-2).

Nickel-catalyzed N-vinylation of heteroaromatic amines via C-H bond activation - Landge, Vinod G.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2017)
Here, we report a ligand- and reductant-free nickel-catalyzed N-vinylation of heteroaromatic amines using biorenewable p-cymene as a solvent. This unprecedented cross-coupling strategy has high functional group tolerance (halides, alkoxy, cyano, chiral motif, etc.) and proceeded via C-H bond activation.
Keywords: Alkylation; Amination Reactions; Anilines; Aryl Chlorides; halides; Monoarylation; O Bonds; Precatalyst; Pyrimidines; Removeble Directing Group

Nonlinear Fowler-Nordheim behavior of a single SnO2 nanowire - Joshi, Padmashree D.; Joag, Dilip S.; Late, Dattatray J.; Mulla, Imtiaz S. (Journal of Vacuum Science & Technology B, 2017)
The present work deals with the field emission study on multiple SnO2 nanowires synthesized by a simple thermal evaporation method. The randomly oriented multiple nanowires grown by the vapor-liquid-solid mechanism exhibit low turn on field (0.8V/mu m defined for the current density of 1 mu A/cm(2)) and linear Fowler-Nordheim nature (FN). However, for the understanding of the nature of the FN plot, field emission behavior of a single SnO2 nanowire is investigated. The FN plot is observed to be nonlinear in nature. A simple model explaining the field emission mechanism from the semiconducting single SnO2 nanowire is proposed. (C) 2017 American Vacuum Society.

Oral feeding with polyunsaturated fatty acids fosters hematopoiesis and thrombopoiesis in healthy and bone marrow-transplanted mice - Limbkar, Kedar; Dhenge, Ankita; Jadhav, Dipesh D.; Thulasiram, Hirekodathakallu V.; Kale, Vaijayanti; Limaye, Lalita (Journal of Nutritional Biochemistry, 2017)
Hematopoietic stem cells play the vital role of maintaining appropriate levels of cells in blood. Therefore, regulation of their fate is essential for their effective therapeutic use. Here we report the role of polyunsaturated fatty acids (PUFAs) in regulating hematopoiesis which has not been explored well so far. Mice were fed daily for 10 days with n-6/n-3 PUFAs, viz. linoleic acid (LA), arachidonic acid (AA), alpha-linolenic acid and docosahexanoic acid (DHA) in four separate test groups with phosphate-buffered saline fed mice as control set. The bone marrow cells of PUFA-fed mice showed a significantly higher hematopoiesis as assessed using side population, Lin-Sca-1(+)ckit+, colony-forming unit (CFU), long-term culture, CFU-spleen assay and engraftment potential as compared to the control set. Thrombopoiesis was also stimulated in PUFA-fed mice. A combination of DHA and AA was found to be more effective than when either was fed individually. Higher incorporation of PUFAs as well as products of their metabolism was observed in the bone marrow cells of PUFA-fed mice. A stimulation of the Wnt, CXCR4 and Notch1 pathways was observed in PUFA-fed mice. The clinical relevance of this study was evident when bone marrow-transplanted recipient mice, which were fed with PUFAs, showed higher engraftment of donor cells, suggesting that the bone marrow microenvironment may also be stimulated by feeding with PUFAs. These data indicate that oral administration of PUFAs in mice stimulates hematopoiesis and thrombopoiesis and could serve as a valuable supplemental therapy in situations of hematopoietic failure. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Bone Marrow Transplantation (Bmt); Cord Blood; Down-regulation; Ex-vivo Expansion; Hematopoiesis; Hematopoietic Stem Cells (Hscs); Lipid rafts; Myocardial-infarction; Polyunsaturated Fatty Acids; Progenitor Cells; Prostaglandin-e2; Self-renewal; Spleen Colonies; Stem-cell Proliferation; Thrombopoiesis

PbS nanostar-like structures as field emitters - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (Chemistryselect, 2017)
The crystalline PbS nanostars were synthesized by thermal decomposition of thioacetamide (TAA) in aqueous solutions of lead acetate and acetic acid at 80 8 degrees C. The structure and morphology of the PbS nanostars have been characterized using X-Ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The optical properties of the PbS nanostars have been studied using UV-Visible absorption Spectroscopy (UVVis). The field emission investigations have been carried out on the as synthesized PbS nanostars at the base pressure of similar to 13 10(-8) mbar. The turn on field required to draw an emission current density of 1 mu A/cm(2) is found to be 1.8 V/mm. The emission current-time plots show good emission current stability of the PbS nanostar emitter over a period of 4 hrs. The results in terms of low turn-on field and long term emission current stability of the PbS nanostars emitter reveals that it can be used in field emission based vacuum microelectronics / nanoelectronic devices.

Proton conduction in a hydrogen-bonded complex of copper(II)-bipyridine glycoluril nitrate - Tayade, Sakharam B.; Dhavale, Vishal M.; Kumbhar, Avinash S.; Kurungot, Sreekumar; Loennecke, Peter; Hey-Hawkins, Evamarie; Pujari, Bhalchandra (Dalton Transactions, 2017)
Bipyridine glycoluril (BPG), a urea-fused bipyridine tecton, forms a square-pyramidal secondary building unit with copper(II) which further self-assembles to give a porous hydrogen-bonded complex. This complex displays a high proton conductivity of 4.45 x 10(-3) S cm(-1) at 90 degrees C and 95% relative humidity (RH). Chains consisting of coordinated water, solvent water and nitrate anions embedded in the complex are responsible for high proton conduction. The proton conduction pathway was corroborated by ab initio electronic structure calculations with molecular dynamics (MD) simulations using the Nudged Elastic Band (NEB) method. The theoretical activation energy estimated to be 0.18 eV is in close agreement with the experimental value of 0.15 eV which evidences a Grotthuss proton hopping mechanism. We thus demonstrate that the hydrogen-bonded complex encapsulating appropriate counter ions, coordinated water and solvent water molecules exhibts superprotonic conductivity.

Role of base fluid on the thermal conductivity of oleic acid coated magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (COLLOIDS AND SURFACES A-PHYSICOCHEMICAL AND ENGINEERING ASPECTS, 2017)
Thermal conductivity enhancement of nanofluids of oleic acid coated magnetite nanoparticles dispersed in four different base fluids (toluene, xylene, mesitylene, kerosene) is studied to understand the role of the solvent (base fluid). From the correlation of the thermophysical properties of the base fluid with the thermal conductivity of the corresponding nanofluid, it is found that the nanofluid with the base fluid of lower intrinsic thermal conductivity and dielectric constant shows relatively larger enhancement in the thermal conductivity. A linear increase in the thermal conductivity with increasing viscosity is observed for all four nanofluids studied. The concentration dependent thermal conductivity studies showed enhancement only above a particular concentration, within the sensitivity of the measurement, and this critical concentration is different for the different nanofluids. The nanofluid with kerosene showed the lowest critical concentration for thermal conductivity enhancement compared to the other nanofluids. The difference between the experimental thermal conductivity and the calculated value using the Maxwell model is found to depend on the critical concentration. By assuming the critical concentration as the zero concentration, it is found that all the studied nanofluids almost follow the Maxwell model of thermal conductivity. Thus, for the dispersions of the same oleic acid coated magnetite nanoparticles, the base fluid affects the critical concentration for thermal conductivity enhancement, probably due to the interfacial effects arising from the surfactant-solvent interactions.
Keywords: Brownian-Motion; Enhancement; Heat-transfer Characteristics; Magnetic nanofluids; Maxwell model; Nanoparticles; Particle Migration; Size; stability; Suspension; Temprature; Thermal conductivity; Thermophysical properties; transport mechanism; viscosity

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.

Studies on the role of unsaturation in the fatty acid surfactant molecule on the thermal conductivity of magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (Journal of colloid and interface science, 2017)
To study the role of unsaturation in the surfactant molecule on the thermal conductivity of magnetite nanofluids, four different fatty acid (stearic, oleic, linoleic, and linolenic acids with different degree of unsaturation) coated magnetite nanoparticles of comparable size are prepared and dispersed in toluene. It is found that the nanofluid with the saturated fatty acid coated nanoparticles show larger viscosity than the fluid with the unsaturated fatty acid coated particles at all concentrations. Thermal conductivity studies show enhancement only above a critical concentration for all fluids. The critical concentration for thermal conductivity enhancement varies with the surfactant, possibly due to the difference in the degree of aggregation of the nanoparticles in the fluid, because of the difference in the conformation of the surfactant molecules on the nanoparticle's surface. The experimental thermal conductivity follows the Maxwell model at higher concentrations. From the overall studies, it is observed that the thermal conductivity of the fluids with aggregated or assembled nanoparticles shows slightly larger enhancement than that of the fluids with isolated particles. However, in the presence of a magnetic field, the fluids with isolated nanoparticles showed relatively larger enhancement, possibly due to the easy response of the isolated magnetite nanoparticles to the applied field. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Chains; Dynamics; Enhancement; Fields; Fluids; Forces; gold nanoparticles; Magnetic fluid; Nanofluid; Surfactant; Unsaturation; Conformation; Thermal conductivity; Viscosity; Self-assembled Monolayers

Study of nanofiber scaffolds of PAA, PAA/CS, and PAA/ALG for its potential use in biotechnological applications - Rodolfo, Velasco; Ricardo, Vera-Graziano; López-Maldonado, E.A.; Mercedes, Oropeza; Dastager, Syed; Adriana, Álvarez-Andrade; Ana, leticia Iglesias; Luis, Jesús Villarreal-Gómez (International Journal of Polymeric Materials, 2017)
In recent times, electrospun nanofibers have been widely studied from several biotechnological approaches; in this work, poly (acrylic acid) solutions mixed with chitosan and alginate were electrospun and characterized in order to determine the behavior of these fibers when used in combination with bacteria, different samples were incubated with the bacterial strains: Streptomyces spp., Micromonospora spp. and Escherichia coli and a OD600 test was performed. The formation of nanofibers via electrospinning and the physicochemical properties of the obtained fibers were evaluated. Results showed that the presence of Chitosan enhanced the thermal stability of poly (acrylic acid), since poly (acrylic acid)/alginate fibers lost 5% of their mass at 41°C while poly (acrylic acid)/chitosan lost this amount at around 125°C. The fibers demonstrated suitable characteristics to be used as a bacteria bioreactor.

Synthesis and biological evaluation of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione as anti-mycobacterial agents - Sonawane, Amol; Rode, Navnath D.; Nawale, Laxman U.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman (Chemical Biology & Drug Design, 2017)
Resistance among dormant mycobacteria leading to multi-drug resistant (MDR) and extremely-drug resistant(XDR) tuberculosis is one of the major threats. Hence, a series of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione derivatives (4a-5c) have been synthesised and screened for their anti-tubercular activity against Mycobacterium tuberculosis H37Ra (H37Ra). Thetriazolethiones4b and 4v showed high anti-tubercular activity (both MIC and IC50) against the dormant H37Ra by in vitro and ex vivo. They were shown to have more specificity towards mycobacteria than other gram-negative and gram- positive pathogenic bacteria. The cytotoxicity was almost insignificant up to 100 μg/mL against THP-1, A549 and PANC-1 human cancer cell lines, and solubility was high in aqueous solution, indicating the potential of developing these compounds further as novel therapeutics against tuberculosis infection.

Synthesis, biological evaluation, and molecular docking studies of novel 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles derivatives targeting Mycobacterium tuberculosis - Rode, Navnath D.; Sonawane, Amol D.; Nawale, Laxman; Khedkar, Vijay M.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman; Joshi, Rohini R. (Chemical Biology & Drug Design, 2017)
A small library of new 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles was synthesized and screened for the antimycobacterial potency against Mycobacterium tuberculosis H37Ra strain and Mycobacterium bovis BCG both in active and dormant stage. Among the synthesized library, 25 compounds exhibited promising anti-TB activity in the range of IC(50)0.03-5.88g/ml for dormant stage and 20 compounds in the range of 0.03-6.96g/ml for active stage. Their lower toxicity (>100g/ml) and higher selectivity (SI=>10) against all cancer cell lines screened make them interesting compounds with potential antimycobacterial effects. Furthermore, to rationalize the observed biological activity data and to establish a structural basis for inhibition of M.tuberculosis, the molecular docking study was carried out against a potential target MTB CYP121 which revealed a significant correlation between the binding score and biological activity for these compounds. Cytotoxicity and in vivo pharmacokinetic studies suggested that 1,2,4-triazole analogues have an acceptable safety index, in vivo stability and bio-availability.

Synthesis of gamma-WO3 thin films by hot wire-CVD and investigation of its humidity sensing properties - Jadkar, Vijaya; Pawbake, Amit; Waykar, Ravindra; Jadhavar, Ashok; Date, Abhijit; Late, Dattatray; Pathan, Habib; Gosavi, Suresh; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2017)
In this study, monoclinic tungsten oxide (gamma-WO3) have been grown in a single step using HW-CVD method by resistively heating W filaments in a constant O-2 pressure. The formation of gamma-WO3 was confirmed using low angle-XRD and Raman spectroscopy analysis. Low angle-XRD analysis revealed that as-deposited WO3 film are highly crystalline and the crystallites have preferred orientation along the (002) direction. HRTEM analysis and SAED pattern also show the highly crystalline nature of WO3 with d spacing of similar to 0.38 nm, having an orientation along the (002) direction. Surface topography investigated by SEM analysis shows the formation of a uniform and homogeneous cauliflower like morphology throughout the substrate surface without flaws and cracks. A humidity sensing device incorporating WO3 is also fabricated, which shows a maximum humidity sensitivity factor of similar to 3954% along with a response time of similar to 14 s and a recovery time of similar to 25 s. The obtained results demonstrate that it is possible to synthesize WO3 in a single step by HW-CVD method and to fabricate a humidity sensor by using it. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim

Synthesis of isohexide-di(ether-ene)s and ADMET polymerization - Rajput, Bhausaheb S.; Lekshmy, Kalpakasseril Girija; Menon, Shamal K.; Chikkali, Samir H. (Green Materials, 2017)
As the fossil fuel reserves deplete and the greenhouse gases increase, the scientific community is challenged to provide sustainable solutions. Sugar-based isohexides can be modified to prepare a library of isohexide-diene monomers for polymerization. Such isohexide diene monomers can be subjected to Acyclic Diene Metathesis Polymerization to obtain green materials. Here we report a single step synthetic protocol to access a small family of isohexide-di(ether-ene)s and the corresponding polymers. The isohexide di(ether-ene)s 2a-2c could be isolated in good to excellent yields under optimized conditions. The resultant isohexide-di(ether-ene)s 2a-2c are potential versatile building blocks for pharmaceuticals and material science. The synthetic utility of 2a-2c was demonstrated by subjecting them to ADMET polymerization using Grubbs 1st and 2nd generation catalysts. The resultant viscous material was evaluated using 1H NMR and MALDI-ToF-MS, which suggests the formation of anticipated ADMET polymers

Synthesis of orthorhombic-molybdenum trioxide (α-MoO3) thin films by hot wire-CVD and investigations of its humidity sensing properties - Jadkar, Vijaya; Pawbake, Amit S.; Waykar,Ravindra G.; Jadhavar, Ashok Arjun; Mayabadi, Azam; Date, Abhijit; Late, Dattatray J.; Pathan, Habib M.; Gosavi, Suresh W.; Jadkar, Sandesh R. (Journal of Materials Science Materials in Electronics, 2017)
In present work, we report synthesis of orthorhombic-molybdenum trioxide (α-MoO 3) thin films using home-build hot wire-CVD (HW-CVD) method simply by heating the Mo filament in a controlled O 2 atmosphere. The formation of α-MoO 3 was confirmed by low angle-XRD and Raman spectroscopy. Low angle-XRD analysis revealed that α-MoO 3 crystallites have orientations along (110), (101) and (111) directions while Raman spectroscopy analysis shows two prominent vibrational modes ~819 and ~994 cm −1 associated with Mo 2–O and Mo=O respectively. SEM and TEM analysis show the formation of nano-sheets like morphology of α-MoO 3 thin films. The SAED pattern shows highly crystalline nature of α-MoO 3. The humidity-sensing properties were investigated at room temperature by fabricating the two probe device. The humidity sensing results showed n-type behavior of α-MoO 3. The maximum humidity sensitivity of ~6957% along with response time of ~66 s and recovery time of ~5 s were observed for α-MoO 3 thin film humidity sensor device. Our results have opened up a new avenue to grow α-MoO 3 for humidity sensor applications.

Thermo-reversible sol-gel transition of aqueous solutions of patchy polymers - Parmar, Indravadan A.; Shedge, Aarti S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Lele, Ashish K. (RSC Advances, 2017)
While aqueous solutions of several amphiphilic thermo-reversible polymers show gelation upon heating, there are fewer examples of polymer solutions that exhibit gelation when cooled. This paper reports an interesting phenomenon of abrupt thermoreversible gelation of aqueous solutions of a hydrophobically modified polymer upon cooling. A high molecular weight precursor copolymer (PCP, (M-w) over bar approximate to 5 x 10(6) g mol(-1)) of N, N-dimethylacrylamide (70 mol%) and acrylic acid (30 mol%) was modified by reacting 10 mol% of the acrylic acid groups with n-dodecyl amine to form a hydrophobically modified copolymer (HMCP). The composition of the copolymer was ascertained using NMR spectroscopy. Cooling the solution of PCP at a controlled rate resulted in a gradual increase in its low shear viscosity as dictated by the flow activation energy. In contrast, cooling the solution of HMCP under identical conditions resulted in an abrupt and large non-Arrhenius increase in viscosity at a specific transition temperature, which decreased with decrease in polymer concentration. Fluorescence measurements and dynamic light scattering data showed that abrupt gelation happened upon cooling, when polymer coils percolate accompanied with concomitant transition in chain conformation from compact micellar coils formed by intra-chain hydrophobic associations to swollen polymer coils connected by inter-chain hydrophobic interactions.

Ultrananocrystalline diamond decoration on to the single wall carbon nano tubes - Sinha, B.; Late, D.; Jejurikar, S.M. (Applied Surface Science, 2017)
We have demonstrated the decoration of the ultrananocrystalline diamonds on single walled carbon nanotubes using a hot filament assisted chemical vapor deposition. Study reveals the critical influence of the filament to substrate distance on the formation of ultrananocrystalline diamonds on to the single walled carbon nanotubes. It is also observed that etching of carbon nanotubes, due to the presence of unavoidable atomic hydrogen throughout the chemical vapor deposition processes, can be significantly reduced by adjusting the filament to substrate distance. Morphological and structural investigations performed using high resolution transmission electron microscope suggests the growth of ultrananocrystalline diamond is subsequent to the formation of crystalline sp2 carbon layer on the nanotube wall, enabling us to suggest a growth model. The composite synthesized can be thought not only to use as a fuel cell catalyst support but also as chemical sensors, bio-sensors and micro electromechanical systems (MEMS).
Keywords: Carbon nanotubes; Composite Coating; Electron microscopy (STEM; Nanostructures; TEM and SEM)

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2017)
The extent of alloying and the alloy composition, which are crucial in determining the activity and selectivity of bimetallic catalysts, were studied in porous silica encapsulated AgPd catalysts using XRD, HRTEM and HAADF-STEM. Water-dispersible ligand protected Pd ultra-small clusters and Ag nanoparticles of three different sizes were used as the precursors. The high reactivity of Pd ultra-small clusters enhanced the alloying of larger Ag nanoparticles to some extent. Encapsulation appeared to have minimised the sintering of the resultant nanoparticles. The earlier suggestions of the role of d-band positions with respect to adsorption energies holds good for the AgPd system and alloying enhances the activity. Alloy with the composition of Ag50Pd50 was found to be the most active with the reaction rate enhanced two fold compared to that in other compositions. Other factors like particle size and sinter-resistance also played important roles in enhancing the activity of these catalysts.

Unified strategy for silver-, base-, and oxidant-free direct arylation of C-H bonds - Sahoo, Manoj K.; Midya, Siba P.; Landge, Vinod G.; Balaraman, Ekambaram (Green Chemistry, 2017)
Here, we report a dual catalytic approach for room temperature direct arylation of C-H bonds with aryldiazonium salts as a simple aryl group donor, also working as an internal oxidant via C-N-2 bond cleavage. This unified strategy has been achieved by the synergistic combination of visible-light metal-free photoredox and palladium catalysis under silver-, base-and/or additive-free conditions. The broad substrate scope, functional group tolerance, excellent regioselectivity and redox-neutral conditions of this process make it attractive for the effective synthesis of a wide range of important N-heterocyclic commodities such as dibenzo [b,d]azepine, carbazole and phenanthridine.

X-ray structure, spectral characteristics, thermal and redox behavior of quinoline encapsulated in sulfonatocalix[4]arene - Thorave, R. G. (Journal of Molecular Liquids, 2017)
Keywords: Crystal Structure Analysis; Partial Encapsulation; single crystal X-ray diffraction; Spectral Characteristics; Sulfanatocalixarene; Theoretical Calculations

2D layered transition metal dichalcogenides (MoS2): Synthesis, applications and theoretical aspects - Singh, A.K.; Kumar, P.; Late, D.J.; Kumar, A.; Patel, S.; Singh, J. (Applied Materials Today, 2018)
Recently, graphene and other two-dimensional (2D) transition metal dichalcogenides (TMDCs) have been widely explored due to their unique optical, mechanical, electrical and sensing properties for versatile electronic and optoelectronic applications. The atomically thin layers of TMDC materials have shown potential to replace state-of-the-art silicon-based technology. Graphene has already revealed an excess of new physics and multifaceted applications in several areas. Similarly, mono-layers of TMDCs such as molybdenum disulfide (MoS2) have also shown excellent electrical and optical properties possessing a direct band-gap of ∼1.8 eV combined with high mechanical flexibility. In contrast to semi-metallic graphene, the semiconducting behavior of MoS2 allows it to overcome the deficiencies of zero-band-gap graphene. This review summarizes the synthesis of 2D MoS2 by several techniques, i.e., mechanical and chemical exfoliation, RF-sputtering, atomic layer deposition (ALD) and chemical vapor deposition (CVD), etc. Furthermore, extensive studies based on potential applications of MoS2 such as the sensor, solar cells, field emission and as an efficient catalyst for hydrogen generation has been included. Theoretical aspects combined with the experimental observations to provide more insights on the dielectric, optical and topological behavior of MoS2 was highlighted.

Analytical solutions of an isothermal two-dimensional model of a cathode flow channel in a proton exchange membrane fuel cell - Thosar, Aniket U.; Lele, Ashish K. (Chemical Engineering Science, 2018)
Two key assumptions are usually made while deriving analytical solutions of coupled kinetics and transport equations in a single channel on the cathode plate of a proton exchange membrane fuel cell (PEMFC). These are: plug flow and uniform oxygen concentration along the depth of the channel. However these assumptions are not always valid under typical operating conditions of a PEMFC, and particularly so at high current density. In this article we relax these two assumptions and present approximate analytical solutions of the governing equations using the methodology of separation of variables followed by power series solution. Spatial profiles of oxygen concentration and current density were derived, which led to the final derivation of a comprehensive current-potential relationship (polarization curve) in the reaction-controlled regime of an operational PEMFC. We compare polarization curves predicted by the present model with predictions of the earlier analytical model and also with a complete 3D-simulation of the same flow geometry and operation conditions. The local profiles of oxygen concentration and the polarization curve predicted by the present model compare far better with the 3D simulations than the earlier analytical model. While this comparison highlights the importance of the effects of finite oxygen diffusion rate and velocity profile in the channel on the polarization curves, it also points to other important factors that affect the current-potential relation.

Bessel's polynomial fitting for electrospun polyacrylonitrile/polyaniline blend nanofibers based ammonia sensor - Anwane, Rajashree S.; Kondawar, Subhash B.; Late, Dattatray J. (Materials Letters, 2018)
In the present paper, we report the fabrication of electrospun polyacrylonitrile/polyaniline (PAN/PANI) blend nanofibers by electrospinning and polymerization and Bessel's polynomial model applied for its ammonia sensing characteristics. As-fabricated PAN/PANI blend nanofibers were characterized by scanning electron microscopy and Fourier transform infrared spectroscopy for the confirmation of fibers with nanoscale and blends of PAN and PANI. The semiconducting behavior of the PAN/PANI blend nanofibers was found to respond quickly towards ammonia gas. Sensitivity of the blend was obtained at near room temperature for different concentrations of ammonia. Bessel's polynomial function was found to be well fitted with the experimental data for the response towards ammonia gas. (C) 2018 Elsevier B.V. All rights reserved.

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using Oxone as an oxidant (vol 43, pg 6875, 2017) - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2018)

Cobalt-catalyzed acceptorless dehydrogenative coupling of aminoalcohols with alcohols: direct access to pyrrole, pyridine and pyrazine derivatives - Midya, Siba P.; Landge, Vinod G.; Sahoo, Manoj K.; Rana, Jagannath; Balaraman, Ekambaram (Chemical Communications, 2018)
Here, the first example is reported of a new, molecularly defined SNS-cobalt(II) catalyst for the acceptorless dehydrogenative coupling (ADC) of unprotected amino alcohols with secondary alcohols leading to pyrrole and pyridine derivatives.

CSGID solves structures and identifies phenotypes for five enzymes in toxoplasma gondii - Lykins, Joseph D.; Filippova, Ekaterina V; Halavaty, Andrei S.; Minasov, George; Zhou, Ying; Dubrovska, Ievgeniia; Flores, Kristin J.; Shuvalova, Ludmilla A.; Ruan, Jiapeng; El Bissati, Kamal; Dovgin, Sarah; Roberts, Craig W.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Toxoplasma gondii, an Apicomplexan parasite, causes significant morbidity and mortality, including severe disease in immunocompromised hosts and devastating congenital disease, with no effective treatment for the bradyzoite stage. To address this, we used the Tropical Disease Research database, crystallography, molecular modeling, and antisense to identify and characterize a range of potential therapeutic targets for toxoplasmosis. Phosphoglycerate mutase II (PGMII), nucleoside diphosphate kinase (NDK), ribulose phosphate 3-epimerase (RPE), ribose-5-phosphate isomerase (RPI), and ornithine aminotransferase (OAT) were structurally characterized. Crystallography revealed insights into the overall structure, protein oligomeric states and molecular details of active sites important for ligand recognition. Literature and molecular modeling suggested potential inhibitors and druggability. The targets were further studied with vivoPMO to interrupt enzyme synthesis, identifying the targets as potentially important to parasitic replication and, therefore, of therapeutic interest. Targeted vivoPMO resulted in statistically significant perturbation of parasite replication without concomitant host cell toxicity, consistent with a previous CRISPR/Cas9 screen showing PGM, RPE, and RPI contribute to parasite fitness. PGM, RPE, and RPI have the greatest promise for affecting replication in tachyzoites. These targets are shared between other medically important parasites and may have wider therapeutic potential.

De novo transcriptome analysis of the egg parasitoid Trichogramma chilonis Ishii (Hymenoptera: Trichogrammatidae): a biological control agent - Kerima, O.Z.; Niranjana, P.; Vinay Kumar, B.S.; Ramachandrappa, R.; Puttappa, S.; Lalitha, Y.; Jalali, S.K.; Ballal, C.R.; H. V. Thulasiram (Gene Reports, 2018)
Trichogramma chilonis Ishii is an endoparasitic wasp widely used as a biological control agent of economically important pests. However, absence of genetic information on T. chilonis hampers further research, especially at the molecular level. Here, we performed the first RNA-Seq of the adult T. chilonis. A total of 18,372,639 high-quality reads were generated using Illumina pair-ended sequencing platform. De novo assembly resulted into 24,488 transcripts, with mean length and N50 values of 1444.2 bp and 2667 bp, respectively. Of the transcripts, 14,643 exhibited putative homology with class Insecta proteins from UniPROT database. To understand the contig functions, gene descriptions, gene ontology and cluster of orthologous group annotations were analyzed. Following functional annotation, a number of transcripts encoding detoxification, target receptor action and olfaction- related proteins were identified and analyzed. In addition, 4520 transcripts containing simple sequence repeats, ranging from dinucleotide to hexanucleotide repeats were discovered, with trinucleotide being the most enriched repeats. This new sequence resource will shed light on various molecular mechanisms in T. chilonis and related species.

Determination of the effect of polyamines on an oil-degrading strain of Yarrowia lipolytica using an odc minus mutant - Campos-Gongora, E.; Palande, A. S.; Leon-Ramirez, C.; Pathan, E. K.; Ruiz-Herrera, J.; Deshpande, M. V. (Fems Yeast Research, 2018)
Yarrowia lipolytica is an ascomycetous dimorphic yeast with immense potential for industrial applications, including bioremediation of crude oil-contaminated environments. It has been shown that a dimorphic marine isolate of Y. lipolytica (var. indica) has significant capacity to degrade fatty acids and alkanes, when in its yeast morphology. It has also been demonstrated that polyamines play an important role in the yeast-to-mycelium transition of different strains of Y. lipolytica that are unable to utilize those carbon sources. To determine the role of polyamines on their capacity to utilize oils and hydrocarbons, on the dimorphic transition, and also on other characteristics of the var. indica strain of Y. lipolytica, we proceeded to obtain ornithine decarboxylase minus (odc(-)) mutants. These mutants behaved as yeasts independently of the concentrations of putrescine added. Further, they conserved the oil-degrading capacity of the parent strain. The odc(-) mutant can thus be used in fatty acid degradation, and oil spill remediation with distinct advantages.

Direct access to N-alkylated amines and imines via acceptorless dehydrogenative coupling catalyzed by a cobalt(ii)-NNN pincer complex - Midya, Siba P.; Pitchaimani, Jayaraman; Landge, Vinod G.; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
A simple, phosphine-free Co(ii)-NNN pincer complex catalyzed direct N-alkylation of anilines with alcohols via hydrogen auto-transfer (HA) and selective acceptorless dehydrogenative coupling (ADC) of benzylamines with alcohols affording imines with the liberation of molecular hydrogen and water is reported.

Distribution of water in the pores of periodic mesoporous organosilicates - a proton solid state MAS NMR study - Veena, V. S.; Illath, Kavya; Lazar, Anish; Vinod, C. P.; Ajithkumar, T. G.; Jayanthi, S. (Physical Chemistry Chemical Physics, 2018)
Solid state proton (H-1) magic angle spinning (MAS) NMR has been employed to study the distribution of confined water in ethane substituted periodic mesoporous organosilicate (PMOE) materials. Proton spectra acquired at different hydration levels are analysed and interpreted in terms of water clusters of various sizes and distributions of water layers on the pore surface. For comparison, we also performed similar experiments on SBA-15. The formation of larger clusters at lower hydration suggests that the pores of PMOE are getting filled with water at lower hydration levels than those in SBA-15. For PMOE, the simultaneous presence of two major resonances in the ranges 3.6-4.1 ppm and 4.4-5.2 ppm and their behaviour upon hydration imply a water layer distribution that is the sum of two contributions, corresponding to fully filled and partially filled pores or pore segments. Furthermore, the behaviour mentioned above suggests that both radial and axial filling mechanisms play a significant role in the hydration process. For SBA-15, as a function of hydration, we observed a smooth variation in the proton chemical shift of the main dynamic resonance. In accordance with previous studies, this is attributed to the gradual increase in the average thickness of water layers with an increase in hydration, and to a pore filling mechanism that is predominantly radial.

Effect of alkali and alkaline earth metal on Co/CeO2 catalyst for the water gas shift reaction of waste derived synthesis gas - Lee, Yeol-Lim; Jha, Ajay; Jang, Won-Jun; Shim, Jae-Oh; Rode, Chandrashekhar V.; Jeon, Byong-Hun; Bae, Jong Wook; Roh, Hyun-Seog (Applied Catalysis A-General, 2018)
We prepared a series of alkali (Na and K) and alkaline earth metal (Ca and Ba) promoted Co/CeO2 catalysts to investigate the effect of the promoter on the catalytic performance of the catalyst in the high-temperature water gas shift (WGS) reaction of waste derived synthesis gas. Interestingly, alkali metal promoted catalysts deactivated rapidly compared to alkaline earth metal promoted catalysts. Alkaline earth metal promoted catalysts showed relatively higher stability (>50 h) even at a very high gas hourly space velocity of 143,000 h(-1). X-ray diffraction (XRD) and transmission electron microscopy (TEM) results reveal that the higher stability of the alkaline earth metal promoted catalysts was due to the strong resistance to sintering, showing a relatively small crystallite size of metallic cobalt compared to the alkali metal promoted catalysts after WGS reaction.
Keywords: Alkaline earth metal; Co/CeO2; High temperature water-gas shift; Sintering resistance; stability; Waste derived synthesis gas

Effect of titration time on the catalytic performance of Cu/CeO2 catalysts for water-gas shift reaction - Na, Hyun-Suk; Shim, Jae-Oh; Jang, Won-Jun; Jeon, Kyung-Won; Kim, Hak-Min; Lee, Yeol-Lim; Lee, Da-We; Yoo, Seong-Yeun; Bae, Jong Wook; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Today, 2018)
We herein report the preparation of ceria (CeO2) via a simple precipitation method for use as a catalyst support in the water-gas shift (WGS) reaction. More specifically, we optimized the titration time required to obtain highly active CeO2-supported catalysts for the WGS reaction. As such, Cu was employed as the active metal coupled with the CeO2 support. Notably, the CeO2-0 supported Cu catalyst (where the precipitant was immediately injected into a cerium nitrate solution) exhibited the highest CO conversion at a gas hourly space velocity of 36,050 h(-1). This high catalytic activity of the Cu/CeO2-0 catalyst was mainly due to its high Brunauer-Emmett-Teller (BET) surface area, enhanced Cu dispersion, high number of oxygen vacancies, and enhanced reducibility.

Electrochemically synthesized faceted CuInTe2 nanorods as an electron source for field emission applications - Lakhe, Manorama G.; Joshi, Padmshree; Choudhary, Ram J.; Ganesan, V.; Joag, Dilip S.; Chaure, Nandu B. (New Journal of Chemistry, 2018)
Herein, CuInTe2 (CIT) thin films with faceted nanorod-like morphology have been synthesized on a flexible molybdenum foil using a water-based low-cost electrodeposition technique. The co-deposition potential for CIT was optimized using cyclic voltammetry with respect to that of the Ag/AgCl reference electrode, and films were deposited from -0.6 V to -0.9 V at the working temperature of 75 degrees C. The as-prepared CIT films exhibited an amorphous nature, whereas the RTP-annealed films exhibited a highly crystalline chalcopyrite nature as a function of the growth potential. A red shift was observed in the Raman spectra of the as-deposited films that shifted towards the original position upon annealing. The Cu/In ratio obtained by the EDS analysis was found to decrease systematically upon increasing the growth potential. X-ray photoelectron spectroscopy (XPS) studies revealed the presence of Cu+, Cu2+ satellites, In3+, Te2-, and Te4+ states of Cu, In, and Te. The field emission study showed a maximum current density of 1.74 mA cm(-2), which was attainable at an applied electric field of 1.5 V mu m(-1). The turn-on field was found to be 0.92 V mu m(-1), comparable to that of the carbon nanofibres. The emitter exhibited stable electron emission over a period of 3 hours. The faceted CIT nanorods with columnar growth are a potential candidate for application as an electron source, and herein, the field emission of CIT nanorods is reported for the first time.

Enzymatic formation of a skipped methyl‐substituted octaprenyl side chain of longestin (KS‐505a): involvement of homo‐IPP as a common extender unit - Taro Ozaki; Shinde, Sandip S.; Gao, Lei; Okuizumi, Ryo; Liu, Chengwei; Ogasawara, Yasushi; Lei, Xiaoguang; Dairi, Tohru; Minami, Atsushi; Oikawa, Hideaki (Angewandte Chemie, 2018)
Longestin (KS‐505a), a specific inhibitor of phosphodiesterase, is a meroterpenoid that consists of a unique octacyclic terpene skeleton with branched methyl groups at unusual positions (C1 and C12). The biochemical analysis of Lon23, a methyltransferase involved in the biosynthesis of longestin, demonstrated that methylation of IPP afforded 3Z‐3‐methyl IPP. This compound as well as IPP was selectively accepted as extender units by Lon22, a geranylgeranyl diphosphate (GGPP) synthase homolog, to yield dimethylated GGPP (dmGGPP). Absolute configuration of dmGGPP was determined to be (4R, 12R) by degradation and chiral GC analysis. These findings led us to propose key steps of the biosynthetic pathway of the unusual homoterpenoid longestin.

Erratum to: catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V. (Research on Chemical Intermediates, 2018)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone®–KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone–KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine–Oxone as an unprecedented catalyst–oxidant combination.
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

Glycolysis is important for optimal asexual growth and formation of mature tissue cysts by Toxoplasma gondii - Shukla, Anurag; Olszewski, Kellen L.; Llinas, Manuel; Rommereim, Leah M.; Fox, Barbara A.; Bzik, David J.; Xia, Dong; Wastling, Jonathan; Beiting, Daniel; Roos, David S.; Shanmugam, Dhanasekaran (International Journal for Parasitology, 2018)
Toxoplasma gondii can grow and replicate using either glucose or glutamine as the major carbon source. Here, we have studied the essentiality of glycolysis in the tachyzoite and bradyzoite stages of T. gondii, using transgenic parasites that lack a functional hexokinase gene (Delta hk) in RH (Type-1) and Prugniaud (Type-II) strain parasites. Tachyzoite stage 411k parasites exhibit a fitness defect similar to that reported previously for the major glucose transporter mutant, and remain virulent in mice. However, although Prugniaud strain Delta hk tachyzoites were capable of transforming into bradyzoites in vitro, they were severely compromised in their ability to make mature bradyzoite cysts in the brain tissue of mice. Isotopic labelling studies reveal that glucose-deprived tacyzoites utilise glutamine to replenish glycolytic and pentose phosphate pathway intermediates via gluconeogenesis. Interestingly, while glutaminedeprived intracellular Delta hk tachyzoites continued to replicate, extracellular parasites were unable to efficiently invade host cells. Further, studies on mutant tachyzoites lacking a functional phosphoenolpyruvate carboxykinase (Delta pepck1) revealed that glutaminolysis is the sole source of gluconeogenic flux in glucose-deprived parasites. In addition, glutaminolysis is essential for sustaining oxidative phosphorylation in zihk parasites, while wild type (wt) and Delta pepck1 parasites can obtain ATP from either glycolysis or oxidative phosphorylation. This study provides insights into the role of nutrient metabolism during asexual propagation and development of T. gondii, and validates the versatile nature of central carbon and energy metabolism in this parasite. (C) 2018 Australian Society for Parasitology. Published by Elsevier Ltd. All rights reserved.

High surface area nanoporous carbon derived from high quality jute from Bangladesh - Khan, Junayet Hossain; Lin, Jianjian; Young, Christine; Matsagar, Babasaheb M.; Wu, Kevin C. W.; Dhepe, Paresh L.; Islam, Md Tofazzal; Rahman, Md Mahbubur; Shrestha, Lok Kumar; Alshehri, Saad M.; Ahamad, Tansir; Salunkhe, Rahul R.; et al. (Materials Chemistry and Physics, 2018)
We report an economically viable and environment-friendly strategy for the preparation of nanoporous carbon (NC) from jute which is one of the most abundant natural fibers produced in Bangladesh and some South Asian countries. Nitrogen adsorption-desorption isotherms, X-ray diffraction, Raman spectroscopy, UV spectroscopy, and scanning/transmission electron microscopy were performed to characterize the obtained NC. Three different types of jute-derived NCs have been synthesized at three different temperatures, 700 degrees C, 800 degrees C and 900 degrees C. The NC prepared at 800 degrees C resulted in a high surface area (981 m(2) g(-2)) and was associated with the retention of the original fibrous shapes. This study shows a promising future for jute as a natural precursor for NCs for a myriad of applications ranging from water purification to gas separation to energy conversion and storage.
Keywords: Adsorbents; Graphitization; Jute; Nanoporous carbons; porous materials

Highly efficient field emission properties of radially aligned carbon nanotubes - Tripathi, P.; Gupta, B.K.; Bhatnagar, A; Patel, C.R.P; Banker, P.K.; Late, D.J.; More, M.A.; Lalla, N.P.; Phase, D.M.,; Choudhary, R.J.; Shaz, M.A.; Ajayan, P.M.; et al. (Journal of Materials Chemistry C, 2018)
Here, we report extraordinary field emission properties from one pot synthesized aligned carbon nanotubes endowed with related Fe nanoparticles (NPs). The CNT configuration is in the form of a carbon hollow cylinder (CHC) with CNTs radially aligned towards the CHC axis. The structure generates electron field emission properties such as an ultralow turn on field (0.35 V μm−1 at 10 μA cm−2), a low threshold field (0.41 V μm−1 at 100 μA cm−2) and a high field emission current density (7.71 mA cm−2 at 0.78 V μm−1). It also exhibits multi-fold improvement in the field enhancement factor (1.34 × 104) with highly stable current emission at 100 μA measured for 14 h. No post synthesis treatment is required for enhanced field emission characteristics. The growth related Fe NPs assist in lowering the work function and hence enhancing the field emission properties. The possibility of assembling nano-structured field emitters into macroscale architectures suggests new prospects for next generation three dimensional electron sources.

Highly selective aqueous phase hydrogenation of phenols over nanostructured RuO2 on MCM-41 catalysts - Betsy, K. J.; Lazar, Anish; Vinod, C. P. (Nano-Structures & Nano-Objects, 2018)
Selective aqueous phase hydrogenation of phenol as well as its derivatives is important for the synthesis of chemical intermediates which are crucial for the manufacture of high-tonnage commodities and a multitude of value added platform chemicals. Herein, we report a facile catalyst made of highly dispersed small RuO2 nanoparticles supported on mesoporous MCM-41 using one-pot approach. The optimal 5RuO2-MCM-41 catalyst with particle size 6-8 nm showed excellent activity and selectivity in aqueous phase hydrogenation of phenol and other functionalized substrates, which are building blocks of lignin, to corresponding cyclohexanol products without any additives. These catalysts showed better stability and can be reused several times without any significant drop in activity which proves the heterogeneity of the immobilized oxide catalyst.

High-performance field emission device utilizing vertically aligned carbon nanotubes-based pillar architectures - Gupta, Bipin Kumar; Kedawat, Garima; Gangwar, Amit Kumar; Nagpal, Kanika; Kashyap, Pradeep Kumar; Srivastava, Shubhda; Singh, Satbir; Kumar, Pawan; Suryawanshi, Sachin R.; Seo, Deok Min; Tripathi, Prashant; More, Mahendra A.; et al. (AIP Advances, 2018)
The vertical aligned carbon nanotubes (CNTs)-based pillar architectures were created on laminated silicon oxide/silicon (SiO2/Si) wafer substrate at 775 degrees C by using water-assisted chemical vapor deposition under low pressure process condition. The lamination was carried out by aluminum (Al, 10.0 nm thickness) as a barrier layer and iron (Fe, 1.5 nm thickness) as a catalyst precursor layer sequentially on a silicon wafer substrate. Scanning electron microscope (SEM) images show that synthesized CNTs are vertically aligned and uniformly distributed with a high density. The CNTs have approximately 2-30 walls with an inner diameter of 3-8 nm. Raman spectrum analysis shows G-band at 1580 cm(-1) and D-band at 1340 cm(-1). The G-band is higher than D-band, which indicates that CNTs are highly graphitized. The field emission analysis of the CNTs revealed high field emission current density (4mA/cm(2) at 1.2V/mu m), low turn-on field (0.6 V/mu m) and field enhancement factor (6917) with better stability and longer lifetime. Emitter morphology resulting in improved promising field emission performances, which is a crucial factor for the fabrication of pillared shaped vertical aligned CNTs bundles as practical electron sources. (c) 2018 Author(s).

Improved nonenzymatic glucose sensing properties of Pd/MnO2 nanosheets: synthesis by facile microwave-assisted route and theoretical insight from quantum simulations - Ponnusamy, Rajeswari; Gangan, Abhijeet; Chakraborty, Brahmananda; Late, Dattatray J.; Rout, Chandra Sekhar (Journal of Physical Chemistry B, 2018)
The electrocatalytic properties of manganese oxide (MnO2) can be improved significantly by making hybrids/composites with noble metals (Au, Pd). Here, efforts have been made to synthesize the MnO2/Au and MnO2/Pd nanocomposites by a facile, rapid microwave irradiation method. The products characterized by X-ray diffraction and transmission electron microscopy exhibited their tetragonal phase and nanosheet morphology. The efficiency of the prepared composite materials as glucose sensor was tested by cyclic voltammetry and chronoamperometry measurements, and the results are discussed. The study revealed that successful modification of MnO2 by Pd led to excellent sensing performance by the reduction of size and the synergistic effect between MnO2 and PdO, which expedites the electron transfer. Besides, the wide detection range, good selectivity, and stability demonstrate its robustness in the design of electrochemical sensor platform. To get theoretical insight into the excellent sensing performance of MnO2/Pd, we have performed detailed density functional theory simulations to explore the charge transfer and bonding mechanism of glucose on MnO2 and Pd/Au-doped MnO2 surface. Pd is bonded strongly on MnO2 and makes MnO2/Pd more conducting due to the enhancement of density of states near Fermi level. The higher binding energy of glucose and enhanced charge transfer from glucose to Pd-doped MnO2 compared to bare MnO2 infer that Pd-doped MnO2 possess superior charge-transfer kinetics, resulting in higher glucose sensing performance, which supports our experimental observations.

Integrated transcriptomic and proteomic analyses suggest the participation of endogenous protease inhibitors in the regulation of protease gene expression in helicoverpa armigera - Lomate, Purushottam R.; Dewangan, Veena; Mahajan, Neha S.; Kumar, Yashwant; Kulkarni, Abhijeet; Wang, Li; Saxena, Smita; Gupta, Vidya S.; Giri, Ashok P. (Molecular & Cellular Proteomics, 2018)
Insects adapt to plant protease inhibitors (PIs) present in their diet by differentially regulating multiple digestive proteases. However, mechanisms regulating protease gene expression in insects are largely enigmatic. Ingestion of multi-domain recombinant Capsicum annuum protease inhibitor-7 (CanPI-7) arrests growth and development of Helicoverpa armigera (Lepidoptera: Noctuidae). Using de novo RNA sequencing and proteomic analysis, we examined the response of H. armigera larvae fed on recombinant CanPI-7 at different time intervals. Here, we present evidence supporting a dynamic transition in H. armigera protease expression on CanPI-7 feeding with general down-regulation of protease genes at early time points (0.5 to 6 h) and significant up-regulation of specific trypsin, chymotrypsin and aminopeptidase genes at later time points (12 to 48 h). Further, coexpression of H. armigera endogenous PIs with several digestive protease genes were apparent. In addition to the differential expression of endogenous H. armigera PIs, we also observed a distinct novel isoform of endogenous PI in CanPI-7 fed H. armigera larvae. Based on present and earlier studies, we propose potential mechanism of protease regulation in H. armigera and subsequent adaptation strategy to cope with anti-nutritional components of plants.

Judicious reduction of supported Ti catalyst enables access to disentangled ultrahigh molecular weight polyethylene - Gote, Ravindra P.; Mandal, Dipa; Patel, Ketan; Chaudhuri, Krishnaroop; Vinod, C. P.; Lele, Ashish K.; Chikkali, Samir H. (Macromolecules, 2018)
Heterogeneous Ziegler-Natta and homogeneous metallocene catalysts are known to produce ultrahigh molecular weight polyethylene (UHMWPE) in the entangled state. On the other hand, only (two) homogeneous single-site catalysts are reported to yield disentangled UHMWPE (dis-UHMWPE). This disparity between the two types of catalysts and the two states of polyethylene can be bridged if a heterogeneous single-site catalyst that can yield dis-UHMWPE is made accessible. Here, one-pot two-step synthesis of a MgCl2 supported [Ti(OEt)(4)] derived catalyst 1 with a two-stage activation strategy is reported to produce dis-UHMWPE. Second activation of catalyst 1 was performed by adding excess modified methylaluminoxane (MMAO12), and XPS analysis indicated that the catalyst existed in only Ti(III) state at [A1]/[Ti] ratio of 600. Catalyst 1 after second activation with MMAO12 was found to be highly active in ethylene polymerization and produced dis-UHMWPE. Polymerization conditions were tailored to obtain molecular weight (M-w) as high as 13 million g/mol PE. To the best of our knowledge, this is the first time a heterogeneous catalyst (catalyst 1) that displays pseudosingle site nature is able to produce dis-UHMWPE. The thus-prepared nascent polyethylene revealed a melting temperature of 141-144 degrees C, which is a characteristic melting transition for a dis-UHMVVPE. The disentangled state of the nascent PE and its M-w and MVVD were further authenticated by rheological investigations. Isothermal time, sweep oscillatory experiments in linear viscoelastic limit revealed a rapid rise in elastic modulus followed by equilibration to plateau modulus, which are characteristic features of the disentangled state. Thus, a pseudo-singlesite heterogeneous catalyst has been accessed, which upon second activation with excess MMAO12 led to the production of dis-UHMWPE.

The Leishmania donovani IMPACT-like protein possesses non-specific nuclease activity - Rao, Shilpa J.; Shukla, Ekta; Bhatia, Varsha; Lohiya, Bharat; Gaikwad, Sushama M.; Kar, Anita; Pal, Jayanta K. (International Journal of Biological Macromolecules, 2018)
IMPACT (Imprinted and Ancient)-like proteins are known to be regulators of GCN2 (General control non-derepressible 2) kinases involved in translation regulation. Here, we report on cloning and characterization of an IMPACT-like protein, LdIMPACT from Leishmania donovani which harbours two domains. 'RWD domain' at the N-terminal end that mediates GCN2 regulation, while a conserved 'ancient domain' lies at the C-terminal end whose function remains elusive. Interestingly, our observations indicated that LdIMPACT has a novel nonspecific nuclease activity. In silico analysis further revealed the resemblance of ancient domain of LdIMPACT to RNase PH domain (known to bind to nucleic acids). The recombinant LdIMPACT exhibited a Mg2+-dependent nuclease activity. Moreover, thermostability and pH stability assays of the protein suggest it to be a stress responsive protein. Circular dichroism studies elucidated the conformational transitions of the enzyme in response to various temperature and pH conditions which correlated well with the activity profiles. Thus, the current study highlights the structural and functional characteristics of LdIMPACT which interestingly also possesses a novel nuclease activity. With its physiological relevance unresolved, the multifaceted LdIMPACT might therefore lie in a hitherto unknown network, whose perturbation could be an attractive therapeutic approach for treating leishmaniasis. (C) 2018 Elsevier B.V. All rights reserved.

Manganese catalyzed N-alkylation of anilines with alcohols: ligand enabled selectivity - Landge, Vinod G.; Mondal, Akash; Kumar, Vinit; Nandakumar, Avanashiappn; Balaraman, Ekambaram (Organic and biomolecular chemistry, 2018)
Ligand enabled Earth-abundant manganese catalyzed N-alkylation of amines with alcohols via a hydrogen auto-transfer strategy is reported. The choice of the ligand plays a significant role in the alcohol reactivity (aliphatic or aromatic) toward N-alkylation reactions.

Mechanical activation in reduced graphite oxide/boron nitride nanocomposite electrocatalysts for significant improvement in dioxygen reduction - Patil, Indrajit M.; Jijil, Chamundi P.; Lokanathan, Moorthi; Swami, Anita; Kakade, Bhalchandra (Sustainable Energy & Fuels, 2018)
A nanocomposite of reduced graphite oxide (rGO) with hexagonal boron nitride (h-BN) is prepared using a simple hydrothermal method. Significant enhancement in the surface area of the composite is mainly due to the pre-mechanical activation of pristine GO. The structural and morphological study reveals the formation of a homogeneous nanocomposite and masking of rGO sheets over micron sized h-BN particles respectively. Interestingly, the as-synthesized GOBN2-BM composite (nanocomposite of 2 wt% h-BN with mechanically activated GO) catalyst exhibits significant oxygen electroreduction kinetics in terms of onset potential (E-onset = 0.89 V), half-wave potential (E-1/2 = 0.74 V) and limiting current density (J(L) = 4.4 mA cm(-2)) with a single step similar to 4-electron transfer pathway in alkaline medium. Though the composite catalysts exhibit higher overpotential (110 mV) than state-of-the-art Pt/C catalysts, they are much superior to previously reported carbon or h-BN based nanocomposite electrocatalysts. Importantly, the GOBN2-BM nanocomposite shows excellent tolerance towards both methanol oxidation and CO poisoning. Moreover, the nanocomposite catalysts show substantially higher stability than Pt/C catalysts even after 5000 cycles under similar conditions. Additionally, they show a better relative current stability (95% retention) than that of a Pt/C catalyst, signifying immense selectivity and durability towards oxygen electroreduction kinetics. The electrocatalytic oxygen reduction activity of the nanocomposite is mainly attributed to the high surface area (thanks to mechanical activation of GO, leading to increased pore distribution) as well as the synergistic mechanism between the h-BN and carbon network of rGO. Hence, it could be a potential cathode catalyst to replace precious-metal based catalysts in alkaline fuel cells.

Melamine formaldehyde-metal organic gel interpenetrating polymer network derived intrinsic Fe-N-doped porous graphitic carbon electrocatalysts for oxygen reduction reaction - Shijina, Kottarathil; llathvalappil, Rajith; Sumitha, N. S.; Sailaja, G. S.; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchig, Takeo; Hareesh, U. S. (New Journal of Chemistry, 2018)
Fe, N doped porous graphitic carbon electrocatalyst (Fe-MOG-MF-C), obtained by pyrolysis of an Interpenetrating Polymer Network (IPN) comprised of melamine formaldehyde (MF as hard segment) and Metal-Organic Gel (MOG as soft segment), exhibited significant Oxygen Reduction Reaction (ORR) activity in alkaline medium. BET surface area analysis of Fe-MOG-MF-C showed high surface area (821 m(2) g(-1)), while TEM, Raman and XPS results confirmed Fe and N co-doping. Furthermore, a modulated porous morphology with a higher degree of surface area (950 m(2) g(-1)) has been accomplished for the system (Fe-MOG-MFN-C) when aided by a sublimable porogen, such as naphthalene. XPS results further demonstrated that these systems exhibited a better degree of distribution of graphitic N and an onset potential value of 0.91 V vs. RHE in 0.1 M KOH solution following an efficient four-electron ORR pathway. The electrocatalytic activity of Fe-MOG-MFN-C is superior to that of Fe-MOG-MF-C by virtue of its higher graphitic N content and surface area. Thus, the study presents a new class of IPN derived MF-MOG nanocomposites with the potential to generate extended versions of in situ Fe-N doped porous graphitic carbon structures with superior ORR activity.

Mesoporous shell@macroporous core aluminosilicates as sustainable nanocatalysts for direct N-alkylation of amines - Sekhar, Anandakumari C. Sunil; Ashokkumar, Anumol Erumpukuthickal; Cygnet, Choorapoikayil T.; Lakshmi, Saseendranpillai Vidhya; Deepak, Francis Leonard; Vinod, Chathakudath P. (Chemnanomat, 2018)
Aluminosilicate spheres with a macroporous core and mesoporous shell (Si/Al ratio of 11) is synthesised by a sol-gel method utilizing cetyltrimethyl ammonium bromide (CTAB) as a structure directing agent in basic medium. The selective incorporation of aluminium in the silica matrix results in the formation of aluminosilicates with an overall acidity of 0.32mmol/g with interconnected pores. Direct N-alkylation reaction is a prototype of C-N bond formation reaction and meso- macroporous aluminosilicate is shown to catalyze this reaction with excellent yield. The catalyst is tested and found sustainable for five catalytic cycles even without any high temperature regeneration step.
Keywords: Aluminosilicates; macroporous; Mesoporous; N-alkylation; nanocatalysis

Microbacterium telephonicum sp nov., isolated from the screen of a cellular phone - Rahi, Praveen; Kurli, Rashmi; Pansare, Aabeejjeet N.; Khairnar, Mitesh; Jagtap, Shubhangi; Patel, Nisha B.; Dastager, Syed G.; Lawson, Paul A.; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2018)
A cultivation-based study of the microbial diversity of cellular phone screens led to the isolation of a Gram-stain-positive, aerobic, rod-shaped and non-endospore-forming bacterium, designated S2T63(T), exhibiting phenotypic and genotypic characteristics unique to the type strains of closely related species. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the strain is a member of Microbacterium, and most closely related to Microbacterium aurantiacum IFO 15234(T) and Microbacterium kitamiense Kitami C2(T). The DNA-DNA relatedness values of the strain S2T63(T) to M. aurantiacum KACC 20510(T), M. kitamiense KACC 20514(T) and Microbacterium laevaniformans KACC 14463(T) were 65% (+/- 4), 29.5% (+/- 3) and 55.9% (+/- 4), respectively. The genomic DNA G+C content was 71.8 mol%. The major fatty acids were anteiso C-15:0, iso-C-16 : 0, C-16 : 0 and anteiso-C-17 : 0. The main polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and two unidentified polar lipids. The peptidoglycan contained the amino acids glycine, lysine, alanine and glutamic acid, with substantial amounts of hydroxy glutamic acid detected, which is characteristic of peptidoglycan type B1 alpha. The predominant menaquinones were MK-12 and MK-13. Rhamnose, fucose and galactose were the whole-cell sugars detected. The strain also showed biofilm production, estimated by using crystal violet assay. Based on the results of the phenotypic and genotypic characterizations, it was concluded that the new strain represents a novel species of the genus Microbacterium, for which the name Microbacterium telephonicum is proposed, with S2T63(T) (=MCC 2967 T = KACC 18715 T = LMG 29293(T)) as the type strain.
Keywords: actinobacteria; bio-film; MALDI-TOF MS; mobile phone

Modelling of water-to-gas hollow fiber membrane humidifier - Pandey, R.; Lele, A. (Chemical Engineering Science, 2018)
A microscopic mathematical model is developed for membrane based water-to-gas humidification by rigorously accounting for phase equilibrium between the membrane and water phases as well as membrane and gas phases in addition to the coupled heat and mass transfer occurring across the membrane. The model is then integrated along the length of a hollow fiber membrane humidifier in order to predict humidifier performance as a function of design variables, operating variables and operational strategies. For realistic values of membrane thickness and flow parameters, the model suggests that while membrane-gas interfacial resistance alone is crucial for heat transfer, the vapor transfer is governed by the combined resistances of diffusion within the membrane and membrane-gas interface. The model is validated against experimental data obtained using a commercial hollow fiber
Keywords: Coupled Heat and Mass; Fuel Cell Applications; Humidification; Phase equilibrium; Proton exchange membrane; Water-to-gas

Multifunctional activated carbon with antimicrobial property derived from Delonix regia biomaterial for treatment of wastewater - Louis, Mary R.; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Bundale, Sunita (Journal of Environmental Chemical Engineering, 2018)
In this work, we report the development of a multifunctional high surface area activated carbon (DRP), from a biomaterial, Delonix regia, with antimicrobial potential and demonstrated its applicability towards removal of two reactive dyes, Reactive Red (RR-120) and Reactive Blue (RB-4) with an adsorption capacity of ∼6.36 and 24 mg·g−1 respectively. The newer multifunctional activated carbon was prepared from the deseeded pods of Delonix regia through thermo-chemical surface modification and characterized for surface and morphological characteristics, chemical composition, and thermal stability. DRP exhibited a high surface area of 1577 m2·g−1 with various active functional groups. The decolourisation efficiency achieved was very high, ∼98% for both the dyes. The effects of various operating parameters like pH, initial dye concentration, adsorbent dosage, surfactant, salt etc. were investigated and the batch adsorption equilibrium data in each dye system was analyzed with various isotherms-Langmuir, Freundlich, and Tempkin. The kinetics of the adsorption process was best represented by pseudo-second order kinetic model and the adsorption efficiency was also illustrated in the binary system of varying dye compositions. DRP could successfully reduce the microbial growth of Gram positive B. subtilis with a higher zone of inhibition.

Organocatalytic asymmetric cascade reaction of gamma-substituted deconjugated butenolides with o-formyl-beta-nitrostyrene - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2018)
An efficient chemo-, diastereo- and enantio-selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of beta,gamma-butenolides with o-formyl-beta-nitrostyrenes in the presence of bi-functional hydrogen-bonding catalyst. Indanol derivatives containing gamma,gamma-disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities.
Keywords: butenolides; Cascade reaction; Enantioselectivity; Indanol; organocatalysis

Pd(II)-Catalyzed gamma-C(sp(3))-H alkynylation of amides: selective functionalization of R chains of amides (RC)-C-1(O)NHR - Landge, Vinod G.; Parveen, Ayisha; Nandakumar, Avanashiappan; Balaraman, Ekambaram (Chemical Communications, 2018)
The gamma C(sp(3))-H bond alkynylation of R chains of amides (RC)-C-1(O)NHR, a fundamental class of synthetic substrates, has not been accomplished to date. Here, the first example of palladium(ii)-catalyzed alkynylation of an unactivated gamma C(sp(3))-H bond of alkyl amides (cyclic, linear, and amino acids) is reported. The kinetic experiment shows that the rate of the reaction depends on the coupling partners and the amides. Late-stage diversification of alkynylated amides was developed by utilizing amine and alkyne functionalities.

Phosphine-free cobalt pincer complex catalyzed Z-selective semi-hydrogenation of unbiased alkynes - Landge, Vinod G.; Pitchaimani, Jayaraman; Midya, Siba P.; Subaramanian, Murugan; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
Herein, we report a novel, molecularly defined NNN-type cobalt pincer complex catalyzed transfer semi-hydrogenation of unbiased alkynes to Z-selective alkenes. This unified process is highly stereo-and chemo-selective and exhibits a broad scope as well as wide functional group tolerance. Ammonia-borane (AB), a bench-stable substrate with high gravimetric hydrogen capacity, was used as a safe and practical transfer hydrogenating source.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 2: Application to the analysis of calcitonin containing pharmaceutical formulation - Vasilescu, Alina; Ye, Ran; Boulahneche, Samia; Lamraoui, Sabrina; Jijie, Roxana; Medjram, Mohamed Salah; Gaspar, Szilveszter; Singh, Santosh K.; Kurungot, Sreekumar; Melinte, Sorin; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2018)
In part 1 (A. Vasilescu et al., Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 1: Lysozyme aggregation at pH 2 and 7.4 Electrochem. Acta, 254 (2017) 375 -383) we proposed porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) in combination with differential pulse voltammetry as a new analytical tool for aggregation studies of proteins. Lysozyme was used as a model to follow its aggregation by electrochemical means at pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Part 2 of this work widens the scope of this approach by investigating a biopharmaceutical product, as the aggregation of peptide based drugs affects their therapeutic activity and can induce allergic reactions in patients. The salmon polypeptide calcitonin (sCT) was chosen as an example of a bioactive peptide with limited pharmaceutical potential due to a tendency to form cytotoxic aggregates and amyloid fibrils. For practical applications, screen printed electrodes (SPE) and flexible electrodes (FE) modified with polydiallyldimethylammonium (PDDA) and prGO by using the layer-by-layer deposition technique have been developed for the detection of sCT. The results indicate that these electrodes can differentiate between formation of amyloid aggregates of calcitonin (2 mg mL(-1)) in citrate buffer to no aggregation in acetate buffer. It was further demonstrated that these electrodes are able to analyze a pharmaceutical drug product of low potency, Miacalcic (8.3 mu g mL(-1)), where no aggregation was observed. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Calcitonin; Disposable electrodes; Electrochemistry; Porous reduced graphene oxide; Protein aggregation

Removable functional group strategy for regiodivergent Wittig rearrangement products - Alam, Md Nirshad; Lakshmi, K. M.; Maity, Pradip (Organic & Biomolecular Chemistry, 2018)
1,2] and [2,3] Wittig rearrangements are competing reaction pathways, often leading to uncontrollable product distribution. We employ a single removable functional group to fulfill the dual role of attaining a reversible [2,3] and stabilizing radical intermediate for the [1,2] path to obtain both the Wittig products selectively for a broad range of substrates.

Repeated photoporation with graphene quantum dots enables homogeneous labeling of live cells with extrinsic markers for fluorescence microscopy - Liu, Jing; Xiong, Ranhua; Brans, Toon; Lippens, Saskia; Parthoens, Eef; Zanacchi, Francesca Cella; Magrassi, Raffaella; Singh, Santosh K.; Kurungot, Sreekumar; Szunerits, Sabine; Bove, Hannelore; Ameloot, Marcel; et al. (Light-Science & Applications, 2018)
In the replacement of genetic probes, there is increasing interest in labeling living cells with high-quality extrinsic labels, which avoid over-expression artifacts and are available in a wide spectral range. This calls for a broadly applicable technology that can deliver such labels unambiguously to the cytosol of living cells. Here, we demonstrate that nanoparticle-sensitized photoporation can be used to this end as an emerging intracellular delivery technique. We replace the traditionally used gold nanoparticles with graphene nanoparticles as photothermal sensitizers to permeabilize the cell membrane upon laser irradiation. We demonstrate that the enhanced thermal stability of graphene quantum dots allows the formation of multiple vapor nanobubbles upon irradiation with short laser pulses, allowing the delivery of a variety of extrinsic cell labels efficiently and homogeneously into live cells. We demonstrate high-quality time-lapse imaging with confocal, total internal reflection fluorescence (TIRF), and Airyscan super-resolution microscopy. As the entire procedure is readily compatible with fluorescence (super resolution) microscopy, photoporation with graphene quantum dots has the potential to become the long-awaited generic platform for controlled intracellular delivery of fluorescent labels for live-cell imaging.

Role of oxygen vacancies and interstitials on structural phase transition, grain growth, and optical properties of Ga doped TiO2 - Khatun, Nasima; Tiwari, Saurabh; Vinod, C. P.; Tseng, Chuan-Ming; Liu, Shun Wei; Biring, Sajal; Sen, Somaditya (Journal of Applied Physics, 2018)
A systematic study on the effect of gallium (Ga) doping (0 <= x <= 0.10) on the structural phase transition and grain growth of TiO2 is reported here. X-ray diffraction spectroscopy and Raman spectroscopy confirm that Ga doping inhibits the phase transition. Activation energy increases from 125 kJ/mol (x = 0.00) to 300 kJ/mol (x = 0.10) upon Ga incorporation. X-ray photoelectron spectroscopy shows the presence of Ti3+/Ga3+ interstitials, substitution (Ti4+ by Ga3+), and oxygen vacancies in the samples. At lower doping (x <= 0.05), interstitials play a more significant role over substitution and oxygen vacancies, thereby resulting in a considerable lattice expansion. At higher doping (x >= 0.05), the effect of interstitials is compensated by both the effect of substitution and oxygen vacancies, thereby resulting in relatively lesser lattice expansion. Inhibition of the phase transition is the result of this lattice expansion. The crystallite size (anatase) and particle size (rutile) both are reduced due to Ga incorporation. It also modifies optical properties of pure TiO2 by increasing the bandgap (from 3.06 to 3.09 eV) and decreasing the Urbach energy (from 58.59 to 47.25 meV). This happens due to regularization of the lattice by the combined effect of substitution/ interstitials and oxygen vacancies. Published by AIP Publishing.

Rufinamide: crystal structure elucidation and solid state characterization - Salunke, Nita; Thipparaboina, Rajesh; Chavan, Rahul B.; Lodagekar, Anurag; Mittapalli, Sudhir; Nangia, Ashwini; Shastri, Nalini R. (Journal of Pharmaceutical and Biomedical Analysis, 2018)
Rufinamide (R) is a triazole derivative approved for the management of partial seizures and seizures associated with Lennox-Gastaut Syndrome, in November 2007. Crystal structure, solid state characterization, drug-excipient compatibility and solubility play a pivotal role in formulation development. This work deals with the crystal structure elucidation of R by single crystal X-ray diffraction and solid state characterization by thermal, spectroscopic and crystallographic techniques. Drug- excipient compatibility was assessed by differential scanning calorimetry (DSC). New RP-HPLC method for quantification of R was developed with improved retention time. Solubility and dissolution of drug in different media was determined. Additionally, the flow behavior of the drug was evaluated by measuring Carr's index and Hausner's ratio, while the compressibility behavior was studied using Well's protocol. R crystallized from dimethylformamide (R-DMF) was utilized for single crystal analysis. The drug crystallized in triclinic crystal system with P-1 space group. Asymmetric unit cell consists of two molecules of R held by intermolecular hydrogen bond (connected by N-H center dot center dot center dot O, which forms the catemeric chain). Analytical outcomes from DSC, thermogravimetric analysis (TGA) and powder X-ray diffraction (PXRD) revealed that the drug was present in pure crystalline form and was devoid of any polymorphic or pseudopolymorphic impurities. Influence of pH on the solubility and dissolution of R-DMF was found to be insignificant. The drug exhibited poor aqueous solubility, which was improved nearly 4.6 fold with the addition of 2% sodium lauryl sulphate (SLS). The drug exhibits poor flow and elastic compression nature. Excipients such as poly ethylene glycol (PEG) 8000, SLS, lactose monohydrate, starch and Hydroxypropyl methylcellulose (HPMC) E15 were incompatible with R-DMF as identified by thermal analysis. It is envisaged that these information regarding solid state properties of R-DMF would aid in identifying a logical path for formulation development. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Compressibility; Dissolution media; DSC; HPLC method; solubility

Ru(II)-functionalized SBA-15 as highly chemoselective, acid free and sustainable heterogeneous catalyst for acetalization of aldehydes and ketones - Lazar, Anish; Betsy, K. J.; Vinod, C. P.; Singh, A. P. (Catalysis Communications, 2018)
Combining electron deficient Ru(II) coordination sites with organofunctionalized SBA-15, (L)Ru(Il)@SBA-15, result in a mild, neutral, water scavenger free and chemo-selective acetalization catalyst for cyclic/acyclic acetals. Vacant coordination sites of ruthenium in (L)Ru(II)@SBA-15 activates protecting groups as well as reactants simultaneously and restricts the reverse acetalization reaction. Synthesized (L)Ru(Il)@SBA-15 catalyst has been thoroughly characterized and act as competitive catalyst compared to conventional acid catalysts. (L) RuaD@SBA-15 performs high catalytic activity as well as selectivity within 20 min with high TOF. The catalyst can be recycled and reaction parameters are optimized.
Keywords: Acetalization reactions; Acid free; chemo-selective; heterogeneous catalyst; Reusable; Ru(II) immobilized SBA-15

Selective oxidation of cyclohexane to cyclohexanone using chromium oxide supported mesoporous MCM-41 nanospheres: probing the nature of catalytically active chromium sites - Betsy, Kurisingal J.; Nayak, Chandrani; Lazar, Anish; Krishnan, Athira; Bhattacharyya, Dibyendu; Jha, Shambhu N.; Vinod, Chathakudath P. (ChemCatChem, 2018)
Highly dispersed chromium oxide supported mesoporous MCM-41 nanosphere catalysts have been synthesized using a simple wet impregnation method. This work is devoted to a systematic study to reveal the active Cr sites in chromium oxide supported MCM-41 nanosphere catalysts for the selective oxidation of cyclohexane to cyclohexanone. To probe the nature of the active species, we synthesized 0.5-10wt% Cr loaded catalysts and characterized them by using XRD, UV/Vis spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure analysis, X-ray absorption near edge structure analysis, N-2 sorption analysis, FTIR spectroscopy, (SiNMR)-Si-29 spectroscopy, SEM, and TEM. The liquid-phase oxidation of cyclohexane to cyclohexanone (99% selectivity) was performed under mild reaction conditions, and the results reveal clearly that the 5wt% Cr loaded catalyst was optimum for the reaction. The initial composition of isolated Cr3+ species in the catalyst is the major factor that influences the enhanced activity for cyclohexane oxidation.
Keywords: chromium; heterogeneous catalysis; Nanostructures; Oxidation; supported catalysts

Solvent and pH-stable poly(2,5-benzimidazole) (ABPBI) based UF membranes: preparation and characterizations - Lohokare, Harshada R.; Chaudhari, Harshal D.; Kharul, Ulhas. K. (Journal of Membrane Science, 2018)
Poly(2,5-benzimidazole), commonly known as ABPBI, is an excellent thermo-chemically stable polymer that is widely evaluated as a proton exchange membrane material in a fuel cell. Its niche intrinsic characteristics could be highly useful in the membrane preparation for various separation applications, especially under harsher environments. To gain insights towards this feasibility, ABPBI based supported membranes were prepared by phase inversion method. Effects of the nonwoven porous support material (polypropylene/polyester), non-solvent (water/0.5 N NaOH) and polymer concentration (6 or 4 wt%) on the membrane properties (water flux, rejection and porosity) were investigated. The stability of these membranes towards common organic solvents, concentrated acid (25 N H2SO4), base (2.5 N NaOH) and an autoclave condition was analyzed. ABPBI membrane showed a pore collapse after drying. In order to avoid this, the glycerol treatment was not only found to be suitable but also repeatable, without significant deviations in the water flux.
Keywords: ABPBI membrane; Pore size distribution; Solvent stable membranes; Ultrafiltration

Spatial-temporal spectroscopy characterizations and electronic structure of methylammonium perovskites - Liu, Zhaoyu; Bhamu, K. C.; Luo, Liang; Shah, Satvik; Park, Joong-Mok; Cheng, Di; Long, Men; Biswas, Rana; Fungara, F.; Shiner, Ruth; Shiner, Joseph; Vela, Javier; et al. (MRS Communications, 2018)
Using time-resolved laser-scanning confocal microscopy and ultrafast optical pump/THz probe spectroscopy, we measure photoluminescence (PL) and THz-conductivity in perovskite micro-crystals and films. PL quenching and lifetime variations occur from local heterogeneity. Ultrafast THz-spectra measure sharp quantum transitions from excitonic Rydberg states, providing weakly bound excitons with a binding energy of similar to 13.5 meV at low temperatures. Ab-initio electronic structure calculations give a direct band gap of 1.64 eV, a dielectric constant of similar to 18, heavy electrons, and light holes, resulting in weakly bound excitons, consistent with the binding energies from the experiment. The complementary spectroscopy and simulations reveal fundamental insights into perovskite light-matter interactions.

Streptomyces sp metabolite(s) promotes Bax mediated intrinsic apoptosis and autophagy involving inhibition of mTOR pathway in cervical cancer cell lines - Dan, Vipin Mohan; Muralikrishnan, Balaji; Sanawar, Rahul; Vinodh, J. S.; Burkul, Bhushan Bapusaheb; Srinivas, Kalanghad Puthankalam; Lekshmi, Asha; Pradeep, N. S.; Dastager, Syed G.; Santhakumari, B.; Santhoshkumar, Thankayyan R.; Kumar, R. Ajay; et al. (Scientific Reports, 2018)
In cervical cancer, the association between HPV infection and dysregulation of phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway (PI3K/AKT/mTOR pathway) places mTOR as an attractive therapeutic target. The failure of current treatment modalities in advanced stages of this cancer and drawbacks of already available mTOR inhibitors demand for novel drug candidates. In the present study we identified the presence of a mTOR inhibitor in an active fraction of the ethyl acetate extract of Streptomyces sp OA293. The metabolites(s) in the active fraction completely inhibited mTORC1 and thereby suppressed activation of both of its downstream targets, 4E-BP1 and P70S6k, in cervical cancer cells. In addition, it also stalled Akt activation via inhibition of mTORC2. The mechanism of mTOR inhibition detailed in our study overcomes significant drawbacks of well known mTOR inhibitors such as rapamycin and rapalogs. The active fraction induced autophagy and Bax mediated apoptosis suggesting that mTOR inhibition resulted in programmed cell death of cancer cells. The molecular weight determination of the components in active fraction confirmed the absence of any previously known natural mTOR inhibitor. This is the first report of complete mTOR complex inhibition by a product derived from microbial source.

Structural characterization and magnetic properties of undoped and copper-doped cobalt ferrite nanoparticles prepared by the octanoate coprecipitation route at very low dopant concentrations - Kamta Tedjieukeng, H.M.; Tsobnang, P.K.; Fomekong, R.L.; Etape, E.P.; Joy, P.A.; Delcorte, A.; Lambi, J.N. (RSC Advances, 2018)
Nanoparticles of undoped and copper-doped cobalt ferrite Co1−xCuxFe2O4 at very low dopant concentrations (x = 0; 0.02; 0.04; 0.06; 0.08) were successfully synthesized by pyrolysis of the corresponding hetero metal octanoate precursors obtained via coprecipitation using the octanoate ligand as precipitating agent. The precursors were then characterized by FTIR, ICP-AES and TG-DTA analyses and the results reveal the formation of a copper-cobalt-iron hydroxooctanoate represented by the formula [Co1−xCuxFe2(C8H15O2)6(OH)2·2H2O]. The decomposition products obtained upon pyrolysis in air at 400 °C for 3 h were characterized by FTIR, XRD, SEM, TEM, XPS and VSM analyses. FTIR and XRD analyses showed the formation of a single phase mixed spinel ferrite while TEM analysis showed that the particles have a spherical shape with a mean size of 20 nm and form spherical agglomerates with sizes reaching 500 nm in some cases as the SEM images show. The chemical states of the metallic species in the samples were revealed by XPS to be Cu2+, Co2+ and Fe3+. These results combined with XRD confirmed the mixed spinel structure, Co1−xCuxFe2O4 in which Cu2+ ions substitute Co2+ ions in tetrahedral sites for x lower than 0.06 and in octahedral sites for x between 0.06 and 0.08. Magnetic parameters such as saturation magnetization (Ms), coercivity (Hc), remanent magnetization (Mr), magnetocrystalline anisotropy constant (K) and reduced magnetization (Mr/Ms), obtained from magnetic hysteresis loops measured at room temperature, are in agreement with this mixed spinel structure and also indicate that these materials are ferromagnetic and could be good candidates for applications in biomedicine and in microwave devices.

Structural, functional and evolutionary diversity of 4-coumarate-CoA ligase in plants - Lavhale, Santosh G.; Kalunke, Raviraj M.; Giri, Ashok P. (Planta, 2018)
Main conclusions The 4-coumarate-CoA ligases (4CL) contribute in channelizing flux of different phenylpropanoid biosynthetic pathways. Expression of 4CL is optimized at developmental stages and in response to environmental triggers such as biotic and abiotic stresses. The enzyme is valuable in metabolic pathway engineering for curcuminoids, resveratrol, biofuel production and nutritional improvement. Vigorous analysis of regulation at functional and expression level is obligatory to attain efficient commercial production of candidate metabolites using 4CL. Phenylpropanoid pathway provides precursors for numerous secondary metabolites in plants. In this pathway, 4-coumarate-CoA ligase (EC 6.2.1.12, 4CL) is the main branch point enzyme which generates activated thioesters. Being the last enzyme of three shared common steps in general phenylpropanoid pathway, it contributes to channelize precursors for different phenylpropanoids. In plants, 4CL enzymes are present in multiple isoforms and encoded by small gene family. It belongs to adenylate-forming enzyme family and catalyzes the reaction that converts hydroxy or methoxy cinnamic acid derivatives to corresponding thioesters. These thioesters are further utilized for biosynthesis of phenylpropanoids, which are known for having numerous nutritional and medicinal applications. In addition, the 4CL enzymes have been characterized from various plants for their role in plant physiology or in biotic and abiotic stresses. Furthermore, specific isoforms are differentially regulated upon exposure to diverse stimuli leading to flux diversion toward the particular metabolite biosynthesis. Evolutionary studies showed that 4CL separately evolved after monocot and dicot segregation. Here, we provide a comprehensive review on 4CL, which includes evolution, function, gene/protein structure, role in metabolite biosynthesis and cellular partition, and their regulation. Based on the available data, we have explored the scope for pathway engineering by utilizing 4CL enzymes.

Study of photoelectrochemical conductivity mechanism and electrochemical impedance spectroscopy of bulk CuInTe2 – Electrolyte interface - Lakhe, M. G.; Rohom, A. B.; Londhe, P. U.; Bhand, G. R.; Chaure, N. B. (Surfaces and interfaces, 2018)
CuInTe2 (CIT) thin films were electrochemically deposited in an aqueous electrolyte on fluorine doped tin oxide (FTO) coated glass substrates for potentials ranging from −0.6 V to −0.9 V at pH 4. Films were annealed at 400 °C for 15 min in air ambient. Both as-deposited and annealed layers were characterized by various characterization techniques. The conductivity type of the CIT layers was studied by photoelectrochemical (PEC) response and solid–electrolyte interface by impedance spectroscopy. As-deposited samples confirmed amorphous nature of CIT in contrast to that of polycrystalline films obtained upon annealing. Three prominent reflections (1 1 2), (2 2 0)/(2 0 4) and (3 1 2)/(1 1 6) of chalcopyrite CIT were obtained upon annealing. The optical band gap values ∼0.90 eV and 1.08 eV and ∼0.88 eV and 1.01 eV were estimated for as-deposited and annealed CIT layers deposited at −0.7 V and −0.8 V respectively. The most prominent A1 mode observed at 123 cm−1 in the Raman spectra of chalcopyrite CIT was shifted towards lower wavelengths due to the development of tensile strain. Very compact, well adhesive and void free globular layers were deposited at pH 4. The indium content was found to be increased with increasing the deposition potential which agrees well with the overpotential deposition of indium. Photoelectrochemical (PEC) study confirms the growth of p-type CIT layers. The negative resistance at higher frequency domain (3 MHz to 10 kHz) from electrochemical impedance spectroscopy (EIS) confirms the power/energy giving nature of CIT/electrolyte interface at higher frequency and diffusion mechanism of ionic species dominate at lower frequency region

Synthesis of 3-azidopiperidine skeleton employing ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether: total synthesis of d-2 receptor agonist (+/-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Lasonkar, Pradeep B.; Gonnade, Rajesh G. (Organic letters, 2018)
The total synthesis of (+/-)-quinagolide, which is a D-2 receptor agonist, was accomplished via a ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether route. Key features of the synthesis include Claisen rearrangement, PPTS (pyridinium p-toluene-sulfonate)-catalyzed one-pot acetal deprotection, followed by a diastereoselective Henry reaction, which enables construction of the required trans ring junction and CAN-mediated regioselective azidoalkoxylation of enol ether. The PPTS-catalyzed intramolecular diastereoselective Henry reaction to fix three contiguous stereocenters on tetrahydronaphthalene and the first-of-its-kind synthesis of the 3-azidopiperidine skeleton, using a CAN -mediated regioselective azidoalkoxylation of enol ether, are important findings of the present work.

Temperature and pressure dependent Raman spectroscopy of plasma treated multilayer graphene nanosheets - Pawbake, Amit S.; Mishra, K. K.; Machuno, Luis G. B.; Gelamo, Rogerio V.; Ravindranathan, T. R.; Rout, Chandra Sekhar; Late, Dattatray J. (Diamond and Related Materials, 2018)
Understanding of the fine structure at the atomic level and properties of graphene by creating defects is important from the point of view of thermal and stress management. Here we report Raman spectroscopic studies on pristine and plasma treated multilayer graphene to explore the remarkable structure and phonon properties with temperature and pressure. Temperature dependent studies illustrate monotonic softening of G and G′ bands in the temperature range 78 to 573 K. This process can be of fundamental importance in other promising and emerging nano and heterostructured materials. The pressure dependent Raman spectroscopic investigations on G-band of these samples were carried out up to 25 GPa using a diamond anvil cell. Comparatively weak and more compressible nature of the G band (E2g in-plane mode) as a function of applied pressure is found in plasma treated graphene. After pressure release, the samples recover to their original ordered structure. The present study is important for further understanding of the fine structure, properties and effect of defects in graphene, which can affect the atomic bonds, thermal expansion, specific heat, and thermal conductivity as well.
Keywords: graphene; high pressure; Phonon; Plasma treated graphene; Raman spectroscopy

Thermal conductivity studies on magnetite nanofluids coated with short-chain and long-chain fatty acid surfactants - Lenin, R.; Dadwal, A.; Joy, P. A. (Bulletin of Materials Science, 2018)
The effect of the length of surfactant molecules on the surface of the nanoparticles on the thermal conductivity of nanofluids is studied. Magnetite (Fe3O4) nanoparticles of comparable sizes are stabilized with short-chain capric acid (C9H19COOH) and long-chain stearic acid (C17H35COOH) molecules. Thermal conductivity of the two surfactant-coated magnetite nanoparticles dispersed in toluene is measured as a function of the concentration of the particles in the fluids and in the presence of a magnetic field. Studies showed that the critical concentration for thermal conductivity enhancement is lower for stearic-acid-coated fluid as compared with the capric-acid-coated fluid. Comparable enhancement in the thermal conductivity is observed at higher concentrations of the particles. Relatively larger enhancement in the thermal conductivity is observed for the capric-acid-coated fluid in a magnetic field. The difference in the enhancement in the thermal conductivity, depending on the chain length of the surfactant, is explained in terms of the inter-particle magnetic interactions and formation of clusters.

Ti-doped Pd-Au catalysts for one-pot hydrogenation and ring opening of furfural - Date, Nandan Shreehari; La Parola, Valeria; Rode, Chandrashekhar Vasant; Testa, Maria Luisa (Catalysts, 2018)
Pd-Au bimetallic catalysts with different Pd/Au atomic ratios, supported on ordered structured silica (Hexagonal mesoporous silica-HMS, or Santa Barbara Amorphous-15-SBA-15) were evaluated for one-pot hydrogenation of furfural to 1,2-pentanediol. The surface and structural properties of the catalysts were deeply investigated by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), N-2 adsorption isotherms (BET), Infrared spectroscopy (IR), and acid capacity measurements. XPS studies revealed that Ti doped supports had higher dispersion of the active phase, particularly in the case of Pd-Au materials in which Ti played an important role in stabilizing the metallic species. Among the various process conditions studied, such as temperature (160 degrees C), catalyst amount (10% w/w), and reaction time (5 h), H-2 pressure (500 psi) was found to improve the 1,2-pentanediol selectivity. The SBA silica bimetallic Ti-doped system showed the best performance in terms of stability and reusability, after multiple cycles. Under specific reaction conditions, the synergism between Pd-Au alloy and Ti doping of the support allowed the ring opening pathway towards the formation of 1,2-pentanediol in furfural hydrogenation.
Keywords: Bimetallic catalyst; furfural; Hydrogenation; ring-opening

Total synthesis of the potent anti-inflammatory natural product solomonamide A along with structural revision and biological activity evaluation - Jachak, Gorakhnath R.; Athawale, Paresh R.; Agarwal, Heena; Barthwal, Manoj Kumar; Lauro, Gianluigi; Bifulco, Giuseppe; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2018)
Herein, we report the total synthesis of solomonamide A along with its structural revision for the first time. The natural product possesses very potent anti-inflammatory activity, and it contains a macrocyclic peptide having four consecutive stereocenters on an unnatural amino acid component. The key features in the present synthesis include the application of an Evans aldol reaction, ligand-free Heck macrocyclization and chemoselective oxidations. The challenging task of fixing the stereochemistry of OH at the C5-position was accomplished with the help of DFT calculations, applying a quantum-mechanical (QM)/NMR combined approach. Biological evaluation in a mouse paw edema model revealed that a low dose (0.3 mg kg(-1)) of the synthesized solomonamide A showed 74% reduction at 6 h, which was comparable to a high dose (10 mg kg(-1)) standard drug dexamethasone effect (75% at 6 h). Thus, we further confirmed the revised structure of solomonamide A.

Transport properties of cuinte2 thin films obtained by the electrochemical route - Lakhe, Manorama G.; Chaure, Nandu B. (Journal of electronic materials, 2018)
uInTe2 (CIT) thin films were potentiostatically electrodeposited onto cadmium sulfide thin films coated on fluorine doped tin oxide (FTO) glass in an aqueous bath at 75 degrees C by the standard three-electrode system at -0.7 V and -0.8 V, with respect to an Ag/AgCl reference electrode. The electrodeposited layers were heat treated at similar to 80 degrees C in air ambient for 60 min. X-ray diffraction pattern and Raman analysis confirmed the formation of chalcopyrite CIT thin films upon heat treatment. The optical band gap of heat treated CIT films was found to be similar to 1.0 eV and 0.95 eV deposited at -0.7 V and -0.8 V, respectively. Compact and good adhesive growth of CIT layers onto CdS coated FTO substrates is confirmed by field emission scanning electron microscopy. The current density-voltage (J-V) and capacitance-voltage (C-V) measurement was studied to understand the electronic quality of material for development of CIT layers for solar cell applications. The current density was found to be increased by two orders of magnitude upon low-temperature heat treatment. The capacitance-voltage measurement showed sharp depletion and accumulation region. The built in potential was found to be similar to 60 mV and 145 mV in the as-deposited samples, deposited at -0.7 V and -0.8 V, respectively, whereas upon heat treatment it shifted to 159 mV and 210 mV. The capacitance of the CIT films was found to be a function of applied bias and increased with increasing the bias voltage. The depletion width of the heat treated sample was found to be similar to 20 nm and 200 nm for the sample deposited at -0.7 V and -0.8 V, respectively. Thus, the sample deposited at -0.8 V shows optimum electronic properties and is found to be suitable for opto-electronic applications.

Understanding conformational dynamics of complex lipid mixtures relevant to biology - Friedman, Ran; Khalid, Syma; Aponte-Santamaria, Camilo; Arutyunova, Elena; Becker, Marlon; Boyd, Kevin J.; Christensen, Mikkel; Coimbra, Joao T. S.; Concilio, Simona; Daday, Csaba; van Eerden, Floris J.; Fernandes, Pedro A.; et al. (Journal of membrane biology, 2018)
This is a perspective article entitled "Frontiers in computational biophysics: understanding conformational dynamics of complex lipid mixtures relevant to biology" which is following a CECAM meeting with the same name.

Allenoate prenucleophiles: a triply diastereoselective approach to beta-hydroxy esters containing all-carbon alpha-quaternary centers - Maki, Samantha L.; Maity, Pradip; Dougherty, Shannon; Johns, Jennifer; Lepore, Salvatore D. (Organic Letters, 2019)
Allenyl esters activated by titanium(IV) underwent additions to a wide range of aldehydes in high regio- and diastereoselectivities leading to products containing an all carbon quaternary center bearing an alpha-vinyl group that was installed with high selectivity for the Z-geometry. An aldol product was also converted to an indanone offering a new route to this important compound class. Product triple diastereoselectivity has been rationalized using a concerted transition-state model.

Amphiphilic polypyridyl ruthenium complexes: synthesis, characterization and aggregation studies - Bhand, Sujit; Lande, Dipali N.; Pereira, Eulalia; Gejji, Shridhar P.; Weyhermueller, Thomas; Chakravarty, Debamitra; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Polyhedron, 2019)
{Synthesis and characterization of five amphiphilic ruthenium(11) complexes of the type [Ru(Cn)(3)]center dot(PF6)(2) (Cn = 4,4'-dialkyl-2,2'-bipyridine
Keywords: 2; 2 `-bipyridine; Aggregation; Amphiphilic ligand; Metallosurfactant; Ruthenium complexes

Analytical solutions of an isothermal two-dimensional model of a cathode flow channel in transport limited operational regimes of a proton exchange membrane fuel cell - Thosar, Aniket U.; Lele, Ashish K. (Chemical Engineering Science, 2019)
In the quest for obtaining accurate closed-form analytical expressions for polarization curve of a proton exchange membrane fuel cell (PEMFC), we have recently presented a two-dimensional model that accounts for oxygen concentration gradient and velocity gradient along the depth of a cathode flow channel. The model was developed for the case when Tafel kinetics of oxygen reduction reaction (ORR) on the cathode governs the overall rate of oxygen consumption. An improved match between predictions of the model and full three-dimensional simulations was obtained over the entire range of current density compared with earlier models which assumed homogenous oxygen concentration in the channel depth and plug flow velocity profile. In reality however, ORR kinetics is often not the rate limiting step for oxygen consumption in the cathode catalyst layer (CCL) at high current density since the Tafel kinetics is modulated by transport resistances in the CCL. In this article, we extend our two-dimensional analytical model to two different transport-limited regimes of CCL operation namely, slow oxygen transport across the CCL and slow proton transport across the CCL. We compare model predictions with results of full three-dimensional simulations in both cases and show that they are in excellent agreement even in these transport limited operational regimes of PEMFC. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Analytical modelling; Polarization curve; Proton exchange membrane fuel cells; Transport resistance

Biosynthesized Co-doped TiO2 nanoparticles based anode for lithium-ion battery application and investigating the influence of dopant concentrations on its performance - Kashale, A. A.; Rasal, A. S.; Kamble, G. P.; Ingole, V. H.; Dwivedi, P. K.; Rajoba, S. J.; Jadhav, L. D.; Ling, Y. C.; Chang, J. Y.; Ghule, A. V. (Composites Part B: Engineering, 2019)
TiO2 is a good alternative anode material for lithium-ion battery application because of its incomparable high structural stability and safety during the charge/discharge cycles. However, the low intrinsic conductivity of TiO2 has been a limiting factor affecting its cycling and rate capability performance. Here in this work, we present Co-doped TiO2 nanoparticles based anode with good reversibility, cycling stability and rate capability performance for its envisaged application in lithium-ion battery. The Co-doped TiO2 nanoparticles with different Co concentrations (3%, 5%, and 7%) are synthesized using simple and economic biomediated green approach, wherein TiCl4 and Co precursors are allowed to react in Bengal gram bean extract containing biomolecules which act as natural capping agents to control the size of nanoparticles. Among the pure TiO2 and different Co-doped TiO2 samples, the 7% Co-doped TiO2 anode show the highest capacity of 167 mAh g−1 (88.3%) after 100 cycles at the 0.5C current density. The Co-doped TiO2 shows higher and stable coulombic efficiency up to 100 GCD cycles indicating good reversibility. Based on the results, it is expected that the Co-doped TiO2 nanoparticles might be contributing to the enhanced electronic conductivity providing an efficient pathway for fast electron transfer.

Chiral separation of styrene oxides supported by enantiomeric tetrahedral neutral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Ferrara, Joseph D.; Del Campo, Mark; Le Magueres, Pierre; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2019)
The separation of enantiomers is of considerable importance in the preparation of the compounds of biological interests, catalysis, and drug development. Here, we report a novel enantioseparation of styrene epoxides (SOs) resolved in the presence of a pair of enantio-enriched tetrahedral cages. Chiral neutral cages of formula [(Pd3X*)(4)(C6O4Cl2)(6)] ([X*](3-) = RRR-or SSS-[PO(N(*CH(CH3)Ph)(3)](3)) are constructed from Pcl, building units supported by tris(imido)phosphate trianions and chloranilate linkers. These cages exhibit considerable enantioselective separation capabilities toward a series of styrene epoxides via a crystallization inclusion method. A highest enantiomeric excess (ee) value of up to 80% is achieved for the (R)-4-fluorostyrene oxide.

Co amorphous valsartan nifedipine system: Preparation, characterization, in vitro and in vivo evaluation - Lodagekar, Anurag; Chavan, Rahul B.; Mannava, M. K. Chaitanya; Yadav, Balvant; Chella, Naveen; Nangia, Ashwini K.; Shastri, Nalini R. (European Journal of Pharmaceutical Sciences, 2019)
Co amorphous systems are supersaturated drug delivery systems which offer a basic platform for delivery of multicomponent adducts (combination of more than one active pharmaceutical ingredient (API)) and/or as a fixed dose combination therapy, in addition to their potential to improve the apparent solubility, dissolution rate and ultimately bioavailability of poorly water soluble APIs. In the present work, a new drug-drug co amorphous system namely valsartan-nifedipine was prepared by quench cooling technique. Prepared co amorphous system was characterized for its solid state behavior with the help of Fourier Transform Infrared spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and Powder X Ray Diffractometry (PXRD). The optimized co amorphous system was stable for 1 month when exposed to accelerated stability condition (40 +/- 2 degrees C and 75 +/- 5% RH). The improved stability of amorphous nifedipine in co amorphous system was attributed to improved miscibility and intra and intermolecular non-covalent interactions mainly due to presence of hydrogen bonding between valsartan and nifedipine which was studied by FTIR analysis. Co amorphous systems were evaluated by mainly in vitro dissolution and in vivo benefit. In vitro dissolution study showed nearly 5.66 folds and 1.61 folds improvement which was translated to 3.63 and 2.19 times enhancement in vivo C-max for nifedipine and valsartan respectively.

Comprehensive analytical model for polarization curve of a PEM fuel cell and experimental validation - Thosar, Aniket U.; Agarwal, Harshal; Govarthan, S.; Lele, Ashish K. (Chemical Engineering Science, 2019)
The kinetics of cathodic oxygen reduction reaction (ORR) in a proton exchange membrane fuel cell (PEMFC) is significantly modulated by the resistances for transport of reactants to the catalytic sites offered by different components of the fuel cell. This modulation governs the polarization curve of the PEMFC. Consequently, the various operating, geometric and material parameters of the fuel cell dictate the polarization curve. The effects of these parameters on the polarization curve over the entire range of current density, from zero to limiting current, can be predicted using detailed numerical simulations, which are however expensive. Analytical models, although simple can capture the essential details of physico-chemical processes occurring inside a PEMFC and are significantly inexpensive. In this article, we derive an analytical equation of the polarization curve which is valid over the entire range of current density. Specifically, the representative situation of a humidified low temperature PEMFC is considered wherein oxygen transport resistance in the cathode catalyst layer (CCL) is encountered at lower current density than proton transport resistance in the CCL. A novel experimental methodology is illustrated to confirm that this is indeed the case. Next, we elucidate a procedure to determine in-situ oxygen diffusion coefficients in the various domains of an operational PEMFC. Finally, it is shown that the analytical polarization curve predicted using these parameters is in excellent agreement with the experimental and numerically simulated polarization curves over the entire range of current density. The significance of this work is that the analytical model relates the performance of a PEMFC to all operating and geometric parameters as well as the average transport and kinetic properties of the materials used in its different components, without the need for computationally expensive numerical simulations. The model can therefore provide useful insights for enhancing the performance of PEMFC in different regimes of current density as well as for diagnostic purposes. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Fuel cell equation; Modelling; PEMFC; Polarization curve

A copper(ii)-coordination polymer based on a sulfonic-carboxylic ligand exhibits high water-facilitated proton conductivity - Tayade, Sakharam B.; Illathvalappil, Rajith; Lapalikar, Vaidehi; Markad, Datta; Kurungot, Sreekumar; Pujari, Bhatchandra; Kumbhar, Avinash S. (Dalton Transactions, 2019)
Proton conduction ability has been investigated in a new Cu(ii) based coordination polymer (CP), {[Cu-2(sba)(2)(bpg)(2)(H2O)(3)]center dot 5H(2)O}(n) (1), synthesized using the combination of 4-sulfobenzoic acid (4-Hsba) and bipyridine-glycoluril (BPG) ligands. Single crystal X-ray structure determination revealed that 1 features 1D porous channels encapsulating a continuous array of water molecules. Proton conductivity measurements reveal a high conductivity value of 0.94 x 10(-2) S cm(-1) at 80 degrees C and 95% RH. The activation energy (E-a) of 0.64 eV demonstrates that the solvate water, coordinated water and hydrophilic groups in the channels promote the mobility of protons in the framework. Water sorption measurements exhibited hysterical behaviour with a high uptake value of 379.07 cm(3) g(-1). Time-dependent measurements revealed that the proton conductivity is retained even after 12 h of measurements. The proton conduction mechanism was validated by ab initio electronic structure calculations using the Nudged Elastic Band (NEB) method with molecular dynamics (MD) simulation studies. The theoretical activation energy is calculated to be 0.54 eV which is in accordance with the experimental value.

Development of pristine and Au-decorated Bi2O3/Bi2WO6 nanocomposites for supercapacitor electrodes - Gote, Gorkshnath H.; Pathak, Mansi; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2019)
Pristine and Au-decorated Bi2O3/Bi2WO6 nanocomposites were synthesized via a facile hydrothermal method. Characterization techniques such as XRD, FESEM, HRTEM and XPS were used to explore the structural, morphological and electronic properties. Furthermore, electrochemical characterizations including cyclic voltammetry (CV), the galvanostatic charge-discharge (GCD) method, and electrochemical impedance spectroscopy (EIS) were performed to investigate the supercapacitance behaviour of the synthesized materials. Interestingly, the Au-decorated Bi2O3/Bi2WO6 nanocomposite showed a higher capacitance of 495.05 F g(-1) (1 M aqueous KOH electrolyte) with improved cycling stability (99.26%) over 2000 cycles, measured at a current density of 1 A g(-1), when compared to the pristine Bi2O3/Bi2WO6 composite (capacitance of 148.81 F g(-1) and good cycling stability (95.99%) over 2000 cycles at a current density of 1 A g(-1)). The results clearly reveal that the decoration of the Bi2O3/Bi2WO6 composite with Au nanoparticles enhances its supercapacitance behaviour, which can be attributed to an increase in electrical conductivity, good electrical contact between the electrode and electrolyte, and an increase in effective area. The Au-decorated Bi2O3/Bi2WO6 nanocomposite can be considered as an electrode material for supercapacitor application.

Dimedone-based rigid organic scaffold for organizing symmetrical helical peptide chains. - Madica, Krishnaprasad; Lakshmi, Jerripothula K.; Madhu, Suresh; Nadimpally, Krishna Chaitanya; Gonnade, Rajesh; Jagadeesh, Bharatam; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
We describe herein design, synthesis and conformational investigations of polypeptides attached on a rigid dimedone template. Two identical peptide chains are attached on a single carbon containing dimedone as a scaffold. Dimedone assists in controlling the secondary interactions through strong intramolecular helical C-12 and C-15 membered bifurcated hydrogen bonding on both the peptide chains along with propagating the helical architecture of the peptide chains attached. There exists a C-6 hydrogen bonding for the single stranded peptides attached to dimedone. Extensive structural investigations involving single crystal X-ray diffraction, solution-state NMR and CD studies of oligopeptides have been undertaken.
Keywords: dimedone; Helical; hydrogen bonding; Peptides; template

Effect of processing conditions on the rheological properties of blends of ultra high molecular weight polyethylene with high‐density polyethylene - Chaudhuri, K.; Poddar, S.; Pol, H.; Lele, A.; Mathur, A.; Srinivasa Rao, G.S.; Jasra, R. (Polymer Engineering and Science, 2019)
Blends of high‐density polyethylene (HDPE) with small amounts of ultra‐high molecular weight polyethylene (UHMWPE) were prepared by melt mixing in a twin‐screw microcompounder. Two types of UHMWPE differing in their states of chain entanglement were used. The blend composition, time of mixing, and rotation speed of the screws were varied. Rheological properties of the blends were studied in oscillatory shear and uniaxial elongational tests. Reduction in phase angle measured in dynamic shear rheology and increase in extensional strain hardening were found to be useful indicators for quantifying the extent of mixing of the two components. Although the disentangled UHMWPE showed reasonable mixing with HDPE during typical residence times of melt compounding operations, the entangled UHMWPE remained essentially undissolved. The extent of mixing increased with mixing time and screw speed. POLYM. ENG. SCI., 2018. © 2018 Society of Plastics Engineers

Efficient broad-band emission from contorted purely corner-shared one dimensional (1D) organic lead halide perovskite - Biswas, Anupam; Bakthavatsalam, Rangarajan; Shaikh, Samir R.; Shinde, Aparna; Lohar, Amruta; Jena, Satyam; Gonnade, Rajesh G.; Kundu, Janardan (Chemistry of Materials, 2019)

Enhanced energy density and stability of self-assembled cauliflower of Pd doped monoclinic WO3 nanostructure supercapacitor - Gupta, S. P.; Patil, V. B.; Tarwal, N. L.; Bhame, S. D.; Gosavi, S. W.; Mulla, I. S.; Late, D. J.; Suryavanshi, S. S.; Walke, P. S. (Materials Chemistry and Physics, 2019)
Enhanced electrochemical performance of WO3 nanostructures by engineering their morphology, structural and surface defect at nanoscale is feasible. Herein we report the effect of Pd doping on the morphological and electrochemical properties of WO3 at nanoscale prepared by a simple hydrothermal method. The synthesized pristine WO3 (cabbage like morphology) and Pd doped WO3 (cauliflower like morphology) are examined by using XRD, XPS, Raman spectra, BET, FE-SEM, TEM. The morphological investigation shows the effective rebuilding of nanosheets assembled cabbage shaped pristine WO3 into nanobricks assembled cauliflower shaped Pd doped WO3 with improvement in crystallinity, surface area and conductivity. As a result, the enhancement in the electrochemical performance of cauliflower shaped Pd-WO3 is recorded four times higher specific capacitance than pristine WO3. Additionally, the excellent cyclic stability (almost ten times higher than pristine WO3) up to 1100 cycles with nearly 86.95% capacity retention is observed in Pd-WO3 attributed to Pd content and highly modified structural arrangement.

Experimental and density functional theory investigations of catechol sensing properties of ZnO/RGO nanocomposites - Ponnusamy, Rajeswari; Venkatesan, Rajiu; Gangan, Abhijeet; Samal, Rutuparna; Chakraborty, Brahmananda; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2019)
Catechol, an essential industrial feedstock is one of the major environmental pollutant which causes several health issues including skin irritation, eye damage and genetic defects. In this work, we have investigated the catechol sensing performance of ZnO/RGO composites for its quantitative detection. ZnO/RGO composite showed superior electron transfer kinetics, sensitivity (162.04 mu A mM cm(-2)) and lower detection limit (47 nM) than that of bare ZnO nanoparticles. Further, the change in the zeta potential towards the lower negative demonstrated the strong electrostatic interaction between ZnO-RGO and catechol where it is converted as 1, 2 Benzoquinone through redox reactions. By using state of the art of Density Functional Theory simulations, we have demonstrated the interaction of catechol molecule on various ZnO clusters and RGO supported ZnO clusters. The strong bonding between p orbital of O atom of catechol and d orbital of Zn atom and its charge transfer facilitate the oxidation of catechol molecule. In the presence of RGO, the binding energy of catechol and charge transfer increases which qualitatively infer that RGO/ZnO exhibits higher sensitivity compared to bare ZnO and in consistency with the experimental observations.

Facile process for ammonia sensing using electrospun polyvinylidene fluoride/polyaniline (PVDF/PANI) nanofibers chemiresister - Kondawar, Sanchit; Late, Dattatray J.; Anwane, Rajashree S.; Kondawar, Subhash B.; Koinkar, Pankaj; Parinov, Ivan A. (Advanced Materials, 2019)
Electrospun polyvinylidene fluoride/polyaniline (PVDF/PANI) nanofibers chemiresister was fabricated by electrospinning and polymerization. As-fabricated PVDF/PANI nanofibers chemiresister was characterized by SEM, FTIR, TGA and DTG analyses. Cost effective with high accuracy microcontroller based sensor set up was designed for the measurement of change in resistance of chemiresister with respect to different concentrations of ammonia gas at various temperatures. The semiconducting behavior of the chemiresister was found to respond quickly towards ammonia gas. High sensitivity, fast response and recovery of PVDF/PANI nanofibers for ammonia gas at room temperature confirmed the chemiresister as potential candidate for ammonia sensing in environmental monitoring safety systems, chemical and automotive industries.

Facile production of mesoporous WO3-rGO hybrids for high-performance supercapacitor electrodes: an experimental and computational study - Samal, Rutuparna; Chakraborty, Brahmananda; Saxena, Manav; Late, Dattatray J.; Rout, Chandra Sekhar (ACS Sustainable Chemistry & Engineering, 2019)
This work explored a promising supercapacitor electrode material (WO3-rGO hybrids) synthesized via a simplistic one-pot hydrothermal synthesis route. Various analytical studies (X-ray diffraction study, Raman spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller analysis) were employed in furtherance to explore the structural, morphological, compositional, and surface areal properties of the prepared materials. The enhancement in electrochemical supercapacitive properties were evaluated from pure hexagonal phase WO3 to the various hybrids, depending on the concentration of GO introduced into it, using cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectroscopy. The WG-80 composite revealed the high rise in capacitance value of 801.6 F/g overcoming the individual capacitance of rGO (71.11 F/g) and WO3 (94.22 F/g) at a current density of 4 A/g with good cycling stability (75.7%) over 5000 cycles. We have presented quantum capacitance from ab initio calculations and provided theoretical explanation from the orbital interactions.
Keywords: Density functional theory; Hydrothermal method; supercapacitor; WO3-rGO hybrids

Fiber optic Fabry-Perot interferometer sensor: an efficient and fast approach for ammonia gas sensing - Kanawade, Rajesh; Kumar, Ajay; Pawar, Dnyandeo; Late, Dattatray; Mondal, Samir; Sinha, Ravindra K. (Journal of the Optical Society of America B-Optical Physics, 2019)
In this work, we propose and demonstrate a Fabry-Perot-interferometer-based polydimethylsiloxane (PDMS) and poly(methyl methacrylate) (PMMA)-composite-coated optical sensor for ammonia and volatile organic compounds (VOCs) detection at room temperature. The principle of sensing is based on change in the cavity length of the FP cavity in the presence of varied concentrations of gases, which results in changes in the total reflectance due to the shift in wavelength of an interference pattern. The sensing composite material was coated on a single-mode optical fiber by using a simple dip-coating technique and explored it for sensing. The ammonia and VOCs measurements were performed for concentrations ranging from 5 to 500 ppm. The corresponding sensitivity and limit of detection of the developed sensor for ammonia gas detection was observed of the order of around 4.16 pm/ppm and 4.8 ppm, respectively. The response and recovery times of the sensor were found to be of the order of 50 s and 10 s, respectively, for the ammonia gas. This sensor provides a simple, cost-effective, highly sensitive, and repeatable approach to measure ammonia gas and other VOCs at room temperature and could fulfill the demands of industrial applications. (C) 2019 Optical Society of America

Freestanding borophene and Its hybrids - Ranjan, Pranay; Sahu, Tumesh Kumar; Bhushan, Rebti; Yamijala, Sharma S. R. K. C.; Late, Dattatray J; Kumar, Prashant; Vinu, Ajayan (Advanced Materials, 2019)
Borophene, an elemental metallic Dirac material is predicted to have unprecedented mechanical and electronic character. Need of substrate and ultrahigh vacuum conditions for deposition of borophene restricts its large-scale applications and significantly hampers the advancement of research on borophene. Herein, a facile and large-scale synthesis of freestanding atomic sheets of borophene through a novel liquid-phase exfoliation and the reduction of borophene oxide is demonstrated. Electron microscopy confirms the presence of beta(12), X-3, and their intermediate phases of borophene; X-ray photoelectron spectroscopy, and scanning tunneling microscopy, corroborated with density functional theory band structure calculations, validate the phase purity and the metallic nature. Borophene with excellent anchoring capabilities is used for sensing of light, gas, molecules, and strain. Hybrids of borophene as well as that of reduced borophene oxide with other 2D materials are synthesized, and the predicted superior performance in energy storage is explored. The specific capacity of borophene oxide is observed to be approximate to 4941 mAh g(-1), which significantly exceeds that of existing 2D materials and their hybrids. These freestanding borophene materials and their hybrids will create a huge breakthrough in the field of 2D materials and could help to develop future generations of devices and emerging applications.

Fundamentals and sensing applications of 2D materials - Hywel, Morgan; Rout, Chandra Sekhar; Late, Dattatray J. (Elsevier, 2019)
Fundamentals and Sensing Applications of 2D Materials provides a comprehensive understanding of a wide range of 2D materials. Examples of fundamental topics include: defect and vacancy engineering, doping and advantages of 2D materials for sensing, 2D materials and composites for sensing, and 2D materials in biosystems. A wide range of applications are addressed, such as gas sensors based on 2D materials, electrochemical glucose sensors, biosensors (enzymatic and non-enzymatic), and printed, stretchable, wearable and flexible biosensors. Due to their sub-nanometer thickness, 2D materials have a high packing density, thus making them suitable for the fabrication of thin film based sensor devices.

Future prospects of 2D materials for sensing applications - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
Two-dimensional (2D) material attracted significant research interest from the discovery of graphene in 2004. These 2D materials allow a platform for artificial integration of heterostructures with unique platforms that show exotic physical attributes and phenomenon as well as properties and applications. Each layer in 2D materials consist of a covalent bond, a dangling bond-free lattice, and weak van der Waals (vdWs) interaction. This makes it feasible to fabricate lateral and vertical vdWs heterostructures without the constraints of lattice matching and processing compatibility. These vdWs heterostructures open a door for a broad range of applications in electronics, optoelectronics, flexible devices, sensors, and photovoltaics. In this chapter, we have critically assessed the recent developments in 2D materials, the fabrication of heterostructures, and their application for sensing purposes. We conclude with current challenges and ideas concerning future developments in this merging field.

Graphene nanosheets assisted carbon hollow cylinder for high-performance field emission applications - Tripathi, Prashant; Gupta, Bipin Kumar; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J.; Srivastava, Onkar Nath (Materials Research Express, 2019)
Electron sources are critical constituents for myriad many electronic applications including electron imaging, mass spectroscopy etc. Here, we report the realization of high-performance field emission from graphene assisted carbon hollow cylinders (Gr-CHCs) composed of multi-stacked radially aligned CNTs. These CHCs have built-in synthesis related Fe nanoparticles (NPs). This engineered nano-structure exhibits excellent field emission properties such as one of the ultra-low turn-on field (0.64V mu m(-1) at 10 mu A cm(-2)), low threshold field (0.74V mu m(-1) at 100 mu A cm(-2)), very high current density (15.49 mA cm(-2) at 1.32V mu m(-1)) which is nearly double the current density obtained in our previous study. High field enhancement factor (0.72. x. 10(4)) with highly stable emission current at 100 mu A was observed for more than 3 hrs at the base pressure of similar to 1. x. 10(-8) mbar. This study suggests an approach to enhance the current density using the proposed innovative nanostructure and forms the basic theme of this communication. Highly efficient and stable field emissions observed are attributed to the geometry of cylinder and the production of the high density of sharp protrusions within the graphene sheets which enhance the local electric field and dramatically enhance field emission. This innovative cylindrical geometry associated with graphene assisted on Fe bearing aligned CNTs along with the periphery of the bulk cylinder provides an easy injection of electrons from the conduction band of CHCs into the vacuum in the presence of an external electric field. The tunability of field emission properties of these CHCs can be easily achieved by tailoring their diameter (10 and 20 mm) and different concentrations of the precursor. This new approach of the graphene assisted cylindrical geometry-based field emitter source provides enormous prospects and demand for next-generation high resolutions display devices.
Keywords: Carbon nanotubes; field emission; graphene assisted carbon hollow cylinder; protrusions

Heteropolyacids supported on mesoporous AlSBA-15 as efficient catalysts for esterification of levulinic acid - Lucas, Nishita; Gurrala, L.; Athawale, Anjali (Journal of Porous Materials, 2019)
A comparative study of different heteropoly acids supported on mesoporous AlSBA-15 for the synthesis of ethyl levulinate has been undertaken for the first time. The catalysts were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, inductively coupled plasma-optical emission spectrometry, thermo gravimetric analysis, temperature programmed desorption of NH3 and N-2 sorption studies. Insights into crucial parameters for the esterification reactions are also furnished. A distinct correlation was observed between acid density and conversion revealing that the distribution of acidic sites and their accessibility by the reactant moieties plays an important role in determining the overall activity. The effects of various reaction parameters were investigated to enhance the catalytic activity and yield of ethyl levulinate. Under the optimized conditions, levulinic acid conversion of 87.4 mol% and ethyl levulinate selectivity of 100% could be obtained with silicotungstic acid supported on AlSBA-15.

Hydrothermal growth of MoSe2 nanoflowers for photo- and humidity sensor applications - Shelke, Nitin T.; Late, Dattatray J. (Sensors and Actuators A-Physical, 2019)
In the present investigation, we report the synthesis of molybdenum diselenide (MoSe2) nanoflowers by facile hydrothermal method for photo- and humidity sensor applications. The obtained samples were characterized thoroughly by x-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The XRD spectrum shows crystalline nature of the sample. Raman spectroscopy shows two prominent vibration modes of E-2 (g)1 and A(1g) at (2) over tilde 41 and (2) over tilde 83 cm(-1) respectively. The crystalline nature of the sample confirmed with the TEM. The MoSe2 nanoflowers based sensor shows high photosensitivity and good response to humidity with excellent prolong stability. The maximum photoresponsitivity of (1) over tilde 94% along with response of (4) over tilde0 ms and recovery time of (4) over tilde8 ms were observed for the sample. In case of humidity sensor, response time of (5) over tilde3 s and recovery time of (1) over tilde3 s with maximum sensitivity -74% were observed under humidity environments. It suggests that, MoSe2 nanoflowers appear as a potential candidate for constructing high-performance nanoelectronics devices. (C) 2019 Elsevier B.V. All rights reserved.

Introduction - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
The book provides comprehensive and updated research contribution about advances in synthesis/growth of 2D materials for various sensor applications, their working principles, and mechanism behind the sensor as well physics and chemistry of materials.

Molecular cobalt(II) complexes for tau polymerization in Alzheimer's disease - Gorantla, Nalini Vijay; Landge, Vinod G.; Nagaraju, Pramod Gudigenahally; Priyadarshini, Poornima C. G.; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (ACS Omega, 2019)
Tau is an axonal protein known to form abnormal aggregates and is the biomarker of Alzheimer's disease. Metal-based therapeutics for inhibition of Tau aggregation is limited and rarely reported in contemporary science. Here, we report the first example of rationally designed molecular cobalt(II)-complexes for effective inhibition of Tau and disaggregation of preformed Tau fibrils. The mechanistic studies reveal that prevention of Tau aggregation by cobalt-based metal complexes (CBMCs) is concentration-dependent and Tau seldom exhibits conformational changes. Interestingly, CBMCs play dual role in causing disassembly of preformed aggregates as well as inhibition of complete Tau aggregation. Furthermore, CBMCs were nontoxic and maintained the tubulin network intact. CBMCs also prevented okadaic acid-induced toxicity in SH-SY5Y cells thus, preventing hyperphosphorylation of Tau. We believe that this unprecedented finding by the newly developed molecular complexes has a potential toward metal-based therapeutics for Alzheimer's disease.

Negative axicon tip-based fiber optic interferometer cavity sensor for volatile gas sensing - Kanavvade, Rajesh; Kumar, Ajay; Pawar, Dnyandeo; Vairagi, Kaushal; Late, Dattatray; Sarkar, Sudipta; Sinha, Ravindra K.; Mondal, Samir (Optics Express, 2019)
In this research work we demonstrated negative axicon optical fiber tip filled with Polydimethylsiloxane (PDMS) as a sensor platform for volatile organic gases detection at room temperature. The response of the sensor was measured with various Volatile Organic Compounds (VOCs) such as Chloroform, Hexane, Isopropanol, Acetone, Toluene and Methanol in the concentration ranging from 5 to 200 ppm. The corresponding sensitivity and limit of detection (LOD) of the developed sensor for the measured VOCs were observed between the order of around 23.7 to 3.2 pm/ppm and 0.84 to 6.10 ppm, respectively. The response and recovery time of sensor were found between the order of 30 to 57 seconds and 8 to 25 seconds respectively for the measured VOCs. Thermal stability of the developed sensor was also studied at 30-70 degrees C with intervals of 10 degrees C. The principle of sensing is based on change in the length of the Fabry-Perot Interferometric (FPI) cavity in the presence of varied concentrations of VOCs, which results in changes in the shift in wavelength of an interference pattern attributed to the change in PDMS filling the cavity length (swelling). The experimentally observed trends in the relative swelling of PDMS with VOCs are found in agreement with the theoretically calculated values obtained from the Hansen solubility parameter (HSP). The developed gas sensor has the potential to fulfill the demands of industrial applications.

Nickel(ii)-catalyzed direct olefination of benzyl alcohols with sulfones with the liberation of H-2 - Landge, Vinod G.; Yadav, Vinita; Subaramanian, Murugan; Dangarh, Pragya; Balaraman, Ekambaram (Chemical Communications, 2019)
A nickel(II)-catalyzed direct olefination of benzyl alcohols with sulfones to access various terminal and internal olefins with the liberation of hydrogen gas is reported.

Photo sensor based on 2D materials - Late, Dattatray J.; Bhat, Anha; Rout, Chandra Sekhar (Fundamentals and Sensing Applications of 2D Materials, 2019)
This chapter starts with a general introduction to the interaction of light with matter and use of this principle for sensing. Photo-sensing devices based on two-dimensional (2D) materials are compared to conventional designs and their respective differences discussed in detail. A range of 2D materials are introduced with a generic comparison based on their individual properties and importance to the generation of a photoresponse. Besides transition-metal dichalcogenides, the chapter also deals with black phosphorous photosensor devices. Different heterostructure architectures based on 2D layered structures are investigated and their role in next generation optoelectronics is discussed.

Pressure-induced phase transitions in germanium telluride: raman signatures of anharmonicity and oxidation - Pawbake, Amit; Bellin, Christophe; Paulatto, Lorenzo; Beneut, Keevin; Biscaras, Johan; Narayana, Chandrabhas; Late, Dattatray J.; Shukla, Abhay (Physical Review Letters, 2019)
Pressure-induced phase transitions in GeTe, a prototype phase change material, have been studied to date with diffraction which is not sensitive to anharmonicity-induced dynamical effects. GeTe is also prone to surface oxidation which may compromise surface sensitive measurements. These factors could be responsible for the lack of clarity about the phases and transitions intervening in the phase diagram of GeTe. We have used high-pressure Raman scattering and ab initio pseudopotential density functional calculations to unambiguously establish the high-pressure phase diagram and identify three phases up to 57 GPa, a low-pressure rhombohedral phase, an intermediate pressure cubic phase, and a high-pressure orthorhombic phase. We detect substantial broadening and softening of Raman modes at low pressure and identify the transition regions and possible intermediate phases.

Realization of efficient field emitter based on reduced graphene oxide-Bi2S3 heterostructures - Gote, Gorkshnath H.; Bhopale, Somnath R.; More, Mahendra A.; Late, Dattatray J. (Physica Status Solidi A-Applications and Materials Science, 2019)
Herein, Bi2S3 nanorods and reduced graphene oxide (rGO)-Bi2S3 heterostructures are synthesized using a simple hydrothermal method. The structural, morphological, chemical, and elemental analysis of as-synthesized materials is performed using X-ray diffraction (XRD), Raman spectroscopy, field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Field emission (FE) studies are carried out on both pristine Bi2S3 nanorods and rGO-Bi2S3 heterostructure samples at a base pressure of approximate to 1 x 10(-8) mbar. The results show that the rGO-Bi2S3 heterostructure emitter has superior FE performance compared to pristine Bi2S3 emitters in terms of the turn-on field (2.6 V mu m(-1) at 10 mu A cm(-2)) and threshold field (4.0 V mu m(-1) at 100 mu A cm(-2)) along with a high emission current density of approximate to 1464 mu A cm(-2) at an applied electric field of 7.0 V mu m(-1). The rGO-Bi2S3 heterostructure emitter exhibits very good emission current stability, tested for more than 3 h duration, characterized by standard deviation values approximate to 2.84 and 4.06, corresponding to preset values 12 and 100 mu A. This study implies that one-step hydrothermal route can be efficiently used to synthesize organic-inorganic heterostructures that possess unique morphology. Furthermore, the synthesized rGO-Bi2S3 heterostructure emitter shows potential as an electron source for practical application in vacuum microelectronic devices.
Keywords: Bi2S3; field emission; Heterostructures; Nanorods; Reduced graphene oxide

Role of Li+ and Fe3+ in modified ZnO: Structural, vibrational, opto-electronic, mechanical and magnetic properties - Bajpai, G.; Moirangthem, I.; Sarkar, S.; Barman, S. R.; Vinod, C. P.; Bajpai, S.; Riyajuddin, S.; Ghosh, K.; Basaula, D. R.; Khan, M.; Liu, S. -W.; Biring, S.; et al. (Ceramics International, 2019)
When Fe is doped in ZnO, a situation of charge imbalance is created due to the higher charge of Fe3+. A charge balance may be obtained by co-doping Li+0.5Fe3+0.5 combinations. A solid solution of Zn1-x(Fe0.5Li0.5)xO (0 ≤ x ≤ 0.03125) is synthesized with this viewpoint. The crystallites belong to a wurtzite P63mc space group, with lattice parameters a, b and c increasing nominally for x = 0.0156 and thereafter remaining invariant. The size varies in the range ~ 60–142 nm. Interstitials of Li and Zn ions are formed. Along with Fe3+ substitution these defects are reasons for O interstitials. These oxygen interstitials increase the red emission while reduction of oxygen vacancies reduces the green emission. These point defects create structural distortion and strain which can generate Zn vacancies. Bandgap reduces due to shallow defects. Mid-bandgap states due to oxygen interstitials and Fe 3d-O 2p hybridization result in NIR emission. On the other hand the crystal surface deforms due to Li addition which hardens the materials. A weak ferromagnetism appears at very low temperature which is enhanced by Li+ addition. Long range exchange mechanism between Fe3+ ions appears in the samples, mediated by magnetic polarons due to point defects.
Keywords: hardness; NIR emission; Shallow and deep level defects; Weak ferromagnetism; ZnO

Solvothermal growth of PbBi2Se4 nano-flowers: a material for humidity sensor and photodetector applications - Aher, Rahul; Bhorde, Ajinkya; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Naik, Dhirsing; Vairale, Priti; Karpe, Smita; Late, Dattatray; Prasad, Mohit; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2019)
In the present work, lead bismuth selenide (PbBi2Se4) nano-flowers are synthesized by using a simple solvothermal method. Humidity sensor and photodetector based on PbBi2Se4 nano-flowers are fabricated on indium tin oxide (ITO) substrates and their sensing properties are investigated. Formation of PbBi2Se4 is confirmed by XRD, EDS, and XPS whereas formation of nano-flowers is confirmed by SEM and TEM analysis. XRD analysis reveals the hexagonal crystal structure of PbBi2Se4 phase with a = b = 4.22 angstrom, and c= 17.42 angstrom. The surface morphology of PbBi2Se4 clearly shows the formation of well-organized flower-like nanostructures which closely resembles the shape of Dahlia. The elemental mapping of chemical constituents obtained from SEM-EDS analysis shows uniform distribution of chemical constituents for the Pb, Bi, and Se in PbBi2Se4 nano-flowers. The PbBi2Se4 nano-flowers based humidity sensor has a typical response time of approximate to 65s and recovery time of approximate to 75 s. In case of PbBi2Se4 nano-flowers-based photodetector, the response and recovery time are observed approximate to 121 and approximate to 123 s, respectively, under visible light illumination with photoresponsivity (5 x 10(-6)), photosensitivity (2.16%), and quantum efficiency (1.5 x 10(4)). The obtained results demonstrate the potential applications of solvothermally grown PbBi2Se4 nano-flowers-based devices for humidity sensors and photodetectors. The ease of the present work is to develop novel material to obtain device quality humidity sensors and photodetectors.
Keywords: humidity sensor; PbBi2Se4; photodetector; XPS; XRD

Study of rheology and plug assist thermoforming of linear and branched pp homopolymer and impact copolymer - Marathe, D.; Shelar, S.; Mahajan, S.; Ahmad, Z.; Gupta, S.; Kulkarni, S.; Juvekar, V; Lele, A. (International Polymer Processing, 2019)
Polypropylene (PP) is one of the fastest growing thermoplastic polymers in the world, second only to polyethylene. This is primarily due to its excellent balance of physical and chemical properties at a lower cost. PP however possesses low melt strength on account of its linear structure and hence is not easily amenable to processing techniques that involve free surface stretching deformations like thermoforming, blow molding and extrusion film casting. One way to enhance the melt strength of PP is to incorporate long chain branches in its molecular architecture. The present study focuses on the impact of rheology of linear and branched PP on their thermoforming characteristics. Two grades each of linear and long chain branched (LCB) PP homopolymer and impact copolymer (ICP) were used. It was observed that the LCB-PP homopolymer and LCB-ICP showed higher flow activation energy, reduced value of loss tangent and nearly equal frequency dependence of storage and loss moduli in shear rheology. Also, a strong strain hardening behavior was displayed in extensional rheology by the LCB grades. Plug assist thermoforming experiments were carried out to assess the effect of long chain branching on surface strain and thickness distribution for axisymmetric cups of two draw ratios. Biaxial surface strain maps of the formed cups were quantified using Grid Strain Analysis (GSA). Thermoformed cups made from LCB-PP homopolymer and LCB-impact copolymer showed lower surface strain and overall higher thickness as compared to cups made from their linear counterparts, which is in accordance with what might be expected from their rheology.

Superior humidity sensor and photodetector of mesoporous ZnO nanosheets at room temperature - Gupta, Shobhnath P.; Pawbake, Amit S.; Sathe, Bhaskar R.; Late, Dattatray J.; Walke, Pravin S. (Sensors and Actuators B-Chemical, 2019)
Miniaturized sensor technology is vastly demanding multifunctional materials to fulfill many requirements simultaneously; instead of integrating various sensors into a single device. Efficient operation of these miniaturized sensors at room temperature is highly feasible and cost-effective. The humidity sensing and photodetection is precise merit of sensing in special usage like artificial skin. Sensitivity enhancement in both humidity and photodetection required the high surface area for adsorption as well as a high charge transfer mechanism. The two dimensional (2D) zinc oxide nanosheets (ZnO NS) is the ultimate structure for dimensionally confined transport properties owing to the specific surface atomic configuration that results in high sensitivity, low operating temperature, fast response and recovery, and improved selectivity. Furthermore, introducing porosity into 2D nanostructures has opened new opportunities to enhance the efficiency of sensors and detectors via increasing large surface area and tunable physical and chemical properties. Here we report preparation of mesoporous and highly crystalline 2D ZnO NS by a single step, template free, cost-effective chemical method. The structural and morphological characterizations of ZnO NS are carried out using XRD, FESEM, XPS, TEM respectively. The high-resolution TEM images emphasize sheet-like morphology with a thickness of around 18-22 nm. Further the mesoporous ZnO NS (MZNS) with the pore size between 5-10 nm are achieved by simple heat-treatment. XPS and PL study is confirming the oxygen deficiency in MZNS. The MZNS exhibits an excellent responsivity than PZNS with a fast response and rapid recovery time of 25 s and 5 s respectively along with good cyclic stability which is highly crucial for smart humidity sensor. Furthermore, it considerably enhances photo-sensor performance than pristine ZnO NS (PZNS) with (similar to)1 s response time as well as (similar to)1 s recovery time along with better stability. These promising results illustrate the great potential of MZNS for next-generation humidity sensors and photodetectors.
Keywords: humidity sensor; Mesoporous; nanosheets; Photo-detector

Synthesis and characterization of zinc oxide nanoparticles by using polyol chemistry for their antimicrobial and antibiofilm activity - Mahamuni, P. P.; Patil, P. M.; Dhanavade, M. J.; Badiger, M. V.; Shadija, P. G.; Lokhande, A. C.; Bohara, R. A. (Biochemistry and Biophysics Reports, 2019)
The present investigation deals with facile polyol mediated synthesis and characterization of ZnO nanoparticles and their antimicrobial activities against pathogenic microorganisms. The synthesis process was carried out by refluxing zinc acetate precursor in diethylene glycol(DEG) and triethylene glycol(TEG) in the presence and in the absence of sodium acetate for 2 h and 3 h. All synthesized ZnO nanoparticles were characterized by X-ray diffraction (XRD), UV visible spectroscopy (UV), thermogravimetric analysis (TGA), fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy(FESEM), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX) technique. All nanoparticles showed different degree of antibacterial and antibiofilm activity against Gram-positive Staphylococcus aureus (NCIM 2654)and Gram-negative Proteus vulgaris (NCIM 2613). The antibacterial and antibiofilm activity was inversely proportional to the size of the synthesized ZnO nanoparticles. Among all prepared particles, ZnO nanoparticles with least size (~ 15 nm) prepared by refluxing zinc acetate dihydrate in diethylene glycol for 3 h exhibited remarkable antibacterial and antibiofilm activity which may serve as potential alternatives in biomedical application.

Synthesis of a 3D free standing crystalline NiSex matrix for electrochemical energy storage applications - Dinara, Syed Mukulika; Samantara, Aneeya K.; Das, Jiban K.; Behera, J. N.; Nayak, Saroj K.; Late, Dattatray J.; Rout, Chandra Sekhar (Dalton Transactions, 2019)
The electrochemical performance for energy storage of three-dimensional (3D) self-supported heterogeneous NiSex cubic-orthorhombic nanocrystals grown by a facile one-step chemical vapour deposition (CVD) approach on Ni foam substrates has been explored. NiSex shows a high specific capacitance of 1333 F g(-1) with ultra-high energy (105 W h kg(-1)) and power (54 kW kg(-1)) densities. Furthermore, by integrating the as-grown NiSex as the anode and reduced graphene oxide as the cathode, a hybrid super-capacitor (HSC) prototype with a coin cell configuration has been fabricated. The device shows better capacitance (40 F g(-1)) with high energy (22 W h kg(-1)) and power (5.8 kW kg(-1)) densities and robust cycling durability (similar to 88% capacitance retention after 10 000 repeated cycles). For practical reliability of the as-fabricated HSC, a red LED has been illuminated by connecting it with two charged coin cells. These outstanding performances of the HSC prove to be promising for applications in high energy storage systems.

Synthesis of nanogate structure in GO-ZnS sandwich material - Kumar, Praveen; Luwang, Meitram Niraj (Scientific Reports, 2019)
Graphite Oxide (multi-layer) composite with other materials has a huge application in various field of science, due to its excellent and unique properties. Even though from past decade, immense research has been done by materials scientists in this field, but the chemistry is still not yet satisfactory. Here, in this work, through the discovery of Nanogate structure, we have reported for the first time the experimental results that enlightened the clear chemistry between the GO and ZnS which is further supported by the DFT calculations. This novel synthesis method led to the discovery of nanogate structure sandwiched between the GO layers. The nanogate formation also shows enhanced properties for various applications like photocatalytic activities, etc. Due to the nanogate formation, there might be a possibility of enormous generation of electrons on excitation of the composite materials, which can be a boom for various applications like photocatalysis, water splitting, solar cell, etc.

Temperature-dependent phonon dynamics of supported and suspended monolayer tungsten diselenide - Carvalho, Thais C. V.; Araujo, Francisco D. V.; dos Santos, Clenilton Costa; Alencar, Luciana M. R.; Ribeiro-Soares, Jenaina; Late, Dattatray J.; Lobo, Anderson Oliveira; Souza Filho, Antonio Gomes; Alencar, Rafael S.; Viana, Bartolomeu C. (AIP Advances, 2019)
Two-dimensional materials exhibit great potential for high-performance electronics applications and the knowledge of their thermal properties is extremely necessary, since they are closely related to efficient heat dissipation and electron-phonon interactions. In this study we report the temperature-dependence of the out-of-plane A(1g) Raman mode of suspended and supported CVD-grown single-crystalline tungsten diselenide (WSe2) monolayer. The A(1g) phonon wavenumber is linearly red-shifted for temperature ranging from 98 to 513 K, with first-order temperature coefficients beta of -0.0044 and -0.0064 cm(-1)/K for suspended and supported monolayer WSe2, respectively. The higher beta module value for supported sample is attributed to the increase of the phonon anharmonicity due to the phonon scattering with the surface roughness of the substrate. Our analysis of the temperature-dependent phonon dynamics reveal the influence of the substrate on thermal properties of monolayer WSe2 and provide fundamental information for developing of atomically-thin 2D materials devices. (C) 2019 Author(s).

Temperature-dependent Raman spectroscopy and sensor applications of PtSe2 nanosheets synthesized by wet chemistry - Pawar, Mahendra S.; Late, Dattatray J. (Beilstein Journal of Nanotechnology, 2019)
We report on a wet chemistry method used to grow PtSe2 nanosheets followed by thermal annealing. The SEM and TEM analysis confirms the formation of PtSe2 nanosheets. Furthermore, XRD, Raman, XPS and SAED patterns were used to analyze the crystal structure and to confirm the formation of the PtSe2 phase. The temperature-dependent Raman spectroscopy investigations were carried out on PtSe2 nanosheets deposited on Si substrates in the temperature range 100-506 K. The shifts in Raman active E-g and A(1g) modes as a function of temperature were monitored. The temperature coefficient for both modes was calculated and was found to match well with the reported 2D transition metal dichalcogenides. A PtSe2 nanosheet-based sensor device was tested for its applicability as a humidity sensor and photodetector. The humidity sensor based on PtSe2 nanosheets showed an excellent recovery time of approximate to 5 s, indicating the great potential of PtSe2 for future sensor devices.
Keywords: nanosheets; PtSe2; Raman spectroscopy; Sensor; thermal effect

Terpene profiling, transcriptome analysis and characterization of cis–terpineol synthase from Ocimum - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Dholakia, Bhushan B.; Lavhale, Santosh G.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Physiology and Molecular Biology of Plants, 2019)
Ocimum species produces a varied mix of different metabolites that imparts immense medicinal properties. To explore this chemo-diversity, we initially carried out metabolite profiling of different tissues of five Ocimum species and identified the major terpenes. This analysis broadly classified these five Ocimum species into two distinct chemotypes namely, phenylpropanoid-rich and terpene-rich. In particular, -caryophyllene, myrcene, limonene, camphor, borneol and selinene were major terpenes present in these Ocimum species. Subsequently, transcriptomic analysis of pooled RNA samples from different tissues of Ocimum gratissimum, O. tenuiflorum and O. kilimandscharicum identified 38 unique transcripts of terpene synthase (TPS) gene family. Full-length gene cloning, followed by sequencing and phylogenetic analysis of three TPS transcripts were carried out along with their expression in various tissues. Terpenoid metabolite and expression profiling of candidate TPS genes in various tissues of Ocimum species revealed spatial variances. Further, putative TPS contig 19414 (TPS1) was selected to corroborate its role in terpene biosynthesis. Agrobacterium-mediated transient over-expression assay of TPS1 in the leaves of O. kilimandscharicum and subsequent metabolic and gene expression analyses indicated it as a cis–terpineol synthase. Overall, present study provided deeper understanding of terpene diversity in Ocimum species and might help in the enhancement of their terpene content through advanced biotechnological approaches.
Keywords: Agro-infiltration assay; Metabolite profiling; Ocimum; Terpene synthase; Terpenes; Transcriptome

Valorization of oceanic waste biomass: a catalytic perspective - Lucas, Nishita; Athawale, Anjali A.; Rode, Chandrashekhar V. (Chemical Record, 2019)
Efficacious waste utilization is vital in context of sustainability. The past decade has witnessed attempts of usage of land biomass and wastes for various applications, contributing towards a sustainable society. Exploitation of the marine biomass, which does not compete with habitation and food production like land biomass has been largely unnoticed and therefore not being utilized judiciously. Researchers have mainly exploited these resources as functional materials having significant potential applications. However, a catalytic perspective for the valorisation of these polymers arising from oceanic waste widens their scope and ameliorates its use. The objective of the present review is to demonstrate the effectiveness of chitin/chitosan as a catalyst and as a feedstock for deriving important fuels and chemicals. It displays all the reactions heterogeneously catalyzed by them along with the strategic methodology. Their important catalytic organic transformations attempted so far, have also been discussed. The future perspectives are also presented which if inculcated would improve the value addition of the waste, paving a way for greener and imperishable world.

VSe2-reduced graphene oxide as efficient cathode material for field emission - Ratha, S. (Journal of Physics and Chemistry of Solids, 2019)
Field emission properties of pristine VSe2 and its hybrid with reduced graphene oxide (RGO) have been investigated in detail. Promising field emission performance were noted with lower values of turn-on and threshold fields of ∼1.3 V μm−1 and 2.12 V μm−1 respectively for the VSe2/RGO hybrid which is much more superior than that of pristine VSe2 emitter and other 2D materials. Density Functional Theory (DFT) simulations have also been performed to qualitatively support our experimental observations through demonstration of Density of States and computation of work function for pristine VSe2 and hybrid VSe2/RGO. The lowering of work function and appearance of additional states near Fermi level from carbon p orbital of RGO is responsible for superior field emission characteristics in hybrid VSe2/RGO compared to pristine VSe2 which supports our experimental observations. Our experimental data and theoretical insight from electronic structure simulations strongly infer that the synthesized hybrid VSe2/RGO has the potential to be tailored as efficient and high performance cathode material in field emission based devices.
Keywords: cathode material; Chalcogenide; Density functional theory; field emission; Vanadium diselenide; Work function

Anthrone-spirolactam and quinoline hybrid based sensor for selective fluorescent detection of Fe(3+)ions - Darole, Ratanamala S.; Christopher Leslee, Denzil Britto; Mukherjee, Anagh; Gonnade, Rajesh G.; Karuppannan, Sekar; Senthilkumar, Beeran (2020)
The synthesis of a novel, and highly selective Fe(3+)ion sensor based on anthrone-spirolactam and its quinoline hybrid ligand is reported. The designed ligand displayed selective detection of Fe(3+)ions with enhanced fluorescence emission. The complexation of Fe(3+)ion led to a red shift of 32 nm from 420 nm to 452 nm, and a several fold increase in intensity with fluorescent green emission. The complexation (detection) of Fe(3+)ions with ligand resulted in chelation enhanced fluorescence and intramolecular charge transfer through the inhibition of C=N isomerization. This hybrid sensor shows high sensitivity and selectivity, spontaneous response, and works on a wide pH range a minimum detection limit of 6.83 x 10(-8)M. Importantly, the sensor works through the fluorescence turn-on mechanism that overcomes the paramagnetic effect of Fe(3+)ions. The binding mechanism between the ligand and the Fe(3+)ions was established from the Job's plot method, optical studies, Fourier transfor infrared spectroscopy, NMR titration, fluorescence life-time studies, and density functional theory optimization. The sensor displayed excellent results in the quantification of Fe(3+)ions from real water samples. Furthermore, due to its biocompatibility nature, fluorescent spotting of Fe(3+)ions in live cells revealed its bioimaging applications.
Keywords: anthrone-spirolactam-quinoline; Cell imaging; fluorescence; intramolecular charge transfer; iron

Boron nitride and oxide supported on dendritic fibrous nanosilica for catalytic oxidative dehydrogenation of propane - Belgamwar, Rajesh; Rankin, Andrew G. M.; Maity, Ayan; Mishra, Amit Kumar; Gomez, Jennifer S.; Trebosc, Julien; Vinod, Chathakudath P.; Lafon, Olivier; Polshettiwar, Vivek (ACS Sustainable Chemistry & Engineering, 2020)
In this work, we were able to significantly increase the activity of boron nitride (BN) catalysts used for the oxidative dehydrogenation (ODH) of propane by designing and synthesizing BN supported on dendritic fibrous nanosilica (DFNS). DFNS/BN showed a markedly increased catalytic efficiency, accompanied by exceptional stability and selectivity. Textural characterization, together with solid-state nuclear magnetic resonance (NMR) and X-ray photoelectron spectroscopic analyses, indicates the presence of a combination of unique fibrous morphology of DFNS and various boron sites connected to silica to be the reason for this increase in the catalytic performance. Notably, DFNS/B2O3 also showed catalytic activity, although with more moderate selectivity compared to that of DFNS/BN. Solid-state NMR spectra indicate that the higher selectivity of DFNS/BN might stem from a larger amount of hydrogen-bonded hydroxyl groups attached to B atoms. This study indicates that both boron nitride and oxide are active catalysts and by using high surface area support (DFNS), conversion from propane to propene as well as productivity of olefins was significantly increased.
Keywords: Electron microscopy; heterogeneous catalysis; Nanostructures; NMR spectroscopy; propane dehydrogenation; X-ray diffraction; X-ray photoelectron spectroscopy

CO2 hydrogenation to formate by palladium nanoparticles supported on N-incorporated periodic mesoporous organosilica - Betsy, K. J.; Lazar, Anish; Pavithran, Anjuna; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2020)
Development of a heterogeneous catalyst capable of selective transformation of CO2 to valuable products still remains a challenge. In this article, we account for the surfactant-directed synthesis of a new framework-incorporated nitrogen-containing periodic mesoporous organosilica nanosphere (NPMO). A thoroughly characterized N-incorporated hybrid PMO was utilized as a platform for stabilizing well-dispersed and easily accessible Pd nanoparticles (Pd-NPMO) without using any stabilizing agents or expensive dendrimers. Further, this bifunctional hybrid catalyst has been demonstrated to heterogeneously catalyze aqueous phase CO2 hydrogenation (CO2/H-2 ratio 1:3) for the direct synthesis of formate under 4 MPa pressure and at 100 degrees C. To validate the superior performance of the Pd-NPMO catalyst, we compared the activity with Pd-SBA-15 catalysts, and the results showed a 10-fold increase in turnover frequency of 108 h(-1) using Pd on NPMO which envisaged the crucial role of nitrogen sites in this catalyst to boost the CO2 valorization to formate.
Keywords: CO2 hydrogenation; Formic acid synthesis; Hybrid silica; Pd nanoparticles; PMO

Degradation of metaldehyde in aqueous solution by nano-sized photocatalysts and granular activated carbon - Kim, Jong Kyu; Jiang, Tingting; Li, Zhoujun; Mayadevi, Suseeladevi; Bharat, Kale; Joo, Jin Chul; Campos, Luiza Cintra (Journal of Nanoscience and Nanotechnology, 2020)
Metaldehyde has been detected in drinking water system in relatively high concentration exceeding European water quality standard. In order to address this problem, the aim of this project was to treat metaldehyde aqueous solution by advanced oxidation processes (AOPs) and granular activated carbon (GAC) column. Ten novel materials were tested for degradation rates of metaldehyde under ultraviolet light irradiation (UVC). For treatment of 1 mg/L metaldehyde solution by AOPs, the highest degradation rate is 16.59% under UVC light with the aid of nitrogen doped titanium dioxide coated graphene (NTiO2/Gr). Furthermore, 0.5 mg/L is the optimal concentration for degradation of metaldehyde with N-TiO2/Gr under UVC light. Apart from that, the lifetime of GAC column could be elongated on condition that metaldehyde has been treated by AOPs previously. Hence, combination of AOPs and GAC column is promising in treating water containing metaldehyde.

Design, expression, and evaluation of novel multiepitope chimeric antigen of Wuchereria bancrofti for the diagnosis of lymphatic filariasis - A structure-based strategy - Yasin, Nazeer; Laxmanappa, Hoti Sugerappa; Muddapur, Uday M.; Cheruvathur, Jennifer; Prakash, S. M. Uday; Thulasiram, Hirekodathakallu Venkataramaiah (International Immunopharmacology, 2020)
The Global Program for Elimination Lymphatic Filariasis (GPELF) is in an advanced stage and requires tools for diagnosing infection, assessing transmission and certification. This study was aimed at developing an antibody-based assay using a chiemric antigen containing multi-B-cell epitopes from antigens highly expressed in different stages of Wuchereria bancrofti to detect LF infection and its transmission. The antigen was express cloned and two indirect ELISA based (IgG1 & IgG4 based) antibody assays were developed using the recombinant antigen. The chimeric antigen displayed 1 and 3-fold reactivity with IgG1 and IgG4 antibodies, respectively in microfilaraial (mf) positive sera when compared to that in sera samples of Non-endemic normal sera (NEN) (O.D, 0.13 +/- 0.20 and 0.18 +/- 0.07), thus differentiating infected from uninfected individuals. In IgG1 and IgG4 antibody assays, the multiepitope antigen also showed reactivity (O.D, 0.27 +/- 0.18 and 0.16 +/- 0.03) in a small proportion (18 and 30, respectively out of 156) endemic normal individuals and in IgG1 antibody in a few (4) chronic patients (CP). The antigen did not react with IgG1 or IgG4 antibodies in the sera samples of malaria, scrub typhus, dengue, hookworm, and roundworm helminth cases (0.139 +/- 0.018, 0.144 +/- 0.007 0.17804 +/- 0.007 and 0.162 +/- 0.006), thus showing its high specificity. The sensitivity (%) and specificity (%) of the multi-epitope antigen-based IgG1 and IgG4 antibody assays are 100, 98.1 and 100, 99.52, respectively. Thus, the recombinant multiepitope antigen appears to have good potential in detecting active LF infection and in assessing its transmission in endemic communities.
Keywords: Filariasis; Multi-epitope antigen; Serodiagnosis; Transmission

DFT/NMR approach for the configuration assignment of groups of stereoisomers by the combination and comparison of experimental and predicted sets of data - Lauro, Gianluigi; Das, Pronay; Riccio, Raffaele; Reddy, D. Srinivasa; Bifulco, Giuseppe (Journal of Organic Chemistry, 2020)
Quantum mechanical/nuclear magnetic resonance (NMR) approaches are widely used for the configuration assignment of organic compounds generally comparing one cluster of experimentally determined data (e.g., C-13 NMR chemical shifts) with those predicted for all possible theoretical stereoisomers. More than one set of experimental data, each related to a specific stereoisomer, may occur in some cases, and the accurate stereoassignments can be obtained by combining the experimental and computed data. We introduce here a straightforward methodology based on the simultaneous analysis, combination, and comparison of all sets of experimental/calculated C-13 chemical shifts for aiding the correct configuration assignment of groups of stereoisomers. The comparison of the differences between the calculated/experimental chemical shifts instead of the shifts themselves led to the advantage of avoiding errors arising from calibration procedures, reducing systematic errors, and highlighting the most diagnostic differences between calculated and experimental data. This methodology was applied on a tetrad of synthesized cladosporin stereoisomers (cladologs) and further corroborated on a tetrad of pochonicine stereoisomers, obtaining the correct correspondences between experimental and calculated sets of data. The new MAE(Delta Delta delta) parameter, useful for indicating the best fit between sets of experimental and calculated data, is here introduced for facilitating the stereochemical assignment of groups of stereoisomers.

Dynamics in amine-functionalized mesoporous hybrid materials probed through deuterium magic angle spinning NMR and molecular dynamic simulations - Veena, V. S.; Kavya, I; Lazar, A.; Vinod, C. P.; Ajithkumar, T. G.; Jayanthi, S. (Journal of Physical Chemistry C, 2020)
We present a deuterium magic angle spinning (MAS) NMR study on two widely used hybrid materials (3-glycidyloxy propyl)trimethoxysilane (3-GPTMS) and 3-(trimethoxysilyl)propyl methacrylate (3-MATMS) grafted on SBA-15. Methylene-deuterated diamine as a pendent group is anchored to GPTMS (O3Si-CH2-CH2-CH2-O-CH2-CH(OH)- CH2-NH-CD2-CD2-NH2) and MATMS (O3Si-CH2-CH2-CH2-O-C(N-CD2-CD2-NH2)-C(CH3)=-CH2) postgrafting. Proton and deuterium solid state NMR experiments under MAS were performed at two hydration levels and temperatures ranging from 253 to 315 K. Deuterium spectra were deconvoluted into three A Dr, components with different average quadrupolar parameters: a relatively rigid component arising from local or librational motion of C-H-2(2) corresponding to ``small angle'' jumps, an intermediate dynamic component, and a large amplitude dynamic component. Population ratios of rigid versus dynamic components show that diamine-MATMS is more rigid when compared with diamine-GPTMS at high hydration. The role of the length of the linkers, steric hindrance, grafting concentration, etc. in defining mobility is investigated. Finally, by correlating proton and deuterium MAS NMR spectral analysis, the role of a few water molecules in inducing dynamics of the linkers was investigated. Molecular dynamic (MD) simulations support the experimental analysis. MD simulations indicate different types of mobility arising from the same molecular binding configuration of diamine-MATMS. Dynamics induced by a few hydroxyls on the pore surface accessible to the linker, various molecular conformations, and stabilization of the linker through hydrogen bonding with the surface, derived from MD simulations, are discussed.

Efficacy of clay catalysts for the dehydration of fructose to 5-hydroxymethyl furfural in biphasic medium - Lucas, Nishita; Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana (Journal of Porous Materials, 2020)
5-Hydroxymethyl furfural (HMF) is one of the important platform chemical obtained from C6 sugars derived from biomass. The efficiency of montmorillonite clay catalysts (K-10, K-20, K-30, and Al pillared clay) has been systematically explored for the synthesis of HMF through dehydration of fructose in a biphasic solvent system. The catalysts were characterized by XRD, N(2)sorption,Al-27 MAS NMR,Si-29 NMR and FT-IR of chemisorbed pyridine. Acid treated K-10 catalyst was found to be the best among the clay catalysts tested. Various reaction parameters such as reaction temperature, catalyst content, solvent were optimized for achieving better yield of HMF. Under optimized reaction conditions, K-10 catalyst affords 80 mol% fructose conversion with HMF yield of 61 mol%. Insight into the type of acid sites essential for such cascade reactions has been furnished. Utilization of clay catalysts for HMF production will be beneficial to improve overall economics for the production of platform chemicals like HMF from biomass-derived raw materials.
Keywords: 5-hydroxymethyl furfural; Acidity; Clays; fructose; Insights

Efficacy of octahedral molecular sieves for green and sustainable catalytic reactions - Lucas, Nishita; Gurrala, Lakshmiprasad; Halligudi, S. B. (Molecular Catalysis, 2020)
Sustainability and Green Chemistry has emerged as catchphrase in modern era and researchers worldwide have embraced it as new paradigm of development. In this context identifying potential materials able to curb multiple grave issues thus contributing towards sustainability is vital. Catalytic materials are quite potent for addressing current social, economic and environmental problems like harnessing alternative energy source, pollution prevention/remediation and manufacturing of commodity chemicals. Thus, the present review accentuates the efficacy of porous octahedral molecular sieves (OMS) as catalyst for such environmentally important reactions. It discusses about structural importance of OMS and their applications for green and sustainable catalytic reactions. Finally, the limitations are highlighted and future perspectives are presented which will ameliorate its catalytic utilization in energy and environmental domains.
Keywords: catalytic transformations; Lignocellulosic biomass; octahedral molecular sieves; platform chemicals; renewable feedstock

Electrospun fibers and sorbents as a possible basis for effective composite wound dressings - Saul Alvarez-Suarez, Alan; Dastager, Syed G.; Bogdanchikova, Nina; Grande, Daniel; Pestryakov, Alexey; Carlos Garcia-Ramos, Juan; Lizeth Perez-Gonzalez, Graciela; Juarez-Moreno, Karla; Toledano-Magana, Yanis; Smolentseva, Elena; Antonio Paz-Gonzalez, Juan; Popova, Tatiana; et al. (Micromachines, 2020)
Skin burns and ulcers are considered hard-to-heal wounds due to their high infection risk. For this reason, designing new options for wound dressings is a growing need. The objective of this work is to investigate the properties of poly (epsilon-caprolactone)/poly (vinyl-pyrrolidone) (PCL/PVP) microfibers produced via electrospinning along with sorbents loaded with Argovit (TM) silver nanoparticles (Ag-Si/Al2O3) as constituent components for composite wound dressings. The physicochemical properties of the fibers and sorbents were characterized using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and inductively coupled plasma optical emission spectroscopy (ICP-OES). The mechanical properties of the fibers were also evaluated. The results of this work showed that the tested fibrous scaffolds have melting temperatures suitable for wound dressings design (58-60 degrees C). In addition, they demonstrated to be stable even after seven days in physiological solution, showing no macroscopic damage due to PVP release at the microscopic scale. Pelletized sorbents with the higher particle size demonstrated to have the best water uptake capabilities. Both, fibers and sorbents showed antimicrobial activity against Gram-negative bacteria Pseudomona aeruginosa and Escherichia coli, Gram-positive Staphylococcus aureus and the fungus Candida albicans. The best physicochemical properties were obtained with a scaffold produced with a PCL/PVP ratio of 85:15, this polymeric scaffold demonstrated the most antimicrobial activity without affecting the cell viability of human fibroblast. Pelletized Ag/Si-Al2O3-3 sorbent possessed the best water uptake capability and the higher antimicrobial activity, over time between all the sorbents tested. The combination of PCL/PVP 85:15 microfibers with the chosen Ag/Si-Al2O3-3 sorbent will be used in the following work for creation of wound dressings possessing exudate retention, biocompatibility and antimicrobial activity.
Keywords: electrospinning; poly (epsilon-caprolactone); poly (vinyl pyrrolidone); silver sorbents; wound dressings

Enhancing thermomechanical and chemical stability of polymer electrolyte membranes using polydopamine coated nanocellulose - Ram, Farsa; Velayutham, Parthiban; Sahu, Akhila Kumar; Lele, Ashish K.; Shanmuganathan, Kadhiravan (ACS Applied Energy Materials, 2020)
We report here an approach to enhance the chemical and thermomechanical stability of polymer electrolyte membranes without compromising proton conductivity. Multifunctional polydopamine coated nanocellulose (PNC) was prepared by oxidative polymerization of dopamine on nano cellulose fibers and subsequently incorporated in Nafion by solution blending. PNC had a very significant effect on the thermomechanical properties of Nafion showing up to 200% improvement in the storage modulus at 90 degrees C. The PNC network also enhanced the dimensional stability of Nafion under constant stress. The 3 wt % PNC composite membrane showed a drastic reduction in creep compliance of about 39.9% and 46.5% in J(max) at 30 degrees and 60 degrees C, respectively. Free radical scavenging properties of polydopamine also helped to significantly enhance the chemical stability of Nafion, which was ascertained by accelerated degradation tests conducted in Fenton's reagent at 70 degrees C over 40 days. F-19 CP MAS solid state NMR, FTIR, and tensile tests on the membranes show higher chemical stability of the 3 wt % PNC composite membrane. The proton conductivity of the 3 wt % PNC composite membrane at 90 degrees C and 100% RH (similar to 125 mS/cm) was slightly higher than the Nafion membrane (similar to 94 mS/cm) at similar conditions. The retention of proton conductivity even with lower water uptake could be ascribed to proton hopping through polydopamine coated nanocellulose. Performance of the composite membrane was also evaluated in a single stack fuel cell and found to be better than recast Nafion. The benefits derived by this approach are not restricted to Nafion alone and shall broadly apply to many other polymer membranes.
Keywords: cellulose nanofibers; chemical stability; dimensional stability; fuel cell; polydopamine; polymer electrolyte membrane

Enolate-mediated regioselective synthesis of 1,2,3-triazoles via azide-aldehydes or ketones [3+2]-cycloaddition reactions in aqueous phase - Tripathi, Anupam; Rode, V, Chandrashekhar; Llop, Jordi; Chavan, Subhash P.; Joshi, Sameer M. (Tetrahedron Letters, 2020)
A synthetic route for the direct conversion of arylazides into the corresponding trizoles via phase transfer catalyst-assisted [3+2] cycloaddition reaction under basic conditions in aqueous medium is reported. This synthetic methodology, which offers high yields and excellent regioselectivity for varieties of triazoles at 100 degrees C for 24 h-48 h and this `greener' synthesis constitutes an alternative to the previously reported well established click reactions. Published by Elsevier Ltd.
Keywords: Azides plus aldehydes or ketones; Click chemistry; triazoles; Water

Evaluation of uttroside B, a saponin from Solanum nigrum Linn, as a promising chemotherapeutic agent against hepatocellular carcinoma (vol 6, 36318, 2016) - Nath, Lekshmi R.; Gorantla, Jaggaiah N.; Thulasidasan, Arun Kumar T.; Vijayakurup, Vinod; Shah, Shabna; Anwer, Shabna; Joseph, Sophia M.; Antony, Jayesh; Veena, Kollery Suresh; Sundaram, Sankar; Marelli, Udaya K.; Lankalapalli, Ravi S.; et al. (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Functionalized magnetic nanosized materials for efficient biodiesel synthesis via acid-base/enzyme catalysis - Wang, Anping; Sudarsanam, Putla; Xu, Yufei; Zhang, Heng; Li, Hu; Yang, Song (Green Chemistry, 2020)
According to the principles of green chemistry, the rapid recovery and reuse of catalysts after a catalytic reaction are important factors to realize the sustainable management of chemical production processes. The functionalization of magnetic nanoparticles is the basis for the efficient separation of heterogeneous catalysts from the reaction system by using the magnetic separation technology as well as for effectively bridging heterogeneous and homogeneous catalytic processes. This can considerably improve the production efficiency and reduce energy consumption as well. Owing to important applications as a potential biofuel or fuel additive, the synthesis of biodiesel mainly from low-cost biomass feedstocks has received considerable attention in the current biorefinery research. A simple synthesis process coupled with the application of functionalized magnetic catalysts can remarkably reduce the production cost and minimize waste generation, thereby promoting the potential development of green catalytic processes for the large-scale synthesis of biodiesel. In this review, the preparation methods, structural and performance control, and protection and functionalization of magnetic nanoparticles as well as the consequent catalytic effects in the synthesis of biodiesel (mainly long-chain fatty acid methyl esters) have been reported. In addition, various representative reaction mechanisms are discussed, emphasizing the existing challenges and prospects of industrialization.

Ice templated nanocomposites containing rod-like hematite particles: Interplay between particle anisotropy and particle-matrix interactions - Kumaraswamy, Guruswamy; Suresh, Karthika; Lama, Hisay; Basavaraj, Madivala G.; Satapathy, Dillip K. (Journal of Applied Physics, 2020)
We demonstrate that the mechanical response of ice templated nanocomposite scaffolds prepared from ellipsoidal hematite particles is determined by both the particle aspect ratio and the interaction between the particles and the matrix polymer. We ice template aqueous dispersions of hematite particles, polyethyleneimine, and diepoxy crosslinker and crosslink the polymer in the frozen state. This protocol results in the formation of elastic macroporous monoliths capable of complete recovery from large compressive strains. Hematite particles show an inversion of their surface charge with pH: they are negatively charged at a basic pH and positively charged under acidic conditions. This allows us to change the interaction between hematite particles and crosslinked matrix polymer that they are embedded in, simply by immersing the monoliths in aqueous solutions with different pH's. We report that under basic conditions, viz, when polyethyleneimine adsorbs on the particle surface, there is a decrease in the monolith modulus with an increase in the particle aspect ratio. We demonstrate that this correlates with a change in the mechanism of monolith response: from wall compression for isotropic particles to wall bending for anisotropic particles with an aspect ratio of 4. Under acidic conditions (pH=2), where hematite particles show a positive zeta potential, the monolith modulus increases with the aspect ratio of the ellipsoidal fillers. Understanding the interplay between filler aspect ratio and filler-matrix interaction has important implications for the control of nanocomposite mechanical properties.

Inhibition of quorum sensing, motility and biofilm formation ofpseudomonas aeruginosaby copper oxide nanostructures - Desai, Dnyanada G.; Swarali, H.; Navale, Govinda R.; Prabhune, A.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Cluster Science, 2020)
Quorum sensing (QS) is the communication between bacterial cells governed by their population density and regulated by the genes controlling virulence factors and biofilm formation. Multiple mechanisms of biofilms are resistive to antimicrobial chemotherapy; therefore novel strategies are required to overcome its limitations. Here, we report the effect of various copper oxide nanostructures (CuO-NSs) on quorum sensing inhibition. The two-dimensional CuO-NSs such as interlaced nanodiscs, nanodiscs and leaf-shaped nanosheets are prepared via a simple chemical method. The Quorum sensing inhibition (QSI) activity of all the CuO-NS are examined using reporter strainChromobacterium violaceumCV026 andEscherichia colipSB1142. We found that the CuO-interlaced nanodisc structures exhibit better QSI activity than nanodiscs and leaf-shaped sheets. The interlaced nanodisc structures are inhibited various long-chainN-acyl homoserine lactones (AHLs) mediated QS individually and confirmed by other QS-associated phenomena forPseudomonas aeruginosa, including biofilm inhibition, inhibition of virulence factors such as pyocyanin, protease production and swarming motility. Thus QSI activity of CuO-NSs is solely dependent on specific shape offering large surface area and more active sites. The CuO-NS is effective quorum sensing inhibitors, which has potential clinical applications in the management ofP. aeruginosaassociated infections.
Keywords: aeruginosa; Biofilm; Nanostructures; P; quorum sensing; Virulence factors

Iron-catalyzed direct julia-type olefination of alcohols - Landge, Vinod G.; Babu, Reshma; Yadav, Vinita; Subaramanian, Murugan; Gupta, Virendrakumar; Balaraman, Ekambaram (Journal of Organic Chemistry, 2020)
Herein, we report an iron-catalyzed, convenient, and expedient strategy for the synthesis of styrene and naphthalene derivatives with the liberation of dihydrogen. The use of a catalyst derived from an earth-abundant metal provides a sustainable strategy to olefins. This method exhibits wide substrate scope (primary and secondary alcohols) functional group tolerance amino, nitro, halo, alkoxy, thiomethoxy, and S- and N-heterocyclic compounds) that can be scaled up. The unprecedented synthesis of 1-methyl naphthalenes proceeds via tandem methenylation/double dehydrogenation. Mechanistic study shows that the cleavage of the C-H bond of alcohol is the rate-determining step.

Ligand structure directed dimensionality reduction (2D -> 1D) in lead bromide perovskite - Bakthavatsalam, Rangarajan; Haris, Muhammed P. U.; Shaikh, Samir R.; Lohar, Amruta; Mohanty, Ashutosh; Moghe, Dhanashree; Sharma, Shivani; Biswas, Chinmoy; Raavi, Sai Santhosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Physical Chemistry C, 2020)
Low dimensional (2D, 1D) lead halide perovskites are currently attracting huge research interest due to their enabling properties. Demonstrating synthetic control on the dimensionality/ structure of these perovskites is highly challenging. Dimensionality in these perovskites is largely dictated by the nature/structure and composition of the incorporating ligands and the utilized synthetic conditions. Here, we demonstrate chemical composition based control on reduction of dimensionality (2D -> 1D) for lead bromide perovskite utilizing 2-(2-aminoethyl)isothiourea dihydrobromide as a common precursor ligand (Isothio Bromide). Controlling the hydrothermal reaction parameters (temperature, time) at a fixed precursor ratio affords corner-shared, contorted 2D sheet perovskite and corner-shared, contorted, chiral 1D chain perovskite. Such dimensionality reduction leads to contrasting photophysical properties: 1D chain perovskite shows long-lived and self-trapped broad band emission, whereas 2D perovskite shows short-lived, band edge emission with a long tail. Mechanistic studies and single crystal structure analysis reveal the incorporation of the utilized precursor ligand (Isothio Bromide) in 2D perovskite. Surprisingly, the 1D perovskite is found to be chiral (P2(1) space group) incorporating 2-(2-aminoethyldisulfanyl)ethanamine and ammonium ions as the achiral ligands generated in situ due to hydrothermal cleavage of the precursor (Isothio Bromide) ligand. Such structural and compositional change of the ligands, which manifests a different hydrogen bonding network in the resultant perovskite structure, plays a decisive role in dictating the final molecular formula and dimensionality/structure of the perovskite which largely controls their photophysical properties.

Magnetic and luminescent multifunctional nanohybrid: Fe3O4@CaF2:Tb3+: a facile synthesis and characterization - Vats, Monika; Kumar, Rakesh; Sharma, Jyotsna; Luwang, Meitram Niraj (Indian Journal of Pure & Applied Physics, 2020)
In the present study, bi-functional hybrid nanomaterial has been synthesized and characterized via facile method and characterized. The synthesized nanomaterial shows both magnetic and luminescent properties which are confirmed by VSM (vibrating sample magnetometer), UV-Vis spectra and the photoluminescence emission spectra. For the magnetic phase, i.e., nanocrystalline magnetite, Fe3O4 is used as the core which is then functionalized using polyethylene glycol (PEG) and for the luminescent phase, polyethylenimine (PEI) functionalized CaF2 doped with Tb3+ is used as the emitter. Wherein, both PEG and PEI serve the dual purpose of functionalization as well as stabilization by steric repulsion. The structure and morphology of the synthesized bifunctional hybrid nanomaterial are studied with the help of scanning electron microscopy (SEM) and X-ray powder diffraction.
Keywords: Biocompatible; CaF2; Co-precipitation; Fe3O4; Luminescent nanoparticle; Magnetic nanoparticles; Nanohybrid; Tb3+ doping

Manganese-catalyzed alpha-olefination of nitriles with secondary alcohols - Yadav, Vinita; Landge, Vinod G.; Subaramanian, Murugan; Balaraman, Ekambaram (ACS Catalysis, 2020)
An expedient catalytic approach for alpha-olefination of nitriles using secondary alcohols with the liberation of molecular hydrogen and water as the only byproducts is reported. This reaction is catalyzed by a molecularly defined manganese(I) pincer complex and operates in the absence of any hydrogen acceptors. A broad range of substrates including cyclic, acyclic, and benzylic alcohols, as well as various nitrile derivatives, such as arylmethyl and heteroarylmethyl nitriles, are employed in the reaction to provide a diverse range of alpha-vinyl nitriles in good to excellent yields. Mechanistic studies showed that the reaction proceeds via dehydrogenative pathway and the activation of alpha(C-H) bond of the alcohol is the rate-determining step.
Keywords: acceptorless dehydrogenation; Alcohol; alpha-olefination; Hydrogen; manganese

Microstructure and yielding of capillary force induced gel - Huprikar, Sameer; Usgaonkar, Saurabh; Lele, Ashish K.; Orpe, Ashish V. (Rheologica Acta, 2020)
We have investigated the rheology and structure of a gel formed from a mixture of non-Brownian particles and two immiscible liquids. The suspension of particles in a liquid undergoes gelation upon the addition of a small content of second, wetting liquid which forms liquid bridges between particles leading to a sample spanning network. The rheology of this gel primarily exhibits a yield stress at low shear rates followed by a linear variation of shear stress at high shear rates. The apparent yield stress extracted from the flow curves increases rapidly with volume fraction of the second liquid before saturation, while it exhibits a monotonic increase with increasing particle concentration. Rescaling of the yield stress curves using suitable shift factors results in an empirical expression for the yield stress showing squared dependence on liquid fraction and a rapid increase with particle fraction above a certain value, both combined in a highly non-linear manner. The microstructural variations with changing secondary liquid content and particle fractions are captured using three-dimensional X-ray tomography technique. The microstructure is observed to show increased local compactness with increased liquid content and increased spatial homogeneity with increased particle fractions. The images from X-ray tomography are analysed to obtain the distributions of particle-particle bonds (coordination number) in the system which serve to explain the observed yield stress behaviour in a qualitative manner.
Keywords: Capillary force; Flow curve; gel; Microstructure; Rheology; Yield stress

Molecular networking and whole-genome analysis aid discovery of an angucycline that inactivates mTORC1/C2 and induces programmed cell death - Dan, Vipin Mohan; Vinodh, J. S.; Sandesh, C. J.; Sanawar, Rahul; Lekshmi, Asha; Kumar, R. Ajay; Kumar, T. R. Santhosh; Marelli, Uday Kiran; Dastager, Syed G.; Pillai, M. Radhakrishna (ACS Chemical Biology, 2020)
Rediscovery of known compounds and time consumed in identification, especially high molecular weight compounds with complex structure, have let down interest in drug discovery. In this study, whole-genome analysis of microbe and Global Natural Products Social (GNPS) molecular networking helped in initial understanding of possible compounds produced by the microbe. Genome data revealed 10 biosythethic gene clusters that encode for secondary metabolites with anticancer potential. NMR analysis of the pure compound revealed the presence of a four-ringed benz[a]anthracene, thus confirming angucycline; molecular networking further confirmed production of this class of compounds. The type II polyketide synthase gene identified in the microbial genome was matched with the urdamycin duster by BLAST analysis. This information led to ease in identification of urdamycin E and a novel natural derivative, urdamycin V, purified from Streptomyces sp. OA293. Urdamycin E (Urd E) induced apoptosis and autophagy in cancer cell lines. Urd E exerted anticancer action through inactivation of the mTOR complex by preventing phosphorylation at Ser 2448 and Ser 2481 of mTORC1 and mTORC2, respectively. Significant reduction in phosphorylation of the major downstream regulators of both mTORC1 (p70s6k and 4e-bp1) and mTORC2 (Akt) were observed, thus further confirming complete inhibition of the mTOR pathway. Urd E presents itself as a novel mTOR inhibitor that employs a novel mechanism in mTOR pathway inhibition.

Novel Ru nanoparticle catalysts for the catalytic transfer hydrogenation of biomass-derived furanic compounds - Nagpure, Atul S.; Gogoi, Pranjal; Lucas, Nishita; Chilukuri, V. Satyanarayana (Sustainable Energy & Fuels, 2020)
The catalytic transfer hydrogenation (CTH) reaction was investigated for boosting the reduction of biomass-derived furanic compounds to obtain high-quality liquid biofuels. The CTH of 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF) and furfural to 2-methylfuran (MF) was thoroughly studied over the Ru, Pd, Au, Pt, Ni, Rh and Cu metal catalysts supported on nitrogen-doped mesoporous carbons (NMCs) by utilizing 2-propanol as a source of hydrogen. The structural characteristics of the materials were examined by employing various physico-chemical methods, such as XRD, N(2)sorption, CHN analysis, XPS, FT-IR spectroscopy, H-2-TPR, TEM, CO2-TPD, ICP-OES and Raman spectroscopy. The influence of the N content, basicity of the catalyst, reaction temperature, hydrogen donor, nature of the catalyst support and transition metal was systematically investigated with regard to the substrate conversions and product yields. The correlation between the N content (wt%) of the catalysts and the Ru nanoparticle size (nm) and turnover frequency (h(-1)) was also investigated. Highly dispersed Ru nanoparticles (1.9 nm) supported on NMC displayed admirable catalytic performance in CTH for the conversion of HMF to DMF and furfural to MF. The catalyst Ru-NMC with a good N content (11.4 wt%) gave 84 and 87 mol% yields of DMF and MF, respectively, with 2-propanol as the source of hydrogen under mild reaction conditions. In addition, this catalyst demonstrated excellent recyclability. The better catalytic activity of the Ru-NMC catalyst in the CTH of HMF and furfural was credited to the small size of the Ru metal nanoparticles (1.9 nm), high N content, superior metal-support interaction and mesoporous framework of the catalyst.

Recent advances in plant nanobionics and nanobiosensors for toxicology applications - Ansari, Mohammad Hasan Dad; Lavhale, Santosh; Kalunke, Raviraj M.; Srivastava, Prabhakar L.; Pandit, Vaibhav; Gade, Subodh; Yadav, Sanjay; Laux, Peter; Luch, Andreas; Gemmati, Donato; Zamboni, Paolo; Singh, Ajay Vikram (Current Nanoscience, 2020)
Emerging applications in the field of nanotechnology are able to solve a gamut of problems surrounding the applications of agroecosystems and food technology. Nano Engineered Material (NEM) based nanosensors are important tools for monitoring plant signaling pathways and metabolism that arc nondestructive, minimally invasive, and can provide real-time analysis of biotic and abiotic threats for better plant health. These sensors can measure chemical flux even at the single molecule level. Therefore, plant health could be monitored through nutrient management, disease assessment, plant hormones level, environmental pollution, etc. This review provides a comprehensive account of the current trends and practices for the proposed NEM related research and its (i) structural aspect, (ii) experimental design and performance as well as (iii) mechanisms of field application in agriculture and food system. This review also discusses the possibility of integration of data from NEM based nanosensors in current and emerging trends of precision agriculture, urban farming, and plant nanobionics to adopt a sustainable approach in agriculture,
Keywords: agro-ecosystems; engineered nanomaterials; nanobionics; Nanosensors; nanotechnology; nanotoxicology

Rheological quantification of the extent of dissolution of ultrahigh molecular weight polyethylene in melt-compounded blends with high density polyethylene - Chaudhuri, Krishnaroop; Lele, Ashish K. (Journal of Rheology, 2020)
Melt compounding of ultrahigh molecular weight polyethylene (UHMWPE) with high density polyethylene (HDPE) promises to be an alternative route to prepare bimodal polyethylene grades. However, complete dissolution of UHMWPE in HDPE cannot be guaranteed during melt compounding. Indeed, in an earlier work [K. Chaudhuri et al., Polym. Eng. Sci. 59, 821-829 (2019)], it was shown that a fully entangled UHMWPE did not mix well with commercial HDPE. However, a disentangled UHMWPE (dPE) could be melt-mixed in the same HDPE as evidenced qualitatively by rheological measurements. The present work is focused on quantifying the extent of dissolution of dPE in HDPE. The proposed method involves fitting rheological models for linear viscoelasticity of entangled bimodal blends of polydisperse polymers to dynamic oscillatory shear data and extracting information on the extent of dissolved species. The time-dependent diffusion model of des Cloizeaux is used along with the theory of double reptation (DR) to describe the dynamics of polydisperse homopolymers and also to extract the molecular weight distribution of the UHMWPE sample. A quadratic mixing rule, consistent with the DR model, is used to describe the dynamics of bimodal blends. Melt-mixed dPE/HDPE blends were prepared and characterized for their linear viscoelastic response by frequency sweep tests. The blends showed complex behavior with multiple crossover points, especially for the higher content of dPE. The bimodal model was then fit to the experimental frequency sweep data to determine the only unknown parameter, namely, the extent of dissolved dPE. It was found that a considerable fraction of dPE is dissolved in HDPE during melt compounding.
Keywords: blends; Disentangled UHMWPE; double reptation; HDPE; Mathematical modeling

Spectroscopic probe of atomically thin domains of CVD-grown MoSe2 - Singh, Vineeta; Late, Dattatray J.; Rath, Shyama (AIP Conference Proceedings, 2020)
Since the discovery of graphene, two-dimensional Layered Transition Metal Dichalcogenides (TMDCs) such as MoS2, MoSe2, and WS2 having a tunable bandgap, have emerged as one of the most stable classes of materials making them attractive for various applications. We have investigated the growth mechanism and shape evolution of various domains of CVD-grown MoSe2 on insulating substrates by spectroscopic techniques. The different morphologies were analyzed using Raman and photoluminescence spectroscopies. The transformation from the precursor MoO3 to MoSe2 is found to depend on a number of growth parameters and experimental conditions.

Structural, molecular, functional and immunological characterization of Wuchereria bancrofti-galectin - Yasin, Nazeer; Laxmanappa, Hoti Sugerappa; Muddapur, Uday M.; Cheruvathur, Jennifer; Prakash, S. M. Udaya; Thulasiram, Hirekodathakallu Venkataramaiah (International Journal of Biological Macromolecules, 2020)
Galectins regulate growth and differentiation of immune cells and inflammation through their carbohydrate-binding function in humans, while also play a role in parasite survival. This study focused on the galectin of lymphatic filarial parasite Wuchereria bancrofti (Wb-Gal). The multiple sequence alignment with other galectins showed that the Wb-Gal belonged to galactoside binding lectin family, particularly tandem repeat type galectin-9. A homology model of Wb-Gal was developed in the I-TASser server using high similarity 3D structures with a quality score of 89.5. Molecular docking and dynamics studies revealed that the CCRD and NCRD of Wb-Gal bind with galactose and lactose. Further, Wb-Gal was cloned into the pET28 vector, expressed in E. coli Rosetta strain and purified by affinity chromatography. In the hemagglutination assays, the rWb-Gal bound to lactose, galactose, and glucose. Indirect Enzyme-Linked Immunosorbent Assay (ELISA) using different clinical filarial sera showed that the IgG and IgM response was against Wb-Gal x very high in all filarial clinical groups, whereas the IgA and IgG2 response was minimum to negligible. There was an enhanced response of IgG1 and IgG4 antibodies in Microfilaremics (MF) cases compared to Chronic Pathology (CP) and Endemic Normal (EN) individuals. Interestingly, the IgE response was comparatively higher in EN than MF and CP. These studies show that Wb-Gal is a member of the lectin family of proteins binding to different carbohydrates and may have an important role in the pathophysiology of filarial infection which needs to be investigated in greater detail. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Filariasis; Hemagglutination assay; Immunomodulation; Wuchereria bancrofti galectin

Synthesis and biological activity of imidazole based 1,4-naphthoquinones - Choudhari, Dinkar; Salunke-Gawali, Sunita; Chakravarty, Debamitra; Shaikh, Samir R.; Lande, Dipali N.; Gejji, Shridhar P.; Rao, Pradeep Kumar; Satpute, Surekha; Puranik, Vedavati G.; Gonnade, Rajesh (New Journal of Chemistry, 2020)
Design and development of drugs in multi-drug resistant (MDR) infections have been of growing interest. We report the syntheses, and antibacterial and antifungal activities of imidazole-based 1,4-naphthoquinones (I-1 to I-4; 1-alkyl-2-methyl-1H-naphtho[2,3-d]imidazole-4,9-dione (alkyl = methyl to butyl)) and their precursors (B-3; N-(3-chloro-1,-dioxo-1,4-dihydronaphthalen-2-yl)acetamide) and A-1 to A-4; N-(3-(alkylamino)-1,4-dioxo-1,4-dihydronaphthalen-2-yl)acetamide (alkyl = methyl to butyl). Crystal structures of B-3, A-1 to A-3 and I-2 to I-4 were obtained through single crystal X-ray diffraction experiments. Electronic structure and charge distribution have further been characterized with the use of Density Functional Theory. Seven of these derivatives display a broad spectrum of antibacterial activity against few selected bacterial strains (Gram-positive and Gram-negative). As demonstrated MIC values with B-2 and B-3 against bacterial isolates were 8-64 mu g ml(-1) and those against pathogenic yeast, C. albicans, were observed in the range of 128-256 mu g ml(-1). MIC data of these derivatives suggest them to be promising against pathogens.

TDR Targets 6: driving drug discovery for human pathogens through intensive chemogenomic data integration - Landaburu, Lionel Uran; Berenstein, Ariel J.; Videla, Santiago; Maru, Parag; Shanmugam, Dhanasekaran; Chernomoretz, Ariel; Aguero, Fernan (Nucleic Acids Research, 2020)
The volume of biological, chemical and functional data deposited in the public domain is growing rapidly, thanks to next generation sequencing and highly-automated screening technologies. These datasets represent invaluable resources for drug discovery, particularly for less studied neglected disease pathogens. To leverage these datasets, smart and intensive data integration is required to guide computational inferences across diverse organisms. The TDR Targets chemogenomics resource integrates genomic data from human pathogens and model organisms along with information on bioactive compounds and their annotated activities. This report highlights the latest updates on the available data and functionality in TDR Targets 6. Based on chemogenomic network models providing links between inhibitors and targets, the database now incorporates network-driven target prioritizations, and novel visualizations of network subgraphs displaying chemical- and target-similarity neighborhoods along with associated target-compound bioactivity links. Available data can be browsed and queried through a new user interface, that allow users to perform prioritizations of protein targets and chemical inhibitors. As such, TDR Targets now facilitates the investigation of drug repurposing against pathogen targets, which can potentially help in identifying candidate targets for bioactive compounds with previously unknown targets. TDR Targets is available at https://tdrtargets.org.

TiO2-based water-tolerant acid catalysis for biomass-based fuels and chemicals - Sudarsanam, Putla; Li, Hu; Sagar, Tatiparthi Vikram (ACS Catalysis, 2020)
Solid acid catalysts alone or in combination with redox metals play a pivotal role in biomass valorization to obtain alternative fuels and chemicals. In acid-catalyzed biomass conversions, water is a key reagent/byproduct that can induce leaching/poisoning of catalyst's acid species, a major problem toward catalyst recyclability and product purification. Thus, developing efficient water-tolerant solid acid catalysts is vital for viable biomass valorization. TiO2 is considered to be a promising water-tolerant solid acid catalyst for biomass conversions because of the presence of coordinatively unsaturated Ti4+ sites, which are robust and less prone to leaching in the aqueous medium. Besides, the synergistic combination of TiO2 with redox metals (Ru, Pd, Ni, Cu, etc.) provides abundant bifunctional acid-redox sites, which exhibit a favorable catalytic role in the deoxygenation of biomass molecules to practically useful hydrocarbons. Therefore, this review provides an overview of recent progress toward TiO2-based water-tolerant acid catalysis for biomass conversion, with a focus on hydrothermal stability of TiO2, its acidity, and catalysts' synthesis methods. Various biomass conversions over TiO2-based catalysts, where water-tolerant acid sites or acid-redox dual sites show a significant catalytic effect, were discussed. Structure-activity relationships based on water-tolerant Lewis acidity of TiO2 were emphasized. We believe that this review will provide valuable information for developing efficient water-tolerant solid acid catalysts not only for biomass valorization but also for other challenging reactions in the aqueous medium.
Keywords: Acid catalysis; acid-redox catalysis; Biomass conversion; renewable fuels and chemicals; TiO2-based catalysts; water-tolerant Lewis acidity

Towards lignin-derived chemicals using atom-efficient catalytic routes - Sudarsanam, Putla; Ruijten, Dieter; Liao, Yuhe; Renders, Tom; Koelewijn, Steven-Friso; Sels, Bert F. (Trends in Chemistry, 2020)
Lignin is a potential non-fossil resource of diverse functionalized phenolic units. The most important lignin- derived monomers are 4-alkylphenols, 4- hydroxybenzaldehydes, 4-hydroxybenzoic acids, and 4-hydroxycinnamic acids/esters. Efficient transformation of lignin and/or its monomers into valuable aromatics and their derivatives is crucial, not only for a sustainable lignocellulose biorefinery, but also to reduce our dependence on fossil feedstocks. This review provides a concise account of the recent advances in lignocellulose fractionation/lignin depolymerization processes towards lignin-derived monomers. Subsequently, numerous potential atom-efficient catalytic routes for upgrading lignin monomers into drop-in chemicals and new polymer building blocks are discussed.

Tris-heteroleptic ruthenium(II) polypyridyl complexes: Synthesis, structural characterization, photophysical, electrochemistry and biological properties - Bhat, Satish S.; Kumbhar, Avinash S.; Purandare, Neeraja; Khan, Ayesha; Grampp, Gunter; Loennecke, Peter; Hey-Hawkins, Evamarie; Dixit, Ruchi; Vanka, Kumar (Journal of Inorganic Biochemistry, 2020)
{Three water-soluble tris-heteroleptic ruthenium(II) polypyridyl complexes [Ru(bpy)(phen)(bpg)](2+) (1), [Ru (bpy)(dppz)(bpg)]2+ (2), and [Ru(phen)(dppz)(bpg)]2+ (3) (where bpy = 2,2'-bipyridine
Keywords: Circular dichroism; Cytotoxicity; fluorescence; Polypyridyl; ruthenium

Tunable light emission from chemical vapor deposited two-dimensional MoSe2 by layer variation and S incorporation - Singh, Vineeta; Late, Dattatray J.; Rath, Shyama (Journal of Vacuum Science & Technology A, 2020)
Mono- and few-layer thick MoSe2 and MoSxSe2-x domains were grown on insulating SiO2/Si substrates by chemical vapor deposition. Scanning electron microscopy and optical contrast images were used to determine the domain size and morphology. The structure, crystallinity, and the thickness (number of layers) of the as-synthesized domains were determined from Raman spectroscopy. The light emission was determined from photoluminescence (PL) spectroscopy. The PL emission started appearing only in domains having four layers or less, with the intensity increasing as the number of layers decreased. The PL peak position varied between 1.48eV (similar to 838nm) for four layers to 1.55eV (similar to 800nm) in the monolayer limit. Sulfur incorporation was done to enable a further tunability of the bandgap. The monolayer bandgap changed from 1.55eV for MoSe2 to 1.64eV (similar to 756nm) for MoS0.32Se0.68. The other effect of S incorporation was the formation of larger area domains in the alloy as compared to binary MoSe2 with an improvement in the structural properties, thus providing a pathway to improve the properties of two-dimensional semiconductors by mixing of two materials with similar atomic arrangements.

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties (vol 41, pg 14652, 2017) - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2020)

Active nickel hollow nanosphere supported over SiO2 catalyst for reduction of nitro compound - Pawar, Priyanka S.; Lokhande, Aboli A.; Nandanwar, Sachin U.; Niphadkar, Prashant S.; Bokade, Vijay V. (Particulate Science and Technology, 2021)
Nickel hollow nanospheres (Ni HNSs) was prepared by solvothermal method using mixture of ethylenediamine (EN) and ethanol (ET), sodium borohydride as reducing agent and nickel chloride hexahydrate as precursor. The particle size of the Ni HNSs were tuned by varying several parameters including precursor concentrations, reaction temperatures (130-190 degrees C), and ET to EN volume ratios. The particle size and morphology of Ni HNSs were confirmed by dynamic light scattering and transmission electron microscope, respectively. Spherical shape of Ni nanoparticles of 300 nm size having similar to 200 nm hollow space and 50 nm thickness was achieved at optimize condition of 4:6 volume ratio of ET/EN, 150 degrees C temperature, 0.1 M NaBH4 concentration, and 7 h. Ni HNSs supported over SiO2 (Ni HNSs/SiO2) with different loading of Ni HNSs (1-10 wt.%) were prepared by impregnation method. The catalyst was characterized by X-ray diffraction, and inductively coupled plasma - optical emission spectroscopy. The catalytic performance of Ni HNSs/SiO2 was carried out in the reduction of 4-Nitrophenol (4-NP) to 4 - Aminophenol (4-AP). 5 wt.% Ni HNSs/SiO2 exhibited 87% reduction of 4-NP in 25 min and stable up to 6 catalyst cycles due to higher surface area of the catalyst.
Keywords: 4-Aminophenol; 4-nitrophenol; Catalyst; hollow nanospheres; Nanoparticles; Nickel

Bimetallic ZnFe2O4 nanosheets prepared via electrodeposition as binder-free high-performance supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Park, Chanwoo; Kim, Yongil; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
Binder-free bimetallic ZnFe2O4 nanosheets were fabricated using one-step electrodeposition, which facilitated excellent electrical contact between the ZnFe2O4 nanosheets and the nickel substrate. The resultant numerous ZnFe2O4 nanosheets with their cubic spinel structures promote interfacial activity to enhance the electrochemical and Faradaic redox reactions. The metallic Zn and Fe from the cubic spinel structure of ZnFe2O4 attract electrolytic ions and increase the energy-storage capability, thus yielding a specific capacitance of 1093 F.g(-1) at a current rate of 1 A.g(-1). Different samples were prepared by varying the amount of metal salts in the electrodeposition solution while maintaining a constant ZnNt:FeSO4 concentration ratio of 1:2 for all cases. The optimal electrode composition, which yielded an energy density of 54 Wh.kg(-1) and a capacitance retention of 93.5% at N = 5000 charge-discharge cycles, was identified.
Keywords: Bimetallic; Electrodeposition; Energy storage device; supercapacitor; ZnFe2O4 nanosheet

Biological process of lysine-tRNA charging is therapeutically targetable in liver cancer - Zhang, Ruyi; Noordam, Lisanne; Ou, Xumin; Ma, Buyun; Li, Yunlong; Das, Pronay; Shi, Shaojun; Liu, Jiaye; Wang, Ling; Li, Pengfei; Verstegen, Monique M. A.; Reddy, D. Srinivasa; et al. (Liver International, 2021)
Background & Aims Mature transfer RNAs (tRNA) charged with amino acids decode mRNA to synthesize proteins. Dysregulation of translational machineries has a fundamental impact on cancer biology. This study aims to map the tRNAome landscape in liver cancer patients and to explore potential therapeutic targets at the interface of charging amino acid with tRNA. Methods Resected tumour and paired tumour-free (TFL) tissues from hepatocellular carcinoma (HCC) patients (n = 69), and healthy liver tissues from organ transplant donors (n = 21), HCC cell lines, and cholangiocarcinoma (CC) patient-derived tumour organoids were used. Results The expression levels of different mature tRNAs were highly correlated and closely clustered within individual tissues, suggesting that different members of the tRNAome function cooperatively in protein translation. Interestingly, high expression of tRNA-Lys-CUU in HCC tumours was associated with more tumour recurrence (HR 1.1;P = .022) and worse patient survival (HR 1.1;P = .0037). The expression of Lysyl-tRNA Synthetase (KARS), the enzyme catalysing the charge of lysine to tRNA-Lys-CUU, was significantly upregulated in HCC tumour tissues compared to tumour-free liver tissues. In HCC cell lines, lysine deprivation, KARS knockdown or treatment with the KARS inhibitor cladosporin effectively inhibited overall cell growth, single cell-based colony formation and cell migration. This was mechanistically mediated by cell cycling arrest and induction of apoptosis. Finally, these inhibitory effects were confirmed in 3D cultured patient-derived CC organoids. Conclusions The biological process of charging tRNA-Lys-CUU with lysine sustains liver cancer cell growth and migration, and is clinically relevant in HCC patients. This process can be therapeutically targeted and represents an unexplored territory for developing novel treatment strategies against liver cancer.
Keywords: Cladosporin; liver cancer; lysine; Lysyl-tRNA Synthetase; tRNA-Lys-CUU; tRNAome

Cotton fabric decorated with manganese oxide nanorods as a supercapacitive flexible electrode for wearable electronics - Samuel, Edmund; Joshi, Bhavana; Kim, Yongil; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
We present the fabrication (using a hydrothermal process) and the properties of wearable fabrics decorated with ultrathin manganese oxide (MnO2) nanorods for supercapacitor applications. The superior mechanical durability of the supercapacitor was confirmed by cyclic voltammetry (CV) curves, which showed little change during 1000 bending cycles. The pseudocapacitive properties of the ultrathin MnO2 nanorods were confirmed by recording the CV curves at various scan rates. The galvanostatic charge-discharge curves at various specific currents confirmed the pseudocapacitance of MnO2. The ultrathin MnO2 nanorods exhibited a superior capacitance of 508 F.g(-1) and an energy density of 35.3 Wh.kg(-1). The MnO2 electrode with optimal properties demonstrated stable long-term cycling performance with 90% retention after 10,000 galvanostatic cycles.
Keywords: Cotton fabric; Manganese oxide; Ultrafine nanostructures; Wearable supercapacitors

Deciphering the role of temperature in Li+ co-dopant occupancy in BaYF5:Yb3+,Er3+ up-converting nanocrystals and its structure-property relationship - Devi, Suman; Luwang, Meitram Niraj (Journal of Chemical Physics, 2021)
Precision engineering of defects in luminescent nanoscale crystalline materials with lesser controls to design is an area of interest in engineering materials with desired properties. Li+ co-doped BaYF5 nanocrystals were engineered, and temperature as controls for determining the co-dopant occupancies in the host lattice is studied. An observed enhancement in the up-conversion photoluminescence results from the co-dopant occupancy at Ba2+ sites via substitution through the hot injection method, whereas for samples prepared using co-precipitation, photoluminescence quenching was observed, which can be correlated with the Li+ occupancy at the interstitial site near Er3+ and also due to the incorporation of OH-. The crystal lattice deformation as a result of doping and the mechanism for the observed enhancement/quenching of luminescence are studied using x-ray diffraction, x-ray photoelectron spectroscopy, and energy transfer mechanism. Cytotoxicity assay and photoluminescence studies of the synthesized nanocrystals confirm that the material is biocompatible.

Enhanced solubility, permeability, and tabletability of nicorandil by salt and cocrystal formation - Mannava, M. K. Chaitanya; Gunnam, Anilkumar; Lodagekar, Anurag; Shastri, Nalini R.; Nangia, Ashwini K.; Solomon, K. Anand (Crystengcomm, 2021)
Cocrystallization is a rational selection crystal engineering approach for the development of novel solid forms with enhanced physicochemical and mechanical properties. Nicorandil (NCR) is a niacinamide vitamin derivative used to treat angina pectoris. A binary solid form screen of NCR with homologous dicarboxylic acids afforded NCR-oxalic acid (NCR-OA, 1:1), NCR-fumaric acid (NCR-FA, 1:1), NCR-succinic acid (NCR-SA, 1:1), and NCR-suberic acid (NCR-SBA, 1:0.5). The binary solids were characterized by powder X-ray diffraction, IR and NMR spectroscopy, and DSC. NCR-FA and NCR-SBA were crystallized by slow evaporation from chloroform and toluene solvents, respectively. Single crystal X-ray diffraction confirmed that NCR-FA is a molecular salt, while NCR-SBA is a neutral cocrystal. NCR and the FA anion are connected via the robust carbovlate-pyridinium synthon, whereas in the NCR-SBA cocrystal, the components associate via the carboxylic acid- -pyridine synthon. The phase stability, solubility, dissolution rate, diffusion rate and tabletability studies have demonstrated that the binary solids exhibit improved physical and mechanical properties compared to the NCR drug. Specifically, the NCR-FA salt and NCR-SBA cocrystal have higher solubility, dissolution rate, and hardness at lower pressures, making the formulation suitable for tablet compression.

Flexible metallized carbon nanofibers decorated with two-dimensional NiGa2S4 nanosheets as supercapacitor electrodes - Kim, Yongil; Samuel, Edmund; Joshi, Bhavana; Park, Chanwoo; Lee, Hae-Seok; Yoon, Sam S. (Chemical Engineering Journal, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Herein, high-power flexible supercapacitor electrodes were fabricated by decorating Ni-electroplated carbon nanofibers (Ni@CNF) with two-dimensional NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> nanosheets. The electrical conductivity of carbon nanofibers was enhanced by the addition of nickel, and the energy storage capability was enhanced by decoration with NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The impact of metal (Ni/Ga) ratio on the overall electrochemical performance of the supercapacitor was studied by varying the Ga concentration. The NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> nanosheets promoted diffusion of the electrolyte into the electrode, thereby improving the electrochemical activity. The nanosheets also intensified the charge transfer rate within the composite electrode, which contributed to the overall improvement in the electrochemical performance. The optimal Ga concentration was the concentration at which the specific capacitance was the highest at 488 F·g<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">−1<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> with a potential window of 1.1 V and current rate of 0.5 A·g<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">−1<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The long-term stability test revealed that the capacitance retention of the electrode with this optimal Ni/Ga ratio was 109% after 20,000 cycles. This flexible supercapacitor electrode was subjected to 2000 bending cycles, and the corresponding cyclic voltammetry performance was assessed. In combination, the outstanding electrochemical performance and durable mechanical properties render the NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/Ni@CNF electrode highly suitable for flexible energy storage applications.

Functional insights into two Ocimum kilimandscharicum 4-coumarate-CoA ligases involved in phenylpropanoid biosynthesis - Lavhale, Santosh G.; Joshi, Rakesh S.; Kumar, Yashwant; Giri, Ashok P. (International Journal of Biological Macromolecules, 2021)
Plant 4-coumarate-CoA ligase (4CL) catalyzes the ligation of CoA to cinnamic acid and its derivatives. Activated CoA esters are utilized for the biosynthesis of phenolic metabolites and lignin that play essential function in plants. Here, we characterize the diversity of Ocimum kilimandscharicum 4CLs (Ok4CLs). Phylogenetic analysis suggest that Ok4CLs could be grouped into three classes, class I -enzymes mostly involved in lignin biosynthesis, class II -non-structural phenylpropanoid biosynthesis and class III -yet to be characterized for specific role(s). We selected two Ok4CLs namely Ok4CL7 and Ok4CL15 for further characterization. Gene expression analysis sug-gested that Ok4CL7 is highly expressed in leaf trichomes, whereas Ok4CL15 is abundant in the roots. The recom-binant Ok4CL7 and Ok4CL15 had optimal enzyme activities at 40 degrees C in pH 8 and 7, respectively. Ok4CL7 showed substrate preference towards p-coumaric acid, ferulic acid and caffeic acid. While, Ok4CL15 preferredp-coumaric acid, ferulic acid and sinapic acid. Feruloyl adenylate showed higher number of contacts and lowers binding en-ergy with Ok4CL7 and 15 compared to cinnamoyl adenylate. Based on root-specific expression and preference for sinapic acid, Ok4CL15 might be involved in lignin biosynthesis. Further exploration is needed to unravel the role of diverse Ok4CLs in O. kilimandscharicum. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: 4-Coumarate-CoA ligase; Flavonoids; lignin; Ocimum kilimandscharicum; Phenylpropanoids

Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).

MoS2 and CdMoS4 nanostructure-based UV light photodetectors - Pawar, Mahendra S.; Kadam, Sunil R.; Kale, Bharat B.; Late, Dattatray J. (Nanoscale Advances, 2021)
We have developed MoS2 nanosheets and CdMoS4 hierarchical nanostructures based on a UV light photodetector. The surface morphologies of the as-prepared samples were investigated via field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The performance parameters for the present photodetectors are investigated under the illumination of UV light having a wavelength of similar to 385 nm. Upon the illumination of UV light, the CdMoS4-based photodetector device showed a better response to UV light compared to the MoS2 device in terms of photoresponsivity, response time (similar to 72 s) and recovery time (similar to 94 s). Our results reveal that CdMoS4 hierarchical nanostructures are practical for enhancing the device performance.

On the origin of controlled anisotropic growth of monodisperse gold nanobipyramids - Meena, Santosh Kumar; Lerouge, Frederic; Baldeck, Patrice; Andraud, Chantal; Garavelli, Marco; Parola, Stephane; Sulpizi, Marialore; Rivalta, Ivan (Nanoscale, 2021)
We elucidate the crucial role of the cetyl trimethylammonium bromide (CTAB) surfactant in the anisotropic growth mechanism of gold nano-bipyramids, nano-objects with remarkable optical properties and high tunability. Atomistic molecular dynamics simulations predict different surface coverages of the CTAB (positively charged) heads and their (bromide) counterions as function of the gold exposed surfaces. High concentration of CTAB surfactant promotes formation of gold nanograins in solution that work as precursors for the smooth anisotropic growth of more elongated nano-bipyramidal objects. Nanobipyramids feature higher index facets with respect to nanorods, allowing higher CTAB coverages that stabilize their formation and leading to narrower inter-micelles channels that smooth down their anisotropic growth. Absorption spectroscopy and scanning electron microscopy confirmed the formation of nanograins and demonstrated the importance of surfactant concentration on driving the growth towards nano-bipyramids rather than nanorods. The outcome explains the formation of the monodisperse bipyramidal nano-objects, the origin of their controlled shapes and sizes along with their remarkable stability.

Performance of Aspergillus niger (NCIM 563) phytase based feed supplement for broiler growth and phosphorus excretion - Puppala, Kumar Raja; Buddhiwant, Priyanka G.; Agawane, Sachin B.; Kadam, Avinash S.; Mote, Chandrashekhar S.; Lonkar, Vijaysinh D.; Khire, Jayant M.; Dharne, Mahesh S. (Biocatalysis and Agricultural Biotechnology, 2021)
Despite availability of commercial enzymes, the phytase produced from relatively inexpensive systems with high yields are gaining global attention in the feed industries in post-antibiotic era. We studied A. niger NCIM 563 Phytase produced in solid state fermentation (SSF) derived Koji powder and evaluated its utility in the poultry feed for broiler growth performance and phosphorous (P) excretion. The ability of phytase in the dried powder was estimated to dephytinize the poultry feed under simulated gastric conditions. Poultry feed was formulated using A. niger NCIM 563 phytase followed by a 42 days feed trial on broilers. After supplementation of phytase to the diet, there was a reduction of dietary P, maintained growth performance, skeletal development of broilers and reduced levels of phytic acid and available P in the litter. Extracellular phytase was able to replace up to 0.1% P in poultry feed. Minimal downstream processing a low-cost feed supplement with significant phytase activity could provide added advantage for anti-nutrition free poultry feed.
Keywords: Phosphorus; Phytase; Poultry feed; Solid state fermentation

Rapid and accurate nucleobase detection using FnCas9 and its application in COVID-19 diagnosis - Azhar, Mohd; Phutela, Rhythm; Kumar, Manoj; Ansari, Asgar Hussain; Rauthan, Riya; Gulati, Sneha; Sharma, Namrata; Sinha, Dipanjali; Sharma, Saumya; Singh, Sunaina; Acharya, Sundaram; Sarkar, Sajal; et al. (Biosensors & Bioelectronics, 2021)
Rapid detection of DNA/RNA pathogenic sequences or variants through point-of-care diagnostics is valuable for accelerated clinical prognosis, as witnessed during the recent COVID-19 outbreak. Traditional methods relying on qPCR or sequencing are tough to implement with limited resources, necessitating the development of accurate and robust alternative strategies. Here, we report FnCas9 Editor Linked Uniform Detection Assay (FELUDA) that utilizes a direct Cas9 based enzymatic readout for detecting nucleobase and nucleotide sequences without transcleavage of reporter molecules. We also demonstrate that FELUDA is 100% accurate in detecting single nucleotide variants (SNVs), including heterozygous carriers, and present a simple web-tool JATAYU to aid end-users. FELUDA is semi-quantitative, can adapt to multiple signal detection platforms, and deploy for versatile applications such as molecular diagnosis during infectious disease outbreaks like COVID-19. Employing a lateral flow readout, FELUDA shows 100% sensitivity and 97% specificity across all ranges of viral loads in clinical samples within 1hr. In combination with RT-RPA and a smartphone application True Outcome Predicted via Strip Evaluation (TOPSE), we present a prototype for FELUDA for CoV-2 detection closer to home.
Keywords: CRISPRDx; FELUDA; FnCas9; LFA; SARS-CoV2; SNV detection

Red fluorescent ultra-small gold nanoclusters functionalized with signal molecules to probe specificity in quorum sensing receptors in gram-negative bacteria - Chahande, Anurag M.; Lathigara, Disha; Prabhune, Asmita A.; Devi, R. Nandini (Archives of Microbiology, 2021)
Ultra-small (size < 2 nm) gold nanoclusters (AuNCs) are used as fluorescent probes which have excellent applications in bioimaging and sensing due to their emission in visible and NIR spectral region. Here, this property is exploited for understanding the quorum sensing phenomenon in bacteria which is regulated by signal molecules which are specific to various species. AuNCs are then functionalized with the signal molecules, Acyl Homoserine Lactones (AHL) of varying carbon chain length, C-6, C-8, and C-12 without 3rd C modification, to sense different strains of gram-negative bacteria i.e., Escherichia coli, Cronobacter sakazakii and Pseudomonas aeruginosa. In the concentration employed, selectivity to a limited extent is observed between the three Gram-negative bacteria tested. E. coli showed emission with all the AHL conjugates and P. aeruginosa did not interact with any of the three conjugates, whereas C. sakazakii showed specificity to C-8AHL. This is probably due to selectivity for cognate AHL molecules of appropriate concentrations.
Keywords: acyl homoserine lactone; fluorescence imaging; Gold nanoclusters; quorum sensing; Receptors; selectivity

Review of the recent progress on thermal conductivity of nanofluid - Lenin, Ramanujam; Joy, Pattayil Alias; Bera, Chandan (Journal of Molecular Liquids, 2021)
Thermal properties of nanofluids are very well investigated by the global research community for their various applications. The dispersion and stability of the nanoparticles in the base fluid are the essential requirements for the efficient utilization of nanofluids in many applications. The interfacial layer plays a crucial role in the dispersion, stability, and heat transfer properties of the nanofluid. The heat transfer property of the nanofluids is mainly influenced by the heat transfer properties at the particle-fluid interface. The thickness and thermal conductivity of the interfacial layer are the crucial factors that decide the heat transfer at the interface, and the difficulties in the determination of these factors limits the progress of the research. In this review article, the experimental studies on the thickness and thermal conductivity of the interfacial layer are reviewed briefly. The effect of interfacial the layer on the nanoscale mechanisms and thermophysical properties of nanofluids are reviewed. The effect of various tunable parameters on the heat transfer properties of the interfacial layer is also reviewed. This review will be beneficial for fine-tuning nanofluid's thermal properties and their commercial applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Interfacial layer; Interfacial thermal conductance; Nanofluid; Surfactants; Thermal conductivity

Rhamonolipids produced by Pseudomonas aeruginosa promotes methane hydrates formation in fixed bed silica gel medium - Arora, Amit; Cameotra, Swaranjit Singh; Balomajumder, Chandrajit; Kumar, Rajnish; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Marine Geophysical Research, 2021)
Natural gas hydrates are seen as an alternative future energy source. They have also been valued for their carbon dioxide capturing capability, gas separation, desalination, natural gas storage and transportation. Developing economical and viable gas hydrate based technology is one of the most promising research areas of present decade. Successful commercialization of gas hydrate based technology is often curtailed due to slow formation rate. The present study evaluates biosurfactant as a kinetic promoter of methane hydrates formation in a fixed bed C type silica gel medium. Biosurfactant was produced by growing Pseudomonas aeruginosa strain A11 in glycerol supplemented mineral salt medium. Biosurfactant characterization with FTIR, NMR and MALDI-TOF spectroscopy reveled it to be a glycolipids type biosurfactant namely rhamnolipids. Saturating C type silica gel with of 100 ppm rhamnolipids solution enhanced the rate of methane hydrates formation by reducing the induction time. Mole of methane consumed and percentage of water to hydrate conversion was observed to be more in 1000 ppm rhamnolipids saturated C type silica gel as compared to quiescent water system and water saturated silica gel system. Overall results suggest that rhamonolipids produced by strain A11 in combination with silica gel can be utilized as environmentally safe kinetic promoter for methane hydrate formation.
Keywords: Biosurfactant; Energy; Glycolipids; Induction time; Kinetic promoter

Room-temperature quasi-catalytic hydrogen generation from waste and water - Wu, Hongguo; Zhang, Li-Long; Wang, Junqi; Jiang, Yiyuan; Li, Hu; Sudarsanam, Putla; Yang, Song (Green Chemistry, 2021)
A solvation-driven catalyst-free H-2 generation system from water and various waste hydrosilanes at room temperature was developed, with good to quantitative H-2 yields in minutes. Using a green solvent is found to promote the strong coordination of proton carriers with hydrosilane to liberate H-2 based on molecular dynamics simulations. Theoretical calculations clarify that OH(-)in situ generated from H2O enabled by solvation is favorable for activating the Si-H species of hydrosilane, and the in situ formed Si-OH interacts more effectively with the adjacent remaining Si-H, both contributing to the overall enhanced H-2 generation. Moreover, the overall life-cycle impacts of the developed system are less than those of industrial H-2 production processes, especially in ozone layer depletion and abiotic depletion resources - fossil fuels. This protocol realizes the potential of efficiently producing H-2 from waste and water, and opens a new avenue to alleviate petroleum consumption.

Sulfonic acid-functionalized heterogeneous catalytic materials for efficient biodiesel production: a review - Tan, Xiang; Sudarsanam, Putla; Tan, Jinyu; Wang, Anping; Zhang, Heng; Li, Hu; Yang, Song (Journal of Environmental Chemical Engineering, 2021)
The development of social productive forces leads to the increasing consumption of fossil fuels. However, the burning of traditional fossil fuels releases huge amounts of carbon emissions into the atmosphere, resulting in drastically increased global surface temperatures, and hence, global warming and abnormal climate change. Biodiesel, which can be produced by (trans)esterification of bio-oils using solid acid catalysts, is recognized as renewable and clean energy, alternative to fossil-derived diesel, and it can meet society's requirements. This review describes the catalytic conversion of bio-derived oils into biodiesel using various sulfonic acid-functionalized heterogeneous catalytic materials that show higher catalytic efficiency and superior recyclability. Besides, various methods of biodiesel preparation and the appropriate design and preparation of robust and efficient catalytic materials for biodiesel production were provided. Finally, the mechanisms of different catalytic esterification and transesterification reactions for biodiesel synthesis, the relevant reaction kinetic models, and techno-economic analysis of biodiesel production were critically discussed in this review.
Keywords: (Trans)esterification; Biodiesel; heterogeneous catalysis; kinetic study; solid acid

Adsorption of toxic Pb(II) on activated carbon derived from agriculture waste (Mahogany fruit shell): isotherm, kinetic and thermodynamic study - Patil, Suryakant A.; Suryawanshi, Umesh P.; Harale, Namdev S.; Patil, Sandip K.; Vadiyar, Madgonda M.; Luwang, Meitram N.; Anuse, Mansing A.; Kim, Jin H.; Kolekar, Sanjay S. (International Journal of Environmental Analytical Chemistry, 2022)
An adsorbent, mahogany fruit shell activated carbon(MFSAC), was derived from environmental friendly raw material, i.e. agriculture waste and explored for bench scale adsorption of toxic Pb(II). A facile MFSAC material was synthesised using a chemical activation method using concentrated sulphuric acid as an impregnating (activating) reagent. So derived adsorbent material was characterised by FTIR, XRD, BET, SEM, EDAX, TGA and XPS techniques to know the properties and plausible adsorption mechanism. Bench scale adsorption of toxic Pb(II) and maximum adsorption capacity of MFSAC were exhibited through batch adsorption experiments. The effect of physico-chemical parameters such as pH (1-7), MFSAC amount (0.5-5.0 g L-1), Pb(II) concentration (200-1000 mgL(-1)), contact period (60-600 min) and orbital shaking speed (60-200 rpm) was studied for maximum removal of Pb(II) upto 99.70 +/- 0.17%. The experimental data follow the Langmuir adsorption isotherm with a maximum monolayer adsorption capacity 322.28 mg g(-1)and pseudo-second-order kinetic uptake rate. The thermodynamic and temperature study revealed that the adsorption process was spontaneous and endothermic in nature (Delta H-o = 43.37 kJ mole(-1), Delta S-o = 158.02 J mol(-1)K(-1)). Most importantly, the MFSAC adsorbent was successfully regenerated and reused with conspicuous performance up to five consecutive cycles. The bench-scale adsorption with simple synthesis route, good stability and remarkable regeneration capability makes the MFSAC as an encouraging adsorbent for wastewater treatment.
Keywords: activated carbon; Adsorption; mahogany fruit shell; Pb(II); sulphuric acid

Artificial intelligence in microbial natural product drug discovery: current and emerging role - SahayaSheela, Vinodh J.; Lankadasari, Manendra B.; Dan, Vipin Mohan; Dastager, Syed G.; Pandian, Ganesh N.; Sugiyama, Hiroshi (Natural Product Reports, 2022)
Covering: up to the end of 2022 Microorganisms are exceptional sources of a wide array of unique natural products and play a significant role in drug discovery. During the golden era, several life-saving antibiotics and anticancer agents were isolated from microbes; moreover, they are still widely used. However, difficulties in the isolation methods and repeated discoveries of the same molecules have caused a setback in the past. Artificial intelligence (AI) has had a profound impact on various research fields, and its application allows the effective performance of data analyses and predictions. With the advances in omics, it is possible to obtain a wealth of information for the identification, isolation, and target prediction of secondary metabolites. In this review, we discuss drug discovery based on natural products from microorganisms with the help of AI and machine learning.

Boosting electrochemical CO2 reduction to methane via tuning oxygen vacancy concentration and surface termination on a copper/ceria catalyst - Patra, Kshirodra Kumar; Liu, Zhu; Lee, Hojeong; Hong, Seungwon; Song, Hakhyeon; Abbas, Hafiz Ghulam; Kwon, Youngkook; Ringe, Stefan; Oh, Jihun (ACS Catalysis, 2022)
Metal oxides are a promising material for designing highly active and selective catalysts for the electrochemical reduction of carbon dioxide (CO2RR). Here, we designed a Cu/ceria catalyst with high selectivity of methane production at single-atomic Cu active sites. Using this, we report favorable design concepts that push the product selectivity of methane formation by combining detailed structural analysis, density functional theory (DFT), in situ Raman spectroscopy, and electrochemical measurements. We demonstrate that a higher concentration of oxygen vacancies on the catalyst surface, resulting from more available Cu+ sites, enables high selectivity for methane formation during CO2RR and can be controlled by the calcination temperature. The DFT calculation and in situ Raman studies indicate that pH controls the surface termination; a more alkaline pH generates hydroxylated surface motifs with more active sites for the hydrogen evolution reaction. These findings provide insights into designing an efficient metal oxide electrocatalyst by controlling the atomic structure via the reaction environment and synthesis conditions.
Keywords: copper-ceria; electrochemical CO2 reduction; electrolyte pH; gas diffusion electrode; methane production; Oxygen vacancy

CdS cubane type clusters encapsulated by rolling of single layer reduced graphene oxide sheets for enhanced mechanical energy harvesting - Kumar, Praveen; Ram, Farsa; Shanmuganathan, Kadhiravan; Luwang, Meitram Niraj (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Composites with Single Layer Graphene Oxide (SLGO) sheets are extremely difficult to achieve, irrespective of the current advancements in graphene composites research. The difficulties in exfoliating the graphite oxide (GO) was associated with a strong interaction among the edge sides of the adjacent layers. This in-turn barricades the foreign intruders to interact with the basal plane, thereby restraining one to form composites with SLGO sheets. In this work, we had successfully exfoliated GO through a spacer [Cd(OAc)(2) + polyethylene glycol (PEG)] to result in nano-engineered CdS cubane-type clusters in rolled up SLGO to form graphene oxide complex compound (GOCC), resembling carbon nanotubes (CNTs). The CdS cubane-type clusters were found to interacting with the carbon skeleton of rolled reduced SLGO sheet through a Manogate' structures, which was supported by density functional theory (DFT) calculations. Our theoretical study reveals that the obtained complex compound (GOCC) is thermodynamically more favourable than its ancestor materials (CdS cubane and empty CNT). Flexible piezoelectric nanogenerators (PENGs) fabricated from GOCC and thermoplastic polyurethane (TPU) resulted in output voltage (V-oc) of 4.5 V and output current of 0.4 mu A at applied force of 13 N. The nanoengineering helps to achieve superior mechanical energy harvesting performance for GOCC compared to pristine CdS, which demonstrate the potential of nanogate structures to enhance the intrinsic properties of materials.
Keywords: Graphene oxide complex compound; Nanogate structure; New material; Novel procedure; Piezoelectric nanogenerator; SLGO

Covalent organic framework with electrodeposited copper nanoparticles - a desirable catalyst for the Ullmann coupling reaction - Chandran, Chandana; Singh, Himan Dev; Leo, Liya S.; Shekhar, Pragalbh; Rase, Deepak; Chakraborty, Debanjan; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Journal of Materials Chemistry A, 2022)
A covalent organic framework is a porous covalently-linked polymeric assembly built from molecular lego blocks, the monomers. A COF's high surface area, ordered pores, and intrinsic low density makes it a perfect heterogeneous catalyst component. Dispersing catalytic metal nanoparticles into the porous COF matrix in a `capping-agent-free' manner can aid the maximal utilization of the active sites. To generate single-site catalysts, metals have been anchored to dense supports, or metal ions have been coordinated to the porous organic framework. The latter has superior atom efficiency and a substrate diffusion advantage. Stably nestling neutral metallic clusters into open-framework supports with no specifically strong binding groups requires a different approach. If infused from extremely dilute electrolytes, metal clusters can be nanoconfined into electrically activated COFs. At low-loadings, it can resemble a single-site catalyst with high atom efficiency. Herein, we report the larger scale synthesis of IISERP-COF15 and electrochemical loading of copper nanoparticles into its pores at loadings as low as 3.34 wt%. We employed classical Ullmann reactions to adjudge its activity. Typical turnover numbers for the catalysts reported in the literature are approximately 50-100. A Cu@COF shows high activity with a very low catalyst loading of 0.25 mol% (TON around similar to 300-350 vs. 4 for neat CuCl2 center dot 2H(2)O (homogeneous catalyst) and turnover frequency (similar to 15-17 h(-1))). We recycled it for up to 3 cycles. Furthermore, we report a multi-fold Ullmann reaction producing an unreported hexaaldehyde to demonstrate the latitude of the catalyst. Our work points to the potential of a dilutely loaded metal@COF as a mimic of the single-site catalyst for synthesizing valuable C-O linked molecules. Our findings from computational modeling shed light on the role of the COF as an active nanoporous support for Ullmann C-O coupling.

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis

Different mechanical responses of dimorphic forms of anthracene schiffbase crystal - Lakshmipathi, Madhumathi; Tothadi, Srinu; Emmerling, Franziska; Bhattacharya, Biswajit; Ghosh, Soumyajit (Journal of Molecular Structure, 2022)
We obtained concomitant dimorphic forms of Anthracene Schiffbase (N-(anthracen-9-yl methylene)-2,5dichloroaniline) from hexane solvent. Two polymorphs can be differentiated by their morphology and mechanical properties. One form is long acicular type and elastically bendable while another form is block shaped and brittle in nature. Mechanical property is attributed to underlying crystal packing. Hirshfeld analysis and energy framework calculations were done to corroborate structure-property correlation of two forms (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Anthracene schiffbase; Dimorphs; Elasticity; mechanical properties

Direct oxidation of bromo-derived Fischer-Borsche oxo-ring using molecular iodine with combined experimental and computational study - Humne, Vivek T.; Ghom, Monica H.; Naykode, Mahavir S.; Dangat, Yuvraj; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2022)
A direct oxidation of the bromo-derived Fischer-Borsche oxo-ring leading to carbazolequinone has been developed by using molecular iodine. This unprecedented transformation has been used for the modular synthesis of the anti-cardiotonic agent murrayaquinone. Furthermore, the present method has been generalized to a broad range of functional groups, with good to excellent yield.

The effects of cis and trans butenedioic acid on the physicochemical behavior of lumefantrine - Tomar, Devendrasingh; Lodagekar, Anurag; Gunnam, Anilkumar; Allu, Suryanarayana; Chavan, Rahul B.; Tharkar, Minakshi; Ajithkumar, T. G.; Nangia, Ashwini K.; Shastri, Nalini R. (Crystengcomm, 2022)
The present work investigates the effects of cis and trans butenedioic acid isomers (maleic acid and fumaric acid) on the crystallinity and pharmaceutical behavior of lumefantrine. Differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), attenuated total reflectance infrared spectroscopy (ATR-IR), solid-state nuclear magnetic resonance spectroscopy (ss-NMR), and single-crystal X-ray diffraction (SC-XRD) studies were employed. Lumefantrine-fumaric acid crystallized as a salt in the monoclinic space group P2(1)/c. In comparison, DSC and PXRD showed the formation of a co-amorphous solid with maleic acid. Complete proton transfer with a strong ionic interaction led to crystalline salt formation with the trans isomer, whereas weaker/fewer hydrogen bonds with the cis isomer of butenedioic acid led to a co-amorphous salt. The in vitro dissolution of both salts resulted in a similar 2.6-2.7-fold improvement in dissolution rate when compared to that of the crystalline lumefantrine. The crystalline and co-amorphous salts were stable under accelerated stability conditions (40 +/- 2 degrees C and 75 +/- 5% RH) for one month.

Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C

Enhanced hydrogen fuel production using synergistic combination of solar radiation and TiO2 photocatalyst coupled with Burkholderia cepacia lipase - de Souza Brandao, Luma Mirely; Barbosa, Milson dos Santos; de Jesus, Roberta Anjos; Bharad, Pradnya Arunrao; Lima, Alvaro Silva; Faria Soares, Cleide Mara; Navarro Yerga, Rufino Manuel; Bilal, Muhammad; Romanholo Ferreira, Luiz Fernando; Iqbal, Hafiz M. N.; Gopinath, Chinnakonda S.; Figueiredo, Renan Tavares (International Journal of Hydrogen Energy, 2022)
Promising and sustainable alternatives for hydrogen production have been investigated. Among these, the use of enzymes may represent an efficient alternative. In this work, an increase in hydrogen production under simulated sunlight by combining TiO2 and TiO2/MgCl2 with Burkholderia cepacia lipase (BCL) was reported. The samples (TiO2, TiO2/MgCl2, and TiO2 /MgCl2/BCL) were characterized by X-ray diffraction (XRD), thermo-gravimetric (TGA), N-2 adsorption-desorption isotherms (BET), scanning electron microscopy (SEM), and UV-Visible absorption spectra. Hydrogen production tests were performed in aqueous methanol solutions under simulated sunlight. The results demonstrated that 130-times greater increase in hydrogen production rate was observed by the addition of BCL than individual TiO2. This better hydrogen production rate can be attributed to the increase in the amount of reduction equivalent of the system due to the oxidation of protein peptides caused by TiO2. In conclusion, the results indicate that hydrogen production efficiency can be significantly improved when integrating TiO2/MgCl2 with BCL. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen production; Lipase; Nano-conjugated enzymes; Photocatalyst; Solar radiation; Titanium dioxide

High-alkaline water-splitting activity of mesoporous 3D heterostructures: an amorphous-shell@crystalline-core nano-assembly of Co-Ni-phosphate ultrathin-nanosheets and V- doped cobalt-nitride nanowires - Singh, Thangjam Ibomcha; Maibam, Ashakiran; Cha, Dun Chan; Yoo, Sunghoon; BabaRao, Ravichandar; Lee, Sang Uck; Lee, Seunghyun (Advanced Science, 2022)
Introducing amorphous and ultrathin nanosheets of transition bimetal phosphate arrays that are highly active in the oxygen evolution reaction (OER) as shells over an electronically modulated crystalline core with low hydrogen absorption energy for an excellent hydrogen evolution reaction (HER) can boost the sluggish kinetics of the OER and HER in alkaline electrolytes. Therefore, in this study, ultrathin and amorphous cobalt-nickel-phosphate (CoNiPOx) nanosheet arrays are deposited over vanadium (V)-doped cobalt-nitride (V-3%-Co4N) crystalline core nanowires to obtain amorphous-shell@crystalline-core mesoporous 3D-heterostructures (CoNiPOx@V-Co4N/NF) as bifunctional electrocatalysts. The optimized electrocatalyst shows extremely low HER and OER overpotentials of 53 and 270 mV at 10 mA cm(-2), respectively. The CoNiPOx@V-3%-Co4N/NF (+/-) electrolyzer utilizing the electrocatalyst as both anode and cathode demonstrates remarkable overall water-splitting activity, requiring a cell potential of only 1.52 V at 10 mA cm(-2), 30 mV lower than that of the RuO2/NF (+)/20%-Pt/C/NF (-) electrolyzer. Such impressive bifunctional activities can be attributed to abundant active sites, adjusted electronic structure, lower charge-transfer resistance, enhanced electrochemically active surface area (ECSA), and surface- and volume-confined electrocatalysis resulting from the synergistic effects of the crystalline V-3%-Co4N core and amorphous CoNiPOx shells boosting water splitting in alkaline media.
Keywords: core-shell; hydrogen productions; metal nitrides; metal phosphates; synergistic effect; water-splitting

Interdigitated flow field impact on mass transport and electrochemical reaction in high-temperature polymer electrolyte fuel cell - Agarwal, Harshal; Thosar, Aniket U.; Bhat, Santoshkumar D.; Lele, Ashish K. (Journal of Power Sources, 2022)
The enhanced performance of Polybenzimidazole (PBI) based high-temperature polymer electrolyte fuel cell (HT-PEFC) with interdigitated flow field over the other flow fields can be a consequence of higher average pressure developed on the flow field due to dead end in the channels or faster mass transport due to pressuredriven convection in the gas diffusion layer (GDL). In the present study, the effect of average pressure on the flow field and mass transport mechanism in the GDL on the HT-PEFC performance have been systematically decoupled. Three-dimensional simulation validated by experimental studies confirm that the enhanced performance in case of the interdigitated flow field is due to faster mass transport in the GDL and not due to higher average gas pressure. The simulation studies are performed on the interdigitated flow field and compared against the parallel flow field to have an insight into the effect of key operating and geometric parameters. There exists an optimum value for channel to rib ratio and current density saturates after an air stoichiometry of 4 which is validated by experiments.
Keywords: HT-PEFC; Interdigitated flow field; Mass transport mechanism; pressure; stoichiometry

Janus cross-links in supramolecular networks - Mondal, Swagata; Lessard, Jacob J.; Meena, Chhuttan L.; Sanjayan, Gangadhar J.; Sumerlin, Brent S. (Journal of the American Chemical Society, 2022)
Thermosets composed of cross-linked polymers demonstrate enhanced thermal, solvent, chemical, and dimensional stability as compared to their non-cross-linked counterparts. However, these often-desirable material properties typically come at the expense of reprocessability, recyclability, and healability. One solution to this challenge comes from the construction of polymers that are reversibly cross-linked. We relied on lessons from Nature to present supramolecular polymer networks comprised of cooperative Janus-faced hydrogen bonded cross-links. A triazine-based guanine-cytosine base (GCB) with two complementary faces capable of self-assembly through three hydrogen bonding sites was incorporated into poly(butyl acrylate) to create a reprocessable and recyclable network. Rheological experiments and dynamic mechanical analysis (DMA) were employed to investigate the flow behavior of copolymers with randomly distributed GCB units of varying incorporation. Our studies revealed that the cooperativity of multiple hydrogen bonding faces yields excellent network integrity evidenced by a rubbery plateau that spanned the widest temperature range yet reported for any supramolecular network. To verify that each Janus-faced motif engages in multiple cross-links, we studied the effects of local concentration of the incorporated GCB units within the polymer chain. Mechanical strength improved by colocalizing the GCB within a block copolymer morphology. This enhanced performance revealed that the number of effective cross-links in the network increased with the local concentration of hydrogen bonding units. Overall, this study demonstrates that cooperative noncovalent interactions introduced through Janus-faced hydrogen bonding moieties confers excellent network stability and predictable viscoelastic flow behavior in supramolecular networks.

Machine learning-based approach to determine infection status in recipients of BBV152 (Covaxin) whole-virion inactivated SARS-CoV-2 vaccine for serological surveys - Singh, Prateek; Ujjainiya, Rajat; Prakash, Satyartha; Naushin, Salwa; Sardana, Viren; Bhatheja, Nitin; Singh, Ajay Pratap; Barman, Joydeb; Kumar, Kartik; Gayali, Saurabh; Khan, Raju; Rawat, Birendra Singh; et al. (Computers in Biology and Medicine, 2022)
Data science has been an invaluable part of the COVID-19 pandemic response with multiple applications, ranging from tracking viral evolution to understanding the vaccine effectiveness. Asymptomatic breakthrough infections have been a major problem in assessing vaccine effectiveness in populations globally. Serological discrimination of vaccine response from infection has so far been limited to Spike protein vaccines since whole virion vaccines generate antibodies against all the viral proteins. Here, we show how a statistical and machine learning (ML) based approach can be used to discriminate between SARS-CoV-2 infection and immune response to an inactivated whole virion vaccine (BBV152, Covaxin). For this, we assessed serial data on antibodies against Spike and Nucleocapsid antigens, along with age, sex, number of doses taken, and days since last dose, for 1823 Covaxin recipients. An ensemble ML model, incorporating a consensus clustering approach alongside the support vector machine model, was built on 1063 samples where reliable qualifying data existed, and then applied to the entire dataset. Of 1448 self-reported negative subjects, our ensemble ML model classified 724 to be infected. For method validation, we determined the relative ability of a random subset of samples to neutralize Delta versus wild-type strain using a surrogate neutralization assay. We worked on the premise that antibodies generated by a whole virion vaccine would neutralize wild type more efficiently than delta strain. In 100 of 156 samples, where ML prediction differed from self-reported uninfected status, neutralization against Delta strain was more effective, indicating infection. We found 71.8% subjects predicted to be infected during the surge, which is concordant with the percentage of sequences classified as Delta (75.6%-80.2%) over the same period. Our approach will help in real-world vaccine effectiveness assessments where whole virion vaccines are commonly used.
Keywords: BBV152; Covaxin; COVID-19; Ensemble methods; Infection; machine learning; SARS-CoV-2

Optimization of Liquid Organic Hydrogen Carrier (LOHC) dehydrogenation system - Rao, Nihal; Lele, Ashish K.; Patwardhan, Ashwin W. (International Journal of Hydrogen Energy, 2022)
In this paper, the perhydrodibenzyltoluene dehydrogenation flowsheet has been simulated. Modelling of the dehydrogenation reactor has been performed using the 1-D model. External and internal mass transfer resistances are also considered. Non-isothermal pellet condition has been considered for simulating the dehydrogenation reactor. The flowsheet simulation has been carried out in DW-Sim v 6.5.2 integrated with the reactor model coded in Python. NET. The dehydrogenation reactor is operated at a feed temperature between 523 K -613 K, a wall temperature of 623 K and 653 K, and a reactor pressure maintained at 1.2 atm. The amount of catalyst required for the perhydrodibenzyltoluene (PDBT) dehy-drogenation reactor is evaluated such that the conversion reaches 99%. The process flowsheet has been simulated to produce 10 Nm(3)/hr of industrial-grade hydrogen. The effects of feed temperature, wall temperature, and hydrogen burner efficiency on various system requirements, including catalyst weight, energy supplied to the dehydrogenation reactor, areas of the heat exchanger, and hydrogen production from the reactor, have been discussed. Preliminary cost optimization based on the heat exchangers and catalyst at various feed temperatures, reactor wall temperature, and hydrogen burner efficiency has been carried out. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Dehydrogenation; DWSim; LOHC; Perhydrodibenzyltoluene; Python; simulation

Porous covalent organic nanotubes and their assembly in loops and toroids - Koner, Kalipada; Karak, Shayan; Kandambeth, Sharath; Karak, Suvendu; Thomas, Neethu; Leanza, Luigi; Perego, Claudio; Pesce, Luca; Capelli, Riccardo; Moun, Monika; Bhakar, Monika; Ajithkumar, Thalasseril G.; et al. (Nature Chemistry, 2022)
Carbon nanotubes, and synthetic organic nanotubes more generally, have in recent decades been widely explored for application in electronic devices, energy storage, catalysis and biosensors. Despite noteworthy progress made in the synthesis of nanotubular architectures with well-defined lengths and diameters, purely covalently bonded organic nanotubes have remained somewhat challenging to prepare. Here we report the synthesis of covalently bonded porous organic nanotubes (CONTs) by Schiff base reaction between a tetratopic amine-functionalized triptycene and a linear dialdehyde. The spatial orientation of the functional groups promotes the growth of the framework in one dimension, and the strong covalent bonds between carbon, nitrogen and oxygen impart the resulting CONTs with high thermal and chemical stability. Upon ultrasonication, the CONTs form intertwined structures that go on to coil and form toroidal superstructures. Computational studies give some insight into the effect of the solvent in this assembly process.

Protophilic solvent-impelled quasi-catalytic CO2 valorization to formic acid and N-formamides - Wu, Hongguo; Li, Hu; Zhao, Wenfeng; Sudarsanam, Putla; Yang, Song (Fuel, 2022)
As a low-price and luxuriant C1 sustainable resource, CO2 has the privilege of synthesizing hydrogen carriers and valuable chemicals. However, expensive metallic and organic catalysts are often indispensable for going on wheels of the relevant reaction processes. In this work, a protophilic solvent-impelled quasi-catalytic system was developed for efficient synthesis of formic acid and various N-formamides with high yields of 76-94% via reductive CO2 functionalization under mild reaction conditions (50 ?). Direct activation of the liquid hydrosilane toward the reduction of CO2 enabled by DMSO with optimum basicity/protophilicity is the predominant reaction route among the examined interaction models, while carbonic acid potentially derived from excessive CO2 and residual water inhibits the reaction, as explicitly disclosed by theoretical calculations and isotope labeling experiments. In addition, the in situ formed O-formyl species is conductive to the cascade CO2 reduction steps, which remarkably facilitated the overall quasi-catalytic upgrading process.
Keywords: CO2 utilization; Formic acid; Green energy; Nitrogenous chemicals; Quasi-catalysis

Sulfur functionalization via epoxide ring opening on a reduced graphene oxide surface to form metal (II) Organo-bis-[1,2]-oxathiin - Kumar, Praveen; Bajpai, Himanshu; Gopinath, Chinnakonda S.; Luwang, Meitram Niraj (Inorganic Chemistry, 2022)
The epoxide ring-opening reaction in graphene oxide (GO) by nucleophiles is a very fascinating and advanced methodology to develop novel functional material. Herewith, we report an advanced strategy for opening the epoxide ring on the rGO surface via easily an available nucleophile (Na2S), which is further functionalized with O atom to obtain four-membered rings (FMRs). The Cd coordination with the S atom puts extra stress on the FMR leading to the C-C bond cleavage of the four-membered heteroatomic rings on the rGO surface. This strategic approach leads to the fabrication of an innovative metal organo-bis-[1,2]-oxathiin (MOBOT) chemical moiety (M = Cd, Zn). The MOBOT compound further shows enhanced H-2 generation activity and hence is promising as a potential photocatalyst for solar hydrogen generation. This compound might also be a potential candidate for optoelectronic applications.

Synthesis, characterization and UV-crosslinking of aromatic (Co)polycarbonates bearing pendant azido groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Talanikar, Aniket A.; Lochab, Bimlesh; Wadgaonkar, Prakash P. (ChemistrySelect, 2022)
A new series of (co)polycarbonates bearing pendent azido groups was synthesized by polycondensation of varying molar proportions of 4, 4'-(5-azidopentane-2, 2-diyl) diphenol and bisphenol-A with triphosgene. The chemical structures, compositions and random nature of (co)polycarbonates were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of (co)polycarbonates were in the range 0.63-0.77 dL g(-1) and 35,400-43,400 g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. (Co)polycarbonates could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polycarbonates were further characterized using IR spectroscopy, XRD, TGA and DSC. The thermal crosslinking of (co)polycarbonates bearing pendant azido groups was studied by DSC analysis. Independently, (co)polycarbonates bearing pendant azido groups were exposed to UV irradiation at wavelength of 254 nm and decomposition reaction of azido groups was monitored by FT-IR spectroscopy. The complete decomposition of azido groups was observed with exposure time of 30 min. The formed cross-linked (co)polycarbonates exhibited improved % char yield values compared to parent (co)polycarbonates. The measurement of mechanical properties of representative crosslinked (co)polycarbonates indicated increase in tensile strength and Young's modulus and decrease in % elongation compared to corresponding parent linear (co)polycarbonates.
Keywords: Aromatic polycarbonate; Pendant azido group; solution polycondensation; Triphosgene; UV-crosslinking

Wearable fabric supercapacitors based on CNTs and polyhedral ZnO with a wide potential window - Samuel, Edmund; Joshi, Bhavana; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (International Journal of Energy Research, 2022)
Wearable electronic devices such as health monitors, sensors, and e-skin can be powered by lightweight, high-power supercapacitors. Using a binder-free and low-temperature hydrothermal method, polyhedral ZnO nanoparticles were grown on carbon nanotube (CNT)-decorated cotton fabric, which is friendly to human skin and highly wearable, inexpensive, and thus commercially viable. The concentration of the starting material, zinc acetate, was varied to optimize the electrochemical performance. The evenly spaced polyhedral ZnO facilitated efficient permeation of the electrolyte into the active material. The fabric filaments were decorated with CNTs to enhance electron transfer and the overall electrochemical processes. The symmetric cell comprised of cotton fabric decorated with ZnO polyhedron/CNT showed no discernible change in the cyclic voltammetry curves even after 500 bending cycles, demonstrating the mechanical durability of the electrode. The potential window of 1.6 V using a Na2SO4/K2SO4 aqueous dual-ion electrolyte improved the long-term electrochemical stability and increased the energy storage capacity. The capacitance retention was 94% after 5000 cycles at a current density of 1 A center dot g(-1), indicating long-term electrochemical stability. A specific capacitance of 375 F center dot g(-1) at a current density of 5 A center dot g(-1) and energy density of 33.3 Wh center dot kg(-1) at a power density of 2000 W center dot kg(-1) were recorded for the optimized electrode. Highlights Polyhedral ZnO was grown on cotton fabric using a hydrothermal process. The electrochemical performance was optimized by varying the zinc acetate concentration. The highest specific capacitance was 375 F center dot g(-1) at a current density of 5 A center dot g(-1). Under optimal conditions, the capacitance retention was 94% at N = 5000 cycles. The energy density of the electrode was as high as 33.3 Wh center dot kg(-1).
Keywords: carbon nanotube; Cotton fabric; hydrothermal process; wearable supercapacitor; ZnO polyhedron

Bacterial communities and diversity of western ghats soil: a study of a biodiversity hotspot - Ghare, Uma; Narvekar, Simran; Lodha, Tushar; Mallebhari, Rubiya; Dastager, Syed; Barvkar, Vitthal T.; Dhotre, Dhiraj; Karmalkar, Nitin R.; Pable, Anupama A. (Current Microbiology, 2023)
The Western Ghats is one of India's mega-diversity hotspots and an ecologically and geologically important area for the diversity of endemic plants and animals. The present study provides insights into the aerobic bacterial diversity and composition of the soils of North Western Ghats located in Maharashtra state (NWGM), India. The samples for the culture-dependent study were collected from 6 different locations namely Malshej Ghat, Bhimashankar, Lonavala, Mulshi, Tail-Baila, and Mahabaleshwar. A total of 173 isolates were obtained from the different samples, which belonged to Proteobacteria (43%), Firmicutes (36%), and Actinobacteria (19%). Sequences of 15 strains shared <= 98.7% similarity (a species cut-off) which represent potential novel species. Metagenomic analysis revealed the presence of Actinobacteria and Proteobacteria as the most dominant phyla at both MB and MG. However, both sites showed variation in the composition of rare phyla and other dominant phyla. This difference in bacterial community composition could be due to differences in altitude or other physicochemical properties. The functional prediction from the amplicon sequencing showed the abundance of carbohydrate, protein, and lipid metabolism which was corroborated by screening the isolated bacterial strains for the same. The present study has a unique take on microbial diversity and defines the importance of community assembly processes such as drift, dispersal, and selection. Such processes are relatively important in controlling community diversity, distribution, as well as succession. This study has shown that the microbial community of NWGM is a rich source of polysaccharide degrading bacteria having biotechnological potential.

Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT): a 3D sandwiched frameworks with efficient hydrogen production - Kumar, Praveen; Bajpai, Himanshu; Luwang, Meitram Niraj (Journal of Catalysis, 2023)
For over a decade, the structure, reactivity, and mechanism of graphene based photocatalysts have been of great interest for hydrogen (H2) generation. Several studies have been done on the edge side groups (ESGs) of graphene oxide (GO), but the basal plane groups (BPGs)-epoxide and hydroxide have acquired far less attention. This is because the GO layers are strongly held with van der waals forces as well as H-bonding which prevents the foreign body from entering inside the layers. To overcome these problems, this study presents the successful synthesis and application of four coordinated sandwiched (FCS) Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT) in rGO-CdS composite (A 3D sandwiched frame-work). Additionally, experimental outcomes have been further supported using density functional theory (DFT), which suggest that CdOTOT is more stable than its precursors as well as thermodynamically favourable. The CdOTOT shows high H2 production activity -67.5 mmol/g or 13.5 mmol/g/h in presence of 1 % Pt cocatalyst and sacrificial reagents (Na2S/Na2SO3). It is around 33 times higher than pristine CdS, and stable up to around 15 hrs without adding any cocatalyst. This mesmerising outcome is over with reported various CdS-rGO based photocatalysts. The higher activity was further explained through the proposed mechanism and observed low electronic work function of CdOTOT. This innovative and extend-able (with other metals) approach provides a revolutionary impact on numerous cutting-edge research applications like photocatalysis, water splitting, solar cell, etc.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: 2]; 3D sandwiched frameworks; Basal Plane Groups (BPGs); Cadmium (II) Organo Tetrakis-[1; hydrogen production; Oxathiin (CdOTOT)

Chemical bridge-mediated heterojunction electron transport layers enable efficient and stable perovskite solar cells - Patil, Pramila; Maibam, Ashakiran; Sangale, Sushil S.; Mann, Dilpreet Singh; Lee, Hyun-Jung; Krishnamurty, Sailaja; Kwon, Sung-Nam; Na, Seok-In (ACS Applied Materials and Interfaces, 2023)
Perovskite solar cells (PSCs) emerged as potential photovoltaicenergy-generating devices developing in recent years because of theirexcellent photovoltaic properties and ease of processing. However,PSCs are still reporting efficiencies much lower than their theoreticallimits owing to various losses caused by the charge transport layerand the perovskite. In this regard, herein, an interface engineeringstrategy using functional molecules and chemical bridges was appliedto reduce the loss of the heterojunction electron transport layer.As a functional interface layer, ethylenediaminetetraacetic acid (EDTA)was introduced between PCBM and the ZnO layer, and as a result, EDTAsimultaneously formed chemical bonds with PCBM and ZnO to serve asa chemical bridge connecting the two. DFT and chemical analyses revealedthat EDTA can act as a chemical bridge between PCBM and ZnO, passivatedefect sites, and improve charge transfer. Optoelectrical analysisproved that EDTA chemical bridge-mediated charge transfer (CBM-CT)provides more efficient interfacial charge transport by reducing trap-assistedrecombination losses at ETL interfaces, thereby improving device performance.The PSC with EDTA chemical bridge-mediated heterojunction ETL exhibiteda high PCE of 21.21%, almost no hysteresis, and excellent stabilityto both air and light.
Keywords: charge transfer; chemical bridge; electron transport layer; ethylenediaminetetraacetic acid; Perovskite solar cells; trap-assisted recombination

Direct conversion of N-acetyl-d-glucosamine to N-containing heterocyclic compounds 3-acetamidofuran and 3-acetamido-5-acetyl Furan - Shaikh, Samrin S.; Patil, Chetana R.; Lucas, Nishita; Bokade, Vijay V.; Rode, Chandrashekhar V. (Waste and Biomass Valorization, 2023)
Purpose Effectual waste utilization from plant as well as marine biomass has gained tremendous importance with reference to sustainability. The valorization of marine biomass produces value added compounds containing not only C, H, O but also renewable N atom in the skeleton which widens the scope for its exploration which may prove to be economically beneficial to the society. Heterogeneous catalytic transformation of marine biomass i.e. N-acetyl glucosamine (NAG) to N-substituted aromatic heterocyclic furan derivatives is reported for the very first time. Cost effective and stable metal oxide catalysts were deployed for the transformation. Catalyst screening study showed that La2O3 was found to be an excellent catalyst for N-acetyl glucosamine (NAG) dehydration which mainly produced 3-acetamidofuran (3AF). Methods The physicochemical properties of the metal oxide catalyst were investigated by various techniques such as XRD, FTIR, MeOH-FTIR, TPD, SEM, N-2 sorption studies and HR-TEM analysis for structure activity relationship. Results The effect of various reaction parameters such as catalyst concentration, reaction temperature, reaction time and solvent effect on dehydration of N-acetyl glucosamine has been studied in detail for higher yields. The results revealed that the presence of weak basic sites which are Bronsted in nature and nano pores present on the surface were responsible for improved dehydration of the chitin biomass to selectively yield 3-acetamidofuran (3AF). La2O3 catalyst showed optimum 50% 3AF yield from N-acetyl glucosamine at 180 degrees C in 3 h. Conclusion Efficacious exploitation of marine biomass to value added chemicals using heterogeneous catalysts can be extensively exploited. Separation of N-substituted heterocyclic aromatics is the most innovative aspect of the current study. Thus, utilization of heterogeneous catalyst and renewable biomass as a raw material indicates a transition towards more sustainable and greener approach.{GRAPHICAL ABSTRACT
Keywords: 3-acetamido-5-acetylfuran; 3-acetamidofuran; dehydration; heterogeneous catalysis; Lanthanum oxide; N-acetyl-D-glucosamine; renewable feedstock

The effect of substituents on the aggregation-induced emission of 9,10-phenanthraquinone-hydrazones - Kumar, M. Naveen; Lyngkhoi, Deikrisha Lyngdoh; Gaikwad, Sudhakar; Samanta, Debabrata; Khatua, Snehadrinarayan; Pramanik, Susnata (New Journal of Chemistry, 2023)
Organic luminophores, particularly & pi;-conjugated systems, have become crucial in modern optoelectronic devices that utilise luminescence as an output signal, requiring aggregate or solid-states, such as nanoparticles, thin films, or crystals. Herein, we report the one-step synthesis of six hydrazone derivatives using condensation reactions between 9,10-phenanthrenedione and different aromatic hydrazines, comprising electron-donating/electron-withdrawing groups and a quinoline moiety. The introduction of a conjugated & pi;-system leads to complete co-planarization of molecules resulting in large bathochromic shifts in their absorption profile, the maximum red-shifts ever observed for the hydrazones. These hydrazones are weakly fluorescent in dilute acetonitrile solutions. However, they exhibit enhanced emissions of up to 300-fold in aggregated states. Dynamic light scattering (DLS) and scanning electron microscopy (SEM) studies support nanoaggregate formation. All the compounds exhibit red to NIR emissions in their crystalline state with as high as 75% quantum efficiency.

Fast normalization and despeckled method for skin optical coherence tomography image via deep learning - Rahaman, Jarjish; Lukas, Brandon; May, Julia; Puyana, Carolina; Tsoukas, Maria; Avanaki, Kamran (Photonics in Dermatology and Plastic Surgery 2023, 2023)
Optical coherence tomography (OCT) is well-known for its high-resolution, non-invasive imaging modality with many medical uses, including skin imaging. Nevertheless, speckle noise limits the analytical capabilities of this imaging tool, causing deterioration in contrast and less exact detection of tissue microstructural heterogeneity. To address this issue, we proposed OCT despeckling approach by combing it with normalization to reduce the speckle noise more effectively. The proposed method contains multiple steps including phase correlation for alignment of misaligned frames, frame averaging which minimizes speckle noise, region-wise pixels normalization that helps to normalize intensity pixels, a modified BM3D filtering to suppress the white and speckle, and contrast enhancement to improve the contrast appropriately. To establish the approach, we applied 130 distinct B-scan skin OCT images and validate and evaluate the performance using qualitatively and quantitatively. Although the output obtained by the algorithm is promising, the method is time-consuming because of a series of steps. To reduce the time complexity, we also develop a supervised deep learning model by mapping between noisy-despeckled image pairs. The effectiveness and applicability of our DL approach were assessed using 130 skin OCT B-scans from various body areas taken from 45 healthy people between the ages of 20 and 60. With the support of the experimental results, we demonstrate that our DL model is capable to normalize and despeckling OCT images simultaneously.
Keywords: CNN; deep learning; denoising; Optical coherence tomography; speckle

Gas sensors and factors influencing sensing mechanism with a special focus on MOS sensors - Nadargi, Digambar Y. Y.; Umar, Ahmad; Nadargi, Jyoti D. D.; Lokare, Smita A. A.; Akbar, Sheikh; Mulla, Imtiaz S. S.; Suryavanshi, Sharad S. S.; Bhandari, Nagesh L. L.; Chaskar, Manohar G. G. (Journal of Materials Science, 2023)
Industrialization and its progress are very important for the economy and to move towards prosperity, stimulating innovation and creating jobs. Nonetheless, industrialization has negative impacts, if not done judiciously, such as pollution, increased greenhouse gas emissions, and global warming. Therefore, amenity-with-security is of fundamental significance in a new and dynamic lifestyle. A gas sensor is one of the crucial devices for monitoring and subsequently preserving the clean atmosphere among a number of other safety technologies. In-depth assessments of gas sensors and their necessity in the environment (air) pollution are provided in the current review. With a special emphasis on metal oxide semiconductor (MOS)-based gas sensors, the review includes a thorough study of gas sensors and the factors relating to sensing mechanisms. It not only describes the basic concepts and brief history of gas sensors, but also highlights the schemes responsible for improving the gas sensing properties and state-of-art literature review. These schemes include (1) surface engineering/morphological tuning and (2) bulk and surface doping. To keep scientific rigour and in-depth analyses, this review focuses on these two schemes only. In the doping area, the emphasis is given on graphene loading, decorated with nanoparticles of noble metals, spillover mechanism, and heterojunction (p-n, n-n, and p-p) formation. The conclusion summarizes the most optimized MOS gas sensors with enhanced gas sensing capabilities. The emphasis is given to formulate the article in such a way that it will be useful for the beginners who wish to explore the gas sensor research field, as well as to the established researchers to further improve the sensing capabilities of MOS gas sensors.

Hydroxide ion-conducting viologen-bakelite organic frameworks for flexible solid-state zinc-air battery applications - Rase, Deepak; Illathvalappil, Rajith; Singh, Himan Dev; Shekhar, Pragalbh; Leo, Liya S.; Chakraborty, Debanjan; Haldar, Sattwick; Shelke, Ankita; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Nanoscale Horizons, 2023)
Adaptable polymer-based solid-state electrolytes can be a game-changer toward safe, lightweight flexible batteries. We present a robust Bakelite-type organic polymer covalently decked with viologen, triazine, and phenolic moieties. Its flexible structure with cationic viologen centers incorporates counter-balancing free hydroxide ions into the polymeric framework. By design, the aromatic groups and heteroatoms in the framework can be activated under an applied potential to prompt a push-pull drive, setting off the towing of hydroxide ions via weak electrostatic, van der Waals, and hydrogen-bond interactions. The frontier orbitals from a DFT-modeled structure certify this. The hydroxyl-polymer requires minimal KOH wetting to maintain a humid environment for Grotthuss-type transport. The hydroxide ion conductivity reaches a value of 1.4 x 10(-2) S cm(-1) at 80 degrees C and 95% RH, which is retained for over 15 h. We enhanced its practical utility by coating it as a thin solid-state separator-cum-electrolyte on readily available filter paper. The composite exhibits a conductivity of 4.5 x 10(-3) S cm(-1) at 80 degrees C and 95% RH. A zinc-air battery (ZAB) constructed using this polymer-coated paper as electrolyte yields a maximum power density of 115 mW cm(-2) and high specific capacitance of 435 mA h g(-1). The power density recorded for our ZAB is among the best reported for polymer electrolyte-based batteries. Subsequently, the flexible battery fabricated with IISERP-POF11_OH@FilterPaper exhibits an OCV of 1.44 V, and three batteries in series power a demo traffic signal. To underscore the efficiency of hydroxide ion transport through the complex multifunctional backbone of the polymer, we calculated the diffusion coefficient for OH- (Exp: 2.9 x 10(-5) cm(2) s(-1); Comp. 5.2 x 10(-6) cm(2) s(-1)) using electrochemical methods and MD simulations. Climbing-edge NEB calculations reveal a large energy barrier of 2.11 eV for Zn2+ to penetrate the polymer and identify hydroxide ions within the polymer, suggesting no undesirable Zn2+ crossover. Our findings assert the readily accessible C-C-linked cationic polymer's capacity as a solid-state electrolyte for ZABs and any anion-conducting membrane.

Industry-oriented method for the aqueous phase oxidation of crude 5-hydroxymethyl furfural (HMF) to 2,5-furandicarboxylic acid (FDCA) - Lokhande, Priya; Sonone, Kalyani; Dhepe, Paresh L. (New Journal of Chemistry, 2023)
Valorization of cellulose, hemicellulose, and lignin into value-added industrially relevant chemicals is important to achieve sustainability goals that various governments and industries have set. In view of this, the oxidative synthesis of 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethyl furfural (HMF) as an analogous compound to terephthalic acid in the synthesis of PEF is interesting to researchers. Though advancements in the oxidation of HMF have been made, the efficient synthesis of HMF, its storage, and isolation are great challenges due to its instability under normal conditions. While purified HMF can be used to synthesize FDCA, it is imperative to use crude HMF for the synthesis of FDCA since several techno-economical studies reveal that the purification of HMF is the most cost-intensive step. Herein, we demonstrate the oxidation of crude HMF, synthesized in the laboratory to FDCA, using nonprecious-based mixed metal oxides in the aqueous medium in the presence of oxygen/air. Among various catalysts, Cu-Mn catalyst at 120 & DEG;C within 8 h in the presence of oxygen (10 bar) could yield 90% FDCA. This activity was comparable with that of the commercially available and well-studied Ru/C (5 wt%) catalyst (93% yield). In addition, the role of HMF purity, air as an oxidant, and the influence of temperature, pressure, and time is systematically studied. It is also demonstrated that FDCA formation proceeds via HMFCA and FFCA formation. The isolation of FDCA and its purity (>99%) is corroborated with various techniques such as NMR, IR, and HRMS.

Parallel evolution of cannabinoid biosynthesis - Berman, Paula; de Haro, Luis Alejandro; Jozwiak, Adam; Panda, Sayantan; Pinkas, Zoe; Dong, Younghui; Cveticanin, Jelena; Barbole, Ranjit; Livne, Rotem; Scherf, Tali; Shimoni, Eyal; Levin-Zaidman, Smadar; et al. (Nature Plants, 2023)
This study reveals a cannabinoid biosynthetic pathway in Helichrysum umbraculigerum, a plant genetically distant from Cannabis, providing a potential source of new cannabinoids and metabolic engineering tools. Modulation of the endocannabinoid system is projected to have therapeutic potential in almost all human diseases. Accordingly, the high demand for novel cannabinoids stimulates the discovery of untapped sources and efficient manufacturing technologies. Here we explored Helichrysum umbraculigerum, an Asteraceae species unrelated to Cannabis sativa that produces Cannabis-type cannabinoids (for example, 4.3% cannabigerolic acid). In contrast to Cannabis, cannabinoids in H. umbraculigerum accumulate in leaves' glandular trichomes rather than in flowers. The integration of de novo whole-genome sequencing data with unambiguous chemical structure annotation, enzymatic assays and pathway reconstitution in Nicotiana benthamiana and in Saccharomyces cerevisiae has uncovered the molecular and chemical features of this plant. Apart from core biosynthetic enzymes, we reveal tailoring ones producing previously unknown cannabinoid metabolites. Orthology analyses demonstrate that cannabinoid synthesis evolved in parallel in H. umbraculigerum and Cannabis. Our discovery provides a currently unexploited source of cannabinoids and tools for engineering in heterologous hosts.

Pd nanoparticles supported on N-incorporated hybrid organosilica as an active and selective low-temperature phenol hydrogenation catalyst - Betsy, K. J.; Bajpai, Priyam; Lazar, Anish; Vanka, Kumar; Vinod, C. P. (ACS Applied Nano Materials, 2023)
A heterogeneous Pd-NPMO hybrid-silicacatalyst is synthesized andits application for aqueous phase selective hydrogenation of phenolto cyclohexanone at near ambient temperature (40 degrees C) and underatmospheric hydrogen pressure is demonstrated. The homogeneously distributedPd nanoparticles on N-bridged hybrid mesoporous organosilica showedremarkable activity and selectivity for cyclohexanone compared tothe unmodified Pd-SBA-15 catalyst. Control experiments strongly claimthe role of nitrogen domains in the organic framework of hybrid silicasupport in stabilizing small Pd nanoparticles and possibly modifyingthe Pd sites responsible for catalysis to activate the substrate moleculesin water. The hybrid silica catalyst was stable and reused severaltimes without any significant drop-in activity, proving the heterogeneityof the bifunctional Pd catalyst. Based on the density functional theorystudy and experimental interventions, a possible reaction mechanismfor the low-temperature phenol hydrogenation explaining the role oforganic domains in the hybrid-silica framework is proposed.
Keywords: cyclohexanone; Hybrid silica; palladium nanoparticles; Periodic mesoporous organosilica; phenol hydrogenation

Selective and robust Ru catalyst for the aqueous phase aerobic oxidation of furfural to 2-furoic acid - Lokhande, Priya; Dhepe, Paresh L. (ACS Applied Materials & Interfaces, 2023)
Synthesis of 2-furoic acid (FURA) via oxidation of furfural (FAL) is vital in evolving the biorefinery concept as FURA has numerous important applications in the pharmaceuticals and optic areas. Though few works on this reaction are done, those are marred with shortcomings such as the nonrecyclability of catalyst, dilute solutions, lower yields, or use of H2O2 as an oxidizing agent. Herein, we report catalytic aqueous phase oxidation of FAL to FURA using molecular oxygen as an oxidizing agent. For the synthesis of FURA, various catalysts with a combination of metal (Pt, Pd, Ru) and supports (carbon, Al2O3) were prepared and characterized by multiple techniques (X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET), X-ray photoelectron spectroscopy (XPS)). Oxidation of FAL carried out over 5 wt % Ru/C catalyst in the presence of Na2CO3 yielded 83% of FURA at 120 degrees C and 15 bar oxygen pressure. The catalyst could show potential for reusability as similar activity was achieved after subjecting the spent catalyst to mild reduction treatment (150 degrees C). Studies on the effects of temperature, pressure, and time could help accomplish enhanced yields of FURA. Additionally, learning about the effect of base (weak/strong/solid) revealed that due to the weak basicity of Na2CO3, higher yields could be achieved by maintaining approximately a pH of 11, which is optimal for suppressing side reactions. Under the given conditions, FURA is stable (>90%) and also adsorption studies divulge that it is immediately removed from the catalyst surface, and hence higher yields could be achieved in our catalytic system. Using the initial rates methodology, an activation energy of 21.91 kJ mol(-1) was derived and also a high turn over frequency (TOF) (85.9 h(-1)) was observed under optimized conditions.
Keywords: 2-furoic acid (FURA); Biomass conversion; furfural (FAL); heterogeneous catalyst; Oxidation; ruthenium on carbon etc

Size does matter: antibacterial activities and cytotoxic evaluation of polymorphic CuO nanostructures - Desai, Dnyanada G.; Navale, Govinda R.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Materials Science, 2023)
Nanostructured materials play a significant role in antibacterial activities. However, understanding the geometrical influence at the nanoscale in terms of size- and shape-correlated physical properties on antibacterial activities is very essential. Herein, we report the antibacterial influence of various copper oxide nanostructures (CuO NS) such as nanoparticles (NPs) (< 10 nm), nanospheres (NSs) (50-100 nm), and porous nanoflowers (NFs) (asymptotic to 350 nm). The XRD confirmed the crystalline nature of CuO NPs without impurities. The antibacterial activities of CuO NPs were investigated by the microplate dilution method and confocal laser scanning microscopic (CLSM) imaging. NPs having a diameter less than 10 nm exhibited significant damage to the bacterial cell membrane than NSs and NFs. Interestingly, NPs illustrated relatively low antibacterial activity against Gram-negative bacteria (Pseudomonas aeruginosa and Acinetobacter baumannii) than Gram-positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis). Acinetobacter baumannii was found to be more susceptible to the NPs than other bacterial strains, attributed to its increased membrane permeability. The death phase was observed at a concentration of 15.6 mu g mL(-1) and 3.9 mu g mL(-1) for P. aeruginosa and A. baumannii, respectively, when treated with CuO NP after the 8 h of incubation. Similarly, for S. aureus and S. epidermidis, the death phase was observed at the concentration of 31.2 mu g mL(-1) and 250 mu g mL(-1), respectively. Furthermore, as the cell cytotoxicity measurements against human fibroblast L9239 cells revealed that CuO NPs were safe. The morphological and cell viability assay demonstrated 100% cell survival, when treated with NPs and NSs (5, 10, and 25 mu g mL(-1)), signifies no cytotoxicity. Therefore, CuO nanoparticles can be used for clinical and therapeutic applications.

Tale of two waves: Delineating diverse genomic and transmission landscapes driving the COVID-19 pandemic in Pune, India - Niveditha, Divya; Khan, Soumen; Khilari, Ajinkya; Nadkarni, Sanica; Bhalerao, Unnati; Kadam, Pradnya; Yadav, Ritu; Kanekar, Jugal B.; Shah, Nikita; Likhitkar, Bhagyashree; Sawant, Rutuja; Thakur, Shikha; et al. (Journal of Infection and Public Health, 2023)
Background: Modern response to pandemics, critical for effective public health measures, is shaped by the availability and integration of diverse epidemiological outbreak data. Tracking variants of concern (VOC) is integral to understanding the evolution of SARS-CoV-2 in space and time, both at the local level and global context. This potentially generates actionable information when integrated with epidemiological outbreak data.Methods: A city-wide network of researchers, clinicians, and pathology diagnostic laboratories was formed for genome surveillance of COVID-19 in Pune, India. The genomic landscapes of 10,496 sequenced samples of SARS-CoV-2 driving peaks of infection in Pune between December-2020 to March-2022, were determined. As a modern response to the pandemic, a ``band of five'' outbreak data analytics approach was used. This integrated the genomic data (Band 1) of the virus through molecular phylogenetics with key outbreak data including sample collection dates and case numbers (Band 2), demographics like age and gender (Band 3-4), and geospatial mapping (Band 5).Results: The transmission dynamics of VOCs in 10,496 sequenced samples identified B.1.617.2 (Delta) and BA(x) (Omicron formerly known as B.1.1.529) variants as drivers of the second and third peaks of infection in Pune. Spike Protein mutational profiling during pre and post-Omicron VOCs indicated differential rank ordering of high-frequency mutations in specific domains that increased the charge and binding properties of the protein. Time-resolved phylogenetic analysis of Omicron sub-lineages identified a highly divergent BA.1 from Pune in addition to recombinant X lineages, XZ, XQ, and XM. Conclusions: The band of five outbreak data analytics approach, which integrates five different types of data, highlights the importance of a strong surveillance system with high-quality meta-data for understanding the spatiotemporal evolution of the SARS-CoV-2 genome in Pune. These findings have important implica-tions for pandemic preparedness and could be critical tools for understanding and responding to future outbreaks.& COPY; 2023 Published by Elsevier Ltd on behalf of King Saud Bin Abdulaziz University for Health Sciences. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: COVID-19; Delta; Omicron; SARS-CoV-2 genomic surveillance; Variant of concern; Whole Genome Sequencing (WGS)

Thermally constructed stable Zn-doped NiCoOx-z alloy structures on stainless steel mesh for efficient hydrogen production via overall hydrazine splitting in alkaline electrolyte - Kashale, Anil Ashok; Rasal, Akash Sanjay; Hsu, Fei-Chien; Chen, ChangChun; Kulkarni, Sayali Nitin; Chang, Chun Hao; Chang, Jia-Yaw; Lai, Yuekun; Chen, I. -Wen Peter (Journal of Colloid and Interface Science, 2023)
Hydrogen has a high energy density of approximately 120 to 140 MJ kg(-1), which is very high compared to other natural energy sources. However, hydrogen generation through electrocatalytic water splitting is a high electricity consumption process due to the sluggish oxygen evolution reaction (OER). As a result, hydrogen generation through hydrazine-assisted water electrolysis has recently been intensively investigated. The hydrazine electrolysis process requires a low potential compared to the water electrolysis process. Despite this, the utilization of direct hydrazine fuel cells (DHFCs) as portable or vehicle power sources necessitates the development of inexpensive , effective anodic hydrazine oxidation catalysts. Here, we prepared oxygen-deficient zinc-doped nickel cobalt oxide (Zn-NiCoOx-z) alloy nanoarrays on stainless steel mesh (SSM) using a hydrothermal synthesis method followed by thermal treatment. Furthermore, the prepared thin films were used as electrocatalysts , the OER and hydrazine oxidation reaction (HzOR) activities were investigated in three-and two-electrode systems. In a three-electrode system, Zn-NiCoOx-z/SSM HzOR requires-0.116 V (vs RHE) potential to achieve a 50 mA cm(-2) current density, which is dramatically lower than the OER potential (1.493 V vs RHE). In a two-electrode system (Zn-NiCoOx-z/SSM(-)IIZn-NiCoOx-z/SSM(+)), the overall hydrazine splitting potential (OHzS) required to reach 50 mA cm(-2) is only 0.700 V, which is dramatically less than the required potential for overall water splitting (OWS). These excellent HzOR results are due to the binder-free oxygen-deficient Zn-NiCoOx-z/ SSM alloy nanoarray, which provides a large number of active sites and improves the wettability of cat-alysts after Zn doping. (C) 2023 Elsevier Inc. All rights reserved.
Keywords: Hydrazine Oxidation Reaction; hydrogen evolution reaction; Oxygen Evolution Reaction; Oxygen-Deficient Materials; Zinc Doping

Titanium trisulfide nanosheets and nanoribbons for field emission- based nanodevices - Pawbake, Amit S.; Khare, Ruchita T.; Island, Joshua O.; Flores, Eduardo; Ares, Jose R.; Sanchez, Carlos; Ferrer, Isabel J.; Pawar, Mahendra; Frank, Otakar; More, Mahendra A.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; et al. (ACS Applied Nano Materials, 2023)
The field emission (FE) properties of TiS3 nanosheets and nanoribbons, synthesized by direct sulfuration of bulk titanium, are investigated. The nanosheets show an enhanced FE behavior with a low turn-on field of similar to 0.3 V/ mu m, required for drawing an emission current density of similar to 10 mu A/cm2. Interestingly, the TiS3 nanosheet emitter delivered a large emission current density of similar to 0.9 mA/ cm2 at a relatively low applied electric field of similar to 0.4 V/mu m. We have estimated the values of the field enhancement factor (beta), which are found to be similar to 5 x 104 for the TiS3 nanosheet emitter and similar to 4 x 103 for the nanoribbon emitter. We attribute the superior FE performance to the presence of atomically sharp edges and the reduced thickness of TiS3, as reflected in the high value of beta. In fact, the nanosheet sample presents a higher density of ultrathin layers (similar to 12 nm-thick), and thus, they have a larger edge to volume ratio than the nanoribbon samples (which are similar to 19 nm-thick). The superior FE behavior of TiS3 nanosheets over nanoribbons makes them a propitious field emitter and can be utilized for various FE-based applications, demanding large emission currents and lower operational voltages. Moreover, the FE current stability recorded on these samples confirms their promising performance. Thus, the present investigation brings out a great promise of TiS3 nanosheets and nanoribbons as field emitters for vacuum nanoelectronics devices.
Keywords: Current stability; field emission; nanoribbon; nanosheets; TiS3